The Cardiovascular Health Study: design and rationale. - Fried, L P; Borhani, N O; Enright, P; Furberg, C D; Gardin, J M; Kronmal, R A; Kuller, L H; Manolio, T A; Mittelmark, M B; Newman, A (Ann Epidemiol, 1991)
The Cardiovascular Health Study (CHS) is a population-based, longitudinal study of coronary heart disease and stroke in adults aged 65 years and older. The main objective of the study is to identify factors related to the onset and course of coronary heart disease and stroke. CHS is designed to determine the importance of conventional cardiovascular disease (CVD) risk factors in older adults, and to identify new risk factors in this age group, especially those that may be protective and modifiable. The study design called for enrollment of 1250 men and women in each of four communities: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. Eligible participants were sampled from Medicare eligibility lists in each area. Extensive physical and laboratory evaluations were performed at baseline to identify the presence and severity of CVD risk factors such as hypertension, hypercholesterolemia and glucose intolerance; subclinical disease such as carotid artery atherosclerosis, left ventricular enlargement, and transient ischemia; and clinically overt CVD. These examinations in CHS permit evaluation of CVD risk factors in older adults, particularly in groups previously under-represented in epidemiologic studies, such as women and the very old. The first of two examination cycles began in June 1989. A second comprehensive examination will be repeated three years later. Periodic interim contacts are scheduled to ascertain and verify the incidence of CVD events, the frequency of recurrent events, and the sequellae of CVD.
Keywords: Aged; Cerebrovascular Disorders; Coronary Disease; Epidemiologic Methods; Female; Health Status; Humans; Longitudinal Studies; Male; Physical Examination; Research Design; Risk Factors; United States

Major electrocardiographic abnormalities in persons aged 65 years and older (the Cardiovascular Health Study). Cardiovascular Health Study Collaborative Research Group. - Furberg, C D; Manolio, T A; Psaty, B M; Bild, D E; Borhani, N O; Newman, A; Tabatznik, B; Rautaharju, P M (Am J Cardiol, 1992)
Electrocardiographic abnormalities are often found in older patients, but their prevalence in free-living elderly populations is not well-defined. In addition, the clinical significance of many of these abnormalities is uncertain. The prevalence of major electrocardiographic abnormalities was determined in 5,150 adults aged greater than or equal to 65 years from the Cardiovascular Health Study--a study of risk factors for stroke and coronary heart disease in the elderly. Ventricular conduction defects, major Q/QS waves, left ventricular hypertrophy, isolated major ST-T-wave abnormalities, atrial fibrillation and first-degree atrioventricular block were collectively categorized as major electrocardiographic abnormalities. Prevalence of any major electrocardiographic abnormality was 29% in the entire cohort, 19% among 2,413 participants who reported no history of coronary artery disease or systemic hypertension, and 37% among 2,737 participants with a history of coronary artery disease or hypertension. Prevalence of major electrocardiographic abnormalities was higher in men than in women regardless of history, and tended to increase with age. Major Q/QS waves were found in 5.2%, and more than half were in those who did not report a previous myocardial infarction. Major electrocardiographic abnormalities are common in elderly men and women irrespective of the history of heart disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Arrhythmias, Cardiac; Chi-Square Distribution; Electrocardiography; Female; Heart Diseases; Humans; Logistic Models; Male; Prevalence; Risk Factors; Sex Factors; United States

Ankle-arm index as a marker of atherosclerosis in the Cardiovascular Health Study. Cardiovascular Heart Study (CHS) Collaborative Research Group. - Newman, A B; Siscovick, D S; Manolio, T A; Polak, J; Fried, L P; Borhani, N O; Wolfson, S K (Circulation, 1993)
BACKGROUND: Peripheral arterial disease measured noninvasively by the ankle-arm index (AAI) is common in older adults, largely asymptomatic, and associated with clinically manifest cardiovascular disease (CVD). The criteria for an abnormal AAI have varied in previous studies. To determine whether there is an inverse dose-response relation between the AAI and clinical CVD, subclinical disease, and risk factors, we examined the relation of the AAI to cardiovascular risk factors, other noninvasive measures of subclinical atherosclerosis using carotid ultrasound, echocardiography and electrocardiography, and clinical CVD. METHODS AND RESULTS: The AAI was measured in 5084 participants > or = 65 years old at the baseline examination of the Cardiovascular Health Study. All subjects had detailed assessment of prevalent CVD, measures of cardiovascular risk factors, and noninvasive measures of disease. Participants were stratified by baseline clinical CVD status and AAI (< 0.8, > or = 0.8 to < 0.9, > or = 0.9 to < 1.0, > or = 1.0 to < 1.5). Analyses tested for a dose-response relation of the AAI with clinical CVD, risk factors, and subclinical disease. The cumulative frequency of a low AAI was 7.4% of participants < 0.8, 12.4% < 0.9, and 23.6% < 1.0. participants with an AAI < 0.8 were more than twice as likely as those with an AAI of 1.0 to 1.5 to have a history of myocardial infarction, angina, congestive heart failure, stroke, or transient ischemic attack (all P < .01). In participants free of clinical CVD at baseline, the AAI was inversely related to history of hypertension, history of diabetes, and smoking, as well as systolic blood pressure, serum creatinine, fasting glucose, fasting insulin, measures of pulmonary function, and fibrinogen level (all P < .01). Risk factor associations with the AAI were similar in men and women free of CVD except for serum total and low-density lipoprotein cholesterol, which were inversely associated with AAI level only in women. Risk factors associated with an AAI of < 1.0 in multivariate analysis included smoking (odds ratio [OR], 2.55), history of diabetes (OR, 3.84), increasing age (OR, 1.54), and nonwhite race (OR, 2.36). In the 3372 participants free of clinical CVD, other noninvasive measures of subclinical CVD, including carotid stenosis by duplex scanning, segmental wall motion abnormalities by echocardiogram, and major ECG abnormalities were inversely related to the AAI (all P < .01). CONCLUSIONS: There was an inverse dose-response relation of the AAI with CVD risk factors and subclinical and clinical CVD among older adults. The lower the AAI, the greater the increase in CVD risk; however, even those with modest, asymptomatic reductions in the AAI (0.8 to 1.0) appear to be at increased risk of CVD.
Keywords: Aged; Ankle; Arm; Arteriosclerosis; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Peripheral Vascular Diseases; Population Surveillance; Predictive Value of Tests; Risk Factors

Recruitment of adults 65 years and older as participants in the Cardiovascular Health Study. - Tell, G S; Fried, L P; Hermanson, B; Manolio, T A; Newman, A B; Borhani, N O (Ann Epidemiol, 1993)
Few large-scale epidemiologic studies have enrolled older adults; hence, little is known about the feasibility of recruiting this group for long-term population-based studies. In this article we present the recruitment experience of the Cardiovascular Health Study (CHS), a population-based, longitudinal study of cardiovascular diseases in adults 65 years and older. Participants were sampled from the Health Care Financing Administration's (HCFA) Medicare eligibility lists in four US communities. Letters were mailed to 11,955 sampled individuals. Persons recruited were required to complete an extensive home interview and then a 4-hour in-clinic examination. Excluded were persons who were expected to be able to complete the baseline examination and who were not expected to return for the 3-year follow-up. Some 3654 participants were recruited from those randomly selected from the Medicare sampling frame. In addition, 1547 other age-eligible persons living in the household with the sampled individuals also participated, yielding a total of 5201 participants. Of those who were contacted, 9.6% were ineligible and 34.9% refused participation. Among those eligible, 38.6% refused and 57.3% were enrolled (the remaining did not refuse but were not enrolled before the recruitment ended). Data from a subsample indicate that compared to those who were ineligible or who refused, enrolled participants were younger, more highly educated, more likely to be married, and less likely to report limitations in activity. Compared to those who were eligible but refused, enrolled participants were less likely to have high blood pressure and stroke and more likely to have quit smoking and to perceive their health status as very good or excellent.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Epidemiologic Methods; Female; Humans; Male

Cardiac arrhythmias on 24-h ambulatory electrocardiography in older women and men: the Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Rautaharju, P M; Siscovick, D; Newman, A B; Borhani, N O; Gardin, J M; Tabatznik, B (J Am Coll Cardiol, 1994)
OBJECTIVES: This study describes the prevalence and correlates of cardiac arrhythmias in older persons. BACKGROUND: Cardiac arrhythmias are frequent in selected samples of elderly persons, but their prevalence and association with cardiovascular disease and its risk factors have not been examined in a large population-based sample. METHODS: In 1,372 participants in the Cardiovascular Health Study, a population-based study of cardiovascular disease risk factors, 24-h ambulatory electrocardiography was performed. RESULTS: Serious arrhythmias, such as sustained ventricular tachycardia and complete atrioventricular block, were uncommon, but brief episodes of ventricular tachycardia (> or = 3 consecutive ventricular depolarizations) were detected in 4.3% of women and 10.3% of men. Ventricular arrhythmias as a group (excluding ectopic beats < 15/h) were more common in men than in women but were not significantly associated with age. The same patterns were true for bradycardia/conduction blocks. Supraventricular arrhythmias as a group (excluding ectopic beats < 15/h), in contrast, did not differ by gender but were strongly associated with increased age. Multivariate analyses showed associations with arrhythmias to differ by gender, with only one association (increased age and supraventricular arrhythmias) present in both women and men. Ventricular arrhythmias, particularly in men, were associated with a higher prevalence of cardiovascular disease and its risk factors and with subclinical disease, as measured by increased left ventricular mass and impaired left ventricular function. CONCLUSIONS: Arrhythmias are common in the elderly, and their association with cardiovascular disease differs by gender. Although risk related to arrhythmias can only be determined by prospective study, such studies should have adequate power to examine potential gender differences in associations.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Cardiovascular Diseases; Circadian Rhythm; Electrocardiography, Ambulatory; Female; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Sex Factors

Physical disability in older adults: a physiological approach. Cardiovascular Health Study Research Group. - Fried, L P; Ettinger, W H; Lind, B; Newman, A B; Gardin, J (J Clin Epidemiol, 1994)
Measures of physical function have been developed primarily to assess health status, prognosis, and service needs. They are now, increasingly, being used as outcome measures in studies seeking to determine the causes of disability. However, the extent to which these standardized measures, as they currently are constituted, are meaningful for the evaluation of underlying pathophysiology is not defined. To assess evidence for an etiologic rationale for these measures, we evaluated self-report of difficulty in physical function in the Cardiovascular Health Study, a study of 5201 men and women 65 years and older in four U.S. communities. We determined (by factor analysis) that self-reported difficulty with each of 17 tasks of daily life aggregates in four groups; i.e. difficulty in one task is associated with having difficulty in the other tasks in the group. These groups include (1) activities primarily dependent on mobility and exercise tolerance; (2) complex activities heavily dependent on cognition and sensory input; (3) selected basic self-care activities; and (4) upper extremity activities. Groups 2 and 3 are similar, but not identical, to Instrumental Activities of Daily Living (IADL) and Activities of Daily Living (ADL), respectively. We then tested whether these groupings were associated with different underlying impairments. Multiple logistic regression analyses indicate that there are constellations of physiologic and disease characteristics significantly (p < 0.01) associated with difficulty in each of these four groups of activities, among 15 chronic diseases and conditions ascertained. Some diseases are uniquely associated with difficulty in one group of tasks; some overlap, and are associated with 2, 3 or 4 groups of tasks. The associations found with difficulty in performing tasks in groups 2 and 3 were frequently stronger than those with the larger groups of ADL or IADL tasks, suggesting increased specificity of associations found with these new groupings. These results suggest that re-grouping of tasks of daily life may provide a more refined physiologically-based outcome measure for use in evaluating causes of disability. The ability to define risk factors for disability may be enhanced by choosing outcome measures with a demonstrated physiologic rationale.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic Disease; Disabled Persons; Factor Analysis, Statistical; Female; Geriatric Assessment; Humans; Logistic Models; Male; Outcome Assessment (Health Care); Risk Factors; Sex Factors; Socioeconomic Factors; United States

Black-white differences in subclinical cardiovascular disease among older adults: the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; Psaty, B M; Newman, A B; Haan, M; Powe, N; Tracy, R P; O'Leary, D H (J Clin Epidemiol, 1995)
Cardiovascular and all-cause mortality are higher in black than white Americans, but racial differences in clinical and subclinical cardiovascular disease (CVD) have not been examined in older adults. Clinical and subclinical CVD and its risk factors were compared in 4926 white and 244 black men and women aged 65 years and older. Black participants had lower socioeconomic status and generally higher prevalences of CVD and its risk factors, except for adverse lipid profiles. Common carotid wall thickness was greater in black than white women, and ankle-arm blood pressure ratios were lower in black women and men (p < 0.01). After adjustment for CVD risk factors, common carotid walls were significantly thicker and ankle-arm ratios were lower in blacks than whites of both sexes, while internal carotid walls were significantly thinner in black women. Racial differences in clinical and subclinical CVD in older adults are similar to those reported in younger populations and do not appear to be explained by CVD risk factors.
Keywords: African Continental Ancestry Group; Aged; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Geriatric Assessment; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Sex Factors

Ischemic episodes in 24-h ambulatory electrocardiograms of elderly persons: the Cardiovascular Health Study. - Rautaharju, P M; Manolio, T A; Furberg, C D; Siscovick, D; Newman, A B; Borhani, N O; Gardin, J M (Int J Cardiol, 1995)
We examined correlates of ischemic episodes in 24-h ambulatory electrocardiograms (ECG) in a sample of 1511 men and women 65 years old and older. Ischemic episodes had a high prevalence period during early afternoon and also during morning hours after awakening, and the overall prevalence was 13% in men and 9% in women (P < 0.001 for gender difference). The prevalence was 9.6% in participants with no history of myocardial infarction and no major or minor resting ECG abnormalities. In multivariate analysis by logistic regression, being on digitalis medication was associated with over a three-fold risk of ischemic episodes, with an odds ratio (95% confidence limits) of 3.21 (1.80 to 5.74). Left ventricular hypertrophy by ECG and atrial fibrillation had almost a three-fold excess risk of ischemic episodes, with odds ratios 2.81 (1.37 to 5.74) and 2.63 (1.17 to 5.91), respectively. Isolated ST-T abnormalities had almost a two-fold excess of ischemic episodes, with an odds ratio of 1.89 (1.01 to 3.54). Being overweight was associated with a 33% reduced likelihood of ischemic episodes after adjustment for other factors, with an odds ratio of 0.67 (0.46 to 0.98). It is concluded that the prevalence of silent ischemic episodes is high in older men and women.
Keywords: Age Factors; Aged; Arrhythmias, Cardiac; Atrial Fibrillation; California; Circadian Rhythm; Digitalis Glycosides; Electrocardiography; Electrocardiography, Ambulatory; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Logistic Models; Male; Maryland; Multivariate Analysis; Myocardial Infarction; Myocardial Ischemia; North Carolina; Obesity; Odds Ratio; Pennsylvania; Prevalence; Risk Factors; Sex Characteristics

Classification accuracy of electrocardiographic criteria for left ventricular hypertrophy in normal weight and overweight older adults: the Cardiovascular Health Study - Rautaharju, PM; Manolio, TA; Siscovick, D; Zhou, SH; Gardin, JM; Furberg, CD; Borhani, NO; Newman, AB (Annals of Noninvasive Electrocardiology, 1996)
BACKGROUND We evaluated classification accuracy of ECG criteria at varying levels of left ventricular hypertrophy (LVH) severity according to echocardiographically measured left ventricular mass (LVM) adjusted body size. METHODS: The test population was derived from the Cardiovascular Health Study (CHS), a population based sample of 5201 men and women aged 65 and older, and consisted of 1844 women and 1119 men with adequate quality ECGs and echocardiograms for LVM determination. The criteria evaluated were Sokolow-Lyon, Cornell Voltage, Cornell product, Framingham modification of Cornell voltage, and the left ventricular mass index (LVMI) of the Novacode ECG program. RESULTS: With LVH thresholds at upper 95% normal limit for weight adjusted LVM for the CHS population and ECG thresholds adjusted for 95% specificity in normal weight and overweight subgroups, the sensitivity of ECG criteria for LVH was relatively low. it was highest (40.8%) for the Novacode LVMI in normal weight men and for the Framingham criteria (30.9%) in normal weight women, but it deteriorated for both of these criteria in the presence of obesity. The overall performance of the Cornell product and Cornell voltage criteria was least influenced by obesity. The Framingham adjustment for the Cornell Voltage criteria for obesity substantially reduced their sensitivity. CONCLUSION: The choice of echocardiographic standard, LVH severity level and overweight in the test groups have a strong influence on ECG evaluation results.
Keywords: Adult; Aged; Body Size; classification; Health; Hypertrophy; methods; Obesity; Population

Prevalence and correlates of snoring and observed apneas in 5,201 older adults. - Enright, P L; Newman, A B; Wahl, P W; Manolio, T A; Haponik, E F; Boyle, P J (Sleep, 1996)
The objectives of this study were to describe the prevalence of snoring, observed apneas, and daytime sleepiness in older men and women, and to describe the relationships of these sleep disturbances to health status and cardiovascular diseases (CVD). A cross-sectional design was employed to study sleep problems, CVD, general health, psychosocial factors, and medication use. The subjects were participants in the Cardiovascular Health Study, which included 5,201 adults, aged 65 and older, who were recruited from a random sample of Medicare enrollees in four U.S. communities. Study measures employed were sleep questions, echocardiography, carotid ultrasound, resting electrocardiogram, cognitive function, cardiopulmonary symptoms and diseases, depression, independent activities of daily living (IADLs), and benzodiazepine use. Thirty-three percent of the men and 19% of the women reported loud snoring, which was less frequent in those over age 75. Snoring was positively associated with younger age, marital status, and alcohol use in men, and obesity, diabetes, and arthritis in women. Snoring was not associated, however, with cardiovascular risk factors or clinical CVD in men or women. Observed apneas were reported much less frequently (13% of men and 4% women) than snoring, and they were associated with alcohol use, chronic bronchitis, and marital status in men. Observed apneas were associated with depression and diabetes in women. In both men and women, daytime sleepiness was associated with poor health, advanced age, and IADL limitations. The conclusions of the study were that loud snoring, observed apneas, and daytime sleepiness are not associated cross-sectionally with hypertension or prevalent CVD in elderly persons.
Keywords: Activities of Daily Living; Age Factors; Aged; Cardiovascular Diseases; Comorbidity; Female; Humans; Incidence; Lung Diseases; Male; Narcolepsy; Prevalence; Random Allocation; Sex Factors; Sleep Apnea Syndromes; Snoring

Social support as a mediator in the relation between functional status and quality of life in older adults. - Newsom, J T; Schulz, R (Psychol Aging, 1996)
The relations among physical functioning, social support, depressive symptoms, and life satisfaction were examined in a national sample of 4,734 adults age 65 and older. Regression analyses were used to examine the relative importance of objective and subjective support measures in understanding the relation between physical impairment and quality of life. Impairment was associated with fewer friendship contacts, fewer family contacts, less perceived belonging support, and less perceived tangible aid, but only measures of perceived support predicted depressive symptomatology. A structural equation modeling approach was then used to explore the mediational role of perceived social support in the relation between impairment and quality of life variables. Results are consistent with the hypothesis that lower reported social support is an important reason for decreases in life satisfaction and increases in depressive symptoms found among older adult populations. Implications for understanding the role of social support in attenuating the effects of physical disability in older adults are discussed.
Keywords: Activities of Daily Living; Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Depression; Disabled Persons; Geriatric Assessment; Health Status; Humans; Personal Satisfaction; Quality of Life; Sick Role; Social Support

Utility of new electrocardiographic models for left ventricular mass in older adults. The Cardiovascular Health Study Collaborative Research Group. - Rautaharju, P M; Manolio, T A; Siscovick, D; Zhou, S H; Gardin, J M; Kronmal, R; Furberg, C D; Borhani, N O; Newman, A (Hypertension, 1996)
Several multivariate statistical models have recently been introduced for estimation of left ventricular mass from standard 12-lead electrocardiographic measurements. The validity of these algorithms has not been adequately evaluated. The objective of this investigation was to compare the associations between echocardiographic and electrocardiographic left ventricular mass values with clinical and subclinical indexes of coronary heart disease. The evaluation was performed with participants of the Cardiovascular Health Study, a population-based sample of 5201 men and women aged 65 years and older. Echocardiographic M-mode measurements of left ventricular mass were performed from videotape recordings with the use of a strictly standardized protocol. Electrocardiographic algorithms of the Novacode program and new algorithms derived from the Cardiovascular Health Study population were used for left ventricular mass prediction. Echocardiographic and electrocardiographic determinations of left ventricular mass were technically successful in 3410 (65.6%) and 5013 (96.4%) participants, respectively. The Novacode model overestimated echocardiographic left ventricular mass. Compared with the Novacode model, the new Cardiovascular Health Study electrocardiographic model, which includes adjustment for body weight, eliminated left ventricular mass prediction bias and improved the correlation between echocardiographic and electrocardiographic left ventricular mass from .33 to .54 in women and from .46 to .51 in men. Echocardiographic and electrocardiographic models both demonstrated similar and about equally strong associations with overt and subclinical disease and with risk factors for left ventricular hypertrophy. These observations demonstrate the potential utility of electrocardiographic models for left ventricular mass estimation.
Keywords: Age Factors; Aged; Echocardiography; Electrocardiography; Female; Humans; Hypertrophy, Left Ventricular; Linear Models; Male; Models, Cardiovascular; Obesity; Odds Ratio; Prognosis; Risk Factors; Sex Factors; Videotape Recording

The association of antihypertensive agents with MRI white matter findings and with Modified Mini-Mental State Examination in older adults. - Heckbert, S R; Longstreth, W T; Psaty, B M; Murros, K E; Smith, N L; Newman, A B; Williamson, J D; Bernick, C; Furberg, C D (J Am Geriatr Soc, 1997)
OBJECTIVES: To examine the association of antihypertensive regimen with magnetic resonance imaging (MRI) white matter hyperintensity and with cognitive impairment in older adults. DESIGN: Cross-sectional study. SETTING: The Cardiovascular Health study, an observational prospective cohort study of risk factors for coronary heart disease and stroke in men and women 65 years of age and older. PARTICIPANTS: 1268 men and women with pharmacologically treated hypertension. MEASUREMENTS: Information on medication use, medical history, and health habits was collected at clinic examinations. Participants completed the Modified Mini-Mental State Examination (3MS) and underwent MRI examination. Without clinical information, study neuroradiologists assigned an overall grade of white matter signal intensity on MRI on a scale from 0 (no findings) to 9 (extensive findings). RESULTS: Adjusted mean white matter grade was higher for users of calcium channel blockers (2.59, P = .007) and users of loop diuretics (2.60, P = .015) than for users of beta blockers (2.12). The association was present for both dihydropyridine and non-dihydropyridine calcium channel blockers. Adjusted mean 3MS scores were lower for users of calcium channel blockers (89.6, P < .002), especially dihydropyridines, and users of loop diuretics (89.7, P < .006) than for users of beta blockers (92.3). No statistically significant association could be shown for users of other drug regimens, including thiazides and ACE inhibitors. CONCLUSION: In this study, users of antihypertensive regimens which included calcium channel blockers or loop diuretics had more severe white matter hyperintensity on MRI and worse performance on 3MS than users of beta blockers.
Keywords: Adrenergic beta-Antagonists; Aged; Aged, 80 and over; Antihypertensive Agents; Brain; Calcium Channel Blockers; Cognition; Cohort Studies; Cross-Sectional Studies; Diuretics; Female; Geriatric Assessment; Humans; Magnetic Resonance Imaging; Male; Risk Factors

Health effects of caregiving: the caregiver health effects study: an ancillary study of the Cardiovascular Health Study. - Schulz, R; Newsom, J; Mittelmark, M; Burton, L; Hirsch, C; Jackson, S (Ann Behav Med, 1997)
We propose that two related sources of variability in studies of caregiving health effects contribute to an inconsistent pattern of findings: the sampling strategy used and the definition of what constitutes caregiving. Samples are often recruited through self-referral and are typically comprised of caregivers experiencing considerable distress. In this study, we examine the health effects of caregiving in large population-based samples of spousal caregivers and controls using a wide array of objective and self-report physical and mental health outcome measures. By applying different definitions of caregiving, we show that the magnitude of health effects attributable to caregiving can vary substantially, with the largest negative health effects observed among caregivers who characterize themselves as being strained. From an epidemiological perspective, our data show that approximately 80% of persons living with a spouse with a disability provide care to their spouse, but only half of care providers report mental or physical strain associated with caregiving.
Keywords: Activities of Daily Living; Aged; Arousal; Cardiovascular Diseases; Caregivers; Cerebrovascular Disorders; Coronary Disease; Cost of Illness; Female; Geriatric Assessment; Health Behavior; Health Status; Humans; Male; Psychophysiologic Disorders; Risk Factors; Spouses; Stress, Psychological

Preventive health behaviors among spousal caregivers. - Burton, L C; Newsom, J T; Schulz, R; Hirsch, C H; German, P S (Prev Med, 1997)
BACKGROUND: The physical and emotional burden of caring for a functionally impaired spouse may adversely affect the preventive health behavior of the caregiver. This study explores the relationship between caregiving and lifestyle health behaviors and use of preventive services. METHODS: The Caregiver Health Effects Study identified spousal caregivers among a sample of more than 3,000 married, community-dwelling older persons, from four counties in the United States, who were enrollees in the Cardiovascular Health Study. High-level caregivers were defined as having a spouse with an ADL impairment (n = 212) and moderate-level caregivers, a spouse with one or more IADL impairments (n = 222). For each caregiver, a control, matched for age and gender, was selected (n = 385). Structured interviews were conducted in the home, following enrollment. RESULTS: Being a high-level caregiver significantly increased the odds of not getting enough rest, not having enough time to exercise, not having time to rest to recuperate from illness, and forgetting to take prescription medications, compared with noncaregivers. These findings did not hold for moderate-level caregivers. The odds were not significantly different for either level of caregiver compared with noncaregivers for missing meals, missing doctor appointments, missing flu shots, and not refilling medications. Larger proportions of caregivers with a strong sense of control had good preventive health behaviors, compared with caregivers with a weak sense of control.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Chi-Square Distribution; Confidence Intervals; Exercise; Female; Health Behavior; Health Status; Health Surveys; Humans; Internal-External Control; Life Style; Logistic Models; Male; Odds Ratio; Preventive Health Services; Self Care; Social Support; Spouses; United States

Sleep disturbance, psychosocial correlates, and cardiovascular disease in 5201 older adults: the Cardiovascular Health Study. - Newman, A B; Enright, P L; Manolio, T A; Haponik, E F; Wahl, P W (J Am Geriatr Soc, 1997)
OBJECTIVES: To describe the prevalence of self reported sleep disturbances in older men and women and to describe their relationships with health status and cardiovascular disease (CVD). DESIGN: Cross-sectional study of sleep disturbance, CVD, general health, psychosocial factors, physical function, and use of psychotropic medications. SETTING: Participants of the Cardiovascular Health Study, 5201 adults aged 65 and older recruited from a random sample of noninstitutionalized Medicare enrollees in four US communities. MEASURES: Self-reported sleep disturbances and standardized questionnaires for cardiopulmonary symptoms and diseases, depression, social support, activities of daily living, physical activity, cognitive function, and current medications, spirometry, ECG, echocardiography, and carotid ultrasound. RESULTS: Women were twice as likely as men to report difficulty falling asleep (30% vs 14%). Daytime sleepiness, difficulty falling asleep, and frequent awakenings increased in prevalence with age. All symptoms were related strongly to depression. Symptoms of daytime sleepiness were also related strongly to poor health and limitations in activities of daily living in men and women. In multivariate analysis, men taking benzodiazepines were likely to report difficulty falling asleep and daytime sleepiness, whereas women taking benzodiazepines reported difficulty falling asleep and waking up too early. After accounting for these factors, the only cardiovascular disease independently associated with sleep disturbances was angina. Men and women with confirmed angina were 1.6 times more likely to report trouble falling asleep. Independent relationships between sleep disturbances and cardiovascular risk factors such as obesity, hypertension, smoking, and diabetes were relatively weak and inconsistent, though smokers were less likely to report frequent awakenings. CONCLUSIONS: Sleep disturbances are relatively common in older men and women and are associated with poor health, depression, angina, limitations in activities of daily living, and the use of benzodiazepines.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depression; Female; Geriatric Assessment; Health Surveys; Humans; Male; Prevalence; Psychotropic Drugs; Random Allocation; Risk Factors; Sex Factors; Sleep Wake Disorders; Social Support; Surveys and Questionnaires; United States

The Sleep Heart Health Study: design, rationale, and methods. - Quan, S F; Howard, B V; Iber, C; Kiley, J P; Nieto, F J; O'Connor, G T; Rapoport, D M; Redline, S; Robbins, J; Samet, J M; Wahl, P W (Sleep, 1997)
The Sleep Heart Health Study (SHHS) is a prospective cohort study designed to investigate obstructive sleep apnea (OSA) and other sleep-disordered breathing (SDB) as risk factors for the development of cardiovascular disease. The study is designed to enroll 6,600 adult participants aged 40 years and older who will undergo a home polysomnogram to assess the presence of OSA and other SDB. Participants in SHHS have been recruited from cohort studies in progress. Therefore, SHHS adds the assessment of OSA to the protocols of these studies and will use already collected data on the principal risk factors for cardiovascular disease as well as follow-up and outcome information pertaining to cardiovascular disease. Parent cohort studies and recruitment targets for these cohorts are the following: Atherosclerosis Risk in Communities Study (1,750 participants), Cardiovascular Health Study (1,350 participants), Framingham Heart Study (1,000 participants), Strong Heart Study (600 participants), New York Hypertension Cohorts (1,000 participants), and Tucson Epidemiologic Study of Airways Obstructive Diseases and the Health and Environment Study (900 participants). As part of the parent study follow-up procedures, participants will be surveyed at periodic intervals for the incidence and recurrence of cardiovascular disease events. The study provides sufficient statistical power for assessing OSA and other SDB as risk factors for major cardiovascular events, including myocardial infarction and stroke.
Keywords: Adult; Aged; Aged, 80 and over; Arteriosclerosis; Cohort Studies; Coronary Disease; Female; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Polysomnography; Positive-Pressure Respiration; Prospective Studies; Research Design; Sleep Apnea Syndromes

Aspirin use and incident stroke in the cardiovascular health study. CHS Collaborative Research Group. - Kronmal, R A; Hart, R G; Manolio, T A; Talbert, R L; Beauchamp, N J; Newman, A (Stroke, 1998)
BACKGROUND AND PURPOSE: Randomized clinical trials testing aspirin in relatively low-risk, middle-aged people have consistently shown small increases in stroke associated with aspirin use. We analyzed the relationship between the regular use of aspirin and incident ischemic and hemorrhagic stroke among people aged 65 years or older participating in the Cardiovascular Health Study. METHODS: We conducted a multivariate analysis of incident stroke rates in a prospectively assessed, observational cohort of 5011 elderly people followed for a mean of 4.2 years. RESULTS: Participants had a mean age of 72 years, and 58% were women. Twenty-three percent used aspirin frequently, and 17% used aspirin infrequently at study entry. Frequent aspirin use was associated with an increased rate of ischemic stroke compared with nonusers (relative risk= 1.6; 95% confidence interval [CI], 1.2 to 2.2; P=0.001). After adjustment for other stroke risk factors, women who used aspirin frequently or infrequently at study entry had a 1.8-fold (95% CI, 1.2 to 2.8) and 1.6-fold (95% CI, 0.9 to 3.0) increased risk of ischemic stroke, respectively (P<0.01, test for trend), compared with nonusers. In men, aspirin use was not statistically significantly associated with stroke risk. Findings were similar when aspirin use in the years before the incident stroke was used in the modeling. Aspirin use at entry was also associated with a 4-fold (95% CI, 1.6 to 10.0) increase in risk of hemorrhagic stroke for both infrequent and frequent users of aspirin (P=0.003). CONCLUSIONS: Aspirin use was associated with increased risks of ischemic stroke in women and hemorrhagic stroke overall in this elderly cohort, after adjustment for other stroke predictors. The possibility exists of confounding by reasons for aspirin use rather than cause and effect. Whether regular aspirin use increases stroke risk for elderly people without cardiovascular disease can only be determined by randomized clinical trials.
Keywords: Aged; Aspirin; Brain Ischemia; Cardiovascular Diseases; Cerebral Hemorrhage; Cerebrovascular Disorders; Cohort Studies; Cyclooxygenase Inhibitors; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Incidence; Male; Regression Analysis; Risk Factors; Sex Factors; Time Factors

Caregiving from the recipient's perspective: negative reactions to being helped. - Newsom, J T; Schulz, R (Health Psychol, 1998)
This study investigated predictors of negative reactions to assistance provided to a physically disabled spouse (n = 276, M age: 76.6 years) and the consequences that negative reactions may have for the mental health of the care recipient. Nearly 40% of recipients reported some emotional distress in response to help they received. Fatalistic attitudes, perceived control, and lower self-esteem predicted greater helping distress, whereas lower self-esteem, fatalistic beliefs, and marital conflict were especially likely to lead to helping distress for those who received higher levels of assistance. Helping distress was also found to predict depression as much as 1 year later, suggesting that there may be long-term consequences of negative reactions to assistance. These findings have important implications for the study of caregiving and the relationship between physical impairment and depression.
Keywords: Activities of Daily Living; Aged; Caregivers; Chronic Disease; Depression; Disabled Persons; Factor Analysis, Statistical; Female; Helping Behavior; Humans; Internal-External Control; Longitudinal Studies; Male; Regression Analysis; Self Concept; Spouses; United States

Correlates and prevalence of benzodiazepine use in community-dwelling elderly. - Gleason, P P; Schulz, R; Smith, N L; Newsom, J T; Kroboth, P D; Kroboth, F J; Psaty, B M (J Gen Intern Med, 1998)
OBJECTIVE: To describe the prevalence of benzodiazepine use, sociodemographic and physical health factors associated with use, dosages taken, and directions for use among individuals aged 65 years and older. DESIGN: Cross-sectional analysis of baseline data from the community-based, prospective observational Cardiovascular Health Study. PATIENTS/PARTICIPANTS: Medicare eligibility lists from four U.S. communities were used to recruit a representative sample of 5,201 community-dwelling elderly, of which 5,181 participants met all study criteria. MEASUREMENTS AND MAIN RESULTS: Among participants, 511 (9.9%) were taking at least one benzodiazepine, primarily anxiolytics (73%). Benzodiazepines were often prescribed to be taken pro re nata (PRN "as needed"), and 36.5% of prescriptions with instructions to be taken regularly were taken at a dose lower than prescribed. Reported over-the-counter (OTC) sleep aid medication use was 39.2% in benzodiazepine users and 3.3% in nonusers. In a multivariate logistic model, the significant independent correlates of benzodiazepine use were being white (odds ratio [OR] 1.9; 95% confidence interval [CI] 1.0, 3.4), female (OR 1.7; CI 1.4, 2.2), and living in Forsyth County, North Carolina, or Washington County, Maryland, compared with living in Sacramento County, California, or Allegheny County, Pennsylvania (OR 2.3; CI 1.4, 2.2); having coronary heart disease (OR 1.6; CI 1.2, 2.1), health status reported as poor or fair (OR 1.8; CI 1.4, 2.3), self-reported diagnosis of nervous or emotional disorder (OR 6.7; CI 5.1, 8.7), and reporting use of an OTC sleep aid medication (OR 18.7; CI 14.1, 24.7). CONCLUSIONS: One in 10 participants reported taking a benzodiazepine, most frequently an anxiolytic, often at a lower dose than prescribed and usually PRN. The high prevalence of OTC sleep aid medication and benzodiazepine use may place the patient at increased risk of psychomotor impairment. Physicians should assess OTC sleep aid medication use when prescribing benzodiazepines.
Keywords: Aged; Aged, 80 and over; Benzodiazepines; Cross-Sectional Studies; Drug Utilization; Female; Humans; Male; Practice Patterns, Physicians'; Socioeconomic Factors

Correlates of daytime sleepiness in 4578 elderly persons: the Cardiovascular Health Study. - Whitney, C W; Enright, P L; Newman, A B; Bonekat, W; Foley, D; Quan, S F (Sleep, 1998)
OBJECTIVES: To describe the prevalence of self-reported daytime sleepiness in older men and women and to describe their relationships with demographic factors, nocturnal complaints, health status, and cardiovascular diseases (CVD). DESIGN: Cross-sectional survey and clinical exam. SETTING: Participants in the Cardiovascular Health Study, 4578 adults aged 65 and older, recruited from a random sample of non-institutionalized Medicare enrollees in four U.S. communities. MEASURES: Daytime sleepiness measured by the Epworth Sleepiness Scale (ESS), magnetic resonance imaging of the brain (MRI), cognitive function tests, and standardized questionnaires for cardiopulmonary symptoms and diseases, depressive symptoms, social support, activities of daily living, physical activity, and current medications. RESULTS: Approximately 20% of the participants reported that they were "usually sleepy in the daytime". Although elderly black men were less likely to report frequent awakenings than those in the other three race and gender groups, they had significantly higher mean ESS scores. The following were independently associated with higher ESS scores in gender-specific models: non-white race, depression, loud snoring, awakening with dyspnea or snorting, frequent nocturnal awakenings, medications used to treat congestive heart failure, non-use of sleeping pills, a sedentary lifestyle, and limitation of activities of daily living in both men and women; additional correlates included hip circumference and current smoking in men, and hayfever in women. The following were not independently associated with ESS in the models: age, education, use of wine or beer to aid sleep, use of tricyclic antidepressants, long- or short-acting benzodiazepines, asthma, angina, myocardial infarction, congestive heart failure itself, forced vital capacity, social support, cognitive function, or MRI evidence of global brain atrophy or white matter abnormality. CONCLUSIONS: Daytime sleepiness is common in the elderly, probably due to nocturnal disturbances such as frequent awakenings and snoring. The occasional use of sleeping pills for insomnia is associated with reduced daytime sleepiness in the elderly, while the use of medications for congestive heart failure is associated with daytime sleepiness. Surprisingly, anatomic abnormalities such as evidence of previous strokes and brain atrophy (as seen on brain MRI scans) were not associated with daytime sleepiness in these non-institutionalized elderly persons.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Brain; Cardiovascular Diseases; Circadian Rhythm; Cognition Disorders; Cohort Studies; Continental Population Groups; Cross-Sectional Studies; Disorders of Excessive Somnolence; Electrocardiography; Female; Health Status; Health Surveys; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prevalence; Sex Distribution

Reliability of scoring respiratory disturbance indices and sleep staging. - Whitney, C W; Gottlieb, D J; Redline, S; Norman, R G; Dodge, R R; Shahar, E; Surovec, S; Nieto, F J (Sleep, 1998)
STUDY OBJECTIVES: Unattended, home-based polysomnography (PSG) is increasingly used in both research and clinical settings as an alternative to traditional laboratory-based studies, although the reliability of the scoring of these studies has not been described. The purpose of this study is to describe the reliability of the PSG scoring in the Sleep Heart Health Study (SHHS), a multicenter study of the relation between sleep-disordered breathing measured by unattended, in-home PSG using a portable sleep monitor, and cardiovascular outcomes. DESIGN: The reliability of SHHS scorers was evaluated based on 20 randomly selected studies per scorer, assessing both interscorer and intrascorer reliability. RESULTS: Both inter- and intrascorer comparisons on epoch-by-epoch sleep staging showed excellent reliability (kappa statistics >0.80), with stage 1 having the greatest discrepancies in scoring and stage 3/4 being the most reliably discriminated. The arousal index (number of arousals per hour of sleep) was moderately reliable, with an intraclass correlation (ICC) of 0.54. The scorers were highly reliable on various respiratory disturbance indices (RDIs), which incorporate an associated oxygen desaturation in the definition of respiratory events (2% to 5%) with or without the additional use of associated EEG arousal in the definition of respiratory events (ICC>0.90). When RDI was defined without considering oxygen desaturation or arousals to define respiratory events, the RDI was moderately reliable (ICC=0.74). The additional use of associated EEG arousals, but not oxygen desaturation, in defining respiratory events did little to increase the reliability of the RDI measure (ICC=0.77). CONCLUSIONS: The SHHS achieved a high degree of intrascorer and interscorer reliability for the scoring of sleep stage and RDI in unattended in-home PSG studies.
Keywords: Humans; Polysomnography; Reproducibility of Results; Research Design; Sleep Apnea Syndromes; Sleep Stages

Risk factors for 5-year mortality in older adults: the Cardiovascular Health Study. - Fried, L P; Kronmal, R A; Newman, A B; Bild, D E; Mittelmark, M B; Polak, J F; Robbins, J A; Gardin, J M (JAMA, 1998)
CONTEXT: Multiple factors contribute to mortality in older adults, but the extent to which subclinical disease and other factors contribute independently to mortality risk is not known. OBJECTIVE: To determine the disease, functional, and personal characteristics that jointly predict mortality in community-dwelling men and women aged 65 years or older. DESIGN: Prospective population-based cohort study with 5 years of follow-up and a validation cohort of African Americans with 4.25-year follow-up. SETTING: Four US communities. PARTICIPANTS: A total of 5201 and 685 men and women aged 65 years or older in the original and African American cohorts, respectively. MAIN OUTCOME MEASURES: Five-year mortality. RESULTS: In the main cohort, 646 deaths (12%) occurred within 5 years. Using Cox proportional hazards models, 20 characteristics (of 78 assessed) were each significantly (P<.05) and independently associated with mortality: increasing age, male sex, income less than $50000 per year, low weight, lack of moderate or vigorous exercise, smoking for more than 50 pack-years, high brachial (>169 mm Hg) and low tibial (< or = 127 mm Hg) systolic blood pressure, diuretic use by those without hypertension or congestive heart failure, elevated fasting glucose level (>7.2 mmol/L [130 mg/dL]), low albumin level (< or = 37 g/L), elevated creatinine level (> or = 106 micromol/L [1.2 mg/dL]), low forced vital capacity (< or = 2.06 mL), aortic stenosis (moderate or severe) and abnormal left ventricular ejection fraction (by echocardiography), major electrocardiographic abnormality, stenosis of internal carotid artery (by ultrasound), congestive heart failure, difficulty in any instrumental activity of daily living, and low cognitive function by Digit Symbol Substitution test score. Neither high-density lipoprotein cholesterol nor low-density lipoprotein cholesterol was associated with mortality. After adjustment for other factors, the association between age and mortality diminished, but the reduction in mortality with female sex persisted. Finally, the risk of mortality was validated in the second cohort; quintiles of risk ranged from 2% to 39% and 0% to 26% for the 2 cohorts. CONCLUSIONS: Objective measures of subclinical disease and disease severity were independent and joint predictors of 5-year mortality in older adults, along with male sex, relative poverty, physical activity, smoking, indicators of frailty, and disability. Except for history of congestive heart failure, objective, quantitative measures of disease were better predictors of mortality than was clinical history of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Health Surveys; Humans; Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Time trends in the use of cholesterol-lowering agents in older adults: the Cardiovascular Health Study. - Lemaitre, R N; Furberg, C D; Newman, A B; Hulley, S B; Gordon, D J; Gottdiener, J S; McDonald, R H; Psaty, B M (Arch Intern Med, 1998)
OBJECTIVES: To describe recent temporal patterns of cholesterol-lowering medication use and the characteristics that may have influenced the initiation of cholesterol-lowering therapy among those aged 65 years or older. SUBJECTS AND METHODS: A cohort of 5201 adults 65 years or older were examined annually between June 1989 and May 1996. We added 687 African American adults to the cohort in 1992-1993. We measured blood lipid levels at baseline and for the original cohort in the third year of follow-up. We assessed the use of cholesterol-lowering drugs at each visit. RESULTS: The prevalence of cholesterol-lowering drug use in 1989-1990 was 4.5% among the men and 5.9% among the women; these figures increased over the next 6 years to 8.1% and 10.0%, respectively, in 1995-1996. There was a 4-fold increase in the use of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors during the 6 years of follow-up, from 1.9% of all participants in 1989-1990 to 7.5% in 1995-1996. The use of bile acid sequestrants, nicotinic acid, and probucol declined from initial levels of less than 1% each. Among the participants who were untreated in 1989-1990, but eligible for cholesterol-lowering therapy after a trial of dietary therapy according to the 1993 guidelines of the National Cholesterol Education Panel, less than 20% initiated drug therapy in the 6 years of follow-up, even among subjects with a history of coronary heart disease. Among participants untreated at baseline but eligible for either cholesterol-lowering therapy or dietary therapy, initiation of cholesterol-lowering drug therapy was directly associated with total cholesterol levels, hypertension, and a history of coronary heart disease, and was inversely related to age, high-density lipoprotein cholesterol levels, and difficulties with activities of daily living. Other characteristics that form the basis of the 1993 National Cholesterol Education Panel guidelines-diabetes, smoking, family history of premature coronary heart disease, and total number of risk factors-were not associated with the initiation of cholesterol-lowering drug therapy. CONCLUSIONS: Given the clinical trial evidence for benefit, those aged 65 to 75 years and with prior coronary heart disease appeared undertreated with cholesterol-lowering drug therapy.
Keywords: Aged; Anticholesteremic Agents; Cholesterol, LDL; Cohort Studies; Female; Humans; Hypercholesterolemia; Male; Prevalence; Risk Factors; United States

Ankle-arm index as a predictor of cardiovascular disease and mortality in the Cardiovascular Health Study. The Cardiovascular Health Study Group. - Newman, A B; Shemanski, L; Manolio, T A; Cushman, M; Mittelmark, M; Polak, J F; Powe, N R; Siscovick, D (Arterioscler Thromb Vasc Biol, 1999)
Peripheral arterial disease (PAD) in the legs, measured noninvasively by the ankle-arm index (AAI) is associated with clinically manifest cardiovascular disease (CVD) and its risk factors. To determine risk of total mortality, coronary heart disease, or stroke mortality and incident versus recurrent CVD associated with a low AAI, we examined the relationship of the AAI to subsequent CVD events in 5888 older adults with and without CVD. The AAI was measured in 5888 participants >/=65 years old at the baseline examination of the Cardiovascular Health Study. All participants had a detailed assessment of prevalent CVD and were contacted every 6 months for total mortality and CVD events (including CVD mortality, fatal and nonfatal myocardial infarction, congestive heart failure, angina, stroke, and hospitalized PAD). The crude mortality rate at 6 years was highest (32.3%) in those participants with prevalent CVD and a low AAI (P<0.9), and it was lowest in those with neither of these findings (8.7%, P<0.01). Similar patterns emerged from analysis of recurrent CVD and incident CVD. The risk for incident congestive heart failure (relative risk [RR]=1.61) and for total mortality (RR=1.62) in those without CVD at baseline but with a low AAI remained significantly elevated after adjustment for cardiovascular risk factors. Hospitalized PAD events occurred months to years after the AAI was measured, with an adjusted RR of 5.55 (95% CI, 3.08 to 9.98) in those at risk for incident events. A statistically significant decline in survival was seen at each 0.1 decrement in the AAI. An AAI of <0.9 is an independent risk factor for incident CVD, recurrent CVD, and mortality in this group of older adults in the Cardiovascular Health Study.
Keywords: Age Distribution; Aged; Aged, 80 and over; Ankle; Arm; Blood Pressure Determination; Cardiovascular Diseases; Cohort Studies; Female; Humans; Hypertension; Male; Predictive Value of Tests; Risk Factors; Sex Distribution; Survival Analysis

Relation of sleepiness to respiratory disturbance index: the Sleep Heart Health Study. - Gottlieb, D J; Whitney, C W; Bonekat, W H; Iber, C; James, G D; Lebowitz, M; Nieto, F J; Rosenberg, C E (Am J Respir Crit Care Med, 1999)
Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age of 65 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Sleep-disordered breathing was quantified by the respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, measured during in-home polysomnography. When RDI was categorized into four groups (< 5, 5 to < 15, 15 to < 30, >/= 30), a significantly progressive increase in mean ESS score was seen across all four levels of SDB, from 7.2 (4.3) in subjects with RDI < 5 to 9.3 (4.9) in subjects with RDI >/= 30 (p < 0.001). There was no significant modification of this effect by age, sex, body mass index, or evidence of chronic restriction of sleep time or periodic limb movement disorder. The percentage of subjects with excessive sleepiness, defined as an ESS score >/= 11, increased from 21% in subjects with RDI < 5 to 35% in those with RDI >/= 30 (p < 0. 001). We conclude that SDB is associated with excess sleepiness in community-dwelling, middle-aged and older adults, not limited to those with clinically apparent sleep apnea.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Respiration; Retrospective Studies; Severity of Illness Index; Sleep Apnea Syndromes; Surveys and Questionnaires

Stability and change in older adults' social contact and social support: the Cardiovascular Health Study. - Martire, L M; Schulz, R; Mittelmark, M B; Newsom, J T (J Gerontol B Psychol Sci Soc Sci, 1999)
OBJECTIVES: The aim of this study was to examine the degree of individual change in structural indicators of social support (family network contact and close friend network contact) and functional indicators of social support (belonging, appraisal, and tangible support) during late life. METHODS: Using a large population-based sample of older adults, hierarchical linear modeling was applied to examine the extent of change in social contact and support as well as sociodemographic characteristics (age, race, gender, and education) that might explain individual variability in contact and support at baseline and over time. RESULTS: Consistent with predictions, small yet significant increases were observed in belonging support and tangible support. Contrary to predictions, no evidence was found for significant individual change in family network contact, close friend network contact, or appraisal support. Sociodemographic characteristics were more consistent predictors of variability in contact and support at baseline than variability over time. DISCUSSION: The findings of this study add to a growing literature suggesting that late life is not typically characterized by a decline in important social resources.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Educational Status; Family; Female; Health Status; Humans; Interpersonal Relations; Linear Models; Longitudinal Studies; Male; Predictive Value of Tests; Sex Factors; Social Support; Socioeconomic Factors; Surveys and Questionnaires; Time Factors; United States

Stroke risk in an elderly population with atrial fibrillation. - Feinberg, W M; Kronmal, R A; Newman, A B; Kraut, M A; Bovill, E G; Cooper, L; Hart, R G (J Gen Intern Med, 1999)
Patients with nonvalvular atrial fibrillation (AF) have an increased risk of stroke, but the absolute rate of stroke varies widely depending on coexistent vascular disease. We assessed the stroke rate and predictive value of two published schemes for stroke risk stratification in a population-derived cohort of 259 elderly people with nonvalvular AF followed for a median of 5.3 years. The rate of ischemic stroke was 2.8% per year (95% confidence interval [CI] 1.9, 3.9). Thirty-one percent were predicted to be at low risk, and their stroke rate was 1.7% per year (95% CI 0.6, 3.8). Many people with AF in this population-derived cohort had relatively low rates of stroke. Further studies to reliably stratify stroke risk in patients with AF are needed.
Keywords: Aged; Atrial Fibrillation; Cerebrovascular Disorders; Cohort Studies; Humans; Male; Poisson Distribution; Proportional Hazards Models; Risk Factors

Temporal trends in the use of anticoagulants among older adults with atrial fibrillation. - Smith, N L; Psaty, B M; Furberg, C D; White, R; Lima, J A; Newman, A B; Manolio, T A (Arch Intern Med, 1999)
BACKGROUND: Several recent randomized clinical trials have demonstrated that warfarin sodium treatment, and to a lesser extent aspirin, reduces risk of stroke and death compared with placebo in persons with atrial fibrillation. Insufficient documentation exists on the extent to which the use of these therapies following trial publications has continued to increase in the elderly with atrial fibrillation. METHODS: We used data from the Cardiovascular Health Study, a study of 5888 community-dwelling adults aged 65 years or older, to determine the prevalence of warfarin and aspirin use in persons with electrocardiogram-identified atrial fibrillation. Electrocardiogram examinations were conducted at baseline from 1989 through 1990, and at 6 subsequent annual examinations through 1995-1996. Medication data were collected by inventory methods at each examination. Temporal change in use of anticoagulants was analyzed by comparing percentage use in 1990 to use in each year through 1996. RESULTS: The use of warfarin increased 4-fold from 13% in 1990 to 50% in 1996 among participants with prevalent atrial fibrillation (P<.001). Daily use of aspirin did not increase over time. Participants younger than 80 years were 4 times more likely to use warfarin in 1996 (P<.001) than those 80 years and older. Use of aspirin did not vary significantly with age. CONCLUSIONS: Warfarin use in community-dwelling elderly persons with electrocardiogram-documented atrial fibrillation increased steadily following the first publication of its treatment benefit, reaching 50% by 1996. In contrast, use of aspirin was unchanged during this same period. Continued efforts to promote appropriate anticoagulation therapy to physicians and their patients may still be needed.
Keywords: Aged; Anticoagulants; Aspirin; Atrial Fibrillation; Cerebrovascular Disorders; Drug Therapy; Electrocardiography; Female; Humans; Incidence; Male; Prevalence; Treatment Outcome; Warfarin

Underdiagnosis and undertreatment of asthma in the elderly. Cardiovascular Health Study Research Group. - Enright, P L; McClelland, R L; Newman, A B; Gottlieb, D J; Lebowitz, M D (Chest, 1999)
OBJECTIVE: To describe the clinical correlates of asthma in a community-based sample of elderly persons. PARTICIPANTS: A community sample of 4,581 persons > or = 65 years old from the Cardiovascular Health Study. MEASUREMENTS: Standardized respiratory, sleep, and quality-of-life (QOL) questions, a medication inventory, spirometry, and ambulatory peak flow. RESULTS: Four percent of the participants reported a current diagnosis of asthma (definite asthma), while another 4% reported at least one attack of wheezing accompanied by chest tightness or dyspnea during the previous 12 months (probable asthma). Smokers and those with congestive heart failure were excluded from the subsequent analyses, leaving 2,527 participants. Of those who had definite asthma, 40% were taking a sympathomimetic bronchodilator, 30% inhaled corticosteroids, 21% theophylline, and 18% oral corticosteroids; 39% were taking no asthma medications. The participants with definite or probable asthma were much more likely than the others to have a family history of asthma, childhood respiratory problems, a history of workplace exposures, dyspnea on exertion, hay fever, chronic bronchitis, nocturnal symptoms, and daytime sleepiness. They were also more likely to report poor general health, symptoms of depression, and limitation of activities of daily living. There was little difference in the morbidity and QOL of participants with recent asthma-like symptoms who had received the diagnosis of asthma versus those who had not. CONCLUSIONS: Asthma in elderly persons is associated with a lower QOL and considerable morbidity when compared with those who do not have asthma symptoms. Asthma is underdiagnosed in this group and is often associated with allergic triggers; inhaled corticosteroids are underutilized.
Keywords: Age Factors; Aged; Aged, 80 and over; Asthma; Female; Humans; Male; Peak Expiratory Flow Rate; Quality of Life; Risk Factors; Spirometry; Vital Capacity

Association of sleep-disordered breathing, sleep apnea, and hypertension in a large community-based study. Sleep Heart Health Study. - Nieto, F J; Young, T B; Lind, B K; Shahar, E; Samet, J M; Redline, S; D'Agostino, R B; Newman, A B; Lebowitz, M D; Pickering, T G (JAMA, 2000)
CONTEXT: Sleep-disordered breathing (SDB) and sleep apnea have been linked to hypertension in previous studies, but most of these studies used surrogate information to define SDB (eg, snoring) and were based on small clinic populations, or both. OBJECTIVE: To assess the association between SDB and hypertension in a large cohort of middle-aged and older persons. DESIGN AND SETTING: Cross-sectional analyses of participants in the Sleep Heart Health Study, a community-based multicenter study conducted between November 1995 and January 1998. PARTICIPANTS: A total of 6132 subjects recruited from ongoing population-based studies (aged > or = 40 years; 52.8% female). MAIN OUTCOME MEASURES: Apnea-hypopnea index (AHI, the average number of apneas plus hypopneas per hour of sleep, with apnea defined as a cessation of airflow and hypopnea defined as a > or = 30% reduction in airflow or thoracoabdominal excursion both of which are accompanied by a > or = 4% drop in oxyhemoglobin saturation) [corrected], obtained by unattended home polysomnography. Other measures include arousal index; percentage of sleep time below 90% oxygen saturation; history of snoring; and presence of hypertension, defined as resting blood pressure of at least 140/90 mm Hg or use of antihypertensive medication. RESULTS: Mean systolic and diastolic blood pressure and prevalence of hypertension increased significantly with increasing SDB measures, although some of this association was explained by body mass index (BMI). After adjusting for demographics and anthropometric variables (including BMI, neck circumference, and waist-to-hip ratio), as well as for alcohol intake and smoking, the odds ratio for hypertension, comparing the highest category of AHI (> or = 30 per hour) with the lowest category (< 1.5 per hour), was 1.37 (95% confidence interval [CI], 1.03-1.83; P for trend = .005). The corresponding estimate comparing the highest and lowest categories of percentage of sleep time below 90% oxygen saturation (> or = 12% vs < 0.05%) was 1.46 (95% CI, 1.12-1.88; P for trend <.001). In stratified analyses, associations of hypertension with either measure of SDB were seen in both sexes, older and younger ages, all ethnic groups, and among normal-weight and overweight individuals. Weaker and nonsignificant associations were observed for the arousal index or self-reported history of habitual snoring. CONCLUSION: Our findings from the largest cross-sectional study to date indicate that SDB is associated with systemic hypertension in middle-aged and older individuals of different sexes and ethnic backgrounds.
Keywords: Adult; Aged; Cohort Studies; Cross-Sectional Studies; Female; Humans; Hypertension; Logistic Models; Male; Middle Aged; Obesity; Polysomnography; Sleep Apnea Syndromes; Snoring

Cognitive test performance and presence of subclinical cardiovascular disease in the cardiovascular health study. - Saxton, J; Ratcliff, G; Newman, A; Belle, S; Fried, L; Yee, J; Kuller, L (Neuroepidemiology, 2000)
The purpose of the present study was to investigate the relationship between performance on a comprehensive battery of neuropsychological tests and the presence of clinical, subclinical or no cardiovascular disease in an elderly community-dwelling population. The results confirm previous reports of significant associations of age, education and gender with test performance. When performance was examined controlling for these variables, significant associations of disease group were seen with five measures emphasizing speed of performance; Parts A and B of the Trail Making Test, the WAIS-R Digit Symbol and Block Design subtests and category verbal fluency. These results add to the evidence that, in addition to other health implications, cardiovascular disease is related to cognitive functioning in the elderly even at subclinical levels.
Keywords: Aged; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Hypertension; Male; Severity of Illness Index; Wechsler Scales

Coronary artery calcification in older adults with minimal clinical or subclinical cardiovascular disease. - Newman, A B; Naydeck, B; Sutton-Tyrrell, K; Edmundowicz, D; Gottdiener, J; Kuller, L H (J Am Geriatr Soc, 2000)
BACKGROUND: Coronary artery calcification (CAC) reflects the extent of coronary artery atherosclerosis. The extent of coronary artery calcification is not well described in older adults. OBJECTIVE: To determine the extent of CAC in older adults participating in a large population study of cardiovascular disease (CVD), especially those characterized as having minimal clinical or subclinical cardiovascular disease. DESIGN: An observational epidemiologic study. POPULATION: Participants in the Cardiovascular Health Study Cohort, mean age 78 years, who had electron beam computed tomography (EBT) scan of the heart (n = 133); included were 106 persons with no prior evidence of clinical or subclinical CVD. MEASUREMENTS: Total CAC score was measured using cardiac EBT. Cardiovascular disease and risk factors, as well as carotid ultrasound, electrocardiogram, echocardiogram, and ankle-arm index, had been measured previously to define subclinical disease. Previous cerebral magnetic resonance imaging was also evaluated. RESULTS: Overall, the CAC scores were higher in those with clinical cardiovascular disease or evidence of subclinical cardiovascular disease than in those with no evidence of disease. For the 106 participants without evidence of clinical or subclinical disease, the median score was 176, compared with 367 in those with subclinical disease and 923 in those with clinical CVD. Seventeen persons had scores of zero. There was little difference in risk factors across quartiles of CAC in the subgroup of 106 with prior characterization of minimal CVD despite the broad range of CAC scores. There was a higher proportion of those with white matter grade > or = 2 by magnetic resonance imaging among those with higher CAC scores (P = .025). Infarct-like lesions prevalence ranged from 12.5% in the lowest group to 47.1% in the highest CAC group (P = .019). CONCLUSIONS: Older adults with evidence of clinical or subclinical CVD have higher total CAC scores. Though the extent of coronary artery calcification was lower in those with minimal evidence of CVD, the range was broad and not explained by CVD risk factors.
Keywords: Aged; Aging; Analysis of Variance; Calcinosis; Cardiovascular Diseases; Chi-Square Distribution; Coronary Artery Disease; Coronary Disease; Female; Humans; Male; Risk Factors; Statistics, Nonparametric; Tomography, X-Ray Computed

Daytime sleepiness predicts mortality and cardiovascular disease in older adults. The Cardiovascular Health Study Research Group. - Newman, A B; Spiekerman, C F; Enright, P; Lefkowitz, D; Manolio, T; Reynolds, C F; Robbins, J (J Am Geriatr Soc, 2000)
INTRODUCTION: As part of the baseline examination in the Cardiovascular Health Study, sleep disturbance symptoms including snoring and daytime sleepiness, were assessed as potential risk factors or precipitants of cardiovascular disease (CVD). Because of the association of sleep disturbance with poorer health and the possible associations of sleep apnea with CVD, we hypothesized that those with poorer sleep or daytime sleepiness may be at increased risk of mortality or incident CVD. SETTING: Participants (n = 5888) were recruited in 1989, with an additional minority cohort recruited in 1993, in four US communities for a cohort study designed to evaluate risk factors for cardiovascular disease. METHODS: An interview-administered questionnaire regarding health and sleep habits with ongoing ascertainment of total mortality and cardiovascular disease morbidity and mortality, including total CVD morbidity and mortality, incident myocardial infarction, and congestive heart failure. RESULTS: Daytime sleepiness was the only sleep symptom that was significantly associated with mortality in both men and women. The unadjusted hazard ratio was 2.12 (1.66, 2.72) in women and 1.40 (1.12, 1.73) in men. Men who reported difficulty falling asleep also had an increased mortality rate (HR = 1.43 (1.14, 1.80)) which was not seen in women. The risks were attenuated with adjustment for age but remained significant for daytime sleepiness in women (HR = 1.82 (1.42, 2.34)) and for difficulty falling asleep in men. (HR = 1.29 (1.03, 1.63)). Frequent awakenings, early morning awakening, and snoring were not associated with a significantly increased risk of mortality in these older men and women. Crude event rates were evaluated for total incident cardiovascular morbidity and mortality, incident myocardial infarction, and incident congestive heart failure (CHF). Incident CVD rates were higher in both men and women with daytime sleepiness. The aged adjusted HR was 1.35 (95% CI = 1.03, 1.76) in men and was 1.66 (95% CI = 1.28, 2.16) in women. Incident CVD was not higher in those with any other sleep disturbance including snoring. The risk of CVD events associated with daytime sleepiness was attenuated but remained significant in women after adjustment for age. Incident myocardial infarction (MI) rates were also higher in women with daytime sleepiness but were not significantly higher in men. Incident CHF rates were increased in both men and women with daytime sleepiness. In men, the age adjusted HR was 1.49 (95% CI, 1.12- 1.98) and in women, was 2.21 (95% CI, 1.64-2.98). Women reporting both daytime sleepiness and frequent awakening had a hazard ratio of 2.34 (95% CI, 1.66-3.29) for incident CHF compared with those with daytime sleepiness but without frequent awakening. This interaction was not found in men. CONCLUSIONS: In this study, daytime sleepiness was the only sleep disturbance symptom that was associated with mortality, incident CVD morbidity and mortality, MI, and CHF. These findings were stronger in women than men, i.e., the associations persisted for mortality, CVD, and CHF in women after adjustment for age and other factors. Thus, a report of daytime sleepiness identifies older adults at increased risk for total and cardiovascular mortality, and is an independent risk factor in women.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Heart Failure; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Odds Ratio; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Sleep Stages; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Orthostatic Hypotension in the Elderly: Contributions of Impaired LV Filling and Altered Sympathovagal Balance. - Gottdiener, John S.; Yanez, David; Rautaharju, Penttii; Gardin, Julius M.; Bild, Diane E.; Lima, Joao; Newman, Anne B. (Am J Geriatr Cardiol, 2000)
Orthostatic hypotension, which occurs in 5%-18% of the elderly, may contribute to age-related disability. While autonomic dysfunction and alterations of cardiac structure and function likely to impair postural maintenance of blood pressure are common in the elderly, these have not been jointly studied in large cohorts. The authors evaluated the association of orthostatic hypotension with echocardiographic measures of cardiac structure and function, and with autonomic function determined by analysis of heart rate variability, in a large population of community-dwelling elderly. A total of 5201 men and women, aged 65-100 years and living in four geographically separate communities, were recruited from Medicare eligibility lists. In this prospective, observational cohort study, measurements included clinical questionnaires, standing and supine blood pressures, mini-glucose tolerance testing, echocardiography, and 24-hour Holter recording for assessment of heart rate variability. Orthostatic hypotension, defined as a decrease in standing systolic blood pressure of 20 mm Hg or more, was positively associated in bivariate analyses with left ventricular wall thickness, peak velocity of late diastolic filling, vagal tone on heart rate variability analysis, supine systolic pressure, supine diastolic pressure, age, and diabetes, and inversely associated with body weight. After statistical adjustment for the presence of myocardial infarction, stroke, and use of antihypertensive medication, the associations were maintained, and a previous trend toward an association with decreased left ventricular cavity size became statistically significant. The data suggest that in elderly, community-based individuals, orthostatic hypotension is associated with increased blood pressure and decreased weight; it possibly acts mechanistically via altered sympathovagal balance, increased left ventricular wall thickness, decreased left ventricular preload, and alterations of left ventricular diastolic filling. (c) 2000 by CVRR, Inc.

Area characteristics and individual-level socioeconomic position indicators in three population-based epidemiologic studies. - Diez-Roux, A V; Kiefe, C I; Jacobs, D R; Haan, M; Jackson, S A; Nieto, F J; Paton, C C; Schulz, R (Ann Epidemiol, 2001)
PURPOSE: There is growing interest in incorporating area indicators into epidemiologic analyses. Using data from the 1990 U.S. Census linked to individual-level data from three epidemiologic studies, we investigated how different area indicators are interrelated, how measures for different sized areas compare, and the relation between area and individual-level social position indicators. METHODS: The interrelations between 13 area indicators of wealth/income, education, occupation, and other socioenvironmental characteristics were investigated using correlation coefficients and factor analyses. The extent to which block-group measures provide information distinct from census tract measures was investigated using intraclass correlation coefficients. Loglinear models were used to investigate associations between area and individual-level indicators. RESULTS: Correlations between area measures were generally in the 0.5--0.8 range. In factor analyses, six indicators of income/wealth, education, and occupation loaded on one factor in most geographic sites. Correlations between block-group and census tract measures were high (correlation coefficients 0.85--0.96). Most of the variability in block-group indicators was between census tracts (intraclass correlation coefficients 0.72--0.92). Although individual-level and area indicators were associated, there was evidence of important heterogeneity in area of residence within individual-level income or education categories. The strength of the association between individual and area measures was similar in the three studies and in whites and blacks, but blacks were much more likely to live in more disadvantaged areas than whites. CONCLUSIONS: Area measures of wealth/income, education, and occupation are moderately to highly correlated. Differences between using census tract or block-group measures in contextual investigations are likely to be relatively small. Area and individual-level indicators are far from perfectly correlated and provide complementary information on living circumstances. Differences in the residential environments of blacks and whites may need to be taken into account in interpreting race differences in epidemiologic studies.
Keywords: Adult; Black or African American; Cardiovascular Diseases; Demography; Educational Status; Factor Analysis, Statistical; Humans; Income; Linear Models; Occupations; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Statistics, Nonparametric; United States; White People

The association of sleep-disordered breathing and sleep symptoms with quality of life in the Sleep Heart Health Study. - Baldwin, C M; Griffith, K A; Nieto, F J; O'Connor, G T; Walsleben, J A; Redline, S (Sleep, 2001)
This study assessed the extent to which sleep-disordered breathing (SDB), difficulty initiating and maintaining sleep (DIMS), and excessive daytime sleepiness (EDS) were associated with impairment of quality of life (QoL) using the SF-36. Participants (n=5,816; mean age=63 years; 52.5% women) were enrolled in the nation-wide population-based Sleep Heart Health Study (SHHS) implemented to investigate sleep-disordered breathing as a risk factor in the development of cardiovascular disease. Each transformed SF-36 scale was analyzed independently using multiple logistic regression analysis with sleep and other potential confounding variables (e.g., age, ethnicity) included as independent variables. Men (11.6%) were significantly more likely to have SDB compared to women (5.6%), while women (42.4%) were significantly more likely to report DIMS than men (32.5%). Vitality was the sole SF-36 scale to have a linear association with the clinical categories of SDB (mild, moderate, severe SDB). However, individuals with severe SDB indicated significantly poorer QoL on several SF-36 scales. Both DIMS and EDS were strongly associated with reduced QoL even after adjusting for confounding variables for both sexes. Findings suggest 1) mild to moderate SDB is associated with reduced vitality, while severe SDB is more broadly associated with poorer QoL, 2) subjective sleep symptoms are comprehensively associated with poorer QoL, and 3) SF-36 mean score profiles for SDB and sleep symptoms are equivalent to other chronic diseases in the U.S. general population.
Keywords: Adult; Cardiovascular Diseases; Chronic Disease; Circadian Rhythm; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Population Surveillance; Prevalence; Quality of Life; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; United States

Associations of subclinical cardiovascular disease with frailty. - Newman, A B; Gottdiener, J S; McBurnie, M A; Hirsch, C H; Kop, W J; Tracy, R; Walston, J D; Fried, L P (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frail health in old age has been conceptualized as a loss of physiologic reserve associated with loss of lean mass, neuroendocrine dysregulation, and immune dysfunction. Little work has been done to define frailty and describe the underlying pathophysiology. METHODS: Frailty status was defined in participants of the Cardiovascular Health Study (CHS), a cohort of 5,201 community-dwelling older adults, based on the presence of three out of five clinical criteria. The five criteria included self-reported weight loss, low grip strength, low energy, slow gait speed, and low physical activity. We examined the spectrum of clinical and subclinical cardiovascular disease in those who were frail (3/5 criteria) or of intermediate frailty status (1 or 2/5 criteria), compared to those who were not frail (0/5). We hypothesized that the severity of frailty would be related to a higher prevalence of reported cardiovascular disease (CVD), as well as to a greater extent of CVD, measured by noninvasive testing. RESULTS: Of 4,735 eligible participants, 2,289 (48%) were not frail, 299 (6%) were frail, and 2.147 (45%) were of intermediate frailty status. Those who were frail were older (77.2 yrs) compared to those who were not frail (71.5 yrs) or intermediate (73.4 yrs) (p < .001). Frailty status was associated with clinical CVD and most strongly with congestive heart failure (odds ratio [OR] = 7.51 (95% confidence interval [CI] = 4.66-12.12). In those without a history of a CVD event (n = 1.259), frailty was associated with many noninvasive measures of CVD. Those with carotid stenosis >75% (adjusted OR = 3.41), ankle-arm index <0.8 (adjusted OR = 3.17) or 0.8-0.9 (adjusted OR = 2.01), major electrocardiography (ECG) abnormalities (adjusted OR = 1.58), greater left ventricular (LV) mass by echocardiography (adjusted OR = 1.16), and higher degree of infarct-like lesions in the brain (adjusted OR = 1.71), were more likely to be frail compared to those who were not frail. The overall associations of each of these noninvasive measures of CVD with frailty level were significant (all p < .05). CONCLUSIONS: Cardiovascular disease was associated with an increased likelihood of frail health. In those with no history of CVD, the extent of underlying cardiovascular disease measured by carotid ultrasound and ankle-arm index, LV hypertrophy by ECG and echocardiography, was related to frailty. Infarct-like lesions in the brain on magnet resonance imaging were related to frailty as well.
Keywords: Aged; Ankle; Arm; Black or African American; Blood Pressure; Brain; Cardiovascular Diseases; Carotid Artery Diseases; Cerebral Infarction; Cerebrovascular Disorders; Cohort Studies; Echocardiography; Electrocardiography; Frail Elderly; Health Status; Heart Failure; Humans; Magnetic Resonance Imaging; United States; Vascular Diseases

Cardiovascular disease and mortality in older adults with small abdominal aortic aneurysms detected by ultrasonography: the cardiovascular health study. - Newman, A B; Arnold, A M; Burke, G L; O'Leary, D H; Manolio, T A (Ann Intern Med, 2001)
BACKGROUND: Persons with abdominal aortic aneurysm are more likely to have a higher prevalence of risk factors for and clinical manifestations of cardiovascular disease. It is unknown whether these factors explain the high mortality rate associated with abdominal aortic aneurysm. OBJECTIVE: To describe the risk for mortality, cardiovascular mortality, and cardiovascular morbidity in persons screened for abdominal aortic aneurysm. DESIGN: Longitudinal cohort study. SETTING: Four communities in the United States. PARTICIPANTS: 4734 men and women older than 65 years of age recruited from Medicare eligibility lists. MEASUREMENTS: Abdominal ultrasonography was used to measure the aortic diameter and the ratio of infrarenal to suprarenal measurement of aortic diameter in 1992-1993. Abdominal aortic aneurysm was defined as aortic diameter of 3 cm or greater or infrarenal-to-suprarenal ratio of 1.2 or greater. Mortality, cardiovascular disease mortality, incident cardiovascular disease, and repair or rupture were assessed after 4.5 years. RESULTS: The prevalence of aneurysm was 8.8%, and 87.7% of aneurysms were 3.5 cm or less in diameter. Rates of total mortality (65.1 vs. 32.8 per 1000 person-years), cardiovascular mortality (34.3 vs. 13.8 per 1000 person-years), and incident cardiovascular disease (47.3 vs. 31.0 per 1000 person-years) were higher in participants with aneurysm than in those without aneurysm; after adjustment for age, risk factors, and presence of other cardiovascular disease, the respective relative risks were 1.32, 1.36, and 1.57. Rates of repair and rupture were low. CONCLUSIONS: Rates of total mortality, cardiovascular disease mortality, and incident cardiovascular disease were higher in participants with abdominal aortic aneurysm than in those without aneurysm, independent of age, sex, other clinical cardiovascular disease, and extent of atherosclerosis detected by noninvasive testing. Persons with smaller aneurysms detected by ultrasonography should be advised to modify risk factors for cardiovascular disease while under surveillance for increase in the size of the aneurysm.
Keywords: Aged; Aged, 80 and over; Aortic Aneurysm, Abdominal; Aortic Rupture; Cardiovascular Diseases; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; Ultrasonography; United States

Coronary artery calcification in older adults to age 99: prevalence and risk factors. - Newman, A B; Naydeck, B L; Sutton-Tyrrell, K; Feldman, A; Edmundowicz, D; Kuller, L H (Circulation, 2001)
BACKGROUND: Coronary artery calcification has been proposed as a noninvasive method to assess cardiovascular disease (CVD) risk. However, the prevalence and risk factors for coronary artery calcification in populations >65 years have not been well studied. METHODS AND RESULTS: Electron beam tomography was performed to assess coronary artery calcium (CAC) in 614 older adults aged, on average, 80 years (range, 67 to 99 years); 367 (60%) were women, and 143 (23%) were black. Calcium scores ranged from 0 to 5459. Median scores were 622 for men and 205 for women. Scores increased by age and were lower in blacks than in whites. Nine percent of subjects (n=57) had no CAC, and 31% (n=190) had a score lower than 100. A history of CVD was associated with calcium score. Age, male sex, white race, CVD, triglyceride level, pack-years of smoking, and asthma, emphysema, or bronchitis (chronic obstructive pulmonary disease) were independently associated with CAC score in the fourth quartile. CONCLUSIONS: A wide range of CAC scores was observed, suggesting adaptation with aging. CAC may have potential to predict CVD in older adults, but this remains to be determined.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Black People; Calcinosis; Calcium; Cohort Studies; Comorbidity; Coronary Angiography; Coronary Artery Disease; Coronary Vessels; Demography; Female; Humans; Logistic Models; Male; Predictive Value of Tests; Prevalence; Risk Factors; Sex Distribution; Sex Factors; Tomography, X-Ray Computed; White People

Factors associated with healthy aging: the cardiovascular health study. - Burke, G L; Arnold, A M; Bild, D E; Cushman, M; Fried, L P; Newman, A; Nunn, C; Robbins, J (J Am Geriatr Soc, 2001)
OBJECTIVES: To identify factors associated with remaining healthy in older adults. DESIGN: Longitudinal cohort study. SETTING: Data were collected at the four Cardiovascular Health Study field centers. PARTICIPANTS: 5,888 participants age 65 years and older in the Cardiovascular Health Study. MEASUREMENTS: Presence of chronic disease was assessed at baseline and over a maximum 7-year follow-up period. Participants who were free of chronic disease (no cardiovascular disease (CVD), chronic obstructive pulmonary disease, or self-reported cancer, except nonmelanoma skin cancer) at the baseline examination were then monitored for the onset of incident cancer, cardiovascular disease, and fatal outcomes. RESULTS: A high proportion of these older adults was healthy at the initial examination and remained healthy over the follow-up period. Numerous behavioral factors were associated with continued health, including physical activity, refraining from cigarette smoking, wine consumption (women), higher educational status, and lower waist circumference. A number of CVD risk factors and subclinical disease measures were associated with continued health, including higher high-density lipoprotein (HDL) cholesterol, lack of diabetes, thinner common carotid intimal nmedial thickness, lower blood pressure, lower C-reactive protein, and higher ankle-arm blood pressure ratio. Among the behavioral factors, exercise, not smoking, and not taking aspirin remained significant predictors of health even after controlling for CVD risk factors and subclinical disease in older adults. CONCLUSIONS: These data suggest that a number of modifiable behavioral factors (physical activity, smoking, and obesity) and cardiovascular risk factors (diabetes, HDL cholesterol, and blood pressure) are associated with maintenance of good health in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cohort Studies; Diet; Exercise; Female; Health Status; Humans; Incidence; Life Style; Longitudinal Studies; Lung Diseases, Obstructive; Male; Neoplasms; Probability; Reference Values; Risk Factors; Sex Distribution; Socioeconomic Factors; Survival Rate; United States

Frailty in older adults: evidence for a phenotype. - Fried, L P; Tangen, C M; Walston, J; Newman, A B; Hirsch, C; Gottdiener, J; Seeman, T; Tracy, R; Kop, W J; Burke, G; McBurnie, M A (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frailty is considered highly prevalent in old age and to confer high risk for falls, disability, hospitalization, and mortality. Frailty has been considered synonymous with disability, comorbidity, and other characteristics, but it is recognized that it may have a biologic basis and be a distinct clinical syndrome. A standardized definition has not yet been established. METHODS: To develop and operationalize a phenotype of frailty in older adults and assess concurrent and predictive validity, the study used data from the Cardiovascular Health Study. Participants were 5,317 men and women 65 years and older (4,735 from an original cohort recruited in 1989-90 and 582 from an African American cohort recruited in 1992-93). Both cohorts received almost identical baseline evaluations and 7 and 4 years of follow-up, respectively, with annual examinations and surveillance for outcomes including incident disease, hospitalization, falls, disability, and mortality. RESULTS: Frailty was defined as a clinical syndrome in which three or more of the following criteria were present: unintentional weight loss (10 lbs in past year), self-reported exhaustion, weakness (grip strength), slow walking speed, and low physical activity. The overall prevalence of frailty in this community-dwelling population was 6.9%; it increased with age and was greater in women than men. Four-year incidence was 7.2%. Frailty was associated with being African American, having lower education and income, poorer health, and having higher rates of comorbid chronic diseases and disability. There was overlap, but not concordance, in the cooccurrence of frailty, comorbidity, and disability. This frailty phenotype was independently predictive (over 3 years) of incident falls, worsening mobility or ADL disability, hospitalization, and death, with hazard ratios ranging from 1.82 to 4.46, unadjusted, and 1.29-2.24, adjusted for a number of health, disease, and social characteristics predictive of 5-year mortality. Intermediate frailty status, as indicated by the presence of one or two criteria, showed intermediate risk of these outcomes as well as increased risk of becoming frail over 3-4 years of follow-up (odds ratios for incident frailty = 4.51 unadjusted and 2.63 adjusted for covariates, compared to those with no frailty criteria at baseline). CONCLUSIONS: This study provides a potential standardized definition for frailty in community-dwelling older adults and offers concurrent and predictive validity for the definition. It also finds that there is an intermediate stage identifying those at high risk of frailty. Finally, it provides evidence that frailty is not synonymous with either comorbidity or disability, but comorbidity is an etiologic risk factor for, and disability is an outcome of, frailty. This provides a potential basis for clinical assessment for those who are frail or at risk, and for future research to develop interventions for frailty based on a standardized ascertainment of frailty.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Fatigue; Female; Frail Elderly; Humans; Incidence; Male; Muscle Weakness; Phenotype; Prevalence; Sex Distribution; United States; Weight Loss

Gait variability in community-dwelling older adults. - Brach, J S; Berthold, R; Craik, R; VanSwearingen, J M; Newman, A B (J Am Geriatr Soc, 2001)
OBJECTIVES: To describe gait variability at usual and fast walking speeds in community-dwelling older adults and to describe the effects of increasing gait speed on gait variability. DESIGN: Cross-sectional, descriptive study. SETTING: The Cardiovascular Health Study at the University of Pittsburgh. PARTICIPANTS: Ninety-five community-living older adults, 54 women and 41 men, age 65 and older (mean age +/- standard deviation 79.4 +/- 3.37). MEASUREMENTS: Gait measured at participant's usual and fast walking speed collected using an instrumented walkway. Step-length and step-width variability were determined using the coefficient of variation. RESULTS: Step-length variability was greatest in those who walked the slowest (r = -0.66, P < .001); step-width variability was smallest in those who walked the slowest (r -0.37, P < .001). Individuals who could not increase their walking speed (<0.10 m/second) on command had an increase in step-length variability and a decrease in step-width variability, whereas those who could increase their speed (>0.10 m/second) had an increase in step-width variability when walking at a faster speed. CONCLUSIONS: Step-length and step-width variability have opposite associations with gait speed in older adults. Improvement in step-length and step-width variability with attempted acceleration might be a key factor to examine in future studies of disability risk and therapeutic interventions.
Keywords: Aged; Aged, 80 and over; Aging; Body Height; Body Weight; Cross-Sectional Studies; Disability Evaluation; Female; Gait; Humans; Male; Residence Characteristics; Risk Factors; Time Factors; Walking

Hormone replacement therapy is associated with higher FEV1 in elderly women. - Carlson, C L; Cushman, M; Enright, P L; Cauley, J A; Newman, A B (Am J Respir Crit Care Med, 2001)
Estrogen and progesterone use have been associated with improved pulmonary function in premenopausal women. However, little research has examined the relationship between hormone replacement therapy (HRT) and pulmonary function in postmenopausal women. We examined the relationship of HRT with spirometry in 2,353 women aged 65 yr and older participating in the Cardiovascular Health Study in 1993/1994. Current use of HRT was hypothesized to be associated with higher FEV1, higher FVC, and less pulmonary obstruction (FEV1/FVC < 65%). FEV1 was higher among current HRT users compared to noncurrent users in the following groups: overall (1.82 L versus 1.66 L, p < 0.0001), among women without asthma (1.85 L versus 1.69 L, p < 0.0001), among former smokers (1.76 L versus 1.60 L, p = 0.013), and among never smokers (1.90 L versus 1.72 L, p < 0.0001). Overall, HRT use was associated with a lower prevalence of pulmonary obstruction (OR 0.75 [95% CI 0.55, 0.99]). After controlling for potential confounders, HRT use was significantly associated with higher FEV(1) (p = 0.031) and with a lower prevalence of obstruction (OR 0.67 [95% CI 0.48, 0.95]). We conclude that postmenopausal women who use HRT have higher levels of FEV1 and less obstruction, which could not be explained by their lower rates of smoking and other health factors associated with HRT use.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Estrogen Replacement Therapy; Female; Forced Expiratory Volume; Humans; Longitudinal Studies; Spirometry; Vital Capacity

Relation of sleep-disordered breathing to cardiovascular disease risk factors: the Sleep Heart Health Study. - Newman, A B; Nieto, F J; Guidry, U; Lind, B K; Redline, S; Pickering, T G; Quan, S F (Am J Epidemiol, 2001)
Associations between sleep-disordered breathing and cardiovascular disease (CVD) may be mediated by higher cardiovascular risk factor levels in those with sleep-disordered breathing. The authors examined these relations in the Sleep Heart Health Study, a multiethnic cohort of 6,440 men and women over age 40 years conducted from October 1995 to February 1998 and characterized by home polysomnography. In 4,991 participants who were free of self-reported CVD at the time of the sleep study, moderate levels of sleep-disordered breathing were common, with a median Respiratory Disturbance Index (RDI) of 4.0 (interquartile range, 1.25-10.7). The level of RDI was associated cross-sectionally with age, body mass index, waist-to-hip ratio, hypertension, diabetes, and lipid levels. These relations were more pronounced in those under age 65 years than in those over age 65. Women under age 65 years with RDI in the higher quartiles were more obese than men with similar RDI. Although the pattern of associations was consistent with greater obesity in those with higher RDI, higher body mass index did not explain all of these associations. If sleep-disordered breathing is shown in future follow-up to increase the risk for incident CVD events, part of the risk is likely to be due to the higher cardiovascular risk factors in those with higher RDI.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Cross-Sectional Studies; Female; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea Syndromes; United States

The role of comorbidity in the assessment of intermittent claudication in older adults. - Newman, A B; Naydeck, B L; Sutton-Tyrrell, K; Polak, J F; Kuller, L H (J Clin Epidemiol, 2001)
The prevalence of intermittent claudication (IC) in older adults by questionnaire is less than 5% while the prevalence of peripheral arterial disease (PAD) by non-invasive testing is 2-4-fold higher. Comorbid conditions may result in under-reporting intermittent claudication (IC) as assessed by the Rose Questionnaire. We examined characteristics of those who report leg pain in relationship to other comorbid conditions and disability in 5888 participants of the Cardiovascular Health Study (CHS). Older adults with exertional leg pain, not meeting criteria for IC, had a higher prevalence of PAD on non-invasive testing with the ankle-arm index than those without pain, as well as a higher prevalence of arthritis. The pattern of responses suggested that pain for both conditions was reported together. The Rose Questionnaire for IC is specific for PAD, but a negative questionnaire does not indicate a lack of symptoms, rather the presence of PAD along with other conditions that can cause pain.
Keywords: Aged; Angina Pectoris; Arterial Occlusive Diseases; Cerebrovascular Disorders; Cohort Studies; Comorbidity; Diabetes Mellitus; Female; Humans; Intermittent Claudication; Leg; Male; Prevalence; Sensitivity and Specificity; Surveys and Questionnaires

Sleep-disordered breathing and cardiovascular disease: cross-sectional results of the Sleep Heart Health Study. - Shahar, E; Whitney, C W; Redline, S; Lee, E T; Newman, A B; Nieto, F J; O'Connor, G T; Boland, L L; Schwartz, J E; Samet, J M (Am J Respir Crit Care Med, 2001)
Disordered breathing during sleep is associated with acute, unfavorable effects on cardiovascular physiology, but few studies have examined its postulated association with cardiovascular disease (CVD). We examined the cross-sectional association between sleep- disordered breathing and self-reported CVD in 6,424 free-living individuals who underwent overnight, unattended polysomnography at home. Sleep-disordered breathing was quantified by the apnea-hypopnea index (AHI)-the average number of apneas and hypopneas per hour of sleep. Mild to moderate disordered breathing during sleep was highly prevalent in the sample (median AHI: 4.4; interquartile range: 1.3 to 11.0). A total of 1,023 participants (16%) reported at least one manifestation of CVD (myocardial infarction, angina, coronary revascularization procedure, heart failure, or stroke). The multivariable-adjusted relative odds (95% CI) of prevalent CVD for the second, third, and fourth quartiles of the AHI (versus the first) were 0.98 (0.77-1.24), 1.28 (1.02-1.61), and 1.42 (1.13-1.78), respectively. Sleep-disordered breathing was associated more strongly with self-reported heart failure and stroke than with self-reported coronary heart disease: the relative odds (95% CI) of heart failure, stroke, and coronary heart disease (upper versus lower AHI quartile) were 2.38 (1.22-4.62), 1.58 (1.02- 2.46), and 1.27 (0.99-1.62), respectively. These findings are compatible with modest to moderate effects of sleep-disordered breathing on heterogeneous manifestations of CVD within a range of AHI values that are considered normal or only mildly elevated.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Sleep Apnea Syndromes

Usefulness of T-axis deviation as an independent risk indicator for incident cardiac events in older men and women free from coronary heart disease (the Cardiovascular Health Study). - Rautaharju, P M; Nelson, J C; Kronmal, R A; Zhang, Z M; Robbins, J; Gottdiener, J S; Furberg, C D; Manolio, T; Fried, L (Am J Cardiol, 2001)
T-axis shift has been reported to be an indicator of increased mortality risk. We evaluated the association of spatial T-axis deviation with incident coronary heart disease (CHD) events in older men and women free from clinically overt CHD. Spatial T-axis deviation was measured from the standard 12-lead electrocardiogram of a subgroup of 4,173 subjects considered free of CHD at baseline in the Cardiovascular Health Study, a prospective cohort study of risk factors for CHD and stroke in older men and women. Cox regression analysis was used to evaluate the association of altered repolarization with the risk of incident CHD events. The prevalence of marked T-axis deviation (> or =45 degrees ) was 12%. During the median follow-up of 7.4 years, there were 161 CHD deaths, 743 deaths from all causes, and 679 incident CHD events. Adjusting for demographic and clinical risk factors, including other electrocardiographic abnormalities, there was a nearly twofold excess risk of CHD death, and approximately a 50% excess risk of incident CHD and all-cause mortality for those with marked T-axis deviation. From other electrocardiographic abnormalities, only QT prolongation was associated with excess risk for incident CHD comparable to that for abnormal T-axis deviation. These results suggest that T-axis deviation is an easily quantified marker for subclinical disease and an independent indicator for the risk of incident CHD events in older men and women free of CHD.
Keywords: Aged; Algorithms; Cohort Studies; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Survival Analysis

Weight change in old age and its association with mortality. - Newman, A B; Yanez, D; Harris, T; Duxbury, A; Enright, P L; Fried, L P (J Am Geriatr Soc, 2001)
OBJECTIVES: Previous studies of weight change and mortality in older adults have relied on self-reported weight loss, have not evaluated weight gain, or have had limited information on health status. Our objective was to determine whether 5% weight gain or loss in 3 years was predictive of mortality in a large sample of older adults. DESIGN: Longitudinal observational cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Four thousand seven hundred fourteen community-dwelling older adults, age 65 and older. MEASUREMENTS: Weight gain or loss of 5% in a 3-year period was examined in relationship to baseline health status and interim health events. Risk for subsequent mortality was estimated in those with weight loss or weight gain compared with the group whose weight was stable. RESULTS: Weight changes occurred in 34.6% of women and 27.3% of men, with weight loss being more frequent than gain. Weight loss was associated with older age, black race, higher weight, lower waist circumference, current smoking, stroke, any hospitalization, death of a spouse, activities of daily living disability, lower grip strength, and slower gait speed. Weight loss but not weight gain of 5% or more was associated with an increased risk of mortality that persisted after multivariate adjustment (Hazard ratio (HR) = 1.67, 95% CI = 1.29-2.15) and was similar in those with no serious illness in the period of weight change. Those with weight loss and low baseline weight had the highest crude mortality rate, although the HR for weight loss was similar for all tertiles of baseline weight and for those with or without a special diet, compared with those whose weight was stable. CONCLUSIONS: This study confirms that even modest decline in body weight is an important and independent marker of risk of mortality in older adults.
Keywords: Aged; Analysis of Variance; Body Weight; Chi-Square Distribution; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; United States; Weight Gain; Weight Loss

Angiotensin II type 1 receptor polymorphisms in the cardiovascular health study: relation to blood pressure, ethnicity, and cardiovascular events. - Hindorff, Lucia A; Heckbert, Susan R; Tracy, Russell; Tang, Zhonghua; Psaty, Bruce M; Edwards, Karen L; Siscovick, David S; Kronmal, Richard A; Nazar-Stewart, Valle (Am J Hypertens, 2002)
BACKGROUND: The angiotensin II type 1 receptor A1166C polymorphism has been associated with increased risks of hypertension and myocardial infarction in several small studies. We examined the association between this polymorphism and new-onset hypertension, blood pressure (BP) control, and incident cardiovascular events in a large population-based cohort of older adults. METHODS: Eight hundred self-identified African Americans and 1,371 randomly selected white participants in the Cardiovascular Health Study were genotyped. The median duration of follow-up was 8.1 years. RESULTS: The A1166C polymorphism was not associated with new-onset hypertension, with BP control, or with incident cardiovascular events in the overall population. In white participants, the CC genotype was associated with higher baseline systolic BP and pulse pressure, compared to the AC or AA genotype. In whites with treated hypertension at baseline, compared to the AA genotype, the CC genotype was associated with increased risks of incident congestive heart failure (hazard ratio = 2.5, 95% confidence interval [CI] 1.3-4.9) and incident ischemic stroke (hazard ratio = 2.6, 95% CI 1.1-6.0). These associations were not observed among white participants without treated hypertension, but the interaction of genotype with treated hypertension on ischemic stroke and heart failure was only marginally significant. CONCLUSIONS: On the whole, in this large cohort of older adults, the A1166C polymorphism was not associated with BP control or incident cardiovascular events. The subgroup findings in treated hypertensives need to be confirmed in additional studies.
Keywords: African Continental Ancestry Group; Aged; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Gene Frequency; Humans; Hypertension; Male; Polymorphism, Genetic; Receptor, Angiotensin, Type 1; Receptors, Angiotensin; United States

Frailty and activation of the inflammation and coagulation systems with and without clinical comorbidities: results from the Cardiovascular Health Study. - Walston, Jeremy; McBurnie, Mary Ann; Newman, Anne; Tracy, Russell P; Kop, Willem J; Hirsch, Calvin H; Gottdiener, John; Fried, Linda P (Arch Intern Med, 2002)
BACKGROUND: The biological basis of frailty has been difficult to establish owing to the lack of a standard definition, its complexity, and its frequent coexistence with illness. OBJECTIVE: To establish the biological correlates of frailty in the presence and absence of concurrent cardiovascular disease and diabetes mellitus. METHODS: Participants were 4735 community-dwelling adults 65 years and older. Frail, intermediate, and nonfrail subjects were identified by a validated screening tool and exclusion criteria. Bivariate relationships between frailty level and physiological measures were evaluated by Pearson chi2 tests for categorical variables and analysis of variance F tests for continuous variables. Multinomial logistic regression was performed to evaluate multivariable relationships between frailty status and physiological measures. RESULTS: Of 4735 Cardiovascular Health Study participants, 299 (6.3%) were identified as frail, 2147 (45.3%) as intermediate, and 2289 (48.3%) as not frail. Frail vs nonfrail participants had increased mean +/- SD levels of C-reactive protein (5.5 +/- 9.8 vs 2.7 +/- 4.0 mg/L), factor VIII (13 790 +/- 4480 vs 11 860 +/- 3460 mg/dL), and, in a smaller subset, D dimer (647 +/- 1033 vs 224 +/- 258 ng/mL) (P< or =.001 for all, chi2 test for trend). These differences persisted when individuals with cardiovascular disease and diabetes were excluded and after adjustment for age, sex, and race. CONCLUSIONS: These findings support the hypothesis that there is a specific physiological basis to the geriatric syndrome of frailty that is characterized in part by increased inflammation and elevated markers of blood clotting and that these physiological differences persist when those with diabetes and cardiovascular disease are excluded.
Keywords: Aged; Aged, 80 and over; Blood Coagulation Disorders; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Diabetes Mellitus; Female; Frail Elderly; Geriatric Assessment; Humans; Inflammation; Longitudinal Studies; Male

Inflammation and coagulation factors in persons > 65 years of age with symptoms of depression but without evidence of myocardial ischemia. - Kop, Willem J; Gottdiener, John S; Tangen, Catherine M; Fried, Linda P; McBurnie, Mary Ann; Walston, Jeremy; Newman, Anne; Hirsch, Calvin; Tracy, Russell P (Am J Cardiol, 2002)
Depression is associated with increased cardiovascular disease, but the underlying mechanisms are not well understood. This study examines associations of depressive symptoms with inflammation and coagulation factors in persons aged > 65 years. Blood samples were obtained from 4,268 subjects free of cardiovascular disease (age 72.4 +/- 5.5 years, 2,623 women). Inflammation markers were C-reactive protein (CRP), white blood cell (WBC) count, total platelet count, and albumin; coagulation factors included factors VIIc and VIIIc and fibrinogen. Depression was assessed with the Center for Epidemiologic Studies Depression scale, and states of energy depletion with a validated exhaustion index. Statistical adjustments were made for risk factors (age, sex, race, systolic blood pressure, smoking status, diabetes mellitus) and physical measures of frailty (isometric handgrip, timed 15-feet walk test, activity level). Depression was associated with elevated CRP (3.31 +/- 0.10 vs 3.51 +/- 0.21 mg/L), WBC (6.14 +/- 0.03 vs 6.43 +/- 0.11 10(6)/L), fibrinogen (319 +/- 1 vs 326 +/- 3 mg/dl), and factor VIIc (124.6 +/- 0.6% vs 127.2 +/- 1.3%; all p <0.05). Exhaustion also was related to elevated inflammation and coagulation markers (p < 0.05). Exhausted men had markedly elevated CRP levels (6.82 +/- 2.10 mg/L) versus nonexhausted men (3.05 +/- 0.16: p = 0.007). After adjustment for control variables, exhaustion remained associated with albumin (p = 0.033), fibrinogen (p = 0.017), CRP (p = 0.066), and WBC (p = 0.060), whereas associations of depressive symptoms with biochemistry measures lost statistical significance. Thus, depression and exhaustion are associated with low-grade inflammation and elevated coagulation factors in persons aged > 65 years.
Keywords: Aged; Blood Chemical Analysis; Blood Coagulation Factors; Cardiovascular Diseases; Depression; Female; Humans; Inflammation; Male; Risk Factors

Measures of cognitive function in persons with varying degrees of sleep-disordered breathing: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Iber, Conrad; Knopman, David S; Kuo, Tracy F; Nieto, F Javier (J Sleep Res, 2002)
Epidemiologic literature suggests that persons with clinically diagnosed sleep apnoea frequently have impaired cognitive function, but whether milder degrees of sleep-disordered breathing (SDB) are associated with cognitive dysfunction in the general population is largely unknown. Approximately 1700 subjects free of clinically diagnosed SDB underwent at-home polysomnography (PSG) as part of the Sleep Heart Health Study (SHHS) and completed three cognitive function tests within 1-2 years of their PSG: the Delayed Word Recall Test (DWR), the WAIS-R Digit Symbol Subtest (DSS), and the Word Fluency test (WF). A respiratory disturbance index (RDI) was calculated as the number of apnoeas and hypopnoeas per hour of sleep. After adjustment for age, education, occupation, field centre, diabetes, hypertension, body-mass index, use of CNS medications, and alcohol drinking status, there was no consistent association between the RDI and any of the three cognitive function measures. There was no evidence of a dose-response relation between the RDI and cognitive function scores and the adjusted mean scores by quartiles of RDI never differed from one another by more than 5% for any of the tests. In this sample of free-living individuals with mostly mild to moderate levels of SDB, the degree of SDB appeared to be unrelated to three measures of cognitive performance.
Keywords: Aged; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Hypoxia; Male; Middle Aged; Neuropsychological Tests; Oxygen; Polysomnography; Severity of Illness Index; Sleep Apnea, Central

Predictors of sleep-disordered breathing in community-dwelling adults: the Sleep Heart Health Study. - Young, Terry; Shahar, Eyal; Nieto, F Javier; Redline, Susan; Newman, Anne B; Gottlieb, Daniel J; Walsleben, Joyce A; Finn, Laurel; Enright, Paul; Samet, Jonathan M (Arch Intern Med, 2002)
BACKGROUND: Sleep-disordered breathing (SDB) is common, but largely undiagnosed in the general population. Information on demographic patterns of SDB occurrence and its predictive factors in the general population is needed to target high-risk groups that may benefit from diagnosis. METHODS: The sample comprised 5615 community-dwelling men and women aged between 40 and 98 years who were enrolled in the Sleep Heart Health Study. Data were collected by questionnaire, clinical examinations, and in-home polysomnography. Sleep-disordered breathing status was based on the average number of apnea and hypopnea episodes per hour of sleep (apnea-hypopnea index [AHI]). We used multiple logistic regression modeling to estimate cross-sectional associations of selected participant characteristics with SDB defined by an AHI of 15 or greater. RESULTS: Male sex, age, body mass index, neck girth, snoring, and repeated breathing pause frequency were independent, significant correlates of an AHI of 15 or greater. People reporting habitual snoring, loud snoring, and frequent breathing pauses were 3 to 4 times more likely to have an AHI of 15 or greater vs an AHI less than 15, but there were weaker associations for other factors with an AHI of 15 or greater. The odds ratios (95% confidence interval) for an AHI of 15 or greater vs an AHI less than 15 were 1.6 and 1.5, respectively, for 1-SD increments in body mass index and neck girth. As age increased, the magnitude of associations for SDB and body habitus, snoring, and breathing pauses decreased. CONCLUSIONS: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; Female; Humans; Male; Middle Aged; Obesity; Predictive Value of Tests; Residence Characteristics; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Snoring

Racial differences in coronary artery calcification in older adults. - Newman, Anne B; Naydeck, Barbara L; Whittle, Jeff; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
Reports on race-related differences in coronary artery calcium (CAC) are just beginning to emerge and have not been well studied in the elderly. This study was undertaken to assess whether such differences exist and the relationship between CAC and cardiovascular risk factors in a cohort of elderly community-dwelling adults. CAC was measured by using electron-beam tomography in 614 adults (aged 67 to 99 years), of whom 59% were women and 23% were black. The median CAC score was lower in blacks than in whites for men (159 versus 787, respectively; P<0.001) and for women (134 versus 233, respectively; P=0.02) after adjustment for age, cardiovascular disease, and risk factors for cardiovascular disease, although this difference was stronger and remained significant among men only. Lower CAC scores were also observed in the subgroup of blacks with a history of myocardial infarction. The lower CAC scores in blacks compared with whites observed in this study is consistent with either a lower prevalence of coronary artery disease or a lower extent of calcification of coronary artery disease.
Keywords: Age Factors; Aged; Calcinosis; Cohort Studies; Coronary Artery Disease; Female; Humans; Logistic Models; Male; Risk Factors; Sex Factors; Tomography, X-Ray Computed

The relationship between chronically disrupted sleep and healthcare use. - Kapur, Vishesh K; Redline, Susan; Nieto, F Javier; Young, Terry B; Newman, Anne B; Henderson, Jeffrey A (Sleep, 2002)
STUDY OBJECTIVES: To determine whether chronic sleep deprivation, sleep disruption, sleepiness, insomnia, and OSA are associated with increased healthcare use in a community-based population. DESIGN: Cross-sectional study. SETTING/PARTICIPANTS: 6440 Sleep Heart Health Study (SHHS) participants recruited from ongoing cohort studies. INTERVENTIONS: N/A. MEASUREMENTS: Polysomnography results (Apnea Hypopnea Index (AHI), percent of sleep time with oxyhemoglobin saturation below 90% (CT90), arousal index) as well as data on sleep related symptoms, medication use, and chronic illness. The indirect measure of predicted healthcare utilization was the modified Chronic Disease Score (CDS) calculated from medication data. RESULTS: After adjustment for age, gender, BMI and study site, subjects in the highest quartiles of AHI, CT90 and Epworth score had CDS that were 6%-9% higher than the lowest quartiles. The adjusted mean CDS for subjects with sleep apnea was similar to that for subjects with hypertension, chronic bronchitis or asthma and 18% greater than the mean CDS for subjects without sleep apnea. Among subjects who did not have significant sleep-disordered breathing, complaints of insomnia, sleepiness, fatigue, and not getting enough sleep were associated with increased CDS. CONCLUSIONS: This study demonstrated an association between subjective complaints of daytime sleepiness, inadequate sleep time, insomnia as well as objective measures of severity of SDB, and an indirect measure of healthcare utilization in a community-based sample. Though the percent increases in healthcare utilization observed were modest, the prevalence of these factors in the general population is high, and may therefore be associated with a substantial cost burden to the healthcare system.
Keywords: Adult; Chronic Disease; Cohort Studies; Community Health Services; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Patient Acceptance of Health Care; Polysomnography; Prevalence; Severity of Illness Index; Sleep Apnea, Obstructive; Sleep Deprivation

Relationship between coronary artery calcification and other measures of subclinical cardiovascular disease in older adults. - Newman, Anne B; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; O'Leary, Daniel; Kronmal, Richard; Burke, Gregory L; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
BACKGROUND: In the Cardiovascular Health Study, subclinical cardiovascular disease (CVD) predicted CVD events in older adults. The extent to which this measure or its components reflect calcified coronary disease is unknown. METHODS AND RESULTS: Coronary artery calcium (CAC) was assessed with electron beam tomography in 414 participants without clinical CVD and examined using cut points (CAC> or =400 and CAC> or =800) and the log(CAC); 274 had subclinical CVD by ankle-arm index, ECG, or carotid ultrasound. Cut points for subclinical disease as previously defined in the Cardiovascular Health Study were examined as well as continuous measures to produce receiver operating characteristic curve curves. A low ankle-arm index was highly specific for a high CAC score. The internal carotid artery intima-media thickness was most strongly correlated with CAC (r=0.30) and was significantly related to both CAC cut points and to the log(CAC) score independently of all other measures. CONCLUSIONS: In these community-dwelling older adults without clinical CVD, internal carotid artery intima-media thickness was most closely related to CAC. However, 17.5% of those with a CAC> or =400 would be missed in the ascertainment of subclinical atherosclerosis using the previously published composite of subclinical atherosclerosis. Prospective follow-up will determine whether the CAC score improves prediction of CVD events over other noninvasive measures.
Keywords: Aged; Aged, 80 and over; Calcinosis; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Coronary Artery Disease; Demography; Female; Humans; Male; Prevalence; Risk Factors; Sensitivity and Specificity; Sex Factors; Tomography, X-Ray Computed; Tunica Intima; Tunica Media

Short-term variability of respiration and sleep during unattended nonlaboratory polysomnography--the Sleep Heart Health Study. [corrected]. - Quan, Stuart F; Griswold, Michael E; Iber, Conrad; Nieto, F Javier; Rapoport, David M; Redline, Susan; Sanders, Mark; Young, Terry (Sleep, 2002)
STUDY OBJECTIVES: To determine the short-term variability of indices of disturbed respiration and sleep during 2 nights of unattended nonlaboratory polysomnography conducted several months apart. DESIGN: Participants were randomly selected using a block design with stratification on preliminary estimates of 2 criteria: respiratory disturbance index [RDI3% (apnea or hypopnea events associated with > or = 3% O2 desaturation): < 15/hour total sleep time, > or = 15/hour total sleep time] and sleep efficiency (SEff: < 85% and > or = 85%). The RDI and sleep data from initial and repeated polysomnography were compared. SETTING: NA. PARTICIPANTS: A subset of 99 participants in the Sleep Heart Health Study who agreed to have a repeat polysomnogram within 4 months of their original study. INTERVENTIONS: NA. MEASUREMENTS AND RESULTS: Acceptable repeat polysomnograms were obtained in 91 subjects (mean study interval: 77 +/- 18 [sd] days; range: 31-112 days). There was no significant bias in RDI between study nights using several different RDI definitions including RDI3% and RDI4% (apnea or hypopnea events associated with > or = 4% O2 desaturation). Variability between studies estimated using intraclass correlations (ICC) ranged from 0.77 to 0.81. For subjects with a RDI3% < 15, variability increased as a function of increasing RDI, but for those with a RDI3% > or = 15, variability was constant. Body mass index, SEff, gender, or age did not directly predict RDI variability. Using RDI4% cutpoints of < or = 5, < or = 10 and < or = 15 events per hour of sleep demonstrated that 79.1%, 85.7%, and 87.9% of subjects, respectively, had the same classification of SDB status on both nights of study. There also was no significant bias in sleep staging, sleep efficiency, or arousal index between studies. However, variability was greater with ICC values ranging from 0.37 (% time in REM) to 0.76 (arousal index). CONCLUSION: In the Sleep Heart Health Study, accurate estimates of the severity of sleep-disordered breathing and the quality of sleep were obtained from a single night of unattended nonlaboratory polysomnography. These findings may be applicable to other large epidemiologic studies provided that similar recording techniques and quality-assurance procedures are followed.
Keywords: Adult; Aged; Aged, 80 and over; Apnea; Arousal; Body Mass Index; Circadian Rhythm; Electrocardiography; Electromyography; Electrooculography; Female; Humans; Male; Middle Aged; Oxygen Consumption; Polysomnography; Respiration; Sleep Apnea Syndromes; Sleep Stages; Time Factors

Therapy with hydroxymethylglutaryl coenzyme a reductase inhibitors (statins) and associated risk of incident cardiovascular events in older adults: evidence from the Cardiovascular Health Study. - Lemaitre, Rozenn N; Psaty, Bruce M; Heckbert, Susan R; Kronmal, Richard A; Newman, Anne B; Burke, Gregory L (Arch Intern Med, 2002)
BACKGROUND: Recommendations to treat older adults with hydroxymethylglutaryl coenzyme A reductase inhibitors (statins) for the primary prevention of coronary heart disease events are supported by a single clinical trial restricted to adults 73 years or younger with low levels of high-density lipoprotein cholesterol. METHODS: We investigated the association of statin use with incident cardiovascular disease and all-cause mortality during up to 7.3 years' follow-up of 1250 women and 664 men from the Cardiovascular Health Study. Study participants were 65 years and older and free of cardiovascular disease at baseline. They received drug therapy to lower cholesterol levels at baseline or no treatment with a recommendation for therapy according to the National Cholesterol Education Program guidelines. Use of these drugs was assessed annually. We used proportional-hazards models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusted for confounding variables. RESULTS: We found 382 incident cardiovascular events (159 myocardial infarctions, 159 strokes, and 64 deaths due to coronary heart disease) and 362 total deaths from June 1, 1989, to May 31, 1997. Compared with no use of drugs to lower cholesterol levels, statin use was associated with decreased risk of cardiovascular events (multivariate HR, 0.44; 95% CI, 0.27-0.71) and all-cause mortality (HR, 0.56; 95% CI, 0.36-0.88). Similar associations were observed among participants 74 years or older at baseline. CONCLUSIONS: Use of statins was associated with decreased risk of incident cardiovascular events among elderly adults. These findings lend support to the National Cholesterol Education Program guidelines, which recommend therapy for the lowering of cholesterol levels for older adults with hypercholesterolemia.
Keywords: Aged; Cholesterol, LDL; Coronary Disease; Female; Follow-Up Studies; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypercholesterolemia; Hypolipidemic Agents; Incidence; Male; Multivariate Analysis; Proportional Hazards Models; Risk Factors; United States

Underdiagnosis of sleep apnea syndrome in U.S. communities. - Kapur, Vishesh; Strohl, Kingman P; Redline, Susan; Iber, Conrad; O'Connor, George; Nieto, Javier (Sleep Breath, 2002)
We hypothesize that clinical recognition rates for obstructive sleep apnea-hypoapnea syndrome (OSAHS) are influenced by comorbidity and demographic factors. Data on medical disorders, symptoms of sleep disorders, and cardiovascular risk factors gathered from 15,699 individuals in the Sleep Heart Health Study were compared. Participants were classified into three groups: those with a self-reported physician diagnosis of OSAHS, those with self-reported physician-diagnosed and -treated OSAHS, and those reporting both frequent snoring and daytime sleepiness (two-symptom group). Among all participants, 4.1% reported two symptoms (range across sites: 1.55 to 7.23%), whereas 1.6% reported a physician diagnosis of OSAHS (range: 0.66 to 2.88%) and 0.6% reported physician diagnosis and treatment (range: 0.11 to 0.88%). Recognized OSAHS groups were similar to the two-symptom group in age, having a sleeping partner, measured blood pressure, total cholesterol, and race. In a logistic model that included age along with characteristics found to vary significantly among the three groups (gender, body mass index [BMI], high-density lipoprotein cholesterol levels, hypertension), only male gender and BMI were increased in those with physician-diagnosed and -treated OSAHS. We conclude that disparities (especially in women and in those with lower BMI) exist between current recognition rates for OSAHS and the estimated prevalence by symptom report across the United States.
Keywords: Diagnosis, Differential; Diagnostic Errors; Female; Humans; Male; Middle Aged; Prevalence; Sleep Apnea Syndromes; United States

Weight-modification trials in older adults: what should the outcome measure be? - Diehr, Paula; Newman, Anne B; Jackson, Sharon A; Kuller, Lewis; Powe, Neil (Curr Control Trials Cardiovasc Med, 2002)
BACKGROUND: Overweight older adults are often counseled to lose weight, even though there is little evidence of excess mortality in that age group. Overweight and underweight may be more associated with health status than with mortality, but few clinical trials of any kind have been based on maximizing years of healthy life (YHL), as opposed to years of life (YOL). OBJECTIVE: This paper examines the relationship of body mass index (BMI) to both YHL and YOL. Results were used to determine whether clinical trials of weight-modification based on improving YHL would be more powerful than studies based on survival. DESIGN: We used data from a cohort of 4,878 non-smoking men and women aged 65-100 at baseline (mean age 73) and followed 7 years. We estimated mean YHL and YOL in four categories of BMI: underweight, normal, overweight, and obese. RESULTS: Subjects averaged 6.3 YOL and 4.6 YHL of a possible 7 years. Both measures were higher for women and whites. For men, none of the BMI groups was significantly different from the normal group on either YOL or YHL. For women, the obese had significantly lower YHL (but not YOL) than the normals, and the underweight had significantly lower YOL and YHL. The overweight group was not significantly different from the normal group on either measure. CONCLUSIONS: Clinical trials of weight loss interventions for obese older women would require fewer participants if YHL rather than YOL was the outcome measure. Interventions for obese men or for the merely overweight are not likely to achieve differences in either YOL or YHL. Evaluations of interventions for the underweight (which would presumably address the causes of their low weight) may be conducted efficiently using either outcome measure.

The 6-min walk test: a quick measure of functional status in elderly adults. - Enright, Paul L; McBurnie, Mary Ann; Bittner, Vera; Tracy, Russell P; McNamara, Robert; Arnold, Alice; Newman, Anne B (Chest, 2003)
OBJECTIVES: To determine the correlates of the total 6-min walk distance (6MWD) in a population sample of adults > or = 68 years old. METHODS: The standardized 6-min walk test (6MWT) was administered to the Cardiovascular Health Study cohort during their seventh annual examination. RESULTS: Of the 3,333 participants with a clinic visit, 2,281 subjects (68%) performed the 6MWT. There were no untoward events. The mean 6MWD was 344 m (SD, 88 m). Independent general correlates of a shorter 6MWD in linear regression models in women and men included the following: older age, higher weight, larger waist, weaker grip strength, symptoms of depression, and decreased mental status. Independent disease or risk factor correlates of a shorter 6MWD included the following: a low ankle BP, use of angiotensin-converting enzyme inhibitors, and arthritis in men and women; higher C-reactive protein, diastolic hypertension, and lower FEV(1) in women; and the use of digitalis in men. Approximately 30% of the variance in 6MWD was explained by the linear regression models. Newly described bivariate associations of a shorter 6MWD included impaired activities of daily living; self-reported poor health; less education; nonwhite race; a history of coronary heart disease, transient ischemic attacks, stroke, or diabetes; and higher levels of C-reactive protein, fibrinogen, or WBC count. CONCLUSIONS: Most community-dwelling elderly persons can quickly and safely perform this functional status test in the outpatient clinic setting. The test may be used clinically to measure the impact of multiple comorbidities, including cardiovascular disease, lung disease, arthritis, diabetes, and cognitive dysfunction and depression, on exercise capacity and endurance in older adults. Expected values should be adjusted for the patient's age, gender, height, and weight.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Exercise Test; Female; Humans; Ischemic Attack, Transient; Linear Models; Male; Mass Screening; Sensitivity and Specificity; Stroke; United States; Walking

The association between the length of the QT interval and mortality in the Cardiovascular Health Study. - Robbins, John; Nelson, Jennifer Clark; Rautaharju, Pentti M; Gottdiener, John S (Am J Med, 2003)
PURPOSE: A long QT interval is a risk factor for arrhythmic events and sudden death. Whether moderate QT prolongation is associated with clinical events in community-dwelling elderly patients is uncertain. METHODS: We measured the QT interval in a population-based sample of 5888 men and women at least 65 years of age who were participants in the Cardiovascular Health Study. The association between Bazett's rate-corrected QT (QTc, in ms) and mortality during the subsequent 10 years was evaluated. We stratified participants by the presence or absence of coronary heart disease status at baseline, and adjusted for coronary heart disease risk factors. RESULTS: The rates of all-cause and coronary heart disease mortality were greater in participants with longer QTc intervals. Among participants without known coronary heart disease, those whose QTc interval was >450 ms were at increased risk of all-cause mortality (relative risk [RR] = 1.34; 95% confidence interval [CI]: 1.07 to 1.67) and coronary heart disease mortality (RR = 1.6; 95% CI: 1.0 to 2.5) when compared with participants whose QTc interval was <410 ms. The associations were stronger among those with known coronary heart disease (RR for all-cause mortality = 2.3; 95% CI: 1.6 to 3.3; and RR for coronary heart disease mortality = 2.0; 95% CI: 1.1 to 3.7). CONCLUSIONS: The QT interval from the standard electrocardiograms is of value for identification of elderly persons at increased risk of coronary heart disease and total mortality. A QTc interval >450 ms should prompt clinical evaluation and possible interventions to reduce the risk of coronary events.
Keywords: Aged; Arrhythmias, Cardiac; Cause of Death; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Male; Randomized Controlled Trials as Topic; Risk Factors; Statistics as Topic; Survival Analysis; United States

Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Hormone replacement therapy and sleep-disordered breathing. - Shahar, Eyal; Redline, Susan; Young, Terry; Boland, Lori L; Baldwin, Carol M; Nieto, F Javier; O'Connor, George T; Rapoport, David M; Robbins, John A (Am J Respir Crit Care Med, 2003)
Disordered breathing during sleep is more common among postmenopausal women than among their premenopausal counterparts, possibly because of declining levels of estrogen and progesterone. We examined the relationship between the use of replacement hormones and sleep-disordered breathing in a sample of 2,852 noninstitutionalized women, 50 years of age or older, who participated in the Sleep Heart Health Study. The frequency of apneas and hypopneas per hour of sleep (apnea-hypopnea index) was determined by unattended, single-night polysomnography at the participant's home. The prevalence of sleep-disordered breathing (apnea-hypopnea index of 15 or more) among hormone users (61 of 907) was approximately half the prevalence among nonusers (286 of 1,945). Multivariable adjustment for known determinants of the disorder, including age, body mass index, and neck circumference, has attenuated the association, but only moderately (adjusted odds ratio, 0.55; 95% confidence interval, 0.41 to 0.75). The inverse association between hormone use and sleep-disordered breathing was evident in various subgroups and was particularly strong among women 50 to 59 years old (adjusted odds ratio, 0.36; 95% confidence interval, 0.21 to 0.60). If the observed associations are causal, hormone replacement therapy could have a role in preventing or alleviating sleep-disordered breathing.
Keywords: Age Distribution; Aged; Body Mass Index; Causality; Cohort Studies; Confidence Intervals; Estrogen Replacement Therapy; Female; Humans; Logistic Models; Middle Aged; Multivariate Analysis; Odds Ratio; Polysomnography; Postmenopause; Prevalence; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Stages; United States

Perceptions and implications of received spousal care: evidence from the Caregiver Health Effects Study. - Martire, Lynn M; Schulz, Richard; Wrosch, Carsten; Newsom, Jason T (Psychol Aging, 2003)
The experiences of older care recipients have received far less theoretical and empirical attention than those of their family caregivers. In this study of 91 care recipients, the authors assessed perceptions of the amount, timing, and manner of spousal assistance; the amount of strain experienced from receiving care; and psychological well-being. Although female care recipients were more likely to report dissatisfaction with the manner in which assistance was provided, there were few gender differences in perceptions of care overall. In a stringent test of the hypothesis that perceived quality of spousal care affects recipient well-being, the authors found that poorer quality of care was related to increased depressive symptoms and a decreased sense of mastery 1 year later. These longitudinal effects were independent of the recipient's physical disability, marital quality, and care-receiving strain as well as the caregiver's well-being. These findings argue for a comprehensive assessment of the care-receiving experience that includes both care-recipient and caregiver perspectives.
Keywords: Aged; Caregivers; Chronic Disease; Disabled Persons; Family Health; Female; Health Status; Humans; Longitudinal Studies; Male; Mental Health; Quality of Health Care; Research Design; Spouses

A prospective analysis of risk factors for white matter disease in the brain stem: the Cardiovascular Health Study. - Ding, Jingzhong; Nieto, F Javier; Beauchamp, Norman J; Longstreth, W T; Manolio, Teri A; Hetmanski, Jacqueline B; Fried, Linda P (Neuroepidemiology, 2003)
BACKGROUND AND PURPOSE: White matter disease (WMD) in the brain stem may be a predictor of poor clinical outcome, independent of WMD in the periventricular and subcortical areas of the brain. Many cardiovascular risk factors such as older age, hypertension, and smoking have been suggested as risk factors for WMD in the periventricular and subcortical areas of the brain. However, no epidemiologic study has examined the associations between cardiovascular risk factors and WMD in the brain stem. METHODS: A total of 789 participants, aged 65 years or older, from the Cardiovascular Health Study constituted the present study population. WMD, defined as hyperintensive lesions on magnetic resonance imaging (MRI), in the brain stem was measured in 1992/1993 and 1997/1998. RESULTS: Of the 789 participants, 212 (26.9%) had WMD in the brain stem in 1997/1998. In multivariate logistic regression analysis, the presence of WMD in the brain stem in 1997/1998 was significantly associated with several variables measured in 1992/1993: an increase by 5 years of age (OR = 1.51, 95% CI: 1.25-1.83), a 10-pack-years increase in smoking (OR = 1.12, 95% CI: 1.04-1.21), a 0.1-liter increase in first-second forced expiratory volume (OR = 0.95, 95% CI: 0.92-0.99), a 1 micromol/l increase in fibrinogen level (OR = 1.13, 95% CI: 1.03-1.23), and MRI infarction (OR = 2.58, 95% CI: 1.78-3.74). Excluding those (n = 167) with WMD in the brain stem in 1992/1993, the pattern remained. Hypertension was not associated with WMD in the brain stem. CONCLUSIONS: Increased age, smoking, lower forced expiratory volume, increased fibrinogen level, and MRI infarction, but not hypertension, may be independent risk factors for WMD in the brain stem in older adults.
Keywords: Age Factors; Aged; Brain Diseases; Brain Infarction; Brain Stem; Cardiovascular Diseases; Female; Fibrinogen; Forced Expiratory Volume; Humans; Magnetic Resonance Imaging; Male; Prospective Studies; Regression Analysis; Risk Factors; Smoking

Regional and racial differences in the prevalence of physician-diagnosed essential tremor in the United States. - Louis, Elan D; Fried, Linda P; Fitzpatrick, Annette L; Longstreth, William T; Newman, Anne B (Mov Disord, 2003)
For reasons that are unclear, prevalence estimates of essential tremor (ET) differ considerably across the United States. Separate communities have never been sampled within the framework of the same study to substantiate these differences. We estimated the prevalence of physician-diagnosed ET in the elderly in four communities in the United States in whom the same screening questions were used, and examined whether this prevalence differed between Caucasians and African Americans. The Cardiovascular Health Study recruited a sample of Medicare beneficiaries >/=65 years of age from four communities in different regions of the United States. In 1998 to 1999, 3,494 participants (mean age, 80.0 years; range, 70-103 years) answered a 12-question screen for ET, including the question, "has a doctor diagnosed you as having familial tremor or benign essential tremor?" Fifty-four participants reported that a doctor had diagnosed them as having ET (1.5%; 95% confidence interval, [CI], 1.1-2.0%). Prevalence was similar across the four communities (1.1-2.0%). A larger proportion of Caucasians than African Americans reported a diagnosis of ET (1.7% vs. 0.4%; odds ratio = 4.9; 95% CI, 1.2-20.2; P = 0.028). In a logistic regression analysis, physician-diagnosed ET was associated with Caucasian ethnicity (P = 0.038) but not with age, gender, education, mental status or depression scores, income, smoking status, or alcohol consumption. When a standardized screening question was used, the proportion of participants with physician-diagnosed ET was similar across four communities, suggesting that the prevalence of this condition may be less variable than is often reported. Caucasians were five times more likely to have physician-diagnosed ET than were African Americans. This study does not provide an explanation for this difference, which deserves further study.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Essential Tremor; European Continental Ancestry Group; Female; Humans; Male; Physicians; Prevalence; United States

Renal insufficiency as a predictor of cardiovascular outcomes and mortality in elderly individuals. - Fried, Linda F; Shlipak, Michael G; Crump, Casey; Bleyer, Anthony J; Gottdiener, John S; Kronmal, Richard A; Kuller, Lewis H; Newman, Anne B (J Am Coll Cardiol, 2003)
OBJECTIVES: This study was designed to evaluate the relationship between elevated creatinine levels and cardiovascular events. BACKGROUND: End-stage renal disease is associated with high cardiovascular morbidity and mortality. The association of mild to moderate renal insufficiency with cardiovascular outcomes remains unclear. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of subjects, aged >65 years, who had a serum creatinine measured at baseline (n = 5,808) and were followed for a median of 7.3 years. Proportional hazards models were used to examine the association of creatinine to all-cause mortality and incident cardiovascular mortality and morbidity. Renal insufficiency was defined as a creatinine level > or =1.5 mg/dl in men or > or =1.3 mg/dl in women. RESULTS: An elevated creatinine level was present in 648 (11.2%) participants. Subjects with elevated creatinine had higher overall (76.7 vs. 29.5/1,000 years, p < 0.001) and cardiovascular (35.8 vs. 13.0/1,000 years, p < 0.001) mortality than those with normal creatinine levels. They were more likely to develop cardiovascular disease (54.0 vs. 31.8/1,000 years, p < 0.001), stroke (21.1 vs. 11.9/1,000 years, p < 0.001), congestive heart failure (38.7 vs. 17/1,000 years, p < 0.001), and symptomatic peripheral vascular disease (10.6 vs. 3.5/1,000 years, p < 0.001). After adjusting for cardiovascular risk factors and subclinical disease measures, elevated creatinine remained a significant predictor of all-cause and cardiovascular mortality, total cardiovascular disease (CVD), claudication, and congestive heart failure (CHF). A linear increase in risk was observed with increasing creatinine. CONCLUSIONS: Elevated creatinine levels are common in older adults and are associated with increased risk of mortality, CVD, and CHF. The increased risk is apparent early in renal disease.
Keywords: Aged; Cardiovascular Diseases; Confidence Intervals; Creatinine; Female; Heart Failure; Humans; Intermittent Claudication; Kidney Failure, Chronic; Male; Odds Ratio; Predictive Value of Tests; Survival Analysis

Risk factors for dementia in the cardiovascular health cognition study. - Kuller, Lewis H; Lopez, Oscar L; Newman, Anne; Beauchamp, Norman J; Burke, Greg; Dulberg, Corinne; Fitzpatrick, Annette; Fried, Linda; Haan, Mary N (Neuroepidemiology, 2003)
BACKGROUND: The Cardiovascular Health Cognition Study has evaluated the determinants of dementia among 3,608 participants that had a magnetic resonance imaging (MRI) of the brain in 1991 and were followed to 1998-1999. METHODS: There were 480 incident dementia cases, 330 (69%) were classified as Alzheimer's disease (AD). RESULTS: In univariate analysis, low scores on the Modified Mini-Mental State Examination (3MSE) and on the Digit Symbol Substitution Test as well as declines in scores over time prior to the development of dementia were significant predictors of dementia. A high ventricular grade on the MRI (atrophy) as well as high white matter grade, a number of brain infarcts on the MRI were all determinants of dementia. Apolipoprotein E epsilon4 (Apo(E-4)) was also a powerful predictor of dementia. In a multivariate Cox proportional hazards model controlling for race, gender and grade, the hazard ratios for age (1.1), 3MSE score (0.9), ventricular size (1.4), white matter grade (1.8), presence of large infarcts >3 mm (1.3) and Apo(E-4) (2.1) were significant predictors of dementia. The combination of an Apo(E-4) genotype, 3MSE score <90, > or =5 ventricular grade, > or =3 white matter grade at the time of the MRI were associated with a 17-fold increased risk (95% CI: 8.6-34.9) of dementia as compared to individuals with none of the above attributes. CONCLUSIONS: Measures of cognition, Apo(E-4) and MRI of the brain are strong predictors of both dementia and of AD.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cardiovascular Diseases; Cognition Disorders; Dementia; Female; Genotype; Humans; Magnetic Resonance Imaging; Male; Odds Ratio; Predictive Value of Tests; Proportional Hazards Models; Risk Factors

Sleep and sleep-disordered breathing in adults with predominantly mild obstructive airway disease. - Sanders, Mark H; Newman, Anne B; Haggerty, Catherine L; Redline, Susan; Lebowitz, Michael; Samet, Jonathan; O'Connor, George T; Punjabi, Naresh M; Shahar, Eyal (Am J Respir Crit Care Med, 2003)
Neither the association between obstructive airways disease (OAD) and sleep apnea-hypopnea (SAH) nor the sleep consequences of each disorder alone and together have been characterized in an adult community setting. Our primary aims were (1) to determine if there is an association between OAD and SAH and (2) identify predictors of oxyhemoglobin desaturation during sleep in persons having OAD with and without SAH. Polysomnography and spirometry results from 5,954 participants in the Sleep Heart Health Study were analyzed. OAD was defined by a FEV1/FVC value less than 70%. Assessment of SAH prevalence in OAD was performed using thresholds of respiratory disturbance index (RDI) greater than 10 and greater than 15. A total of 1,132 participants had OAD that was predominantly mild (FEV1/FVC 63.81 +/- 6.56%, mean +/- SD). SAH was not more prevalent in participants with OAD than in those without OAD (22.32 versus 28.86%, with and without OAD, respectively, at RDI threshold values greater than 10; and 13.97 versus 18.63%, with and without OAD, respectively, at RDI threshold value greater than 15). In the absence of SAH, the adjusted odds ratio for sleep desaturation (> 5% total sleep time with saturation < 90%) was greater than 1.9 when FEV1/FVC was less than 65%. Participants with both OAD and SAH had greater sleep perturbation and desaturation than those with one disorder. Generally mild OAD alone was associated with minimally altered sleep quality. We conclude that (1) there is no association between generally mild OAD and SAH; (2) exclusive of SAH and after adjusting for demographic factors and awake oxyhemoglobin saturation, an FEV1/FVC value less than 65% is associated with increased risk of sleep desaturation; (3) desaturation is greater in persons with both OAD and SAH compared with each of these alone; and (4) individuals with generally mild OAD and without SAH in the community have minimally perturbed sleep.
Keywords: Aged; Cohort Studies; Female; Forced Expiratory Volume; Humans; Male; Middle Aged; Oxyhemoglobins; Polysomnography; Prospective Studies; Pulmonary Disease, Chronic Obstructive; Sleep; Sleep Apnea, Obstructive; Spirometry; Vital Capacity

"Successful aging": effect of subclinical cardiovascular disease. - Newman, Anne B; Arnold, Alice M; Naydeck, Barbara L; Fried, Linda P; Burke, Gregory L; Enright, Paul; Gottdiener, John; Hirsch, Calvin; O'Leary, Daniel; Tracy, Russell (Arch Intern Med, 2003)
BACKGROUND: Cardiovascular diseases are the primary cause of death in older adults. Among those without clinical disease, high levels of subclinical disease are associated with poor survival. The effect of the extent of subclinical cardiovascular disease on the quality of the remaining years has not been defined. METHODS: In a longitudinal cohort study, 2932 men and women aged 65 years and older were followed up for 8 years to determine the likelihood of maintaining intact health and functioning. Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and with intact physical and cognitive functioning. RESULTS: Younger age at study entry and a lower extent of subclinical cardiovascular disease were independently associated with the likelihood of maintaining successful aging. In age-stratified summaries, those with subclinical disease had a trajectory of decline similar to subjects 5 years older without subclinical vascular disease. Regression analyses showed that the decline associated with subclinical disease was equivalent to 6.5 (95% confidence interval, 6.4-6.6) years of aging for women and 5.6 (95% confidence interval, 5.4-5.8) years of aging for men. Individual measures of the extent of cardiovascular disease, diabetes mellitus, smoking, and higher C-reactive protein level were also independently predictive of fewer years of successful aging, but none of these factors substantially attenuated the effect of age itself. CONCLUSIONS: There is a graded relationship between the extent of vascular disease measured noninvasively and the likelihood of maintaining intact health and function. Prevention of subclinical vascular disease may increase the quality and the quantity of years in late life.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Female; Health Status; Humans; Longitudinal Studies; Male; Quality of Life; Regression Analysis; Risk Factors

Variation in symptoms of sleep-disordered breathing with race and ethnicity: the Sleep Heart Health Study. - O'Connor, George T; Lind, Bonnie K; Lee, Elisa T; Nieto, F Javier; Redline, Susan; Samet, Jonathan M; Boland, Lori L; Walsleben, Joyce A; Foster, Gregory L (Sleep, 2003)
STUDY OBJECTIVES: To examine the relation of sleep-related symptoms to race and ethnicity in a diverse sample of middle-aged and older men and women. DESIGN: Cross-sectional questionnaire survey. SETTING: In the initial phase of the Sleep Heart Health Study, men and women enrolled in participating epidemiologic cohort studies were surveyed. PARTICIPANTS: 13,194 men and women 40 years of age and older, including 11,517 non-Hispanic white, 648 black, 643 American Indian, 296 Hispanic, and 90 Asian-Pacific Islander. INTERVENTIONS: Not applicable. MEASUREMENTS AND RESULTS: After adjustment for BMI and other factors, frequent snoring was more common among Hispanic women (odds ratio (OR) = 2.25, 95% confidence interval (CI) = 1.48, 3.42) and black women (OR = 1.55, 95% Ci = 1.13, 2.13) than among non-Hispanic white women. Hispanic men were significantly more likely to report frequent snoring than non-Hispanic white men (OR = 2.30, 95% CI = 1.43, 3.69). Black, American Indian, and Asian men did not differ significantly from white men in snoring prevalence. American Indian women were significantly more likely to report breathing pauses during sleep than their white, non-Hispanic counterparts (OR = 1.52, 95% CI 1.03, 2.24), although polysomnography data on a subset of the sample suggested that the association between this symptom reported on questionnaire and objective evidence of sleep-disordered breathing may be weaker among American Indians than among other groups. Mean Epworth Sleepiness Scale scores were slightly higher in black men and women than in their white, non-hispanic counterparts. CONCLUSIONS: Frequent snoring was more common among black and Hispanic women and Hispanic men than among their white non-Hispanic counterparts, even after adjusting for BMI and other factors. Further research including polysomnography and objective measurements of sleepiness is needed to assess the physiologic and clinical significance of these findings.
Keywords: Adult; Cross-Sectional Studies; Electroencephalography; Electrooculography; Ethnic Groups; Female; Heart Rate; Humans; Male; Polysomnography; Severity of Illness Index; Sleep Apnea Syndromes; Snoring; Surveys and Questionnaires

The association between lipid levels and the risks of incident myocardial infarction, stroke, and total mortality: The Cardiovascular Health Study. - Psaty, Bruce M; Anderson, Melissa; Kronmal, Richard A; Tracy, Russell P; Orchard, Trevor; Fried, Linda P; Lumley, Thomas; Robbins, John; Burke, Greg; Newman, Anne B; Furberg, Curt D (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the association between lipid levels and cardiovascular events in older adults. DESIGN: A prospective population-based study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: A total of 5,201 adults aged 65 and older living in U.S. communities, plus a recruitment of 687 African Americans 3 years later. MEASUREMENTS: Fasting lipid measures included low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, and triglycerides. RESULTS: At baseline, 1,954 men and 2,931 women were at risk for an incident myocardial infarction (MI) or stroke. During an average 7.5-year follow-up, 436 subjects had a coronary event, 332 had an ischemic stroke, 104 a hemorrhagic stroke, and 1,096 died. After adjustment, lipid measures were not major predictors of the outcomes of MI, ischemic stroke, hemorrhagic stroke, and total mortality. For total cholesterol and LDL-C, the associations with MI and ischemic stroke were only marginally significant. HDL-C was inversely associated with MI risk (hazard ratio=0.85 per standard deviation of 15.7 mg/dL, 95% confidence interval=0.76-0.96). For the outcome of ischemic stroke, high levels of HDL-C were associated with a decreased risk in men but not women. Lipid measures were generally only weakly associated with the risks of hemorrhagic stroke or total mortality. CONCLUSION: In this population-based study of older adults, most lipid measures were weakly associated with cardiovascular events. The association between low HDL-C and increased MI risk was nonetheless strong and consistent.
Keywords: African Americans; African Continental Ancestry Group; Aged; Female; Health Surveys; Humans; Incidence; Lipids; Male; Mortality; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk Factors; Stroke; United States

The association of personal and neighborhood socioeconomic indicators with subclinical cardiovascular disease in an elderly cohort. The cardiovascular health study. - Nordstrom, Cheryl K; Diez Roux, Ana V; Jackson, Sharon A; Gardin, Julius M (Soc Sci Med, 2004)
There has been recent interest in determining whether neighborhood characteristics are related to the cardiovascular health of residents. However, there are no data regarding the relationship between neighborhood socioeconomic status (SES) and prevalence of subclinical cardiovascular disease (CVD) in the elderly. We related personal SES (education, income, and occupation type) and neighborhood socioeconomic characteristics (a block-group score summing six variables reflecting neighborhood income and wealth, education, and occupation) to the prevalence of subclinical CVD (asymptomatic peripheral vascular disease or carotid atherosclerosis, electrocardiogram or echocardiogram abnormalities, and/or positive responses to Rose Questionnaire claudication or angina pectoris) among 3545 persons aged 65 and over, without prevalent CVD, in the Cardiovascular Health Study. Sixty percent of participants had at least one indicator of subclinical disease. Compared to those without, those with subclinical disease had significantly lower education, income, and neighborhood scores and were more likely to have blue-collar jobs. After adjustment for age, gender, and race, those in the lowest SES groups had increased prevalence of subclinical disease compared with those in the highest SES groups (OR = 1.50; 95% CI 1.21, 1.86 for income; OR = 1.41; 95% CI 1.18, 1.69 for education; OR = 1.39; 95% CI 1.16, 1.67 for block-group score). Those reporting a blue-collar lifetime occupation had greater prevalence of subclinical disease relative to those reporting a white-collar occupation (OR = 1.29; 95% CI 1.02-1.59). After adjustment for behavioral and biomedical risk factors, all of these associations were reduced. Neighborhood score tended to remain inversely associated with subclinical disease after adjustment for personal socioeconomic indicators but associations were not statistically significant. Personal income and blue-collar occupation remained significantly associated with subclinical disease after simultaneous adjustment for neighborhood score and education. Personal and neighborhood socioeconomic indicators were associated with subclinical disease prevalence in this elderly cohort. These relationships were reduced after controlling for traditional CVD risk factors.
Keywords: Aged; California; Cardiovascular Diseases; Cohort Studies; Female; Geography; Humans; Male; Maryland; Medicare; North Carolina; Pennsylvania; Residence Characteristics; Risk Factors; Social Class; Socioeconomic Factors; Surveys and Questionnaires

Associations between gender and measures of daytime somnolence in the Sleep Heart Health Study. - Baldwin, Carol M; Kapur, Vishesh K; Holberg, Catharine J; Rosen, Carol; Nieto, F Javier (Sleep, 2004)
STUDY OBJECTIVES: To examine the relationship of gender to subjective measures of sleepiness, including the Epworth Sleepiness Scale (ESS), in a community-based population. DESIGN: A cross-sectional study. SETTING/PARTICIPANTS: Multicenter Sleep Heart Health Study participants (N = 6.440, 52% women) recruited from ongoing cohort studies. INTERVENTIONS: N/A. MEASUREMENTS: Scores from the ESS, Sleep Heart Health Study daytime sleepiness and feeling unrested questions, polysomnography results (respiratory disturbance index at 4% desaturation), as well as data on difficulty initiating and maintaining sleep, insufficient sleep, sedative use, alcohol use, cardiovascular or respiratory disease, frequent awakening due to leg cramps. RESULTS: Women reported feeling sleepy as often as men did (odds ratio [OR] = 1.06; confidence interval [CI], 0.86-1.32), but women were less likely to have an ESS score > 10 (adjusted OR = 0.77; CI, 0.66-0.90) and more likely to report feeling unrested (adjusted OR = 1.39; CI, 1.14-1.69) than men. In men, the ESS score was more strongly correlated with reports of feeling unrested or sleepy compared to women. CONCLUSIONS: Men and women answer questions on sleepiness differently. Findings indicate that using the ESS to detect subjective sleepiness is more likely to identify men with sleepiness. Since the ESS is more strongly related to other subjective measures in men, the ESS may be a more sensitive measure of subjective sleepiness in men than in women.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Hypertension; Male; Middle Aged; Polysomnography; Severity of Illness Index; Sex Factors

The Cardiovascular Health Study: risk factors, subclinical disease, and clinical cardiovascular disease in older adults. - Newman, Anne B; Siscovick, David (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Cardiovascular Diseases; Female; Geriatric Assessment; Humans; Male; Risk Factors

Chronic renal insufficiency and cardiovascular events in the elderly: findings from the Cardiovascular Health Study. - Shlipak, Michael G; Fried, Linda F; Stehman-Breen, Catherine; Siscovick, David; Newman, Anne B (Am J Geriatr Cardiol, 2004)
In the Cardiovascular Health Study, the authors sought to evaluate the impact of chronic renal insufficiency (CRI) on cardiovascular risk status and outcomes in a representative sample of community-dwelling elderly adults. Defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men, CRI was present in 647 (11%) of 5808 participants. At baseline, the prevalence of clinical or subclinical cardiovascular disease was 64% in participants with CRI and 43% in those without CRI (odds ratio, 2.34; 95% confidence interval, 1.96-2.80). The incidence of cardiovascular disease events during follow-up was 3% per year in participants with creatinine levels <1.10 mg/dL and increased steadily to reach 7% per year in those with creatinine > or =1.70 mg/dL. Among the possible mediators for the association between CRI and cardiovascular morbidity are inflammatory (C-reactive protein, fibrinogen, and interleukin-6) and hemostatic (factor VII, factor VIII, plasmin-antiplasmin product, and D-dimer) biomarkers, all of which were significantly elevated in Cardiovascular Health Study participants with CRI. Future studies should evaluate the contribution of novel and traditional cardiovascular risk factors to the cardiovascular risk of elderly persons with CRI. The identification of CRI in the elderly and the use of cardiovascular prevention therapies represent a major opportunity to reduce their burden of cardiovascular morbidity.
Keywords: Aged; Blood Coagulation Factors; Cardiovascular Diseases; Chronic Disease; Creatinine; Cystatin C; Cystatins; Female; Fibrinogen; Geriatric Assessment; Humans; Incidence; Male; Prevalence; Renal Insufficiency; Risk Factors

The effects of age, sex, ethnicity, and sleep-disordered breathing on sleep architecture. - Redline, Susan; Kirchner, H Lester; Quan, Stuart F; Gottlieb, Daniel J; Kapur, Vishesh; Newman, Anne (Arch Intern Med, 2004)
BACKGROUND: Polysomnography is used to assess sleep quality and to gauge the functional effect of sleep disorders. Few population-based data are available to estimate the variation in sleep architecture across the population and the extent to which sleep-disordered breathing (SDB), a common health condition, contributes to poor sleep independent of other factors. The objective of this study was to describe the population variability in sleep quality and to quantify the independent associations with SDB. METHODS: Cross-sectional analyses were performed on data from 2685 participants, aged 37 to 92 years, in a community-based multicenter cohort study. Dependent measures included the percentage time in each sleep stage, the arousal index, and sleep efficiency. Independent measures were age, sex, ethnicity, comorbidity status, and the respiratory disturbance index. RESULTS: Lighter sleep was found in men relative to women and in American Indians and blacks relative to other ethnic groups. Increasing age was associated with impaired sleep in men, with less consistent associations in women. Notably, women had, on average, 106% more slow wave sleep. Sleep-disordered breathing was associated with poorer sleep; however, these associations were generally smaller than associations with sex, ethnicity, and age. Current smokers had lighter sleep than ex-smokers or never smokers. Obesity had little effect on sleep. CONCLUSIONS: Sleep architecture varies with sex, age, ethnicity, and SDB. Individual assessment of the effect of SDB on sleep quality needs to account for other host characteristics. Men, but not women, show evidence of poorer sleep with aging, suggesting important sex differences in sleep physiology.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Comorbidity; Female; Humans; Male; Middle Aged; Multivariate Analysis; Sex Factors; Sleep; Sleep Apnea Syndromes

Inflammatory and prothrombotic markers and the progression of renal disease in elderly individuals. - Fried, Linda; Solomon, Cam; Shlipak, Michael; Seliger, Stephen; Stehman-Breen, Catherine; Bleyer, Anthony J; Chaves, Paolo; Furberg, Curt; Kuller, Lewis; Newman, Anne (J Am Soc Nephrol, 2004)
Inflammatory and prothrombotic markers are elevated in individuals with mild to moderate renal disease. It was hypothesized that these markers may also be determinants of the progression of renal disease. The association of six markers-serum C-reactive protein (CRP), white blood cell (WBC) count, fibrinogen, factor VII, albumin, and hemoglobin-with subsequent elevations of creatinine and decline in estimated GFR in the Cardiovascular Health Study, a community-based cohort of elderly individuals, was analyzed. Linear regression was used to determine predictors of an annualized change in serum creatinine as the main outcome. Duration of follow-up was 7 yr for the original cohort and 4 yr for the more recently recruited black cohort. A total of 588 (12.7%) individuals had a decline in estimated GFR of at least 3 ml/min per yr per 1.73 m(2). Higher CRP (P < 0.001), WBC count (P < 0.001), fibrinogen (P < 0.001), and factor VII (P < 0.001) levels and lower albumin (P < 0.001) and hemoglobin levels (P < 0.001) were associated with a rise in creatinine, after adjusting for age. With additional adjustments for race, gender, baseline creatinine, systolic and diastolic BP, lipid levels, weight, and pack-years smoking, higher CRP, factor VII, fibrinogen, WBC count, and lower albumin and hemoglobin levels remained associated with a rise in creatinine. Similar results were found for decline in estimated GFR. The decline in GFR was greater with increasing number of inflammatory or prothrombotic markers that were above the median (below for hemoglobin and albumin). Inflammatory and prothrombotic markers are predictors for a change in kidney function in elderly individuals. Interventions that reduce inflammation might confer significant cardiovascular and renal benefits.
Keywords: Aged; Biomarkers; C-Reactive Protein; Creatinine; Factor VII; Female; Fibrinogen; Follow-Up Studies; Glomerular Filtration Rate; Hemoglobins; Humans; Leukocyte Count; Linear Models; Longitudinal Studies; Male; Predictive Value of Tests; Prospective Studies; Renal Insufficiency; Serum Albumin; Thrombosis

Preclinical Alzheimer disease: neuropsychological test performance 1.5 to 8 years prior to onset. - Saxton, J; Lopez, O L; Ratcliff, G; Dulberg, C; Fried, L P; Carlson, M C; Newman, A B; Kuller, L (Neurology, 2004)
OBJECTIVE: To determine if individuals ultimately diagnosed with Alzheimer disease (AD) exhibited evidence of cognitive impairment on neuropsychological tests administered between 1.5 years and 8.1 years before dementia onset. METHODS: A total of 693 community-dwelling individuals, part of the Cardiovascular Health Study, completed a neuropsychological test battery in 1991/92. Subjects were followed annually over the next 8 years (median follow-up = 7.4 years). Seventy-two individuals were ultimately diagnosed with AD (median follow-up = 4.5 years): 24 with AD onset 1.5 to 3.4 years after baseline neuropsychological testing, 20 with AD onset 3.5 to 5.0 years after testing, and 28 with onset 5.1 to 8.1 years after testing. A total of 621 individuals remained nondemented throughout the 8 years of follow-up (median follow-up = 7.5 years). RESULTS: Subjects ultimately diagnosed with AD had poorer scores on baseline neuropsychological measures than subjects who remained nondemented. Although individuals closest to AD onset (i.e., 1.5 to 3.4 years) performed the most poorly, cognitive impairment was detected in individuals who did not develop AD until 5 to 8 years later. CONCLUSIONS: Cognitive changes can be detected well before onset of Alzheimer disease.
Keywords: Age of Onset; Alzheimer Disease; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Confounding Factors, Epidemiologic; Disease Progression; Early Diagnosis; Educational Status; Female; Follow-Up Studies; Humans; Male; Memory Disorders; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk; Sensitivity and Specificity; Time Factors

The presence of frailty in elderly persons with chronic renal insufficiency. - Shlipak, Michael G; Stehman-Breen, Catherine; Fried, Linda F; Song, Xiao; Siscovick, David; Fried, Linda P; Psaty, Bruce M; Newman, Anne B (Am J Kidney Dis, 2004)
BACKGROUND: Frailty has been defined as a tool to define individuals who lack functional reserve and are at risk for functional decline. We hypothesized that chronic renal insufficiency (CRI) would be associated with a greater prevalence of frailty and disability in the elderly. METHODS: This cross-sectional analysis used baseline data collected from the Cardiovascular Health Study, which enrolled 5,888 community-dwelling adults aged 65 years or older from 4 clinical centers in the United States. Renal insufficiency is defined as a serum creatinine level of 1.3 mg/dL or greater (> or =115 micromol/L) in women and 1.5 mg/dL or greater (> or =133 micromol/L) in men. Frailty is defined by the presence of 3 of the following abnormalities: unintentional weight loss, self-reported exhaustion, measured weakness, slow walking speed, and low physical activity. Disability is defined as any self-reported difficulty with activities of daily living. RESULTS: Among 5,808 participants with creatinine levels measured at entry, 15.9% of men (n = 394) and 7.6% of women (n = 254) had CRI. Prevalences of frailty (15% versus 6%; P < 0.001) and disability (12% versus 7%; P = 0.001) were greater in participants with CRI compared with those with normal renal function. After multivariate adjustment for comorbidity, CRI remained significantly associated with frailty (odds ratio, 1.76; 95% confidence interval, 1.28 to 2.41), but not disability (odds ratio, 1.26; 95% confidence interval, 0.94 to 1.69). CONCLUSION: Elderly persons with CRI have a high prevalence of frailty, which may signal their risk for progression to adverse health outcomes. If confirmed in other studies, identification of frailty in patients with CRI may warrant special interventions to preserve their independence, quality of life, and survival.
Keywords: Activities of Daily Living; Aged; Cross-Sectional Studies; Female; Frail Elderly; Humans; Kidney Failure, Chronic; Male; United States

Respiratory muscle strength and the risk of incident cardiovascular events. - van der Palen, J; Rea, T D; Manolio, T A; Lumley, T; Newman, A B; Tracy, R P; Enright, P L; Psaty, B M (Thorax, 2004)
BACKGROUND: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. METHODS: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI), and stroke. RESULTS: Subjects in the lowest quintile of MIP had a 1.5-fold increased risk of MI (HR 1.48, 95% CI 1.07 to 2.06) and cardiovascular disease (CVD) death (HR 1.54, 95% CI 1.09 to 2.15) after adjustment for non-pulmonary function covariates. There was a potential inverse relationship with stroke (HR 1.36, 95% CI 0.97 to 1.90), but there was little evidence of an association between MIP and CHF (HR 1.22, 95% CI 0.93 to 1.60). The addition of FVC to models attenuated the HR associated with MIP only modestly; similarly, addition of MIP attenuated the HR associated with FVC only modestly. CONCLUSIONS: A reduced MIP is an independent risk factor for MI and CVD death, and a suggestion of an increased risk for stroke. This association with MIP appeared to be mediated through mechanisms other than inflammation.
Keywords: Cardiovascular Diseases; Female; Follow-Up Studies; Forced Expiratory Volume; Humans; Male; Maximal Voluntary Ventilation; Prospective Studies; Respiratory Muscles; Risk Factors; Vital Capacity

Self-reported alcohol consumption and falls in older adults: cross-sectional and longitudinal analyses of the cardiovascular health study. - Mukamal, Kenneth J; Mittleman, Murray A; Longstreth, W T; Newman, Anne B; Fried, Linda P; Siscovick, David S (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the cross-sectional and longitudinal associations between alcohol consumption and risk of falls in older adults. DESIGN: Cross-sectional and longitudinal analyses. SETTING: Four U.S. communities. PARTICIPANTS: A total of 5,841 older adults enrolled in the Cardiovascular Health Study, an ongoing, population-based, prospective cohort study, participated. MEASUREMENTS: Self-reported alcohol consumption at baseline, self-reported frequent falls at baseline, and the 4-year risk of falls of participants who denied frequent falls at baseline. RESULTS: Cross-sectional analysis indicated an apparent inverse association between alcohol consumption and risk of frequent falls (adjusted odds ratio in consumers of 14 or more drinks per week=0.41; 95% confidence interval (CI)=0.14-1.17; P for trend=.06), but longitudinal analysis indicated a similar 4-year risk of falls in abstainers and light to moderate drinkers but a 25% higher risk in consumers of 14 or more drinks per week (95% CI=3-52%; P for trend=.07). Similar results were found in analyses stratified by age, sex, race, and physical activity. CONCLUSION: Consumption of 14 or more drinks per week is associated with an increased risk of subsequent falls in older adults. Cross-sectional studies may fail to identify this risk of heavier drinking, perhaps because older adults at risk for falls decrease their alcohol use over time or because heavier drinkers at risk for falls tend not to enroll in cohort studies. However, because this study relied upon annual reporting of falls, further prospective studies should be conducted to confirm these findings.
Keywords: Accidental Falls; Aged; Alcohol Drinking; Chi-Square Distribution; Cross-Sectional Studies; Female; Humans; Longitudinal Studies; Male; Regression Analysis; Risk Factors; Self Disclosure; United States

Sleep and reported daytime sleepiness in normal subjects: the Sleep Heart Health Study. - Walsleben, Joyce A; Kapur, Vishesh K; Newman, Anne B; Shahar, Eyal; Bootzin, Richard R; Rosenberg, Carl E; O'Connor, George; Nieto, F Javier (Sleep, 2004)
STUDY OBJECTIVES: To describe the distribution of nocturnal sleep characteristics and reports of daytime sleepiness in a large well-defined group of healthy adults. DESIGN: The Sleep Heart Health Study is a multicenter study examining sleep and cardiopulmonary parameters through nocturnal polysomnography in adults enrolled in geographically distinct cardiovascular cohorts. SETTING: Community setting. PARTICIPANTS: 470 subjects enrolled in the Sleep Heart Health Study (n = 6440) were selected as a 'normative' group based on screening of health conditions and daily habits that could interfere with sleep. MEASUREMENTS AND RESULTS: Home-based nocturnal polysomnography was obtained on all participants and centrally scored for sleep and respiratory parameters. Demographic and health-related data were obtained and updated at the time of the home visit. Sleep efficiency decreased by 1.6% for each 10 years of increased age. Sleep time decreased by 0.1 hours (6.0 minutes) for each 10-year age increase and was longer in women. The arousal index increased by 0.8 for each 10-year increase in age and was lower by 1.4 in women. Women had a lower mean percentage of stage 1 and stage 2 sleep. Mean percentage of slow-wave sleep was higher in women (by 6.7%). Percentage of slow-wave sleep decreased with increased age for men only (by 1.9% for each 10-year age change). CONCLUSIONS: Data suggest a clear lessening in the quantity and quality of sleep with age that appears to be more rapid in males compared to females.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Sleep; Sleep Stages; Surveys and Questionnaires

Sleep apnea and markers of vascular endothelial function in a large community sample of older adults. - Nieto, F Javier; Herrington, David M; Redline, Susan; Benjamin, Emelia J; Robbins, John A (Am J Respir Crit Care Med, 2004)
Clinical studies have suggested that sleep apnea is associated with impaired brachial artery flow-mediated dilation, a surrogate of endothelial dysfunction. We examined this question among older participants in the baseline examination of the Sleep Heart Health/Cardiovascular Health Study cohort (n = 1,037, age 68 years or older, 56% female). Indices of sleep apnea, derived from 12-channel home polysomnography, were the apnea-hypopnea index (average number of apneas/hypopneas per hour) and the hypoxemia index (percentage of time below 90% O2 saturation). Baseline arterial diameter and percentage of flow-mediated dilation were measured by ultrasound. Sleep apnea measures were associated with baseline diameter and the percentage of flow-mediated dilation, although these associations were weakened after adjustment for other cardiovascular risk factors, particularly body mass index. However, a statistically significant linear association between the hypoxemia index and baseline diameter was observed even after adjustment for body mass index and other confounders (p < 0.01). The associations were stronger among participants who were younger than 80 years and among those who with hypertension. This study adds to the growing body of evidence linking sleep apnea with vascular dysfunction in older subjects. Whether these relationships are entirely independent of obesity is unclear. This association might be one of the mechanisms explaining the relationship between sleep apnea, hypertension, and cardiovascular disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Body Mass Index; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Comorbidity; Endothelium, Vascular; Female; Humans; Hypertension; Linear Models; Male; Polysomnography; Prevalence; Probability; Residence Characteristics; Risk Assessment; Sampling Studies; Severity of Illness Index; Sleep Apnea Syndromes; Ultrasonography, Doppler

Sleep-disordered breathing and white matter disease in the brainstem in older adults. - Ding, Jingzhong; Nieto, F Javier; Beauchamp, Norman J; Harris, Tamara B; Robbins, John A; Hetmanski, Jacqueline B; Fried, Linda P; Redline, Susan (Sleep, 2004)
STUDY OBJECTIVES: To examine whether sleep-disordered breathing is associated with white matter disease in the brainstem. DESIGN: A population-based longitudinal study. SETTING: Allegheny County, PA; Sacramento County, CA; and Washington County, MD. PATIENTS OR PARTICIPANTS: A total of 789 individuals, aged 68 years or older, drawn from the Sleep Heart Health Study. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: The participants underwent home polysomnography in 1995-1998 and cerebral magnetic resonance imaging in both 1992-1993 and 1997-1998. The apnea-hypopnea index was not associated with white matter disease in the brainstem, with or without adjusting for age, sex, race, community, body mass index, smoking status, alcohol use, systolic blood pressure, and the use of antihypertensive medication. In contrast, the arousal index (number of arousals per hour of sleep) was inversely associated with brainstem white matter disease (odds ratio = 0.75 for a SD increase in the arousal index, 95% confidence interval: 0.62, 0.92). CONCLUSIONS: The frequency of apneas and hypopneas was not associated with brainstem white matter disease in these older adults. A unique relationship with arousal frequency suggests that ischemic changes in the brainstem may be associated with arousals during sleep.
Keywords: Aged; Arousal; Brain; Brain Stem; Cerebrovascular Disorders; Electrooculography; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Polysomnography; Population Surveillance; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Stages

Sleep-disordered breathing is not associated with the presence of retinal microvascular abnormalities: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Wong, Tien Y; Klein, Ronald; Punjabi, Naresh; Robbins, John A; Newman, Anne B (Sleep, 2004)
STUDY OBJECTIVE: Sleep apnea and milder forms of sleep-disordered breathing (SDB) have been associated with overt clinical cardiovascular disease, but it is unknown whether SDB is associated with arterial microvascular pathology. We examined the relation between SDB and retinal microvascular abnormalities. DESIGN: Cross-sectional study. PARTICIPANTS: Subjects were 2,927 men and women, aged 51 to 97 years, who participated in the Sleep Heart Health Study and had retinal photographs taken within approximately 3 years of overnight, unattended, at-home polysomnography. MEASUREMENTS AND RESULTS: A respiratory disturbance index (RDI), calculated as the average number of apneas and hypopneas per hour of sleep, was used as an indicator of SDB in analysis. The overall prevalence of retinopathy was slightly higher in people with higher RDI values (5.4%, 4.9%, 8.6%, and 7.6%, respectively, in increasing quartiles of RDI), but after adjustment for age, body-mass index, hypertension, diabetes, and other factors, the presence of retinopathy was not associated with SDB. With the possible exceptions of microaneurysms and generalized arteriolar narrowing, as measured by lower arteriole-to-venule ratio, specific retinal abnormalities were not associated consistently with the RDI. Relative to the first quartile of RDI, the adjusted odds ratios (95% confidence interval) for the presence of microaneurysm in the second, third, and fourth quartiles of RDI were 1.05 (0.44-2.55), 1.97 (0.89-4.37), and 1.79 (0.78-4.10), respectively. An increase of RDI from 0 to 10 was associated with a predicted decrease in arteriole-to-venule ratio of 0.01. Results were similar when analyses were conducted in normotensive and nondiabetic persons separately. CONCLUSIONS: These data do not demonstrate a notable relation between SDB and retinal abnormalities. However, since this is the first investigation of a link between retinopathy and SDB, similar studies should be conducted in other population samples to demonstrate either consistency or inconsistency of our findings across studies.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Coronary Disease; Cross-Sectional Studies; Female; Humans; Hypoxia; Middle Aged; Polysomnography; Positive-Pressure Respiration; Retina; Retinal Vessels; Sleep Apnea Syndromes

Subclinical cardiovascular disease in older adults: insights from the Cardiovascular Health Study. - Chaves, Paulo H M; Kuller, Lewis H; O'Leary, Daniel H; Manolio, Teri A; Newman, Anne B (Am J Geriatr Cardiol, 2004)
Knowledge about the epidemiology of subclinical cardiovascular disease (SCVD) in older adults may hold the key for improved opportunities for primary prevention of cardiovascular disease (CVD), a top clinical and public health priority. This review reports findings on the prevalence of SCVD and the ability of SCVD measures to predict incident and adverse outcomes from one of the largest (N=5888) and most comprehensive prospective observational studies on SCVD in older adults, the Cardiovascular Health Study. According to a composite index that combined SCVD measures from different vascular beds, the overall prevalence of SCVD was 37%, making it as common as clinically overt CVD in older adults. SCVD measures strongly predicted incident CVD, stroke, mortality, frailty, and physical and cognitive decline, even after adjustment for traditional CVD risk factors. Ongoing research will address the potential use of SCVD for clinical decision making in older adults.
Keywords: Aged; Cardiovascular Diseases; Coronary Artery Disease; Heart Failure; Humans; Longitudinal Studies; Prevalence; Risk Assessment; Risk Factors

Age-dependent associations between sleep-disordered breathing and hypertension: importance of discriminating between systolic/diastolic hypertension and isolated systolic hypertension in the Sleep Heart Health Study. - Haas, Donald C; Foster, Gregory L; Nieto, F Javier; Redline, Susan; Resnick, Helaine E; Robbins, John A; Young, Terry; Pickering, Thomas G (Circulation, 2005)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with hypertension in the middle-aged. The association is less clear in older persons. Most middle-aged hypertensives have systolic/diastolic hypertension, whereas isolated systolic hypertension (ISH) is common among persons over 60 years. Mechanistically, only systolic/diastolic hypertension is expected to be associated with SDB, but few studies of SDB and hypertension distinguish systolic/diastolic hypertension from ISH. Prior investigations may have underestimated an association between SDB and systolic/diastolic hypertension in the elderly by categorizing individuals with ISH as simply hypertensive. METHODS AND RESULTS: We conducted cross-sectional analyses of 6120 participants in the Sleep Heart Health Study, stratified by age: 40 to 59 (n=2477) and > or =60 years. Outcome measures included apnea-hypopnea index (AHI; average number of apneas plus hypopneas per hour of sleep), systolic/diastolic hypertension (> or =140 and > or =90 mm Hg), and ISH (> or =140 and <90 mm Hg). With adjustment for covariates, ISH was not associated with SDB in either age category. In those aged<60 years, AHI was significantly associated with higher odds of systolic/diastolic hypertension (AHI 15 to 29.9, OR=2.38 [95% CI 1.30 to 4.38]; AHI > or =30, OR=2.24 [95% CI 1.10 to 4.54]). Among those aged > or =60 years, no adjusted association between AHI and systolic/diastolic hypertension was found. CONCLUSIONS: SDB is associated with systolic/diastolic hypertension in those aged <60 years. No association was found between SDB and systolic/diastolic hypertension in those aged > or =60 years or between SDB and ISH in either age category. These findings have implications for SDB screening and treatment. Distinguishing between hypertensive subtypes reveals a stronger association between SDB and hypertension for those aged <60 years than previously reported.
Keywords: Adult; Age Factors; Aged; Antihypertensive Agents; Cross-Sectional Studies; Diastole; Female; Humans; Hypertension; Male; Middle Aged; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Central; Systole

Association of sleep time with diabetes mellitus and impaired glucose tolerance. - Gottlieb, Daniel J; Punjabi, Naresh M; Newman, Ann B; Resnick, Helaine E; Redline, Susan; Baldwin, Carol M; Nieto, F Javier (Arch Intern Med, 2005)
BACKGROUND: Experimental sleep restriction causes impaired glucose tolerance (IGT); however, little is known about the metabolic effects of habitual sleep restriction. We assessed the cross-sectional relation of usual sleep time to diabetes mellitus (DM) and IGT among participants in the Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. METHODS: Participants were 722 men and 764 women, aged 53 to 93 years. Usual sleep time was obtained by standardized questionnaire. Diabetes mellitus was defined as a serum glucose level of 126 mg/dL or more (> or =7.0 mmol/L) fasting or 200 mg/dL or more (> or =11.1 mmol/L) 2 hours following standard oral glucose challenge or medication use for DM. Impaired glucose tolerance was defined as a 2-hour postchallenge glucose level of 140 mg/dL or more (> or =7.8 mmol/L) and less than 200 mg/dL. The relation of sleep time to DM and IGT was examined using categorical logistic regression with adjustment for age, sex, race, body habitus, and apnea-hypopnea index. RESULTS: The median sleep time was 7 hours per night, with 27.1% of subjects sleeping 6 hours or less per night. Compared with those sleeping 7 to 8 hours per night, subjects sleeping 5 hours or less and 6 hours per night had adjusted odds ratios for DM of 2.51 (95% confidence interval, 1.57-4.02) and 1.66 (95% confidence interval, 1.15-2.39), respectively. Adjusted odds ratios for IGT were 1.33 (95% confidence interval, 0.83-2.15) and 1.58 (95% confidence interval, 1.15-2.18), respectively. Subjects sleeping 9 hours or more per night also had increased odds ratios for DM and IGT. These associations persisted when subjects with insomnia symptoms were excluded. CONCLUSIONS: A sleep duration of 6 hours or less or 9 hours or more is associated with increased prevalence of DM and IGT. Because this effect was present in subjects without insomnia, voluntary sleep restriction may contribute to the large public health burden of DM.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Glucose; Diabetes Mellitus; Disease Progression; Female; Glucose Intolerance; Humans; Male; Middle Aged; Odds Ratio; Prevalence; Prospective Studies; Sleep; Surveys and Questionnaires; Time Factors; United States

Associations of sleep-disordered breathing and cerebral changes on MRI. - Robbins, John; Redline, Susan; Ervin, Ann; Walsleben, Joyce A; Ding, Jingzhong; Nieto, F Javier (J Clin Sleep Med, 2005)
STUDY OBJECTIVES: Population-based studies have demonstrated associations between sleep-disordered breathing (SDB), hypertension, and cardiovascular disease; few large-scale studies have examined associations of SDB with objective measures of cerebrovascular disease. This study tested the significance of associations of SDB with evidence of brain injury or ischemia determined by cerebral magnetic resonance imaging (MRI) studies. DESIGN: Cross-sectional and longitudinal analyses in a nested sample of Cardiovascular Health Study participants in the Sleep Heart Health Study. PARTICIPANTS: The 843 individuals (mean age 77, SD 4.3 years, 58% women) who had MRI studies as part of the Cardiovascular Health Study before and after polysomnography obtained as part of the Sleep Heart Health Study. MEASUREMENTS: A 12-channel polysomnogram was used to derive indexes of sleep-disordered breathing. Repeated MRI measurements provided indexes of infarct (presence and size) and white matter disease. Logistic regression analyses were used to model MRI changes of infarct-like lesions and white matter disease as a function of age, baseline white matter grade, and indexes of central and obstructive sleep-disordered breathing. RESULTS: Individuals who showed progression in white matter disease compared to those who did not were significantly more likely to show a Cheyne-Stokes respiration pattern and to have an increased number of central but not obstructive apneas. CONCLUSIONS: An association between change in white matter grade and measures of central sleep apnea was demonstrated that was consistent with a causal pathway in which central sleep apnea contributes to the progression of white matter disease; alternatively, central sleep apnea may be a marker of subclinical cerebrovascular or cardiovascular disease.
Keywords: Aged; Brain; Cerebral Infarction; Cerebrovascular Circulation; Female; Humans; Magnetic Resonance Imaging; Male; Polysomnography; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Cardiovascular mortality risk in chronic kidney disease: comparison of traditional and novel risk factors. - Shlipak, Michael G; Fried, Linda F; Cushman, Mary; Manolio, Teri A; Peterson, Do; Stehman-Breen, Catherine; Bleyer, Anthony; Newman, Anne; Siscovick, David; Psaty, Bruce (JAMA, 2005)
CONTEXT: Elderly persons with chronic kidney disease have substantial risk for cardiovascular mortality, but the relative importance of traditional and novel risk factors is unknown. OBJECTIVE: To compare traditional and novel risk factors as predictors of cardiovascular mortality. DESIGN, SETTING, AND PATIENTS: A total of 5808 community-dwelling persons aged 65 years or older living in 4 communities in the United States participated in the Cardiovascular Health Study cohort. Participants were initially recruited from 1989 to June 1990; an additional 687 black participants were recruited in 1992-1993. The average length of follow-up in this longitudinal study was 8.6 years. MAIN OUTCOME MEASURES: Cardiovascular mortality among those with and without chronic kidney disease. Chronic kidney disease was defined as an estimated glomerular filtration rate of less than 60 mL/min per 1.73 m2. RESULTS: Among the participants, 1249 (22%) had chronic kidney disease at baseline. The cardiovascular mortality risk rate was 32 deaths/1000 person-years among those with chronic kidney disease vs 16/1000 person-years among those without it. In multivariate analyses, diabetes, systolic hypertension, smoking, low physical activity, nonuse of alcohol, and left ventricular hypertrophy were predictors of cardiovascular mortality in persons with chronic kidney disease (all P values <.05). Among the novel risk factors, only log C-reactive protein (P = .05) and log interleukin 6 (P<.001) were associated with the outcome as linear predictors. Traditional risk factors were associated with the largest absolute increases in risks for cardiovascular deaths among persons with chronic kidney disease: for left ventricular hypertrophy, there were 25 deaths per 1000 person-years; current smoking, 20 per 1000 person-years; physical inactivity, 15 per 1000 person-years; systolic hypertension, 14 per 1000 person-years; diabetes, 14 per 1000 person-years; and nonuse of alcohol, 11 per 1000 person-years vs 5 deaths per 1000 person-years for those with increased C-reactive protein and 5 per 1000 person-years for those with increased interleukin 6 levels. A receiver operating characteristic analysis found that traditional risk factors had an area under the curve of 0.73 (95% confidence interval, 0.70-0.77) among those with chronic kidney disease. Adding novel risk factors only increased the area under the curve to 0.74 (95% confidence interval, 0.71-0.78; P for difference = .15). CONCLUSIONS: Traditional cardiovascular risk factors had larger associations with cardiovascular mortality than novel risk factors in elderly persons with chronic kidney disease. Future research should investigate whether aggressive lifestyle intervention in patients with chronic kidney disease can reduce their substantial cardiovascular risk.
Keywords: Aged; Cardiovascular Diseases; Chronic Disease; Humans; Kidney Diseases; Longitudinal Studies; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

Coronary artery calcium: associations with brain magnetic resonance imaging abnormalities and cognitive status. - Rosano, Caterina; Naydeck, Barbara; Kuller, Lewis H; Longstreth, William T; Newman, Anne B (J Am Geriatr Soc, 2005)
OBJECTIVES: To evaluate the association between coronary atherosclerosis and subclinical brain magnetic resonance imaging (MRI) abnormalities and between coronary atherosclerosis and abnormal cognitive function (dementia/mild cognitive impairment). DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), an epidemiological study of risk factors for cardiovascular disease in older adults. PARTICIPANTS: Four hundred nine men and women, mean age 79, recruited from the Pittsburgh center of the CHS. MEASUREMENTS: Coronary atherosclerosis was defined according to the level of coronary artery calcification (CAC), as measured using electronic beam tomography. Subclinical brain MRI abnormalities included ventricular enlargement, white matter hyperintensities, and number of subcortical brain infarcts. Brain MRI and CAC measurements were performed between 1998 and 2000 at the Pittsburgh center of the CHS. Prevalence of brain MRI abnormalities and abnormal cognitive status were examined across quartiles of the CAC score, before and after controlling for age. Multivariate logistic regression models were used to assess whether CAC level was associated with abnormalities of brain MRI or abnormal cognitive status. RESULTS: Older adults with high CAC scores were more likely to have more-severe brain MRI abnormalities, including subcortical infarction and high white matter hyperintensities. The associations between CAC and ventricular enlargement showed a similar but not significant trend. The presence of any of the MRI abnormalities attenuated the association between CAC and abnormal cognitive status. CONCLUSION: Older adults with higher levels of CAC were more likely to have more-severe brain MRI abnormalities and abnormal cognitive status.
Keywords: Aged; Brain; Calcinosis; Cognition Disorders; Coronary Artery Disease; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Risk Factors; United States

Cystatin C and incident peripheral arterial disease events in the elderly: results from the Cardiovascular Health Study. - O'Hare, Ann M; Newman, Anne B; Katz, Ronit; Fried, Linda F; Stehman-Breen, Catherine O; Seliger, Stephen L; Siscovick, David S; Shlipak, Michael G (Arch Intern Med, 2005)
BACKGROUND: The association of cystatin C, a novel marker of renal function, with risk for developing complications related to peripheral arterial disease (PAD) has not been examined. METHODS: We evaluated the hypothesis that a high cystatin C concentration is independently associated with future PAD events among 4025 participants in the Cardiovascular Health Study who underwent serum cystatin C measurement at the 1992-1993 visit and who did not have PAD at baseline. The association of cystatin C quintiles with time to first lower-extremity PAD procedure (bypass surgery, angioplasty, or amputation) was evaluated using multivariable proportional hazards models. Secondary analyses were conducted using quintiles of serum creatinine level and estimated glomerular filtration rate (eGFR). RESULTS: The annualized risk of undergoing a procedure for PAD was 0.43% per year among participants in the highest cystatin C quintile (>1.27 mg/L) compared with 0.21% per year or less in all other quintiles. After multivariable adjustment for known risk factors for PAD, elevated cystatin C levels remained associated with the outcome (hazard ratio, 2.5 for highest vs lowest quintile of cystatin C, 95% confidence interval, 1.2-5.1). The highest quintiles of serum creatinine level and eGFR were not associated with future PAD events in either unadjusted or adjusted analyses. CONCLUSION: Elevated concentrations of cystatin C were independently predictive of incident PAD events among community-dwelling elderly patients.
Keywords: Aged; Cohort Studies; Cystatin C; Cystatins; Female; Health Surveys; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Predictive Value of Tests; Risk Factors; ROC Curve; United States

Cystatin C and subclinical brain infarction. - Seliger, Stephen L; Longstreth, W T; Katz, Ronit; Manolio, Teri; Fried, Linda F; Shlipak, Michael; Stehman-Breen, Catherine O; Newman, Anne; Sarnak, Mark; Gillen, Daniel L; Bleyer, Anthony; Siscovick, David S (J Am Soc Nephrol, 2005)
Subclinical brain infarcts (SBI) are common in the elderly and are associated with covert neurologic and cognitive impairment. Although renal impairment is associated with accelerated cerebrovascular disease and an increased risk for clinically apparent brain infarct, few studies have examined the relationship between renal function and SBI, and these may have been limited by the inaccuracy of creatinine as a renal function marker. A cross-sectional study was performed among older adults in the Cardiovascular Health Study to examine associations between SBI and two serum markers of renal function: Serum creatinine (SCr) and cystatin C (CysC). Patients had cranial magnetic resonance imaging and renal markers measured in 1992 to 1993. Logistic regression was used to estimate the associations between renal function (estimated by 1/SCr and 1/CysC) and SBI, controlling for potential confounding factors. SBI were present in 789 (28.7%) of 2784 participants. A linear association with SBI was observed for 1/CysC (per 1-SD decrement; odds ratio [OR] 1.20; 95% confidence interval [CI] 1.09 to 1.32; P < 0.001) but not for 1/SCr (OR 1.08; 95% CI 0.98 to 1.19; P = 0.14), for which a quadratic U-shaped association was suggested (P = 0.004). In a model with both markers, 1/CysC was linearly associated with SBI (OR 1.26; P < 0.001), whereas 1/SCr was not (OR 1.06; P = 0.3). The prevalence of SBI was directly associated with quintile of CysC, whereas the association between SCr and SBI was U-shaped, with greater prevalence at high and low levels. Compared with creatinine, CysC, a novel marker of renal function, has a stronger and more direct association with SBI in the elderly.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Brain Infarction; Confidence Intervals; Creatinine; Cross-Sectional Studies; Cystatin C; Cystatins; Disease Progression; Female; Geriatric Assessment; Humans; Incidence; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Odds Ratio; Predictive Value of Tests; Prognosis; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index; Sex Factors; Survival Analysis

Cystatin C and the risk of death and cardiovascular events among elderly persons. - Shlipak, Michael G; Sarnak, Mark J; Katz, Ronit; Fried, Linda F; Seliger, Stephen L; Newman, Anne B; Siscovick, David S; Stehman-Breen, Catherine (N Engl J Med, 2005)
BACKGROUND: Cystatin C is a serum measure of renal function that appears to be independent of age, sex, and lean muscle mass. We compared creatinine and cystatin C levels as predictors of mortality from cardiovascular causes and from all causes in the Cardiovascular Health Study, a cohort study of elderly persons living in the community. METHODS: Creatinine and cystatin C were measured in serum samples collected from 4637 participants at the study visit in 1992 or 1993; follow-up continued until June 30, 2001. For each measure, the study population was divided into quintiles, with the fifth quintile subdivided into thirds (designated 5a, 5b, and 5c). RESULTS: Higher cystatin C levels were directly associated, in a dose-response manner, with a higher risk of death from all causes. As compared with the first quintile, the hazard ratios (and 95 percent confidence intervals) for death were as follows: second quintile, 1.08 (0.86 to 1.35); third quintile, 1.23 (1.00 to 1.53); fourth quintile, 1.34 (1.09 to 1.66); quintile 5a, 1.77 (1.34 to 2.26); 5b, 2.18 (1.72 to 2.78); and 5c, 2.58 (2.03 to 3.27). In contrast, the association of creatinine categories with mortality from all causes appeared to be J-shaped. As compared with the two lowest quintiles combined (cystatin C level, < or =0.99 mg per liter), the highest quintile of cystatin C (> or =1.29 mg per liter) was associated with a significantly elevated risk of death from cardiovascular causes (hazard ratio, 2.27 [1.73 to 2.97]), myocardial infarction (hazard ratio, 1.48 [1.08 to 2.02]), and stroke (hazard ratio, 1.47 [ 1.09 to 1.96]) after multivariate adjustment. The fifth quintile of creatinine, as compared with the first quintile, was not independently associated with any of these three outcomes. CONCLUSIONS: Cystatin C, a serum measure of renal function, is a stronger predictor of the risk of death and cardiovascular events in elderly persons than is creatinine.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cerebrospinal Fluid Proteins; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Mortality; Multivariate Analysis; Prognosis; Risk

Cystatin C concentration as a risk factor for heart failure in older adults. - Sarnak, Mark J; Katz, Ronit; Stehman-Breen, Catherine O; Fried, Linda F; Jenny, Nancy Swords; Psaty, Bruce M; Newman, Anne B; Siscovick, David; Shlipak, Michael G (Ann Intern Med, 2005)
BACKGROUND: Previous studies that evaluated the association of kidney function with incident heart failure may be limited by the insensitivity of serum creatinine concentration for detecting abnormal kidney function. OBJECTIVE: To compare serum concentrations of cystatin C (a novel marker of kidney function) and creatinine as predictors of incident heart failure. DESIGN: Observational study based on measurement of serum cystatin C from frozen sera obtained at the 1992-1993 visit of the Cardiovascular Health Study. Follow-up occurred every 6 months. SETTING: Adults 65 years of age or older from 4 communities in the United States. PARTICIPANTS: 4384 persons without previous heart failure who had measurements of serum cystatin C and serum creatinine. MEASUREMENTS: Incident heart failure. RESULTS: The mean (+/-SD) serum concentrations of cystatin C and creatinine were 82 +/- 25 nmol/L (1.10 +/- 0.33 mg/L) and 89 +/- 34 micromol/L (1.01 +/- 0.39 mg/dL), respectively. During a median follow-up of 8.3 years (maximum, 9.1 years), 763 (17%) participants developed heart failure. After adjustment for demographic factors, traditional and novel cardiovascular risk factors, cardiovascular disease status, and medication use, sequential quintiles of cystatin C concentration were associated with a stepwise increased risk for heart failure in Cox proportional hazards models (hazard ratios, 1.0 [reference], 1.30 [95% CI, 0.96 to 1.75], 1.44 [CI, 1.07 to 1.94], 1.58 [CI, 1.18 to 2.12], and 2.16 [CI, 1.61 to 2.91]). In contrast, quintiles of serum creatinine concentration were not associated with risk for heart failure in adjusted analysis (hazard ratios, 1.0 [reference], 0.77 [CI, 0.59 to 1.01], 0.85 [CI, 0.64 to 1.13], 0.97 [CI, 0.72 to 1.29], and 1.14 [CI, 0.87 to 1.49]). LIMITATIONS: The mechanism by which cystatin C concentration predicts risk for heart failure remains unclear. CONCLUSIONS: The cystatin C concentration is an independent risk factor for heart failure in older adults and appears to provide a better measure of risk assessment than the serum creatinine concentration. *For a full list of participating Cardiovascular Health Study investigators and institutions, see http://www.chs-nhlbi.org.
Keywords: Aged; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney; Kidney Function Tests; Male; Risk Factors; United States

Cystatin-C and inflammatory markers in the ambulatory elderly. - Shlipak, Michael G; Katz, Ronit; Cushman, Mary; Sarnak, Mark J; Stehman-Breen, Catherine; Psaty, Bruce M; Siscovick, David; Tracy, Russell P; Newman, Anne; Fried, Linda (Am J Med, 2005)
PURPOSE: Inflammatory factors are elevated in persons with severe renal dysfunction, but their association across all levels of renal function is unclear. We compared cystatin-C, a novel marker of renal function, with creatinine and estimated glomerular filtration rate (eGFR) as predictors of C-reactive protein and fibrinogen levels. METHODS: This study is a cross-sectional analysis to evaluate cystatin-C, creatinine, and eGFR as predictors of the inflammatory markers C-reactive protein and fibrinogen. Participants included 4637 ambulatory elderly patients from the Cardiovascular Health Study. Multivariate linear regression was used to determine the independent associations of each renal function measurement with the inflammatory marker outcomes. RESULTS: After adjustment for confounding factors, cystatin-C was correlated with both C-reactive protein (coefficient = 0.13; 95% confidence interval: 0.10-1.16, P <.0001) and fibrinogen levels (0.15; 0.13-0.18, P <.0001). Associations were larger than those for creatinine and C-reactive protein (0.05; 0.02-0.07, P = .003) or fibrinogen (0.07; 0.04-0.10, P <.0001). Adjusted levels of C-reactive protein increased incrementally across quintiles of cystatin-C, from a median of 2.2 mg/L in quintile 1 to 3.7 mg/L in quintile 5. In contrast, both C-reactive protein and fibrinogen had U-shaped associations with quintiles of creatinine and eGFR, because the inflammatory markers were equivalently elevated in quintiles 1 and 5. CONCLUSIONS: The finding of a significant linear association of cystatin-C and inflammation markers suggests that even small reductions in renal function may be associated with adverse pathophysiologic consequences.
Keywords: Age Factors; Aged; Biomarkers; C-Reactive Protein; Cross-Sectional Studies; Cystatin C; Cystatins; Female; Fibrinogen; Glomerular Filtration Rate; Humans; Kidney Diseases; Male; Predictive Value of Tests; Sensitivity and Specificity

Cystatin-C and mortality in elderly persons with heart failure. - Shlipak, Michael G; Katz, Ronit; Fried, Linda F; Jenny, Nancy Swords; Stehman-Breen, Catherine O; Newman, Anne B; Siscovick, David; Psaty, Bruce M; Sarnak, Mark J (J Am Coll Cardiol, 2005)
OBJECTIVES: We sought to evaluate cystatin-C, a novel measure of renal function, as a predictor of mortality in elderly persons with heart failure (HF) and to compare it with creatinine. BACKGROUND: Renal function is an important prognostic factor in patients with HF, but creatinine levels, which partly reflect muscle mass, may be insensitive for detecting renal insufficiency. METHODS: A total of 279 Cardiovascular Health Study participants with prevalent HF and measures of serum cystatin-C and creatinine were followed for mortality outcomes over a median of 6.5 years. RESULTS: Median creatinine and cystatin-C levels were 1.05 mg/dl and 1.26 mg/l. Each standard deviation increase in cystatin-C (0.35 mg/l) was associated with a 31% greater adjusted mortality risk (95% confidence interval [CI] 20% to 43%, p < 0.001), whereas each standard deviation increase in creatinine (0.39 mg/dl) was associated with a 17% greater adjusted mortality risk (95% CI 1% to 36%, p = 0.04). When both measures were combined in a single adjusted model, cystatin-C remained associated with elevated mortality risk (hazard ratio 1.60, 95% CI 1.32 to 1.94), whereas creatinine levels appeared associated with lower risk (hazard ratio 0.73, 95% CI 0.57 to 0.95). CONCLUSIONS: Cystatin-C is a stronger predictor of mortality than creatinine in elderly persons with HF. If confirmed in future studies, this new marker of renal function could improve risk stratification in patients with HF.
Keywords: Age Factors; Aged; Aged, 80 and over; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Pilot Projects; Predictive Value of Tests; Risk Assessment; Survival Analysis

Dementia and Alzheimer's disease incidence in relationship to cardiovascular disease in the Cardiovascular Health Study cohort. - Newman, Anne B; Fitzpatrick, Annette L; Lopez, Oscar; Jackson, Sharon; Lyketsos, Constantine; Jagust, William; Ives, Diane; DeKosky, Steven T; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether coronary artery disease, peripheral arterial disease (PAD), or noninvasive markers of cardiovascular disease (CVD) predict the onset of dementia and Alzheimer's disease (AD). DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Men and women (N=3,602) with a brain magnetic resonance imaging (MRI) scan but no dementia were followed for 5.4 years. Participants with stroke were excluded. MEASUREMENTS: Neurologists and psychiatrists classified incident cases of dementia and subtype using neuropsychological tests, examination, medical records and informant interviews. CVD was defined at the time of the MRI scan. Noninvasive tests of CVD were assessed within 1 year of the MRI. Apolipoprotein E allele status, age, race, sex, education, Mini-Mental State Examination score, and income were assessed as potential confounders. RESULTS: The incidence of dementia was higher in those with prevalent CVD, particularly in the subgroup with PAD. The rate of AD was 34.4 per 1,000 person-years for those with a history of CVD, versus 22.2 per 1,000 person-years without a history of CVD (adjusted hazard ratio (HR)=1.3, 95% confidence interval (CI)=1.0-1.7). Rates of AD were highest in those with PAD (57.4 vs 23.7 per 100 person-years, adjusted HR=2.4, 95% CI=1.4-4.2). Results were similar with further exclusion of those with vascular dementia from the AD group. A gradient of increasing risk was noted with the extent of vascular disease. CONCLUSION: Older adults with CVD other than stroke had a higher risk of dementia and AD than did those without CVD. The risk was highest in people with PAD, suggesting that extensive peripheral atherosclerosis is a risk factor for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Peripheral Vascular Diseases; Risk Factors

Factors associated with incidence and persistence of symptoms of disturbed sleep in an elderly cohort: the Cardiovascular Health Study. - Quan, Stuart F; Katz, Ronit; Olson, Jean; Bonekat, William; Enright, Paul L; Young, Terry; Newman, Anne (Am J Med Sci, 2005)
BACKGROUND: There are limited data pertaining to the factors influencing the incidence and persistence of sleep symptoms in the elderly. The purpose of this study was to determine the incidence and nonremission rates of the following sleep symptoms: trouble falling asleep (TFA), frequent awakenings (FA), and excessive daytime sleepiness (EDS) in the Cardiovascular Health Study (CHS), a prospective multicenter study of cardiovascular disease in a large cohort of elderly adults. Factors influencing these rates were assessed as well. METHODS: 4467 participants in CHS were surveyed for the presence of TFA, FA, and EDS as well as other health problems at their baseline examination and at a follow-up examination 1 to 4 years later. RESULTS: Annualized incidence and nonremission rates were the following: TFA (2.8% and 15.4%), FA (12.3% and 22.7%), and EDS (4.4% and 13.4%). Women were more likely to have incident and persistent TFA. Depression was the primary factor predicting the incidence of all three sleep symptoms. However, other health conditions, including respiratory symptoms and cardiovascular disease, and limitation in activities of daily living were important as well. Depression also was the most important factor associated with persistence of these sleep symptoms. The role of other health conditions in determining nonremission was much more limited. CONCLUSIONS: Incidence of sleep disturbances in the elderly is related to depression, health conditions, and physical functioning. However, persistence of sleep disturbances is best predicted by the presence of depression.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Depression; Female; Health Status; Humans; Incidence; Logistic Models; Male; Odds Ratio; Prevalence; Risk Factors; Sex Factors; Sleep Initiation and Maintenance Disorders; Surveys and Questionnaires

Kidney function as a predictor of noncardiovascular mortality. - Fried, Linda F; Katz, Ronit; Sarnak, Mark J; Shlipak, Michael G; Chaves, Paulo H M; Jenny, Nancy Swords; Stehman-Breen, Catherine; Gillen, Dan; Bleyer, Anthony J; Hirsch, Calvin; Siscovick, David; Newman, Anne B (J Am Soc Nephrol, 2005)
Chronic kidney disease is associated with a higher risk for cardiovascular mortality, as well as all-cause mortality. Whether chronic kidney disease is a predictor of noncardiovascular mortality is less clear. To further explore the latter, the association of kidney function with total noncardiovascular mortality and cause-specific mortality was assessed in the Cardiovascular Health Study, a community-based cohort of older individuals. Kidney disease was assessed using cystatin C and estimated GFR in 4637 participants in 1992 to 1993. Participants were followed until June 30, 2001. Deaths were adjudicated as cardiovascular or noncardiovascular disease by committee, and an underlying cause of death was assigned. The associations of kidney function with total noncardiovascular mortality and cause-specific mortality were analyzed by proportional hazards regression. Noncardiovascular mortality rates increased with higher cystatin C quartiles (16.8, 17.1, 21.6, and 50.0 per 1000 person-years). The association of cystatin C with noncardiovascular mortality persisted after adjustment for demographic factors; the presence of diabetes, C-reactive protein, hemoglobin, and prevalent cardiovascular disease; and measures of atherosclerosis (hazard ratio 1.69; 95% confidence interval 1.33 to 2.15, for the fourth quartile versus the first quartile). Results for estimated GFR were similar. The risk for noncardiac deaths attributed to pulmonary disease, infection, cancer, and other causes was similarly associated with cystatin C levels. Kidney function predicts noncardiovascular mortality from multiple causes in the elderly. Further research is needed to understand the mechanisms and evaluate interventions to reduce the high mortality rate in chronic kidney disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cause of Death; Cohort Studies; Confidence Intervals; Creatinine; Cystatin C; Cystatins; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Kidney Function Tests; Longitudinal Studies; Male; Probability; Proportional Hazards Models; Risk Assessment; Severity of Illness Index; Survival Analysis; United States

Morphometric analysis of gray matter volume in demented older adults: exploratory analysis of the cardiovascular health study brain MRI database. - Rosano, C; Becker, J; Lopez, O; Lopez-Garcia, P; Carter, C S; Newman, A; Kuller, L; Aizenstein, H (Neuroepidemiology, 2005)
We tested the feasibility of a fully automated brain MRI voxel count technique--automated labeling pathway (ALP)--in a sample of 15 demented and 13 cognitively normal women (age 75-85 years) participating to the Cardiovascular Health Study (CHS). We hypothesized that ALP would replicate well-established findings of the anatomical correlates of dementia. In particular, we hypothesized that ALP volumetric measures would: (1) significantly differ between cognitively normal and demented women in those brain areas that are established markers for diagnosis of dementia (temporal and medial temporal lobes, hippocampus, amygdala and parahippocampus) but not in other brain areas (e.g., occipital lobe, visual cortex, motor cortex) and (2) correlate with visual ratings of brain disease which have been previously collected as part of the CHS. ALP required minimal operator intervention (input of brain images and verification of misalignments) and employed computer time of about 1 h per brain. ALP detected significant focal volumetric differences in the limbic system (p values between groups for hippocampus and parahippocampus: 0.002 and 0.005, respectively), temporal lobe (p < 0.0001) and caudate (p = 0.009), but not in other brain areas (e.g. occipital lobe, visual or motor cortex). Furthermore, ALP measures of medial temporal lobe atrophy strongly correlated with CHS visual ratings of ventricular enlargement (r(2) = 0.6, p = 0.002 for medial temporal lobe). In conclusion, ALP-detected focal brain atrophy was strongly associated with dementia. Because of its fully automated design, ALP technique is an ideal candidate to assess whether volumetric measures of specific areas can discriminate dementia better than currently available measures of global brain atrophy in large epidemiological studies.
Keywords: Aged; Aged, 80 and over; Brain; Dementia; Educational Status; Feasibility Studies; Female; Health Status; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Organ Size; Reproducibility of Results

Population structure, admixture, and aging-related phenotypes in African American adults: the Cardiovascular Health Study. - Reiner, Alexander P; Ziv, Elad; Lind, Denise L; Nievergelt, Caroline M; Schork, Nicholas J; Cummings, Steven R; Phong, Angie; Burchard, Esteban González; Harris, Tamara B; Psaty, Bruce M; Kwok, Pui-Yan (Am J Hum Genet, 2005)
U.S. populations are genetically admixed, but surprisingly little empirical data exists documenting the impact of such heterogeneity on type I and type II error in genetic-association studies of unrelated individuals. By applying several complementary analytical techniques, we characterize genetic background heterogeneity among 810 self-identified African American subjects sampled as part of a multisite cohort study of cardiovascular disease in older adults. On the basis of the typing of 24 ancestry-informative biallelic single-nucleotide-polymorphism markers, there was evidence of substantial population substructure and admixture. We used an allele-sharing-based clustering algorithm to infer evidence for four genetically distinct subpopulations. Using multivariable regression models, we demonstrate the complex interplay of genetic and socioeconomic factors on quantitative phenotypes related to cardiovascular disease and aging. Blood glucose level correlated with individual African ancestry, whereas body mass index was associated more strongly with genetic similarity. Blood pressure, HDL cholesterol level, C-reactive protein level, and carotid wall thickness were not associated with genetic background. Blood pressure and HDL cholesterol level varied by geographic site, whereas C-reactive protein level differed by occupation. Both ancestry and genetic similarity predicted the number and quality of years lived during follow-up, but socioeconomic factors largely accounted for these associations. When the 24 genetic markers were tested individually, there were an excess number of marker-trait associations, most of which were attenuated by adjustment for genetic ancestry. We conclude that the genetic demography underlying older individuals who self identify as African American is complex, and that controlling for both genetic admixture and socioeconomic characteristics will be required in assessing genetic associations with chronic-disease-related traits in African Americans. Complementary methods that identify discrete subgroups on the basis of genetic similarity may help to further characterize the complex biodemographic structure of human populations.
Keywords: African Americans; Aged; Aging; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Genetics, Population; Genotype; Humans; Male; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Socioeconomic Factors

Progression and regression of sleep-disordered breathing with changes in weight: the Sleep Heart Health Study. - Newman, Anne B; Foster, Greg; Givelber, Rachel; Nieto, F Javier; Redline, Susan; Young, Terry (Arch Intern Med, 2005)
BACKGROUND: The relationship of weight changes to the incidence, progression, and remission of sleep-disordered breathing (SDB) is not well defined. This study aims to determine the relationship between change in weight and progression or remission of SDB by polysomnography. METHODS: We performed a longitudinal cohort study of the cardiovascular consequences of sleep apnea in diverse US communities. Sleep apnea and polysomnographic indicators of SDB were assessed 5 years apart. RESULTS: A total of 2968 men and women (mean age, 62 years) participated in the study. Men were more likely to have an increase in Respiratory Disturbance Index (RDI) with a given increase in weight than were women, and this was not explained by differences in starting weight, waist circumference, age, or ethnicity. In a linear regression analysis, both men and women had a greater increase in RDI with weight gain than a decrease in RDI with weight loss. In a categorical analysis of larger degrees of change, this sex difference was also evident. Associations were similar in diverse ethnic groups. However, SDB progressed over time, even in those with stable weight. CONCLUSION: Modest changes in weight were related to an increase or decrease in SDB, and this association was stronger in men than in women.
Keywords: Body Weights and Measures; Causality; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Humans; Linear Models; Male; Middle Aged; Obesity; Odds Ratio; Sex Distribution; Sleep Apnea Syndromes; United States; Weight Gain; Weight Loss

A prospective study of anemia status, hemoglobin concentration, and mortality in an elderly cohort: the Cardiovascular Health Study. - Zakai, Neil A; Katz, Ronit; Hirsch, Calvin; Shlipak, Michael G; Chaves, Paulo H M; Newman, Anne B; Cushman, Mary (Arch Intern Med, 2005)
BACKGROUND: Anemia is viewed as a negative prognostic factor in the elderly population; its independent impact on survival is unclear. METHODS: Baseline hemoglobin quintiles and anemia, as defined by the World Health Organization criteria, were assessed in relation to mortality in the Cardiovascular Health Study, a prospective cohort study with 11.2 years of follow-up of 5888 community-dwelling men and women 65 years or older, enrolled in 1989-1990 or 1992-1993 in 4 US communities. RESULTS: A total of 1205 participants were in the lowest hemoglobin quintile (<13.7 g/dL for men; <12.6 g/dL for women), and 498 (8.5%) were anemic (<13 g/dL for men; <12 g/dL for women). A reverse J-shaped relationship with mortality was observed; age-, sex-, and race-adjusted hazard ratios (95% confidence interval [CI]) in the first and fifth quintiles, compared with the fourth quintile, were 1.42 (95% CI, 1.25-1.62) and 1.24 (95% CI, 1.09-1.42). After multivariate adjustment, these hazard ratios were 1.33 (95% CI, 1.15-1.54) and 1.17 (95% CI, 1.01-1.36). The demographic- and fully-adjusted hazard ratios of anemia for mortality were 1.57 (95% CI, 1.38-1.78) and 1.38 (95% CI, 1.19-1.54). Adjustment for causes and consequences of anemia (renal function, inflammation, or frailty) did not reduce associations. CONCLUSIONS: Lower and higher hemoglobin concentrations and anemia by World Health Organization criteria were independently associated with increased mortality. The World Health Organization criteria did not identify risk as well as a lower hemoglobin value. Additional study is needed on the clinically valid definition for and causes of anemia in the elderly and on the increased mortality at the extremes of hemoglobin concentrations.
Keywords: Age Factors; Aged; Anemia; California; Female; Follow-Up Studies; Health Status; Hemoglobins; Humans; Male; Maryland; Multivariate Analysis; North Carolina; Observation; Pennsylvania; Prospective Studies; Risk Factors; Severity of Illness Index; Survival Rate

Risk factors for declining ankle-brachial index in men and women 65 years or older: the Cardiovascular Health Study. - Kennedy, Margaret; Solomon, Cam; Manolio, Teri A; Criqui, Michael H; Newman, Anne B; Polak, Joseph F; Burke, Gregory L; Enright, Paul; Cushman, Mary (Arch Intern Med, 2005)
BACKGROUND: An ankle-brachial index (ABI) of less than 0.9 is a noninvasive measure of lower extremity arterial disease and a predictor of cardiovascular events. Little information is available on longitudinal change in ABI or on risk factors for declining ABI in a community-based population. METHODS: To assess risk factors for ABI decline, we studied 5888 participants in the Cardiovascular Health Study cohort (men and women 65 years or older). We measured ABI in 1992-1993 and again in 1998-1999. At baseline, we excluded individuals with an ABI less than 0.9, ABI greater than 1.4, or confirmed symptomatic lower extremity arterial disease (n = 823). The group with ABI decline included 218 participants with decline greater than 0.15 and to 0.9 or less. The comparison group comprised the remaining 2071 participants with follow-up ABI. RESULTS: The percentage of participants with ABI decline was 9.5% over 6 years of follow-up. The mean +/- SD decline was 0.33 +/- 0.12 in cases of ABI decline and 0.02 +/- 0.13 in non-cases. Independent predictors of ABI decline, reported as odds ratios, were age, 1.96 (95% confidence interval [CI], 1.42-2.71) for 75 to 84 years and 3.79 (95% CI, 1.36-10.5) for those older than 85 years compared with those younger than 75 years; current cigarette use, 1.74 (95% CI, 1.02-2.96); hypertension, 1.64 (95% CI, 1.18-2.28); diabetes, 1.77 (95% CI, 1.14-2.76); higher low-density lipoprotein cholesterol level, 1.60 (95% CI, 1.03-2.51), and lipid-lowering drug use 1.74 (95% CI, 1.05-2.89). CONCLUSION: Worsening lower extremity arterial disease, assessed as ABI decline, occurred in 9.5% of this elderly cohort over 6 years and was associated with modifiable vascular disease risk factors.
Keywords: Aged; Aged, 80 and over; Ankle; Brachial Artery; Cardiovascular Diseases; Female; Humans; Male; Peripheral Vascular Diseases; Risk Assessment; Risk Factors

Sleepiness in patients with moderate to severe sleep-disordered breathing. - Kapur, Vishesh K; Baldwin, Carol M; Resnick, Helaine E; Gottlieb, Daniel J; Nieto, F Javier (Sleep, 2005)
BACKGROUND: Population-based studies suggest that complaints of sleepiness are absent in many individuals with sleep-disordered breathing. We investigated the prevalence of sleepiness as well as factors associated with sleepiness in individuals with moderate to severe sleep-disordered breathing (apnea-hypopnea index > or = 15). DESIGN: Cross-sectional study. SETTING: The Sleep Heart Health Study. PARTICIPANTS: Sleep Heart Health Study participants (N = 6440). MEASUREMENTS AND RESULTS: Sleepiness was defined as an Epworth Sleepiness Scale score >10 or a report of at least frequently feeling unrested or sleepy. Forty-six percent of participants with moderate to severe sleep-disordered breathing (n = 1149) reported sleepiness. Characteristics associated with sleepiness after adjustment for confounders included presence of respiratory disease, shorter self-reported weekday and weekend sleep, sleep durations, complaints of insufficient sleep, complaints of sleep maintenance insomnia, early morning awakening, habitual snoring, and complaints of awakening with leg cramps or leg jerks. Some respiratory polysomnography measures were associated with sleepiness, but sleep-stage percentages and measures of sleep disruption were not. CONCLUSIONS: In this community-based cohort, subjective sleepiness is absent in many individuals with significant sleep-disordered breathing. Comorbid conditions, including respiratory disease, sleep restriction, insomnia, and nocturnal leg complaints, are important risk factors for sleepiness in individuals with moderate to severe sleep-disordered breathing.
Keywords: Aged; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Oxygen; Polysomnography; Prevalence; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Arousal Disorders; Sleep Stages; Surveys and Questionnaires

Statin use and the risk of incident dementia: the Cardiovascular Health Study. - Rea, Thomas D; Breitner, John C; Psaty, Bruce M; Fitzpatrick, Annette L; Lopez, Oscar L; Newman, Anne B; Hazzard, William R; Zandi, Peter P; Burke, Gregory L; Lyketsos, Constantine G; Bernick, Charles; Kuller, Lewis H (Arch Neurol, 2005)
BACKGROUND: Statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) reduce cardiovascular risk through mechanisms that might affect the development of dementia. OBJECTIVE: To evaluate whether statin use is associated with a lower risk of dementia compared with never use of lipid-lowering agents (LLAs). DESIGN: Cohort study of community-dwelling adults 65 years and older. The analysis included 2798 participants free of dementia at baseline. MAIN OUTCOME MEASURES: Using Cox proportional hazards regression analysis, we estimated the risk of incident all-cause and type-specific dementia associated with time-dependent statin therapy compared with never use of LLAs. The primary analyses incorporated a 1-year lag between exposure and outcome. Secondary analyses included the final year of exposure and modeled statin use as current use vs nonuse to simulate a case-control approach. RESULTS: Compared with never use of LLAs, ever use of statins was not associated with the risk of all-cause dementia (multivariable-adjusted hazard ratio [HR], 1.08; 95% confidence interval [CI], 0.77-1.52), Alzheimer disease alone (HR, 1.21; 95% CI, 0.76-1.91), mixed Alzheimer disease and vascular dementia (HR, 0.87; 95% CI, 0.44-1.72), or vascular dementia alone (HR, 1.36; 95% CI, 0.61-3.06). In contrast, in secondary analyses, current use of statins compared with nonuse of LLAs was associated with HRs of 0.69 (95% CI, 0.46-1.02) for all-cause dementia and 0.56 (95% CI, 0.35-0.92) for any Alzheimer disease. CONCLUSIONS: In this cohort study, statin therapy was not associated with a decreased risk of dementia. Methodological differences may explain why results of this cohort investigation differ from those of prior case-control studies. Additional investigation is needed to determine whether and for whom statin use may affect dementia risk.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hyperlipidemias; Male

Subclinical brain magnetic resonance imaging abnormalities predict physical functional decline in high-functioning older adults. - Rosano, Caterina; Kuller, Lewis H; Chung, Hyoju; Arnold, Alice M; Longstreth, William T; Newman, Anne B (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether severity of subclinical brain magnetic resonance imaging (MRI) abnormalities predicts incident self-reported physical impairment or rate of decline in motor performance. DESIGN: Longitudinal analysis, average follow-up time: 4.0 years. SETTING: Cardiovascular Health Study (CHS). PARTICIPANTS: CHS participants with modified Mini-Mental State Examination (3MS) score of 80 or greater, no self-reported disability, no history of stroke, and at least one assessment of mobility (n=2,450, mean age=74.4). MEASUREMENTS: Brain MRI abnormalities (ventricular enlargement, white matter hyperintensities, subcortical and basal ganglia small brain infarcts), self-reported physical impairment (difficulty walking half a mile or with one or more activities of daily living), and motor performance (gait speed, timed chair stand). RESULTS: After adjusting for demographics, cardiovascular risk factors, and diseases, risk of incident self-reported physical impairment was 35% greater for those with severe ventricular enlargement than for those with minimal ventricular enlargement, 22% greater for those with moderate white matter hyperintensities than for those with minimal white matter hyperintensities, and 26% greater for participants with at least one brain infarct than for those with no infarcts. Those with moderate to severe brain abnormalities experienced faster gait speed decline (0.02 m/s per year) than those with no MRI abnormalities (0.01 m/s per year). Further adjustment for incident stroke, incident dementia, and 3MS score did not substantially attenuate hazard ratios for incident self-reported physical impairment or coefficients for decline in gait speed. CONCLUSION: Subclinical structural brain abnormalities in high-functioning older adults can increase the risk of developing physical disabilities and declining in motor performance.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Brain; Female; Follow-Up Studies; Gait; Humans; Incidence; Magnetic Resonance Imaging; Male; Proportional Hazards Models; Psychomotor Disorders; Risk Factors; United States

Too much or too little step width variability is associated with a fall history in older persons who walk at or near normal gait speed. - Brach, Jennifer S; Berlin, Jaime E; VanSwearingen, Jessie M; Newman, Anne B; Studenski, Stephanie A (J Neuroeng Rehabil, 2005)
BACKGROUND: Decreased gait speed and increased stride time, stride length, double support time, and stance time variability have consistently been associated with falling whereas step width variability has not been strongly related to falls. The purpose was to examine the linear and nonlinear associations between gait variability and fall history in older persons and to examine the influence of gait speed. METHODS: Gait characteristics and fall history were obtained in 503 older adults (mean age = 79; 61% female) participating in the Cardiovascular Health Study who could ambulate independently. Gait characteristics were recorded from two trials on a 4 meter computerized walkway at the subject's self-selected walking speed. Gait variability was calculated as the coefficient of variation. The presence of a fall in the past 12 months was determined by interview. The nonlinear association between gait variability and fall history was examined using a simple three level classification derived from the distribution of the data and from literature based cut-points. Multivariate logistic regression was used to examine the association between step width variability (extreme or moderate) and fall history stratifying by gait speed (1.0 m/s) and controlling for age and gender. RESULTS: Step length, stance time, and step time variability did not differ with respect to fall history (p > .33). Individuals with extreme step width variability (either low or high step width variability) were more likely to report a fall in the past year than individuals with moderate step width variability. In individuals who walked > or = 1.0 m/s (n = 281), after controlling for age, gender, and gait speed, compared to individuals with moderate step width variability individuals with either low or high step width variability were more likely to have fallen in the past year (OR and 95% CI 4.38 [1.79-10.72]). The association between step width variability and fall history was not significant in individuals who walked < 1.0 m/s (n = 224). CONCLUSION: Extreme (either too little or too much) step width variability is associated with falls in the past year in older persons who walk at or near normal gait speed and not in older persons who walk slowly (< 1.0 m/s).

The association of markers of inflammation with weight change in older adults: the Cardiovascular Health Study. - Barzilay, J I; Forsberg, C; Heckbert, S R; Cushman, M; Newman, A B (Int J Obes (Lond), 2006)
OBJECTIVE: Elevated levels of inflammation factors often precede weight loss and may be causally related to it. Newer studies suggest that elevated levels of inflammation factors also precede weight gain. In this study, we examined whether inflammation factors are elevated in individuals, age >or=65 years, who lost or gained >5% weight over a 3 year follow-up period compared to those with stable weight. SUBJECTS: In total, 3254 participants in the Cardiovascular Health Study whose weight was stable; 661 who gained >5% weight; and 842 who lost >5% weight. MEASUREMENTS: C-reactive protein (CRP), fibrinogen, factor VIIIc, white blood cell (WBC) and platelet counts, and interleukin-6 (IL-6) levels. RESULTS: As compared to participants whose weight was stable, those who lost >5% weight had higher baseline CRP concentration (1.05 (95% CI, 1.02, 1.08) per interquartile increase) and WBC count (1.10 (1.01, 1.19) per interquartile increase) on adjusted analyses. Those who gained >5% weight had higher baseline CRP (1.05 (1.01, 1.08)), fibrinogen (1.13 (1.01, 1.27)), and factor VIIIc (1.15 (1.03, 1.30)). CONCLUSIONS: Inflammation factors are associated with weight gain and weight loss in older individuals. These findings suggest that subclinical inflammation, or unknown factors associated with subclinical inflammation, contribute to weight change.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Factor VIII; Female; Fibrinogen; Humans; Inflammation; Interleukin-6; Leukocyte Count; Male; Platelet Count; Weight Gain; Weight Loss

Association of nocturnal arrhythmias with sleep-disordered breathing: The Sleep Heart Health Study. - Mehra, Reena; Benjamin, Emelia J; Shahar, Eyal; Gottlieb, Daniel J; Nawabit, Rawan; Kirchner, H Lester; Sahadevan, Jayakumar; Redline, Susan (Am J Respir Crit Care Med, 2006)
RATIONALE: Sleep-disordered breathing recurrent intermittent hypoxia and sympathetic nervous system activity surges provide the milieu for cardiac arrhythmia development. OBJECTIVE: We postulate that the prevalence of nocturnal cardiac arrhythmias is higher among subjects with than without sleep-disordered breathing. METHODS: The prevalence of arrhythmias was compared in two samples of participants from the Sleep Heart Health Study frequency-matched on age, sex, race/ethnicity, and body mass index: (1) 228 subjects with sleep-disordered breathing (respiratory disturbance index>or=30) and (2) 338 subjects without sleep-disordered breathing (respiratory disturbance index<5). RESULTS: Atrial fibrillation, nonsustained ventricular tachycardia, and complex ventricular ectopy (nonsustained ventricular tachycardia or bigeminy or trigeminy or quadrigeminy) were more common in subjects with sleep-disordered breathing compared with those without sleep-disordered breathing: 4.8 versus 0.9% (p=0.003) for atrial fibrillation; 5.3 versus 1.2% (p=0.004) for nonsustained ventricular tachycardia; 25.0 versus 14.5% (p=0.002) for complex ventricular ectopy. Compared with those without sleep-disordered breathing and adjusting for age, sex, body mass index, and prevalent coronary heart disease, individuals with sleep-disordered breathing had four times the odds of atrial fibrillation (odds ratio [OR], 4.02; 95% confidence interval [CI], 1.03-15.74), three times the odds of nonsustained ventricular tachycardia (OR, 3.40; 95% CI, 1.03-11.20), and almost twice the odds of complex ventricular ectopy (OR, 1.74; 95% CI, 1.11-2.74). A significant relation was also observed between sleep-disordered breathing and ventricular ectopic beats/h (p<0.0003) considered as a continuous outcome. CONCLUSIONS: Individuals with severe sleep-disordered breathing have two- to fourfold higher odds of complex arrhythmias than those without sleep-disordered breathing even after adjustment for potential confounders.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Circadian Rhythm; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Middle Aged; Odds Ratio; Polysomnography; Prevalence; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea, Obstructive

Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima

The association of race with frailty: the cardiovascular health study. - Hirsch, Calvin; Anderson, Melissa L; Newman, Anne; Kop, Willem; Jackson, Sharon; Gottdiener, John; Tracy, Russell; Fried, Linda P (Ann Epidemiol, 2006)
PURPOSE: Frailty, which has been conceptualized as a state of decreased physiologic reserve contributing to functional decline, has a prevalence among older African Americans that is twice that in older whites. This study assesses the independent contribution of race to frailty. METHODS: We evaluated 786 African-American and 4491 white participants of the Cardiovascular Health Study (CHS). Frailty is defined as meeting three or more of five criteria derived from CHS measures: lowest quintile for grip strength, self-reported exhaustion, unintentional weight loss of 10 lbs or greater in 1 year, slowest quintile for gait speed, and lowest quintile for physical activity. Controlling for age, sex, comorbidity, socioeconomic factors, and race, multinomial logistic regression estimated the odds ratio (OR) of prefrail (one or two criteria) to not frail and frail to not frail. RESULTS: Among African Americans, 8.7% of men and 15.0% of women were frail compared with 4.6% and 6.8% of white men and women, respectively. In adjusted models, nonobese African Americans had a fourfold greater odds of frailty compared with whites. The increased OR of frailty associated with African-American race was less pronounced among those who were obese or disabled. CONCLUSION: African-American race is associated independently with frailty.
Keywords: African Americans; Aged; Asthenia; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Frail Elderly; Health Status; Humans; Male; Middle Aged; Motor Activity; Odds Ratio; United States; Weight Loss

Association of usual sleep duration with hypertension: the Sleep Heart Health Study. - Gottlieb, Daniel J; Redline, Susan; Nieto, F Javier; Baldwin, Carol M; Newman, Anne B; Resnick, Helaine E; Punjabi, Naresh M (Sleep, 2006)
STUDY OBJECTIVES: Limited experimental data suggest that sleep restriction acutely elevates blood pressure; however, little is known about the relationship between usual sleep duration and hypertension. This study assesses the relationship between usual sleep duration and hypertension in a community-based cohort. DESIGN: Cross-sectional observational study. SETTING: The Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. PARTICIPANTS: Two thousand eight hundred thirteen men and 3097 women, aged 40 to 100 years. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: Usual weekday and weekend sleep durations were obtained by questionnaire, and their weighted average were categorized as less than 6, 6 to less than 7, 7 to less than 8, 8 to less than 9, and 9 or more hours per night. Hypertension was defined as a systolic blood pressure of 140 mm Hg or greater, a diastolic blood pressure of 90 mm Hg or greater, or use of medication to treat hypertension. The relationship between sleep duration and hypertension was examined using categorical logistic regression with adjustment for age, sex, race, apnea-hypopnea index, and body mass index. Compared to subjects sleeping 7 to less than 8 hours per night, those sleeping less than 6 and between 6 and 7 hours per night had adjusted odds ratios for hypertension of 1.66 (95% confidence interval 1.35-2.04) and 1.19 (1.02-1.39), respectively, whereas those sleeping between 8 and 9 and 9 or more hours per night had adjusted odds ratios for hypertension of 1.19 (1.04-1.37) and 1.30 (1.04-1.62), respectively (p < .0001 for association of sleep duration with hypertension). These associations persisted when analyses were further adjusted for caffeine and alcohol consumption, current smoking, insomnia symptoms, depression symptoms, sleep efficiency, and prevalent diabetes mellitus or cardiovascular disease. CONCLUSIONS: Usual sleep duration above or below the median of 7 to less than 8 hours per night is associated with an increased prevalence of hypertension, particularly at the extreme of less than 6 hours per night.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Health Surveys; Humans; Hypertension; Male; Middle Aged; Odds Ratio; Prospective Studies; Sleep; Sleep Apnea, Obstructive; Sleep Deprivation; Statistics as Topic

Cardiovascular morbidity and mortality in community-dwelling elderly individuals with calcification of the fibrous skeleton of the base of the heart and aortosclerosis (The Cardiovascular Health Study). - Barasch, Eddy; Gottdiener, John S; Marino Larsen, Emily K; Chaves, Paulo H M; Newman, Anne B (Am J Cardiol, 2006)
In the elderly, mitral annular calcification (MAC) and aortic valve sclerosis (AVS) are associated with increased cardiovascular morbidity and mortality. Aortic annular calcification (AAC) commonly occurs with MAC. However, the prognostic value of AAC, singly or in combination with MAC and AVS, for incident cardiovascular disease and mortality is unknown. From the Cardiovascular Health Study, we analyzed 3,782 participants (76 +/- 5 years of age, 60% women) who had an echocardiogram at the 1994 to 1995 examination and who were prospectively followed for an average of 6.6 years (range 0.01 to 8.5). All 3 calcification categories were associated with incident congestive heart failure (MAC: hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.35 to 2.18, AAC: HR 1.62, 95% CI 1.28 to 2.06, and AVS: HR 1.50, 95% CI 1.19 to 1.89) and death. A stronger association with incident cardiovascular disease and mortality was observed with a larger number of calcification categories and with increased MAC severity. Moreover, in the participants with prevalent cardiovascular disease at echocardiographic examination (n = 1,054), MAC and AAC were still associated with cardiovascular mortality (MAC: HR 1.91, 95% CI 1.04 to 3.50; AAC: HR 2.11, 95% CI 1.16 to 3.85) even in fully adjusted models. In conclusion, MAC, AAC, and AVS are associated with a significant risk of incident congestive heart failure, cardiovascular and all-cause mortalities, and worse outcome in older patients with preexisting cardiovascular disease. Elderly patients with these findings represent a high-risk group and may require close medical attention.
Keywords: Aged; Aortic Valve; Calcinosis; Echocardiography; Female; Follow-Up Studies; Heart Failure; Heart Valve Diseases; Humans; Male; Mitral Valve; Prospective Studies; Risk Factors; Sclerosis; Severity of Illness Index; United States

Clinical significance of calcification of the fibrous skeleton of the heart and aortosclerosis in community dwelling elderly. The Cardiovascular Health Study (CHS). - Barasch, Eddy; Gottdiener, John S; Larsen, Emily K Marino; Chaves, Paulo H M; Newman, Anne B; Manolio, Teri A (Am Heart J, 2006)
BACKGROUND: Mitral annular calcification (MAC), aortic annular calcification (AAC), and aortic valve sclerosis (AVS) are associated with aging, and MAC and AVS are markers of advanced atherosclerosis. No studies have examined the prevalence and the clinical relevance of all 3 forms of calcification in a single free-living elderly population. METHODS: We used 2-dimensional echocardiography to evaluate MAC, AAC, AVS and all 3 combined in 3929 participants, mean age 76 +/- 5 years, 60% women, in the Cardiovascular Health Study, a prospective community-based observational study designed to assess cardiovascular disease (CVD) risk factors and outcomes in elderly persons. RESULTS: Mitral annular calcification was found in 1640 (42 %) subjects, AAC in 1710 (44 %), AVS in 2114 (54 %), and all 3 combined in 662 (17 %). The participants with these findings were older than those without them, and those with MAC had worse cardiovascular, renal, metabolic, and functional profile than those with AAC and AVS. Age-, sex-, and race-adjusted logistic regression analysis found a significant association between the 3 calcification categories and CVD, the strongest being between the combined group with congestive heart failure (odds ratio 2.04, 95% CI 1.34-3.09). In highly adjusted models, only MAC was associated with CVD, and the strength of association was related to the severity of MAC. CONCLUSIONS: In free-living elderly, MAC, AAC, and AVS are highly prevalent and are associated with CVD. Mitral annular calcification in particular has strong association with CVD, and with an adverse biomedical profile.
Keywords: Aged; Aortic Valve; Calcinosis; Female; Heart Valve Diseases; Humans; Male; Mitral Valve; Prevalence; Prospective Studies; Risk Factors; Sclerosis; Ultrasonography

Comparison of mortality risk for electrocardiographic abnormalities in men and women with and without coronary heart disease (from the Cardiovascular Health Study). - Rautaharju, Pentti M; Ge, Sijian; Nelson, Jennifer C; Marino Larsen, Emily K; Psaty, Bruce M; Furberg, Curt D; Zhang, Zhu-Ming; Robbins, John; Gottdiener, John S; Chaves, Paulo H M (Am J Cardiol, 2006)
Mortality risk associated with electrocardiographic (ECG) abnormalities has been commonly reported to be lower in women than in men. We compared coronary heart disease (CHD) and all-cause mortality risk for ECG variables during a mean 9.1-year follow-up in 4,912 participants in the Cardiovascular Health Study who were > or = 65 years of age. The hypothesis was that mortality risk for ECG abnormalities is not lower in women than in men. Five ECG variables were significant mortality predictors in Cox regression models that were adjusted for demographic, clinical, and medication variables. Gender differences were significant and mortality risk was higher in women for ECG estimates of left ventricular mass for both end points and for nondipolar QRS voltage for all-cause mortality. When evaluated simultaneously in multiple ECG variable risk models in subgroups that were stratified by baseline CHD status, no gender difference was significant. In the latter models, ST depression was a strong predictor of CHD mortality in groups with and without previous CHD. Other significant ECG predictors were previous myocardial infarction in the previous CHD group and nondipolar QRS voltage in the CHD-free group. Four ECG abnormalities were significant predictors of all-cause mortality in the CHD-free group, with risk increases of 18% to 50%. The risk of all-cause mortality in the previous CHD group was significantly increased for ST depression (by 64%), the ECG estimate of left ventricular mass (by 48%), and previous myocardial infarction (by 34%). In conclusion, we found no evidence that the relative risk of mortality for ECG abnormalities is lower in women than in men.
Keywords: Aged; Coronary Disease; Electrocardiography; Female; Humans; Male; Risk

A cross-sectional study of vitamin C and cognitive function in older adults: the differential effects of gender. - Sato, R; Helzlsouer, K J; Comstock, G W; Hoffman, S C; Norkus, E P; Fried, L P (J Nutr Health Aging, 2006)
Previous studies have suggested that vitamin C status may be associated with cognitive function in community-dwelling populations. However, this has not been consistent across all studies due to methodological differences. This cross-sectional study assessed the association between vitamin C and cognitive function in 544 community-dwelling older adults aged 65 or older who participated in both the Cardiovascular Health Study (CHS) and the CLUE II study in 1989. Three percent of the subjects had low plasma vitamin C concentrations (< 40 mg/dL) and 15% had low total vitamin C intake (< 60 mg/day). Most participants (96.7 percent) had normal cognitive function. In the unadjusted analyses, the highest fifth of plasma vitamin C concentration was associated with better Digit Symbol Substitution Test (DSST) scores and marginally associated with Mini-Mental State Examination (MMSE) compared to the lowest fifth. Total vitamin C intake, measured by Block's food frequency questionnaire, was generally associated with higher MMSE scores, though it was not significant. Adjusting for numerous factors did not substantially change results. In a stratified analysis by gender, higher plasma concentrations or intake were associated with higher MMSE scores for men but not for women. These mixed results do not provide strong evidence of an association between vitamin C concentrations or intake and cognitive function.
Keywords: Aged; Aging; Ascorbic Acid; Cognition; Cross-Sectional Studies; Diet; Female; Health Surveys; Humans; Male; Mental Status Schedule; Nutrition Surveys; Nutritional Requirements; Sex Factors; Surveys and Questionnaires

Cystatin C and prognosis for cardiovascular and kidney outcomes in elderly persons without chronic kidney disease. - Shlipak, Michael G; Katz, Ronit; Sarnak, Mark J; Fried, Linda F; Newman, Anne B; Stehman-Breen, Catherine; Seliger, Stephen L; Kestenbaum, Brian; Psaty, Bruce; Tracy, Russell P; Siscovick, David S (Ann Intern Med, 2006)
BACKGROUND: Cystatin C is an alternative measure of kidney function that may have prognostic importance among elderly persons who do not meet standard criteria for chronic kidney disease (estimated glomerular filtration rate [GFR] > or =60 mL/min per 1.73 m2). OBJECTIVE: To evaluate cystatin C as a prognostic biomarker for death, cardiovascular disease, and incident chronic kidney disease among elderly persons without chronic kidney disease. DESIGN: Cohort study. SETTING: The Cardiovascular Health Study, a population-based cohort recruited from 4 communities in the United States. PARTICIPANTS: 4663 elderly persons. MEASUREMENTS: Measures of kidney function were creatinine-based estimated GFR by using the Modification of Diet in Renal Disease equation and cystatin C concentration. Outcomes were death, cardiovascular death, noncardiovascular death, heart failure, stroke, myocardial infarction, and incident chronic kidney disease during follow-up (median, 9.3 years). RESULTS: At baseline, 78% of participants did not have chronic kidney disease (estimated GFR > or =60 mL/min per 1.73 m2) and mean cystatin C concentration, creatinine concentration, and estimated GFR were 1.0 mg/L, 79.6 micromol/L (0.9 mg/dL), and 83 mL/min per 1.73 m2, respectively. Cystatin C concentrations (per SD, 0.18 mg/L) had strong associations with death (hazard ratio, 1.33 [95% CI, 1.25 to 1.40]), cardiovascular death (hazard ratio, 1.42 [CI, 1.30 to 1.54]), noncardiovascular death (hazard ratio, 1.26 [CI, 1.17 to 1.36]), incident heart failure (hazard ratio, 1.28 [CI, 1.17 to 1.40]), stroke (hazard ratio, 1.22 [CI, 1.08 to 1.38]), and myocardial infarction (hazard ratio, 1.20 [CI, 1.06 to 1.36]) among these participants. Serum creatinine concentrations had much weaker associations with each outcome and only predicted cardiovascular death. Participants without chronic kidney disease who had elevated cystatin C concentrations (> or =1.0 mg/L) had a 4-fold risk for progressing to chronic kidney disease after 4 years of follow-up compared with those with cystatin C concentrations less than 1.0 mg/L. LIMITATIONS: Because this study did not directly measure GFR or albuminuria, the extent to which cystatin C may be influenced by nonrenal factors was not determined and participants with albuminuria might have been misclassified as having no kidney disease. CONCLUSIONS: Among elderly persons without chronic kidney disease, cystatin C is a prognostic biomarker of risk for death, cardiovascular disease, and chronic kidney disease. In this setting, cystatin C seems to identify a "preclinical" state of kidney dysfunction that is not detected with serum creatinine or estimated GFR.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Cystatins; Glomerular Filtration Rate; Humans; Kidney; Longitudinal Studies; Prognosis; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors

Education and the cognitive decline associated with MRI-defined brain infarct. - Elkins, J S; Longstreth, W T; Manolio, T A; Newman, A B; Bhadelia, R A; Johnston, S C (Neurology, 2006)
OBJECTIVE: To assess whether educational attainment, a correlate of cognitive reserve, predicts the amount of cognitive decline associated with a new brain infarct. METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of people aged 65 years and older. Cognitive function was measured annually using the Modified Mini-Mental State Examination (3MS) and the Digit-Symbol Substitution Test (DSST). The authors tested whether education level modified 1) the cross-sectional association between cognitive performance and MRI-defined infarct and 2) the change in cognitive function associated with an incident infarct at a follow-up MRI. RESULTS: In cross-sectional analysis (n = 3,660), MRI-defined infarct was associated with a greater impact on 3MS performance in the lowest education quartile when compared with others (p for heterogeneity = 0.012). Among those with a follow-up MRI who had no infarct on initial MRI (n = 1,433), education level was not associated with the incidence, size, or location of new brain infarct. However, a new MRI-defined infarct predicted substantially greater decline in 3MS scores in the lowest education group compared with the others (6.3, 95% CI 4.4- to 8.2-point decline vs 1.7, 95% CI 0.7- to 2.7-point decline; p for heterogeneity < 0.001). Higher education was not associated with smaller declines in DSST performance in the setting of MRI-defined infarct. CONCLUSIONS: Education seems to modify an individual's decline on a test of general cognitive function when there is incident brain infarct. These findings are consistent with the hypothesis that cognitive reserve influences the impact of vascular injury in the brain.
Keywords: Cerebral Infarction; Cognition Disorders; Cross-Sectional Studies; Educational Status; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Neuropsychological Tests

Factors associated with geographic variations in stroke incidence among older populations in four US communities. - El-Saed, Aiman; Kuller, Lewis H; Newman, Anne B; Lopez, Oscar; Costantino, Joseph; McTigue, Kathleen; Cushman, Mary; Kronmal, Richard (Stroke, 2006)
BACKGROUND AND PURPOSE: In the Cardiovascular Health Study (CHS), we previously observed lower stroke incidence in Allegheny County, PA compared with the other 3 study sites. The purpose of this study was to study possible reasons for the lower stroke incidence in Allegheny County. METHODS: CHS participants 65 years or older who were stroke-free at baseline (n=5639) were followed between 1989 to 1990 and 2000 for the development of stroke. Risk factors at baseline and their subsequent control were compared among both groups. Site-specific hazard ratios for stroke incidence were calculated using Cox regression models. RESULTS: The unadjusted hazard ratio for total stroke incidence in Forsyth County, NC; Sacramento County, CA; and Washington County, MD combined compared with Allegheny County, PA was 1.74 (95% CI: 1.42, 2.14). After adjustment for age and other traditional risk factors, there was modest reduction of the excess hazard in non-Allegheny sites compared with Allegheny County (hazard ratio=1.52, 95% CI: 1.17, 1.98). Between baseline and the seventh-year visits, control of hypertension, diabetes, lipids, smoking, atrial fibrillation and transient ischemic attack were similar across sites. White matter grade > or = 3 on the baseline brain MRI was less common in Allegheny County (25.8% versus 36.3%, respectively; P<0.001) and accounted for 25% of the excess hazard in non-Allegheny sites compared with Allegheny County. CONCLUSIONS: Site differences in stroke risk factors at baseline and subsequent control only partially explain site differences in stroke incidence. White matter grade as a possible integrated measure of exposure and control of risk factors may help in explaining geographic variations in stroke incidence.
Keywords: Aged; Brain; California; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Maryland; North Carolina; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke

Geographic variations in stroke incidence and mortality among older populations in four US communities. - El-Saed, Aiman; Kuller, Lewis H; Newman, Anne B; Lopez, Oscar; Costantino, Joseph; McTigue, Kathleen; Cushman, Mary; Kronmal, Richard (Stroke, 2006)
BACKGROUND AND PURPOSE: Stroke is a leading cause of death and disability in the US. There is limited data on geographic variations in stroke incidence among older US populations who experience the majority of stroke burden. The purpose of this study was to compare stroke incidence and mortality rates in 4 US communities. METHODS: Participants in the Cardiovascular Health Study (CHS) who had no history of stroke at baseline (n=5639) were followed for 10 or 7 years in predominantly white (n=5002) and black (n=637) participants, respectively. Incident stroke was validated by a stroke adjudication committee after ascertainment at annual visits, interim telephone contacts, and review of Medicare hospitalization data. RESULTS: The 2000 US population age and sex standardized total stroke incidence rate for all CHS participants was 17.7 per 1000 person-years (95% CI: 15.9, 19.5). The rate was significantly lower in Allegheny County, Pennsylvania 9.6/1000 person-years (95% CI: 7.7, 11.5) than Forsyth County, North Carolina 19.2/1000 person-years (95% CI: 15.6, 22.8), Sacramento County, California 20.7/1000 person-years (95% CI: 16.9, 24.5), and Washington County, Maryland 19.8/1000 person-years (95% CI: 16.1, 23.5). The lower stroke incidence rate in Allegheny County was consistent in gender, race, and age groups. Though not statistically significant, stroke mortality was also lower in Allegheny County than other 3 sites. The 1-month case fatality rate was similar in the 4 sites for all strokes, and by stroke types. CONCLUSIONS: Understanding geographic variations in stroke incidence may be an important step in improving preventive practices of stroke.
Keywords: Aged; Aged, 80 and over; California; Female; Humans; Incidence; Male; Maryland; North Carolina; Pennsylvania; Stroke

Kidney function predicts the rate of bone loss in older individuals: the Cardiovascular Health Study. - Fried, Linda F; Shlipak, Michael G; Stehman-Breen, Catherine; Mittalhenkle, Anuja; Seliger, Stephen; Sarnak, Mark; Robbins, John; Siscovick, David; Harris, Tamara B; Newman, Anne B; Cauley, Jane A (J Gerontol A Biol Sci Med Sci, 2006)
BACKGROUND: Results of cross-sectional analyses of the association of kidney function with bone mineral density (BMD) have been conflicting. We examined the association of cystatin-C, a new marker of kidney function that is unrelated to lean mass, with initial and follow-up BMD, in an ancillary study of the Cardiovascular Health Study, a population-based cohort of individuals > or = 65 years old. METHODS: Two years after measurement of cystatin-C and other covariates, the first BMD was measured in Pittsburgh, Pennsylvania and Davis, California, by using dual energy x-ray absorptiometry. Follow-up BMD was measured in Pittsburgh 4 years later. Associations of cystatin-C with initial BMD and the change in BMD (%/y) at the hip were examined with linear regression. Analyses were conducted separately for men and women. RESULTS: In 1519 participants who had cystatin-C and initial BMD assessed, 614 had follow-up BMD. The percent annual change in BMD at the total hip by cystatin-C quartiles was -0.24, -0.13, -0.40, and -0.66%/y (first to fourth quartile) in women and -0.02, -0.30, -0.18, and -0.94%/y in men. After adjusting for potential confounders, cystatin-C was marginally associated with initial BMD in men but not women. Cystatin-C was associated with bone loss in men; after adjustment for weight loss, cystatin-C was not associated with bone loss in women. CONCLUSION: Kidney dysfunction, as assessed by cystatin-C, is associated with a more rapid loss of BMD at the hip, especially in men. Further studies are needed to confirm these findings and to determine whether this loss leads to an elevated risk of fracture.
Keywords: Absorptiometry, Photon; Aged; Bone Density; Creatinine; Cystatin C; Cystatins; Female; Hip; Humans; Kidney Diseases; Kidney Function Tests; Linear Models; Longitudinal Studies; Male; Osteoporosis; Predictive Value of Tests

Mortality and cardiovascular risk across the ankle-arm index spectrum: results from the Cardiovascular Health Study. - O'Hare, Ann M; Katz, Ronit; Shlipak, Michael G; Cushman, Mary; Newman, Anne B (Circulation, 2006)
BACKGROUND: A low ankle-arm index (AAI) is a strong predictor of mortality and cardiovascular events. A high AAI also appears to be associated with higher mortality risk in select populations. However, mortality and cardiovascular risk across the AAI spectrum have not been described in a more broadly defined population. METHODS AND RESULTS: We examined total and cardiovascular mortality and cardiovascular events across the AAI spectrum among 5748 participants in the Cardiovascular Health Study (CHS). The mean age of the sample population was 73+/-6 years, and the sample included 3289 women (57%) and 883 blacks (15%). The median duration of follow-up was 11.1 (0.1 to 12) years for mortality and 9.6 (0.1 to 12.1) years for cardiovascular events. There were 2311 deaths (953 of which were cardiovascular) and 1491 cardiovascular events during follow-up. After adjustment for potential confounders, AAI measurements < or =0.60 (hazard ratio [HR] 1.82, 95% CI 1.42 to 2.32), 0.61 to 0.7 (HR 2.08, 95% CI 1.61 to 2.69), 0.71 to 0.8 (HR 1.80, 95% CI 1.44 to 2.26), 0.81 to 0.9 (HR 1.73 95% CI 1.43 to 2.11), 0.91 to 1.0 (HR 1.40, 95% CI 1.20 to 1.63), and >1.40 (HR 1.57, 95% CI 1.07 to 2.31) were associated with higher mortality risk from all causes compared with the referent group (AAI 1.11 to 1.20). The pattern was similar for cardiovascular mortality. For cardiovascular events, risk was higher at all AAI levels <1 but not for AAI levels >1.4 (HR 1.00, 95% CI 0.57 to 1.74). The association of a high AAI with mortality was stronger in men than in women and in younger than in older cohort members. CONCLUSIONS: In a cohort of community-dwelling elders, mortality risk was higher than the referent category of 1.11 to 1.2 among participants with AAI values above the traditional cutpoint of 0.9 (ie, 0.91 to 1.0 and >1.4), and the specific association of AAI with mortality varied by age and gender.
Keywords: Aged; Ankle; Arm; Blood Pressure; Body Mass Index; Cholesterol, LDL; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Risk Factors; Smoking

Quantitative measures of gait characteristics indicate prevalence of underlying subclinical structural brain abnormalities in high-functioning older adults. - Rosano, Caterina; Brach, Jennifer; Longstreth, William T; Newman, Anne B (Neuroepidemiology, 2006)
Abnormal gait in high-functioning older adults may indicate underlying subtle structural brain abnormalities. We tested the hypothesis that temporal and spatial parameters of gait, including speed, stride length and double support time, are cross-sectionally associated with white matter hyperintensity, subcortical infarcts or brain atrophy on brain MRI. We examined 321 men and women (mean age = 78.3) participating to the Cardiovascular Health Study who were free of dementia or stroke at the time of the gait assessment. Analyses were set with gait as independent variable and brain MRIs as dependent variables. Gait measures were determined from the footfalls recorded on a 4-meter-long instrumented walking surface, the GaitMat II. Brain MRIs were examined for the presence of white matter hyperintensity (WMG, graded from 0 to 9), brain infarcts (predominantly subcortical) and ventricular enlargement (graded from 0 to 9). Slower gait, shorter stride length and longer double support times were associated with greater prevalence of white matter grade > or =3 (p = 0.02), and at least 1 brain infarct (p = 0.04) independent of age. In multivariate logistic regression models adjusted for demographics and clinical cardiovascular diseases, those with gait speed <1.02 m/s were more likely to have WMG > or =3 and at least 1 brain infarct, compared with those with faster gait - odds ratio (OR): 2.85, 95% confidence interval (95% CI): 1.35, 6.02, and OR: 2.09, 95% CI: 1.04, 4.19. Shorter stride length was also associated with greater probability of having at least 1 brain infarct (gait stride <0.88 vs. >1.10 m: OR: 3.20, 95% CI: 1.49, 6.88), while longer double support times were associated with a greater probability of having WMG > or =3 (double support time >0.19 vs. <0.14 s: OR: 2.3, 95% CI: 1.1, 4.7) independent of demographics and clinical cardiovascular diseases. Gait parameters were not significantly associated with ventricular grade. In summary, in this group of high-functioning older adults, poorer gait speed, shorter stride and longer double support time are associated with high white matter disease and subclinical strokes.
Keywords: Aged; Brain; Cerebral Infarction; Cerebral Ventricles; Cerebrovascular Disorders; Cohort Studies; Dementia; Female; Gait; Gait Disorders, Neurologic; Humans; Hypertension; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke; United States

Sleep apnea in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the Sleep Heart Health Study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Hammond, Terese C; Sharief, Imran; Punjabi, Naresh M; Newman, Anne B (J Am Soc Nephrol, 2006)
Sleep-disordered breathing (SDB) has been noted commonly in hemodialysis (HD) patients, but it is not known whether this is related directly to the treatment of kidney failure with HD or to the higher prevalence of obesity and older age. Forty-six HD patients were compared with 137 participants from the Sleep Heart Health Study (SHHS) who were matched for age, gender, body mass index (BMI), and race. Home unattended polysomnography was performed and scored using similar protocols. The study sample was 62.7 +/- 10.1 yr, was predominantly male (72%) and white (63%), and had an average BMI of 28 +/- 5.3 kg/m(2). The HD sample had a higher systolic BP (137 versus 121 mmHg; P < 0.01) and a higher prevalence of diabetes (33 versus 9%; P < 0.01) and cardiovascular disease (33 versus 13%; P < 0.01) compared with the SHHS sample. The HD group had significantly less sleep time (320 versus 379 min; P < 0.0001) but similar sleep efficiency. HD patients had a higher frequency of arousals per hour (25.1 versus 17.1; P < 0.0001) and apnea-hypopneas per hour (27.2 versus 15.2; P < 0.0001) and greater percentage of the total sleep time below an oxygen saturation of 90% (7.2 versus 1.8; P < 0.0001). HD patients were more likely to have severe SDB (>30 respiratory events per hour) compared with the SHHS sample (odds ratio 4.07; 95% confidence interval 1.83 to 9.07). There was a strong association of HD with severe SDB and nocturnal hypoxemia independent of age, BMI, and the higher prevalence of chronic disease. The potential mechanisms for the higher likelihood of SDB in the HD population must be identified to provide specific prevention and therapy.
Keywords: Blood Pressure; Body Mass Index; Cardiovascular Diseases; Case-Control Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Kidney Failure, Chronic; Male; Middle Aged; Prevalence; Renal Dialysis; Severity of Illness Index; Sleep Apnea Syndromes

Association of kidney function with incident hip fracture in older adults. - Fried, Linda F; Biggs, Mary Louise; Shlipak, Michael G; Seliger, Stephen; Kestenbaum, Bryan; Stehman-Breen, Catherine; Sarnak, Mark; Siscovick, David; Harris, Tamara; Cauley, Jane; Newman, Anne B; Robbins, John (J Am Soc Nephrol, 2007)
Kidney dysfunction is associated with bone loss, and patients with ESRD have an increased risk for hip fracture. However, the association of mild to moderate kidney disease with hip fracture has not been studied previously. The association of kidney function with incident hip fracture was examined among participants in the Cardiovascular Health Study, a community-based cohort of older individuals. The primary measure of kidney function was serum cystatin C, a measure that does not depend on lean mass. Hip fractures were identified using International Classification of Diseases, Ninth Revision codes for hospitalizations. A total of 4699 individuals had cystatin C measured in 1992 to 1993 and did not have a hip fracture before cystatin C measurement. The association of kidney function with hip fracture was analyzed with Cox proportional hazards models. Analyses were conducted separately for men and women. After a mean follow-up of 7.1 yr, 195 incident hip fractures occurred in women and 79 occurred in men. Higher cystatin C levels were associated with a higher risk for fracture in women (hazard ratio [HR] 1.26; 95% confidence interval [CI] 1.14 to 1.38 per SD) and in men (HR 1.27; 95% CI 1.11 to 1.46). After multivariable adjustment, higher cystatin C levels were significantly associated with hip fracture in women (HR 1.16; 95% CI 1.01, 1.33) but not in men (HR 1.14; 95% CI 0.86 to 1.52), although the magnitude of the association was similar. Kidney dysfunction, as assessed by cystatin C, is associated with an increased risk for hip fracture. Further studies are needed to evaluate potential mediators of this relationship and to assess whether interventions can decrease this risk.
Keywords: Aged; Aged, 80 and over; Cystatin C; Cystatins; Female; Hip Fractures; Humans; Kidney; Kidney Failure, Chronic; Longitudinal Studies; Male; Osteoporosis; Prospective Studies; Risk Factors; Sex Factors

Clinical factors, but not C-reactive protein, predict progression of calcific aortic-valve disease: the Cardiovascular Health Study. - Novaro, Gian M; Katz, Ronit; Aviles, Ronnier J; Gottdiener, John S; Cushman, Mary; Psaty, Bruce M; Otto, Catherine M; Griffin, Brian P (J Am Coll Cardiol, 2007)
OBJECTIVES: The purpose of this study was to examine the relationship between C-reactive protein (CRP) and calcific aortic valve disease in a large, randomly selected, population-based cohort. BACKGROUND: The pathobiology of calcific aortic stenosis involves an active inflammatory, atheromatous, osteogenic process. Elevations in CRP, a measure of systemic inflammation, have been associated with aortic stenosis. METHODS: Two-dimensional and Doppler echocardiography and CRP measurement were performed at baseline in 5,621 participants in the Cardiovascular Health Study. Multivariable analysis was used to identify CRP as a predictor of baseline and incident aortic stenosis. RESULTS: At a mean echocardiographic follow-up of 5 years, 9% of subjects with aortic sclerosis progressed to some degree of aortic stenosis. Increasing age (odds ratio [OR] 1.13, 95% confidence interval [CI] 1.09 to 1.16; p < 0.001) and male gender (OR 3.05, 95% CI 1.76 to 5.27; p < 0.001) were related to risk of incident aortic stenosis, whereas increasing height (OR 0.96, 95% CI 0.94 to 0.99; p = 0.013) and African-American ethnicity conveyed a lower risk (OR 0.49, 95% CI 0.25 to 0.95; p = 0.035). C-reactive protein, treated as a continuous variable, was not associated with baseline aortic stenosis, progression to aortic sclerosis (adjusted OR 0.93, 95% CI 0.85 to 1.02; p = 0.107), or progression to aortic stenosis (adjusted OR 0.85, 95% CI 0.70 to 1.03; p = 0.092). CONCLUSIONS: In this large population-based cohort, approximately 9% of subjects with aortic sclerosis progressed to aortic stenosis over a 5-year follow-up period. There was no association between CRP levels and the presence of calcific aortic-valve disease or incident aortic stenosis. C-reactive protein appears to be a poor predictor of subclinical calcific aortic-valve disease.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; C-Reactive Protein; Calcinosis; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Follow-Up Studies; Heart Valve Diseases; Humans; Male; Risk Factors

Collaborative meta-analysis of individual participant data from observational studies of Lp-PLA2 and cardiovascular diseases. - Ballantyne, C; Cushman, M; Psaty, B; Furberg, C; Khaw, K T; Sandhu, M; Oldgren, J; Rossi, G P; Maiolino, G; Cesari, M; Lenzini, L; James, S K; et al. (Eur J Cardiovasc Prev Rehabil, 2007)
BACKGROUND: A large number of observational epidemiological studies have reported generally positive associations between circulating mass and activity levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and the risk of cardiovascular diseases. Few studies have been large enough to provide reliable estimates in different circumstances, such as in different subgroups (e.g., by age group, sex, or smoking status) or at different Lp-PLA2 levels. Moreover, most published studies have related disease risk only to baseline values of Lp-PLA2 markers (which can lead to substantial underestimation of any risk relationships because of within-person variability over time) and have used different approaches to adjustment for possible confounding factors. OBJECTIVES: By combination of data from individual participants from all relevant observational studies in a systematic 'meta-analysis', with correction for regression dilution (using available data on serial measurements of Lp-PLA2), the Lp-PLA2 Studies Collaboration will aim to characterize more precisely than has previously been possible the strength and shape of the age and sex-specific associations of plasma Lp-PLA2 with coronary heart disease (and, where data are sufficient, with other vascular diseases, such as ischaemic stroke). It will also help to determine to what extent such associations are independent of possible confounding factors and to explore potential sources of heterogeneity among studies, such as those related to assay methods and study design. It is anticipated that the present collaboration will serve as a framework to investigate related questions on Lp-PLA2 and cardiovascular outcomes. METHODS: A central database is being established containing data on circulating Lp-PLA2 values, sex and other potential confounding factors, age at baseline Lp-PLA2 measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of Lp-PLA2 and potential confounding factors has been sought to allow adjustment for possible confounding and correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available observational studies of Lp-PLA2 will yield information on a total of about 15 000 cardiovascular disease endpoints.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Cardiovascular Diseases; Humans; Phospholipases A2

The effect of different public health interventions on longevity, morbidity, and years of healthy life. - Diehr, Paula; Derleth, Ann; Cai, Liming; Newman, Anne B (BMC Public Health, 2007)
BACKGROUND: Choosing cost-effective strategies for improving the health of the public is difficult because the relative effects of different types of interventions are not well understood. The benefits of one-shot interventions may be different from the benefits of interventions that permanently change the probability of getting sick, recovering, or dying. Here, we compare the benefits of such types of public health interventions. METHODS: We used multi-state life table methods to estimate the impact of five types of interventions on mortality, morbidity (years of life in fair or poor health), and years of healthy life (years in excellent, very good, or good health). RESULTS: A one-shot intervention that makes all the sick persons healthy at baseline would increase life expectancy by 3 months and increase years of healthy life by 6 months, in a cohort beginning at age 65. An equivalent amount of improvement can be obtained from an intervention that either decreases the probability of getting sick each year by 12%, increases the probability of a sick person recovering by 16%, decreases the probability that a sick person dies by 15%, or decreases the probability that a healthy person dies by 14%. Interventions aimed at keeping persons healthy increased longevity and years of healthy life, while decreasing morbidity and medical expenditures. Interventions focused on preventing mortality had a greater effect on longevity, but had higher future morbidity and medical expenditures. Results differed for older and younger cohorts and depended on the value to society of an additional year of sick life. CONCLUSION: Interventions that promote health and prevent disease performed well, but other types of intervention were sometimes better. The value to society of interventions that increase longevity but also increase morbidity needs further research. More comprehensive screening and treatment of new Medicare enrollees might improve their health and longevity without increasing future medical expenditures.
Keywords: Actuarial Analysis; Cost-Benefit Analysis; Disease Management; Health Priorities; Health Promotion; Health Services; Health Status; Humans; Life Expectancy; Medicare; Models, Biological; Morbidity; United States; United States Public Health Service

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Ethnic-specific prevalence of peripheral arterial disease in the United States. - Allison, Matthew A; Ho, Elena; Denenberg, Julie O; Langer, Robert D; Newman, Anne B; Fabsitz, Richard R; Criqui, Michael H (Am J Prev Med, 2007)
BACKGROUND: Individuals diagnosed with peripheral arterial disease (PAD) are at increased risk for future functional limitations as well as cardiovascular morbidity and mortality. The aim of this study was to estimate the age-, gender-, and ethnic-specific burden of PAD in the United States for the year 2000. METHODS: Data were collected from seven community-based studies that assessed subjects for the presence of PAD using the ankle-brachial index (ABI). Using standardized weighting criteria, age-, gender-, and ethnic-specific prevalence rates were computed and then multiplied by the corresponding 2000 Census population totals to estimate the burden of PAD in the United States for that year. Evidence-based adjustments for studies which did not consider possible subclavian stenosis, prior revascularization for PAD, or both were employed. RESULTS: In 2000, it is conservatively estimated that at least 6.8 million (5.8%) individuals aged 40 years or older had PAD based on an ABI of less than 0.9 or previous revascularization for PAD, and that that there are an additional 1.7 million Americans with PAD but "normal" ABIs. Including this group gives a total of 8.5 million (7.2%) individuals with PAD. CONCLUSIONS: Roughly one in 16 individuals residing in the United States in 2000 who were aged 40 years and older had PAD. Clinicians are encouraged to screen for the presence of PAD using the ABI.
Keywords: Adult; Aged; Aged, 80 and over; Databases as Topic; Female; Humans; Male; Middle Aged; Peripheral Vascular Diseases; United States

Focal atrophy and cerebrovascular disease increase dementia risk among cognitively normal older adults. - Rosano, Caterina; Aizenstein, Howard J; Wu, Minjie; Newman, Anne B; Becker, James T; Lopez, Oscar L; Kuller, Lewis H (J Neuroimaging, 2007)
BACKGROUND AND PURPOSE: This study investigated the association of medial temporal lobe (MTL) atrophy and cerebrovascular disease (white matter hyperintensities [WMH], subclinical infarcts) with the risk of developing Alzheimer's disease (AD) among cognitively normal older adults. METHODS: Risk of developing AD was examined for 155 cognitively normal older adults (77.4 years, 60% women, 81% white). The MTL volumes and the presence of WMH and of subclinical infarcts were determined from brain magnetic resonance imaging (MRI) at the beginning of the study. Follow-up cognitive evaluations (average 4.3 years) identified those who developed AD. RESULTS: The presence of either MTL atrophy or subclinical infarcts was independently and significantly associated with a greater risk to develop AD (OR [95% CI]: 4.4 [1.5, 12.3] and 2.7 [1.0, 7.1], respectively). In addition, those participants with both MTL atrophy and at least one brain infarct had a 7-fold increase in the risk of developing AD (OR [95% CI]: 7.0 [1.5, 33.1]), compared to those who had neither of these conditions. CONCLUSIONS: In cognitively normal older adults, markers of neurodegeneration (as reflected by MTL atrophy) and of cerebrovascular disease (as reflected by infarcts on MRI) independently contribute to the risk to develop AD.
Keywords: Aged; Alzheimer Disease; Analysis of Variance; Atrophy; Cerebrovascular Disorders; Cognition; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Temporal Lobe; United States

Gait variability and the risk of incident mobility disability in community-dwelling older adults. - Brach, Jennifer S; Studenski, Stephanie A; Perera, Subashan; VanSwearingen, Jessie M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2007)
BACKGROUND: Gait speed is a strong predictor of incident walking disability. The objective was to determine if gait variability adds to the prediction of incident mobility disability independent of gait speed. METHODS: Participants included 379 older adults (mean age = 79 years; 78% Caucasian, and 40% men) in the Cardiovascular Health Study at the Pittsburgh site. All could ambulate independently and reported no difficulty walking a half mile. Gait characteristics were determined from a 4-meter computerized walkway. For each gait parameter, variability was defined as the standard deviation from the individual steps from two passes. Incident walking disability was obtained by phone interview every 6 months for 54 months and was defined as new difficulty walking a half mile or inability to walk a half mile. RESULTS: Of the 379 participants, 222 (58.6%) developed incident mobility disability. In unadjusted Cox proportional hazards models gait speed, mean step length, mean stance time, and stance time variability were associated with incident mobility disability. After adjusting for gait speed, demographics, chronic conditions, prescription medications, health status, and physical activity level, only stance time variability remained an important indicator of disability. In the adjusted model, an increase in stance time variability of 0.01 seconds was associated with a 13% higher incidence of mobility disability (hazard ratio 1.13, 95% confidence interval, 1.01-1.27). CONCLUSIONS: Stance time variability is an independent predictor of future mobility disability. Future efforts are needed to determine whether interventions that decrease stance time variability will also delay mobility disability.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Gait; Gait Disorders, Neurologic; Humans; Male; Mobility Limitation; Prospective Studies; Risk Factors; Walking

Gait variability is associated with subclinical brain vascular abnormalities in high-functioning older adults. - Rosano, Caterina; Brach, Jennifer; Studenski, Stephanie; Longstreth, W T; Newman, Anne B (Neuroepidemiology, 2007)
BACKGROUND: Gait variability is an index of how much gait parameters, such as step length, change from one step to the next. Gait variability increases with age and in individuals affected by cortical and subcortical neurodegenerative conditions, and it is associated with falls and incident mobility disability. The brain anatomical correlates of gait variability have not been studied in high-functioning community-dwelling older adults. METHODS: Gait variability and brain MRIs were assessed in a cohort of 331 men and women (mean age = 78.3 years) free from stroke, dementia or Parkinson's disease. Gait variability was computed for spatial parameters (step length and step width) and for temporal parameters (stance time). Subclinical brain vascular abnormalities were measured on brain MRIs as infarcts and white matter hyperintensities. RESULTS: Greater variability of step length was associated with greater prevalence of infarcts, including infarcts in the basal ganglia, and with greater white matter hyperintensities severity, independent of age, gender, cognitive function and cardiovascular disease. Weaker associations were found between the other variability measures and the MRI measures. CONCLUSION: In this group of older adults free from neurodegenerative diseases, a greater variability of step length was associated with greater burden of subclinical brain vascular abnormalities as defined by MRI.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Basal Ganglia Cerebrovascular Disease; Brain; Cerebral Infarction; Comorbidity; Female; Gait Disorders, Neurologic; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mobility Limitation; Neurodegenerative Diseases; Neurologic Examination; Risk Factors; United States

Kidney function, electrocardiographic findings, and cardiovascular events among older adults. - Kestenbaum, Bryan; Rudser, Kyle D; Shlipak, Michael G; Fried, Linda F; Newman, Anne B; Katz, Ronit; Sarnak, Mark J; Seliger, Stephen; Stehman-Breen, Catherine; Prineas, Ronald; Siscovick, David S (Clin J Am Soc Nephrol, 2007)
Chronic kidney disease (CKD) is associated with cardiovascular (CV) disease and mortality. It is not known whether cardiac rhythm disturbances are more prevalent among individuals with CKD or whether resting electrocardiogram findings predict future CV events in the CKD setting. Data were obtained from the Cardiovascular Health Study, a community-based study of adults aged >/=65 yr. After exclusions for prevalent heart disease, atrial fibrillation, implantable pacemaker, or antiarrhythmic medication use, 3238 participants were analyzed. CKD was defined by an estimated GFR <60 ml/min per 1.73 m(2). Outcomes were adjudicated incident heart failure (HF), incident coronary heart disease (CHD), and mortality. Participants with CKD had longer PR and corrected QT intervals compared with those without CKD; however, differences in electrocardiographic markers were explained by traditional CV risk factors and CV medication use. After adjustment for known risk factors, each 10-ms increase in the QRS interval was associated with a 15% greater risk for incident HF (95% confidence interval [CI] 1.04 to 1.27), a 13% greater risk for CHD (95% CI 1.04 to 1.24), and a 17% greater risk for mortality (95% CI 1.09, 1.25) among CKD participants. Each 5% increase in QTI was associated with a 42% (95% CI 1.23 to 1.65), 22% (95% CI 1.07 to 1.40), and 10% (95% CI 0.98 to 1.22) greater risk for HF, CHD, and mortality, respectively. Associations seemed stronger for participants with CKD; however, no significant interactions were detected. Resting electrocardiographic abnormalities are common in CKD and independently predict future clinical CV events in this setting.
Keywords: Aged; Aged, 80 and over; Cardiac Output, Low; Cardiovascular Diseases; Chronic Disease; Coronary Disease; Electrocardiography; Female; Humans; Kidney; Kidney Diseases; Male; Risk Assessment

The number of sick persons in a cohort. - Diehr, P; Derleth, A; Newman, AB; Cai, L (Research on Aging, 2007)
In the Cardiovascular Health Study, a cohort study of older adults followed up to 14 years, the number of sick persons was approximately constant over time. This was true whether we defined “sick” based on self-rated health, ADL or IADL difficulties, the timed walk, bed days, depression, cognitive problems, or cardiovascular disease. To better understand this phenomenon, we estimated the probabilities of transition among the healthy, sick, and dead states, and projected the number who would be in each health state over time for a birth cohort. The estimated number of sick persons in the birth cohort increased slowly over time and was approximately constant from ages 55-75, after which it decreased. The relative excess of older persons who are sick in later life is caused by a decline in the number of healthy persons rather than an increase in the number who are sick. Estimated total medical expenditures for a birth cohort may decline after about age 73. These findings may suggest a different way of thinking about trends in the health and medical expenditures of the population over time.
Keywords: Aging; equilibrium; transition probabilities; years of healthy life

A regions-of-interest volumetric analysis of mobility limitations in community-dwelling older adults. - Rosano, Caterina; Aizenstein, Howard J; Studenski, Stephanie; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2007)
BACKGROUND: In community-dwelling older adults, greater mobility impairment is associated with greater burden of diffuse brain structural abnormalities, such as higher white matter hyperintensities. This study examined the association between gray matter volumes of regions related to motor control, gait, and balance and whether this association is independent of burden of white matter hyperintensities. METHODS: A random sample of 327 participants of the Cardiovascular Health Study (78.3 +/- 4.1 years old, 57% women) contributed brain magnetic resonance imaging (MRI) and mobility data. A brain imaging automated method measured gray matter volume in cerebellum, basal ganglia, and prefrontal and parietal cortex in both hemispheres. Gait speed was measured while walking 15 feet at usual pace. Standing balance was assessed by timing tandem stance. Associations between each region's volume and gait speed or balance were measured before and after adjustment for demographics, head size, cardiovascular risk factors, and 0-9 grading scores of white matter hyperintensities. RESULTS: Smaller left cerebellum and left prefrontal regions were associated with slower gait, independently of covariates and of white matter hyperintensities. Smaller right putamen, right posterior superior parietal cortex, and both left and right cerebellum were associated with balance difficulty, independently of covariates and white matter hyperintensities. CONCLUSIONS: Smaller gray matter volumes in regions crucial for motor control are associated with slower gait and poorer balance, and the association appears to be independent of other diffuse brain abnormalities such as white matter hyperintensities.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Female; Gait; Humans; Magnetic Resonance Imaging; Male; Mobility Limitation; Postural Balance

Relationship of uric acid with progression of kidney disease. - Chonchol, Michel; Shlipak, Michael G; Katz, Ronit; Sarnak, Mark J; Newman, Anne B; Siscovick, David S; Kestenbaum, Bryan; Carney, Jan Kirk; Fried, Linda F (Am J Kidney Dis, 2007)
BACKGROUND: Uric acid levels are increased in patients with kidney dysfunction. We tested the hypothesis that uric acid may be associated with kidney disease progression. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 5,808 participants of the Cardiovascular Health Study. PREDICTOR: Uric acid levels. OUTCOMES & MEASUREMENTS: Kidney disease progression was defined as a decrease in estimated glomerular filtration rate (GFR) of 3 mL/min/1.73 m(2) per year or greater (>or=0.05 mL/s) and as incident chronic kidney disease (CKD). Measures of kidney function were estimated GFR using the Modification of Diet in Renal Disease Study equation. RESULTS: Higher quintiles of uric acid levels were associated with greater prevalences of estimated GFR less than 60 mL/min/1.73 m(2) (<1.00 mL/s) of 7%, 14%, 12%, 25%, and 42% for quintiles 1 (<or=4.41 mg/dL [<or=262 micromol/L]), 2 (4.41 to 5.20 mg/dL [262 to 309 micromol/L]), 3 (5.21 to 5.90 mg/dL [310 to 351 micromol/L]), 4 (5.91 to 6.90 mg/dL [352 to 410 micromol/L]), and 5 (>6.90 mg/dL [>410 micromol/L]), respectively. In comparison, there was only a modest, but significant, association between quintiles of uric acid levels and progression of kidney function decrease, with adjusted odds ratios of 1.0, 0.88 (95% confidence interval [CI], 0.64 to 1.21), 1.23 (95% CI, 0.87 to 1.75), 1.47 (95% CI, 1.04 to 2.07), and 1.49 (95% CI, 1.00 to 2.22) for quintiles 1 through 5, respectively. No significant association was found between uric acid level and incident CKD (adjusted odds ratio, 1.00; 95% CI, 0.89 to 1.14). LIMITATIONS: Measurements of albuminuria were not available. CONCLUSIONS: Uric acid levels are associated strongly with prevalent CKD. In comparison, greater uric acid levels had a significant, but much weaker, association with progression of kidney disease.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Disease Progression; Female; Glomerular Filtration Rate; Humans; Kidney Diseases; Male; Prospective Studies; Uric Acid

Socioeconomic position and incident mobility impairment in the Cardiovascular Health Study. - Nordstrom, Cheryl K; Diez Roux, Ana V; Schulz, Richard; Haan, Mary N; Jackson, Sharon A; Balfour, Jennifer L (BMC Geriatr, 2007)
BACKGROUND: We investigated if personal socioeconomic position (SEP) factors and neighborhood characteristics were associated with incident mobility impairment in the elderly. METHODS: We used data from the Cardiovascular Health Study, a longitudinal, population-based examination of coronary heart disease and stroke among persons aged 65 and older in the United States. RESULTS: Among 3,684 persons without baseline mobility impairment, lower baseline SEP was associated with increased risk of incident mobility disability during the 10-year follow-up period, although the strengths of these associations varied by socioeconomic indicator and race/sex group. CONCLUSION: Among independent-living elderly, SEP affected development of mobility impairment into later life. Particular effort should be made to prevent or delay its onset among the elderly with low income, education, and/or who live in economically disadvantaged neighborhoods.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Disabled Persons; Education; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Mobility Limitation; Residence Characteristics; Social Class; Stroke; United States

USF1 gene variants, cardiovascular risk, and mortality in European Americans: analysis of two US cohort studies. - Reiner, Alexander P; Carlson, Christopher S; Jenny, Nancy S; Durda, J Peter; Siscovick, David S; Nickerson, Deborah A; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: A common haplotype of the upstream transcription factor 1 gene (USF1) has been associated with decreased susceptibility to familial combined hyperlipidemia (FCHL) and, paradoxically, with increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS AND RESULTS: We assessed associations between USF1 tagSNPs, CVD risk factors, and aging-related phenotypes using data from 2 large population-based cohorts, Coronary Artery Risk Development in Young Adults (CARDIA) and the Cardiovascular Health Study (CHS), comprising younger and older adults, respectively. In CARDIA, each additional copy of the FCHL low-risk allele was associated with 2.4 mg/dL lower levels of LDL cholesterol (P=0.01) and decreased risk of subclinical atherosclerosis as assessed by coronary artery calcium (odds ratio 0.79; 95%CI 0.63 to 0.98). Whereas there was little association between USF1 genotype and metabolic or CVD traits in older adults from CHS, the USF1 low-risk dyslipidemia allele was associated with higher plasma C-reactive protein and interleukin (IL)-6 levels and with increased risk of mortality, particularly attributable to noncardiovascular causes. CONCLUSIONS: There appears to be a complex and possibly age-dependent relationship between USF1 genotype, atherosclerosis phenotypes, and CVD risk. USF1 may influence mortality through pathways distinct from atherosclerosis. Alternatively, linkage disequilibrium with neighboring polymorphisms in other genes such as F11R may be responsible for the observed USF1 genotype-phenotype associations in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Blood Glucose; C-Reactive Protein; Calcium; Cardiovascular Diseases; Carotid Artery, Common; Cohort Studies; Coronary Artery Disease; Coronary Vessels; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Hyperlipidemia, Familial Combined; Insulin; Interleukin-6; Linkage Disequilibrium; Lipids; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Upstream Stimulatory Factors

White matter grade and ventricular volume on brain MRI as markers of longevity in the cardiovascular health study. - Kuller, Lewis H; Arnold, Alice M; Longstreth, W T; Manolio, Teri A; O'Leary, Daniel H; Burke, Gregory L; Fried, Linda P; Newman, Anne B (Neurobiol Aging, 2007)
High white matter grade (WMG) on magnetic resonance imaging (MRI) is a risk factor for dementia, stroke and disability. Higher ventricular size is a marker of brain "atrophy." In the Cardiovascular Health Study (CHS) (n=3245) mean age 75 years, 50% black and 40% men, we evaluated WM and ventricular grade (VG), total, cardiovascular and noncardiovascular mortality and longevity before and after adjusting for numerous determinants of longevity over an approximate 10-12 years of follow-up. A low WMG and VG was a marker for low total, cardiovascular and noncardiovascular mortality and for increased longevity over 10+ years of follow-up. We estimated that a 75-year-old with WMG below median would have about a 5-6 years greater longevity and for VG about 3 years, than above the median even after adjustment for numerous risk factors. Low WMG and VG on MRI is a powerful determinant of long-term survival among older individuals.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Biomarkers; Brain; Cardiovascular Diseases; Cerebral Ventricles; European Continental Ancestry Group; Female; Geriatric Assessment; Health Status; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Retrospective Studies; Risk Factors; Sex Factors

Abdominal aortic aneurysms, increasing infrarenal aortic diameter, and risk of total mortality and incident cardiovascular disease events: 10-year follow-up data from the Cardiovascular Health Study. - Freiberg, Matthew S; Arnold, Alice M; Newman, Anne B; Edwards, Matthew S; Kraemer, Kevin L; Kuller, Lewis H (Circulation, 2008)
BACKGROUND: Long-term data describing small abdominal aortic aneurysms (AAAs) and increasing infrarenal aortic diameters and their relationship to future surgical repair, total mortality, and incident cardiovascular disease (CVD) events, particularly among women, are sparse. METHODS AND RESULTS: In 1992 to 1993, 4734 Cardiovascular Health Study participants > or = 65 years old had an abdominal aortic ultrasound evaluation. Of those screened, 416 had an AAA (infrarenal aortic diameter > or = 3.0 cm or an infrarenal/suprarenal ratio > or = 1.2). By 2002, there were 56 surgical AAA repairs and 10 AAA-related deaths. A single ultrasound screening demonstrated that aneurysm dilation > or = 3 cm identified 68% of all AAA repairs over the next 10 years and 6 of the 10 AAA-related deaths in 4% of the total population and that a > or = 2.5-cm dilation identified 91% of all AAA repairs and 9 of the 10 deaths in 10% of the total population. With adjusted Cox proportional hazard models, AAAs were associated with a higher risk of total mortality (hazard ratio 1.44, 95% confidence interval 1.25 to 1.66) and incident CVD events (hazard ratio 1.52, 95% confidence interval 1.25 to 1.85). Compared with diameters < 2.0 cm, infrarenal aortic diameters 2.0 to < 3.0 cm were associated with increased risk of incident CVD events in women and total mortality in men. CONCLUSIONS: This study suggests that a 1-time screening of the abdominal aorta can acceptably identify individuals with a clinically significant AAA. Infrarenal aortic diameters > 2.0 cm are associated with a significantly increased risk of future CVD events and total mortality.
Keywords: Aged; Aged, 80 and over; Aorta, Abdominal; Aortic Aneurysm, Abdominal; Cause of Death; Female; Follow-Up Studies; Humans; Incidence; Intermittent Claudication; Kidney; Male; Prospective Studies; Risk Factors; Sex Distribution; Ultrasonography

Age-specific prevalence and years of healthy life in a system with three health states. - Diehr, Paula; Yanez, David; Derleth, Ann; Newman, Anne B (Stat Med, 2008)
Consider a 3-state system with one absorbing state, such as Healthy, Sick, and Dead. Over time, the prevalence of the Healthy state will approach an 'equilibrium' value that is independent of the initial conditions. We derived this equilibrium prevalence (Prev:Equil) as a function of the local transition probabilities. We then used Prev:Equil to estimate the expected number of years spent in the healthy state over time. This estimate is similar to the one calculated by multi-state life table methods, and has the advantage of having an associated standard error. In longitudinal data for older adults, the standard error was accurate when a valid survival table was known from other sources, or when the available data set was sufficient to estimate survival accurately. Performance was better with fewer waves of data. If validated in other situations, these estimates of prevalence and years of healthy life (YHL) and their standard errors may be useful when the goal is to compare YHL for different populations.
Keywords: Age Factors; Biometry; Health Status; Humans; Life Tables; Longitudinal Studies; Middle Aged; Models, Statistical; Probability; Quality-Adjusted Life Years

Alcohol consumption and lower extremity arterial disease among older adults: the cardiovascular health study. - Mukamal, Kenneth J; Kennedy, Margaret; Cushman, Mary; Kuller, Lewis H; Newman, Anne B; Polak, Joseph; Criqui, Michael H; Siscovick, David S (Am J Epidemiol, 2008)
Few studies of the relation of alcohol intake to lower-extremity arterial disease (LEAD) have included clinical events and objective measurements repeated longitudinally. As part of the Cardiovascular Health Study, a study of older adults from four US communities, 5,635 participants reported their use of beer, wine, and spirits yearly. Incident LEAD was identified by hospitalization surveillance. Technicians measured ankle-brachial index 6 years apart in 2,298 participants. A total of 172 cases of LEAD were documented during a mean of 7.5 years of follow-up between 1989 and 1999. Compared with abstention, the multivariable-adjusted hazard ratios were 1.10 (95% confidence interval (CI): 0.71, 1.71) for <1 alcoholic drink per week, 0.56 (95% CI: 0.33, 0.95) for 1-13 drinks per week, and 1.02 (95% CI: 0.53, 1.97) for > or =14 drinks per week (p for quadratic trend = 0.04). These relations were consistent within strata of sex, age, and apolipoprotein E genotype, and neither lipids nor inflammatory markers appeared to be important intermediates. Change in ankle-brachial index showed a similar relation (p for quadratic trend = 0.01). Alcohol consumption of 1-13 drinks per week in older adults may be associated with lower risk of LEAD, but heavier drinking is not associated with lower risk.
Keywords: Aged; Alcohol Drinking; Female; Follow-Up Studies; Health Surveys; Humans; Intermittent Claudication; Male; Prevalence; Prospective Studies; Risk Factors; Surveys and Questionnaires; Time Factors; United States

Anemia is associated with the progression of white matter disease in older adults with high blood pressure: the cardiovascular health study. - Inzitari, Marco; Studenski, Stephanie; Rosano, Caterina; Zakai, Neil A; Longstreth, William T; Cushman, Mary; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To investigate whether anemia predicts worsening white matter hyperintensities (WMHs) in older community-dwellers. DESIGN: Prospective cohort study. SETTING: Older community-dwellers. PARTICIPANTS: One thousand eight hundred forty-six Cardiovascular Health Study (CHS) participants (mean age 73.7 +/- 4.4, 41% male, 15.6% African American). MEASUREMENTS: Participants had hemoglobin measured and brain magnetic resonance imaging (MRI) in 1992/93 and a second brain MRI in 1997/98. Anemia was defined according to World Health Organization criteria (hemoglobin <12 g/dL in women and <13 g/dL in men). Worsening WMHs were determined according to standardized side-by-side readings. RESULTS: After 5 years, WMHs worsened in 517 participants (28%). Progression was not associated with anemia in the whole sample, in sex or race strata, or in other prespecified subgroups (participants with renal dysfunction or diabetes mellitus), except in participants with high blood pressure (>or=140/90 mmHg). Of the 678 participants with high blood pressure, those with anemia (10.5%) had a 1.79 times greater risk of WMHs worsening (95% confidence interval=1.06-2.98; P for interaction between anemia and high blood pressure=.01) independent of demographics, baseline WMHs, cardiovascular risk factors and comorbidities, medications, renal function, inflammation, and incident stroke (logistic regression models). There was no greater risk in participants with anemia with normal blood pressure. CONCLUSION: Anemia may contribute to worsening of WMHs in older adults with high blood pressure.
Keywords: Aged; Anemia; Brain; Cardiovascular Diseases; Disease Progression; Female; Humans; Hypertension; Leukoaraiosis; Magnetic Resonance Imaging; Male

Ankle brachial index combined with Framingham Risk Score to predict cardiovascular events and mortality: a meta-analysis. - Fowkes, F G R; Murray, G D; Butcher, I; Heald, C L; Lee, R J; Chambless, L E; Folsom, A R; Hirsch, A T; Dramaix, M; deBacker, G; Wautrecht, J-C; Kornitzer, M; et al. (JAMA, 2008)
CONTEXT: Prediction models to identify healthy individuals at high risk of cardiovascular disease have limited accuracy. A low ankle brachial index (ABI) is an indicator of atherosclerosis and has the potential to improve prediction. OBJECTIVE: To determine if the ABI provides information on the risk of cardiovascular events and mortality independently of the Framingham risk score (FRS) and can improve risk prediction. DATA SOURCES: Relevant studies were identified. A search of MEDLINE (1950 to February 2008) and EMBASE (1980 to February 2008) was conducted using common text words for the term ankle brachial index combined with text words and Medical Subject Headings to capture prospective cohort designs. Review of reference lists and conference proceedings, and correspondence with experts was conducted to identify additional published and unpublished studies. STUDY SELECTION: Studies were included if participants were derived from a general population, ABI was measured at baseline, and individuals were followed up to detect total and cardiovascular mortality. DATA EXTRACTION: Prespecified data on individuals in each selected study were extracted into a combined data set and an individual participant data meta-analysis was conducted on individuals who had no previous history of coronary heart disease. RESULTS: Sixteen population cohort studies fulfilling the inclusion criteria were included. During 480,325 person-years of follow-up of 24,955 men and 23,339 women, the risk of death by ABI had a reverse J-shaped distribution with a normal (low risk) ABI of 1.11 to 1.40. The 10-year cardiovascular mortality in men with a low ABI (< or = 0.90) was 18.7% (95% confidence interval [CI], 13.3%-24.1%) and with normal ABI (1.11-1.40) was 4.4% (95% CI, 3.2%-5.7%) (hazard ratio [HR], 4.2; 95% CI, 3.3-5.4). Corresponding mortalities in women were 12.6% (95% CI, 6.2%-19.0%) and 4.1% (95% CI, 2.2%-6.1%) (HR, 3.5; 95% CI, 2.4-5.1). The HRs remained elevated after adjusting for FRS (2.9 [95% CI, 2.3-3.7] for men vs 3.0 [95% CI, 2.0-4.4] for women). A low ABI (< or = 0.90) was associated with approximately twice the 10-year total mortality, cardiovascular mortality, and major coronary event rate compared with the overall rate in each FRS category. Inclusion of the ABI in cardiovascular risk stratification using the FRS would result in reclassification of the risk category and modification of treatment recommendations in approximately 19% of men and 36% of women. CONCLUSION: Measurement of the ABI may improve the accuracy of cardiovascular risk prediction beyond the FRS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Ankle; Atherosclerosis; Blood Pressure; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Female; Global Health; Humans; Male; Middle Aged; Odds Ratio; Predictive Value of Tests; Risk Assessment; Risk Factors; Severity of Illness Index

Association between lower digit symbol substitution test score and slower gait and greater risk of mortality and of developing incident disability in well-functioning older adults. - Rosano, Caterina; Newman, Anne B; Katz, Ronit; Hirsch, Calvin H; Kuller, Lewis H (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether, in well-functioning older adults, a lower score on the Digit Symbol Substitution Test (DSST) and slower gait are associated with greater risk of mortality and of developing incident disability independent of other risk factors, including brain structural abnormalities (white matter hyperintensities, brain infarcts, ventricular enlargement) and whether the combination of varying levels of DSST score and gait speed are associated with a greater risk of mortality and disability than low DSST or slow gait alone. DESIGN: Observational cohort study. SETTING: Community. PARTICIPANTS: Three thousand one hundred fifty-six (43% men, 29% black, mean age 70.4) participants in the Cardiovascular Health Study (CHS), free from stroke and physical disability and with a modified Mini-Mental State Examination (3MS) score of 80 or higher. MEASUREMENTS: Total mortality and incident disability (self-report of any difficulty performing one or more of the six activities of daily living) ascertained over a median follow-up time of 8.4 years. RESULTS: By the end of follow-up, 704 participants had died and 1,096 had incident disability. In Cox proportional hazards models adjusted for age, sex, race, education, cardiovascular disease, and brain magnetic resonance imaging abnormalities, lower DSST score and slower gait remained significantly associated with greater risk of mortality and of incident disability. Mortality rates were higher in those who had both low DSST score (<27 points) and slow gait (speed <1.0 m/s) than in those who had only low DSST score, only slow gait, or neither (rates per 1,000 person years (p-y): 61.2, 42.8, 20.8, and 16.3, respectively). A similar risk gradient was observed for incident disability (82.0, 57.9, 47.9, and 36.0/1,000 p-y, respectively). CONCLUSION: In well-functioning older adults, low DSST score and slow gait, alone or in combination, could be risk factors for mortality and for developing disability, independent of other risk factors, including measures of brain integrity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Analysis of Variance; Atrophy; Brain; Brain Diseases; Cause of Death; Cohort Studies; Disability Evaluation; Discrimination Learning; Female; Gait; Humans; Male; Memory, Short-Term; Mobility Limitation; Neuropsychological Tests; Pattern Recognition, Visual; Psychometrics; Psychomotor Performance; Risk Factors

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Cardiovascular risk factors and incident acute renal failure in older adults: the cardiovascular health study. - Mittalhenkle, Anuja; Stehman-Breen, Catherine O; Shlipak, Michael G; Fried, Linda F; Katz, Ronit; Young, Bessie A; Seliger, Stephen; Gillen, Daniel; Newman, Anne B; Psaty, Bruce M; Siscovick, David (Clin J Am Soc Nephrol, 2008)
BACKGROUND AND OBJECTIVES: Although the elderly are at increased risk for acute renal failure, few prospective studies have identified risk factors for acute renal failure in the elderly. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The associations of cardiovascular disease risk factors, subclinical cardiovascular disease, and clinical coronary heart disease with the risk for development of acute renal failure were examined in older adults in the Cardiovascular Health Study, a prospective cohort study of community-dwelling older adults. Incident hospitalized cases of acute renal failure were identified through hospital discharge International Classification of Diseases, Ninth Revision codes and confirmed through physician diagnoses of acute renal failure in discharge summaries. RESULTS: Acute renal failure developed in 225 (3.9%) of the 5731 patients during a median follow-up period of 10.2 yr. In multivariate analyses, diabetes, current smoking, hypertension, C-reactive protein, and fibrinogen were associated with acute renal failure. Prevalent coronary heart disease was associated with incident acute renal failure, and among patients without prevalent coronary heart disease, subclinical vascular disease measures were also associated with acute renal failure: Low ankle-arm index (< or =0.9), common carotid intima-media thickness, and internal carotid intima-media thickness. CONCLUSIONS: In this large, population-based, prospective cohort study, cardiovascular risk factors and both subclinical and clinical vascular disease were associated with incident acute renal failure in the elderly.
Keywords: Acute Kidney Injury; Aged; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Male; Prospective Studies; Risk Factors

Common variants in the CRP gene in relation to longevity and cause-specific mortality in older adults: the Cardiovascular Health Study. - Hindorff, Lucia A; Rice, Kenneth M; Lange, Leslie A; Diehr, Paula; Halder, Indrani; Walston, Jeremy; Kwok, Pui; Ziv, Elad; Nievergelt, Caroline; Cummings, Steven R; Newman, Anne B; Tracy, Russell P; et al. (Atherosclerosis, 2008)
Common polymorphisms in the CRP gene are associated with plasma CRP levels in population-based studies, but associations with age-related events are uncertain. A previous study of CRP haplotypes in older adults was broadened to include longevity and cause-specific mortality (all-cause, noncardiovascular (non-CV), and cardiovascular (CV)). Common haplotypes were inferred from four tagSNPs in 4512 whites and five tagSNPs in 812 blacks from the Cardiovascular Health Study, a longitudinal cohort of adults over age 65. Exploratory analyses addressed early versus late mortality. CRP haplotypes were not associated with all-cause mortality or longevity overall in either population, but associations with all-cause mortality differed during early and late periods. In blacks, the haplotype tagged by 3872A (rs1205) was associated with increased risk of non-CV mortality, relative to other haplotypes (adjusted hazard ratio for each additional copy: 1.42, 95% CI: 1.07, 1.87). Relative to other haplotypes, this haplotype was associated with decreased risk of early but not decreased risk of late CV mortality in blacks; among whites, a haplotype tagged by 2667C (rs1800947) gave similar but nonsignificant findings. If confirmed, CRP genetic variants may be weakly associated with CV and non-CV mortality in older adults, particularly in self-identified blacks.
Keywords: African Americans; Aged; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Linear Models; Longevity; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Coronary artery calcium and physical function in older adults: the Cardiovascular Health Study. - Inzitari, Marco; Naydeck, Barbara L; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults without clinical cardiovascular disease, coronary artery calcium (CAC) is associated with other subclinical vascular diseases, which, in turn, predict physical dysfunction. However, the association between CAC and physical function is unstudied. METHODS: In 387 older community-dwellers from the Cardiovascular Health Study without clinical cardiovascular diseases (mean age +/- standard deviation = 78.7 +/- 3.7, 35% men, 22% African Americans), CAC was measured using electron beam tomography, and physical performance was assessed by usual pace gait speed, chair stand, and tandem stand. Differences in physical performance across CAC quartiles were investigated in the whole cohort and by gender. Associations with gait speed (m/s) were assessed in multivariable models using both the continuous form of CAC score (log(CAC)) and quartiles of CAC, adjusting for demographics and comorbidities. RESULTS: No differences in physical performance were observed across CAC quartiles in the whole group. In gender-stratified analyses, a significant association was shown among women, who had progressively lower gait speed across CAC quartiles: Those with CAC > 220 walked more than 0.1 m/s slower than those with CAC < 35 (age-adjusted ptrend =.017). After multivariable adjustment, the association remained statistically significant for women in both linear (log(CAC) and gait speed, p =.025) and logistic models: Each of the top three CAC quartiles (35-220, 221-659, and > or = 660) had a more than twofold odds of walking slower than 1 m/s, compared to the lowest CAC quartile (< 35; p =.021). CONCLUSIONS: In this sample of older community-dwellers without overt cardiovascular disease, CAC was inversely related to gait speed in women, but not in men.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Calcinosis; Coronary Artery Disease; Female; Geriatric Assessment; Humans; Male; Regression Analysis; Risk Factors; Tomography, X-Ray Computed; Walking

Coronary artery calcium, carotid artery wall thickness, and cardiovascular disease outcomes in adults 70 to 99 years old. - Newman, Anne B; Naydeck, Barbara L; Ives, Diane G; Boudreau, Robert M; Sutton-Tyrrell, Kim; O'Leary, Daniel H; Kuller, Lewis H (Am J Cardiol, 2008)
Few population studies have evaluated the associations of both coronary artery calcium (CAC) and carotid ultrasound with cardiovascular events, especially in adults >70 years of age. At the Pittsburgh Field Center of the Cardiovascular Health Study, 559 men and women, mean age 80.2 (SD 4.1) years had CAC score assessed by electron beam computerized tomographic scan and common and internal carotid artery intimal medial wall thickness (CCA-IMT and ICA-IMT) by carotid ultrasound between 1998 and 2000 and were followed for total and incident cardiovascular disease events through June 2003. Crude rates and hazard ratios for total and incident events were examined with and without adjustment for cardiovascular risk factors. After 5 years, there were 127 cardiovascular disease events, 48 myocardial infarctions or cardiovascular disease deaths, and 28 strokes or stroke deaths. Total and incident cardiovascular disease event rates were higher in each quartile of CAC and CCA-IMT, but not of ICA-IMT. For total cardiovascular disease, the adjusted hazard ratio for the fourth versus first quartile of CAC was 2.1 (95% confidence interval 1.2 to 3.9) and for CCA-IMT was 2.3 (95% confidence interval 1.3 to 4.1). The CCA-IMT was more strongly related to stroke risk than was CAC, although CAC was also an important predictor of stroke. No significant gender differences were found, although relative risks appeared to be stronger in women, especially for stroke. In conclusion, in adults >70 years of age, CAC and CCA-IMT had similar hazard ratios for total cardiovascular disease and coronary heart disease. The CCA-IMT was more strongly related to stroke than CAC, but CAC was also a predictor of stroke.
Keywords: Aged; Aged, 80 and over; Carotid Artery Diseases; Carotid Artery, Common; Carotid Artery, Internal; Coronary Artery Disease; Coronary Vessels; Female; Humans; Male; ROC Curve; Severity of Illness Index; Survival Analysis; Ultrasonography; United States

Cystatin C and aging success. - Sarnak, Mark J; Katz, Ronit; Fried, Linda F; Siscovick, David; Kestenbaum, Brian; Seliger, Stephen; Rifkin, Dena; Tracy, Russell; Newman, Anne B; Shlipak, Michael G (Arch Intern Med, 2008)
BACKGROUND: To our knowledge, the effect of kidney function on successful aging has not been examined. METHODS: We evaluated the relationship between cystatin C and aging success during a 6-year follow-up in the Cardiovascular Health Study, a community-based cohort of older adults (aged >or= 65 years). Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and having intact physical and cognitive functioning. In adjusted analysis, an accelerated failure time model was used to evaluate the percentage reduction in successful years by level of cystatin C. A separate Cox proportional hazards model evaluated whether cystatin C was related to incident physical and cognitive disability. RESULTS: A total of 2140 participants had cystatin C measured and were free of the previously mentioned conditions at baseline. Their mean age was 74 years. The mean cystatin C level, creatinine level, and estimated glomerular filtration rate were 1.06 mg/L, 0.93 mg/dL, and 78 mL/min/1.73 m(2), respectively (to convert cystatin C to nanomoles per liter, multiply by 75; and to convert creatinine to micromoles per liter, multiply by 88.4). A total of 873 participants reached a first event in follow-up, 138 because of cognitive disability, 238 because of physical disability, 34 because of chronic obstructive pulmonary disease, 146 because of cancer, and 317 because of cardiovascular disease. The adjusted percentage reduction in successful life years in the highest vs the lowest quartile of cystatin C was 27% (95% confidence interval, 11%-39%). The highest vs lowest quartile of cystatin C also was independently associated with incident cognitive or physical disability (hazard ratio, 1.39; 95% confidence interval, 1.00-1.98). CONCLUSION: A higher cystatin C level, even within a range of relatively normal kidney function, was associated with unsuccessful aging.
Keywords: Aged; Aging; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney; Male

Diabetes mellitus and gait dysfunction: possible explanatory factors. - Brach, Jennifer S; Talkowski, Jaime B; Strotmeyer, Elsa S; Newman, Anne B (Phys Ther, 2008)
BACKGROUND AND OBJECTIVE: Gait characteristics differ in individuals with diabetes compared with those without diabetes. Limited information regarding potential explanatory factors for this association exists. This study examined the association between diabetes and gait characteristics in older adults and explored potential explanatory factors. DESIGN: A cross-sectional, observational study design was used. METHODS: At the 1998-1999 clinic visit, 558 ambulatory older adults (mean age=79 years) from the Pittsburgh site of the Cardiovascular Health Study had an assessment of their gait characteristics, diabetes, health status, cognition, mood, lower-extremity circulation and sensation, vision, lower-extremity strength (force-producing capacity), physical activity, and body mass index (BMI). A series of linear regression models were developed to examine the association between diabetes and gait characteristics and to examine potential explanatory factors for the associations. RESULTS: Diabetes was related to gait speed (beta=-.06 m/s); however, the association was partially explained by health status variables, cognition, mood, lower-extremity circulation and sensation, visual impairment, lower-extremity strength, physical activity, and BMI. Health status and lower-extremity strength each explained the greatest proportion of the association (beta reduced 66% by each). Diabetes was related to step width (beta=.02 m), and the association could not be explained by the examined factors. CONCLUSIONS: Diabetes was associated with gait alterations in older adults. Slowed gait speed appears to be secondary to the peripheral effect of the disease on other body systems. The effect of diabetes on step width was not explained in the analyses and may be related to peripheral motor nerve function or central influences of the disease, which could not be assessed in this study.
Keywords: Aged; Body Mass Index; Cognition; Cross-Sectional Studies; Diabetes Mellitus; Female; Gait; Geriatric Assessment; Health Status; Humans; Linear Models; Longitudinal Studies; Male; Multicenter Studies as Topic; Muscle Strength

Distribution and correlates of lipoprotein-associated phospholipase A2 in an elderly cohort: the Cardiovascular Health Study. - Furberg, Curt D; Nelson, Jeanenne J; Solomon, Cam; Cushman, Mary; Jenny, Nancy Swords; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether high levels of lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) are associated with prevalent cardiovascular disease (CVD) and to evaluate factors most influencing Lp-PLA(2) levels in a community-based cohort of older adults. DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), a population-based cohort study of men and women aged 65 and older. PARTICIPANTS: Five thousand five hundred thirty-one CHS participants. MEASUREMENTS: Levels of Lp-PLA(2) activity were determined using stored blood samples from the baseline examination. RESULTS: Mean Lp-PLA(2) was higher in participants with electrocardiographically determined ventricular conduction defect and major Q-wave abnormality and was positively correlated with left ventricular (LV) mass. It was high in those with echocardiographically determined abnormal LV ejection fraction, which persisted after adjustment. Mean Lp-PLA(2) was also higher in participants with mild renal insufficiency and kidney disease. After multivariable adjustment, there was a modest but significant 27% greater risk of prevalent CHF per standard deviation increment of Lp-PLA(2) and a modest but significant 12% greater risk of prevalent myocardial infarction. Lp-PLA(2) was weakly but mainly most strongly correlated with cholesterol and lipoproteins, but those correlations were not especially strong. Lp-PLA(2) was weakly positively correlated with soluble intercellular adhesion molecule-1 but not interleukin-6. In total, all factors considered could explain only 29% of Lp-PLA(2) activity. CONCLUSION: Novel findings in the study are the associations, in those aged 65 and older, between Lp-PLA(2) activity and LV dysfunction, CHF, and renal disease. CVD risk factors only minimally explain levels of Lp-PLA(2).
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Atherosclerosis; Body Mass Index; Cardiac Output, Low; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cross-Sectional Studies; Electrocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Long QT Syndrome; Male; Reference Values; Renal Insufficiency; Risk Factors; Statistics as Topic; Triglycerides

Enhanced risk for Alzheimer disease in persons with type 2 diabetes and APOE epsilon4: the Cardiovascular Health Study Cognition Study. - Irie, Fumiko; Fitzpatrick, Annette L; Lopez, Oscar L; Kuller, Lewis H; Peila, Rita; Newman, Anne B; Launer, Lenore J (Arch Neurol, 2008)
BACKGROUND: Diabetes and the apolipoprotein E epsilon4 allele (APOE epsilon4) increase the risk for Alzheimer disease (AD). We hypothesize that APOE epsilon4 may modify the risk for AD in individuals with diabetes. OBJECTIVE: To examine the joint effect of type 2 diabetes and APOE epsilon4 on the risk of AD, AD with vascular dementia (mixed AD), and vascular dementia without AD. DESIGN: The Cardiovascular Health Study (CHS) Cognition Study (1992-2000) is a prospective study designed to identify all existing and new cases of dementia among study participants. Diagnoses were made according to international criteria for dementia and subtypes. There were 2547 dementia-free participants in the CHS Cognition Study cohort with complete information on APOE epsilon4 and type 2 diabetes status; among these, 411 new cases of dementia developed. Risk of dementia was estimated with a Cox proportional hazard model adjusted for age and other demographic and cardiovascular risk factors. RESULTS: Compared with those who had neither type 2 diabetes nor APOE epsilon4, those with both factors had a significantly higher risk of AD (hazard ratio, 4.58; 95% confidence interval, 2.18-9.65) and mixed AD (hazard ratio, 3.89; 95% confidence interval, 1.46-10.40). CONCLUSION: These data suggest that having both diabetes and APOE epsilon4 increases the risk of dementia, especially for AD and mixed AD.
Keywords: African Americans; Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Cognition; Cohort Studies; Confidence Intervals; Dementia, Vascular; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Genotype; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors

Impact of health perception, balance perception, fall history, balance performance, and gait speed on walking activity in older adults. - Talkowski, Jaime B; Brach, Jennifer S; Studenski, Stephanie; Newman, Anne B (Phys Ther, 2008)
BACKGROUND AND PURPOSE: Disagreement currently exists regarding the contributions of various factors to physical activity in older adults. The purpose of this cross-sectional study was to investigate the simultaneous impact of psychological (health perception and balance perception) and physiological (gait speed, fall history, and balance performance) factors on walking activity in older adults. SUBJECTS AND METHODS: This cross-sectional secondary data analysis included 2,269 community-dwelling older adults from the Cardiovascular Health Study. A series of simultaneous linear regression models were constructed to examine the association of walking activity with health and balance perception, gait speed, fall history, and balance performance after controlling for potential confounding factors. RESULTS: Health and balance perception and gait speed were significantly related to walking activity after controlling for potential confounding factors. Participants who perceived both their health and their balance to be good walked more blocks per week than those who reported a discordant perception, who walked more than those who perceived both their health and their balance to be poor. Participants who walked at a normal speed walked more blocks per week than those who walked at a slow speed. DISCUSSION AND CONCLUSION: The measure of physical activity used in this study included only walking, not other low- to moderate-intensity activities that are common in older adults. Health and balance perception and gait speed were associated with walking activity more so than fall history or balance performance after controlling for potential confounding factors.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Attitude to Health; Cross-Sectional Studies; Female; Gait; Geriatric Assessment; Health Status; Humans; Male; Motor Activity; Multivariate Analysis; Perception; Postural Balance; Risk Assessment; Walking

Incident physical disability in people with lower extremity peripheral arterial disease: the role of cardiovascular disease. - Brach, Jennifer S; Solomon, Cam; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Enright, Paul L; Jenny, Nancy Swords; Chaves, Paulo M; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To evaluate the risk of incident physical disability and the decline in gait speed over a 6-year follow-up associated with a low ankle-arm index (AAI) in older adults. DESIGN: Observational cohort study. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Four thousand seven hundred five older adults, 58% women and 17.6% black, participating in the Cardiovascular Health Study. MEASUREMENTS: AAI was measured in 1992/93 (baseline). Self-reported mobility, activity of daily living (ADL), and instrumental activity of daily living (IADL) disability and gait speed were recorded at baseline and at 1-year intervals over 6 years of follow-up. Mobility disability was defined as any difficulty walking half a mile and ADL and IADL disability was defined as any difficulty with 11 specific ADL and IADL tasks. Individuals with mobility, ADL, or IADL disability at baseline were excluded from the respective incident disability analyses. RESULTS: Lower baseline AAI values were associated with increased risk of mobility disability and ADL/IADL disability. Clinical cardiovascular disease (CVD), diabetes mellitus, and interim CVD events partially explained these associations for mobility disability and clinical CVD and diabetes mellitus partially explained these associations for ADL and IADL disability. Individuals with an AAI less than 0.9 had on average a mean decrease in gait speed of 0.02 m/s per year, or a decline of 0.12 m/s over the 6-year follow-up. Prevalent CVD partly explained this decrease but interim CVD events did not further attenuate it. CONCLUSION: Low AAI serves as marker of future disability risk. Reduction of disability risk in patients with a low AAI should consider cardiovascular comorbidity and the prevention of additional disabling CVD events.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cohort Studies; Comorbidity; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Lower Extremity; Male; Mobility Limitation; Peripheral Vascular Diseases; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Inflammatory markers and longitudinal lung function decline in the elderly. - Jiang, Rui; Burke, Gregory L; Enright, Paul L; Newman, Anne B; Margolis, Helene G; Cushman, Mary; Tracy, Russell P; Wang, Yuanjia; Kronmal, Richard A; Barr, R Graham (Am J Epidemiol, 2008)
Longitudinal studies examining associations of the inflammatory markers fibrinogen and C-reactive protein (CRP) with lung function decline are sparse. The authors examined whether elevated fibrinogen and CRP levels were associated with greater longitudinal lung function decline in the elderly. The Cardiovascular Health Study measured fibrinogen and CRP in 5,790 Whites and African Americans from four US communities aged 65 years or older in 1989-1990 or 1992-1993. Spirometry was performed in 1989-1990 and 4, 7, and 16 years later. Fibrinogen and CRP were inversely associated with lung function at baseline after adjustment for multiple potential confounders. In mixed models, the rate of decline in forced expiratory volume in 1 second (FEV(1))/forced vital capacity (FVC) ratio with increasing age was faster among those with higher baseline fibrinogen (-0.032%/year per standard deviation higher fibrinogen (95% confidence interval: -0.057, -0.0074)) but not among those with higher CRP (-0.0037%/year per standard deviation higher CRP (95% confidence interval: -0.013, 0.0056)). Longitudinal analyses for FEV(1) and FVC yielded results in the direction opposite of that hypothesized, possibly because of the high mortality rate and strong inverse association of FEV(1) and FVC but not FEV(1)/FVC with mortality. An alternative approach to missing data yielded similar results. In conclusion, higher levels of fibrinogen, but not CRP, independently predicted greater FEV(1)/FVC decline in the elderly.
Keywords: Aged; C-Reactive Protein; Cross-Sectional Studies; Female; Fibrinogen; Forced Expiratory Volume; Geriatric Assessment; Humans; Logistic Models; Longitudinal Studies; Lung Volume Measurements; Male; Multicenter Studies as Topic; Pulmonary Disease, Chronic Obstructive; Spirometry

Insulin-like growth factor-(IGF)-axis, inflammation, and glucose intolerance among older adults. - Rajpathak, Swapnil N; McGinn, Aileen P; Strickler, Howard D; Rohan, Thomas E; Pollak, Michael; Cappola, Anne R; Kuller, Lewis; Xue, XiaoNan; Newman, Anne B; Strotmeyer, Elsa S; Psaty, Bruce M; Kaplan, Robert C (Growth Horm IGF Res, 2008)
Increasing evidence suggests that the insulin-like growth factor (IGF)-axis may play a role in glucose metabolism and may also be associated with systemic inflammation. The aim of this study was to evaluate the association of insulin-like growth factor-1 (IGF-I) and its binding proteins, IGFBP-1 and IGFBP-3, with glucose intolerance and inflammation among older adults. We conducted a cross-sectional analysis in a in a random subsample (n=922) of the Cardiovascular Health Study (CHS), a prospective cohort of men and women > or = 65 years. Mean IGFBP-1 levels were significantly lower in older adults with impaired glucose tolerance (IGT), impaired fasting glucose (IFG) and diabetes compared to those with normal fasting and post-load glucose. High IGFBP-1 was associated with a reduced prevalence of IGT and IFG; the multivariable OR between extreme quartiles of IGFBP-1 was 0.60 (95% CI: 0.37, 0.95; p-trend: 0.03) for IGT and 0.41 (95% CI: 0.26, 0.64; p-trend: <0.01) for IFG. We did not find any significant association between IGF-I and glucose intolerance in this study and the association for IGFBP-3 was less clear. However, low levels of IGF-I and IGFBP-3 were associated with increased levels of markers of inflammation including C-reactive protein and interleukin-6 levels. We conclude that among adults > or = 65 years, low IGFBP-1 levels are associated with increased prevalence of glucose intolerance. We did not confirm prior associations of low IGF-I with glucose intolerance in this cohort of older individuals.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Female; Glucose Intolerance; Humans; Inflammation; Insulin-Like Growth Factor Binding Proteins; Male; Signal Transduction; Somatomedins

Item response theory facilitated cocalibrating cognitive tests and reduced bias in estimated rates of decline. - Crane, Paul K; Narasimhalu, Kaavya; Gibbons, Laura E; Mungas, Dan M; Haneuse, Sebastien; Larson, Eric B; Kuller, Lewis; Hall, Kathleen; van Belle, Gerald (J Clin Epidemiol, 2008)
OBJECTIVE: To cocalibrate the Mini-Mental State Examination, the Modified Mini-Mental State, the Cognitive Abilities Screening Instrument, and the Community Screening Instrument for Dementia using item response theory (IRT) to compare screening cut points used to identify cases of dementia from different studies, to compare measurement properties of the tests, and to explore the implications of these measurement properties on longitudinal studies of cognitive functioning over time. STUDY DESIGN AND SETTING: We used cross-sectional data from three large (n>1000) community-based studies of cognitive functioning in the elderly. We used IRT to cocalibrate the scales and performed simulations of longitudinal studies. RESULTS: Screening cut points varied quite widely across studies. The four tests have curvilinear scaling and varied levels of measurement precision, with more measurement error at higher levels of cognitive functioning. In longitudinal simulations, IRT scores always performed better than standard scoring, whereas a strategy to account for varying measurement precision had mixed results. CONCLUSION: Cocalibration allows direct comparison of cognitive functioning in studies using any of these four tests. Standard scoring appears to be a poor choice for analysis of longitudinal cognitive testing data. More research is needed into the implications of varying levels of measurement precision.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Dementia; Disease Progression; Epidemiologic Methods; Female; Humans; Male; Neuropsychological Tests; Psychometrics

A physiologic index of comorbidity: relationship to mortality and disability. - Newman, Anne B; Boudreau, Robert M; Naydeck, Barbara L; Fried, Linda F; Harris, Tamara B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults, there is often substantial undiagnosed chronic disease detectable on noninvasive testing, not accounted for by most comorbidity indices. We developed a simple physiologic index of comorbidity by scoring five noninvasive tests across the full range of values. We examined the predictive validity of this index for mortality and disability. METHODS: There were 2928 (mean age 74.5 years, 60% women, 85% white, and 15% black) participants in the Cardiovascular Health Study (1992-1993) who had carotid ultrasound, pulmonary function testing, brain magnetic resonance scan, serum cystatin-C, and fasting glucose. These were combined into a single physiologic index of comorbid chronic disease on a scale of 0-10. Cox proportional hazard models were used to predict mortality, mobility limitation, and activities of daily living (ADL) difficulty after a maximum of 9 years. RESULTS: The range of the physiologic index was quite broad, with very few individuals having total scores of either 0 or 10. Those with an index of 7-10 had a hazard ratio of 3.80 (95% confidence interval, 2.82-5.13) for mortality compared to those with scores of 0-2, after adjustment for demographics, behavioral risk factors, and clinically diagnosed conditions. Associations with mobility limitation and ADL difficulty were also significant. The index explained about 40% of the age effect on mortality risk. CONCLUSION: Older adults with low levels of markers of chronic disease are rather rare but have remarkably good health outcomes. The ability of such an index to distinguish usual from low risk might provide an opportunity to better understand optimal health in old age.
Keywords: Activities of Daily Living; Aged; Comorbidity; Disabled Persons; Female; Health Status; Humans; Male; Mobility Limitation; Mortality; Predictive Value of Tests; Proportional Hazards Models

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

PROC, PROCR and PROS1 polymorphisms, plasma anticoagulant phenotypes, and risk of cardiovascular disease and mortality in older adults: the Cardiovascular Health Study. - Reiner, A P; Carty, C L; Jenny, N S; Nievergelt, C; Cushman, M; Stearns-Kurosawa, D J; Kurosawa, S; Kuller, L H; Lange, L A (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: Genes encoding protein C anticoagulant pathways are candidates for atherothrombotic and other aging-related disorders. METHODS: Using a tagSNP approach, and data from the Cardiovascular Health Study (CHS), we assessed associations of common polymorphisms of PROC, PROS1 and PROCR with: (i) plasma protein C, soluble protein C endothelial receptor (sEPCR) and protein S levels measured in a subsample of 336 participants at study entry; and (ii) risk of incident clinical outcomes [coronary heart disease (CHD), stroke, and mortality] in 4547 participants during follow-up. Secondarily, we explored associations between plasma protein C, protein S and sEPCR levels and other candidate genes involved in thrombosis, inflammation, and aging. RESULTS: The PROCR Ser219Gly polymorphism (rs867186) was strongly associated with higher sEPCR levels, explaining 75% of the phenotypic variation. The PROCR Ser219Gly variant was also associated with higher levels of circulating protein C antigen. An IL10 polymorphism was associated with higher free protein S levels. The minor alleles of PROC rs2069901 and PROS1 rs4857343 were weakly associated with lower protein C and free protein S levels, respectively. There was no association between PROCR Ser219Gly and risk of CHD, stroke, or mortality. The minor allele of another common PROCR tagSNP, rs2069948, was associated with lymphoid PROCR mRNA expression and with increased risk of incident stroke and all-cause mortality, and decreased healthy survival during follow-up. CONCLUSIONS: A common PROCR variant may be associated with decreased healthy survival in older adults. Additional studies are warranted to establish the role of PROCR variants in ischemic and aging-related disorders.
Keywords: Aged; Aged, 80 and over; Aging; Antigens, CD; Blood Coagulation Factor Inhibitors; Cardiovascular Diseases; Coronary Disease; Endothelial Protein C Receptor; Female; Humans; Inflammation; Male; Middle Aged; Mortality; Polymorphism, Genetic; Protein C; Protein S; Receptors, Cell Surface; Risk; Stroke; Thrombosis

Rapid kidney function decline and mortality risk in older adults. - Rifkin, Dena E; Shlipak, Michael G; Katz, Ronit; Fried, Linda F; Siscovick, David; Chonchol, Michel; Newman, Anne B; Sarnak, Mark J (Arch Intern Med, 2008)
BACKGROUND: Impaired kidney function is associated with increased mortality risk in older adults. It remains unknown, however, whether longitudinal declines in kidney function are independently associated with increased cardiovascular and all-cause mortality in older adults. METHODS: The Cardiovascular Health Study evaluated a cohort of community-dwelling older adults enrolled from 1989 to 1993 in 4 US communities with follow-up through 2005. Among 4380 participants, the slope of annual decline in estimated glomerular filtration rate (eGFR) was estimated using both serum creatinine (eGFR(creat)) and cystatin C (eGFR(cys)) rates, which were measured at baseline, year 3, and year 7 of follow-up. Rapid decline in eGFR was defined as a loss greater than 3 mL/min/1.73 m(2) per year, and cardiovascular and all-cause mortality were assessed over a mean of 9.9 years of follow-up. RESULTS: Mean (SD) levels of creatinine and cystatin C were 0.93 (0.30) mg/dL and 1.03 (0.25) mg/L, respectively; mean (SD) eGFR(creat) and eGFR(cys) were 79 (23) mL/min/1.73 m(2) and 79 (19) mL/min/1.73 m(2), respectively. Individuals with rapid decline measured by eGFR(creat) (n = 714; 16%) had increased risk of cardiovascular (adjusted hazard ratio [AHR], 1.70; 95% confidence interval [CI], 1.40-2.06) and all-cause (AHR, 1.73; 95% CI, 1.54-1.94) mortality. Individuals with rapid decline measured by eGFR(cys) (n = 1083; 25%) also had increased risk of cardiovascular (AHR, 1.53; 95% CI, 1.29-1.80) and all-cause (AHR, 1.53; 95% CI, 1.38-1.69) mortality. The association of rapid decline in eGFR with elevated mortality risk did not differ across subgroups based on baseline kidney function, age, sex, race, or prevalent coronary heart disease. CONCLUSION: Rapid decline in eGFR is associated with an increased risk of cardiovascular and all-cause mortality in older adults, independent of baseline eGFR and other demographic variables.
Keywords: Aged; Cardiovascular Diseases; Creatinine; Cystatins; Female; Glomerular Filtration Rate; Humans; Kidney; Male; Mortality

The reliability and validity of measures of gait variability in community-dwelling older adults. - Brach, Jennifer S; Perera, Subashan; Studenski, Stephanie; Newman, Anne B (Arch Phys Med Rehabil, 2008)
OBJECTIVE: To examine the test-retest reliability and concurrent validity of variability of gait characteristics. DESIGN: Cross-sectional study. SETTING: Research laboratory. PARTICIPANTS: Older adults (N=558) from the Cardiovascular Health Study. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Gait characteristics were measured using a 4-m computerized walkway. SD determined from the steps recorded were used as the measures of variability. Intraclass correlation coefficients (ICC) were calculated to examine test-retest reliability of a 4-m walk and two 4-m walks. To establish concurrent validity, the measures of gait variability were compared across levels of health, functional status, and physical activity using independent t tests and analysis of variances. RESULTS: Gait variability measures from the two 4-m walks demonstrated greater test-retest reliability than those from the single 4-m walk (ICC=.22-.48 and ICC=.40-.63, respectively). Greater step length and stance time variability were associated with poorer health, functional status and physical activity (P<.05). CONCLUSIONS: Gait variability calculated from a limited number of steps has fair to good test-retest reliability and concurrent validity. Reliability of gait variability calculated from a greater number of steps should be assessed to determine if the consistency can be improved.
Keywords: Activities of Daily Living; Aged; Cross-Sectional Studies; Disability Evaluation; Exercise; Female; Gait; Health Status; Humans; Male; Pennsylvania; Rehabilitation; Reproducibility of Results

Sleep-disordered breathing and cardiovascular disease: an outcome-based definition of hypopneas. - Punjabi, Naresh M; Newman, Anne B; Young, Terry B; Resnick, Helaine E; Sanders, Mark H (Am J Respir Crit Care Med, 2008)
RATIONALE: Epidemiologic studies on the consequences of sleep-disordered breathing invariably use the apnea-hypopnea index as the primary measure of disease severity. Although hypopneas constitute a majority of disordered breathing events, significant controversy remains about the best criteria used to define these events. OBJECTIVES: The current investigation sought to assess the most appropriate definition for hypopneas that would be best correlated with cardiovascular disease. METHODS: A community sample of middle-aged and older adults was recruited as part of the Sleep Heart Health Study. Full-montage polysomnography was conducted and hypopneas were defined using different thresholds of oxyhemoglobin desaturation with and without arousals. Prevalent cardiovascular disease was assessed based on self-report. Logistic regression analysis was used to characterize the independent association between the hypopnea index and prevalent cardiovascular disease. MEASUREMENTS AND MAIN RESULTS: Using a sample of 6,106 adults with complete data on cardiovascular disease status and polysomnography, the current study found that hypopneas associated with an oxyhemoglobin desaturation of 4% or more were associated with prevalent cardiovascular disease independent of confounding covariates. The adjusted prevalent odds ratios for quartiles of the hypopnea index using a 4% desaturation criterion were as follows: 1.00 (<1.10 events/h), 1.10 (1.01-3.20 events/h), 1.33 (3.21-7.69 events/h), and 1.41 (>7.69 events/h). Hypopnea measures based on less than 4% oxyhemoglobin desaturation or presence of arousals showed no association with cardiovascular disease. CONCLUSIONS: Hypopneas comprise a significant component of sleep-disordered breathing in the general community. By varying the criteria for defining hypopneas, this study demonstrates that hypopneas with a desaturation of at least 4% are independently associated with cardiovascular disease. In contrast, no association was observed between cardiovascular disease and hypopneas associated with milder desaturations or arousals.
Keywords: Aged; Apnea; Cardiovascular Diseases; Cohort Studies; Female; Humans; Male; Middle Aged; Odds Ratio; Oxyhemoglobins; Polysomnography; Sleep Apnea Syndromes; Terminology as Topic

Stance time and step width variability have unique contributing impairments in older persons. - Brach, Jennifer S; Studenski, Stephanie; Perera, Subashan; VanSwearingen, Jessie M; Newman, Anne B (Gait Posture, 2008)
Gait variability may have multiple causes. We hypothesized that central nervous system (CNS) impairments would affect motor control and be manifested as increased stance time and step length variability, while sensory impairments would affect balance and be manifested as increased step width variability. Older adults (mean+/-standard deviation (S.D.) age=79.4+/-4.1, n=558) from the Pittsburgh site of the Cardiovascular Health Study participated. The S.D. across steps was the indicator of gait variability, determined for three gait measures, step length, stance time and step width, using a computerized walkway. Impairment measures included CNS function (modified mini-mental state examination, Trails A and B, Digit Symbol Substitution, finger tapping), sensory function (lower extremity (LE) vibration, vision), strength (grip strength, repeated chair stands), mood, and LE pain. Linear regression models were fit for the three gait variability characteristics using impairment measures as independent variables, adjusted for age, race, gender, and height. Analyses were repeated stratified by gait speed. All measures of CNS impairment were directly related to stance time variability (p<0.01), with increased CNS impairment associated with increased stance time variability. CNS impairments were not related to step length or width variability. Both sensory impairments were inversely related to step width (p<0.01) but not step length or stance time variability. CNS impairments affected stance time variability especially in slow walkers while sensory impairments affected step width variability in fast walkers. Specific patterns of gait variability may imply different underlying causes. Types of gait variability should be specified. Interventions may be targeted at specific types of gait variability.
Keywords: Aged; Aged, 80 and over; Biomechanical Phenomena; Female; Gait Disorders, Neurologic; Humans; Linear Models; Longitudinal Studies; Male; Neuropsychological Tests; Postural Balance; Range of Motion, Articular; Risk Factors; Signal Processing, Computer-Assisted

Subclinical thyroid dysfunction, cardiac function, and the risk of heart failure. The Cardiovascular Health study. - Rodondi, Nicolas; Bauer, Douglas C; Cappola, Anne R; Cornuz, Jacques; Robbins, John; Fried, Linda P; Ladenson, Paul W; Vittinghoff, Eric; Gottdiener, John S; Newman, Anne B (J Am Coll Cardiol, 2008)
OBJECTIVES: The goal of this study was to determine whether subclinical thyroid dysfunction was associated with incident heart failure (HF) and echocardiogram abnormalities. BACKGROUND: Subclinical hypothyroidism and hyperthyroidism have been associated with cardiac dysfunction. However, long-term data on the risk of HF are limited. METHODS: We studied 3,044 adults>or=65 years of age who initially were free of HF in the Cardiovascular Health Study. We compared adjudicated HF events over a mean 12-year follow-up and changes in cardiac function over the course of 5 years among euthyroid participants, those with subclinical hypothyroidism (subdivided by thyroid-stimulating hormone [TSH] levels: 4.5 to 9.9, >or=10.0 mU/l), and those with subclinical hyperthyroidism. RESULTS: Over the course of 12 years, 736 participants developed HF events. Participants with TSH>or=10.0 mU/l had a greater incidence of HF compared with euthyroid participants (41.7 vs. 22.9 per 1,000 person years, p=0.01; adjusted hazard ratio: 1.88; 95% confidence interval: 1.05 to 3.34). Baseline peak E velocity, which is an echocardiographic measurement of diastolic function associated with incident HF in the CHS cohort, was greater in those patients with TSH>or=10.0 mU/l compared with euthyroid participants (0.80 m/s vs. 0.72 m/s, p=0.002). Over the course of 5 years, left ventricular mass increased among those with TSH>or=10.0 mU/l, but other echocardiographic measurements were unchanged. Those patients with TSH 4.5 to 9.9 mU/l or with subclinical hyperthyroidism had no increase in risk of HF. CONCLUSIONS: Compared with euthyroid older adults, those adults with TSH>or=10.0 mU/l have a moderately increased risk of HF and alterations in cardiac function but not older adults with TSH<10.0 mU/l. Clinical trials should assess whether the risk of HF might be ameliorated by thyroxine replacement in individuals with TSH>or=10.0 mU/l.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Echocardiography; Female; Heart; Heart Failure; Heart Function Tests; Humans; Hyperthyroidism; Hypertrophy, Left Ventricular; Hypothyroidism; Male; Risk Factors; Time Factors

Subjective and objective sleep quality in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the sleep heart health study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Chami, Hassan; Budhiraja, Rohit; Punjabi, Naresh M; Buysse, Daniel; Newman, Anne B (Am J Kidney Dis, 2008)
BACKGROUND: Studies examining sleep in the hemodialysis (HD) population have largely lacked an adequate comparison group. It therefore is uncertain whether poor sleep quality in the HD population reflects age, chronic health conditions, or effects of conventional HD therapy. STUDY DESIGN: Cross-sectional matched-group study. SETTING & PARTICIPANTS: Forty-six in-center HD patients were compared with 137 community participants participating in the Sleep Heart Health Study matched for age, sex, body mass index, and race. PREDICTOR: HD patients compared with community-dwelling non-HD participants. OUTCOMES & MEASUREMENTS: Home unattended polysomnography was performed and scored by using similar protocols. Sleep habits and sleepiness were assessed by using the Sleep Habits Questionnaire and Epworth Sleepiness Scale. RESULTS: Average age of study samples was 63 years, 72% were white, and average body mass index was 28 +/- 5 kg/m(2). HD patients were significantly more likely than community participants to have short sleep (odds ratio, 3.27; 95% confidence interval, 1.16 to 9.25) and decreased sleep efficiency (odds ratio, 5.5; 95% confidence interval, 1.5 to 19.6). HD patients reported more difficulty getting back to sleep (odds ratio, 2.25; 95% confidence interval, 1.11 to 4.60) and waking up too early (odds ratio, 2.39; 95% confidence interval, 1.01 to 5.66). There was no association between polysomnography sleep time and self-reported sleep time (r = 0.09; P = 0.6) or between the Epworth Sleepiness Scale and severity of sleep apnea (r = 0.10; P = 0.5) in the HD population. LIMITATIONS: The study was limited to participants older than 45 years. CONCLUSIONS: Kidney failure treated with thrice-weekly HD is significantly associated with poor subjective and objective sleep quality.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Pennsylvania; Polysomnography; Prognosis; Renal Dialysis; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea Syndromes; Surveys and Questionnaires

Total insulinlike growth factor 1 and insulinlike growth factor binding protein levels, functional status, and mortality in older adults. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Xue, XiaoNan; Kritchevsky, Stephen B; Newman, Anne B; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To assess the association between total insulinlike growth factor (IGF)-1, IGF binding protein-1 (IGFBP-1), and IGFBP-3 levels and functioning and mortality in older adults. DESIGN: Cohort study. SETTING/PARTICIPANTS: One thousand one hundred twenty-two individuals aged 65 and older without prior cardiovascular disease events participating in the Cardiovascular Health Study. MEASUREMENTS: Baseline fasting plasma levels of IGF-1, IGFBP-1, and IGFBP-3 (defined as tertiles, T1-T3) were examined in relationship to handgrip strength, time to walk 15 feet, development of new difficulties with activities of daily living (ADLs), and mortality. RESULTS: Higher IGFBP-1 predicted worse handgrip strength (P-trend(T1-T3)<.01) and slower walking speed (P-trend(T1-T3)=.03), lower IGF-1 had a borderline significant association with worse handgrip strength (P-trend(T1-T3)=.06), and better grip strength was observed in the middle IGFBP-3 tertile than in the low or high tertiles (P=.03). Adjusted for age, sex, and race, high IGFBP-1 predicted greater mortality (P-trend(T1-T3)<.001, hazard ratio (HR)(T3vsT1)=1.48, 95% confidence interval (CI)=1.15-1.90); this association was borderline significant after additional confounder adjustment (P-trend(T1-T3)=.05, HR(T3vsT1)=1.35, 95% CI=0.98-1.87). High IGFBP-1 was associated with greater risk of incident ADL difficulties after adjustment for age, sex, race, and other confounders (P-trend(T1-T3)=.04, HR(T3vsT1)=1.40, CI=1.01-1.94). Neither IGF-1 nor IGFBP-3 level predicted mortality or incident ADL difficulties. CONCLUSION: In adults aged 65 and older, high IGFBP-1 levels were associated with greater risk of mortality and poorer functional ability, whereas IGF-1 and IGFBP-3 had little association with these outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Enzyme-Linked Immunosorbent Assay; Fasting; Female; Follow-Up Studies; Hand Strength; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Survival Rate; United States; Walking

Weight, mortality, years of healthy life, and active life expectancy in older adults. - Diehr, Paula; O'Meara, Ellen S; Fitzpatrick, Annette; Newman, Anne B; Kuller, Lewis; Burke, Gregory (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether weight categories predict subsequent mortality and morbidity in older adults. DESIGN: Multistate life tables, using data from the Cardiovascular Health Study, a longitudinal population-based cohort of older adults. SETTING: Data were provided by community-dwelling seniors in four U.S. counties: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Five thousand eight hundred eighty-eight adults aged 65 and older at baseline. MEASUREMENTS: The age- and sex-specific probabilities of transition from one health state to another and from one weight category to another were estimated. From these probabilities, future life expectancy, years of healthy life, active life expectancy, and the number of years spent in each weight and health category after age 65 were estimated. RESULTS: Women who are healthy and of normal weight at age 65 have a life expectancy of 22.1 years. Of that, they spend, on average, 9.6 years as overweight or obese and 5.3 years in fair or poor health. For both men and women, being underweight at age 65 was associated with worse outcomes than being normal weight, whereas being overweight or obese was rarely associated with worse outcomes than being normal weight and was sometimes associated with significantly better outcomes. CONCLUSION: Similar to middle-aged populations, older adults are likely to be or to become overweight or obese, but higher weight is not associated with worse health in this age group. Thus, the number of older adults at a "healthy" weight may be much higher than currently believed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Body Weight; Female; Health Status Indicators; Humans; Life Expectancy; Life Style; Male; Prognosis; Risk Factors; Sex Factors; Survival Rate; United States

Association of chronic kidney disease with the spectrum of ankle brachial index the CHS (Cardiovascular Health Study). - Ix, Joachim H; Katz, Ronit; de Boer, Ian H; Kestenbaum, Brian R; Allison, Matthew A; Siscovick, David S; Newman, Anne B; Sarnak, Mark J; Shlipak, Michael G; Criqui, Michael H (J Am Coll Cardiol, 2009)
OBJECTIVES: This study sought to determine the association of chronic kidney disease (CKD) with high ankle brachial index (ABI) measurement and to compare its strength with that of CKD with a low ABI. BACKGROUND: CKD is an important risk factor for cardiovascular disease (CVD) events. A high ABI, a marker of lower extremity arterial stiffness, is associated with CVD events and mortality. The association between CKD and high ABI is unknown. METHODS: The CHS (Cardiovascular Health Study) enrolled community-living people >65 years of age and measured kidney function and ABI. Glomerular filtration rate (GFR) was estimated using equations that incorporated either cystatin C or creatinine, and CKD was defined by estimated GFR <60 ml/min/1.73 m(2). The ABI was categorized as low (<0.90), low-normal (0.90 to 1.09), normal (1.10 to 1.40), and high (>1.40 or incompressible). Multinomial logistic regression was used to evaluate the associations of CKD with ABI categories. RESULTS: Among 4,513 participants, 23% had CKD, 13% had a low ABI, and 3% had a high ABI. In models adjusted for age, sex, race, hypertension, diabetes, smoking, body mass index, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and C-reactive protein, cystatin C-based CKD was associated with both low ABI (relative risk [RR]: 2.0; 95% confidence interval [CI]: 1.6 to 2.5; p <0.001) and high ABI (RR: 1.6; 95% CI: 1.0 to 2.3; p = 0.03). Results were similar when CKD was defined by creatinine. CONCLUSIONS: CKD is associated with both the high and the low extremes of ABI in community-living older people. Future studies should evaluate whether arterial stiffness is an important mechanism leading to CVD in people with CKD.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; C-Reactive Protein; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Female; Glomerular Filtration Rate; Humans; Kidney Diseases; Lipids; Male; Risk Factors

Change in cardiovascular risk factors with progression of kidney disease. - Fried, Linda F; Katz, Ronit; Cushman, Mary; Sarnak, Mark; Shlipak, Michael G; Kuller, Lewis; Newman, Anne B (Am J Nephrol, 2009)
BACKGROUND: Prior studies evaluating the relationship of kidney disease with cardiovascular risk factors have been limited by their cross-sectional design. We evaluated the change in lipids, inflammatory and procoagulant biomarkers with decline in kidney function in a nested case-cohort study in the Cardiovascular Health Study, a community-based study of adults aged >65 years. METHODS: Individuals with an increase in serum creatinine >or=0.3 mg/dl (baseline to 3 years later, n = 207) were matched to controls of similar age, race, gender, diabetes and baseline serum creatinine, but whose change in creatinine was <0.3 mg/dl. Baseline and change in risk factors were analyzed with conditional logistic regression. RESULTS: Changes in C-reactive protein were similar. In contrast, cases had larger increases in fibrinogen (OR 1.38 per standard deviation, 95% confidence interval 1.08-1.76) and factor VIII [1.38 (1.10-1.72)] and larger decreases in HDL [OR 0.80 (0.64, 1.00)]. Change in interleukin-6 was greater in cases than controls, but this did not persist after multivariate adjustment. However, in linear regression, change in interleukin-6 was correlated with change in creatinine. CONCLUSION: Cardiovascular risk factors and kidney function may change concurrently. This could lead to an increased risk of cardiovascular disease as kidney function worsens.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cholesterol, HDL; Creatinine; Diabetes Mellitus; Factor VIII; Female; Follow-Up Studies; Humans; Hypertension, Renal; Interleukin-6; Logistic Models; Male; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Vasculitis

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

Inflammation and stress-related candidate genes, plasma interleukin-6 levels, and longevity in older adults. - Walston, Jeremy D; Matteini, Amy M; Nievergelt, Caroline; Lange, Leslie A; Fallin, Dani M; Barzilai, Nir; Ziv, Elad; Pawlikowska, Ludmila; Kwok, Pui; Cummings, Steve R; Kooperberg, Charles; LaCroix, Andrea; et al. (Exp Gerontol, 2009)
Interleukin-6 (IL-6) is an inflammatory cytokine that influences the development of inflammatory and aging-related disorders and ultimately longevity. In order to study the influence of variants in genes that regulate inflammatory response on IL-6 levels and longevity, we screened a panel of 477 tag SNPs across 87 candidate genes in >5000 older participants from the population-based Cardiovascular Health Study (CHS). Baseline plasma IL-6 concentration was first confirmed as a strong predictor of all-cause mortality. Functional alleles of the IL6R and PARP1 genes were significantly associated with 15%-20% higher baseline IL-6 concentration per copy among CHS European-American (EA) participants (all p<10(-4)). In a case/control analysis nested within this EA cohort, the minor allele of PARP1 rs1805415 was nominally associated with decreased longevity (p=0.001), but there was no evidence of association between IL6R genotype and longevity. The PARP1 rs1805415--longevity association was subsequently replicated in one of two independent case/control studies. In a pooled analysis of all three studies, the "risk" of longevity associated with the minor allele of PARP1 rs1805415 was 0.79 (95%CI 0.62-1.02; p=0.07). These findings warrant further study of the potential role of PARP1 genotype in inflammatory and aging-related phenotypes.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Case-Control Studies; Female; Genetic Variation; Genotype; Humans; Inflammation; Interleukin-6; Longevity; Male; Phenotype; Poly (ADP-Ribose) Polymerase-1; Poly(ADP-ribose) Polymerases; Risk Factors

Lipoprotein-associated phospholipase A(2) and risk of congestive heart failure in older adults: the Cardiovascular Health Study. - Suzuki, Takeki; Solomon, Cam; Jenny, Nancy Swords; Tracy, Russell; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt; Cushman, Mary (Circ Heart Fail, 2009)
BACKGROUND: Inflammation may be a causative factor in congestive heart failure (CHF). Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is an inflammation marker associated with vascular risk. One previous study showed an association of Lp-PLA(2) activity with CHF risk, but there were only 94 CHF cases and Lp-PLA(2) antigen, which is available clinically in the United States, was not measured. METHODS AND RESULTS: We measured baseline Lp-PLA(2) antigen and activity in 3991 men and women without baseline CHF or cardiovascular disease who were participating in the Cardiovascular Health Study, a prospective observational study of adults 65 years or older. Cox proportional hazards models adjusted for age, sex, clinic site, race, low-density and high-density lipoprotein cholesterol, body mass index, systolic and diastolic blood pressure, hypertension, smoking status, pack-years, and diabetes were used to calculate hazard ratios and 95% CIs for incident CHF. Further models adjusted for coronary disease events during follow-up and C-reactive protein. Eight hundred twenty-nine participants developed CHF during 12.1 years. Adjusted hazard ratios for CHF with Lp-PLA(2) in the fourth compared with the first quartile were 1.44 (95% CI, 1.16 to 1.79) for Lp-PLA(2) antigen and 1.06 (95% CI, 0.84 to 1.32) for activity. Adjustment for incident coronary disease attenuated the hazard ratio for Lp-PLA(2) antigen to 1.26 (95% CI, 1.02 to 1.57), adjustment for C-reactive protein had minimal impact. CONCLUSIONS: Lp-PLA(2) antigen was associated with risk of future CHF in older people, independent of CHF and coronary risk factors, and partly mediated by coronary disease events. Further clinical and basic research is needed to better understand the role of Lp-PLA(2) in CHF.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Biomarkers; C-Reactive Protein; Female; Fibrinogen; Heart Failure; Humans; Incidence; Inflammation Mediators; Interleukin-6; Kaplan-Meier Estimate; Male; Population Surveillance; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Long-term function in an older cohort--the cardiovascular health study all stars study. - Newman, Anne B; Arnold, Alice M; Sachs, Michael C; Ives, Diane G; Cushman, Mary; Strotmeyer, Elsa S; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Fried, Linda P; Robbins, John (J Am Geriatr Soc, 2009)
OBJECTIVES: To evaluate shared and unique risk factors for maintaining physical and cognitive function into the ninth decade and beyond. DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: One thousand six hundred seventy-seven participants in the Cardiovascular Health Study All Stars Study, assessed in 2005/06. Median age was 85 (range 77-102), 66.5% were women, and 16.6% were black. MEASUREMENTS: Intact function was defined as no difficulty with any activities of daily living and a score of 80 or higher on the Modified Mini-Mental State Examination. Baseline characteristics assessed in 1992/93 included demographics, behavioral health factors, chronic disease history, subclinical disease markers, cardiovascular risk factors, and inflammatory markers. Multinomial logistic regression was used to compare risk for physical disability, cognitive impairment,and combined impairments with no functional impairment. RESULTS: Of the 1,677 participants evaluated in both domains, 891 (53%) were functionally intact. Continuous measures of function, including the Digit Symbol Substitution Test and gait speed, showed that all groups, including the most functional, had declined over time. The functional group had less decline but also tended to have higher starting values. Functional individuals had a higher baseline health profile than those with either or cognitive impairment or both impairments combined. Women and individuals with greater weight had higher rates of physical impairment but not cognitive impairment. Risk factors common to both types of impairment included cardiovascular disease and hypertension. CONCLUSION: Intact function was found in only approximately half of these older adults in the ninth decade and beyond. High baseline function and low vascular disease risk characterized functional aging.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Attention; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Follow-Up Studies; Gait; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Male; Memory, Short-Term; Mental Status Schedule; Proportional Hazards Models; Psychometrics; Risk Factors; United States

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Polysomnographic and health-related quality of life correlates of restless legs syndrome in the Sleep Heart Health Study. - Winkelman, John W; Redline, Susan; Baldwin, Carol M; Resnick, Helaine E; Newman, Anne B; Gottlieb, Daniel J (Sleep, 2009)
STUDY OBJECTIVES: Sleep disturbance is the primary clinical morbidity of restless legs syndrome (RLS). To date, sleep disturbance in RLS has been measured in (1) clinical samples with polysomnography (PSG) or (2) population-based samples by self-report. The objective of this study was to analyze sleep by PSG in a population-based sample with symptoms of RLS. DESIGN: Cross-sectional observational study. SETTING: Community-based. PARTICIPANTS: 3433 older men and women. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: RLS was evaluated using an 8-item self-administered questionnaire based on NIH diagnostic criteria and required symptoms occurring > or = five times per month and associated with at least moderate distress. Health-related quality of life (HRQOL) was determined using the SF-36. Unattended, in-home PSG was performed. Data were assessed using general linear models with adjustment for demographic, health-related variables, and apnea-hypopnea index (AHI). Subjects with RLS had longer adjusted mean sleep latency (39.8 vs 26.4 min, P < 0.0001) and higher arousal index (20.1 vs 18.0, P = 0.0145) than those without RLS. Sleep latency increased progressively as the frequency of RLS symptoms increased from 5-15 days per month to 6-7 days per week. No differences in sleep stage percentages were observed between participants with and without RLS. Subjects with RLS also reported poorer HRQOL in all physical domains as well as in the Mental Health and Vitality domains. CONCLUSIONS: These novel PSG data from a nonclinical, community-based sample of individuals with RLS document sleep disturbance in the home even in individuals with intermittent symptoms.
Keywords: Adult; Aged; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Polysomnography; Prospective Studies; Quality of Life; Restless Legs Syndrome; Sleep Initiation and Maintenance Disorders; Statistics as Topic

Prospective study of sleep-disordered breathing and hypertension: the Sleep Heart Health Study. - O'Connor, George T; Caffo, Brian; Newman, Anne B; Quan, Stuart F; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Samet, Jonathan; Shahar, Eyal (Am J Respir Crit Care Med, 2009)
RATIONALE: Cross-sectional epidemiologic studies show an association between sleep-disordered breathing and hypertension, but only one cohort study has examined sleep-disordered breathing as a risk factor for incident hypertension. OBJECTIVES: To examine whether sleep-disordered breathing increases the risk of incident hypertension among persons 40 years of age and older. METHODS: In a prospective cohort study, we analyzed data from 2,470 participants who at baseline did not have hypertension, defined as blood pressure of at least 140/90 mm Hg or taking antihypertensive medication. The apnea-hypopnea index (AHI), the number of apneas plus hypopneas per hour of sleep, was measured by overnight in-home polysomnography. We estimated odds ratios for developing hypertension during 5 years of follow-up according to baseline AHI. MEASUREMENTS AND MAIN RESULTS: The odds ratios for incident hypertension increased with increasing baseline AHI; however, this relationship was attenuated and not statistically significant after adjustment for baseline body-mass index. Although not statistically significant, the observed association between a baseline AHI greater than 30 and future hypertension (odds ratio, 1.51; 95% confidence interval, 0.93-2.47) does not exclude the possibility of a modest association. CONCLUSIONS: Among middle-aged and older persons without hypertension, much of the relationship between AHI and risk of incident hypertension was accounted for by obesity. After adjustment for body mass index, the AHI was not a significant predictor of future hypertension, although a modest influence of an AHI greater than 30 on hypertension could not be excluded.
Keywords: Adult; Blood Pressure; Confidence Intervals; Cross-Sectional Studies; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Middle Aged; Odds Ratio; Polysomnography; Prognosis; Prospective Studies; Risk Factors; Sleep Apnea Syndromes; Time Factors; United States

Rapid decline of kidney function increases cardiovascular risk in the elderly. - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan; Siscovick, David; Fried, Linda; Newman, Anne; Rifkin, Dena; Sarnak, Mark J (J Am Soc Nephrol, 2009)
Chronic kidney disease (CKD), defined at a specific time point, is an important risk factor for cardiovascular disease. Whether the rate of kidney function decline contributes additional cardiovascular risk is unknown. In the Cardiovascular Health Study, we compared the associations of changes in kidney function during the first 7 yr with the incidence of heart failure (HF), myocardial infarction (MI), stroke, and peripheral arterial disease (PAD) during the subsequent 8 yr. We defined a rapid decline in cystatin C-based estimated GFR as >3 ml/min per 1.73 m(2)/yr, on the basis of determination at baseline, year 3, and year 7. Among eligible participants, 1083 (24%) had rapid kidney decline. The incidence of each type of cardiovascular event was significantly higher among patients with rapid decline (all P < 0.001). After multivariate adjustment for demographics, cardiovascular disease risk factors, and baseline kidney function, rapid kidney function decline was significantly associated with HF (adjusted hazard ratio [HR] 1.32; 95% confidence interval [CI] 1.13 to 1.53), MI (HR 1.48; 95% CI 1.21 to 1.83), and PAD (HR 1.67; 95% CI 1.02 to 2.75) but not with stroke (HR 1.19; 95% CI 0.97 to 1.45). The association of rapid decline with each outcome did not differ by the presence or absence of CKD. In conclusion, declining kidney function associates with higher risk for HF, MI, and PAD among patients with or without CKD.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Heart Failure; Humans; Longitudinal Studies; Male; Myocardial Infarction; Peripheral Vascular Diseases; Renal Insufficiency, Chronic; Risk Factors; Stroke; Time Factors; United States

Rate of kidney function decline in older adults: a comparison using creatinine and cystatin C. - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda F; Newman, Anne B; Siscovick, David S; Stevens, Lesley; Sarnak, Mark J (Am J Nephrol, 2009)
BACKGROUND/AIMS: The aim of this study was to determine the decline in the estimated glomerular filtration rate (eGFR) in elderly persons and to compare estimates based on creatinine and cystatin C. METHODS: In the Cardiovascular Health Study, GFR changes in an elderly cohort were estimated from serum creatinine and cystatin C measured at baseline, year 3 and year 7 in 4,380 participants (age 72 +/- 5 years at entry). Outcomes were mean eGFR decline, incident chronic kidney disease (CKD) and rapid decline in eGFR (annual loss >3 ml/min/1.73 m(2)). RESULTS: Mean annual eGFR loss as estimated from creatinine was 0.4 +/- 3.6 ml/min/1.73 m(2), with 16% of the participants experiencing a rapid decline. Mean eGFR loss as estimated from cystatin C was 1.8 +/- 2.6, with 25% of the participants experiencing a rapid decline (p < 0.001 for both). Among participants without baseline CKD, incident CKD was detected at year 7 in 10% (n = 263) using creatinine and 19% (n = 544) using cystatin C (p < 0.001). Increasing age was the strongest predictor of rapid decline; adjusted odds ratios were 1.38 (1.16-1.65), 1.62 (1.31-1.99) and 2.96 (2.28-3.84) for participants aged 70-74, 75-79 and 80+ at baseline, compared with those aged 65-69. CONCLUSION: In elderly persons, cystatin C estimated substantially larger declines in kidney function than creatinine did. Defining the optimal measurement of kidney function in elderly persons should be a high priority for future research.
Keywords: Age Factors; Aged; Creatinine; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Risk Factors

Sleep-disordered breathing and frailty in the Cardiovascular Health Study Cohort. - Endeshaw, Yohannes W; Unruh, Mark L; Kutner, Michael; Newman, Anne B; Bliwise, Donald L (Am J Epidemiol, 2009)
Sleep-disordered breathing (SDB) is associated with pathophysiology that may influence the development and progression of frailty. Using data collected in 1995-1996, the authors explored the relation between SDB and components of frailty among 1,042 participants of the Cardiovascular Health Study. Diagnosis of SDB was based on the results of overnight polysomnography, and severe SDB was defined as an apnea-hypopnea index of >30 per hour of sleep. Slow walking speed, low grip strength, exhaustion, low physical activity, and unexplained weight loss were referred to as frailty indicator variables. There were 584 (56%) female and 458 (44%) male participants, and the mean age was 77 (standard deviation, 4) years. There was independent association between severe SDB and 1 or more frailty indicator variables (adjusted odds ratio = 4.85, 95% confidence interval: 1.40, 16.78), slow walking speed (adjusted odds ratio = 2.67, 95% confidence interval: 1.04, 6.84), and low grip strength (adjusted odds ratio = 3.29, 95% confidence interval: 1.36, 7.96) among female study participants. The finding of an independent association between SDB and frailty indicator variables among older women could have important implications in interventions aimed at preventing or delaying the progression of frailty.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cardiovascular System; Cohort Studies; Confidence Intervals; Exercise Tolerance; Female; Frail Elderly; Hand Strength; Humans; Logistic Models; Male; Mobility Limitation; Models, Statistical; Motor Activity; Muscle Strength; Odds Ratio; Polysomnography; Psychometrics; Risk Factors; Sleep Apnea, Obstructive; Weight Loss

Sleep-disordered breathing and mortality: a prospective cohort study. - Punjabi, Naresh M; Caffo, Brian S; Goodwin, James L; Gottlieb, Daniel J; Newman, Anne B; O'Connor, George T; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Robbins, John A; Shahar, Eyal; Unruh, Mark L; et al. (PLoS Med, 2009)
BACKGROUND: Sleep-disordered breathing is a common condition associated with adverse health outcomes including hypertension and cardiovascular disease. The overall objective of this study was to determine whether sleep-disordered breathing and its sequelae of intermittent hypoxemia and recurrent arousals are associated with mortality in a community sample of adults aged 40 years or older. METHODS AND FINDINGS: We prospectively examined whether sleep-disordered breathing was associated with an increased risk of death from any cause in 6,441 men and women participating in the Sleep Heart Health Study. Sleep-disordered breathing was assessed with the apnea-hypopnea index (AHI) based on an in-home polysomnogram. Survival analysis and proportional hazards regression models were used to calculate hazard ratios for mortality after adjusting for age, sex, race, smoking status, body mass index, and prevalent medical conditions. The average follow-up period for the cohort was 8.2 y during which 1,047 participants (587 men and 460 women) died. Compared to those without sleep-disordered breathing (AHI: <5 events/h), the fully adjusted hazard ratios for all-cause mortality in those with mild (AHI: 5.0-14.9 events/h), moderate (AHI: 15.0-29.9 events/h), and severe (AHI: >or=30.0 events/h) sleep-disordered breathing were 0.93 (95% CI: 0.80-1.08), 1.17 (95% CI: 0.97-1.42), and 1.46 (95% CI: 1.14-1.86), respectively. Stratified analyses by sex and age showed that the increased risk of death associated with severe sleep-disordered breathing was statistically significant in men aged 40-70 y (hazard ratio: 2.09; 95% CI: 1.31-3.33). Measures of sleep-related intermittent hypoxemia, but not sleep fragmentation, were independently associated with all-cause mortality. Coronary artery disease-related mortality associated with sleep-disordered breathing showed a pattern of association similar to all-cause mortality. CONCLUSIONS: Sleep-disordered breathing is associated with all-cause mortality and specifically that due to coronary artery disease, particularly in men aged 40-70 y with severe sleep-disordered breathing. Please see later in the article for the Editors' Summary.
Keywords: Aged; Coronary Artery Disease; Female; Humans; Hypoxia; Male; Middle Aged; Odds Ratio; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Survival Analysis

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Total and cause-specific mortality in the cardiovascular health study. - Newman, Anne B; Sachs, Michael C; Arnold, Alice M; Fried, Linda P; Kronmal, Richard; Cushman, Mary; Psaty, Bruce M; Harris, Tamara B; Robbins, John A; Burke, Gregory L; Kuller, Lewis H; Lumley, Thomas (J Gerontol A Biol Sci Med Sci, 2009)
BACKGROUND: Few cohort studies have adequate numbers of carefully reviewed deaths to allow an analysis of unique and shared risk factors for cause-specific mortality. Shared risk factors could be targeted for prevention of premature death and the study of longevity. METHODS: A total of 5,888 community-dwelling persons aged 65 years or older living in four communities in the United States participated in the Cardiovascular Health Study cohort. Participants were initially recruited from 1989 to 1990; an additional 687 black participants were recruited in 1992-1993. The average length of follow-up was 16 years. Total and cause-specific mortality, including cardiovascular disease, stroke, cancer, dementia, pulmonary disease, infection, and other cause, were examined as outcomes. Variables previously associated with total mortality were examined for each cause of death using Cox proportional hazard models. RESULTS: Multiple risk factors were related to total mortality. When examining specific causes, many factors were related to cardiovascular death, whereas fewer were related to other causes. For most causes, risk factors were specific for that cause. For example, apolipoprotein E epsilon4 was strongly associated for dementia death and forced vital capacity with pulmonary death. Age, male sex, markers of inflammation, and cognitive function were related to multiple causes of death. CONCLUSIONS: In these older adults, associations of risk factors with a given cause of death were related to specific deficits in that same organ system. Inflammation may represent a common pathway to all causes of death.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cause of Death; Chronic Disease; Cohort Studies; Female; Geriatric Assessment; Health Surveys; Humans; Kaplan-Meier Estimate; Male; Probability; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Survival Analysis; United States

Trajectories of dehydroepiandrosterone sulfate predict mortality in older adults: the cardiovascular health study. - Cappola, Anne R; O'Meara, Ellen S; Guo, Wensheng; Bartz, Traci M; Fried, Linda P; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2009)
BACKGROUND: Dehydroepiandrosterone sulfate (DHEAS) has been proposed as an antiaging hormone, but its importance is unclear. Assessment of an individual's ability to maintain a DHEAS set point, through examination of multiple DHEAS levels over time, may provide insight into biologic aging. METHODS: Using Cox proportional hazard models, we examined the relationship between DHEAS trajectory patterns and all-cause death in 950 individuals aged >or=65 years who were enrolled in the Cardiovascular Health Study and had DHEAS levels measured at three to six time points. RESULTS: Overall, there was a slight decline in DHEAS levels over time (-0.013 microg/mL/y). Three trajectory components were examined: slope, variability, and baseline DHEAS. When examined individually, a steep decline or extreme variability in DHEAS levels was associated with higher mortality (p < .001 for each), whereas baseline DHEAS level was not. In adjusted models including all three components, steep decline (hazard ratio [HR] 1.75, confidence interval [CI] 1.32-2.33) and extreme variability (HR 1.89, CI 1.47-2.43) remained significant predictors of mortality, whereas baseline DHEAS level remained unpredictive of mortality (HR 0.97 per standard deviation, CI 0.88-1.07). The effect of trajectory pattern was more pronounced in men than in women. Individuals with both a steep decline and extreme variability in DHEAS levels had a significantly higher death rate than those with neither pattern (141 vs 48 deaths per 1,000 person-years, p < .001). CONCLUSIONS: Our data show significant heterogeneity in the individual trajectories of DHEAS levels and suggest that these trajectories provide important biologic information about the rate of aging, whereas the DHEAS level itself does not.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; Cardiovascular Diseases; Cause of Death; Cohort Studies; Dehydroepiandrosterone Sulfate; Female; Geriatric Assessment; Humans; Longitudinal Studies; Male; Predictive Value of Tests; Proportional Hazards Models; Risk Assessment; Severity of Illness Index; Sex Factors; Survival Analysis; United States

Using telephone and informant assessments to estimate missing Modified Mini-Mental State Exam scores and rates of cognitive decline. The cardiovascular health study. - Arnold, Alice M; Newman, Anne B; Dermond, Norma; Haan, Mary; Fitzpatrick, Annette (Neuroepidemiology, 2009)
AIM: To estimate an equivalent to the Modified Mini-Mental State Exam (3MSE), and to compare changes in the 3MSE with and without the estimated scores. METHODS: Comparability study on a subset of 405 participants, aged >or=70 years, from the Cardiovascular Health Study (CHS), a longitudinal study in 4 United States communities. The 3MSE, the Telephone Interview for Cognitive Status (TICS) and the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) were administered within 30 days of one another. Regression models were developed to predict the 3MSE score from the TICS and/or IQCODE, and the predicted values were used to estimate missing 3MSE scores in longitudinal follow-up of 4,274 CHS participants. RESULTS: The TICS explained 67% of the variability in 3MSE scores, with a correlation of 0.82 between predicted and observed scores. The IQCODE alone was not a good estimate of 3MSE score, but improved the model fit when added to the TICS model. Using estimated 3MSE scores classified more participants with low cognition, and rates of decline were greater than when only the observed 3MSE scores were considered. CONCLUSIONS: 3MSE scores can be reliably estimated from the TICS, with or without the IQCODE. Incorporating these estimates captured more cognitive decline in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Interviews as Topic; Longitudinal Studies; Male; Predictive Value of Tests; Psychiatric Status Rating Scales; Regression Analysis; Risk Factors; ROC Curve; United States

Variants in ZFHX3 are associated with atrial fibrillation in individuals of European ancestry. - Benjamin, Emelia J; Rice, Kenneth M; Arking, Dan E; Pfeufer, Arne; van Noord, Charlotte; Smith, Albert V; Schnabel, Renate B; Bis, Joshua C; Boerwinkle, Eric; Sinner, Moritz F; Dehghan, Abbas; Lubitz, Steven A; et al. (Nat Genet, 2009)
We conducted meta-analyses of genome-wide association studies for atrial fibrillation (AF) in participants from five community-based cohorts. Meta-analyses of 896 prevalent (15,768 referents) and 2,517 incident (21,337 referents) AF cases identified a new locus for AF (ZFHX3, rs2106261, risk ratio RR = 1.19; P = 2.3 x 10(-7)). We replicated this association in an independent cohort from the German AF Network (odds ratio = 1.44; P = 1.6 x 10(-11); combined RR = 1.25; combined P = 1.8 x 10(-15)).
Keywords: Atrial Fibrillation; Chromosomes, Human, Pair 16; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeodomain Proteins; Humans; Meta-Analysis as Topic; Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results

Admixture mapping of ankle-arm index: identification of a candidate locus associated with peripheral arterial disease. - Scherer, M L; Nalls, M A; Pawlikowska, L; Ziv, E; Mitchell, G; Huntsman, S; Hu, D; Sutton-Tyrrell, K; Lakatta, E G; Hsueh, W-C; Newman, A B; Tandon, A; et al. (J Med Genet, 2010)
BACKGROUND: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality, and has a higher prevalence in African Americans than Caucasians. Ankle-arm index (AAI) is the ratio of systolic blood pressure in the leg to that in the arm, and, when low, is a marker of PAD. METHODS: The authors used an admixture mapping approach to search for genetic loci associated with low AAI. Using data from 1040 African American participants in the observational, population based Health, Aging, and Body Composition Study who were genotyped at 1322 single nucleotide polymorphisms (SNPs) that are informative for African versus European ancestry and span the entire genome, we estimated genetic ancestry in each chromosomal region and then tested the association between AAI and genetic ancestry at each locus. RESULTS: The authors found a region of chromosome 11 that reaches its peak between 80 and 82 Mb associated with low AAI (p<0.001 for rs12289502 and rs9665943, both within this region). 753 African American participants in the observational, population based Cardiovascular Health Study were genotyped at rs9665943 to test the reproducibility of this association, and this association was also statistically significant (odds ratio (OR) for homozygous African genotype 1.59, 95% confidence interval (CI) 1.12 to 2.27). Another candidate SNP (rs1042602) in the same genomic region was tested in both populations, and was also found to be significantly associated with low AAI in both populations (OR for homozygous African genotype 1.89, 95% CI 1.29 to 2.76). CONCLUSION: This study identifies a novel region of chromosome 11 representing an area with a potential candidate gene associated with PAD in African Americans.
Keywords: African Americans; Aged; Ankle Brachial Index; Chromosome Mapping; Chromosomes, Human, Pair 11; Female; Genetic Loci; Genotype; Humans; Male; Odds Ratio; Peripheral Vascular Diseases; Polymorphism, Single Nucleotide

Age and cystatin C in healthy adults: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Katz, Ronit; Fried, Linda F; Newman, Anne B; Canada, Robert B; Harris, Tamara; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Nephrol Dial Transplant, 2010)
BACKGROUND: Kidney function declines with age, but a substantial portion of this decline has been attributed to the higher prevalence of risk factors for kidney disease at older ages. The effect of age on kidney function has not been well described in a healthy population across a wide age spectrum. METHODS: The authors pooled individual-level cross-sectional data from 18 253 persons aged 28-100 years in four studies: the Cardiovascular Health Study; the Health, Aging and Body Composition Study; the Multi-Ethnic Study of Atherosclerosis and the Prevention of Renal and Vascular End-Stage Disease cohort. Kidney function was measured by cystatin C. Clinical risk factors for kidney disease included diabetes, hypertension, obesity, smoking, coronary heart disease, cerebrovascular disease, peripheral arterial disease and heart failure. RESULTS: Across the age range, there was a strong, non-linear association of age with cystatin C concentration. This association was substantial, even among participants free of clinical risk factors for kidney disease; mean cystatin C levels were 46% higher in participants 80 and older compared with those <40 years (1.06 versus 0.72 mg/L, P < 0.001). Participants with one or more risk factors had higher cystatin C concentrations for a given age, and the age association was slightly stronger (P < 0.001 for age and risk factor interaction). CONCLUSIONS: There is a strong, non-linear association of age with kidney function, even in healthy individuals. An important area for research will be to investigate the mechanisms that lead to deterioration of kidney function in apparently healthy persons.
Keywords: Adult; Aged; Aged, 80 and over; Cross-Sectional Studies; Cystatin C; Humans; Kidney; Middle Aged; Reference Values

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Association between adiposity in midlife and older age and risk of diabetes in older adults. - Biggs, Mary L; Mukamal, Kenneth J; Luchsinger, José A; Ix, Joachim H; Carnethon, Mercedes R; Newman, Anne B; de Boer, Ian H; Strotmeyer, Elsa S; Mozaffarian, Dariush; Siscovick, David S (JAMA, 2010)
CONTEXT: Adiposity is a well-recognized risk factor for type 2 diabetes among young and middle-aged adults, but the relationship between body composition and type 2 diabetes is not well described among older adults. OBJECTIVE: To examine the relationship between adiposity, changes in adiposity, and risk of incident type 2 diabetes in adults 65 years of age and older. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study (1989-2007) of 4193 men and women 65 years of age and older in the Cardiovascular Health Study. Measures of adiposity were derived from anthropometry and bioelectrical impedance data at baseline and anthropometry repeated 3 years later. MAIN OUTCOME MEASURE: Incident diabetes was ascertained based on use of antidiabetic medication or a fasting glucose level of 126 mg/dL or greater. RESULTS: Over median follow-up of 12.4 years (range, 0.9-17.8 years), 339 cases of incident diabetes were ascertained (7.1/1000 person-years). The adjusted hazard ratio (HR) (95% confidence interval [CI]) of type 2 diabetes for participants in the highest quintile of baseline measures compared with those in the lowest was 4.3 (95% CI, 2.9-6.5) for body mass index (BMI [calculated as weight in kilograms divided by height in meters squared]), 3.0 (95% CI, 2.0-4.3) for BMI at 50 years of age, 4.2 (95% CI, 2.8-6.4) for weight, 4.0 (95% CI, 2.6-6.0) for fat mass, 4.2 (95% CI, 2.8-6.2) for waist circumference, 2.4 (95% CI, 1.6-3.5) for waist-hip ratio, and 3.8 (95% CI, 2.6-5.5) for waist-height ratio. However, when stratified by age, participants 75 years of age and older had HRs approximately half as large as those 65 to 74 years of age. Compared with weight-stable participants (+/-2 kg), those who gained the most weight from 50 years of age to baseline (> or = 9 kg), and from baseline to the third follow-up visit (> or = 6 kg), had HRs for type 2 diabetes of 2.8 (95% CI, 1.9-4.3) and 2.0 (95% CI, 1.1-3.7), respectively. Participants with a greater than 10-cm increase in waist size from baseline to the third follow-up visit had an HR of type 2 diabetes of 1.7 (95% CI, 1.1-2.8) compared with those who gained or lost 2 cm or less. CONCLUSION: Among older adults, overall and central adiposity, and weight gain during middle age and after the age of 65 years are associated with risk of diabetes.
Keywords: Adiposity; Age Factors; Aged; Body Mass Index; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States; Weight Gain

Association between baseline kidney function and change in CRP: an analysis of the cardiovascular health study. - Rifkin, Dena E; Katz, Ronit; Fried, Linda F; Kestenbaum, Bryan; Jenny, Nancy Swords; Newman, Anne B; Siscovick, David S; Shlipak, Michael G; Sarnak, Mark J (Nephron Clin Pract, 2010)
BACKGROUND: In cross-sectional analyses, C-reactive protein (CRP) levels are inversely related to levels of kidney function. The relationship between kidney function and subsequent changes in CRP is unknown. METHODS: We studied 4,364 individuals from the Cardiovascular Health Study, a longitudinal cohort of community-dwelling older adults. Baseline eGFRcys was estimated using cystatin C. CRP was measured at baseline and after 3 and 7 years of follow-up; slopes of change in CRP were calculated. RESULTS: The mean (SD) age of the cohort was 72 (5.2) years; mean (SD) eGFRcys was 78.9 (18.4) ml/min/1.73 m(2). The median (interquartile range IQR) baseline CRP was 2.39 (1.22, 4.33) mg/l; the median (IQR) yearly change in CRP was -0.0051 (-0.020 to 0.27) mg/l/year. After adjustment for demographic characteristics and the initial level of CRP, each standard deviation lower baseline eGFR was associated with a small and non-significant yearly increase in CRP (0.032 mg/l/year; 95% CI: -0.005 to 0.070, p = 0.094). CONCLUSIONS: We did not find a relationship between eGFR and subsequent changes in CRP. The association between kidney function and CRP in cross-sectional analyses may reflect unmeasured confounding by atherosclerosis; alternatively, the burden of comorbidity and interval mortality in this population may have masked a stronger longitudinal association between kidney function and change in CRP. Further study in younger populations may clarify whether impaired kidney function leads to change in inflammation over time.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney Function Tests; Longitudinal Studies; Male; Residence Characteristics

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Body weight dynamics and their association with physical function and mortality in older adults: the Cardiovascular Health Study. - Arnold, Alice M; Newman, Anne B; Cushman, Mary; Ding, Jingzhong; Kritchevsky, Stephen (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: To estimate the associations of weight dynamics with physical functioning and mortality in older adults. METHODS: Longitudinal cohort study using prospectively collected data on weight, physical function, and health status in four U.S. Communities in the Cardiovascular Health Study. Included were 3,278 participants (2,013 women and 541 African Americans), aged 65 or older at enrollment, who had at least five weight measurements. Weight was measured at annual clinic visits between 1992 and 1999, and summary measures of mean weight, coefficient of variation, average annual weight change, and episodes of loss and gain (cycling) were calculated. Participants were followed from 1999 to 2006 for activities of daily living (ADL) difficulty, incident mobility limitations, and mortality. RESULTS: Higher mean weight, weight variability, and weight cycling increased the risk of new onset of ADL difficulties and mobility limitations. After adjustment for risk factors, the hazard ratio (95% confidence interval) for weight cycling for incident ADL impairment was 1.28 (1.12, 1.47), similar to that for several comorbidities in our model, including cancer and diabetes. Lower weight, weight loss, higher variability, and weight cycling were all risk factors for mortality, after adjustment for demographic risk factors, height, self-report health status, and comorbidities. CONCLUSIONS: Variations in weight are important indicators of future physical limitations and mortality in the elderly and may reflect difficulties in maintaining homeostasis throughout older ages. Monitoring the weight of an older person for fluctuations or episodes of both loss and gain is an important aspect of geriatric care.
Keywords: Activities of Daily Living; Age Factors; Aged, 80 and over; Body Weight; Cardiovascular Diseases; Female; Follow-Up Studies; Health Status; Humans; Longevity; Male; Prospective Studies; Risk Factors; Survival Rate; United States

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Cardiovascular disease is associated with greater incident dehydroepiandrosterone sulfate decline in the oldest old: the cardiovascular health study all stars study. - Sanders, Jason L; Boudreau, Robert M; Cappola, Anne R; Arnold, Alice M; Robbins, John; Cushman, Mary; Newman, Anne B (J Am Geriatr Soc, 2010)
OBJECTIVES: To describe cross-sectional and longitudinal associations with dehydroepiandrosterone sulfate (DHEAS) and change in DHEAS with age. DESIGN: Longitudinal cohort study. SETTING: Pittsburgh, Pennsylvania. PARTICIPANTS: Cardiovascular Health Study All Stars study participants assessed in 2005/06 (N=989, mean age 85.2, 63.5% women, 16.5% African American). MEASUREMENTS: Health characteristics were assessed in 2005/06 according to DHEAS level, mean DHEAS and DHEAS change across age categories were tested, and linear and logistic regression was used to identify factors present in 1996/97 associated with continuous and categorical DHEAS change. RESULTS: Mean +/- standard deviation DHEAS was 0.555 +/- 0.414 microg/mL in 1996/97 and 0.482 +/- 0.449 microg/mL in 2005/06 for women and 0.845 +/- 0.520 microg/mL in 1996/97 and 0.658 +/- 0.516 microg/mL in 2005/06 for men. In 2005/06, DHEAS was lower in women and subjects with cardiovascular disease (CVD) and chronic pulmonary disease and higher for African Americans and subjects with hypertension and high cholesterol. Mean DHEAS change was greater in men (-0.200 microg/mL) than in women (-0.078 microg/mL) (P<.001). Each 1-year increase in age attenuated the effect of male sex by 0.01 microg/mL (P=.009), abolishing the sex difference in DHEAS change by age 79. Presence of CVD before the study period was associated with greater absolute DHEAS change (beta=-0.04 microg/mL, P=.04) and with the fourth quartile of DHEAS change versus the first to third quartiles (odds ratio=1.46, 95% confidence interval=1.03-2.05). CONCLUSION: DHEAS change continues into very old age, is not homogenous, is affected by sex, and is associated with prevalent CVD. Future studies should investigate factors that might accelerate DHEAS decline.
Keywords: Age Distribution; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cross-Sectional Studies; Dehydroepiandrosterone Sulfate; Female; Humans; Longitudinal Studies; Male; Multivariate Analysis; Regression Analysis; Sex Distribution; United States

Change in circulating adiponectin in advanced old age: determinants and impact on physical function and mortality. The Cardiovascular Health Study All Stars Study. - Kizer, Jorge R; Arnold, Alice M; Strotmeyer, Elsa S; Ives, Diane G; Cushman, Mary; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Cross-sectional studies show that adiponectin is higher in older than in younger adults but long-term change in adiponectin, its determinants, and its relationship to functional decline or survival in the elderly population have not been evaluated. METHODS: We investigated predictors of longitudinal change in adiponectin, and the association of this adipokine or its antecedent change with physical deterioration and all-cause mortality in 988 participants in a population-based study who completed examinations in 1996-1997 and 2005-2006, had serial adiponectin measurements and underwent follow-up through June 2009. RESULTS: Adiponectin level rose significantly during follow-up, but the increase was smaller in blacks, was associated with declining weight or fasting glucose and, in men, lower albumin, and was affected by medications. Adiponectin was independently associated with greater physical decline, but the relationship for adiponectin change was driven by concomitant weight decrease. Both adiponectin and its change independently predicted mortality, even after adjustment for weight change. The association for adiponectin and mortality was observed in whites but not in blacks and only for levels in the upper range (hazard ratio = 1.85, 95% confidence interval = 1.36-2.52 per SD ≥ 20 mg/L), whereas that for adiponectin change was linear throughout in both racial groups (hazard ratio = 1.30, 95% confidence interval = 1.10-1.52 per SD). CONCLUSIONS: Adiponectin levels increase over time in long-lived adults and are associated with greater physical disability and mortality. Such increases may occur in response to age-related homeostatic dysregulation. Additional investigation is required to define the underlying mechanisms and whether this represents a marker or causal factor for mortality in this age group.
Keywords: Adiponectin; Age Factors; Aged; Aging; Analysis of Variance; Cardiovascular Diseases; Cause of Death; Chi-Square Distribution; Cohort Studies; Cross-Sectional Studies; Female; Health Status; Humans; Linear Models; Male; Physical Fitness; Proportional Hazards Models; Risk Factors; Sex Factors; Time Factors; United States

Chronic medical conditions and the sex-based disparity in disability: the Cardiovascular Health Study. - Whitson, Heather E; Landerman, Lawrence R; Newman, Anne B; Fried, Linda P; Pieper, Carl F; Cohen, Harvey Jay (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Older women experience disability more commonly than their male peers. This disparity may be due, in part, to sex-based differences in the prevalence or the disabling effects of common medical conditions. The objectives of this analysis were to (a) quantify the extent to which excess disability in women is explained by higher prevalence of selected medical conditions and (b) evaluate whether the same conditions have differing effects on disability in men and women. METHODS: We analyzed cross-sectional data from 5,888 community-dwelling older men and women. Disability was defined as difficulty with greater than or equal to one activity of daily living. Thirteen medical conditions were assessed by self-report, testing, or record review. RESULTS: Controlling for age, race, education, and marital status, women were more likely to experience disability (odds ratio = 1.70, 95% confidence interval = 1.36-2.11). Higher prevalence of arthritis and obesity in women explained 30.2% and 12.9%, respectively, of the sex-based difference in disability rates, whereas male prevalent diseases like vascular conditions and emphysema narrowed the disability gap. Women with arthritis, hearing problems, coronary artery disease, congestive heart failure, stroke, and claudication were more likely to exhibit disability compared with men with the same conditions (p < .001). CONCLUSIONS: Efforts to lessen sex-based inequality in disability should focus on reducing the prevalence of arthritis and obesity. Future generations may see greater functional disparity if rates of vascular disease and emphysema rise among women. Several conditions were more often associated with disability in women, suggesting additional sex-based differences in the disablement process.
Keywords: Aged; Arthritis; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Comorbidity; Cross-Sectional Studies; Disabled Persons; Emphysema; Female; Hearing Disorders; Humans; Male; Obesity; Prevalence; Sex Distribution

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Concurrent change in dehydroepiandrosterone sulfate and functional performance in the oldest old: results from the Cardiovascular Health Study All Stars study. - Sanders, J L; Cappola, A R; Arnold, A M; Boudreau, R M; Chaves, P H; Robbins, J; Cushman, M; Newman, A B (J Gerontol A Biol Sci Med Sci, 2010)
INTRODUCTION: The correlation between dehydroepiandrosterone sulfate (DHEAS) decline and age led to the hypothesis that DHEAS might be a marker of primary aging, though conflicting data from observational studies of mortality do not support this. We evaluated concurrent DHEAS and functional decline in a very old cohort to test if DHEAS change tracks with functional change during aging. METHODS: DHEAS and functional performance (gait speed, grip strength, Modified Mini-Mental State Examination [3MSE] score, and digit symbol substitution test [DSST] score) were measured in 1996-1997 and 2005-2006 in 989 participants in the Cardiovascular Health Study All Stars study (mean age 85.2 years in 2005-2006, 63.5% women and 16.5% African American). We used multivariable linear regression to test the association of DHEAS decline with functional decline. RESULTS: After adjustment, each standard deviation decrease in DHEAS was associated with greater declines in gait speed (0.12 m/s, p = .01), grip strength (0.09 kg, p = .03), 3MSE score (0.13 points, p < .001), and DSST score (0.14 points, p = .001) in women only. Additional adjustment for baseline DHEAS attenuated the association with grip strength but did not alter other estimates appreciably, and baseline DHEAS was unassociated with functional decline. CONCLUSIONS: In this cohort of very old individuals, DHEAS decline tracked with declines in gait speed, 3MSE score, and DSST score, but not grip strength, in women independent of baseline DHEAS level. DHEAS decline might be a marker for age-associated performance decline, but its relevance is specific to women.
Keywords: Aged, 80 and over; Biomarkers; Cognition; Cohort Studies; Dehydroepiandrosterone Sulfate; Female; Gait; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Sex Factors; United States

CRP gene variation and risk of community-acquired pneumonia. - Mukamal, Kenneth J; Pai, Jennifer K; O'Meara, Ellen S; Tracy, Russell P; Psaty, Bruce M; Kuller, Lewis H; Newman, Anne B; Yende, Sachin; Curhan, Gary C; Siscovick, David S; Rimm, Eric B (Respirology, 2010)
BACKGROUND AND OBJECTIVE: CRP has several potentially antibacterial effects, and variation in the CRP gene is known to influence CRP levels. Whether this variation influences risk of infection, and hence whether CRP has anti-infective activity in humans, is uncertain. METHODS: We evaluated a series of haplotype-tagging single nucleotide polymorphisms among 5374 individuals in the Cardiovascular Health Study, a cohort of older adults from four communities, who were followed for community-acquired pneumonia for 12-13 years. Secondarily, we evaluated whether these polymorphisms varied among men in the Health Professionals Follow-up Study who self-reported pneumonia on biennial questionnaires. RESULTS: There were 581 (507 white and 74 black) Cardiovascular Health Study participants with incident hospitalizations for pneumonia. No single nucleotide polymorphism or haplotypes were associated with risk among white Cardiovascular Health Study participants. Among black participants, the haplotype tagged by A790T was associated with lower risk of incident pneumonia (hazard ratio 0.5; 95% confidence interval: 0.3-0.9) and with higher CRP levels. In Health Professionals Follow-up Study, a separate haplotype was associated with less frequent self-reported pneumonia but not with circulating CRP levels. CONCLUSIONS: Some genetic variants in CRP may be associated with risk of pneumonia, but haplotypes associated with risk are variably associated with baseline CRP levels. If CRP is a relevant component of innate immunity in humans, the inducibility or tissue-specificity of expression may be at least as important as chronic circulating levels.
Keywords: African Americans; Aged; Aged, 80 and over; Body Mass Index; C-Reactive Protein; Cohort Studies; Community-Acquired Infections; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Pneumonia; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

Egg consumption and risk of type 2 diabetes in older adults. - Djoussé, Luc; Kamineni, Aruna; Nelson, Tracy L; Carnethon, Mercedes; Mozaffarian, Dariush; Siscovick, David; Mukamal, Kenneth J (Am J Clin Nutr, 2010)
BACKGROUND: Type 2 diabetes (T2D) remains an important public health issue in the United States. There are limited and inconsistent data on the association between egg consumption and fasting glucose or incident diabetes. OBJECTIVES: We assessed the association between egg intake and incident diabetes in older adults. DESIGN: In this prospective study of 3898 men and women from the Cardiovascular Health Study (1989-2007), we assessed egg consumption by using a picture-sorted food questionnaire and ascertained incident T2D annually by using information on hypoglycemic agents and plasma glucose. We used Cox proportional hazards models to estimate adjusted relative risks. RESULTS: During a mean follow-up of 11.3 y, 313 new cases of T2D occurred. Crude incidence rates of T2D were 7.39, 6.83, 7.00, 6.72, and 12.20 per 1000 person-years in people who reported egg consumption of never, <1 egg/mo, 1-3 eggs/mo, 1-4 eggs/wk, and almost daily, respectively. In multivariable-adjusted models, there was no association between egg consumption and increased risk of T2D in either sex and overall. In a secondary analysis, dietary cholesterol was not associated with incident diabetes (P for trend = 0.47). In addition, egg consumption was not associated with clinically meaningful differences in fasting glucose, fasting insulin, or measures of insulin resistance despite small absolute analytic differences that were significant. CONCLUSION: In this cohort of older adults with limited egg intake, there was no association between egg consumption or dietary cholesterol and increased risk of incident T2D.
Keywords: Aged; Blood Glucose; Cholesterol, Dietary; Diabetes Mellitus, Type 2; Diet; Diet Surveys; Eggs; Feeding Behavior; Female; Humans; Insulin; Insulin Resistance; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; Surveys and Questionnaires

Genetic ancestry in lung-function predictions. - Kumar, Rajesh; Seibold, Max A; Aldrich, Melinda C; Williams, L Keoki; Reiner, Alex P; Colangelo, Laura; Galanter, Joshua; Gignoux, Christopher; Hu, Donglei; Sen, Saunak; Choudhry, Shweta; Peterson, Edward L; et al. (N Engl J Med, 2010)
BACKGROUND: Self-identified race or ethnic group is used to determine normal reference standards in the prediction of pulmonary function. We conducted a study to determine whether the genetically determined percentage of African ancestry is associated with lung function and whether its use could improve predictions of lung function among persons who identified themselves as African American. METHODS: We assessed the ancestry of 777 participants self-identified as African American in the Coronary Artery Risk Development in Young Adults (CARDIA) study and evaluated the relation between pulmonary function and ancestry by means of linear regression. We performed similar analyses of data for two independent cohorts of subjects identifying themselves as African American: 813 participants in the Health, Aging, and Body Composition (HABC) study and 579 participants in the Cardiovascular Health Study (CHS). We compared the fit of two types of models to lung-function measurements: models based on the covariates used in standard prediction equations and models incorporating ancestry. We also evaluated the effect of the ancestry-based models on the classification of disease severity in two asthma-study populations. RESULTS: African ancestry was inversely related to forced expiratory volume in 1 second (FEV(1)) and forced vital capacity in the CARDIA cohort. These relations were also seen in the HABC and CHS cohorts. In predicting lung function, the ancestry-based model fit the data better than standard models. Ancestry-based models resulted in the reclassification of asthma severity (based on the percentage of the predicted FEV(1)) in 4 to 5% of participants. CONCLUSIONS: Current predictive equations, which rely on self-identified race alone, may misestimate lung function among subjects who identify themselves as African American. Incorporating ancestry into normative equations may improve lung-function estimates and more accurately categorize disease severity. (Funded by the National Institutes of Health and others.)
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; Female; Forced Expiratory Volume; Genetic Markers; Genotype; Humans; Linear Models; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Reference Values; Respiratory Function Tests; Vital Capacity; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology. - Levy, Daniel; Neuhausen, Susan L; Hunt, Steven C; Kimura, Masayuki; Hwang, Shih-Jen; Chen, Wei; Bis, Joshua C; Fitzpatrick, Annette L; Smith, Erin; Johnson, Andrew D; Gardner, Jeffrey P; Srinivasan, Sathanur R; et al. (Proc Natl Acad Sci U S A, 2010)
Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is observed in a host of aging-related complex genetic diseases and is associated with diminished survival in the elderly. We report results of a genome-wide association study of LTL in a consortium of four observational studies (n = 3,417 participants with LTL and genome-wide genotyping). SNPs in the regions of the oligonucleotide/oligosaccharide-binding folds containing one gene (OBFC1; rs4387287; P = 3.9 x 10(-9)) and chemokine (C-X-C motif) receptor 4 gene (CXCR4; rs4452212; P = 2.9 x 10(-8)) were associated with LTL at a genome-wide significance level (P < 5 x 10(-8)). We attempted replication of the top SNPs at these loci through de novo genotyping of 1,893 additional individuals and in silico lookup in another observational study (n = 2,876), and we confirmed the association findings for OBFC1 but not CXCR4. In addition, we confirmed the telomerase RNA component (TERC) as a gene associated with LTL (P = 1.1 x 10(-5)). The identification of OBFC1 through genome-wide association as a locus for interindividual variation in LTL in the general population advances the understanding of telomere biology in humans and may provide insights into aging-related disorders linked to altered LTL dynamics.
Keywords: Cohort Studies; Genome-Wide Association Study; Genotype; Humans; Leukocytes; Polymorphism, Single Nucleotide; Receptors, CXCR4; Telomere; Telomere-Binding Proteins

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci. - Franke, Andre; McGovern, Dermot P B; Barrett, Jeffrey C; Wang, Kai; Radford-Smith, Graham L; Ahmad, Tariq; Lees, Charlie W; Balschun, Tobias; Lee, James; Roberts, Rebecca; Anderson, Carl A; Bis, Joshua C; et al. (Nat Genet, 2010)
We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate genes including SMAD3, ERAP2, IL10, IL2RA, TYK2, FUT2, DNMT3A, DENND1B, BACH2 and TAGAP. Combined with previously confirmed loci, these results identify 71 distinct loci with genome-wide significant evidence for association with Crohn's disease.
Keywords: Computational Biology; Crohn Disease; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Reproducibility of Results

Geriatric impairments and disability: the cardiovascular health study. - Chaudhry, Sarwat I; McAvay, Gail; Ning, Yuming; Allore, Heather G; Newman, Anne B; Gill, Thomas M (J Am Geriatr Soc, 2010)
OBJECTIVES: To determine the relative importance of geriatric impairments (in muscle strength, physical capacity, cognition, vision, hearing, and psychological status) and chronic diseases in predicting subsequent functional disability in longitudinal analyses. DESIGN: Longitudinal data from the Cardiovascular Health Study were analyzed. Multivariable Cox hazards regression modeling was used to analyze associations between time-dependent predictors and onset of disability in activities of daily living (ADLs) and mobility. SETTING: Four communities across the United States (Sacramento County, CA; Washington County, MD; Forsyth County, NC; and Allegheny County, PA). PARTICIPANTS: Five thousand eight hundred eighty-eight elderly persons. MEASUREMENTS: Data were collected annually through in-person examinations. RESULTS: ADL disability developed in 15% of participants and mobility disability in 30%. A single multivariable model was developed that included demographics, marital status, body mass index, and number of impairments and diseases. The hazard ratios (HRs) of having one, two, and three or more geriatric impairments (vs none) for the outcome of ADL disability were 2.12 (95% confidence interval (CI)=1.63-2.75), 4.25 (95% CI=3.30-5.48), and 7.87 (95% CI=6.10-10.17), respectively, and for having one, two, and three or more chronic diseases were 1.75 (95% CI=1.41-2.19), 2.45 (95% CI=1.95-3.07), and 3.26 (95% CI=2.53-4.19), respectively. Similarly, the HRs of having one, two, and three or more impairments for the outcome of mobility disability were 1.48 (95% CI=1.27-1.73), 2.08 (95% CI=1.77-2.45), and 3.70 (95% CI=3.09-4.42), respectively, and for having one, two, and three or more diseases were 2.06 (95% CI=1.76-2.40), 2.80 (95% CI=2.36-3.31), and 4.20 (95% CI=3.44-5.14), respectively. CONCLUSION: Number of geriatric impairments was more strongly associated than number of chronic diseases with subsequent ADL disability and nearly as strongly associated with the subsequent mobility disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Morbidity; Retrospective Studies; Risk Factors; Time Factors; United States

Glycosylated hemoglobin and the risk of death and cardiovascular mortality in the elderly. - Chonchol, M; Katz, R; Fried, L F; Sarnak, M J; Siscovick, D S; Newman, A B; Strotmeyer, E S; Bertoni, A; Shlipak, M G (Nutr Metab Cardiovasc Dis, 2010)
BACKGROUND AND AIMS: Glycosylated hemoglobin (HbA(1c)) has been associated with incident cardiovascular disease (CVD), but the findings are inconsistent. We tested the hypothesis that HbA(1c) may be associated with an increased risk of death and cardiovascular mortality in older adults. METHODS AND RESULTS: We evaluated the association between HbA(1c) with all-cause and cardiovascular mortality in 810 participants without a history of diabetes in a sub-study of the Cardiovascular Health Study (CHS), a community cohort study of individuals > or =65 years of age. Glycosylated hemoglobin was measured at baseline and all-cause and cardiovascular mortality was assessed during the follow-up period. The relation between baseline HbA(1c) and death was evaluated with multivariate Cox proportional hazards regression models. After a median follow-up of 14.2 years, 416 deaths were observed. The crude incidence rates of all-cause mortality across HbA(1c) groups were: 4.4% per year, 4.3% per year and 4.6% per year for tertile 1 (< or =5.6%), tertile 2 (5.61-6.20%) and tertile 3 (> or =6.21%), respectively. In unadjusted and fully adjusted analyses, baseline HbA(1c) was not associated with all-cause mortality and cardiovascular mortality (hazard ratio: 1.16 [95% confidence interval 0.91-1.47] and hazard ratio: 1.31 [95% confidence interval 0.90-1.93], respectively for the highest HbA(1c) tertile compared with the lowest). CONCLUSION: These results suggest that HbA(1c) does not significantly predict all-cause and cardiovascular mortality in non-diabetic community-dwelling older adults.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Glycated Hemoglobin A; Health Surveys; Heart Failure; Humans; Incidence; Male; Myocardial Infarction; Risk Factors; Statistics as Topic; Stroke; United States

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; European Continental Ancestry Group; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin

Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) and risk of cardiovascular disease in older adults: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Solomon, Cam; Cushman, Mary; Tracy, Russell P; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt D (Atherosclerosis, 2010)
OBJECTIVE: To examine associations between lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) antigen level (mass) and enzymatic activity (activity) and cardiovascular disease (CVD) in older adults. METHODS: We examined associations of Lp-PLA(2) mass and activity with incident myocardial infarction (MI; n=508), stroke (n=565) and CVD death (n=665) using Cox regressions adjusted for age, sex, ethnicity and CVD risk factors in 3949 older adults, aged > or =65 years at baseline, from the Cardiovascular Health Study (CHS). RESULTS: Lp-PLA(2) was associated with incident CVD events in these older adults. Hazard ratios (95% confidence intervals) for highest versus lowest tertiles of Lp-PLA(2) mass were 1.49 (1.19-1.85) for MI, 1.21 (0.98-1.49) for stroke and 1.11 (0.92-1.33) for CVD death. The highest tertile of Lp-PLA(2) activity was associated with MI (1.36; 1.09-1.70) and CVD death (1.23; 1.02-1.50). Combined Lp-PLA(2) tertile 3 and CRP>3mg/l, compared to Lp-PLA(2) tertile 1 and CRP<1mg/l, was associated with MI (2.29; 1.49-3.52) for Lp-PLA(2) mass and MI (1.66; 1.10-2.51) and CVD death (1.57; 1.08-2.26) for activity. For MI, both mass and activity added excess risk to elevated CRP alone ( approximately 20% excess risk) and activity added excess risk for CVD death ( approximately 12%). CONCLUSION: Lp-PLA(2) mass and activity were associated with incident CVD events in older adults in CHS. Lp-PLA(2) and CRP were independent and additive in prediction of events. While associations were modest, these results support further exploration of Lp-PLA(2) to identify older individuals at risk for CVD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk; Stroke

Long-term retention of older adults in the Cardiovascular Health Study: implications for studies of the oldest old. - Strotmeyer, Elsa S; Arnold, Alice M; Boudreau, Robert M; Ives, Diane G; Cushman, Mary; Robbins, John A; Harris, Tamara B; Newman, Anne B (J Am Geriatr Soc, 2010)
OBJECTIVES: To describe retention according to age and visit type (clinic, home, telephone) and to determine characteristics associated with visit types for a longitudinal epidemiological study in older adults. DESIGN: Longitudinal cohort study. SETTING: Four U.S. clinical sites. PARTICIPANTS: Five thousand eight hundred eighty-eight Cardiovascular Health Study (CHS) participants aged 65 to 100 at 1989/90 or 1992/93 enrollment (58.6% female; 15.7% black). CHS participants were contacted every 6 months, with annual assessments through 1999 and in 2005/06 for the All Stars Study visit of the CHS cohort (aged 77-102; 66.5% female; 16.6% black). MEASUREMENTS: All annual contacts through 1999 (n=43,772) and for the 2005/06 visit (n=1,942). RESULTS: CHS had 43,772 total participant contacts from 1989 to 1999: 34,582 clinic visits (79.0%), 2,238 refusals (5.1%), 4,401 telephone visits (10.1%), 1,811 home visits (4.1%), and 740 other types (1.7%). In 2005/06, the All Stars participants of the CHS cohort had 36.6% clinic, 22.3% home, and 41.1% telephone visits. Compared with participants aged 65 to 69, odds ratios of not attending a CHS clinic visit were 1.82 (95% confidence interval (CI)=1.54-2.13), 2.94 (95% CI=2.45-3.57), 4.55 (95% CI=3.70-5.56), and 9.09 (95% CI=7.69-11.11) for those aged 70 to 74, 75 to 79, 80 to 84, and 85 and older, respectively, in sex-adjusted regression. In multivariable regression, participants with a 2005/06 clinic visit were younger, more likely to be male and in good health, and had had better cognitive and physical function 7 years earlier than participants with other visit types. Participants with home, telephone, and missing visits were similar on characteristics measured 7 years earlier. CONCLUSION: Offering home, telephone, and proxy visits are essential to optimizing follow-up of aging cohorts. Home visits increased in-person retention from 36.5% to 58.8% and diversified the cohort with respect to age, health, and physical functioning.
Keywords: Age Factors; Aged; Aged, 80 and over; Ambulatory Care Facilities; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Epidemiologic Studies; Female; Geriatric Assessment; House Calls; Humans; Logistic Models; Longitudinal Studies; Male; Multivariate Analysis; Patient Dropouts; Patient Selection; Research Subjects; Telephone; United States

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function. - Hancock, Dana B; Eijgelsheim, Mark; Wilk, Jemma B; Gharib, Sina A; Loehr, Laura R; Marciante, Kristin D; Franceschini, Nora; van Durme, Yannick M T A; Chen, Ting-Hsu; Barr, R Graham; Schabath, Matthew B; Couper, David J; et al. (Nat Genet, 2010)
Spirometric measures of lung function are heritable traits that reflect respiratory health and predict morbidity and mortality. We meta-analyzed genome-wide association studies for two clinically important lung-function measures: forced expiratory volume in the first second (FEV(1)) and its ratio to forced vital capacity (FEV(1)/FVC), an indicator of airflow obstruction. This meta-analysis included 20,890 participants of European ancestry from four CHARGE Consortium studies: Atherosclerosis Risk in Communities, Cardiovascular Health Study, Framingham Heart Study and Rotterdam Study. We identified eight loci associated with FEV(1)/FVC (HHIP, GPR126, ADAM19, AGER-PPT2, FAM13A, PTCH1, PID1 and HTR4) and one locus associated with FEV(1) (INTS12-GSTCD-NPNT) at or near genome-wide significance (P < 5 x 10(-8)) in the CHARGE Consortium dataset. Our findings may offer insights into pulmonary function and pathogenesis of chronic lung disease.
Keywords: Databases, Genetic; Female; Forced Expiratory Volume; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung; Lung Diseases; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Spirometry; Vital Capacity

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

Multiple genetic loci influence serum urate levels and their relationship with gout and cardiovascular disease risk factors. - Yang, Qiong; Köttgen, Anna; Dehghan, Abbas; Smith, Albert V; Glazer, Nicole L; Chen, Ming-Huei; Chasman, Daniel I; Aspelund, Thor; Eiriksdottir, Gudny; Harris, Tamara B; Launer, Lenore; Nalls, Michael; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed a genome-wide association study to search for genetic susceptibility loci for serum urate and gout and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). METHODS AND RESULTS: Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the Cohorts for Heart and Aging Research in Genome Epidemiology consortium for serum urate and gout in 28 283 white participants. The effect of the most significant single-nucleotide polymorphism at all genome-wide significant loci on serum urate was added to create a genetic urate score. Findings were replicated in the Women's Genome Health Study (n=22 054). Single-nucleotide polymorphisms at 8 genetic loci achieved genome-wide significance with serum urate levels (P=4×10(-8) to 2×10(-242) in SLC22A11, GCKR, R3HDM2-INHBC region, RREB1, PDZK1, SLC2A9, ABCG2, and SLC17A1). Only 2 loci (SLC2A9, ABCG2) showed genome-wide significant association with gout. The genetic urate score was strongly associated with serum urate and gout (odds ratio, 12.4 per 100 μmol/L; P=3×10(-39)) but not with blood pressure, glucose, estimated glomerular filtration rate, chronic kidney disease, or CHD. The lack of association between the genetic score and the latter phenotypes also was observed in the Women's Genome Health Study. CONCLUSIONS: The genetic urate score analysis suggested a causal relationship between serum urate and gout but did not provide evidence for one between serum urate and cardiovascular risk factors and CHD.
Keywords: Cardiovascular Diseases; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Gout; Humans; Male; Risk Factors; Uric Acid

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Physical activity and years of healthy life in older adults: results from the cardiovascular health study. - Hirsch, Calvin H; Diehr, Paula; Newman, Anne B; Gerrior, Shirley A; Pratt, Charlotte; Lebowitz, Michael D; Jackson, Sharon A (J Aging Phys Act, 2010)
Little is known about how many years of life and disability-free years seniors can gain through exercise. Using data from the Cardiovascular Health Study, the authors estimated the extra years of life and self-reported healthy life (over 11 years) and years without impairment in activities of daily living (over 6 years) associated with quintiles of physical activity (PA) in older adults from different age groups. They estimated PA from the Minnesota Leisure Time Activities Questionnaire. Multivariable linear regression adjusted for health-related covariates. The relative gains in survival and years of healthy life (YHL) generally were proportionate to the amount of PA, greater among those 75+, and higher in men. Compared with being sedentary, the most active men 75+ had 1.49 more YHL (95% CI: 0.79, 2.19), and the most active women 75+ had 1.06 more YHL (95% CI: 0.44, 1.68). Seniors over age 74 experience the largest relative gains in survival and healthy life from physical activity.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Exercise; Female; Health Behavior; Health Status; Humans; Leisure Activities; Life Style; Male; Quality-Adjusted Life Years; Sex Factors

Physical activity predicts gray matter volume in late adulthood: the Cardiovascular Health Study. - Erickson, K I; Raji, C A; Lopez, O L; Becker, J T; Rosano, C; Newman, A B; Gach, H M; Thompson, P M; Ho, A J; Kuller, L H (Neurology, 2010)
OBJECTIVES: Physical activity (PA) has been hypothesized to spare gray matter volume in late adulthood, but longitudinal data testing an association has been lacking. Here we tested whether PA would be associated with greater gray matter volume after a 9-year follow-up, a threshold could be identified for the amount of walking necessary to spare gray matter volume, and greater gray matter volume associated with PA would be associated with a reduced risk for cognitive impairment 13 years after the PA evaluation. METHODS: In 299 adults (mean age 78 years) from the Cardiovascular Health Cognition Study, we examined the association between gray matter volume, PA, and cognitive impairment. Physical activity was quantified as the number of blocks walked over 1 week. High-resolution brain scans were acquired 9 years after the PA assessment on cognitively normal adults. White matter hyperintensities, ventricular grade, and other health variables at baseline were used as covariates. Clinical adjudication for cognitive impairment occurred 13 years after baseline. RESULTS: Walking amounts ranged from 0 to 300 blocks (mean 56.3; SD 69.7). Greater PA predicted greater volumes of frontal, occipital, entorhinal, and hippocampal regions 9 years later. Walking 72 blocks was necessary to detect increased gray matter volume but walking more than 72 blocks did not spare additional volume. Greater gray matter volume with PA reduced the risk for cognitive impairment 2-fold. CONCLUSION: Greater amounts of walking are associated with greater gray matter volume, which is in turn associated with a reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Motor Activity; Neuropsychological Tests; Odds Ratio; Predictive Value of Tests; Surveys and Questionnaires

Post hoc Parkinson's disease: identifying an uncommon disease in the Cardiovascular Health Study. - Ton, T G; Jain, S; Boudreau, R; Thacker, E L; Strotmeyer, E S; Newman, A B; Longstreth, W T; Checkoway, H (Neuroepidemiology, 2010)
BACKGROUND: Although ongoing cohort studies offer a unique opportunity to apply existing information collected prospectively to further the scientific understanding of Parkinson's disease (PD), they typically have limited information for clinical diagnosis. METHODS: We used combinations of self-report, International Classification of Diseases - 9th edition codes and antiparkinsonian medications to identify PD in the Cardiovascular Health Study. To determine whether the expected inverse association between smoking and PD is evident using our outcome definitions, we assessed baseline smoking characteristics for various definitions of PD. RESULTS: We identified 60 cases with prevalent PD (1.0%; 95% confidence interval, CI = 0.8-1.3%) and 154 with incident PD by year 14. Clear associations were observed for current smokers (odds ratio, OR = 0.50; 95% CI = 0.26-0.95) and for those who smoked ≥50 pack-years (OR = 0.53; 95% CI = 0.29-0.96). Estimates for smoking were similar when ≥2 data sources were required. Estimates for self-report alone were attenuated towards null. CONCLUSIONS: Using multiple data sources to identify PD represents an alternative method of outcome identification in a cohort that would otherwise not be possible for PD research. Ongoing cohort studies can provide settings in which rapid replication and explorations of new hypotheses for PD are possible.
Keywords: Aged; Aged, 80 and over; Cardiovascular System; Cohort Studies; Female; Health Status; Humans; Incidence; Male; Odds Ratio; Parkinson Disease; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Prospective study of obstructive sleep apnea and incident coronary heart disease and heart failure: the sleep heart health study. - Gottlieb, Daniel J; Yenokyan, Gayane; Newman, Anne B; O'Connor, George T; Punjabi, Naresh M; Quan, Stuart F; Redline, Susan; Resnick, Helaine E; Tong, Elisa K; Diener-West, Marie; Shahar, Eyal (Circulation, 2010)
BACKGROUND: Clinic-based observational studies in men have reported that obstructive sleep apnea is associated with an increased incidence of coronary heart disease. The objective of this study was to assess the relation of obstructive sleep apnea to incident coronary heart disease and heart failure in a general community sample of adult men and women. METHODS AND RESULTS: A total of 1927 men and 2495 women > or =40 years of age and free of coronary heart disease and heart failure at the time of baseline polysomnography were followed up for a median of 8.7 years in this prospective longitudinal epidemiological study. After adjustment for multiple risk factors, obstructive sleep apnea was a significant predictor of incident coronary heart disease (myocardial infarction, revascularization procedure, or coronary heart disease death) only in men < or =70 years of age (adjusted hazard ratio 1.10 [95% confidence interval 1.00 to 1.21] per 10-unit increase in apnea-hypopnea index [AHI]) but not in older men or in women of any age. Among men 40 to 70 years old, those with AHI > or =30 were 68% more likely to develop coronary heart disease than those with AHI <5. Obstructive sleep apnea predicted incident heart failure in men but not in women (adjusted hazard ratio 1.13 [95% confidence interval 1.02 to 1.26] per 10-unit increase in AHI). Men with AHI > or =30 were 58% more likely to develop heart failure than those with AHI <5. CONCLUSIONS: Obstructive sleep apnea is associated with an increased risk of incident heart failure in community-dwelling middle-aged and older men; its association with incident coronary heart disease in this sample is equivocal.
Keywords: Adult; Aged; Coronary Disease; Female; Heart Failure; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Sleep Apnea, Obstructive; Survival Analysis

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Validation of the health ABC heart failure model for incident heart failure risk prediction: the Cardiovascular Health Study. - Kalogeropoulos, Andreas; Psaty, Bruce M; Vasan, Ramachandran S; Georgiopoulou, Vasiliki; Smith, Andrew L; Smith, Nicholas L; Kritchevsky, Stephen B; Wilson, Peter W F; Newman, Anne B; Harris, Tamara B; Butler, Javed (Circ Heart Fail, 2010)
BACKGROUND: The recently developed and internally validated Health ABC HF model uses 9 routinely available clinical variables to determine incident heart failure risk. In this study, we sought to externally validate the Health ABC HF model. METHODS AND RESULTS: Observed 5-year incidence of heart failure, defined as first hospitalization for new-onset heart failure, was compared with 5-year risk estimates derived from the Health ABC HF model among participants without heart failure at baseline in the Cardiovascular Health Study. During follow-up, 400 of 5335 (7.5%) participants developed heart failure over 5 years versus 364 (6.8%) predicted by the Health ABC HF model (predicted-to-observed ratio, 0.90). Observed versus predicted 5-year heart failure probabilities were 3.2% versus 2.8%, 9.0% versus 7.0%, 15.9% versus 13.7%, and 24.6% versus 30.8% for the <5%, 5% to 10%, 10% to 20%, and >20% 5-year risk categories, respectively. The Hosmer-Lemeshow chi(2) was 14.72 (degrees of freedom, 10; P=0.14), and the C index was 0.74 (95% CI, 0.72 to 0.76). Calibration and discrimination demonstrated adequate performance across sex and race overall; however, risk was underestimated in white men, especially in the 5% to 10% risk category. Model performance was optimal when participants with normal left ventricular function at baseline were assessed separately. Performance was consistent across age groups. Analyses with death as a competing risk yielded similar results. CONCLUSIONS: The Health ABC HF model adequately predicted 5-year heart failure risk in a large community-based study, providing support for the external validity of the model. This tool may be used to identify individuals to whom to target heart failure prevention efforts.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Confidence Intervals; Disease Progression; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Models, Statistical; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Survival Analysis; United States

Association of body mass index with peripheral arterial disease in older adults: the Cardiovascular Health Study. - Ix, Joachim H; Biggs, Mary L; Kizer, Jorge R; Mukamal, Kenneth J; Djoussé, Luc; Zieman, Susan J; de Boer, Ian H; Nelson, Tracy L; Newman, Anne B; Criqui, Michael H; Siscovick, David S (Am J Epidemiol, 2011)
The authors hypothesized that the absence of cross-sectional associations of body mass index (BMI; weight (kg)/height (m)(2)) with peripheral arterial disease (PAD) in prior studies may reflect lower weight among persons who smoke or have poor health status. They conducted an observational study among 5,419 noninstitutionalized residents of 4 US communities aged ≥ 65 years at baseline (1989-1990 or 1992-1993). Ankle brachial index was measured, and participants reported their history of PAD procedures. Participants were followed longitudinally for adjudicated incident PAD events. At baseline, mean BMI was 26.6 (standard deviation, 4.6), and 776 participants (14%) had prevalent PAD. During 13.2 (median) years of follow-up through June 30, 2007, 276 incident PAD events occurred. In cross-sectional analysis, each 5-unit increase in BMI was inversely associated with PAD (prevalence ratio (PR) = 0.92, 95% confidence interval (CI): 0.85, 1.00). However, among persons in good health who had never smoked, the direction of association was opposite (PR = 1.20, 95% CI: 0.94, 1.52). Similar results were observed between BMI calculated using weight at age 50 years and PAD prevalence (PR = 1.30, 95% CI: 1.11, 1.51) and between BMI at baseline and incident PAD events occurring during follow-up (hazard ratio = 1.32, 95% CI: 1.00, 1.76) among never smokers in good health. Greater BMI is associated with PAD in older persons who remain healthy and have never smoked. Normal weight maintenance may decrease PAD incidence and associated comorbidity in older age.
Keywords: Aged; Ankle Brachial Index; Body Mass Index; Cross-Sectional Studies; Health Status; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Obesity; Peripheral Arterial Disease; Prevalence; Sex Factors; Smoking; United States

Association of coagulation-related and inflammation-related genes and factor VIIc levels with stroke: the Cardiovascular Health Study. - Zakai, N A; Lange, L; Longstreth, W T; O'Meara, E S; Kelley, J L; Fornage, M; Nikerson, D; Cushman, M; Reiner, A P (J Thromb Haemost, 2011)
BACKGROUND: Thrombosis and inflammation are critical in stroke etiology, but associations of coagulation and inflammation gene variants with stroke, and particularly factor VII levels, are inconclusive. OBJECTIVES: To test the associations between 736 single-nucleotide polymorphisms (SNPs) between tagging haplotype patterns of 130 coagulation and inflammation genes, and stroke events, in the 5888 participants aged ≥ 65 years of the observational Cardiovascular Health Study cohort. PATIENTS/METHODS: With 16 years of follow-up, age-adjusted and sex-adjusted Cox models were used to estimate associations of SNPs and FVIIc levels with future stroke. RESULTS: Eight hundred and fifteen strokes occurred in 5255 genotyped participants without baseline stroke (748 ischemic strokes; 586 among whites). Among whites, six SNPs were associated with stroke, with a nominal P-value of < 0.01: rs6046 and rs3093261 (F7); rs4918851 and rs3781387 (HABP2); and rs3138055 (NFKB1A) and rs4648004 (NFKB1). Two of these SNPs were associated with FVIIc levels (units of percentage activity): rs6046 (β = -18.5, P = 2.38 × 10(-83)) and rs3093261 (β = 2.99, P = 3.93 × 10(-6)). After adjustment for age, sex, race, and cardiovascular risk factors, the association of FVIIc quintiles (Q) with stroke were as follows (hazard ratio; 95% confidence interval): Q1, reference; Q2, 1.4, 1.1-1.9); Q3, 1.1, 0.8-1.5); Q4, 1.5, 1.1-2.0); and Q5, 1.6, 1.2-2.2). Associations between SNPs and stroke were independent of FVIIc levels. CONCLUSIONS: Variations in FVII-related genes and FVIIc levels were associated with risk of incident ischemic stroke in this elderly cohort, suggesting a potential causal role for FVII in stroke etiology.
Keywords: Blood Coagulation Factors; Cardiovascular Diseases; Cohort Studies; Factor VII; Female; Humans; Inflammation; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Chronic kidney disease and the risk of end-stage renal disease versus death. - Dalrymple, Lorien S; Katz, Ronit; Kestenbaum, Bryan; Shlipak, Michael G; Sarnak, Mark J; Stehman-Breen, Catherine; Seliger, Stephen; Siscovick, David; Newman, Anne B; Fried, Linda (J Gen Intern Med, 2011)
BACKGROUND: Among older adults with chronic kidney disease (CKD), the comparative event rates of end-stage renal disease (ESRD) and cause-specific death are unknown. OBJECTIVE: To compare the rates of ESRD, cardiovascular and non-cardiovascular death and examine risk factors for ESRD and all-cause mortality in Cardiovascular Health Study (CHS) participants. DESIGN: The CHS is a longitudinal cohort study of community-dwelling adults aged 65 years and older. PARTICIPANTS: 1,268 participants with an estimated glomerular filtration rate (eGFR) < 60 ml/min per 1.73 m(2) were followed until the time of first event (ESRD, cardiovascular or non-cardiovascular death) or until March 31, 2003. MAIN MEASURES: The outcomes were ESRD, cardiovascular- and non-cardiovascular death. Rates of each event were calculated, and a Cox Proportional Hazards Model with a competing risk framework was used to examine risk factors for ESRD as compared with death. Predictors included age, gender, race, BMI, hypertension, diabetes, cardiovascular disease, heart failure, tobacco use, eGFR, and total cholesterol. KEY RESULTS: During 9.7 years of follow-up, 5% of the cohort progressed to ESRD, and 61% of the cohort died. The rate (per 100 person-years) was 0.5 for ESRD and 6.8 for all-cause mortality (3.0 for cardiovascular and 3.8 for non-cardiovascular mortality). In the competing risk framework, lower eGFR, male gender, African-American race, and higher BMI were associated with an increased risk of ESRD. CONCLUSIONS: Older adults with CKD are 13-fold more likely to die from any cause than progress to ESRD and are 6-fold more likely to die from cardiovascular causes than develop ESRD.
Keywords: Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Female; Follow-Up Studies; Humans; Kidney Failure, Chronic; Longitudinal Studies; Male; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors; Treatment Outcome

Chronic kidney disease in octogenarians. - Shastri, Shani; Tighiouart, Hocine; Katz, Ronit; Rifkin, Dena E; Fried, Linda F; Shlipak, Michael G; Newman, Anne B; Sarnak, Mark J (Clin J Am Soc Nephrol, 2011)
BACKGROUND AND OBJECTIVES: There are limited data on the prevalence of chronic kidney disease (CKD) and its clinical importance in the very old. We examined the prevalence of CKD in octogenarians and its association with cardiovascular disease (CVD). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In a cross-sectional analysis of 1028 participants from the Cardiovascular Health Study All Stars, we evaluated association of prevalent CKD with CVD using multivariable logistic regression. CKD was defined as eGFR of <60 ml/min per 1.73 m(2). GFR was estimated using CKD-Epi creatinine and cystatin C equations that incorporate coefficients for age, gender, and race (eGFR(EPI), eGFR(CYS3var)) and the one-variable cystatin C equation (eGFR(CYS1var)). Prevalent CVD was defined as a composite of coronary heart disease, heart failure, and stroke. RESULTS: Mean age was 86 years, 64% were women, 86% were Caucasians, 14% had diabetes, and 39% had prevalent CVD. Mean eGFR(EPI), eGFR(CYS3var), and eGFR(CYS1var) were 59, 62, and 70 ml/min per 1.73 m(2), and 51%, 46%, and 33% had CKD, respectively. Associations of CKD with CVD varied by equation in adjusted analyses: CKD(EPI) (OR, 1.53; 95% CI, 1.15 to 2.03), CKD(CYS3var) (OR, 1.67; 95% CI, 1.25, 2.23), and CKD(CYS1var) (OR, 2.09; 95% CI, 1.55, 2.83). CONCLUSIONS: Reduced eGFR is highly prevalent in octogenarians, and the eGFR(CYS1var) equation yielded the lowest prevalence of CKD but the strongest association with prevalent CVD. Because there are no validated estimating equations in the elderly, estimation of kidney function on the basis of on any one equation should be interpreted with caution.
Keywords: Age Factors; Aged, 80 and over; Analysis of Variance; Biomarkers; Cardiovascular Diseases; Chi-Square Distribution; Chronic Disease; Creatinine; Cross-Sectional Studies; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Logistic Models; Male; Models, Biological; Prevalence; Risk Assessment; Risk Factors; United States

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Diabetes mellitus, fasting glucose, and risk of cause-specific death. - Rao Kondapally Seshasai, Sreenivasa; Kaptoge, Stephen; Thompson, Alexander; Di Angelantonio, Emanuele; Gao, Pei; Sarwar, Nadeem; Whincup, Peter H; Mukamal, Kenneth J; Gillum, Richard F; Holme, Ingar; Njølstad, Inger; Fletcher, Astrid; et al. (N Engl J Med, 2011)
BACKGROUND: The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS: We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS: After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with persons without diabetes were as follows: 1.80 (95% confidence interval [CI], 1.71 to 1.90) for death from any cause, 1.25 (95% CI, 1.19 to 1.31) for death from cancer, 2.32 (95% CI, 2.11 to 2.56) for death from vascular causes, and 1.73 (95% CI, 1.62 to 1.85) for death from other causes. Diabetes (vs. no diabetes) was moderately associated with death from cancers of the liver, pancreas, ovary, colorectum, lung, bladder, and breast. Aside from cancer and vascular disease, diabetes (vs. no diabetes) was also associated with death from renal disease, liver disease, pneumonia and other infectious diseases, mental disorders, nonhepatic digestive diseases, external causes, intentional self-harm, nervous-system disorders, and chronic obstructive pulmonary disease. Hazard ratios were appreciably reduced after further adjustment for glycemia measures, but not after adjustment for systolic blood pressure, lipid levels, inflammation or renal markers. Fasting glucose levels exceeding 100 mg per deciliter (5.6 mmol per liter), but not levels of 70 to 100 mg per deciliter (3.9 to 5.6 mmol per liter), were associated with death. A 50-year-old with diabetes died, on average, 6 years earlier than a counterpart without diabetes, with about 40% of the difference in survival attributable to excess nonvascular deaths. CONCLUSIONS: In addition to vascular disease, diabetes is associated with substantial premature death from several cancers, infectious diseases, external causes, intentional self-harm, and degenerative disorders, independent of several major risk factors. (Funded by the British Heart Foundation and others.).
Keywords: Blood Glucose; Cause of Death; Diabetes Mellitus; Female; Humans; Hyperglycemia; Life Expectancy; Male; Middle Aged; Risk; Survival Analysis

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Gait speed and survival in older adults. - Studenski, Stephanie; Perera, Subashan; Patel, Kushang; Rosano, Caterina; Faulkner, Kimberly; Inzitari, Marco; Brach, Jennifer; Chandler, Julie; Cawthon, Peggy; Connor, Elizabeth Barrett; Nevitt, Michael; Visser, Marjolein; et al. (JAMA, 2011)
CONTEXT: Survival estimates help individualize goals of care for geriatric patients, but life tables fail to account for the great variability in survival. Physical performance measures, such as gait speed, might help account for variability, allowing clinicians to make more individualized estimates. OBJECTIVE: To evaluate the relationship between gait speed and survival. DESIGN, SETTING, AND PARTICIPANTS: Pooled analysis of 9 cohort studies (collected between 1986 and 2000), using individual data from 34,485 community-dwelling older adults aged 65 years or older with baseline gait speed data, followed up for 6 to 21 years. Participants were a mean (SD) age of 73.5 (5.9) years; 59.6%, women; and 79.8%, white; and had a mean (SD) gait speed of 0.92 (0.27) m/s. MAIN OUTCOME MEASURES: Survival rates and life expectancy. RESULTS: There were 17,528 deaths; the overall 5-year survival rate was 84.8% (confidence interval [CI], 79.6%-88.8%) and 10-year survival rate was 59.7% (95% CI, 46.5%-70.6%). Gait speed was associated with survival in all studies (pooled hazard ratio per 0.1 m/s, 0.88; 95% CI, 0.87-0.90; P < .001). Survival increased across the full range of gait speeds, with significant increments per 0.1 m/s. At age 75, predicted 10-year survival across the range of gait speeds ranged from 19% to 87% in men and from 35% to 91% in women. Predicted survival based on age, sex, and gait speed was as accurate as predicted based on age, sex, use of mobility aids, and self-reported function or as age, sex, chronic conditions, smoking history, blood pressure, body mass index, and hospitalization. CONCLUSION: In this pooled analysis of individual data from 9 selected cohorts, gait speed was associated with survival in older adults.
Keywords: Aged; Cohort Studies; Female; Gait; Geriatric Assessment; Humans; Life Expectancy; Male; Survival Analysis; United States

A gene-centric association scan for Coagulation Factor VII levels in European and African Americans: the Candidate Gene Association Resource (CARe) Consortium. - Taylor, Kira C; Lange, Leslie A; Zabaneh, Delilah; Lange, Ethan; Keating, Brendan J; Tang, Weihong; Smith, Nicholas L; Delaney, Joseph A; Kumari, Meena; Hingorani, Aroon; North, Kari E; Kivimaki, Mika; et al. (Hum Mol Genet, 2011)
Polymorphisms in several distinct genomic regions, including the F7 gene, were recently associated with factor VII (FVII) levels in European Americans (EAs). The genetic determinants of FVII in African Americans (AAs) are unknown. We used a 50,000 single nucleotide polymorphism (SNP) gene-centric array having dense coverage of over 2,000 candidate genes for cardiovascular disease (CVD) pathways in a community-based sample of 16,324 EA and 3898 AA participants from the Candidate Gene Association Resource (CARe) consortium. Our aim was the discovery of new genomic loci and more detailed characterization of existing loci associated with FVII levels. In EAs, we identified three new loci associated with FVII, of which APOA5 on chromosome 11q23 and HNF4A on chromosome 20q12-13 were replicated in a sample of 4289 participants from the Whitehall II study. We confirmed four previously reported FVII-associated loci (GCKR, MS4A6A, F7 and PROCR) in CARe EA samples. In AAs, the F7 and PROCR regions were significantly associated with FVII. Several of the FVII-associated regions are known to be associated with lipids and other cardiovascular-related traits. At the F7 locus, there was evidence of at least five independently associated SNPs in EAs and three independent signals in AAs. Though the variance in FVII explained by the existing loci is substantial (20% in EA and 10% in AA), larger sample sizes and investigation of lower frequency variants may be required to identify additional FVII-associated loci in EAs and AAs and further clarify the relationship between FVII and other CVD risk factors.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Factor VII; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Health and function of participants in the Long Life Family Study: A comparison with other cohorts. - Newman, Anne B; Glynn, Nancy W; Taylor, Christopher A; Sebastiani, Paola; Perls, Thomas T; Mayeux, Richard; Christensen, Kaare; Zmuda, Joseph M; Barral, Sandra; Lee, Joseph H; Simonsick, Eleanor M; Walston, Jeremy D; et al. (Aging (Albany NY), 2011)
Individuals from families recruited for the Long Life Family Study (LLFS) (n= 4559) were examined and compared to individuals from other cohorts to determine whether the recruitment targeting longevity resulted in a cohort of individuals with better health and function. Other cohorts with similar data included the Cardiovascular Health Study, the Framingham Heart Study, and the New England Centenarian Study. Diabetes, chronic pulmonary disease and peripheral artery disease tended to be less common in LLFS probands and offspring compared to similar aged persons in the other cohorts. Pulse pressure and triglycerides were lower, high density lipids were higher, and a perceptual speed task and gait speed were better in LLFS. Age-specific comparisons showed differences that would be consistent with a higher peak, later onset of decline or slower rate of change across age in LLFS participants. These findings suggest several priority phenotypes for inclusion in future genetic analysis to identify loci contributing to exceptional survival.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Gait; Humans; Longevity; Male; Middle Aged; Psychomotor Performance; Research Design

High blood pressure accelerates gait slowing in well-functioning older adults over 18-years of follow-up. - Rosano, Caterina; Longstreth, William T; Boudreau, Robert; Taylor, Christopher A; Du, Yan; Kuller, Lewis H; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine whether the association between hypertension and decline in gait speed is significant in well-functioning older adults and whether other health-related factors, such as brain, kidney, and heart function, can explain it. DESIGN: Longitudinal cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Of 2,733 potential participants with a brain magnetic resonance imaging (MRI) scan, measures of mobility and systolic blood pressure (BP), no self-reported disability in 1992 to 1994 (baseline), and with at least 1 follow-up gait speed measurement through 1997 to 1999, 643 (aged 73.6, 57% female, 15% black) who had received a second MRI in 1997 to 1999 and an additional gait speed measure in 2005 to 2006 were included. MEASUREMENTS: Mixed models with random slopes and intercepts were adjusted for age, race, and sex. Main explanatory factors included white matter hyperintensity progression, baseline cystatin-C, and left cardiac ventricular mass. Incidence of stroke and dementia, BP trajectories, and intake of antihypertensive medications during follow-up were tested as other potential explanatory factors. RESULTS: Higher systolic BP was associated with faster rate of gait speed decline in this selected group of 643 participants, and results were similar in the parent cohort (N = 2,733). Participants with high BP (n = 293) had a significantly faster rate of gait speed decline than those with baseline BP less than 140/90 mmHg and no history of hypertension (n = 350). Rates were similar for those with history of hypertension who were uncontrolled (n = 110) or controlled (n = 87) at baseline and for those who were newly diagnosed (n = 96) at baseline. Adjustment for explanatory factors or for other covariates (education, prevalent cardiovascular disease, physical activity, vision, mood, cognition, muscle strength, body mass index, osteoporosis) did not change the results. CONCLUSION: High BP accelerates gait slowing in well-functioning older adults over a long period of time, even for those who control their BP or develop hypertension later in life. Health-related measurements did not explain these associations. Future studies to investigate the mechanisms linking hypertension to slowing gait in older adults are warranted.
Keywords: Aged; Antihypertensive Agents; Comorbidity; Female; Follow-Up Studies; Gait; Geriatric Assessment; Humans; Hypertension; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Statistics, Nonparametric

Hypertension, white matter hyperintensities, and concurrent impairments in mobility, cognition, and mood: the Cardiovascular Health Study. - Hajjar, Ihab; Quach, Lien; Yang, Frances; Chaves, Paulo H M; Newman, Anne B; Mukamal, Kenneth; Longstreth, Will; Inzitari, Marco; Lipsitz, Lewis A (Circulation, 2011)
BACKGROUND: Our objective was to investigate the association between hypertension and concurrent impairments in mobility, cognition, and mood; the role of brain white matter hyperintensities in mediating this association; and the impact of these impairments on disability and mortality in elderly hypertensive individuals. METHODS AND RESULTS: -Blood pressure, gait speed, digit symbol substitution test, and the Center for Epidemiological Studies Depression Scale were measured yearly (1992-1999) on 4700 participants in the Cardiovascular Health Study (age: 74.7, 58% women, 17% blacks, 68% hypertension, 3600 had brain magnetic resonance imaging in 1992-1993, survival data 1992-2005). Using latent profile analysis at baseline, we found that 498 (11%) subjects had concurrent impairments and 3086 (66%) were intact on all 3 measures. Between 1992 and 1999, 651 (21%) became impaired in all 3 domains. Hypertensive individuals were more likely to be impaired at baseline (odds ratio 1.23, 95% confidence interval 1.04 to 1.42, P=0.01) and become impaired during the follow-up (hazard ratio=1.3, 95% confidence interval 1.02 to 1.66, P=0.037). A greater degree of white matter hyperintensities was associated with impairments in the 3 domains (P=0.007) and mediated the association with hypertension (P=0.19 for hypertension after adjusting for white matter hyperintensities in the model, 21% hazard ratio change). Impairments in the 3 domains increased subsequent disability with hypertension (P<0.0001). Hypertension mortality also was increased in those impaired (compared with unimpaired hypertensive individuals: HR=1.10, 95% confidence interval 1.04 to 1.17, P=0.004). CONCLUSIONS: Hypertension increases the risk of concurrent impairments in mobility, cognition, and mood, which increases disability and mortality. This association is mediated in part by microvascular brain injury.
Keywords: Aged; Aged, 80 and over; Brain; Cognition Disorders; Female; Humans; Hypertension; Kaplan-Meier Estimate; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Mobility Limitation; Mood Disorders; Nerve Fibers, Myelinated; Retrospective Studies; Risk Factors

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

The Impact of Sleep-Disordered Breathing on Body Mass Index (BMI): The Sleep Heart Health Study (SHHS). - Brown, Mark A; Goodwin, James L; Silva, Graciela E; Behari, Ajay; Newman, Anne B; Punjabi, Naresh M; Resnick, Helaine E; Robbins, John A; Quan, Stuart F (Southwest J Pulm Crit Care, 2011)
INTRODUCTION: It is well known that obesity is a risk factor for sleep-disordered breathing (SDB). However, whether SDB predicts increase in BMI is not well defined. Data from the Sleep Heart Health Study (SHHS) were analyzed to determine whether SDB predicts longitudinal increase in BMI, adjusted for confounding factors. METHODS: A full-montage unattended home polysomnogram (PSG) and body anthropometric measurements were obtained approximately five years apart in 3001 participants. Apnea-hypopnea index (AHI) was categorized using clinical thresholds: < 5 (normal), ≥ 5 to <15 (mild sleep apnea), and ≥ 15 (moderate to severe sleep apnea). Linear regression was used to examine the association between the three AHI groups and increased BMI. The model included age, gender, race, baseline BMI, and change in AHI as covariates. RESULTS: Mean (SD) age was 62.2 years (10.14), 55.2% were female and 76.1% were Caucasian. Five-year increase in BMI was modest with a mean (SD) change of 0.53 (2.62) kg/m(2) (p=0.071). A multivariate regression model showed that subjects with a baseline AHI between 5-15 had a mean increase in BMI of 0.22 kg/m(2) (p=0.055) and those with baseline AHI ≥ 15 had a BMI increase of 0.51 kg/m(2) (p<0.001) compared to those with baseline AHI of <5. CONCLUSION: Our findings suggest that there is a positive association between severity of SDB and subsequent increased BMI over approximately 5 years. This observation may help explain why persons with SDB have difficulty losing weight.

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Lipoprotein-associated phospholipase A(2) and future risk of subclinical disease and cardiovascular events in individuals with type 2 diabetes: the Cardiovascular Health Study. - Nelson, T L; Kamineni, A; Psaty, B; Cushman, M; Jenny, N S; Hokanson, J; Furberg, C; Mukamal, K J (Diabetologia, 2011)
AIMS/HYPOTHESIS: Type 2 diabetes is an established risk factor for cardiovascular disease (CVD). This increased risk may be due in part to the increased levels of inflammatory factors associated with diabetes. Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is a risk marker for CVD and has pro-inflammatory effects in atherosclerotic plaques. We therefore sought to determine whether Lp-PLA(2) levels partially explain the greater prevalence of subclinical CVD and greater incidence of CVD outcomes associated with type 2 diabetes in the Cardiovascular Health Study. METHODS: We conducted a cross-sectional and prospective study of 4,062 men and women without previous CVD from the Cardiovascular Health Study (1989 to 2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Subclinical disease was determined at baseline and incident CVD was ascertained annually. We used logistic regression for cross-sectional analyses and Cox proportional hazards models for incident analyses. RESULTS: At baseline, Lp-PLA(2) mass did not differ significantly by type 2 diabetes status; however, Lp-PLA(2) activity was significantly higher among type 2 diabetic individuals. Baseline subclinical disease was significantly associated with baseline diabetes and this association was similar in models unadjusted or adjusted for Lp-PLA(2) (OR 1.68 [95% CI 1.31-2.15] vs OR 1.67 [95% CI 1.30-2.13]). Baseline type 2 diabetes was also significantly associated with incident CVD events, including fatal CHD, fatal myocardial infarction (MI) and non-fatal MI in multivariable analyses. There were no differences in these estimates after further adjustment for Lp-PLA(2) activity. CONCLUSIONS/INTERPRETATION: In this older cohort, differences in Lp-PLA(2) activity did not explain any of the excess risk for subclinical disease or CVD outcomes related to diabetes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors

Longitudinal changes in adiponectin and inflammatory markers and relation to survival in the oldest old: the Cardiovascular Health Study All Stars study. - Kizer, Jorge R; Arnold, Alice M; Jenny, Nancy S; Cushman, Mary; Strotmeyer, Elsa S; Ives, Diane G; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Adiponectin has anti-inflammatory properties, and its production is suppressed by inflammatory factors. Although elevated levels of adiponectin and inflammatory markers each predict mortality in older adults, the implications of their interdependent actions have not been examined. METHODS: We investigated the joint associations of levels and interval changes in adiponectin, C-reactive protein (CRP), and interleukin 6 (IL-6) with risk of death in 840 older adults participating in a population-based study. Adiponectin, CRP, and IL-6 were measured in samples collected 8.9 (8.2-9.8) years apart, and all-cause mortality was subsequently ascertained (n = 176). RESULTS: Interval changes and end levels of adiponectin, CRP, and IL-6 showed mostly positive, independent associations with mortality, without evidence of multiplicative interaction. Joint models, however, showed an U-shaped relationship between end level of adiponectin and outcome (hazard ratio [HR] [95% CI] = 0.72 [0.52-0.99] per standard deviation [SD] for levels <20.0 mg/L; HR = 1.91 [1.61-3.44] per SD for levels ≥20.0 mg/L). Participants with the greatest longitudinal increases (upper quartile) in both adiponectin and inflammatory markers had a higher risk of death (HR = 2.85 [1.78-4.58]) than those with large increases in adiponectin alone (HR = 1.87 [1.20-2.92]) (p = .043), but not inflammatory markers alone (HR = 2.48 [1.67-3.67]) (p = .55), as compared with smaller changes for both. CONCLUSION: Higher levels or interval change in adiponectin and inflammatory markers predict increased mortality in older persons independent of each other, although for adiponectin, the association appears inverse below 20 mg/L. These findings suggest that inflammatory and noninflammatory mechanisms governing aging-related decline operate in parallel and provide a potential explanation for paradoxical adiponectin-outcome associations reported previously.
Keywords: Adiponectin; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Chi-Square Distribution; Enzyme-Linked Immunosorbent Assay; Female; Humans; Inflammation; Interleukin-6; Male; Mortality; Predictive Value of Tests; Risk Factors; Sensitivity and Specificity; Survival Analysis; United States

Measurement of organ structure and function enhances understanding of the physiological basis of frailty: the Cardiovascular Health Study. - Sanders, Jason L; Boudreau, Robert M; Fried, Linda P; Walston, Jeremy D; Harris, Tamara B; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To determine whether disease burden is associated with frailty independent of diagnosed chronic disease and whether physiological measurements provide greater understanding of the etiology of frailty. DESIGN: Cross-sectional. SETTING: Community. PARTICIPANTS: Two thousand four hundred thirty-seven participants in the Cardiovascular Health Study, 1992/93 examination (mean age 74.8 ± 4.8, 43.4% male, 95.8% white). MEASUREMENTS: Disease burden and frailty were tabulated using 10-point scales (0 = healthy, 10 = unhealthy). Disease burden was the sum of measurements characterizing the vasculature, brain, kidneys, lungs, and glucose metabolism. Frailty was assessed using the frailty index reported by Fried. Multivariate linear models were used to determine the association between disease burden (predictor) and frailty (outcome). RESULTS: Unadjusted, 1-point-higher disease burden was associated with a 0.28-point-higher frailty score (P < .001). White matter grade, forced vital capacity, and cystatin-C were particularly strongly and significantly associated with frailty. Disease burden attenuated the association between frailty and age by 29%, and disease burden and age had similar associations with frailty. Disease burden attenuated the association between frailty and fibrinogen, Factor VIII, and C-reactive protein by 32%, 56%, and 83%, respectively. Frailty was associated with diagnosed depression, stroke, cognitive impairment, arthritis, and pulmonary disease but not coronary heart disease, diabetes mellitus, or kidney disease in the presence of a summary of disease burden. In the adjusted model, disease burden remained significantly associated with frailty (β = 0.11, P < .001). CONCLUSION: Disease burden was independently and significantly associated with frailty. These results emphasize that typically unrecognized physiological changes may contribute significantly to frailty.
Keywords: Aged, 80 and over; Cardiovascular Diseases; Chronic Disease; Cost of Illness; Cross-Sectional Studies; Female; Frail Elderly; Humans; Male

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

The Next PAGE in understanding complex traits: design for the analysis of Population Architecture Using Genetics and Epidemiology (PAGE) Study. - Matise, Tara C; Ambite, Jose Luis; Buyske, Steven; Carlson, Christopher S; Cole, Shelley A; Crawford, Dana C; Haiman, Christopher A; Heiss, Gerardo; Kooperberg, Charles; Marchand, Loic Le; Manolio, Teri A; North, Kari E; et al. (Am J Epidemiol, 2011)
Genetic studies have identified thousands of variants associated with complex traits. However, most association studies are limited to populations of European descent and a single phenotype. The Population Architecture using Genomics and Epidemiology (PAGE) Study was initiated in 2008 by the National Human Genome Research Institute to investigate the epidemiologic architecture of well-replicated genetic variants associated with complex diseases in several large, ethnically diverse population-based studies. Combining DNA samples and hundreds of phenotypes from multiple cohorts, PAGE is well-suited to address generalization of associations and variability of effects in diverse populations; identify genetic and environmental modifiers; evaluate disease subtypes, intermediate phenotypes, and biomarkers; and investigate associations with novel phenotypes. PAGE investigators harmonize phenotypes across studies where possible and perform coordinated cohort-specific analyses and meta-analyses. PAGE researchers are genotyping thousands of genetic variants in up to 121,000 DNA samples from African-American, white, Hispanic/Latino, Asian/Pacific Islander, and American Indian participants. Initial analyses will focus on single nucleotide polymorphisms (SNPs) associated with obesity, lipids, cardiovascular disease, type 2 diabetes, inflammation, various cancers, and related biomarkers. PAGE SNPs are also assessed for pleiotropy using the "phenome-wide association study" approach, testing each SNP for associations with hundreds of phenotypes. PAGE data will be deposited into the National Center for Biotechnology Information's Database of Genotypes and Phenotypes and made available via a custom browser.
Keywords: Epidemiologic Methods; Epidemiologic Research Design; Ethnic Groups; Genetic Association Studies; Genetics, Population; Genome-Wide Association Study; Humans; Interinstitutional Relations; Multifactorial Inheritance; National Human Genome Research Institute (U.S.); Phenotype; Pilot Projects; Research Design; Risk Factors; United States

NK-like T cells and plasma cytokines, but not anti-viral serology, define immune fingerprints of resilience and mild disability in exceptional aging. - Vallejo, Abbe N; Hamel, David L; Mueller, Robert G; Ives, Diane G; Michel, Joshua J; Boudreau, Robert M; Newman, Anne B (PLoS One, 2011)
Exceptional aging has been defined as maintenance of physical and cognitive function beyond the median lifespan despite a history of diseases and/or concurrent subclinical conditions. Since immunity is vital to individual fitness, we examined immunologic fingerprint(s) of highly functional elders. Therefore, survivors of the Cardiovascular Health Study in Pittsburgh, Pennsylvania, USA were recruited (n = 140; mean age = 86 years) and underwent performance testing. Blood samples were collected and examined blindly for humoral factors and T cell phenotypes. Based on results of physical and cognitive performance testing, elders were classified as "impaired" or "unimpaired", accuracy of group assignment was verified by discriminant function analysis. The two groups showed distinct immune profiles as determined by factor analysis. The dominant immune signature of impaired elders consisted of interferon (IFN)-γ, interleukin (IL)-6, tumor necrosis factor-α, and T cells expressing inhibitory natural killer-related receptors (NKR) CD158a, CD158e, and NKG2A. In contrast, the dominant signature of unimpaired elders consisted of IL-5, IL-12p70, and IL-13 with co-expression of IFN-γ, IL-4, and IL-17, and T cells expressing stimulatory NKRs CD56, CD16, and NKG2D. In logistic regression models, unimpaired phenotype was predicted independently by IL-5 and by CD4(+)CD28(null)CD56(+)CD57(+) T cells. All elders had high antibody titers to common viruses including cytomegalovirus. In cellular bioassays, T cell receptor (TCR)-independent ligation of either CD56 or NKG2D elicited activation of T cells. Collectively, these data demonstrate the importance of immunological parameters in distinguishing between health phenotypes of older adults. NKR(+) T cells and cytokine upregulation indicate a unique physiologic environment in old age. Correlation of particular NKR(+) T cell subsets and IL-5 with unimpaired performance, and NKR-driven TCR-independent activation of T cells suggest novel immunopathway(s) that could be exploited to improve immunity in old age.
Keywords: Adolescent; Adult; Aged, 80 and over; Aging; Cardiovascular Physiological Phenomena; CD56 Antigen; Cognition Disorders; Cytokines; Gene Expression Regulation; Humans; Immunity, Humoral; Killer Cells, Natural; Longevity; Male; NK Cell Lectin-Like Receptor Subfamily K; Phenotype; Physical Fitness; T-Lymphocyte Subsets; Young Adult

Patterns and predictors of recovery from exhaustion in older adults: the cardiovascular health study. - Whitson, Heather E; Thielke, Stephen; Diehr, Paula; O'Hare, Ann M; Chaves, Paulo H M; Zakai, Neil A; Arnold, Alice; Chaudhry, Sarwat; Ives, Diane; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To estimate the likelihood of, and factors associated with, recovery from exhaustion in older adults. DESIGN: Secondary analysis of a cohort study. SETTING: Six annual examinations in four U.S. communities. PARTICIPANTS: Four thousand five hundred eighty-four men and women aged 69 and older. MEASUREMENTS: Exhaustion was considered present when a participant responded "a moderate amount" or "most of the time" to either of two questions: "How often have you had a hard time getting going?" and "How often does everything seem an effort?" RESULTS: Of the 964 participants who originally reported exhaustion, 634 (65.8%) were exhaustion free at least once during follow-up. When data from all time points were considered, 48% of those who reported exhaustion were exhaustion free the following year. After adjustment for age, sex, race, education, and marital status, 1-year recovery was less likely in individuals with worse self-rated health and in those who were taking six or more medications or were obese, depressed, or had musculoskeletal pain or history of stroke. In proportional hazards models, the following risk factors were associated with more persistent exhaustion over 5 years: poor self-rated health, six or more medications, obesity, and depression. Recovery was not less likely in participants with a history of cancer or heart disease. CONCLUSION: Exhaustion is common in old age but is dynamic, even in those with a history of cancer and congestive heart failure. Recovery is especially likely in seniors who have a positive perception of their overall health, take few medications, and are not obese or depressed. These findings support the notion that resiliency is associated with physical and psychological well-being.
Keywords: Aged; Aging; Cardiovascular Physiological Phenomena; Exercise Test; Exercise Tolerance; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Predictive Value of Tests; Recovery of Function; Retrospective Studies; United States

A phenomics-based strategy identifies loci on APOC1, BRAP, and PLCG1 associated with metabolic syndrome phenotype domains. - Avery, Christy L; He, Qianchuan; North, Kari E; Ambite, José L; Boerwinkle, Eric; Fornage, Myriam; Hindorff, Lucia A; Kooperberg, Charles; Meigs, James B; Pankow, James S; Pendergrass, Sarah A; Psaty, Bruce M; et al. (PLoS Genet, 2011)
Despite evidence of the clustering of metabolic syndrome components, current approaches for identifying unifying genetic mechanisms typically evaluate clinical categories that do not provide adequate etiological information. Here, we used data from 19,486 European American and 6,287 African American Candidate Gene Association Resource Consortium participants to identify loci associated with the clustering of metabolic phenotypes. Six phenotype domains (atherogenic dyslipidemia, vascular dysfunction, vascular inflammation, pro-thrombotic state, central obesity, and elevated plasma glucose) encompassing 19 quantitative traits were examined. Principal components analysis was used to reduce the dimension of each domain such that >55% of the trait variance was represented within each domain. We then applied a statistically efficient and computational feasible multivariate approach that related eight principal components from the six domains to 250,000 imputed SNPs using an additive genetic model and including demographic covariates. In European Americans, we identified 606 genome-wide significant SNPs representing 19 loci. Many of these loci were associated with only one trait domain, were consistent with results in African Americans, and overlapped with published findings, for instance central obesity and FTO. However, our approach, which is applicable to any set of interval scale traits that is heritable and exhibits evidence of phenotypic clustering, identified three new loci in or near APOC1, BRAP, and PLCG1, which were associated with multiple phenotype domains. These pleiotropic loci may help characterize metabolic dysregulation and identify targets for intervention.
Keywords: African Americans; Apolipoprotein C-I; Blood Glucose; Dyslipidemias; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Humans; Metabolic Syndrome; Obesity, Abdominal; Phenotype; Phospholipase C gamma; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Ubiquitin-Protein Ligases; Vascular Diseases

Potential explanatory factors for higher incident hip fracture risk in older diabetic adults. - Strotmeyer, Elsa S; Kamineni, Aruna; Cauley, Jane A; Robbins, John A; Fried, Linda F; Siscovick, David S; Harris, Tamara B; Newman, Anne B (Curr Gerontol Geriatr Res, 2011)
Type 2 diabetes is associated with higher fracture risk. Diabetes-related conditions may account for this risk. Cardiovascular Health Study participants (N = 5641; 42.0% men; 15.5% black; 72.8±5.6 years) were followed 10.9 ± 4.6 years. Diabetes was defined as hypoglycemic medication use or fasting glucose (FG) ≥126 mg/dL. Peripheral artery disease (PAD) was defined as ankle-arm index <0.9. Incident hip fractures were from medical records. Crude hip fracture rates (/1000 person-years) were higher for diabetic vs. non-diabetic participants with BMI <25 (13.6, 95% CI: 8.9-20.2 versus 11.4, 95% CI: 10.1-12.9) and BMI ≥25 to <30 (8.3, 95% CI: 5.7-11.9 versus 6.6, 95% CI: 5.6-7.7), but similar for BMI ≥30. Adjusting for BMI, sex, race, and age, diabetes was related to fractures (HR = 1.34; 95% CI: 1.01-1.78). PAD (HR = 1.25 (95% CI: 0.92-1.57)) and longer walk time (HR = 1.07 (95% CI: 1.04-1.10)) modified the fracture risk in diabetes (HR = 1.17 (95% CI: 0.87-1.57)). Diabetes was associated with higher hip fracture risk after adjusting for BMI though this association was modified by diabetes-related conditions.

Retinal microvascular signs and functional loss in older persons: the cardiovascular health study. - Kim, Dae Hyun; Newman, Anne B; Hajjar, Ihab; Strotmeyer, Elsa S; Klein, Ronald; Newton, Elizabeth; Sarnak, Mark J; Burke, Gregory L; Lipsitz, Lewis A (Stroke, 2011)
BACKGROUND AND PURPOSE: We hypothesized that retinal microvascular signs are associated with executive dysfunction, slow gait, and depressive mood, which are characteristic features of microvascular disease affecting frontal subcortical regions of the brain. METHODS: In the Cardiovascular Health Study, 1744 participants (mean age, 78) free of stroke had retinal photographs and carotid ultrasound during the 1997 to 1998 visit. We examined the cross-sectional association of retinal signs with the digit-symbol substitution test (DSST) score, gait speed, the Center for Epidemiologic Studies-Depression score, and depressive mood, defined as Center for Epidemiologic Studies-Depression score >9 or antidepressant use. RESULTS: After adjusting for potential confounders, retinal signs were associated with lower DSST score (generalized arteriolar narrowing and arteriovenous nicking), slower gait (retinopathy), and depressive mood (generalized arteriolar narrowing). A higher number of retinal signs was associated with lower DSST score (-0.76 and -2.79 points for 1 sign and ≥2 signs versus none; P<0.001) and slower gait (-0.009 and -0.083 m/s; P=0.047), but not with the square root of Center for Epidemiologic Studies-Depression score (0.079 and -0.208; P=0.072). In addition, coexistence of retinal signs (generalized arteriolar narrowing and arteriovenous nicking) and carotid atherosclerosis was associated with lower DSST score compared with either process alone (P for interaction <0.01). Notably, further adjustment for ventricular size, white matter disease, and infarcts on MRI did not attenuate the association. CONCLUSIONS: Retinal signs are associated with executive dysfunction and slow gait, and possibly with depressive mood, suggesting a common process involving small vessels.
Keywords: Aged; Cardiovascular Diseases; Depressive Disorder; Frontal Lobe; Humans; Microcirculation; Neuropsychological Tests; Retinal Diseases; Retinal Vessels; Risk Factors

Risk factors for onset of disability among older persons newly diagnosed with heart failure: the Cardiovascular Health Study. - Chaudhry, Sarwat I; McAvay, Gail; Ning, Yuming; Allore, Heather G; Newman, Anne B; Gill, Thomas M (J Card Fail, 2011)
BACKGROUND: As the heart failure population continues to age, disability is becoming an increasingly important issue. Our objective was to identify risk factors for the onset of disability in activities of daily living among older persons with heart failure. METHODS: The study population included participants with newly diagnosed heart failure from the Cardiovascular Health Study, a longitudinal study of community-living, older persons. Data were collected through annual examinations. Cox regression modeling was used to examine associations between time-dependent predictors and onset of disability. RESULTS: Of 461 participants newly diagnosed with heart failure (mean age 78.7 [SD 5.89]), 23% subsequently developed disability. The first year after heart failure diagnosis was the period of greatest risk for onset of disability (chi-square P value <.001). Factors that were independently associated with disability included: impaired gait speed (HR 2.29, 95% CI 1.34-3.90); impaired cognition (HR 1.87, 95% CI 1.14-3.05); and depressive symptoms (HR 1.72, 95% CI 1.04-2.83). CONCLUSIONS: Onset of disability is a common occurrence among older persons newly diagnosed with heart failure. Risk factors for onset of disability in this population are potentially modifiable, and should be routinely assessed in an effort to reduce disability in this growing population.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Disability Evaluation; Disabled Persons; Female; Health Status; Heart Failure; Humans; Longitudinal Studies; Male; Risk Factors

The risk of Parkinson disease associated with urate in a community-based cohort of older adults. - Jain, S; Ton, T G; Boudreau, R M; Yang, M; Thacker, E L; Studenski, S; Longstreth, W T; Strotmeyer, E S; Newman, A B (Neuroepidemiology, 2011)
BACKGROUND/AIMS: Studies suggest an inverse association between urate concentration and the risk of Parkinson disease (PD). We investigated this in the Cardiovascular Health Study in an elderly community-based cohort of adults. METHODS: The association of baseline urate (µmol/l) and incident PD over 14 years was assessed with locally weighted scatterplot smoothing (LOESS) regression from which categories of low (<300 µmol/l), middle (300-500 µmol/l), and high (>500 µmol/l) urate ranges were derived. Multivariate logistic regression models assessed the risk of PD for each urate range. Linear and quadratic terms were tested when modeling the association between urate and the risk of PD. RESULTS: Women had significantly lower urate concentrations than did men [316.8 µmol/l (SD 88.0) vs. 367.4 µmol/l (SD 87.7), p < 0.0001] and in women no associations between urate and PD risk were observed. In men, LOESS curves suggested a U-shaped or threshold effect between urate and PD risk. With the middle range as reference, the risk of developing PD was significantly increased for urate <300 µmol/l (OR 1.69, 95% CI 1.03-2.78) but not for urate >500 µmol/l (OR 1.55, 95% CI 0.72-3.32) in men. A negative linear term was significant for urate <500 µmol/l, and across the entire range a convex quadratic term was significant. CONCLUSIONS: Results suggest a more complex relationship than previously reported between urate levels and the risk of PD in men. Low urate concentrations were associated with a higher PD risk and high urate concentrations were not associated with a further decrease in PD risk.
Keywords: Aged; California; Cohort Studies; Female; Humans; Male; Maryland; North Carolina; Parkinson Disease; Pennsylvania; Prospective Studies; Risk Factors; Sex Distribution; Sex Factors; Uric Acid

Separate and combined associations of body-mass index and abdominal adiposity with cardiovascular disease: collaborative analysis of 58 prospective studies. - Wormser, David; Kaptoge, Stephen; Di Angelantonio, Emanuele; Wood, Angela M; Pennells, Lisa; Thompson, Alex; Sarwar, Nadeem; Kizer, Jorge R; Lawlor, Debbie A; Nordestgaard, Børge G; Ridker, Paul; Salomaa, Veikko; et al. (Lancet, 2011)
BACKGROUND: Guidelines differ about the value of assessment of adiposity measures for cardiovascular disease risk prediction when information is available for other risk factors. We studied the separate and combined associations of body-mass index (BMI), waist circumference, and waist-to-hip ratio with risk of first-onset cardiovascular disease. METHODS: We used individual records from 58 cohorts to calculate hazard ratios (HRs) per 1 SD higher baseline values (4.56 kg/m(2) higher BMI, 12.6 cm higher waist circumference, and 0.083 higher waist-to-hip ratio) and measures of risk discrimination and reclassification. Serial adiposity assessments were used to calculate regression dilution ratios. RESULTS: Individual records were available for 221,934 people in 17 countries (14,297 incident cardiovascular disease outcomes; 1.87 million person-years at risk). Serial adiposity assessments were made in up to 63,821 people (mean interval 5.7 years [SD 3.9]). In people with BMI of 20 kg/m(2) or higher, HRs for cardiovascular disease were 1.23 (95% CI 1.17-1.29) with BMI, 1.27 (1.20-1.33) with waist circumference, and 1.25 (1.19-1.31) with waist-to-hip ratio, after adjustment for age, sex, and smoking status. After further adjustment for baseline systolic blood pressure, history of diabetes, and total and HDL cholesterol, corresponding HRs were 1.07 (1.03-1.11) with BMI, 1.10 (1.05-1.14) with waist circumference, and 1.12 (1.08-1.15) with waist-to-hip ratio. Addition of information on BMI, waist circumference, or waist-to-hip ratio to a cardiovascular disease risk prediction model containing conventional risk factors did not importantly improve risk discrimination (C-index changes of -0.0001, -0.0001, and 0.0008, respectively), nor classification of participants to categories of predicted 10-year risk (net reclassification improvement -0.19%, -0.05%, and -0.05%, respectively). Findings were similar when adiposity measures were considered in combination. Reproducibility was greater for BMI (regression dilution ratio 0.95, 95% CI 0.93-0.97) than for waist circumference (0.86, 0.83-0.89) or waist-to-hip ratio (0.63, 0.57-0.70). INTERPRETATION: BMI, waist circumference, and waist-to-hip ratio, whether assessed singly or in combination, do not importantly improve cardiovascular disease risk prediction in people in developed countries when additional information is available for systolic blood pressure, history of diabetes, and lipids. FUNDING: British Heart Foundation and UK Medical Research Council.
Keywords: Age Factors; Blood Pressure; Body Mass Index; Cardiovascular Diseases; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Middle Aged; Obesity, Abdominal; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Factors; Smoking; Systole; Waist Circumference; Waist-Hip Ratio

Serum 25-hydroxyvitamin D and physical function in older adults: the Cardiovascular Health Study All Stars. - Houston, Denise K; Tooze, Janet A; Davis, Cralen C; Chaves, Paulo H M; Hirsch, Calvin H; Robbins, John A; Arnold, Alice M; Newman, Anne B; Kritchevsky, Stephen B (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine the association between 25-hydroxyvitamin D (25(OH)D) and physical function in adults of advanced age. DESIGN: Cross-sectional and longitudinal analysis of physical function over 3 years of follow-up in the Cardiovascular Health Study All Stars. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Community-dwelling adults aged 77 to 100 (N = 988). MEASUREMENTS: Serum 25-hydroxyvitamin D 25(OH)D), Short Physical Performance Battery (SPPB), and grip and knee extensor strength assessed at baseline. Mobility disability (difficulty walking half a mile or up 10 steps) and activities of daily living (ADLs) disability were assessed at baseline and every 6 months over 3 years of follow-up. RESULTS: Almost one-third (30.8%) of participants were deficient in 25(OH)D (<20 ng/mL). SPPB scores were lower in those with deficient 25(OH)D (mean (standard error) 6.53 (0.24)) than in those with sufficient 25(OH)D (≥30 ng/mL) (7.15 (0.25)) after adjusting for sociodemographic characteristics, season, health behaviors, and chronic conditions (P = .006). Grip strength adjusted for body size was also lower in those with deficient 25(OH)D than in those with sufficient 25(OH)D (24.7 (0.6) kg vs 26.0 (0.6) kg, P = .02). Participants with deficient 25(OH)D were more likely to have prevalent mobility (OR = 1.44, 95% confidence interval (CI)) = 0.96-2.14) and ADL disability (OR = 1.51, 95% CI = 1.01-2.25) at baseline than those with sufficient 25(OH)D. Furthermore, participants with deficient 25(OH)D were at greater risk of incident mobility disability over 3 years of follow-up (hazard ratio = 1.56, 95% CI = 1.06-2.30). CONCLUSION: Vitamin D deficiency was common and was associated with poorer physical performance, lower muscle strength, and prevalent mobility and ADL disability in community-dwelling older adults. Moreover, vitamin D deficiency predicted incident mobility disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Female; Follow-Up Studies; Geriatric Assessment; Health Surveys; Humans; Male; Mobility Limitation; Muscle Strength; Physical Fitness; Proportional Hazards Models; Reference Values; United States; Vitamin D; Vitamin D Deficiency

Subclinical vascular disease burden and risk for death and cardiovascular events in older community dwellers. - Inzitari, Marco; Arnold, Alice M; Patel, Kushang V; Mercer, Laina D; Karlamangla, Arun; Ding, Jingzhong; Psaty, Bruce M; Williamson, Jeff D; Kuller, Lewis H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Individual measures and previous composite measures of subclinical vascular disease defined high risk for cardiovascular events, but did not detect low and modest risk. A different approach might better describe the spectrum from low to high risk. Methods and Results. In the Cardiovascular Health Study, 3,252 participants without history of clinical cardiovascular disease (M ± SD 74.3 years ± 5.1, 63% women, 17% African Americans) had noninvasive vascular assessments in 1992-1993. We assigned a score of 0, 1, or 2 (no, mild, or severe abnormalities) to ankle-arm index, electrocardiogram, and common carotid intima-media thickness, based on clinical cutoffs. A summary index (range 0-6, absent to severe disease) summed individual scores. Abdominal aortic ultrasound and brain magnetic resonance imaging were collected in a subsample. Mortality and incident cardiovascular events were identified through June 2008. Event and death rates increased across index grades. Comparing grades 1 to 5+ with absent disease, and adjusting for demographics, hazard ratios for cardiovascular events within 8 years ranged from 1.1 (95% confidence interval 0.8-1.6) to 4.7 (3.4-6.9) and, for mortality, from 1.5 (1.0-2.3) to 5.0 (3.3-7.7) (p for trend across grades <.001 for both outcomes). Adjustment for cardiovascular risk factors did not substantially change the associations. The index improved mortality risk classification over demographics and risk factors in participants who did not die during the follow-up. Including in the index the aortic ultrasound and the brain magnetic resonance imaging further improved risk classification. CONCLUSIONS: Older adults with minimal subclinical vascular disease had low cardiovascular events risk and mortality. This approach might more fully account for vascular burden.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cost of Illness; Female; Humans; Male; Risk; Vascular Diseases

Systolic blood pressure and incident heart failure in the elderly. The Cardiovascular Health Study and the Health, Ageing and Body Composition Study. - Butler, Javed; Kalogeropoulos, Andreas P; Georgiopoulou, Vasiliki V; Bibbins-Domingo, Kirsten; Najjar, Samer S; Sutton-Tyrrell, Kim C; Harris, Tamara B; Kritchevsky, Stephen B; Lloyd-Jones, Donald M; Newman, Anne B; Psaty, Bruce M (Heart, 2011)
BACKGROUND: The exact form of the association between systolic blood pressure (SBP) and heart failure (HF) risk in the elderly remains incompletely defined, especially in individuals not receiving antihypertensive drugs. OBJECTIVE: To examine the association between SBP and HF risk in the elderly. DESIGN: Competing-risks proportional hazards modelling of incident HF risk, using 10-year follow-up data from two NIH-sponsored cohort studies: the Cardiovascular Health Study (inception: 1989-90 and 1992-3) and the Health ABC Study (inception: 1997-8). SETTING: Community-based cohorts. PARTICIPANTS: 4408 participants (age, 72.8 (4.9) years; 53.1% women, 81.7% white; 18.3% black) without prevalent HF and not receiving antihypertensive drugs at baseline. MAIN OUTCOME MEASURES: Incident HF, defined as first adjudicated hospitalisation for HF. RESULTS: Over 10 years, 493 (11.2%) participants developed HF. Prehypertension (120-139 mm Hg), stage 1 (140-159 mm Hg), and stage 2 (≥160 mm Hg) hypertension were associated with escalating HF risk; HRs versus optimal SBP (<120 mm Hg) in competing-risks models controlling for clinical characteristics were 1.63 (95% CI 1.23 to 2.16; p=0.001), 2.21 (95% CI 1.65 to 2.96; p<0.001) and 2.60 (95% CI 1.85 to 3.64; p<0.001), respectively. Overall 255/493 (51.7%) HF events occurred in participants with SBP <140 mm Hg at baseline. Increasing SBP was associated with higher HF risk in women than in men; no race-SBP interaction was seen. In analyses with continuous SBP, HF risk had a continuous positive association with SBP to levels as low as 113 mm Hg in men and 112 mm Hg in women. CONCLUSIONS: There is a continuous positive association between SBP and HF risk in the elderly for levels of SBP as low as <115 mm Hg; over half of incident HF events occur in individuals with SBP <140 mm Hg.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Body Composition; Epidemiologic Methods; Female; Heart Failure; Humans; Hypertension; Male; Myocardial Infarction; Sex Factors; Stroke; Stroke Volume

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Age and association of kidney measures with mortality and end-stage renal disease. - Hallan, Stein I; Matsushita, Kunihiro; Sang, Yingying; Mahmoodi, Bakhtawar K; Black, Corri; Ishani, Areef; Kleefstra, Nanne; Naimark, David; Roderick, Paul; Tonelli, Marcello; Wetzels, Jack F M; Astor, Brad C; et al. (JAMA, 2012)
CONTEXT: Chronic kidney disease (CKD) is prevalent in older individuals, but the risk implications of low estimated glomerular filtration rate (eGFR) and high albuminuria across the full age range are controversial. OBJECTIVE: To evaluate possible effect modification (interaction) by age of the association of eGFR and albuminuria with clinical risk, examining both relative and absolute risks. DESIGN, SETTING, AND PARTICIPANTS: Individual-level meta-analysis including 2,051,244 participants from 33 general population or high-risk (of vascular disease) cohorts and 13 CKD cohorts from Asia, Australasia, Europe, and North/South America, conducted in 1972-2011 with a mean follow-up time of 5.8 years (range, 0-31 years). MAIN OUTCOME MEASURES: Hazard ratios (HRs) of mortality and end-stage renal disease (ESRD) according to eGFR and albuminuria were meta-analyzed across age categories after adjusting for sex, race, cardiovascular disease, diabetes, systolic blood pressure, cholesterol, body mass index, and smoking. Absolute risks were estimated using HRs and average incidence rates. RESULTS: Mortality (112,325 deaths) and ESRD (8411 events) risks were higher at lower eGFR and higher albuminuria in every age category. In general and high-risk cohorts, relative mortality risk for reduced eGFR decreased with increasing age; eg, adjusted HRs at an eGFR of 45 mL/min/1.73 m2 vs 80 mL/min/1.73 m2 were 3.50 (95% CI, 2.55-4.81), 2.21 (95% CI, 2.02-2.41), 1.59 (95% CI, 1.42-1.77), and 1.35 (95% CI, 1.23-1.48) in age categories 18-54, 55-64, 65-74, and ≥75 years, respectively (P <.05 for age interaction). Absolute risk differences for the same comparisons were higher at older age (9.0 [95% CI, 6.0-12.8], 12.2 [95% CI, 10.3-14.3], 13.3 [95% CI, 9.0-18.6], and 27.2 [95% CI, 13.5-45.5] excess deaths per 1000 person-years, respectively). For increased albuminuria, reduction of relative risk with increasing age was less evident, while differences in absolute risk were higher in older age categories (7.5 [95% CI, 4.3-11.9], 12.2 [95% CI, 7.9-17.6], 22.7 [95% CI, 15.3-31.6], and 34.3 [95% CI, 19.5-52.4] excess deaths per 1000 person-years, respectively by age category, at an albumin-creatinine ratio of 300 mg/g vs 10 mg/g). In CKD cohorts, adjusted relative hazards of mortality did not decrease with age. In all cohorts, ESRD relative risks and absolute risk differences at lower eGFR or higher albuminuria were comparable across age categories. CONCLUSIONS: Both low eGFR and high albuminuria were independently associated with mortality and ESRD regardless of age across a wide range of populations. Mortality showed lower relative risk but higher absolute risk differences at older age.
Keywords: Adolescent; Adult; Age Factors; Aged; Albuminuria; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Risk; Young Adult

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Association of fetuin-a with incident diabetes mellitus in community-living older adults: the cardiovascular health study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth J; Kizer, Jorge R; Zieman, Susan J; Siscovick, David S; Mozzaffarian, Dariush; Jensen, Majken K; Nelson, Lauren; Ruderman, Neil; Djoussé, Luc (Circulation, 2012)
BACKGROUND: The liver-secreted protein fetuin-A induces peripheral insulin resistance in vitro. In a pilot study, we observed that higher fetuin-A levels were associated with diabetes mellitus in older persons. However, this finding has not been confirmed in large cohorts. We sought to confirm the association of fetuin-A with incident diabetes mellitus in older persons and to determine whether the association differs by age, sex, and race and among persons with cardiovascular disease (CVD). METHODS AND RESULTS: Among 3710 community-living individuals ≥ 65 years of age without diabetes mellitus at baseline, fetuin-A was measured in serum collected in 1992 to 1993. Participants were followed up for 10.6 years (median) for incident diabetes mellitus. Cox regression models evaluated the association of fetuin-A with incident diabetes mellitus. Interaction terms evaluated heterogeneity by age, sex, race, and CVD. Mean age was 75 years; 60 were female; 15 were black; and 16 had CVD. Mean fetuin-A concentrations were 0.47 ± 0.10 g/L. During follow-up, 305 incident diabetes cases occurred. Each 0.10-g/L (SD)-greater fetuin-A was associated with 19 higher risk of diabetes mellitus (hazard ratio, 1.19; 95 confidence interval, 1.06-1.33) after adjustment for demographics, lifestyle factors, albumin, kidney function, and CVD. Further adjustment for potential mediators (body mass index, waist circumference, hypertension, lipids, and C-reactive protein) moderately attenuated the association (hazard ratio, 1.13; 95 confidence interval, 1.00-1.28). Results were similar by sex, race, and CVD status but were stronger in persons <75 years old (P for interaction=0.01). CONCLUSIONS: Higher fetuin-A is associated with incident diabetes mellitus in older persons regardless of sex, race, or prevalent CVD status. The association may be attenuated in those ≥ 75 years of age.
Keywords: African Continental Ancestry Group; Age Distribution; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Humans; Incidence; Life Style; Lipids; Male; Pilot Projects; Prevalence; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Distribution

Association of mild to moderate chronic kidney disease with venous thromboembolism: pooled analysis of five prospective general population cohorts. - Mahmoodi, Bakhtawar K; Gansevoort, Ron T; Næss, Inger Anne; Lutsey, Pamela L; Brækkan, Sigrid K; Veeger, Nic J G M; Brodin, Ellen E; Meijer, Karina; Sang, Yingying; Matsushita, Kunihiro; Hallan, Stein I; Hammerstrøm, Jens; et al. (Circulation, 2012)
BACKGROUND: Recent findings suggest that chronic kidney disease (CKD) may be associated with an increased risk of venous thromboembolism (VTE). Given the high prevalence of mild-to-moderate CKD in the general population, in depth analysis of this association is warranted. METHODS AND RESULTS: We pooled individual participant data from 5 community-based cohorts from Europe (second Nord-Trøndelag Health Study [HUNT2], Prevention of Renal and Vascular End-stage Disease [PREVEND], and the Tromsø study) and the United States (Atherosclerosis Risks in Communities [ARIC] and Cardiovascular Health Study [CHS]) to assess the association of estimated glomerular filtration rate (eGFR), albuminuria, and CKD with objectively verified VTE. To estimate adjusted hazard ratios for VTE, categorical and continuous spline models were fit by using Cox regression with shared-frailty or random-effect meta-analysis. A total of 1178 VTE events occurred over 599 453 person-years follow-up. Relative to eGFR 100 mL/min per 1.73 m(2), hazard ratios for VTE were 1.29 (95% confidence interval, 1.04-1.59) for eGFR 75, 1.31 (1.00-1.71) for eGFR 60, 1.82 (1.27-2.60) for eGFR 45, and 1.95 (1.26-3.01) for eGFR 30 mL/min per 1.73 m(2). In comparison with an albumin-to-creatinine ratio (ACR) of 5.0 mg/g, the hazard ratios for VTE were 1.34 (1.04-1.72) for ACR 30 mg/g, 1.60 (1.08-2.36) for ACR 300 mg/g, and 1.92 (1.19-3.09) for ACR 1000 mg/g. There was no interaction between clinical categories of eGFR and ACR (P=0.20). The adjusted hazard ratio for CKD, defined as eGFR <60 mL/min per 1.73 m(2) or albuminuria ≥30 mg/g, (versus no CKD) was 1.54 (95% confidence interval, 1.15-2.06). Associations were consistent in subgroups according to age, sex, and comorbidities, and for unprovoked versus provoked VTE, as well. CONCLUSIONS: Both eGFR and ACR are independently associated with increased risk of VTE in the general population, even across the normal eGFR and ACR ranges.
Keywords: Aged; Cohort Studies; Europe; Female; Humans; Incidence; Male; Middle Aged; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Severity of Illness Index; Venous Thromboembolism

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis. - Fox, Caroline S; Matsushita, Kunihiro; Woodward, Mark; Bilo, Henk J G; Chalmers, John; Heerspink, Hiddo J Lambers; Lee, Brian J; Perkins, Robert M; Rossing, Peter; Sairenchi, Toshimi; Tonelli, Marcello; Vassalotti, Joseph A; et al. (Lancet, 2012)
BACKGROUND: Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. METHODS: We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-stage renal disease (ESRD) associated with eGFR and albuminuria in individuals with and without diabetes. FINDINGS: We analysed data for 1,024,977 participants (128,505 with diabetes) from 30 general population and high-risk cardiovascular cohorts and 13 chronic kidney disease cohorts. In the combined general population and high-risk cohorts with data for all-cause mortality, 75,306 deaths occurred during a mean follow-up of 8·5 years (SD 5·0). In the 23 studies with data for cardiovascular mortality, 21,237 deaths occurred from cardiovascular disease during a mean follow-up of 9·2 years (SD 4·9). In the general and high-risk cohorts, mortality risks were 1·2-1·9 times higher for participants with diabetes than for those without diabetes across the ranges of eGFR and albumin-to-creatinine ratio (ACR). With fixed eGFR and ACR reference points in the diabetes and no diabetes groups, HR of mortality outcomes according to lower eGFR and higher ACR were much the same in participants with and without diabetes (eg, for all-cause mortality at eGFR 45 mL/min per 1·73 m(2) [vs 95 mL/min per 1·73 m(2)], HR 1·35; 95% CI 1·18-1·55; vs 1·33; 1·19-1·48 and at ACR 30 mg/g [vs 5 mg/g], 1·50; 1·35-1·65 vs 1·52; 1·38-1·67). The overall interactions were not significant. We identified much the same findings for ESRD in the chronic kidney disease cohorts. INTERPRETATION: Despite higher risks for mortality and ESRD in diabetes, the relative risks of these outcomes by eGFR and ACR are much the same irrespective of the presence or absence of diabetes, emphasising the importance of kidney disease as a predictor of clinical outcomes. FUNDING: US National Kidney Foundation.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Cause of Death; Diabetic Nephropathies; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Risk Factors

Associations of total and high-molecular-weight adiponectin with all-cause and cardiovascular mortality in older persons: the Cardiovascular Health Study. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Mantzoros, Christos S; deFilippi, Christopher R; Newman, Anne B; Djoussé, Luc (Circulation, 2012)
BACKGROUND: Adiponectin shows opposite associations with adverse outcomes in healthy middle-aged populations (lower risk) and cohorts with prevalent cardiovascular disease, heart failure, or advanced age (higher risk). METHODS AND RESULTS: In a population-based study of older adults, we examined the relationships of total and high-molecular-weight adiponectin with mortality among subgroups defined by baseline cardiovascular status: No cardiovascular disease, heart failure, or atrial fibrillation (group 1); cardiovascular disease but no heart failure/atrial fibrillation (group 2); and heart failure/atrial fibrillation (group 3). We found significant differences in the associations with all-cause mortality across the groups. The association in group 1 was U-shaped; increasing levels of total adiponectin up to 12.4 mg/L were associated with lower mortality after adjustment for confounders (hazard ratio=0.81 per 1 SD [95% confidence interval, 0.65-0.95]), but above this cut point, higher levels conferred greater risk (hazard ratio=1.19 [95% confidence interval, 1.12-1.27]). Further adjustment for diabetes mellitus or insulin resistance, protection against which has been proposed to mediate the beneficial relationships of adiponectin with outcome, attenuated the association in the lower range. There was no significant association in group 2, but in group 3, total adiponectin showed a direct adjusted association. Additional adjustment for putative metabolic/inflammatory intermediates suggested a direct association for group 2, and magnified the one for group 3 (hazard ratio=1.31 [1.15-1.50]). Results were similar for high-molecular-weight adiponectin and for cardiovascular mortality. CONCLUSIONS: Adiponectin exhibits distinct associations with mortality in elders, which shift from U-shaped to flat to direct with greater baseline cardiovascular dysfunction but become more consistently adverse after accounting for metabolic/inflammatory factors presumed to be favorably regulated by the adipokine. These findings advance understanding of the adiponectin paradox as it relates to older adults.
Keywords: Adiponectin; Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Female; Health Surveys; Humans; Male; Molecular Weight

Cardiovascular physiology in premotor Parkinson's disease: a neuroepidemiologic study. - Jain, Samay; Ton, Thanh G; Perera, Subashan; Zheng, Yan; Stein, Phyllis K; Thacker, Evan; Strotmeyer, Elsa S; Newman, Anne B; Longstreth, Will T (Mov Disord, 2012)
Changes in cardiovascular physiology in Parkinson's disease (PD) are common and may occur prior to diagnostic parkinsonian motor signs. We investigated associations of electrocardiographic (ECG) abnormalities, orthostasis, heart rate variability, and carotid stenosis with the risk of PD diagnosis in the Cardiovascular Health Study, a community-based cohort of older adults. ECG abnormality, orthostasis (symptomatic or asymptomatic), heart rate variability (24-hour Holter monitoring), and any carotid stenosis (≥1%) by ultrasound were modeled as primary predictors of incident PD diagnosis using multivariable logistic regression. Incident PD cases were identified by at least 1 of the following: self-report, antiparkinsonian medication use, and ICD-9. If unadjusted models were significant, they were adjusted or stratified by age, sex, and smoking status, and those in which predictors were still significant (P ≤ .05) were also adjusted for race, diabetes, total cholesterol, low-density lipoprotein, blood pressure, body mass index, physical activity, education level, stroke, and C-reactive protein. Of 5888 participants, 154 incident PD cases were identified over 14 years of follow-up. After adjusting models with all covariates, those with any ECG abnormality (odds ratio [OR], 1.45; 95% CI, 1.02-2.07; P = .04) or any carotid stenosis (OR, 2.40; 95% CI, 1.40-4.09; P = .001) at baseline had a higher risk of incident PD diagnosis. Orthostasis and heart rate variability were not significant predictors. This exploratory study suggests that carotid stenosis and ECG abnormalities occur prior to motor signs in PD, thus serving as potential premotor features or risk factors for PD diagnosis. Replication is needed in a population with more thorough ascertainment of PD onset.
Keywords: Aged; Antiparkinson Agents; Cardiovascular Physiological Phenomena; Carotid Stenosis; Cohort Studies; Data Interpretation, Statistical; Dizziness; Electrocardiography; Female; Heart Rate; Hospitalization; Humans; Longitudinal Studies; Male; Movement Disorders; Neurologic Examination; Parkinson Disease; Risk; Ultrasonography

Common genetic variants differentially influence the transition from clinically defined states of fasting glucose metabolism. - Walford, G A; Green, T; Neale, B; Isakova, T; Rotter, J I; Grant, S F A; Fox, C S; Pankow, J S; Wilson, J G; Meigs, J B; Siscovick, D S; Bowden, D W; et al. (Diabetologia, 2012)
AIMS/HYPOTHESIS: Common genetic variants have been associated with type 2 diabetes. We hypothesised that a subset of these variants may have different effects on the transition from normal fasting glucose (NFG) to impaired fasting glucose (IFG) than on that from IFG to diabetes. METHODS: We identified 16 type 2 diabetes risk variants from the Illumina Broad Candidate-gene Association Resource (CARe) array genotyped in 26,576 CARe participants. Participants were categorised at baseline as NFG, IFG or type 2 diabetic (n = 16,465, 8,017 or 2,291, respectively). Using Cox proportional hazards and likelihood ratio tests (LRTs), we compared rates of progression by genotype for 4,909 (NFG to IFG) and 1,518 (IFG to type 2 diabetes) individuals, respectively. We then performed multinomial regression analyses at baseline, comparing the risk of assignment to the NFG, IFG or diabetes groups by genotype. RESULTS: The rate of progression from NFG to IFG was significantly greater in participants carrying the risk allele at MTNR1B (p = 1 × 10(-4)), nominally greater at GCK and SLC30A8 (p < 0.05) and nominally smaller at IGF2BP2 (p = 0.01) than the rate of progression from IFG to diabetes by the LRT. Results of the baseline, multinomial regression model were consistent with these findings. CONCLUSIONS/INTERPRETATION: Common genetic risk variants at GCK, SLC30A8, IGF2BP2 and MTNR1B influence to different extents the development of IFG and the transition from IFG to type 2 diabetes. Our findings may have implications for understanding the genetic contribution of these variants to the development of IFG and type 2 diabetes.
Keywords: Adult; Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Disease Progression; Fasting; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Proportional Hazards Models; Regression Analysis; Risk

Comparing years of healthy life, measured in 16 ways, for normal weight and overweight older adults. - Diehr, Paula; Thielke, Stephen; O'Meara, Ellen; Fitzpatrick, Annette L; Newman, Anne (J Obes, 2012)
Introduction. The traditional definitions of overweight and obesity are not age specific, even though the relationship of weight to mortality is different for older adults. Effects of adiposity on aspects of health beside mortality have not been well investigated. Methods. We calculated the number of years of healthy life (YHL) in the 10 years after baseline, for 5,747 older adults. YHL was defined in 16 different ways. We compared Normal and Overweight persons, classified either by body mass index (BMI) or by waist circumference (WC). Findings. YHL for Normal and Overweight persons differed significantly in 25% of the comparisons, of which half favored the Overweight. Measures of physical health favored Normal weight, while measures of mental health and quality of life favored Overweight. Overweight was less favorable when defined by WC than by BMI. Obese persons usually had worse outcomes. Discussion. Overweight older adults averaged as many years of life and years of healthy life as those of Normal weight. There may be no outcome based reason to distinguish Normal from Overweight for older adults. Conclusion. The "Overweight paradox" appears to hold for nonmortality outcomes. New adiposity standards are needed for older adults, possibly different by race and sex.

Consistent directions of effect for established type 2 diabetes risk variants across populations: the population architecture using Genomics and Epidemiology (PAGE) Consortium. - Haiman, Christopher A; Fesinmeyer, Megan D; Spencer, Kylee L; Bůzková, Petra; Voruganti, V Saroja; Wan, Peggy; Haessler, Jeff; Franceschini, Nora; Monroe, Kristine R; Howard, Barbara V; Jackson, Rebecca D; Florez, Jose C; et al. (Diabetes, 2012)
Common genetic risk variants for type 2 diabetes (T2D) have primarily been identified in populations of European and Asian ancestry. We tested whether the direction of association with 20 T2D risk variants generalizes across six major racial/ethnic groups in the U.S. as part of the Population Architecture using Genomics and Epidemiology Consortium (16,235 diabetes case and 46,122 control subjects of European American, African American, Hispanic, East Asian, American Indian, and Native Hawaiian ancestry). The percentage of positive (odds ratio [OR] >1 for putative risk allele) associations ranged from 69% in American Indians to 100% in European Americans. Of the nine variants where we observed significant heterogeneity of effect by racial/ethnic group (P(heterogeneity) < 0.05), eight were positively associated with risk (OR >1) in at least five groups. The marked directional consistency of association observed for most genetic variants across populations implies a shared functional common variant in each region. Fine-mapping of all loci will be required to reveal markers of risk that are important within and across populations.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Metagenomics; Middle Aged; Population Groups; Risk; Risk Factors

Decline in circulating insulin-like growth factors and mortality in older adults: cardiovascular health study all-stars study. - Kaplan, Robert C; Bůzková, Petra; Cappola, Anne R; Strickler, Howard D; McGinn, Aileen P; Mercer, Laina D; Arnold, Alice M; Pollak, Michael N; Newman, Anne B (J Clin Endocrinol Metab, 2012)
BACKGROUND: The association between changes in IGF-I and IGF binding protein (IGFBP) levels and mortality in older adults is unknown. STUDY DESIGN: Participants were 997 persons 77 to 100 yr old enrolled in the Cardiovascular Health Study All Stars Study. Plasma levels of IGF-I, IGFBP-1, and IGFBP-3 were assessed at two study examinations (1996-1997 and 2005-2006). Mortality was assessed between 2006 and 2010. RESULTS: Cumulative mortality (CM) was similar among individuals who had at least 10% decreases over time in IGF-I levels (CM = 29.6%), individuals who had at least 10% increases over time in IGF-I levels (CM = 24.7%), and individuals who had IGF-I levels remaining within ±10% over time (CM = 23.5%). Adjusted for age, sex, race, diabetes, body mass index, creatinine, albumin, and C-reactive protein, decreasing IGF-I level had no significant association with overall cancer mortality or noncancer mortality. Levels of IGFBP-1 increased markedly over time by 38% (median). Individuals with the largest increases in IGFBP-1 level over time had significantly increased risk of mortality. The adjusted hazard ratio per sd of IGFBP-1 change was 1.40 for overall cancer mortality (95% confidence interval = 1.10, 1.77; P = 0.01) and 1.14 for noncancer mortality (95% confidence interval = 1.02, 1.27; P = 0.02). Changes in IGFBP-3 levels were not significantly associated with mortality. CONCLUSION: Among older adults, decreasing IGF-I level over time does not predict subsequent all-cause mortality, whereas increasing IGFBP-1 predicts increased risk of mortality.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Longitudinal Studies; Male; Mortality; Predictive Value of Tests; Risk Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Evaluation of the metabochip genotyping array in African Americans and implications for fine mapping of GWAS-identified loci: the PAGE study. - Buyske, Steven; Wu, Ying; Carty, Cara L; Cheng, Iona; Assimes, Themistocles L; Dumitrescu, Logan; Hindorff, Lucia A; Mitchell, Sabrina; Ambite, Jose Luis; Boerwinkle, Eric; Bůzková, Petra; Carlson, Chris S; et al. (PLoS One, 2012)
The Metabochip is a custom genotyping array designed for replication and fine mapping of metabolic, cardiovascular, and anthropometric trait loci and includes low frequency variation content identified from the 1000 Genomes Project. It has 196,725 SNPs concentrated in 257 genomic regions. We evaluated the Metabochip in 5,863 African Americans; 89% of all SNPs passed rigorous quality control with a call rate of 99.9%. Two examples illustrate the value of fine mapping with the Metabochip in African-ancestry populations. At CELSR2/PSRC1/SORT1, we found the strongest associated SNP for LDL-C to be rs12740374 (p = 3.5 × 10(-11)), a SNP indistinguishable from multiple SNPs in European ancestry samples due to high correlation. Its distinct signal supports functional studies elsewhere suggesting a causal role in LDL-C. At CETP we found rs17231520, with risk allele frequency 0.07 in African Americans, to be associated with HDL-C (p = 7.2 × 10(-36)). This variant is very rare in Europeans and not tagged in common GWAS arrays, but was identified as associated with HDL-C in African Americans in a single-gene study. Our results, one narrowing the risk interval and the other revealing an associated variant not found in Europeans, demonstrate the advantages of high-density genotyping of common and rare variation for fine mapping of trait loci in African American samples.
Keywords: African Americans; Cardiovascular Diseases; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human; Cohort Studies; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; Metabolic Diseases; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Evolution and functional impact of rare coding variation from deep sequencing of human exomes. - Tennessen, Jacob A; Bigham, Abigail W; O'Connor, Timothy D; Fu, Wenqing; Kenny, Eimear E; Gravel, Simon; McGee, Sean; Do, Ron; Liu, Xiaoming; Jun, Goo; Kang, Hyun Min; Jordan, Daniel; et al. (Science, 2012)
As a first step toward understanding how rare variants contribute to risk for complex diseases, we sequenced 15,585 human protein-coding genes to an average median depth of 111× in 2440 individuals of European (n = 1351) and African (n = 1088) ancestry. We identified over 500,000 single-nucleotide variants (SNVs), the majority of which were rare (86% with a minor allele frequency less than 0.5%), previously unknown (82%), and population-specific (82%). On average, 2.3% of the 13,595 SNVs each person carried were predicted to affect protein function of ~313 genes per genome, and ~95.7% of SNVs predicted to be functionally important were rare. This excess of rare functional variants is due to the combined effects of explosive, recent accelerated population growth and weak purifying selection. Furthermore, we show that large sample sizes will be required to associate rare variants with complex traits.
Keywords: African Americans; Disease; European Continental Ancestry Group; Evolution, Molecular; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Polymorphism, Single Nucleotide; Population Growth; Selection, Genetic

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Genome-wide meta-analysis points to CTC1 and ZNF676 as genes regulating telomere homeostasis in humans. - Mangino, Massimo; Hwang, Shih-Jen; Spector, Timothy D; Hunt, Steven C; Kimura, Masayuki; Fitzpatrick, Annette L; Christiansen, Lene; Petersen, Inge; Elbers, Clara C; Harris, Tamara; Chen, Wei; Srinivasan, Sathanur R; et al. (Hum Mol Genet, 2012)
Leukocyte telomere length (LTL) is associated with a number of common age-related diseases and is a heritable trait. Previous genome-wide association studies (GWASs) identified two loci on chromosomes 3q26.2 (TERC) and 10q24.33 (OBFC1) that are associated with the inter-individual LTL variation. We performed a meta-analysis of 9190 individuals from six independent GWAS and validated our findings in 2226 individuals from four additional studies. We confirmed previously reported associations with OBFC1 (rs9419958 P = 9.1 × 10(-11)) and with the telomerase RNA component TERC (rs1317082, P = 1.1 × 10(-8)). We also identified two novel genomic regions associated with LTL variation that map near a conserved telomere maintenance complex component 1 (CTC1; rs3027234, P = 3.6 × 10(-8)) on chromosome17p13.1 and zinc finger protein 676 (ZNF676; rs412658, P = 3.3 × 10(-8)) on 19p12. The minor allele of rs3027234 was associated with both shorter LTL and lower expression of CTC1. Our findings are consistent with the recent observations that point mutations in CTC1 cause short telomeres in both Arabidopsis and humans affected by a rare Mendelian syndrome. Overall, our results provide novel insights into the genetic architecture of inter-individual LTL variation in the general population.
Keywords: Genome-Wide Association Study; Humans; Kruppel-Like Transcription Factors; Telomere; Telomere Homeostasis; Telomere-Binding Proteins

Hemoglobin A1c and arterial and ventricular stiffness in older adults. - Zieman, Susan J; Kamineni, Aruna; Ix, Joachim H; Barzilay, Joshua; Djoussé, Luc; Kizer, Jorge R; Biggs, Mary L; de Boer, Ian H; Chonchol, Michel; Gottdiener, John S; Selvin, Elizabeth; Newman, Anne B; et al. (PLoS One, 2012)
OBJECTIVE: Arterial and ventricular stiffening are characteristics of diabetes and aging which confer significant morbidity and mortality; advanced glycation endproducts (AGE) are implicated in this stiffening pathophysiology. We examined the association between HbA(1c), an AGE, with arterial and ventricular stiffness measures in older individuals without diabetes. RESEARCH DESIGN & METHODS: Baseline HbA(1c) was measured in 830 participants free of diabetes defined by fasting glucose or medication use in the Cardiovascular Health Study, a population-based cohort study of adults aged ≥ 65 years. We performed cross-sectional analyses using baseline exam data including echocardiography, ankle and brachial blood pressure measurement, and carotid ultrasonography. We examined the adjusted associations between HbA(1c) and multiple arterial and ventricular stiffness measures by linear regression models and compared these results to the association of fasting glucose (FG) with like measures. RESULTS: HbA(1c) was correlated with fasting and 2-hour postload glucose levels (r = 0.21; p<0.001 for both) and positively associated with greater body-mass index and black race. In adjusted models, HbA(1c) was not associated with any measure of arterial or ventricular stiffness, including pulse pressure (PP), carotid intima-media thickness, ankle-brachial index, end-arterial elastance, or left ventricular mass (LVM). FG levels were positively associated with systolic, diastolic and PP and LVM. CONCLUSIONS: In this sample of older adults without diabetes, HbA(1c) was not associated with arterial or ventricular stiffness measures, whereas FG levels were. The role of AGE in arterial and ventricular stiffness in older adults may be better assessed using alternate AGE markers.
Keywords: Adult; African Continental Ancestry Group; Aged; Ankle Brachial Index; Arteries; Blood Glucose; Blood Pressure; Body Mass Index; Cross-Sectional Studies; Fasting; Female; Genetic Association Studies; Glycated Hemoglobin A; Glycation End Products, Advanced; Heart Ventricles; Humans; Male; Middle Aged; Ultrasonography; Vascular Stiffness

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Impact of blood pressure and blood pressure change during middle age on the remaining lifetime risk for cardiovascular disease: the cardiovascular lifetime risk pooling project. - Allen, Norrina; Berry, Jarett D; Ning, Hongyan; Van Horn, Linda; Dyer, Alan; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: Prior estimates of lifetime risk (LTR) for cardiovascular disease (CVD) examined the impact of blood pressure (BP) at the index age and did not account for changes in BP over time. We examined how changes in BP during middle age affect LTR for CVD, coronary heart disease, and stroke. METHODS AND RESULTS: Data from 7 diverse US cohort studies were pooled. Remaining LTRs for CVD, coronary heart disease, and stroke were estimated for white and black men and women with death free of CVD as a competing event. LTRs for CVD by BP strata and by changes in BP over an average of 14 years were estimated. Starting at 55 years of age, we followed up 61 585 men and women for 700 000 person-years. LTR for CVD was 52.5% (95% confidence interval, 51.3-53.7) for men and 39.9% (95% confidence interval, 38.7-41.0) for women. LTR for CVD was higher for blacks and increased with increasing BP at index age. Individuals who maintained or decreased their BP to normal levels had the lowest remaining LTR for CVD, 22% to 41%, compared with individuals who had or developed hypertension by 55 years of age, 42% to 69%, suggesting a dose-response effect for the length of time at high BP levels. CONCLUSIONS: Individuals who experience increases or decreases in BP in middle age have associated higher and lower remaining LTR for CVD. Prevention efforts should continue to emphasize the importance of lowering BP and avoiding or delaying the incidence of hypertension to reduce the LTR for CVD.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Humans; Hypertension; Life Tables; Longitudinal Studies; Male; Middle Aged; Risk Factors

Insulin resistance and incident peripheral artery disease in the Cardiovascular Health Study. - Britton, Kathryn A; Mukamal, Kenneth J; Ix, Joachim H; Siscovick, David S; Newman, Anne B; de Boer, Ian H; Thacker, Evan L; Biggs, Mary L; Gaziano, J Michael; Djoussé, Luc (Vasc Med, 2012)
Type 2 diabetes is a risk factor for peripheral artery disease (PAD), and insulin resistance is a key feature of diabetes and pre-diabetes. No longitudinal epidemiological study has examined the relation between insulin resistance and PAD. Our study analyzed the association of quartiles of the homeostatic model of insulin resistance (HOMA-IR) and the development of PAD defined by two methods. PAD was first defined as the development of an abnormal ankle-brachial index (ABI) (dichotomous outcome) after 6 years of follow-up. PAD was alternatively defined as the development of clinical PAD (time-to-event analysis). The study samples included adults over the age of 65 years who were enrolled in the Cardiovascular Health Study, had fasting measurements of insulin and glucose, had ABI measurements, and were not receiving treatment for diabetes. Multivariable models were adjusted for potential confounders, including age, sex, field center and cohort, body mass index (BMI), smoking status, alcohol use, and exercise intensity. Additional models adjusted for potential mediators, including blood pressure, lipids, kidney function, and prevalent vascular disease. In the ABI analysis (n = 2108), multivariable adjusted models demonstrated a positive relation between HOMA-IR and incident PAD (odds ratio = 1.80 comparing the 4th versus 1st quartile of HOMA-IR, 95% confidence interval [CI] 1.20-2.71). In the clinical PAD analysis (n = 4208), we found a similar relation (hazard ratio = 2.30 comparing the 4th versus 1st quartile of HOMA-IR, 95% CI 1.15-4.58). As expected, further adjustment for potential mediators led to some attenuation of effect estimates. In conclusion, insulin resistance is associated with a higher risk of PAD in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Blood Glucose; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Fasting; Female; Health Surveys; Humans; Incidence; Insulin; Insulin Resistance; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Peripheral Arterial Disease; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Kidney function and mortality in octogenarians: Cardiovascular Health Study All Stars. - Shastri, Shani; Katz, Ronit; Rifkin, Dena E; Fried, Linda F; Odden, Michelle C; Peralta, Carmen A; Chonchol, Michel; Siscovick, David; Shlipak, Michael G; Newman, Anne B; Sarnak, Mark J (J Am Geriatr Soc, 2012)
OBJECTIVES: To examine the association between kidney function and all-cause mortality in octogenarians. DESIGN: Retrospective analysis of prospectively collected data. SETTING: Community. PARTICIPANTS: Serum creatinine and cystatin C were measured in 1,053 Cardiovascular Health Study (CHS) All Stars participants. MEASUREMENTS: Estimated glomerular filtration rate (eGFR) was determined using the Chronic Kidney Disease Epidemiology Collaboration creatinine (eGFR(CR) ) and cystatin C one-variable (eGFR(CYS) ) equations. The association between quintiles of kidney function and all-cause mortality was analyzed using unadjusted and adjusted Cox proportional hazards models. RESULTS: Mean age of the participants was 85, 64% were female, 66% had hypertension, 14% had diabetes mellitus, and 39% had prevalent cardiovascular disease. There were 154 deaths over a median follow-up of 2.6 years. The association between eGFR(CR) and all-cause mortality was U-shaped. In comparison with the reference quintile (64-75 mL/min per 1.73 m(2) ), the highest (≥ 75 mL/min per 1.73 m(2) ) and lowest (≤ 43 mL/min per 1.73 m(2) ) quintiles of eGFR(CR) were independently associated with mortality (hazard ratio (HR) = 2.49, 95% confidence interval (CI) = 1.36-4.55; HR = 2.28, 95% CI = 1.26-4.10, respectively). The association between eGFR(CYS) and all-cause mortality was linear in those with eGFR(CYS) of less than 60 mL/min per 1.73 m(2) , and in the multivariate analyses, the lowest quintile of eGFR(CYS) (<52 mL/min per 1.73 m(2) ) was significantly associated with mortality (HR = 2.04, 95% CI = 1.12-3.71) compared with the highest quintile (>0.88 mL/min per 1.73 m(2) ). CONCLUSION: Moderate reduction in kidney function is a risk factor for all-cause mortality in octogenarians. The association between eGFR(CR) and all-cause mortality differed from that observed with eGFR(CYS) ; the relationship was U-shaped for eGFR(CR) , whereas the risk was primarily present in the lowest quintile for eGFR(CYS) .
Keywords: Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Creatinine; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney Diseases; Male; Prevalence; Proportional Hazards Models; Retrospective Studies; Risk Factors; United States

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Leukocyte telomere length is associated with noninvasively measured age-related disease: The Cardiovascular Health Study. - Sanders, Jason L; Fitzpatrick, Annette L; Boudreau, Robert M; Arnold, Alice M; Aviv, Abraham; Kimura, Masayuki; Fried, Linda F; Harris, Tamara B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Most studies of leukocyte telomere length (LTL) focus on diagnosed disease in one system. A more encompassing depiction of health is disease burden, defined here as the sum of noninvasively measured markers of structure or function in different organ systems. We determined if (a) shorter LTL is associated with greater age-related disease burden and (b) shorter LTL is less strongly associated with disease in individual systems or diagnosed chronic conditions (cardiovascular disease, stroke, pulmonary disease, diabetes, kidney disease, arthritis, or depression). METHODS: LTL was measured by Southern blots of terminal restriction fragment length. Age-related disease was measured noninvasively and included carotid intima-media thickness, lung vital capacity, white matter grade, cystatin-C, and fasting glucose; each graded 0 (best tertile), 1 (middle tertile), or 2 (worst tertile) and summed (0 to 10) to estimate disease burden. Of 419 participants randomly selected for LTL measurement, 236 had disease burden assessed (mean [SD] age 74.2 [4.9] years, 42.4% male, 86.8% white, and 13.2% black). RESULTS: Mean (SD) LTL was 6,312 (615) bp, and disease score was 4.7 (2.1) points. An SD higher disease score (β [SE] = -132 [47] bp, p < .01), age (β [SE] = -107 [46], p = .02) or carotid thickness (β [SE] = -95 [40] bp, p = .02) was associated with shorter LTL, but diagnosed conditions or number of conditions were not associated with LTL. Disease score attenuated the effect of age on LTL by 35%. CONCLUSION: LTL was associated with a characterization of age-related disease burden across multiple physiologic systems, which was comparable to, but independent of, its association with age.
Keywords: African Americans; Aged; Aged, 80 and over; Cardiovascular Diseases; Carotid Intima-Media Thickness; Chronic Disease; Cystatin C; European Continental Ancestry Group; Female; Humans; Leukocytes; Lung; Male; Middle Aged; Telomere Homeostasis

Lifetime risk and years lived free of total cardiovascular disease. - Wilkins, John T; Ning, Hongyan; Berry, Jarett; Zhao, Lihui; Dyer, Alan R; Lloyd-Jones, Donald M (JAMA, 2012)
CONTEXT: Estimates of lifetime risk for total cardiovascular disease (CVD) may provide projections of the future population burden of CVD and may assist in clinician-patient risk communication. To date, no lifetime risk estimates of total CVD have been reported. OBJECTIVES: To calculate lifetime risk estimates of total CVD by index age (45, 55, 65, 75 years) and risk factor strata and to estimate years lived free of CVD across risk factor strata. DESIGN, SETTING, AND PARTICIPANTS: Pooled survival analysis of as many as 905,115 person-years of data from 1964 through 2008 from 5 National Heart, Lung, and Blood Institute-funded community-based cohorts: Framingham Heart Study, Framingham Offspring Study, Atherosclerosis Risk in Communities Study, Chicago Heart Association Detection Project in Industry Study, and Cardiovascular Health Study. All participants were free of CVD at baseline with risk factor data (blood pressure [BP], total cholesterol [TC], diabetes, and smoking status) and total CVD outcome data. MAIN OUTCOME MEASURES: Any total CVD event (including fatal and nonfatal coronary heart disease, all forms of stroke, congestive heart failure, and other CVD deaths). RESULTS: At an index age of 45 years, overall lifetime risk for total CVD was 60.3% (95% CI, 59.3%-61.2%) for men and 55.6% (95% CI, 54.5%-56.7%) for women. Men had higher lifetime risk estimates than women across all index ages. At index ages 55 and 65 years, men and women with at least 1 elevated risk factor (BP, 140-149/90-99 mm Hg; or TC, 200-239 mg/dL; but no diabetes or smoking), 1 major risk factor, or at least 2 major risk factors (BP, ≥160/100 mm Hg or receiving treatment; TC, ≥240 mg/dL or receiving treatment; diabetes mellitus; or current smoking) had lifetime risk estimates to age 95 years that exceeded 50%. Despite an optimal risk factor profile (BP, <120/80 mm Hg; TC, <180 mg/dL; and no smoking or diabetes), men and women at the index age of 55 years had lifetime risks (through 85 years of age) for total CVD of greater than 40% and 30%, respectively. Compared with participants with at least 2 major risk factors, those with an optimal risk factor profile lived up to 14 years longer free of total CVD. CONCLUSIONS: Lifetime risk estimates for total CVD were high (>30%) for all individuals, even those with optimal risk factors in middle age. However, maintenance of optimal risk factor levels in middle age was associated with substantially longer morbidity-free survival.
Keywords: Adult; Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Forecasting; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Morbidity; Risk; Risk Factors; Smoking

Lifetime risks of cardiovascular disease. - Berry, Jarett D; Dyer, Alan; Cai, Xuan; Garside, Daniel B; Ning, Hongyan; Thomas, Avis; Greenland, Philip; Van Horn, Linda; Tracy, Russell P; Lloyd-Jones, Donald M (N Engl J Med, 2012)
BACKGROUND: The lifetime risks of cardiovascular disease have not been reported across the age spectrum in black adults and white adults. METHODS: We conducted a meta-analysis at the individual level using data from 18 cohort studies involving a total of 257,384 black men and women and white men and women whose risk factors for cardiovascular disease were measured at the ages of 45, 55, 65, and 75 years. Blood pressure, cholesterol level, smoking status, and diabetes status were used to stratify participants according to risk factors into five mutually exclusive categories. The remaining lifetime risks of cardiovascular events were estimated for participants in each category at each age, with death free of cardiovascular disease treated as a competing event. RESULTS: We observed marked differences in the lifetime risks of cardiovascular disease across risk-factor strata. Among participants who were 55 years of age, those with an optimal risk-factor profile (total cholesterol level, <180 mg per deciliter [4.7 mmol per liter]; blood pressure, <120 mm Hg systolic and 80 mm Hg diastolic; nonsmoking status; and nondiabetic status) had substantially lower risks of death from cardiovascular disease through the age of 80 years than participants with two or more major risk factors (4.7% vs. 29.6% among men, 6.4% vs. 20.5% among women). Those with an optimal risk-factor profile also had lower lifetime risks of fatal coronary heart disease or nonfatal myocardial infarction (3.6% vs. 37.5% among men, <1% vs. 18.3% among women) and fatal or nonfatal stroke (2.3% vs. 8.3% among men, 5.3% vs. 10.7% among women). Similar trends within risk-factor strata were observed among blacks and whites and across diverse birth cohorts. CONCLUSIONS: Differences in risk-factor burden translate into marked differences in the lifetime risk of cardiovascular disease, and these differences are consistent across race and birth cohorts. (Funded by the National Heart, Lung, and Blood Institute.).
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Effect; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Risk; Risk Assessment; Risk Factors; United States

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Lipoprotein-associated phospholipase A2 (Lp-PLA2) and future risk of type 2 diabetes: results from the Cardiovascular Health Study. - Nelson, T L; Biggs, M L; Kizer, J R; Cushman, M; Hokanson, J E; Furberg, C D; Mukamal, K J (J Clin Endocrinol Metab, 2012)
INTRODUCTION: Lipoprotein-associated phospholipase A2 (Lp-PLA(2)) has been consistently associated with cardiovascular disease (CVD) risk factors and predictive of CVD outcomes; furthermore, it is consistently higher among type 2 diabetics than nondiabetics. However, the relationships of circulating Lp-PLA(2) mass and activity with incident type 2 diabetes mellitus have not been examined. Therefore, the purpose of this study was to determine the association of Lp-PLA(2) mass and activity with type 2 diabetes among older adults. METHODS: We conducted analyses of Lp-PLA(2) and prevalent and incident diabetes among 5474 men and women from the Cardiovascular Health Study (1989-2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Diabetes status was ascertained annually with medication inventories and repeated blood glucose measurements. Generalized linear and Cox proportional hazards models were used to adjust for confounding factors including body mass index and inflammation. RESULTS: At baseline, the top two quintiles of Lp-PLA(2) activity were significantly associated with prevalent type 2 diabetes with a multivariable relative risk = 1.35 [95% confidence interval (CI) = 1.11-1.63] for quintile 4, and relative risk = 1.33 (95% CI = 1.07-1.66) for quintile 5. Among participants free of diabetes at baseline, we found a significant positive association with both the homeostatic model assessment for insulin resistance and β-cell function per SD increase in Lp-PLA(2) activity (P values for both <0.01). In prospective analyses, the risk of incident type 2 diabetes was significantly higher among those in the highest quintile of Lp-PLA(2) activity [multivariable hazard ratio = 1.45 (95% CI = 1.01-2.07)] compared with the lowest quintile. Lp-PLA(2) mass was not significantly associated with incident type 2 diabetes. DISCUSSION: Lp-PLA(2) activity is positively associated with insulin resistance and predicts incident type 2 diabetes among older adults independent of multiple factors associated with diabetes pathogenesis.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Insulin Resistance; Male; Middle Aged; Predictive Value of Tests; Prevalence; Prospective Studies; Risk; Risk Factors

Longitudinal changes in thyroid function in the oldest old and survival: the cardiovascular health study all-stars study. - Waring, Avantika C; Arnold, Alice M; Newman, Anne B; Bůzková, Petra; Hirsch, Calvin; Cappola, Anne R (J Clin Endocrinol Metab, 2012)
CONTEXT: Data on thyroid function in the oldest old are sparse, and existing studies show conflicting evidence on the relationship between thyroid function and mortality in this age group. OBJECTIVE: We describe longitudinal changes in thyroid function in a cohort of elderly individuals and determine the relationship between thyroid function and mortality. DESIGN, SETTING, AND PARTICIPANTS: Eight hundred forty-three participants in the Cardiovascular Health Study All Stars Study who were not taking thyroid medications and had thyroid function testing in 2005-2006 (mean age 85 yr). MAIN OUTCOME MEASURE: Thyroid-stimulating hormone (TSH), free T(4) (FT4), total T(3), and thyroid peroxidase antibody status were measured in 1992-1993 and 2005-2006. Deaths were ascertained through February 2011. RESULTS: There was a statistically significant 13% increase in TSH, 1.7% increase in FT4, and 13% decrease in total T(3) over the 13-yr period. Two hundred eighty-seven deaths occurred over a median follow-up of 5.1 yr. There was no association between subclinical hypothyroidism[hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.66-1.43], TSH level (HR per milliunits per liter 0.94, 95% CI 0.88-1.01), or persistent thyroid peroxidase antibody positivity (HR 1.09, 95% CI 0.62-1.92), and death. However, FT4 was positively associated with death (HR per nanograms per deciliter 2.57, 95% CI 1.32-5.02). CONCLUSIONS: TSH increased over time in these older individuals. This elevation was not associated with increased or decreased mortality, although higher FT4 levels were associated with death. These findings raise concern for treatment of mild elevations of TSH in advanced age. Further studies are needed to determine the potential benefit of treating age-related changes in thyroid function.
Keywords: Aged, 80 and over; Female; Humans; Longitudinal Studies; Male; Thyroid Diseases; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Triiodothyronine

Long-term assessment of inflammation and healthy aging in late life: the Cardiovascular Health Study All Stars. - Jenny, Nancy S; French, Benjamin; Arnold, Alice M; Strotmeyer, Elsa S; Cushman, Mary; Chaves, Paulo H M; Ding, Jingzhong; Fried, Linda P; Kritchevsky, Stephen B; Rifkin, Dena E; Sarnak, Mark J; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Associations of inflammation with age-related pathologies are documented; however, it is not understood how changes in inflammation over time impact healthy aging. METHODS: We examined associations of long-term change in C-reactive protein (CRP) and interleukin-6 (IL-6) with concurrent onset of physical and cognitive impairment, subsequent cardiovascular disease (CVD), and mortality in 1,051 participants in the Cardiovascular Health Study All Stars Study. Biomarkers were measured in 1996-1997 and 2005-2006. RESULTS: In 2005-2006, median age was 84.9 years, 63% were women and 17% non-white; 21% had at least a doubling in CRP over time and 23% had at least a doubling in IL-6. Adjusting for demographics, CVD risk factors, and 1996-1997 CRP level, each doubling in CRP change over 9 years was associated with higher risk of physical or cognitive impairment (odds ratio 1.29; 95% confidence interval 1.15, 1.45). Results were similar for IL-6 (1.45; 1.20, 1.76). A doubling in IL-6 change over time, but not CRP, was associated with incident CVD events; hazard ratio (95% confidence interval) 1.34 (1.03, 1.75). Doubling in change in each biomarker was individually associated with mortality (CRP: 1.12 [1.03, 1.22]; IL-6 1.39 [1.16, 1.65]). In models containing both change and 2005-2006 level, only level was associated with CVD events and mortality. CONCLUSIONS: Although increases in inflammation markers over 9 years were associated with higher concurrent risk of functional impairment and subsequent CVD events and mortality, final levels of each biomarker appeared to be more important in determining risk of subsequent events than change over time.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Cognition; Cohort Studies; Cross-Sectional Studies; Female; Humans; Inflammation; Inflammation Mediators; Interleukin-6; Longitudinal Studies; Male; Risk Factors; Vermont

Markers of inflammation in prevalent and incident Parkinson's disease in the Cardiovascular Health Study. - Ton, Thanh G N; Jain, Samay; Biggs, Mary L; Thacker, Evan L; Strotmeyer, Elsa S; Boudreau, Robert; Newman, Anne B; Longstreth, W T; Checkoway, Harvey (Parkinsonism Relat Disord, 2012)
BACKGROUND: Studies demonstrate existence of inflammation in prevalent Parkinson's disease (PD). We assessed associations of baseline levels of inflammatory markers with prevalent PD at baseline (1989) and incident PD identified over 13 years of follow-up of the Cardiovascular Health Study. METHODS: Blood samples at baseline were measured for fibrinogen, interleukin-6, tumor necrosis factor-α, C-reactive protein, albumin, and white blood cells. The analysis included 60 prevalent and 154 incident PD cases. RESULTS: Risk of prevalent PD was significantly higher per doubling of IL-6 among women (odds ratio [OR]=1.5, 95% confidence interval [CI]: 1.0, 2.4) and WBC among men (OR: 2.4, 95% CI: 1.2, 4.9) in multivariate models. Risk of incident PD was not associated with higher levels of any biomarker after adjusting for age, smoking, African American race, and history of diabetes. Inverse associations with incident PD were observed per doubling of C-reactive protein (OR=0.9; 95% CI: 0.8, 1.0) and of fibrinogen among women (OR=0.4; 95% CI: 0.2, 0.8). CONCLUSIONS: Although inflammation exists in PD, it may not represent an etiologic factor. Our findings suggest the need for larger studies that measure inflammatory markers before PD onset.
Keywords: Aged; Aged, 80 and over; Albumins; Biomarkers; C-Reactive Protein; Enzyme-Linked Immunosorbent Assay; Female; Fibrinogen; Humans; Incidence; Inflammation; Interleukin-6; Leukocyte Count; Male; Parkinson Disease; Prevalence; Risk Factors; Tumor Necrosis Factor-alpha

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Persistence and remission of musculoskeletal pain in community-dwelling older adults: results from the cardiovascular health study. - Thielke, Stephen M; Whitson, Heather; Diehr, Paula; O'Hare, Ann; Kearney, Patricia M; Chaudhry, Sarwat I; Zakai, Neil A; Kim, Dae; Sekaran, Nishant; Sale, Joanna E M; Arnold, Alice M; Chaves, Paulo; et al. (J Am Geriatr Soc, 2012)
OBJECTIVES: To characterize longitudinal patterns of musculoskeletal pain in a community sample of older adults over a 6-year period and to identify factors associated with persistence of pain. DESIGN: Secondary analysis of the Cardiovascular Health Study. SETTING: Community-based cohort drawn from four U.S. counties. PARTICIPANTS: Five thousand ninety-three men and women aged 65 and older. MEASUREMENTS: Over a 6-year period, pain was assessed each year using a single question about the presence of pain in any bones or joints during the last year. If affirmative, participants were queried about pain in seven locations (hands, shoulders, neck, back, hips, knees, feet). Participants were categorized according to the percentage of time that pain was present and according to the intermittent or chronic pattern of pain. Factors associated with persistent pain during five remaining years of the study were identified. RESULTS: Over 6 years, 32% of participants reported pain for three or more consecutive years, and 32% reported pain intermittently. Of those who reported pain the first year, 54% were pain free at least once during the follow-up period. Most of the pain at specific body locations was intermittent. Factors associated with remission of pain over 5 years included older age, male sex, better self-rated health, not being obese, taking fewer medications, and having fewer depressive symptoms. Approximately half of those with pain reported fewer pain locations the following year. CONCLUSION: Musculoskeletal pain in older adults, despite high prevalence, is often intermittent. The findings refute the notion that pain is an inevitable, unremitting, or progressive consequence of aging.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Male; Musculoskeletal Pain; Remission Induction; Residence Characteristics

Predicting late-life disability and death by the rate of decline in physical performance measures. - Hirsch, Calvin Hayes; Bůzková, Petra; Robbins, John A; Patel, Kushang V; Newman, Anne B (Age Ageing, 2012)
BACKGROUND: the rate of performance decline may influence the risk of disability or death. METHODS: for 4,182 Cardiovascular Health Study participants, we used multinomial Poisson log-linear models to assess the contribution of physical performance in 1998-99, and the rate of performance change between 1992-93 and 1998-99, to the risk of death or disability in 2005-06 in three domains: mobility, upper-extremity function (UEF) and activities of daily living (ADL). We evaluated performance in finger-tapping, grip strength, stride length, gait speed and chair stands separately and together for each outcome, adjusting for age, gender, race and years of disability in that outcome between 1992-93 and 1998-99. RESULTS: participants' age averaged 79.4 in 1998-99; 1,901 died over 7 years. Compared with the lowest change quintile in stride length, the highest quintile had a 1.32 relative risk (RR) of ADL disability (95% CI: 1.16 -1.96) and a 1.27 RR of death (95% CI: 1.07 -1.51). The highest change quintile for grip strength increased the risk of ADL disability by 35% (95% CI: 1.13 -1.61) and death by 31% (95% CI: 1.16 -1.49), compared with the lowest quintile. The annual change in stride length and grip strength also predicted disability in mobility and UEF. CONCLUSION: performance trajectories independently predict death and disability.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Disability Evaluation; Disabled Persons; Female; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Linear Models; Male; Mobility Limitation; Mortality; Motor Skills; Predictive Value of Tests; Risk Assessment; Risk Factors; Survival Analysis; Time Factors; United States; Upper Extremity; Walking

Racial differences in risks for first cardiovascular events and noncardiovascular death: the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. - Feinstein, Matthew; Ning, Hongyan; Kang, Joseph; Bertoni, Alain; Carnethon, Mercedes; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: No studies have compared first cardiovascular disease (CVD) events and non-CVD death between races in a competing risks framework, which examines risks for numerous events simultaneously. METHODS AND RESULTS: We used competing Cox models to estimate hazards for first CVD events and non-CVD death within and between races in 3 multicenter, National Heart, Lung, and Blood Institute-sponsored cohorts. Of 14 569 Atherosclerosis Risk in Communities (ARIC) study participants aged 45 to 64 years with mean follow-up of 10.5 years, 11.6% had CVD and 5.0% had non-CVD death as first events; among 4237 Cardiovascular Health Study (CHS) study participants aged 65 to 84 years and followed for 8.5 years, these figures were 43.2% and 15.7%, respectively. Middle-aged blacks were significantly more likely than whites to experience any CVD as a first event; this disparity disappeared by older adulthood and after adjustment for CVD risk factors. The pattern of results was similar for Multi-Ethnic Study of Atherosclerosis (MESA) participants. Traditional Cox and competing risks models yielded different results for coronary heart disease risk. Black men appeared somewhat more likely than white men to experience coronary heart disease with use of a standard Cox model (hazard ratio 1.06; 95% CI 0.90, 1.26), whereas they appeared less likely than white men to have a first coronary heart disease event with use of a competing risks model (hazard ratio, 0.77; 95% CI, 0.60, 1.00). CONCLUSIONS: CVD affects blacks at an earlier age than whites; this may be attributable in part to elevated CVD risk factor levels among blacks. Racial disparities in first CVD incidence disappear by older adulthood. Competing risks analyses may yield somewhat different results than traditional Cox models and provide a complementary approach to examining risks for first CVD events.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Continental Population Groups; Ethnic Groups; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Residence Characteristics; Risk Factors

Retinal microvascular signs and disability in the Cardiovascular Health Study. - Kim, Dae Hyun; Chaves, Paulo H M; Newman, Anne B; Klein, Ronald; Sarnak, Mark J; Newton, Elizabeth; Strotmeyer, Elsa S; Burke, Gregory L; Lipsitz, Lewis A (Arch Ophthalmol, 2012)
OBJECTIVE: To study the associations of retinal microvascular changes, which are associated with systemic conditions and cognitive decline, with disability in performing activities of daily living (ADL). DESIGN: Prospective cohort study of 1487 community-dwelling participants in the Cardiovascular Health Study (mean age, 78 years) who were free of ADL disability and had available data on retinal signs and carotid intima-media thickness at the 1998-1999 visit. Main outcome measures were incident ADL disability, defined as self-reported difficulty in performing any ADL, by the presence of retinal signs and advanced carotid atherosclerosis, defined by carotid intima-media thickness in the 80th percentile or more or 25% or more stenosis, and potential mediation by cerebral microvascular disease on brain imaging or by executive dysfunction, slow gait, and depressive mood, which are symptoms of frontal subcortical dysfunction. RESULTS: During the median follow-up of 3.1 years (maximum, 7.8 years), participants with 2 or more retinal signs had a higher rate of disability than those with fewer than 2 retinal signs (10.1% vs 7.1%; adjusted hazard ratio, 1.45; 95% confidence interval, 1.24-1.69; P < .001). There was no evidence of interaction by advanced carotid atherosclerosis (P > .10). The association seemed to be partially mediated by executive dysfunction, slow gait, and depressive symptoms but not by cerebral microvascular disease on brain imaging. CONCLUSIONS: These results provide further support for the pathophysiologic and prognostic significance of microvascular disease in age-related disability. However, it remains to be determined how to best use retinal photography in clinical risk prediction.
Keywords: Activities of Daily Living; Aged; Carotid Artery Diseases; Cognition Disorders; Diagnostic Techniques, Ophthalmological; Disability Evaluation; Follow-Up Studies; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Microcirculation; Predictive Value of Tests; Prevalence; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Smoking

Slower gait, slower information processing and smaller prefrontal area in older adults. - Rosano, Caterina; Studenski, Stephanie A; Aizenstein, Howard J; Boudreau, Robert M; Longstreth, William T; Newman, Anne B (Age Ageing, 2012)
BACKGROUND: Slower gait in older adults is related to smaller volume of the prefrontal area (PFAv). The pathways underlying this association have not yet been explored. Understanding slowing gait could help improve function in older age. We examine whether the association between smaller PFAv and slower gait is explained by lower performance on numerous neuropsychological tests. HYPOTHESIS: We hypothesise that slower information processing explains this association, while tests of language or memory will not. METHODS: Data on brain imaging, neuropsychological tests (information processing speed, visuospatial attention, memory, language, mood) and time to walk 15 feet were obtained in 214 adults (73.3 years, 62% women) free from stroke and dementia. Covariates included central (white matter hyperintensities, vision) and peripheral contributors of gait (vibration sense, muscle strength, arthritis, body mass index), demographics (age, race, gender, education), as well as markers of prevalent vascular diseases (cardiovascular disease, diabetes and ankle arm index). RESULTS: In linear regression models, smaller PFAv was associated with slower time to walk independent of covariates. This association was no longer significant after adding information processing speed to the model. None of the other neuropsychological tests significantly attenuated this association. CONCLUSIONS: We conclude that smaller PFAv may contribute to slower gait through slower information processing. Future longitudinal studies are warranted to examine the casual relationship between focal brain atrophy with slowing in information processing and gait.
Keywords: Affect; Aged; Aged, 80 and over; Aging; Attention; Body Mass Index; Cross-Sectional Studies; Female; Gait Disorders, Neurologic; Geriatric Assessment; Humans; Male; Memory; Mental Disorders; Mental Processes; Muscle Strength; Neuroimaging; Neuropsychological Tests; Prefrontal Cortex; Prevalence; Walking

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Ultraconserved elements in the human genome: association and transmission analyses of highly constrained single-nucleotide polymorphisms. - Chiang, Charleston W K; Liu, Ching-Ti; Lettre, Guillaume; Lange, Leslie A; Jorgensen, Neal W; Keating, Brendan J; Vedantam, Sailaja; Nock, Nora L; Franceschini, Nora; Reiner, Alex P; Demerath, Ellen W; Boerwinkle, Eric; et al. (Genetics, 2012)
Ultraconserved elements in the human genome likely harbor important biological functions as they are dosage sensitive and are able to direct tissue-specific expression. Because they are under purifying selection, variants in these elements may have a lower frequency in the population but a higher likelihood of association with complex traits. We tested a set of highly constrained SNPs (hcSNPs) distributed genome-wide among ultraconserved and nearly ultraconserved elements for association with seven traits related to reproductive (age at natural menopause, number of children, age at first child, and age at last child) and overall [longevity, body mass index (BMI), and height] fitness. Using up to 24,047 European-American samples from the National Heart, Lung, and Blood Institute Candidate Gene Association Resource (CARe), we observed an excess of associations with BMI and height. In an independent replication panel the most strongly associated SNPs showed an 8.4-fold enrichment of associations at the nominal level, including three variants in previously identified loci and one in a locus (DENND1A) previously shown to be associated with polycystic ovary syndrome. Finally, using 1430 family trios, we showed that the transmissions from heterozygous parents to offspring of the derived alleles of rare (frequency ≤ 0.5%) hcSNPs are not biased, particularly after adjusting for the rates of genotype missingness and error in the data. The lack of transmission bias ruled out an immediately and strongly deleterious effect due to the rare derived alleles, consistent with the observation that mice homozygous for the deletion of ultraconserved elements showed no overt phenotype. Our study also illustrated the importance of carefully modeling potential technical confounders when analyzing genotype data of rare variants.
Keywords: Alleles; Animals; Body Height; Body Mass Index; Child; Conserved Sequence; Dogs; Evolution, Molecular; Female; Genetic Fitness; Genetic Variation; Genome, Human; Genotype; Humans; Inheritance Patterns; Male; Mice; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Rats; Reproduction; Young Adult

Use of stance time variability for predicting mobility disability in community-dwelling older persons: a prospective study. - Brach, Jennifer S; Wert, David; VanSwearingen, Jessie M; Newman, Anne B; Studenski, Stephanie A (J Geriatr Phys Ther, 2012)
BACKGROUND AND PURPOSE: Mobility disability is a serious and frequent adverse health outcome associated with aging. Early identification of individuals at risk for mobility disability is important if interventions to prevent disability are to be instituted. The objectives of this prospective study were to (1) determine the magnitude of stance time variability (STV) that discriminates individuals who currently have mobility disability (prevalent mobility disability) and (2) determine the magnitude of STV that predicts a new onset of mobility disability at 1 year (incident mobility disability). METHODS: A total of 552 community-dwelling older adults were evaluated as part of the Cardiovascular Health Study, a longitudinal cohort study. Stance time, in milliseconds, was determined from 2 passes on a 4-m computerized walkway at self-selected walking speed, and STV was defined as the standard deviation from approximately 12 individual steps. Mobility disability was defined as self-reported difficulty walking a one-half mile. Receiver operating characteristic (ROC) curves were plotted to determine an optimal cutoff value for STV for prevalent and incident mobility disability, and the area under the receiver operating characteristic curve (AUC) was computed. RESULTS: The optimal cutoff score for STV (maximizing sensitivity and specificity) for prevalent mobility disability was 0.037 seconds (sensitivity = 65%, specificity = 65%, AUC = 0.70) and for incident 1-year mobility disability was 0.034 seconds (sensitivity = 61%, specificity = 60%, AUC = 0.65). The use of likelihood ratios demonstrated a gradient of risk across values of STV, with mobility risk increasing as values of STV increased. DISCUSSION AND CONCLUSION: Values of STV may be useful in identifying older adults with mobility disability and at risk for future disability. We recommend the more conservative estimate for identifying risk, STV = 0.034 seconds, which maximizes the sensitivity and minimizes false negatives. The relatively modest values on the validity indices could possibly be improved by increasing the reliability of the measurement of STV. Clinicians should interpret the cutoff values liberally and use STV in conjunction with other measures until further work is completed to validate STV as an indicator of mobility disability.
Keywords: Aged; Aged, 80 and over; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Independent Living; Male; Mobility Limitation; Physical Therapy Modalities; Postural Balance; Prospective Studies; Reproducibility of Results

Adiposity and cognitive decline in the cardiovascular health study. - Luchsinger, José A; Biggs, Mary L; Kizer, Jorge R; Barzilay, Joshua; Fitzpatrick, Annette; Newman, Anne; Longstreth, William T; Lopez, Oscar; Siscovick, David; Kuller, Lewis (Neuroepidemiology, 2013)
BACKGROUND: Studies relating adiposity to cognition in the elderly show conflicting results, which may be explained by the choice of adiposity measures. Thus, we studied the longitudinal associations of different adiposity measures, fat mass by bioelectrical impedance analysis, body mass index (BMI) and waist circumference (WC), with cognitive performance in the Cardiovascular Health Study. METHODS: Cognitive performance was assessed with the modified Mini-Mental State Examination, the Digit Symbol Substitution Test, and a composite of both. We used linear mixed models to estimate rates of change in cognitive function scores associated with adiposity measured at baseline. RESULTS: The final sample was comprised of 2,681 women (57.9%) and 1,949 men (42.1%) aged 73 ± 5.2 and 73.9 ± 5.6 years, respectively. Adiposity was associated with slower cognitive decline in most analyses. Results were similar for fat mass, BMI and WC. Higher fat-free mass was also related to slower cognitive decline. Results were similar in analyses excluding persons with cancer, smokers, and persons with short follow-up, poor self-reported health, or persons with cardiovascular disease. CONCLUSIONS: Higher adiposity and higher fat-free mass in the elderly was related to better cognitive performance. This finding was not explained by confounding by preexisting conditions.
Keywords: Adiposity; Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cognition Disorders; Electric Impedance; Female; Humans; Male; Risk Factors; Waist Circumference; Waist-Hip Ratio

Association of functional polymorphism rs2231142 (Q141K) in the ABCG2 gene with serum uric acid and gout in 4 US populations: the PAGE Study. - Zhang, Lili; Spencer, Kylee L; Voruganti, V Saroja; Jorgensen, Neal W; Fornage, Myriam; Best, Lyle G; Brown-Gentry, Kristin D; Cole, Shelley A; Crawford, Dana C; Deelman, Ewa; Franceschini, Nora; Gaffo, Angelo L; et al. (Am J Epidemiol, 2013)
A loss-of-function mutation (Q141K, rs2231142) in the ATP-binding cassette, subfamily G, member 2 gene (ABCG2) has been shown to be associated with serum uric acid levels and gout in Asians, Europeans, and European and African Americans; however, less is known about these associations in other populations. Rs2231142 was genotyped in 22,734 European Americans, 9,720 African Americans, 3,849 Mexican Americans, and 3,550 American Indians in the Population Architecture using Genomics and Epidemiology (PAGE) Study (2008-2012). Rs2231142 was significantly associated with serum uric acid levels (P = 2.37 × 10(-67), P = 3.98 × 10(-5), P = 6.97 × 10(-9), and P = 5.33 × 10(-4) in European Americans, African Americans, Mexican Americans, and American Indians, respectively) and gout (P = 2.83 × 10(-10), P = 0.01, and P = 0.01 in European Americans, African Americans, and Mexican Americans, respectively). Overall, the T allele was associated with a 0.24-mg/dL increase in serum uric acid level (P = 1.37 × 10(-80)) and a 1.75-fold increase in the odds of gout (P = 1.09 × 10(-12)). The association between rs2231142 and serum uric acid was significantly stronger in men, postmenopausal women, and hormone therapy users compared with their counterparts. The association with gout was also significantly stronger in men than in women. These results highlight a possible role of sex hormones in the regulation of ABCG2 urate transporter and its potential implications for the prevention, diagnosis, and treatment of hyperuricemia and gout.
Keywords: Adult; African Americans; Age Distribution; ATP-Binding Cassette Transporters; Comorbidity; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Gout; Hormone Replacement Therapy; Humans; Indians, North American; Male; Mexican Americans; Middle Aged; Neoplasm Proteins; Polymorphism, Genetic; Postmenopause; Sex Distribution; United States; Uric Acid

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Association of heat shock proteins with all-cause mortality. - Broer, L; Demerath, E W; Garcia, M E; Homuth, G; Kaplan, R C; Lunetta, K L; Tanaka, T; Tranah, G J; Walter, S; Arnold, A M; Atzmon, G; Harris, T B; et al. (Age (Dordr), 2013)
Experimental mild heat shock is widely known as an intervention that results in extended longevity in various models along the evolutionary lineage. Heat shock proteins (HSPs) are highly upregulated immediately after a heat shock. The elevation in HSP levels was shown to inhibit stress-mediated cell death, and recent experiments indicate a highly versatile role for these proteins as inhibitors of programmed cell death. In this study, we examined common genetic variations in 31 genes encoding all members of the HSP70, small HSP, and heat shock factor (HSF) families for their association with all-cause mortality. Our discovery cohort was the Rotterdam study (RS1) containing 5,974 participants aged 55 years and older (3,174 deaths). We assessed 4,430 single nucleotide polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. After adjusting for multiple testing by permutation analysis, three SNPs showed evidence for association with all-cause mortality in RS1. These findings were followed in eight independent population-based cohorts, leading to a total of 25,007 participants (8,444 deaths). In the replication phase, only HSF2 (rs1416733) remained significantly associated with all-cause mortality. Rs1416733 is a known cis-eQTL for HSF2. Our findings suggest a role of HSF2 in all-cause mortality.
Keywords: Aged, 80 and over; Aging; Cause of Death; Forecasting; Genotype; Heat-Shock Proteins; Humans; Longevity; Promoter Regions, Genetic; Retrospective Studies; Transcription, Genetic; United States

Bidirectional relationship between cognitive function and pneumonia. - Shah, Faraaz Ali; Pike, Francis; Alvarez, Karina; Angus, Derek; Newman, Anne B; Lopez, Oscar; Tate, Judith; Kapur, Vishesh; Wilsdon, Anthony; Krishnan, Jerry A; Hansel, Nadia; Au, David; et al. (Am J Respir Crit Care Med, 2013)
RATIONALE: Relationships between chronic health conditions and acute infections remain poorly understood. Preclinical studies suggest crosstalk between nervous and immune systems. OBJECTIVES: To determine bidirectional relationships between cognition and pneumonia. METHODS: We conducted longitudinal analyses of a population-based cohort over 10 years. We determined whether changes in cognition increase risk of pneumonia hospitalization by trajectory analyses and joint modeling. We then determined whether pneumonia hospitalization increased risk of subsequent dementia using a Cox model with pneumonia as a time-varying covariate. MEASUREMENTS AND MAIN RESULTS: Of the 5,888 participants, 639 (10.9%) were hospitalized with pneumonia at least once. Most participants had normal cognition before pneumonia. Three cognition trajectories were identified: no, minimal, and severe rapid decline. A greater proportion of participants hospitalized with pneumonia were on trajectories of minimal or severe decline before occurrence of pneumonia compared with those never hospitalized with pneumonia (proportion with no, minimal, and severe decline were 67.1%, 22.8%, and 10.0% vs. 76.0%, 19.3%, and 4.6% for participants with and without pneumonia, respectively; P < 0.001). Small subclinical changes in cognition increased risk of pneumonia, even in those with normal cognition and physical function before pneumonia (β = -0.02; P < 0.001). Participants with pneumonia were subsequently at an increased risk of dementia (hazard ratio, 2.24 [95% confidence interval, 1.62-3.11]; P = 0.01). Associations were independent of demographics, health behaviors, other chronic conditions, and physical function. Bidirectional relationship did not vary based on severity of disease, and similar associations were noted for those with severe sepsis and other infections. CONCLUSIONS: A bidirectional relationship exists between pneumonia and cognition and may explain how a single episode of infection in well-appearing older individuals accelerates decline in chronic health conditions and loss of functional independence.
Keywords: Aged; Cognition Disorders; Dementia; Female; Hospitalization; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Pneumonia; Proportional Hazards Models; Risk Factors

Blood pressure components and decline in kidney function in community-living older adults: the Cardiovascular Health Study. - Rifkin, Dena E; Katz, Ronit; Chonchol, Michel; Shlipak, Michael G; Sarnak, Mark J; Fried, Linda F; Newman, Anne B; Siscovick, David S; Peralta, Carmen A (Am J Hypertens, 2013)
BACKGROUND: Although hypertension contributes to kidney dysfunction in the general population, the contributions of elevated systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure (PP) to kidney function decline in community-dwelling older adults are unknown. METHODS: We used linear and logistic regression to examine the separate and combined associations of SBP, DBP, and PP at baseline with kidney function decline among 4,365 older adults in the Cardiovascular Health Study. We used cystatin C to estimate glomerular filtration rate on 3 occasions over 7 years of follow-up. We defined rapid decline ≥ 3ml/min/year. RESULTS: Average age was 72.2 and mean (standard deviation) SBP, DBP, and PP were 135 (21), 71 (11), and 65 (18) mm Hg, respectively. SBP and PP, rather than DBP, were most significantly associated with kidney function decline. In adjusted linear models, each 10-mm Hg increment in SBP and PP was associated with 0.13ml/min/year (-0.19, -0.08, P < 0.001) and 0.15-ml/min/year faster decline (-0.21, -0.09, P < 0.001), respectively. Each 10-mm Hg increment in DBP was associated with a nonsignificant 0.10-ml/min/year faster decline (95% confidence interval, -0.20, 0.01). In adjusted logistic models, SBP had the strongest associations with rapid decline, with 14% increased hazard of rapid decline (95% confidence interval, 10% to 17%, P < 0.01) per 10mm Hg. In models combining BP components, only SBP consistently had independent associations with rapid decline. CONCLUSIONS: Our findings suggest that elevated BP, particularly SBP, contributes to declining kidney function in older adults.
Keywords: Aged; Blood Pressure; Cohort Studies; Cystatin C; Diastole; Disease Progression; Female; Glomerular Filtration Rate; Humans; Hypertension; Logistic Models; Longitudinal Studies; Male; Pulse; Renal Insufficiency, Chronic; Systole

Circulating 25-hydroxyvitamin D is associated with insulin resistance cross-sectionally but not longitudinally in older adults: The Cardiovascular Health Study. - Danziger, John; Biggs, Mary L; Niemi, Matt; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; de Boer, Ian H; Siscovick, David S; Kestenbaum, Bryan; Mukamal, Kenneth J (Metabolism, 2013)
BACKGROUND: Despite extensive study, the role of vitamin D in insulin resistance and secretion remains unclear. OBJECTIVE: To examine the cross-sectional and longitudinal relationships between 25-hydroxyvitamin D (25(OH)D) concentrations and indices of insulin resistance and secretion in older adults. METHODS AND RESULTS: Among 2134 participants of the Cardiovascular Health Study who were free from cardiovascular disease, we measured serum 25(OH)D concentrations in samples collected in 1992-1993. We examined insulin resistance and secretion using Homeostasis Model Assessment (HOMA) estimates cross-sectionally and among 1469 participants who had repeated HOMA measures four years later (1996-1997). In cross-sectional analysis, each 10 ng/mL increment in 25(OH)D concentration was associated with a 0.09 lower adjusted HOMA-IR [95% CI (-0.17, -0.02), p=0.01]. However, baseline 25(OH)D concentrations were not associated with change in HOMA-IR over 4 years of follow up (p=0.48). 25(OH)D concentrations were not associated with insulin secretion, as determined by HOMA-β, in either cross-sectional or longitudinal analysis. CONCLUSIONS: Circulating 25(OH)D concentrations are associated with lower insulin resistance in cross-sectional but not longitudinal analyses. Whether this reflects residual confounding in cross-sectional analyses or the short-term nature of the relationship between vitamin D and insulin sensitivity will require trials with repeated measures of these factors.
Keywords: Adiposity; Aged; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; Exercise; Female; Humans; Hydroxycholecalciferols; Inflammation; Insulin; Insulin Resistance; Longitudinal Studies; Male; Middle Aged; Obesity; Risk Factors; Surveys and Questionnaires

Common carotid intima-media thickness does not add to Framingham risk score in individuals with diabetes mellitus: the USE-IMT initiative. - den Ruijter, H M; Peters, S A E; Groenewegen, K A; Anderson, T J; Britton, A R; Dekker, J M; Engstrom, G; Eijkemans, M J; Evans, G W; de Graaf, J; Grobbee, D E; Hedblad, B; et al. (Diabetologia, 2013)
AIMS/HYPOTHESIS: The aim of this work was to investigate whether measurement of the mean common carotid intima-media thickness (CIMT) improves cardiovascular risk prediction in individuals with diabetes. METHODS: We performed a subanalysis among 4,220 individuals with diabetes in a large ongoing individual participant data meta-analysis involving 56,194 subjects from 17 population-based cohorts worldwide. We first refitted the risk factors of the Framingham heart risk score on the individuals without previous cardiovascular disease (baseline model) and then expanded this model with the mean common CIMT (CIMT model). The absolute 10 year risk for developing a myocardial infarction or stroke was estimated from both models. In individuals with diabetes we compared discrimination and calibration of the two models. Reclassification of individuals with diabetes was based on allocation to another cardiovascular risk category when mean common CIMT was added. RESULTS: During a median follow-up of 8.7 years, 684 first-time cardiovascular events occurred among the population with diabetes. The C statistic was 0.67 for the Framingham model and 0.68 for the CIMT model. The absolute 10 year risk for developing a myocardial infarction or stroke was 16% in both models. There was no net reclassification improvement with the addition of mean common CIMT (1.7%; 95% CI -1.8, 3.8). There were no differences in the results between men and women. CONCLUSIONS/INTERPRETATION: There is no improvement in risk prediction in individuals with diabetes when measurement of the mean common CIMT is added to the Framingham risk score. Therefore, this measurement is not recommended for improving individual cardiovascular risk stratification in individuals with diabetes.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Diabetes Mellitus; Humans; Myocardial Infarction; Risk Factors; Stroke

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Decline in health for older adults: five-year change in 13 key measures of standardized health. - Diehr, Paula H; Thielke, Stephen M; Newman, Anne B; Hirsch, Calvin; Tracy, Russell (J Gerontol A Biol Sci Med Sci, 2013)
BACKGROUND: The health of older adults declines over time, but there are many ways of measuring health. It is unclear whether all health measures decline at the same rate or whether some aspects of health are less sensitive to aging than others. METHODS: We compared the decline in 13 measures of physical, mental, and functional health from the Cardiovascular Health Study: hospitalization, bed days, cognition, extremity strength, feelings about life as a whole, satisfaction with the purpose of life, self-rated health, depression, digit symbol substitution test, grip strength, activities of daily living, instrumental activities of daily living, and gait speed. Each measure was standardized against self-rated health. We compared the 5-year change to see which of the 13 measures declined the fastest and the slowest. RESULTS: The 5-year change in standardized health varied from a decline of 12 points (out of 100) for hospitalization to a decline of 17 points for gait speed. In most comparisons, standardized health from hospitalization and bed days declined the least, whereas health measured by activities of daily living, instrumental activities of daily living, and gait speed declined the most. These rankings were independent of age, sex, mortality patterns, and the method of standardization. CONCLUSIONS: All of the health variables declined, on average, with advancing age, but at significantly different rates. Standardized measures of mental health, cognition, quality of life, and hospital utilization did not decline as fast as gait speed, activities of daily living, and instrumental activities of daily living. Public health interventions to address problems with gait speed, activities of daily living, and instrumental activities of daily living may help older adults to remain healthier in all dimensions.
Keywords: Activities of Daily Living; Aged; Aging; Cohort Studies; Female; Gait; Health Status; Health Status Indicators; Hospitalization; Humans; Longitudinal Studies; Male; Mental Health; Quality of Life; Self Report; United States

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Effects of smoking on the genetic risk of obesity: the population architecture using genomics and epidemiology study. - Fesinmeyer, Megan D; North, Kari E; Lim, Unhee; Bůzková, Petra; Crawford, Dana C; Haessler, Jeffrey; Gross, Myron D; Fowke, Jay H; Goodloe, Robert; Love, Shelley-Ann; Graff, Misa; Carlson, Christopher S; et al. (BMC Med Genet, 2013)
BACKGROUND: Although smoking behavior is known to affect body mass index (BMI), the potential for smoking to influence genetic associations with BMI is largely unexplored. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE)' Consortium, we investigated interaction between genetic risk factors associated with BMI and smoking for 10 single nucleotide polymorphisms (SNPs) previously identified in genome-wide association studies. We included 6 studies with a total of 56,466 subjects (16,750 African Americans (AA) and 39,716 European Americans (EA)). We assessed effect modification by testing an interaction term for each SNP and smoking (current vs. former/never) in the linear regression and by stratified analyses. RESULTS: We did not observe strong evidence for interactions and only observed two interactions with p-values <0.1: for rs6548238/TMEM18, the risk allele (C) was associated with BMI only among AA females who were former/never smokers (β = 0.018, p = 0.002), vs. current smokers (β = 0.001, p = 0.95, p(interaction) = 0.10). For rs9939609/FTO, the A allele was more strongly associated with BMI among current smoker EA females (β = 0.017, p = 3.5 x 10(-5)), vs. former/never smokers (β = 0.006, p = 0.05, p(interaction) = 0.08). CONCLUSIONS: These analyses provide limited evidence that smoking status may modify genetic effects of previously identified genetic risk factors for BMI. Larger studies are needed to follow up our results. CLINICAL TRIAL REGISTRATION: NCT00000611.
Keywords: Adolescent; Adult; African Americans; Aged; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Mass Index; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Smoking; Young Adult

Epidemiology and long-term clinical and biologic risk factors for pneumonia in community-dwelling older Americans: analysis of three cohorts. - Yende, Sachin; Alvarez, Karina; Loehr, Laura; Folsom, Aaron R; Newman, Anne B; Weissfeld, Lisa A; Wunderink, Richard G; Kritchevsky, Stephen B; Mukamal, Kenneth J; London, Stephanie J; Harris, Tamara B; Bauer, Doug C; et al. (Chest, 2013)
BACKGROUND: Preventing pneumonia requires better understanding of incidence, mortality, and long-term clinical and biologic risk factors, particularly in younger individuals. METHODS: This was a cohort study in three population-based cohorts of community-dwelling individuals. A derivation cohort (n = 16,260) was used to determine incidence and survival and develop a risk prediction model. The prediction model was validated in two cohorts (n = 8,495). The primary outcome was 10-year risk of pneumonia hospitalization. RESULTS: The crude and age-adjusted incidences of pneumonia were 6.71 and 9.43 cases/1,000 person-years (10-year risk was 6.15%). The 30-day and 1-year mortality were 16.5% and 31.5%. Although age was the most important risk factor (range of crude incidence rates, 1.69-39.13 cases/1,000 person-years for each 5-year increment from 45-85 years), 38% of pneumonia cases occurred in adults < 65 years of age. The 30-day and 1-year mortality were 12.5% and 25.7% in those < 65 years of age. Although most comorbidities were associated with higher risk of pneumonia, reduced lung function was the most important risk factor (relative risk = 6.61 for severe reduction based on FEV1 by spirometry). A clinical risk prediction model based on age, smoking, and lung function predicted 10-year risk (area under curve [AUC] = 0.77 and Hosmer-Lemeshow [HL] C statistic = 0.12). Model discrimination and calibration were similar in the internal validation cohort (AUC = 0.77; HL C statistic, 0.65) but lower in the external validation cohort (AUC = 0.62; HL C statistic, 0.45). The model also calibrated well in blacks and younger adults. C-reactive protein and IL-6 were associated with higher pneumonia risk but did not improve model performance. CONCLUSIONS: Pneumonia hospitalization is common and associated with high mortality, even in younger healthy adults. Long-term risk of pneumonia can be predicted in community-dwelling adults with a simple clinical risk prediction model.
Keywords: Age Factors; Aged; Aged, 80 and over; Community-Acquired Infections; Comorbidity; Female; Follow-Up Studies; Hospitalization; Humans; Incidence; Male; Middle Aged; Pneumonia; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors

Exome sequencing and genome-wide linkage analysis in 17 families illustrate the complex contribution of TTN truncating variants to dilated cardiomyopathy. - Norton, Nadine; Li, Duanxiang; Rampersaud, Evadnie; Morales, Ana; Martin, Eden R; Zuchner, Stephan; Guo, Shengru; Gonzalez, Michael; Hedges, Dale J; Robertson, Peggy D; Krumm, Niklas; Nickerson, Deborah A; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Familial dilated cardiomyopathy (DCM) is a genetically heterogeneous disease with >30 known genes. TTN truncating variants were recently implicated in a candidate gene study to cause 25% of familial and 18% of sporadic DCM cases. METHODS AND RESULTS- We used an unbiased genome-wide approach using both linkage analysis and variant filtering across the exome sequences of 48 individuals affected with DCM from 17 families to identify genetic cause. Linkage analysis ranked the TTN region as falling under the second highest genome-wide multipoint linkage peak, multipoint logarithm of odds, 1.59. We identified 6 TTN truncating variants carried by individuals affected with DCM in 7 of 17 DCM families (logarithm of odds, 2.99); 2 of these 7 families also had novel missense variants that segregated with disease. Two additional novel truncating TTN variants did not segregate with DCM. Nucleotide diversity at the TTN locus, including missense variants, was comparable with 5 other known DCM genes. The average number of missense variants in the exome sequences from the DCM cases or the ≈5400 cases from the Exome Sequencing Project was ≈23 per individual. The average number of TTN truncating variants in the Exome Sequencing Project was 0.014 per individual. We also identified a region (chr9q21.11-q22.31) with no known DCM genes with a maximum heterogeneity logarithm of odds score of 1.74. CONCLUSIONS- These data suggest that TTN truncating variants contribute to DCM cause. However, the lack of segregation of all identified TTN truncating variants illustrates the challenge of determining variant pathogenicity even with full exome sequencing.
Keywords: Adolescent; Adult; Aged; Cardiomyopathy, Dilated; Chromosomes, Human, Pair 9; Connectin; Exome; Female; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genome, Human; Humans; Male; Middle Aged; Muscle Proteins; Mutation, Missense; Odds Ratio; Pedigree; Protein Kinases; Sequence Analysis, DNA; Young Adult

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Generalization and dilution of association results from European GWAS in populations of non-European ancestry: the PAGE study. - Carlson, Christopher S; Matise, Tara C; North, Kari E; Haiman, Christopher A; Fesinmeyer, Megan D; Buyske, Steven; Schumacher, Fredrick R; Peters, Ulrike; Franceschini, Nora; Ritchie, Marylyn D; Duggan, David J; Spencer, Kylee L; et al. (PLoS Biol, 2013)
The vast majority of genome-wide association study (GWAS) findings reported to date are from populations with European Ancestry (EA), and it is not yet clear how broadly the genetic associations described will generalize to populations of diverse ancestry. The Population Architecture Using Genomics and Epidemiology (PAGE) study is a consortium of multi-ancestry, population-based studies formed with the objective of refining our understanding of the genetic architecture of common traits emerging from GWAS. In the present analysis of five common diseases and traits, including body mass index, type 2 diabetes, and lipid levels, we compare direction and magnitude of effects for GWAS-identified variants in multiple non-EA populations against EA findings. We demonstrate that, in all populations analyzed, a significant majority of GWAS-identified variants have allelic associations in the same direction as in EA, with none showing a statistically significant effect in the opposite direction, after adjustment for multiple testing. However, 25% of tagSNPs identified in EA GWAS have significantly different effect sizes in at least one non-EA population, and these differential effects were most frequent in African Americans where all differential effects were diluted toward the null. We demonstrate that differential LD between tagSNPs and functional variants within populations contributes significantly to dilute effect sizes in this population. Although most variants identified from GWAS in EA populations generalize to all non-EA populations assessed, genetic models derived from GWAS findings in EA may generate spurious results in non-EA populations due to differential effect sizes. Regardless of the origin of the differential effects, caution should be exercised in applying any genetic risk prediction model based on tagSNPs outside of the ancestry group in which it was derived. Models based directly on functional variation may generalize more robustly, but the identification of functional variants remains challenging.
Keywords: African Americans; Asian Americans; Body Mass Index; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Lipids; Metagenomics; Oceanic Ancestry Group; Polymorphism, Single Nucleotide

Genetic risk factors for BMI and obesity in an ethnically diverse population: results from the population architecture using genomics and epidemiology (PAGE) study. - Fesinmeyer, Megan D; North, Kari E; Ritchie, Marylyn D; Lim, Unhee; Franceschini, Nora; Wilkens, Lynne R; Gross, Myron D; Bůzková, Petra; Glenn, Kimberly; Quibrera, P Miguel; Fernandez-Rhodes, Lindsay; Li, Qiong; et al. (Obesity (Silver Spring), 2013)
OBJECTIVE: Several genome-wide association studies (GWAS) have demonstrated that common genetic variants contribute to obesity. However, studies of this complex trait have focused on ancestrally European populations, despite the high prevalence of obesity in some minority groups. DESIGN AND METHODS: As part of the "Population Architecture using Genomics and Epidemiology (PAGE)" Consortium, we investigated the association between 13 GWAS-identified single-nucleotide polymorphisms (SNPs) and BMI and obesity in 69,775 subjects, including 6,149 American Indians, 15,415 African-Americans, 2,438 East Asians, 7,346 Hispanics, 604 Pacific Islanders, and 37,823 European Americans. For the BMI-increasing allele of each SNP, we calculated β coefficients using linear regression (for BMI) and risk estimates using logistic regression (for obesity defined as BMI ≥ 30) followed by fixed-effects meta-analysis to combine results across PAGE sites. Analyses stratified by racial/ethnic group assumed an additive genetic model and were adjusted for age, sex, and current smoking. We defined "replicating SNPs" (in European Americans) and "generalizing SNPs" (in other racial/ethnic groups) as those associated with an allele frequency-specific increase in BMI. RESULTS: By this definition, we replicated 9/13 SNP associations (5 out of 8 loci) in European Americans. We also generalized 8/13 SNP associations (5/8 loci) in East Asians, 7/13 (5/8 loci) in African Americans, 6/13 (4/8 loci) in Hispanics, 5/8 in Pacific Islanders (5/8 loci), and 5/9 (4/8 loci) in American Indians. CONCLUSION: Linkage disequilibrium patterns suggest that tagSNPs selected for European Americans may not adequately tag causal variants in other ancestry groups. Accordingly, fine-mapping in large samples is needed to comprehensively explore these loci in diverse populations.
Keywords: Alleles; Body Mass Index; Ethnic Groups; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Metagenomics; Obesity; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Hemoglobin decline, function, and mortality in the elderly: the cardiovascular health study. - Zakai, Neil A; French, Benjamin; Arnold, Alice M; Newman, Anne B; Fried, Linda F; Robbins, John; Chaves, Paulo; Cushman, Mary (Am J Hematol, 2013)
While anemia is associated with poor functional and mortality outcomes in the elderly, the impact of hemoglobin decline is less studied. We evaluated the determinants and consequences of hemoglobin decline in 3,758 non-anemic participants from the Cardiovascular Health Study, a prospective cohort of community-dwelling elderly ≥65 years old at baseline and followed for up to 16 years. Hemoglobin was measured at baseline and 3 years later and anemia defined by World Health Organization (WHO) criteria. We modeled hemoglobin decline in two ways: (1) per each 1 g/dL decrease in hemoglobin and (2) development of anemia by the WHO criteria. Among participants without baseline anemia, hemoglobin decreased by 0.4 g/dL and 9% developed anemia over 3 years. Baseline increasing age, female sex, diabetes, and kidney disease predicted hemoglobin decline over 3 years. Baseline increasing age, being African-American, and kidney disease predicted anemia development over 3 years. Hemoglobin decline was associated with subsequent worse cognitive function in men and anemia development with subsequent worse cognitive function in women. Both anemia development (HR 1.39, 95% CI 1.15, 1.69) and hemoglobin decline (HR 1.11, 95% CI 1.04, 1.18 per 1 g/dL decrease) predicted subsequent mortality in men and women. Hemoglobin decreases identified a large group of elderly individuals at risk for subsequent adverse outcomes who would not be identified using the WHO anemia criteria. These data may allow clinicians to identify at-risk elderly individuals for early intervention to improve the quality and quantity of life.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Anemia; Diabetes Complications; Female; Follow-Up Studies; Hemoglobins; Humans; Kidney Diseases; Male; Prospective Studies; Quality of Life; Risk Factors; Sex Factors; Survival Rate; Time Factors; World Health Organization

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Hypertension and low HDL cholesterol were associated with reduced kidney function across the age spectrum: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Fried, Linda F; Newman, Anne B; Katz, Ronit; Satterfield, Suzanne; Harris, Tamara B; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Ann Epidemiol, 2013)
PURPOSE: To determine if the associations among established risk factors and reduced kidney function vary by age. METHODS: We pooled cross-sectional data from 14,788 nondiabetics aged 40 to 100 years in 4 studies: Cardiovascular Health Study, Health, Aging, and Body Composition Study, Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular End-Stage Disease cohort. RESULTS: Hypertension and low high-density lipoprotein (HDL) cholesterol were associated with reduced cystatin C-based estimated glomerular filtration rate (eGFR) across the age spectrum. In adjusted analyses, hypertension was associated with a 2.3 (95% confidence interval [CI], 0.1, 4.4), 5.1 (95% CI, 4.1, 6.1), and 6.9 (95% CI, 3.0, 10.4) mL/min/1.73 m(2) lower eGFR in participants 40 to 59, 60 to 79, and at least 80 years, respectively (P for interaction < .001). The association of low HDL cholesterol with reduced kidney function was also greater in the older age groups: 4.9 (95% CI, 3.5, 6.3), 7.1 (95% CI, 6.0, 8.3), 8.9 (95% CI, 5.4, 11.9) mL/min/1.73 m(2) (P for interaction < .001). Smoking and obesity were associated with reduced kidney function in participants under 80 years. All estimates of the potential population impact of the risk factors were modest. CONCLUSIONS: Hypertension, obesity, smoking, and low HDL cholesterol are modestly associated with reduced kidney function in nondiabetics. The associations of hypertension and HDL cholesterol with reduced kidney function seem to be stronger in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Causality; Cholesterol, LDL; Cohort Studies; Comorbidity; Cross-Sectional Studies; Cystatin C; Female; Humans; Hypertension; Kidney Function Tests; Male; Netherlands; Obesity; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Smoking; United States

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

The influence of obesity-related single nucleotide polymorphisms on BMI across the life course: the PAGE study. - Graff, Mariaelisa; Gordon-Larsen, Penny; Lim, Unhee; Fowke, Jay H; Love, Shelly-Ann; Fesinmeyer, Megan; Wilkens, Lynne R; Vertilus, Shawyntee; Ritchie, Marilyn D; Prentice, Ross L; Pankow, Jim; Monroe, Kristine; et al. (Diabetes, 2013)
Evidence is limited as to whether heritable risk of obesity varies throughout adulthood. Among >34,000 European Americans, aged 18-100 years, from multiple U.S. studies in the Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we examined evidence for heterogeneity in the associations of five established obesity risk variants (near FTO, GNPDA2, MTCH2, TMEM18, and NEGR1) with BMI across four distinct epochs of adulthood: 1) young adulthood (ages 18-25 years), adulthood (ages 26-49 years), middle-age adulthood (ages 50-69 years), and older adulthood (ages ≥70 years); or 2) by menopausal status in women and stratification by age 50 years in men. Summary-effect estimates from each meta-analysis were compared for heterogeneity across the life epochs. We found heterogeneity in the association of the FTO (rs8050136) variant with BMI across the four adulthood epochs (P = 0.0006), with larger effects in young adults relative to older adults (β [SE] = 1.17 [0.45] vs. 0.09 [0.09] kg/m², respectively, per A allele) and smaller intermediate effects. We found no evidence for heterogeneity in the association of GNPDA2, MTCH2, TMEM18, and NEGR1 with BMI across adulthood. Genetic predisposition to obesity may have greater effects on body weight in young compared with older adulthood for FTO, suggesting changes by age, generation, or secular trends. Future research should compare and contrast our findings with results using longitudinal data.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Body Mass Index; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Genetic Association Studies; Health Surveys; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; United States; Young Adult

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Kidney function and prevalent and incident frailty. - Dalrymple, Lorien S; Katz, Ronit; Rifkin, Dena E; Siscovick, David; Newman, Anne B; Fried, Linda F; Sarnak, Mark J; Odden, Michelle C; Shlipak, Michael G (Clin J Am Soc Nephrol, 2013)
BACKGROUND AND OBJECTIVES: Kidney disease is associated with physiologic changes that may predispose to frailty. This study sought to investigate whether lower levels of kidney function were associated with prevalent or incident frailty in Cardiovascular Health Study (CHS) participants. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: CHS enrolled community-dwelling adults age ≥65 years between 1989-1990 and 1992-1993. To examine prevalent frailty, included were 4150 participants without stroke, Parkinson disease, prescribed medications for Alzheimer disease or depression, or severely impaired cognition. To examine incident frailty, included were a subset of 3459 participants without baseline frailty or development of exclusion criteria during follow-up. The primary predictor was estimated GFR (eGFR) calculated using serum cystatin C (eGFR(cys)). Secondary analyses examined eGFR using serum creatinine (eGFR(SCr)). Outcomes were prevalent frailty and incident frailty at 4 years of follow-up. Frailty was ascertained on the basis of weight loss, exhaustion, weakness, slowness, and low physical activity. RESULTS: The mean age was 75 years and the median eGFR(cys) was 73 ml/min per 1.73 m(2). Among participants with an eGFR(cys) <45 ml/min per 1.73 m(2), 24% had prevalent frailty. In multivariable analysis and compared with eGFR(cys) ≥90 ml/min per 1.73 m(2), eGFR(cys) categories of 45-59 (odds ratio [OR], 1.80; 95% confidence interval [CI], 1.17 to 2.75) and 15-44 (OR, 2.87; 95% CI, 1.72 to 4.77) were associated with higher odds of frailty, whereas 60-75 (OR, 1.14; 95% CI, 0.76 to 1.70) was not. In multivariable analysis, eGFR(cys) categories of 60-75 (incidence rate ratio [IRR], 1.72; 95% CI, 1.07 to 2.75) and 15-44 (IRR, 2.28; 95% CI, 1.23 to 4.22) were associated with higher incidence of frailty whereas 45-59 (IRR, 1.53; 95% CI, 0.90 to 2.60) was not. Lower levels of eGFR(SCr) were not associated with higher risk of prevalent or incident frailty. CONCLUSIONS: In community-dwelling elders, lower eGFR(cys) was associated with a higher risk of prevalent and incident frailty whereas lower eGFR(SCr) was not. These findings highlight the importance of considering non-GFR determinants of kidney function.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; Creatinine; Cross-Sectional Studies; Cystatin C; Fatigue; Female; Frail Elderly; Geriatric Assessment; Glomerular Filtration Rate; Humans; Incidence; Independent Living; Kidney; Kidney Diseases; Logistic Models; Male; Motor Activity; Multivariate Analysis; Muscle Weakness; Odds Ratio; Phenotype; Prevalence; Prospective Studies; Risk Factors; Time Factors; United States; Weight Loss

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Lifetime risk for heart failure among white and black Americans: cardiovascular lifetime risk pooling project. - Huffman, Mark D; Berry, Jarett D; Ning, Hongyan; Dyer, Alan R; Garside, Daniel B; Cai, Xuan; Daviglus, Martha L; Lloyd-Jones, Donald M (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to estimate lifetime risk for heart failure (HF) by sex and race. BACKGROUND: Prior estimates of lifetime risk for developing HF range from 20% to 33% in predominantly white cohorts. Short-term risks for HF appear higher for blacks than whites, but only limited comparisons of lifetime risk for HF have been made. METHODS: Using public-release and internal datasets from National Heart, Lung, and Blood Institute-sponsored cohorts, we estimated lifetime risks for developing HF to age 95 years, with death free of HF as the competing event, among participants in the CHA (Chicago Heart Association Detection Project in Industry), ARIC (Atherosclerosis Risk in Communities), and CHS (Cardiovascular Health Study) cohorts. RESULTS: There were 39,578 participants (33,652 [85%] white; 5,926 [15%] black) followed for 716,976 person-years; 5,983 participants developed HF. At age 45 years, lifetime risks for HF through age 95 years in CHA and CHS were 30% to 42% in white men, 20% to 29% in black men, 32% to 39% in white women, and 24% to 46% in black women. Results for ARIC demonstrated similar lifetime risks for HF in blacks and whites through age 75 years (limit of follow-up). Lifetime risk for HF was higher with higher blood pressure and body mass index at all ages in both blacks and whites, and did not diminish substantially with advancing index age. CONCLUSIONS: These are among the first data to compare lifetime risks for HF between blacks and whites. Lifetime risks for HF are high and appear similar for black and white women, yet are somewhat lower for black compared with white men due to competing risks.
Keywords: Adolescent; Adult; African Americans; Age Factors; Aged; Anthropometry; Body Mass Index; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Health Surveys; Heart Failure; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Predictive Value of Tests; Prognosis; Risk Assessment; Severity of Illness Index; Sex Factors; Survival Analysis; Time Factors; United States; Young Adult

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies. - Smith, C E; Ngwa, J; Tanaka, T; Qi, Q; Wojczynski, M K; Lemaitre, R N; Anderson, J S; Manichaikul, A; Mikkilä, V; van Rooij, F J A; Ye, Z; Bandinelli, S; et al. (Int J Obes (Lond), 2013)
OBJECTIVE: Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS: We conducted race/ethnic-specific meta-analyses using data from 14 studies of US and European whites and 4 of African Americans to evaluate associations of dietary fatty acids and LRP1 genotypes with body mass index (BMI), waist circumference and hip circumference, as well as interactions between dietary fatty acids and LRP1 genotypes. Seven single-nucleotide polymorphisms (SNPs) of LRP1 were evaluated in whites (N up to 42 000) and twelve SNPs in African Americans (N up to 5800). RESULTS: After adjustment for age, sex and population substructure if relevant, for each one unit greater intake of percentage of energy from saturated fat (SFA), BMI was 0.104 kg m(-2) greater, waist was 0.305 cm larger and hip was 0.168 cm larger (all P<0.0001). Other fatty acids were not associated with outcomes. The association of SFA with outcomes varied by genotype at rs2306692 (genotyped in four studies of whites), where the magnitude of the association of SFA intake with each outcome was greater per additional copy of the T allele: 0.107 kg m(-2) greater for BMI (interaction P=0.0001), 0.267 cm for waist (interaction P=0.001) and 0.21 cm for hip (interaction P=0.001). No other significant interactions were observed. CONCLUSION: Dietary SFA and LRP1 genotype may interactively influence anthropometric traits. Further exploration of this, and other diet x genotype interactions, may improve understanding of interindividual variability in the relationships of dietary factors with anthropometric traits.
Keywords: Adipose Tissue; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Body Mass Index; Europe; European Continental Ancestry Group; Fatty Acids; Female; Gene Frequency; Gene-Environment Interaction; Genetic Predisposition to Disease; Genotype; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Obesity; Phenotype; Polymorphism, Single Nucleotide; Prevalence; United States

Long-term survival in adults 65 years and older with white matter hyperintensity: association with performance on the digit symbol substitution test. - Rosano, Caterina; Chang, Yue-Fang; Kuller, Lewis H; Guralnik, Jack M; Studenski, Stephanie A; Aizenstein, Howard J; Gianaros, Peter J; Lopez, Oscar L; Longstreth, William T; Newman, Anne B (Psychosom Med, 2013)
OBJECTIVE: White matter hyperintensity (WMH) confers increased mortality risk in patients with cardiovascular diseases. However, little is known about differences in survival times among adults 65 years and older who have WMH and live in the community. To characterize the factors that may reduce mortality risk in the presence of WMH, measures of race, sex, apolipoprotein E4, neuroimaging, and cardiometabolic, physiological, and psychosocial characteristics were examined, with a particular focus on information processing as measured by the Digit Symbol Substitution Test (DSST). METHODS: Cox proportional models were used to estimate mortality risks in a cohort of 3513 adults (74.8 years, 58% women, 84% white) with WMH (0-9 points), DSST (0-90 points), risk factor assessment in 1992 to 1994, and data on mortality and incident stroke in 2009 (median follow-up [range] = 14.2 [0.5-18.1] years). RESULTS: WMH predicted a 48% greater mortality risk (age-adjusted hazard ratio [HR; 95% confidence interval CI] for WMH >3 points = 1.48 [1.35-1.62]). This association was attenuated after adjustment for DSST (HR [CI] = 1.38 [1.27-1.51]) or lacunar infarcts (HR [CI] = 1.37 [1.25,1.50]) but not after adjustment for other factors. The interaction between DSST and WMH was significant (p = .011). In fully adjusted models stratified by WMH of 3 or higher, participants with DSST greater than or equal to median had a 34% lower mortality risk among those with WMH of 3 or higher (n = 532/1217) and a 28% lower mortality risk among those with WMH lower than 3 (n = 1364/2296), compared with participants with DSST less than median (HR [95% CI] = 0.66 [0.55-0.81] and 0.72 [0.62-0.83], respectively). CONCLUSIONS: WMH is associated with increased long-term mortality risk in community-dwelling adults 65 years and older. The increased risk is attenuated for those with higher DSST. Assessment of cognitive function with DSST may improve risk stratification of individuals with WMH.
Keywords: Aged; Apolipoprotein E4; Biomarkers; Brain; Cardiovascular Diseases; Epidemiologic Methods; Female; Humans; Life Style; Magnetic Resonance Imaging; Male; Neuroimaging; Neuropsychological Tests; Reaction Time; Sex Factors; Stroke; Survivors

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Hum Genet, 2013)
Genome-wide association studies (GWAS) have identified many variants that influence high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and/or triglycerides. However, environmental modifiers, such as smoking, of these known genotype-phenotype associations are just recently emerging in the literature. We have tested for interactions between smoking and 49 GWAS-identified variants in over 41,000 racially/ethnically diverse samples with lipid levels from the Population Architecture Using Genomics and Epidemiology (PAGE) study. Despite their biological plausibility, we were unable to detect significant SNP × smoking interactions.
Keywords: Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Gene-Environment Interaction; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide; Prevalence; Smoking; Triglycerides; Young Adult

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

The QT interval and risk of incident atrial fibrillation. - Mandyam, Mala C; Soliman, Elsayed Z; Alonso, Alvaro; Dewland, Thomas A; Heckbert, Susan R; Vittinghoff, Eric; Cummings, Steven R; Ellinor, Patrick T; Chaitman, Bernard R; Stocke, Karen; Applegate, William B; Arking, Dan E; et al. (Heart Rhythm, 2013)
BACKGROUND: Abnormal atrial repolarization is important in the development of atrial fibrillation (AF), but no direct measurement is available in clinical medicine. OBJECTIVE: To determine whether the QT interval, a marker of ventricular repolarization, could be used to predict incident AF. METHODS: We examined a prolonged QT interval corrected by using the Framingham formula (QT(Fram)) as a predictor of incident AF in the Atherosclerosis Risk in Communities (ARIC) study. The Cardiovascular Health Study (CHS) and Health, Aging, and Body Composition (ABC) study were used for validation. Secondary predictors included QT duration as a continuous variable, a short QT interval, and QT intervals corrected by using other formulas. RESULTS: Among 14,538 ARIC study participants, a prolonged QT(Fram) predicted a roughly 2-fold increased risk of AF (hazard ratio [HR] 2.05; 95% confidence interval [CI] 1.42-2.96; P < .001). No substantive attenuation was observed after adjustment for age, race, sex, study center, body mass index, hypertension, diabetes, coronary disease, and heart failure. The findings were validated in Cardiovascular Health Study and Health, Aging, and Body Composition study and were similar across various QT correction methods. Also in the ARIC study, each 10-ms increase in QT(Fram) was associated with an increased unadjusted (HR 1.14; 95% CI 1.10-1.17; P < .001) and adjusted (HR 1.11; 95% CI 1.07-1.14; P < .001) risk of AF. Findings regarding a short QT interval were inconsistent across cohorts. CONCLUSIONS: A prolonged QT interval is associated with an increased risk of incident AF.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Humans; Incidence; Long QT Syndrome; Male; Middle Aged; Risk Factors

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Results differ by applying distinctive multiple imputation approaches on the longitudinal cardiovascular health study data. - Ning, Yuming; McAvay, Gail; Chaudhry, Sarwat I; Arnold, Alice M; Allore, Heather G (Exp Aging Res, 2013)
UNLABELLED: BACKGROUND/STUDY CONTEXT: The objective of this study was to examine sequential and simultaneous approaches to multiple imputation of missing data in a longitudinal data set where losses due to death were common. METHODS: Comparison of results from analyses and simulations of time to incident difficulty of activities of daily living (ADL) in the Cardiovascular Health Study when missing data were imputed simultaneously or sequentially. RESULTS: Results differed with imputation methods. The largest proportional differences in 12 risk factor parameter estimates were heart failure by 106%, social support by 33%, and arthritis by 27%. CONCLUSION: Decedents' final characteristics were influential on future imputations of those with missing values.
Keywords: Activities of Daily Living; Aged; Arthritis; Cardiac Rehabilitation; Cardiovascular Diseases; Data Interpretation, Statistical; Female; Humans; Longitudinal Studies; Male; Outcome Assessment (Health Care); Regression Analysis; Social Support

Risk factors for hospital admission among older persons with newly diagnosed heart failure: findings from the Cardiovascular Health Study. - Chaudhry, Sarwat I; McAvay, Gail; Chen, Shu; Whitson, Heather; Newman, Anne B; Krumholz, Harlan M; Gill, Thomas M (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to identify risk factors for the occurrence of all-cause hospital admissions among older persons after heart failure diagnosis, and to determine whether geriatric conditions would emerge as independent risk factors for admission when evaluated in the context of other relevant clinical data. BACKGROUND: Efforts to reduce costs in heart failure have focused on hospital utilization, yet few studies have examined how geriatric conditions affect the long-term risk for hospital admission after heart failure diagnosis. With the aging of the population with heart failure, geriatric conditions such as slow gait and muscle weakness are becoming increasingly common. METHODS: The study population included participants with a new diagnosis of heart failure in the Cardiovascular Health Study, a longitudinal study of community-living older persons. Data were collected through annual examinations and medical-record reviews. Geriatric conditions assessed were slow gait, muscle weakness (defined as weak grip), cognitive impairment, and depressive symptoms. Anderson-Gill regression modeling was used to determine the predictors of hospital admission after heart failure diagnosis. RESULTS: Of the 758 participants with a new diagnosis of heart failure, the mean rate of hospital admission was 7.9 per 10 person-years (95% CI: 7.4 to 8.4). Independent risk factors for hospital admission included diabetes mellitus (HR: 1.36; 95% CI: 1.13 to 1.64), New York Heart Association functional class III or IV (HR: 1.32; 95% CI: 1.11 to 1.57), chronic kidney disease (HR: 1.32; 95% CI: 1.14 to 1.53), slow gait (HR: 1.28; 95% CI: 1.06 to 1.55), depressed ejection fraction (HR: 1.25; 95% CI: 1.04 to 1.51), depression (HR: 1.23; 95% CI: 1.05 to 1.45), and muscle weakness (HR: 1.19; 95% CI: 1.00 to 1.42). CONCLUSIONS: Geriatric conditions are important, and potentially modifiable, risk factors for hospital admission in heart failure that should be routinely assessed at the time of heart failure diagnosis.
Keywords: Age Factors; Aged; Aged, 80 and over; Comorbidity; Effect Modifier, Epidemiologic; Female; Geriatric Assessment; Health Surveys; Heart Failure; Hospitalization; Humans; Longitudinal Studies; Male; Mental Competency; Risk Assessment; Risk Factors; Severity of Illness Index; Stroke Volume; Time-to-Treatment; United States

Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls. - Simone, Benedetto; De Stefano, Valerio; Leoncini, Emanuele; Zacho, Jeppe; Martinelli, Ida; Emmerich, Joseph; Rossi, Elena; Folsom, Aaron R; Almawi, Wassim Y; Scarabin, Pierre Y; den Heijer, Martin; Cushman, Mary; et al. (Eur J Epidemiol, 2013)
Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden, FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95 % confidence intervals [CI]: 0.98-1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR = 4.22; 95 % CI: 3.35-5.32; and OR = 2.79;95 % CI: 2.25-3.46, respectively), in double heterozygotes (OR = 3.42; 95 %CI 1.64-7.13), and in homozygous FVL or PT20210A (OR = 11.45; 95 %CI: 6.79-19.29; and OR: 6.74 (CI 95 % 2.19-20.72), respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤ 45 years (p value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.
Keywords: Case-Control Studies; Factor V; Genetic Predisposition to Disease; Humans; Methylenetetrahydrofolate Reductase (NADPH2); Prothrombin; Risk Factors; Venous Thromboembolism

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Sleep and insulin-like growth factors in the Cardiovascular Health Study. - Shah, Neomi; Rice, Tom; Tracy, Daniel; Rohan, Thomas; Bůzková, Petra; Newman, Anne; Kaplan, Robert C (J Clin Sleep Med, 2013)
STUDY OBJECTIVES: Sleep and sleep disordered breathing (obstructive sleep apnea [OSA]) are known to affect the growth hormone/insulin-like growth factor (GH/IGF) axis. There are few relevant population studies in this area, particularly in the elderly. We conducted this study to investigate the relationship between sleep (architecture and OSA) and circulating IGF-I (insulin-like growth factor-1), IGFBP-1 (insulin-like growth factor binding protein-1), and IGFBP-3 (insulin-like growth factor binding protein-3) levels in an elderly population. DESIGN SETTING: Cross-sectional analysis of participants from the year 9 visit of the Cardiovascular Health Study (CHS) who were enrolled in the Sleep Heart Health Study (SHHS). PATIENTS OR PARTICIPANTS: 1,233 elderly participants from the CHS and SHHS. MEASUREMENTS AND RESULTS: The mean age of males (n = 526) and females (n = 697) was 77 years. The mean value of IGF-I (ng/mL) in males was 112.4 vs. 97.1 in females (p < 0.01). Mean IGFBP-1 and IGFBP-3 levels were higher in females than males (p < 0.01). As expected, slow wave sleep was better preserved in females compared to males (22% total sleep time vs. 9% total sleep time, p < 0.01). Furthermore, as expected, OSA (apneahypopnea index [AHI] ≥ 5/h) was more prevalent in males compared to females (60% vs. 46%, p < 0.01). Multivariable linear regression was used to determine the relationship between objective sleep parameters and circulating IGF-I, IGFBP-1, and IGFBP-3 levels, with adjustment for age, sex, race, BMI, diabetes, estrogen use, progestin use, and physical activity. We did not detect a significant association between slow wave sleep (SWS) (per 5 min) and IGF-I, IGFBP-1, and IGFBP-3 levels (ng/mL). We found no significant linear association between OSA (AHI ≥ 5/h) and IGF-I, IGFBP-1, and IGFBP-3 levels. Gender-stratification of the entire cohort did not alter these findings. Sensitivity analyses excluding diabetics revealed that moderate OSA (AHI ≥ 5 and < 15) is inversely associated with IGFBP-3 levels in women. Conclusions The relationship between SWS and GH/IGF system is not significant in the elderly. Furthermore, OSA does not appear to adversely influence the GH/IGF axis, as reported in younger individuals. Whether our study findings are due to diminished GH/IGF-I axis activity in elderly needs further investigation by replication in other large population based elderly cohorts.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Geriatric Assessment; Health Surveys; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Sex Distribution; Sleep; Sleep Apnea, Obstructive; Somatomedins; United States

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

Trans-ethnic fine-mapping of lipid loci identifies population-specific signals and allelic heterogeneity that increases the trait variance explained. - Wu, Ying; Waite, Lindsay L; Jackson, Anne U; Sheu, Wayne H-H; Buyske, Steven; Absher, Devin; Arnett, Donna K; Boerwinkle, Eric; Bonnycastle, Lori L; Carty, Cara L; Cheng, Iona; Cochran, Barbara; et al. (PLoS Genet, 2013)
Genome-wide association studies (GWAS) have identified ~100 loci associated with blood lipid levels, but much of the trait heritability remains unexplained, and at most loci the identities of the trait-influencing variants remain unknown. We conducted a trans-ethnic fine-mapping study at 18, 22, and 18 GWAS loci on the Metabochip for their association with triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), respectively, in individuals of African American (n = 6,832), East Asian (n = 9,449), and European (n = 10,829) ancestry. We aimed to identify the variants with strongest association at each locus, identify additional and population-specific signals, refine association signals, and assess the relative significance of previously described functional variants. Among the 58 loci, 33 exhibited evidence of association at P<1 × 10(-4) in at least one ancestry group. Sequential conditional analyses revealed that ten, nine, and four loci in African Americans, Europeans, and East Asians, respectively, exhibited two or more signals. At these loci, accounting for all signals led to a 1.3- to 1.8-fold increase in the explained phenotypic variance compared to the strongest signals. Distinct signals across ancestry groups were identified at PCSK9 and APOA5. Trans-ethnic analyses narrowed the signals to smaller sets of variants at GCKR, PPP1R3B, ABO, LCAT, and ABCA1. Of 27 variants reported previously to have functional effects, 74% exhibited the strongest association at the respective signal. In conclusion, trans-ethnic high-density genotyping and analysis confirm the presence of allelic heterogeneity, allow the identification of population-specific variants, and limit the number of candidate SNPs for functional studies.
Keywords: African Americans; Apolipoproteins A; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Proprotein Convertases; Serine Endopeptidases; Triglycerides

ADAM19 and HTR4 variants and pulmonary function: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - London, Stephanie J; Gao, Wei; Gharib, Sina A; Hancock, Dana B; Wilk, Jemma B; House, John S; Gibbs, Richard A; Muzny, Donna M; Lumley, Thomas; Franceschini, Nora; North, Kari E; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The pulmonary function measures of forced expiratory volume in 1 second (FEV1) and its ratio to forced vital capacity (FVC) are used in the diagnosis and monitoring of lung diseases and predict cardiovascular mortality in the general population. Genome-wide association studies (GWASs) have identified numerous loci associated with FEV1 and FEV1/FVC, but the causal variants remain uncertain. We hypothesized that novel or rare variants poorly tagged by GWASs may explain the significant associations between FEV1/FVC and 2 genes: ADAM19 and HTR4. METHODS AND RESULTS: We sequenced ADAM19 and its promoter region along with the ≈21-kb portion of HTR4 harboring GWAS single-nucleotide polymorphisms for pulmonary function and analyzed associations with FEV1/FVC among 3983 participants of European ancestry from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Meta-analysis of common variants in each region identified statistically significant associations (316 tests; P<1.58×10(-4)) with FEV1/FVC for 14 ADAM19 single-nucleotide polymorphisms and 24 HTR4 single-nucleotide polymorphisms. After conditioning on the sentinel GWASs hit in each gene (ADAM19 rs1422795, minor allele frequency=0.33 and HTR4 rs11168048, minor allele frequency=0.40], 1 single-nucleotide polymorphism remained statistically significant (ADAM19 rs13155908, minor allele frequency=0.12; P=1.56×10(-4)). Analysis of rare variants (minor allele frequency <1%) using sequence kernel association test did not identify associations with either region. CONCLUSIONS: Sequencing identified 1 common variant associated with FEV1/FVC independent of the sentinel ADAM19 GWAS hit and supports the original HTR4 GWAS findings. Rare variants do not seem to underlie GWAS associations with pulmonary function for common variants in ADAM19 and HTR4.
Keywords: ADAM Proteins; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Age- and sex-dependent upper reference limits for the high-sensitivity cardiac troponin T assay. - Gore, M Odette; Seliger, Stephen L; deFilippi, Christopher R; Nambi, Vijay; Christenson, Robert H; Hashim, Ibrahim A; Hoogeveen, Ron C; Ayers, Colby R; Sun, Wensheng; McGuire, Darren K; Ballantyne, Christie M; de Lemos, James A (J Am Coll Cardiol, 2014)
OBJECTIVES: The study sought to determine the 99th percentile upper reference limit for the high-sensitivity cardiac troponin T assay (hs-cTnT) in 3 large independent cohorts. BACKGROUND: The presently recommended 14 ng/l cut point for the diagnosis of myocardial infarction using the hs-cTnT assay was derived from small studies of presumably healthy individuals, with relatively little phenotypic characterization. METHODS: Data were included from 3 well-characterized population-based studies: the Dallas Heart Study (DHS), the Atherosclerosis Risk in Communities (ARIC) Study, and the Cardiovascular Health Study (CHS). Within each cohort, reference subcohorts were defined excluding individuals with recent hospitalization, overt cardiovascular disease, and kidney disease (subcohort 1), and further excluding those with subclinical structural heart disease (subcohort 2). Data were analyzed stratified by age, sex, and race. RESULTS: The 99th percentile values for the hs-cTnT assay in DHS, ARIC, and CHS were 18, 22, and 36 ng/l (subcohort 1) and 14, 21, and 28 ng/l (subcohort 2), respectively. These differences in 99th percentile values paralleled age differences across cohorts. Analyses within sex/age strata yielded similar results between cohorts. Within each cohort, 99th percentile values increased with age and were higher in men. More than 10% of men 65 to 74 years of age with no cardiovascular disease in our study had cardiac troponin T values above the current myocardial infarction threshold. CONCLUSIONS: Use of a uniform 14 ng/l cutoff for the hs-cTnT assay may lead to over-diagnosis of myocardial infarction, particularly in men and the elderly. Clinical validation is needed of new age- and sex-specific cutoff values for this assay.
Keywords: Adult; Age Factors; Aged; Biological Assay; Biomarkers; Blood Chemical Analysis; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Myocardial Infarction; Reference Values; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index; Sex Factors; Troponin T

Association Between 6-Minute Walk Test and All-Cause Mortality, Coronary Heart Disease-Specific Mortality, and Incident Coronary Heart Disease. - Yazdanyar, Ali; Aziz, Michael M; Enright, Paul L; Edmundowicz, Daniel; Boudreau, Robert; Sutton-Tyrell, Kim; Kuller, Lewis; Newman, Anne B (J Aging Health, 2014)
OBJECTIVE: To examine the association between 6-min walk test (6 MWT) performance and all-cause mortality, coronary heart disease mortality, and incident coronary heart disease in older adults. METHOD: We conducted a time-to-event analysis of 1,665 Cardiovascular Health Study participants without prevalent cardiovascular disease with a 6 MWT. RESULTS: During a mean follow-up of 8 years, there were 305 incident coronary heart disease events, and 504 deaths of which 100 were coronary heart disease-related deaths. The 6 MWT performance in the shortest two distance quintiles was associated with increased risk of all-cause mortality (290-338 m: hazard ratio [HR] = 1.7; 95% confidence interval [CI] = [1.2, 2.5]; <290 m: HR = 2.1; 95% CI = [1.4, 3.0]). The adjusted risk of coronary heart disease mortality incident events among those with a 6 MWT < 290 m was not significant. DISCUSSION: Performance on the 6 MWT is independently associated with all-cause mortality and is of prognostic utility in community-dwelling older adults.

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Brain imaging findings in elderly adults and years of life, healthy life, and able life over the ensuing 16 years: the Cardiovascular Health Study. - Longstreth, W T; Diehr, Paula H; Yee, Laura M; Newman, Anne B; Beauchamp, Norman J (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine whether elderly people with different patterns of magnetic resonance imaging (MRI) findings have different long-term outcomes. DESIGN: Longitudinal cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older were recruited (N = 5,888); 3,660 of these underwent MRI, and 3,230 without a stroke before MRI were included in these analyses. MEASUREMENTS: Cluster analysis of brain MRI findings was previously used to define five clusters: normal, atrophy, simple infarct, leukoaraiosis, and complex infarct. Participants were subsequently classified as healthy if they rated their health as excellent, very good, or good and as able if they did not report any limitations in activities of daily living (ADLs). Mean years of life (YoL), years of healthy life (YHL), and years of able life (YAL) were calculated over 16 years after the MRI and compared between clusters using unadjusted and adjusted regression analyses. RESULTS: Mean age of participants was 75.0. With 16 years of follow-up, mean YoL was 11.3; YHL, 8.0; and YAL, 8.4. Outcomes differed significantly between clusters. With or without adjustments, outcomes were all significantly better in the normal than complex infarct cluster. The three remaining clusters had intermediate results, significantly different from the normal and complex infarct clusters but not usually from one another. Over 16 years of follow-up, participants in the complex infarct cluster (n = 368) spent the largest percentage of their 8.4 years alive being sick (38%) and not able (38%). CONCLUSION: Findings on MRI scans in elderly adults are associated not only with long-term survival, but also with long-term self-rated health and limitation in ADLs. The combination of infarcts and leukoaraiosis carried the worst prognosis, presumably reflecting small vessel disease.
Keywords: Activities of Daily Living; Aged; Atrophy; Brain; Brain Infarction; Cohort Studies; Disability Evaluation; Female; Health Status; Humans; Leukoaraiosis; Longevity; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prognosis; Regression Analysis; United States

Common carotid intima-media thickness measurements do not improve cardiovascular risk prediction in individuals with elevated blood pressure: the USE-IMT collaboration. - Bots, Michiel L; Groenewegen, Karlijn A; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; Hedblad, Bo; Hofman, Albert; Holewijn, Suzanne; et al. (Hypertension, 2014)
Carotid intima-media thickness (CIMT) is a marker of cardiovascular risk. It is unclear whether measurement of mean common CIMT improves 10-year risk prediction of first-time myocardial infarction or stroke in individuals with elevated blood pressure. We performed an analysis among individuals with elevated blood pressure (i.e., a systolic blood pressure ≥140 mm Hg and a diastolic blood pressure ≥ 90 mm Hg) in USE-IMT, a large ongoing individual participant data meta-analysis. We refitted the risk factors of the Framingham Risk Score on asymptomatic individuals (baseline model) and expanded this model with mean common CIMT (CIMT model) measurements. From both models, 10-year risks to develop a myocardial infarction or stroke were estimated. In individuals with elevated blood pressure, we compared discrimination and calibration of the 2 models and calculated the net reclassification improvement (NRI). We included 17 254 individuals with elevated blood pressure from 16 studies. During a median follow-up of 9.9 years, 2014 first-time myocardial infarctions or strokes occurred. The C-statistics of the baseline and CIMT models were similar (0.73). NRI with the addition of mean common CIMT was small and not significant (1.4%; 95% confidence intervals, -1.1 to 3.7). In those at intermediate risk (n=5008, 10-year absolute risk of 10% to 20%), the NRI was 5.6% (95% confidence intervals, 1.6-10.4). There is no added value of measurement of mean common CIMT in individuals with elevated blood pressure for improving cardiovascular risk prediction. For those at intermediate risk, the addition of mean common CIMT to an existing cardiovascular risk score is small but statistically significant.
Keywords: Adult; Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Carotid Artery, Common; Carotid Intima-Media Thickness; Cohort Studies; Female; Humans; Hypertension; Male; Meta-Analysis as Topic; Middle Aged; Risk Assessment; Risk Factors

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Coronary heart disease risks associated with high levels of HDL cholesterol. - Wilkins, John T; Ning, Hongyan; Stone, Neil J; Criqui, Michael H; Zhao, Lihui; Greenland, Philip; Lloyd-Jones, Donald M (J Am Heart Assoc, 2014)
BACKGROUND: The association between high-density lipoprotein cholesterol (HDL-C) and coronary heart disease (CHD) events is not well described in individuals with very high levels of HDL-C (>80 mg/dL). METHODS AND RESULTS: Using pooled data from 6 community-based cohorts we examined CHD and total mortality risks across a broad range of HDL-C, including values in excess of 80 mg/dL. We used Cox proportional hazards models with penalized splines to assess multivariable, adjusted, sex-stratified associations of HDL-C with the hazard for CHD events and total mortality, using HDL-C 45 mg/dL and 55 mg/dL as the referent in men and women, respectively. Analyses included 11 515 men and 12 925 women yielding 307 245 person-years of follow-up. In men, the association between HDL-C and CHD events was inverse and linear across most HDL-C values; however at HDL-C values >90 mg/dL there was a plateau effect in the pattern of association. In women, the association between HDL-C and CHD events was inverse and linear across lower values of HDL-C, however at HDL-C values >75 mg/dL there were no further reductions in the hazard ratio point estimates for CHD. In unadjusted models there were increased total mortality risks in men with very high HDL-C, however mortality risks observed in participants with very high HDL-C were attenuated after adjustment for traditional risk factors. CONCLUSIONS: We did not observe further reductions in CHD risk with HDL-C values higher than 90 mg/dL in men and 75 mg/dL in women.
Keywords: Aged; Biomarkers; Cholesterol, HDL; Coronary Disease; Female; Humans; Linear Models; Male; Middle Aged; Multivariate Analysis; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Development and validation of a brief dementia screening indicator for primary care. - Barnes, Deborah E; Beiser, Alexa S; Lee, Anne; Langa, Kenneth M; Koyama, Alain; Preis, Sarah R; Neuhaus, John; McCammon, Ryan J; Yaffe, Kristine; Seshadri, Sudha; Haan, Mary N; Weir, David R (Alzheimers Dement, 2014)
BACKGROUND: Detection of "any cognitive impairment" is mandated as part of the Medicare annual wellness visit, but screening all patients may result in excessive false positives. METHODS: We developed and validated a brief Dementia Screening Indicator using data from four large, ongoing cohort studies (the Cardiovascular Health Study [CHS]; the Framingham Heart Study [FHS]; the Health and Retirement Study [HRS]; the Sacramento Area Latino Study on Aging [SALSA]) to help clinicians identify a subgroup of high-risk patients to target for cognitive screening. RESULTS: The final Dementia Screening Indicator included age (1 point/year; ages, 65-79 years), less than 12 years of education (9 points), stroke (6 points), diabetes mellitus (3 points), body mass index less than 18.5 kg/m(2) (8 points), requiring assistance with money or medications (10 points), and depressive symptoms (6 points). Accuracy was good across the cohorts (Harrell's C statistic: CHS, 0.68; FHS, 0.77; HRS, 0.76; SALSA, 0.78). CONCLUSIONS: The Dementia Screening Indicator is a simple tool that may be useful in primary care settings to identify high-risk patients to target for cognitive screening.
Keywords: Aged; Cohort Studies; Dementia; Female; Humans; Male; Mass Screening; Predictive Value of Tests; Primary Health Care; Proportional Hazards Models; Risk Assessment

Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. - Fowkes, F G R; Murray, G D; Butcher, I; Folsom, A R; Hirsch, A T; Couper, D J; deBacker, G; Kornitzer, M; Newman, A B; Sutton-Tyrrell, K C; Cushman, M; Lee, A J; et al. (Eur J Prev Cardiol, 2014)
BACKGROUND: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. DESIGN: An analysis of participant data from 18 cohorts in which 24,375 men and 20,377 women free of coronary heart disease had ABI measured and were followed up for events. METHODS: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. RESULTS: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. CONCLUSIONS: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.
Keywords: Adult; Aged; Aged, 80 and over; Ankle Brachial Index; Cardiovascular Diseases; Europe; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States; Young Adult

Do changes in circulating biomarkers track with each other and with functional changes in older adults? - Sanders, Jason L; Ding, Victoria; Arnold, Alice M; Kaplan, Robert C; Cappola, Anne R; Kizer, Jorge R; Boudreau, Robert M; Cushman, Mary; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: It is unclear if changes in proposed circulating biomarkers of aging are strongly correlated to each other or functional change. We tested if biomarker changes track with each other and with functional measures over 9 years in older adults. METHODS: Dehydroepiandrosterone sulfate (DHEAS), adiponectin, insulin-like growth factor 1 (IGF-1), IGF binding proteins 1 (IGFBP-1) and 3 (IGFBP-3), interleukin-6 (IL-6), cholesterol, and function (gait speed, grip strength, Modified Mini Mental Status Exam [3MSE] and Digit Symbol Substitution Test [DSST] scores) were measured in 1996-1997 and 2005-2006 in the Cardiovascular Health Study All Stars study (N = 901, mean [standard deviation, SD] age 85.3 [3.6] years in 2005-2006). Adjusted Pearson correlations illustrated if biomarkers tracked together. Multivariable linear regression demonstrated if biomarker changes tracked with functional changes. RESULTS: Correlations among biomarker changes were mostly <0.2. In models with each biomarker entered separately, a 1-SD increase biomarker change was associated with change in function as follows: grip strength (DHEAS β = 0.61kg, p = .001; IL-6 β = -0.46kg, p = .012; cholesterol men β = 0.79kg, p = .016); gait speed (DHEAS β = 0.02 meters per second, p = .039; IL-6 β = -0.018 meters per second, p = .049); and DSST score (DHEAS women β = 1.46, p = .004; IL-6 β = -0.83, p = .027). When biomarkers were entered in the same model, significant associations remaining were as follows: grip strength (DHEAS β = 0.54kg, p = .005; IL-6 β = -0.43kg, p = .022); 3MSE score (IGF-1 β = 0.96, p = .04; IGFBP-3 β = -1.07, p = .024); and DSST score (DHEAS women β = 1.27, p = .012; IL-6 β = -0.80, p = .04). CONCLUSION: Changes in biomarkers were poorly correlated, supporting a model of stochastic, independent change across systems. DHEAS and IL-6 tracked most closely with function, illustrating that changes in inflammation and sex steroids may play dominant roles in changes of these functional outcomes.
Keywords: Adiponectin; Aged; Aged, 80 and over; Aging; Biomarkers; Cholesterol; Cognition; Cohort Studies; Dehydroepiandrosterone Sulfate; Female; Gait; Hand Strength; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Interleukin-6; Male; Neuropsychological Tests; Psychomotor Performance; Time Factors

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Enhancing case ascertainment of Parkinson's disease using Medicare claims data in a population-based cohort: the Cardiovascular Health Study. - Ton, Thanh G N; Biggs, Mary Lou; Comer, Diane; Curtis, Lesley; Hu, Shu-Ching; Thacker, Evan L; Searles Nielsen, Susan; Delaney, Joseph A; Landsittel, Douglas; Longstreth, William T; Checkoway, Harvey; Jain, Samay (Pharmacoepidemiol Drug Saf, 2014)
PURPOSE: We sought to improve a previous algorithm to ascertain Parkinson's disease (PD) in the Cardiovascular Health Study by incorporating additional data from Medicare outpatient claims. We compared our results to the previous algorithm in terms of baseline prevalence and incidence of PD, as well as associations with baseline smoking characteristics. METHODS: Our original case ascertainment used self-reported diagnosis, antiparkinsonian medication, and hospitalization discharge International Classification of Diseases-Ninth version code. In this study, we incorporated additional data from fee-for-service Medicare claims, extended follow-up time, review of hospitalization records, and adjudicated cause of death. Two movement disorders specialists adjudicated final PD status. We used logistic regression models and controlled for age, sex, African American race, and education. RESULTS: We identified 75 additional cases but reclassified 80 previously identified cases as not having PD. We observed significant inverse association with smoking status (odds ratio = 0.42; 95% confidence interval (CI) = 0.22, 0.79), and inverse linear trends with pack-years (p = 0.005), and cigarettes per day (p = 0.019) with incident PD. All estimates were stronger than those from the previous algorithm. CONCLUSIONS: Our enhanced method did not alter prevalence and incidence estimates compared with our previous algorithm. However, our enhanced method provided stronger estimates of association, potentially due to reduced level of disease misclassification.
Keywords: Aged; Aged, 80 and over; Algorithms; Antiparkinson Agents; Cohort Studies; Databases, Factual; Female; Hospitalization; Humans; Incidence; Logistic Models; Male; Medicare; Parkinson Disease; Prevalence; Prospective Studies; Smoking; Time Factors; United States

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Extreme deep white matter hyperintensity volumes are associated with African American race. - Nyquist, Paul A; Bilgel, Murat S; Gottesman, Rebecca; Yanek, Lisa R; Moy, Taryn F; Becker, Lewis C; Cuzzocreo, Jennifer; Prince, Jerry; Yousem, David M; Becker, Diane M; Kral, Brian G; Vaidya, Dhananjay (Cerebrovasc Dis, 2014)
BACKGROUND: African Americans (AAs) have a higher prevalence of extreme ischemic white matter hyperintensities (WMHs) on magnetic resonance imaging (MRI) than do European Americans (EAs) based on the Cardiovascular Health Study (CHS) score. Ischemic white matter disease, limited to the deep white matter, may be biologically distinct from disease in other regions and may reflect a previously observed trend toward an increased risk of subcortical lacunar infarcts in AAs. We hypothesized that extreme deep WMH volume (DWMV) or periventricular volume (PV) may also have a higher prevalence in AAs. Thus, we studied extreme CHS scores and extreme DWMV and PV in a healthy population enriched for cardiovascular disease risk factors. METHODS: We imaged the brains of 593 subjects who were first-degree relatives of probands with early onset coronary disease prior to 60 years of age. WMHs were manually delineated on 3-tesla cranial MRI by a trained radiology reader; the location and volume of lesions were characterized using automated software. DWMV and PV were measured directly with automated software, and the CHS score was determined by a neuroradiologist. Volumes were characterized as being in the upper 25% versus lower 75% of total lesion volume. Volumes in the upper versus the remaining quartiles were examined for AA versus EA race using multiple logistic regression (generalized estimating equations adjusted for family relatedness) and adjusted for major vascular disease risk factors including age ≥55 years versus <55, sex, current smoking, obesity, hypertension, diabetes and low-density lipoprotein >160 mg/dl. RESULTS: Participants were 58% women and 37% AAs, with a mean age of 51.5 ± 11.0 years (range, 29-74 years). AAs had significantly higher odds of having extreme DWMVs (odds ratio, OR, 1.8; 95% confidence interval, CI, 1.2-2.9; p = 0.0076) independently of age, sex, hypertension and all other risk factors. AAs also had significantly higher odds of having extreme CHS scores ≥3 (OR, 1.3; 95% CI, 1.1-3.6; p = 0.025). Extreme PV was not significantly associated with AA race (OR, 1.3; 95% CI, 0.81-2.1; p = 0.26). CONCLUSIONS: AAs from families with early-onset cardiovascular disease are more likely to have extreme DWMVs (a subclinical form of cerebrovascular disease) and an extreme CHS score, but not extreme PV, independently of age and other cardiovascular disease risk factors. These findings suggest that this AA population is at an increased risk for DWMV and may be at an increased risk for future subcortical stroke. Longitudinal studies are required to see if DWMV is predictive of symptomatic subcortical strokes in this population.
Keywords: Adult; African Americans; Age Factors; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Prevalence; Risk Factors; White Matter

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gender and telomere length: systematic review and meta-analysis. - Gardner, Michael; Bann, David; Wiley, Laura; Cooper, Rachel; Hardy, Rebecca; Nitsch, Dorothea; Martin-Ruiz, Carmen; Shiels, Paul; Sayer, Avan Aihie; Barbieri, Michelangela; Bekaert, Sofie; Bischoff, Claus; et al. (Exp Gerontol, 2014)
BACKGROUND: It is widely believed that females have longer telomeres than males, although results from studies have been contradictory. METHODS: We carried out a systematic review and meta-analyses to test the hypothesis that in humans, females have longer telomeres than males and that this association becomes stronger with increasing age. Searches were conducted in EMBASE and MEDLINE (by November 2009) and additional datasets were obtained from study investigators. Eligible observational studies measured telomeres for both females and males of any age, had a minimum sample size of 100 and included participants not part of a diseased group. We calculated summary estimates using random-effects meta-analyses. Heterogeneity between studies was investigated using sub-group analysis and meta-regression. RESULTS: Meta-analyses from 36 cohorts (36,230 participants) showed that on average females had longer telomeres than males (standardised difference in telomere length between females and males 0.090, 95% CI 0.015, 0.166; age-adjusted). There was little evidence that these associations varied by age group (p=1.00) or cell type (p=0.29). However, the size of this difference did vary by measurement methods, with only Southern blot but neither real-time PCR nor Flow-FISH showing a significant difference. This difference was not associated with random measurement error. CONCLUSIONS: Telomere length is longer in females than males, although this difference was not universally found in studies that did not use Southern blot methods. Further research on explanations for the methodological differences is required.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Sex Factors; Telomere

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Genetic variants related to height and risk of atrial fibrillation: the cardiovascular health study. - Rosenberg, Michael A; Kaplan, Robert C; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Newton-Cheh, Christopher; Mukamal, Kenneth J (Am J Epidemiol, 2014)
Increased height is a known independent risk factor for atrial fibrillation (AF). However, whether genetic determinants of height influence risk is uncertain. In this candidate gene study, we examined the association of 209 height-associated single-nucleotide polymorphisms (SNPs) with incident AF in 3,309 persons of European descent from the Cardiovascular Health Study, a prospective cohort study of older adults (aged ≥ 65 years) enrolled in 1989-1990. After a median follow-up period of 13.2 years, 879 participants developed incident AF. The height-associated SNPs together explained approximately 10% of the variation in height (P = 6.0 × 10(-8)). Using an unweighted genetic height score, we found a nonsignificant association with risk of AF (per allele, hazard ratio = 1.01, 95% confidence interval: 1.00, 1.02; P = 0.06). In weighted analyses, we found that genetically predicted height was strongly associated with AF risk (per 10 cm, hazard ratio = 1.30, 95% confidence interval: 1.03, 1.64; P = 0.03). Importantly, for all models, the inclusion of actual height completely attenuated the genetic height effect. Finally, we identified 1 nonsynonymous SNP (rs1046934) that was independently associated with AF and may warrant future study. In conclusion, we found that genetic determinants of height appear to increase the risk of AF, primarily via height itself. This approach of examining SNPs associated with an intermediate phenotype should be considered as a method for identifying novel genetic targets.
Keywords: African Americans; Aged; Atrial Fibrillation; Body Height; Endonucleases; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Heritability of and mortality prediction with a longevity phenotype: the healthy aging index. - Sanders, Jason L; Minster, Ryan L; Barmada, M Michael; Matteini, Amy M; Boudreau, Robert M; Christensen, Kaare; Mayeux, Richard; Borecki, Ingrid B; Zhang, Qunyuan; Perls, Thomas; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Longevity-associated genes may modulate risk for age-related diseases and survival. The Healthy Aging Index (HAI) may be a subphenotype of longevity, which can be constructed in many studies for genetic analysis. We investigated the HAI's association with survival in the Cardiovascular Health Study and heritability in the Long Life Family Study. METHODS: The HAI includes systolic blood pressure, pulmonary vital capacity, creatinine, fasting glucose, and Modified Mini-Mental Status Examination score, each scored 0, 1, or 2 using approximate tertiles and summed from 0 (healthy) to 10 (unhealthy). In Cardiovascular Health Study, the association with mortality and accuracy predicting death were determined with Cox proportional hazards analysis and c-statistics, respectively. In Long Life Family Study, heritability was determined with a variance component-based family analysis using a polygenic model. RESULTS: Cardiovascular Health Study participants with unhealthier index scores (7-10) had 2.62-fold (95% confidence interval: 2.22, 3.10) greater mortality than participants with healthier scores (0-2). The HAI alone predicted death moderately well (c-statistic = 0.643, 95% confidence interval: 0.626, 0.661, p < .0001) and slightly worse than age alone (c-statistic = 0.700, 95% confidence interval: 0.684, 0.717, p < .0001; p < .0001 for comparison of c-statistics). Prediction increased significantly with adjustment for demographics, health behaviors, and clinical comorbidities (c-statistic = 0.780, 95% confidence interval: 0.765, 0.794, p < .0001). In Long Life Family Study, the heritability of the HAI was 0.295 (p < .0001) overall, 0.387 (p < .0001) in probands, and 0.238 (p = .0004) in offspring. CONCLUSION: The HAI should be investigated further as a candidate phenotype for uncovering longevity-associated genes in humans.
Keywords: Aged; Aging; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotype; Health Behavior; Humans; Longevity; Male; Phenotype; Retrospective Studies; Risk Factors; Survival Rate; United States

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12. - Kilarski, Laura L; Achterberg, Sefanja; Devan, William J; Traylor, Matthew; Malik, Rainer; Lindgren, Arne; Pare, Guillame; Sharma, Pankaj; Slowik, Agniesczka; Thijs, Vincent; Walters, Matthew; Worrall, Bradford B; et al. (Neurology, 2014)
OBJECTIVES: To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases. METHODS: Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a further 8,480 cases and 56,032 controls in the METASTROKE consortium. A final in silico "look-up" of 2 single nucleotide polymorphisms in 2,522 cases and 1,899 controls was performed. Associations were also examined in 1,088 cases with intracerebral hemorrhage and 1,102 controls. RESULTS: In an overall analysis of 17,970 cases of ischemic stroke and 70,764 controls, we identified a novel association on chromosome 12q24 (rs10744777, odds ratio [OR] 1.10 [1.07-1.13], p = 7.12 × 10(-11)) with ischemic stroke. The association was with all ischemic stroke rather than an individual stroke subtype, with similar effect sizes seen in different stroke subtypes. There was no association with intracerebral hemorrhage (OR 1.03 [0.90-1.17], p = 0.695). CONCLUSION: Our results show, for the first time, a genetic risk locus associated with ischemic stroke as a whole, rather than in a subtype-specific manner. This finding was not associated with intracerebral hemorrhage.
Keywords: Brain Ischemia; Cerebral Hemorrhage; Chromosomes, Human, Pair 12; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Meta-analysis of loci associated with age at natural menopause in African-American women. - Chen, Christina T L; Liu, Ching-Ti; Chen, Gary K; Andrews, Jeanette S; Arnold, Alice M; Dreyfus, Jill; Franceschini, Nora; Garcia, Melissa E; Kerr, Kathleen F; Li, Guo; Lohman, Kurt K; Musani, Solomon K; et al. (Hum Mol Genet, 2014)
Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis in 6510 women with African ancestry derived from 11 studies across the USA. We did not identify any additional loci significantly associated with age at menopause in African Americans. We replicated the associations between six loci and age at menopause (P-value < 0.05): AMHR2, RHBLD2, PRIM1, HK3/UMC1, BRSK1/TMEM150B and MCM8. In addition, associations of 14 loci are directionally consistent with previous reports. We provide evidence that genetic variants influencing reproductive traits identified in European populations are also important in women of African ancestry residing in USA.
Keywords: African Americans; Age Factors; Chromosomes, Human; European Continental Ancestry Group; Female; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Menopause; United States

Metabolic syndrome and risk of incident peripheral artery disease: the cardiovascular health study. - Garg, Parveen K; Biggs, Mary L; Carnethon, Mercedes; Ix, Joachim H; Criqui, Michael H; Britton, Kathryn A; Djoussé, Luc; Sutton-Tyrrell, Kim; Newman, Anne B; Cushman, Mary; Mukamal, Kenneth J (Hypertension, 2014)
Prior studies evaluating metabolic syndrome (MetS) and incident peripheral artery disease (PAD) have been limited by use of modified MetS criteria and restriction to clinical PAD end points. We investigated MetS and risk of developing a low ankle-brachial index (ABI) and clinical PAD in the Cardiovascular Health Study, a population-based cohort of adults aged ≥65 years. Participants with MetS met at least 3 of 5 Adult Treatment Panel III criteria. Baseline C-reactive protein-MetS or fibrinogen-MetS were defined as presence of 3 of 6 components, with elevated C-reactive protein (>3 mg/L) or fibrinogen (>341 mg/dL) as a sixth component. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among a subset of 1899 individuals with 2 ABI measurements 6 years apart. Over a median follow-up of 13.7 years, 4632 individuals were followed up for clinical PAD, defined as revascularization or diagnosed claudication. Adult Treatment Panel III MetS was associated with both incident low ABI (risk ratio, 1.26; 95% confidence interval [CI], 1.00-1.58) and clinical PAD (hazard ratio, 1.47; 95% CI, 1.11-1.94). Incorporating C-reactive protein or fibrinogen into Adult Treatment Panel III criteria identified an additional 16% to 20% of individuals as having MetS, and both C-reactive protein-MetS and fibrinogen-MetS were associated with incident low ABI (risk ratio, 1.36; 95% CI, 1.07-1.72 and risk ratio, 1.43; 95% CI, 1.13-1.81, respectively) and clinical PAD (hazard ratio, 1.56; 95% CI, 1.17-2.08 and hazard ratio, 1.55; 95% CI, 1.17-2.07, respectively). Among Adult Treatment Panel III MetS criteria, risk of PAD was most strongly associated with hypertension.
Keywords: Aged; Ankle Brachial Index; C-Reactive Protein; Female; Fibrinogen; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Metabolic Syndrome; Peripheral Arterial Disease; Prevalence; Risk Factors; Vasculitis

Multiancestral analysis of inflammation-related genetic variants and C-reactive protein in the population architecture using genomics and epidemiology study. - Kocarnik, Jonathan M; Pendergrass, Sarah A; Carty, Cara L; Pankow, James S; Schumacher, Fredrick R; Cheng, Iona; Durda, Peter; Ambite, Jose Luis; Deelman, Ewa; Cook, Nancy R; Liu, Simin; Wactawski-Wende, Jean; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: C-reactive protein (CRP) is a biomarker of inflammation. Genome-wide association studies (GWAS) have identified single-nucleotide polymorphisms (SNPs) associated with CRP concentrations and inflammation-related traits such as cardiovascular disease, type 2 diabetes mellitus, and obesity. We aimed to replicate previous CRP-SNP associations, assess whether these associations generalize to additional race/ethnicity groups, and evaluate inflammation-related SNPs for a potentially pleiotropic association with CRP. METHODS AND RESULTS: We selected and analyzed 16 CRP-associated and 250 inflammation-related GWAS SNPs among 40 473 African American, American Indian, Asian/Pacific Islander, European American, and Hispanic participants from 7 studies collaborating in the Population Architecture using Genomics and Epidemiology (PAGE) study. Fixed-effect meta-analyses combined study-specific race/ethnicity-stratified linear regression estimates to evaluate the association between each SNP and high-sensitivity CRP. Overall, 18 SNPs in 8 loci were significantly associated with CRP (Bonferroni-corrected P<3.1×10(-3) for replication, P<2.0×10(-4) for pleiotropy): Seven of these were specific to European Americans, while 9 additionally generalized to African Americans (1), Hispanics (5), or both (3); 1 SNP was seen only in African Americans and Hispanics. Two SNPs in the CELSR2/PSRC1/SORT1 locus showed a potentially novel association with CRP: rs599839 (P=2.0×10(-6)) and rs646776 (P=3.1×10(-5)). CONCLUSIONS: We replicated 16 SNP-CRP associations, 10 of which generalized to African Americans and/or Hispanics. We also identified potentially novel pleiotropic associations with CRP for two SNPs previously associated with coronary artery disease and/or low-density lipoprotein-cholesterol. These findings demonstrate the benefit of evaluating genotype-phenotype associations in multiple race/ethnicity groups and looking for pleiotropic relationships among SNPs previously associated with related phenotypes.
Keywords: Adult; African Continental Ancestry Group; Aged; Asian Continental Ancestry Group; C-Reactive Protein; Female; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Inflammation; Male; Middle Aged; Polymorphism, Single Nucleotide; United States; Young Adult

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Prognostic implications of microvascular and macrovascular abnormalities in older adults: cardiovascular health study. - Kim, Dae Hyun; Grodstein, Francine; Newman, Anne B; Chaves, Paulo H M; Odden, Michelle C; Klein, Ronald; Sarnak, Mark J; Patel, Kushang V; Lipsitz, Lewis A (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Microvascular and macrovascular abnormalities are frequently found on noninvasive tests performed in older adults. Their prognostic implications on disability and life expectancy have not been collectively assessed. METHODS: This prospective study included 2,452 adults (mean age: 79.5 years) with available measures of microvascular (brain, retina, kidney) and macrovascular abnormalities (brain, carotid, coronary, peripheral artery) in the Cardiovascular Health Study. The burden of microvascular and macrovascular abnormalities was examined in relation to total, activity-of-daily-living disability-free, and severe disability-free life expectancies in the next 10 years (1999-2009). RESULTS: At 75 years, individuals with low burden of both abnormalities lived, on average, 8.71 years (95% confidence interval: 8.29, 9.12) of which 7.67 years (7.16, 8.17) were without disability. In comparison, individuals with high burden of both abnormalities had shortest total life expectancy (6.95 years [6.52, 7.37]; p < .001) and disability-free life expectancy (5.60 years [5.10, 6.11]; p < .001). Although total life expectancy was similarly reduced for those with high burden of either type of abnormalities (microvascular: 7.96 years [7.50, 8.42] vs macrovascular: 8.25 years [7.80, 8.70]; p = .10), microvascular abnormalities seemed to have larger impact than macrovascular abnormalities on disability-free life expectancy (6.45 years [5.90, 6.99] vs 6.96 years [6.43, 7.48]; p = .016). These results were consistent for severe disability-free life expectancy and in individuals without clinical cardiovascular disease. CONCLUSIONS: Considering both microvascular and macrovascular abnormalities from multiple noninvasive tests may provide additional prognostic information on how older adults spend their remaining life. Optimal clinical use of this information remains to be determined.
Keywords: Aged; Aged, 80 and over; Aging; Ankle Brachial Index; Disability Evaluation; Electrocardiography; Female; Follow-Up Studies; Forecasting; Humans; Life Expectancy; Magnetic Resonance Imaging; Male; Microcirculation; Prognosis; Prospective Studies; Risk Factors; Vascular Malformations

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Risk factors for cardiovascular disease across the spectrum of older age: the Cardiovascular Health Study. - Odden, Michelle C; Shlipak, Michael G; Whitson, Heather E; Katz, Ronit; Kearney, Patricia M; deFilippi, Chris; Shastri, Shani; Sarnak, Mark J; Siscovick, David S; Cushman, Mary; Psaty, Bruce M; Newman, Anne B (Atherosclerosis, 2014)
OBJECTIVE: The associations of some risk factors with cardiovascular disease (CVD) are attenuated in older age; whereas others appear robust. The present study aimed to compare CVD risk factors across older age. METHODS: Participants (n = 4883) in the Cardiovascular Health Study free of prevalent CVD, were stratified into three age groups: 65-74, 75-84, 85+ years. Traditional risk factors included systolic blood pressure (BP), LDL-cholesterol, HDL-cholesterol, obesity, and diabetes. Novel risk factors included kidney function, C-reactive protein (CRP), and N-terminal pro-B-type natriuretic peptide (NT pro-BNP). RESULTS: There were 1498 composite CVD events (stroke, myocardial infarction, and cardiovascular death) over 5 years. The associations of high systolic BP and diabetes appeared strongest, though both were attenuated with age (p-values for interaction = 0.01 and 0.002, respectively). The demographic-adjusted hazard ratios (HR) for elevated systolic BP were 1.79 (95% confidence interval: 1.49, 2.15), 1.59 (1.37, 1.85) and 1.10 (0.86, 1.41) in participants aged 65-74, 75-84, 85+, and for diabetes, 2.36 (1.89, 2.95), 1.55 (1.27, 1.89), 1.51 (1.10, 2.09). The novel risk factors had consistent associations with the outcome across the age spectrum; low kidney function: 1.69 (1.31, 2.19), 1.61 (1.36, 1.90), and 1.57 (1.16, 2.14) for 65-74, 75-84, and 85+ years, respectively; elevated CRP: 1.54 (1.28, 1.87), 1.33 (1.13, 1.55), and 1.51 (1.15, 1.97); elevated NT pro-BNP: 2.67 (1.96, 3.64), 2.71 (2.25, 3.27), and 2.18 (1.43, 3.45). CONCLUSIONS: The associations of most traditional risk factors with CVD were minimal in the oldest old, whereas diabetes, eGFR, CRP, and NT pro-BNP were associated with CVD across older age.
Keywords: Aged; Aged, 80 and over; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Complications; Diabetes Mellitus; Female; Humans; Inflammation; Kidney; Kidney Diseases; Lipids; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Risk Factors

Sequence variation in TMEM18 in association with body mass index: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Liu, Ching-Ti; Young, Kristin L; Brody, Jennifer A; Olden, Matthias; Wojczynski, Mary K; Heard-Costa, Nancy; Li, Guo; Morrison, Alanna C; Muzny, Donna; Gibbs, Richard A; Reid, Jeffrey G; Shao, Yaming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies for body mass index (BMI) previously identified a locus near TMEM18. We conducted targeted sequencing of this region to investigate the role of common, low-frequency, and rare variants influencing BMI. METHODS AND RESULTS: We sequenced TMEM18 and regions downstream of TMEM18 on chromosome 2 in 3976 individuals of European ancestry from 3 community-based cohorts (Atherosclerosis Risk in Communities, Cardiovascular Health Study, and Framingham Heart Study), including 200 adults selected for high BMI. We examined the association between BMI and variants identified in the region from nucleotide position 586 432 to 677 539 (hg18). Rare variants (minor allele frequency, <1%) were analyzed using a burden test and the sequence kernel association test. Results from the 3 cohort studies were meta-analyzed. We estimate that mean BMI is 0.43 kg/m(2) higher for each copy of the G allele of single-nucleotide polymorphism rs7596758 (minor allele frequency, 29%; P=3.46×10(-4)) using a Bonferroni threshold of P<4.6×10(-4). Analyses conditional on previous genome-wide association study single-nucleotide polymorphisms associated with BMI in the region led to attenuation of this signal and uncovered another independent (r(2)<0.2), statistically significant association, rs186019316 (P=2.11×10(-4)). Both rs186019316 and rs7596758 or proxies are located in transcription factor binding regions. No significant association with rare variants was found in either the exons of TMEM18 or the 3' genome-wide association study region. CONCLUSIONS: Targeted sequencing around TMEM18 identified 2 novel BMI variants with possible regulatory function.
Keywords: Adult; Aged; Aging; Body Mass Index; Cohort Studies; Female; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Sequencing of 2 subclinical atherosclerosis candidate regions in 3669 individuals: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Bis, Joshua C; White, Charles C; Franceschini, Nora; Brody, Jennifer; Zhang, Xiaoling; Muzny, Donna; Santibanez, Jireh; Gibbs, Richard; Liu, Xiaoming; Lin, Honghuang; Boerwinkle, Eric; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Atherosclerosis, the precursor to coronary heart disease and stroke, is characterized by an accumulation of fatty cells in the arterial intimal-medial layers. Common carotid intima media thickness (cIMT) and plaque are subclinical atherosclerosis measures that predict cardiovascular disease events. Previously, genome-wide association studies demonstrated evidence for association with cIMT (SLC17A4) and plaque (PIK3CG). METHODS AND RESULTS: We sequenced 120 kb around SLC17A4 (6p22.2) and 251 kb around PIK3CG (7q22.3) among 3669 European ancestry participants from the Atherosclerosis Risk in Communities (ARIC) study, Cardiovascular Health Study (CHS), and Framingham Heart Study (FHS) in Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Primary analyses focused on 438 common variants (minor allele frequency ≥1%), which were independently meta-analyzed. A 3' untranslated region CCDC71L variant (rs2286149), upstream from PIK3CG, was the most significant finding in cIMT (P=0.00033) and plaque (P=0.0004) analyses. A SLC17A4 intronic variant was also associated with cIMT (P=0.008). Both were in low linkage disequilibrium with the genome-wide association study single nucleotide polymorphisms. Gene-based tests including T1 count and sequence kernel association test for rare variants (minor allele frequency <1%) did not yield statistically significant associations. However, we observed nominal associations for rare variants in CCDC71L and SLC17A3 with cIMT and of the entire 7q22 region with plaque (P=0.05). CONCLUSIONS: Common and rare variants in PIK3CG and SLC17A4 regions demonstrated modest association with subclinical atherosclerosis traits. Although not conclusive, these findings may help to understand the genetic architecture of regions previously implicated by genome-wide association studies and identify variants within these regions for further investigation in larger samples.
Keywords: Aged; Aged, 80 and over; Aging; Atherosclerosis; Class Ib Phosphatidylinositol 3-Kinase; Cohort Studies; European Continental Ancestry Group; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sodium-Phosphate Cotransporter Proteins, Type I

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Serum carboxymethyl-lysine, disability, and frailty in older persons: the Cardiovascular Health Study. - Whitson, Heather E; Arnold, Alice M; Yee, Laura M; Mukamal, Kenneth J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Siscovick, David; Tracy, Russell P; Thielke, Stephen M; Hirsch, Calvin; Newman, Anne B; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Advanced glycation endproducts are biologically active compounds that accumulate in disordered metabolism and normal aging. Carboxymethyl-lysine (CML), a ubiquitous human advanced glycation endproduct, has been associated with age-related conditions and mortality. Our objective was to ascertain the relationship between CML and geriatric outcomes (disability and frailty) in a large cohort of older men and women. METHODS: In 1996-1997, serum CML was measured in 3,373 Cardiovascular Health Study participants (mean age 78.1 ± 4.8 years). Disability, defined as difficulty in any of six activities of daily living, was assessed every 6-12 months for 14 years. Frailty was defined according to five standard criteria at the 1996-1997 visit. Cox proportional hazard models estimated the relationship between CML and incident disability (N = 2,643). Logistic regression models estimated the relationship between CML and prevalent frailty. RESULTS: Adjusting for multiple potential confounders, higher CML was associated with incident disability (hazard ratio per standard deviation [225 ng/mL] increase: 1.05, 95% CI 1.01-1.11). In men, odds of frailty increased with higher CML values (odds ratio = 1.30 per standard deviation, 95% CI 1.14-1.48), but the relationship was attenuated by adjustment for cognitive status, kidney function, and arthritis. CML was not associated with frailty in women. CONCLUSIONS: Higher serum CML levels in late life are associated with incident disability and prevalent frailty. Further work is needed to understand CML's value as a risk stratifier, biomarker, or target for interventions that promote healthy aging.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Biomarkers; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Health Status; Humans; Incidence; Lysine; Male; Prevalence; Prognosis; Retrospective Studies; United States

Simple biologically informed inflammatory index of two serum cytokines predicts 10 year all-cause mortality in older adults. - Varadhan, Ravi; Yao, Wenliang; Matteini, Amy; Beamer, Brock A; Xue, Qian-Li; Yang, Huanle; Manwani, Bhavish; Reiner, Alexander; Jenny, Nancy; Parekh, Neel; Fallin, M Daniele; Newman, Anne; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Individual measurements of inflammation have been utilized to assess adverse outcomes risk in older adults with varying degrees of success. This study was designed to identify biologically informed, aggregate measures of inflammation for optimal risk assessment and to inform further biological study of inflammatory pathways. METHODS: In total, 15 nuclear factor-kappa B-mediated pathway markers of inflammation were first measured in baseline serum samples of 1,155 older participants in the InCHIANTI population. Of these, C-reactive protein, interleukin-1-receptor antagonist, interleukin-6, interleukin-18, and soluble tumor necrosis factor-α receptor-1 were independent predictors of 5-year mortality. These five inflammatory markers were measured in baseline serum samples of 5,600 Cardiovascular Health Study participants. A weighted summary score, the first principal component summary score, and an inflammation index score were developed from these five log-transformed inflammatory markers, and their prediction of 10-year all-cause mortality was evaluated in Cardiovascular Health Study and then validated in InCHIANTI. RESULTS: The inflammation index score that included interleukin-6 and soluble tumor necrosis factor-α receptor-1 was the best predictor of 10-year all-cause mortality in Cardiovascular Health Study, after adjusting for age, sex, education, race, smoking, and body mass index (hazards ratio = 1.62; 95% CI: 1.54, 1.70) compared with all other single and combined measures. The inflammation index score was also the best predictor of mortality in the InCHIANTI validation study (hazards ratio 1.33; 95% CI: 1.17-1.52). Stratification by sex and CVD status further strengthened the association of inflammation index score with mortality. CONCLUSION: A simple additive index of serum interleukin-6 and soluble tumor necrosis factor-α receptor-1 best captures the effect of chronic inflammation on mortality in older adults among the 15 biomarkers measured.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cohort Studies; Female; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Interleukin-6; Longevity; Male; Receptors, Tumor Necrosis Factor, Type I; Risk Factors

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Subclinical vascular disease burden and longer survival. - Odden, Michelle C; Yee, Laura M; Arnold, Alice M; Sanders, Jason L; Hirsch, Calvin; DeFilippi, Christopher; Kizer, Jorge R; Inzitari, Marco; Newman, Anne B (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the contribution of gradations of subclinical vascular disease (SVD) to the likelihood of longer survival and to determine what allows some individuals with SVD to live longer. DESIGN: Cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals born between June 30, 1918, and June 30, 1921 (N = 2,082; aged 70-75 at baseline (1992-93)). MEASUREMENTS: A SVD index was scored as 0 for no abnormalities, 1 for mild abnormalities, and 2 for severe abnormalities on ankle-arm index, electrocardiogram, and common carotid intima-media thickness measured at baseline. Survival groups were categorized as 80 and younger, 81 to 84, 85 to 89, and 90 and older. RESULTS: A 1-point lower SVD score was associated with 1.22 greater odds (95% confidence interval = 1.14-1.31) of longer survival, independent of potential confounders. This association was unchanged after adjustment for intermediate incident cardiovascular events. There was suggestion of an interaction between kidney function, smoking, and C-reactive protein and SVD; the association between SVD and longer survival appeared to be modestly greater in persons with poor kidney function, inflammation, or a history of smoking. CONCLUSION: A lower burden of SVD is associated with longer survival, independent of intermediate cardiovascular events. Abstinence from smoking, better kidney function, and lower inflammation may attenuate the effects of higher SVD and promote longer survival.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Carotid Intima-Media Thickness; Cohort Studies; Cystatin C; Depression; Diabetes Mellitus; Electrocardiography; Female; Humans; Inflammation; Kidney Diseases; Male; Smoking; Survival Analysis; United States; Vascular Diseases

Systolic and diastolic blood pressure, incident cardiovascular events, and death in elderly persons: the role of functional limitation in the Cardiovascular Health Study. - Peralta, Carmen A; Katz, Ronit; Newman, Anne B; Psaty, Bruce M; Odden, Michelle C (Hypertension, 2014)
Whether limitation in the ability to perform activities of daily living (ADL) or gait speed can identify elders in whom the association of systolic and diastolic blood pressure (DBP) with cardiovascular events (CVDs) and death differs is unclear. We evaluated whether limitation in ADL or gait speed modifies the association of systolic blood pressure or DBP with incident CVD (n=2358) and death (n=3547) in the Cardiovascular Health Study. Mean age was 78±5 and 21% reported limitation in ≥1 ADL. There were 778 CVD and 1289 deaths over 9 years. Among persons without and those with ADL limitation, systolic blood pressure was associated with incident CVD: hazard ratio [HR] (per 10-mm Hg increase) 1.08 (95% confidence interval, 1.03, 1.13) and 1.06 (0.97, 1.17), respectively. ADL modified the association of DBP with incident CVD. Among those without ADL limitation, DBP was weakly associated with incident CVD, HR 1.04 (0.79, 1.37) for DBP >80, compared with <65 mm Hg. Among those with ADL limitation, DBP was inversely associated with CVD: HR 0.65 (0.44, 0.96) for DBP 66 to 80 mm Hg and HR 0.49 (0.25, 0.94) for DBP >80, compared with DBP ≤65. Among people with ADL limitation, a DBP of 66 to 80 had the lowest risk of death, HR 0.72 (0.57, 0.91), compared with a DBP of ≤65. Associations did not vary by 15-feet walking speed. ADL can identify elders in whom diastolic hypotension is associated with higher cardiovascular risk and death. Functional status, rather than chronologic age alone, should inform design of hypertension trials in elders.
Keywords: Activities of Daily Living; African Continental Ancestry Group; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Diastole; European Continental Ancestry Group; Female; Follow-Up Studies; Gait; Heart Rate; Humans; Incidence; Longitudinal Studies; Male; Risk Factors; Survival Rate; Systole

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Troponin T, NT-proBNP, and venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Lutsey, Pamela L; Nambi, Vijay; deFilippi, Christopher R; Heckbert, Susan R; Cushman, Mary; Ballantyne, Christie M (Vasc Med, 2014)
Increased levels of plasma troponins and natriuretic peptides are markers of cardiac dysfunction associated with increased risk of cardiovascular disease. Little information exists on cardiac dysfunction and occurrence of venous thromboembolism (VTE). In two prospective epidemiological cohorts, we tested the hypothesis that high-sensitivity troponin T (TnT) and N-terminal pro B-type natriuretic peptide (NT-proBNP) are associated positively with VTE occurrence. The Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS) measured plasma TnT and NT-proBNP in 13,719 men or women with no history of venous thrombosis, coronary heart disease, or heart failure and followed them for approximately 10 years for VTE occurrence (n = 348 VTEs). In both ARIC and CHS, TnT was associated positively with incidence of total VTE and provoked VTE, but not with unprovoked VTE: age, race, and sex-adjusted hazard ratios for total VTE in the pooled analysis were 1.00, 0.85, 1.36, 1.51, and 1.98 (p-trend <0.0001) across five categories of TnT. In contrast, the association of NT-proBNP with VTE was positive in ARIC (hazard ratios approximately 2.5-fold for the highest versus lowest NT-proBNP quintiles), but non-existent in CHS.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Factors; Troponin T; Venous Thromboembolism

A variant of sparse partial least squares for variable selection and data exploration. - Olson Hunt, Megan J; Weissfeld, Lisa; Boudreau, Robert M; Aizenstein, Howard; Newman, Anne B; Simonsick, Eleanor M; Van Domelen, Dane R; Thomas, Fridtjof; Yaffe, Kristine; Rosano, Caterina (Front Neuroinform, 2014)
When data are sparse and/or predictors multicollinear, current implementation of sparse partial least squares (SPLS) does not give estimates for non-selected predictors nor provide a measure of inference. In response, an approach termed "all-possible" SPLS is proposed, which fits a SPLS model for all tuning parameter values across a set grid. Noted is the percentage of time a given predictor is chosen, as well as the average non-zero parameter estimate. Using a "large" number of multicollinear predictors, simulation confirmed variables not associated with the outcome were least likely to be chosen as sparsity increased across the grid of tuning parameters, while the opposite was true for those strongly associated. Lastly, variables with a weak association were chosen more often than those with no association, but less often than those with a strong relationship to the outcome. Similarly, predictors most strongly related to the outcome had the largest average parameter estimate magnitude, followed by those with a weak relationship, followed by those with no relationship. Across two independent studies regarding the relationship between volumetric MRI measures and a cognitive test score, this method confirmed a priori hypotheses about which brain regions would be selected most often and have the largest average parameter estimates. In conclusion, the percentage of time a predictor is chosen is a useful measure for ordering the strength of the relationship between the independent and dependent variables, serving as a form of inference. The average parameter estimates give further insight regarding the direction and strength of association. As a result, all-possible SPLS gives more information than the dichotomous output of traditional SPLS, making it useful when undertaking data exploration and hypothesis generation for a large number of potential predictors.

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association between hospitalization for pneumonia and subsequent risk of cardiovascular disease. - Corrales-Medina, Vicente F; Alvarez, Karina N; Weissfeld, Lisa A; Angus, Derek C; Chirinos, Julio A; Chang, Chung-Chou H; Newman, Anne; Loehr, Laura; Folsom, Aaron R; Elkind, Mitchell S; Lyles, Mary F; Kronmal, Richard A; et al. (JAMA, 2015)
IMPORTANCE: The risk of cardiovascular disease (CVD) after infection is poorly understood. OBJECTIVE: To determine whether hospitalization for pneumonia is associated with an increased short-term and long-term risk of CVD. DESIGN, SETTINGS, AND PARTICIPANTS: We examined 2 community-based cohorts: the Cardiovascular Health Study (CHS, n = 5888; enrollment age, ≥65 years; enrollment period, 1989-1994) and the Atherosclerosis Risk in Communities study (ARIC, n = 15,792; enrollment age, 45-64 years; enrollment period, 1987-1989). Participants were followed up through December 31, 2010. We matched each participant hospitalized with pneumonia to 2 controls. Pneumonia cases and controls were followed for occurrence of CVD over 10 years after matching. We estimated hazard ratios (HRs) for CVD at different time intervals, adjusting for demographics, CVD risk factors, subclinical CVD, comorbidities, and functional status. EXPOSURES: Hospitalization for pneumonia. MAIN OUTCOMES AND MEASURES: Incident CVD (myocardial infarction, stroke, and fatal coronary heart disease). RESULTS: Of 591 pneumonia cases in CHS, 206 had CVD events over 10 years after pneumonia hospitalization. CVD risk after pneumonia was highest in the first year. CVD occurred in 54 cases and 6 controls in the first 30 days (HR, 4.07; 95% CI, 2.86-5.27); 11 cases and 9 controls between 31 and 90 days (HR, 2.94; 95% CI, 2.18-3.70); and 22 cases and 55 controls between 91 days and 1 year (HR, 2.10; 95% CI, 1.59-2.60). Additional CVD risk remained elevated into the tenth year, when 4 cases and 12 controls developed CVD (HR, 1.86; 95% CI, 1.18-2.55). In ARIC, of 680 pneumonia cases, 112 had CVD over 10 years after hospitalization. CVD occurred in 4 cases and 3 controls in the first 30 days (HR, 2.38; 95% CI, 1.12-3.63); 4 cases and 0 controls between 31 and 90 days (HR, 2.40; 95% CI, 1.23-3.47); 11 cases and 8 controls between 91 days and 1 year (HR, 2.19; 95% CI, 1.20-3.19); and 8 cases and 7 controls during the second year (HR, 1.88; 95% CI, 1.10-2.66). After the second year, the HRs were no longer statistically significant. CONCLUSIONS AND RELEVANCE: Hospitalization for pneumonia was associated with increased short-term and long-term risk of CVD, suggesting that pneumonia may be a risk factor for CVD.
Keywords: Aged; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Hospitalization; Humans; Male; Middle Aged; Pneumonia; Risk Factors

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Association of mitochondrial DNA levels with frailty and all-cause mortality. - Ashar, Foram N; Moes, Anna; Moore, Ann Z; Grove, Megan L; Chaves, Paulo H M; Coresh, Josef; Newman, Anne B; Matteini, Amy M; Bandeen-Roche, Karen; Boerwinkle, Eric; Walston, Jeremy D; Arking, Dan E (J Mol Med (Berl), 2015)
Mitochondrial function is altered with age and variants in mitochondrial DNA (mtDNA) modulate risk for several age-related disease states. However, the association of mtDNA copy number, a readily available marker which reflects mitochondrial depletion, energy reserves, and oxidative stress, on aging and mortality in the general population has not been addressed. To assess the association between mtDNA copy number and two primary outcomes--prevalent frailty and all-cause mortality--we utilize data from participants who were from two multicenter, multiethnic, community-based, prospective studies--the Cardiovascular Health Study (CHS) (1989-2006) and the Atherosclerosis Risk in Communities (ARIC) study (1987-2013). A total of 4892 participants (43.3% men) from CHS and 11,509 participants (44.9% men) from ARIC self-identifying as white or black were included in the analysis. mtDNA copy number, the trait of interest, was measured using a qPCR-based method in CHS and an array-based method in ARIC from DNA isolated from whole blood in participants from both cohorts. In race-stratified meta-analyses, we observe a significant inverse association of mtDNA copy number with age and higher mtDNA copy number in women relative to men. Lower mtDNA copy number was also significantly associated with prevalent frailty in white participants from CHS (OR 0.91, 95% CI 0.85-0.97). Additionally, mtDNA copy number was a strong independent predictor of all-cause mortality in an age- and sex-adjusted, race-stratified analysis of 16,401 participants from both cohorts with a pooled hazard ratio of 1.47 (95% CI 1.33-1.62) for the lowest quintile of mtDNA copy number relative to the highest quintile. Key messages: Mitochondrial DNA (mtDNA) copy number is associated with age and sex. Lower mtDNA copy number is also associated with prevalent frailty. mtDNA copy number is a significant predictor of all-cause mortality in a multiethnic population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; DNA, Mitochondrial; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Dosage; Geriatric Assessment; Humans; Kaplan-Meier Estimate; Male; Mortality; Odds Ratio; Population Surveillance; Prospective Studies; Surveys and Questionnaires; United States

Changes in insulin-like growth factor-I and its binding proteins are associated with diabetes mellitus in older adults. - Aneke-Nash, Chino S; Parrinello, Christina M; Rajpathak, Swapnil N; Rohan, Thomas E; Strotmeyer, Elsa S; Kritchevsky, Stephen B; Psaty, Bruce M; Bůzková, Petra; Kizer, Jorge R; Newman, Anne B; Strickler, Howard D; Kaplan, Robert C (J Am Geriatr Soc, 2015)
OBJECTIVES: To determine whether changes in insulin-like growth factor (IGF) protein levels are greater in participants with type 2 diabetes mellitus or worsening glycemia than in normoglycemic individuals over a 9-year follow-up period. DESIGN: Retrospective analysis of a cohort study. SETTING: Participants were recruited from North Carolina, California, Maryland, and Pennsylvania. PARTICIPANTS: Cardiovascular Health Study All Stars participants, a cohort study of community-dwelling adults aged 65 and older (N=897). MEASUREMENTS: Plasma IGF-I, IGF binding protein (IGFBP)-1, and IGFBP-3 levels were assessed and American Diabetes Association cut-points for impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and diabetes mellitus were used to classify participants at baseline (1996-97) and follow-up (2005-06). RESULTS: At baseline, mean age was 76.3±3.6, and 18.5% had diabetes mellitus. Participants with IFG alone and IGT plus IFG had higher IGF-I levels and lower IGFBP-1 levels than those with normoglycemia or diabetes mellitus. The greatest percentage change in IGF levels occurred in those who had diabetes mellitus at baseline (9-year changes: -9.3% for IGF-I, 59.7% for IGFBP-1, -13.4% for IGFBP-3), the smallest in individuals who remained normoglycemic at follow-up (9-year changes: -3.7% for IGF-I, 25.6% for IGFBP-1, -6.4% for IGFBP-3), and intermediate in those who were normoglycemic but developed IFG at follow-up. CONCLUSION: Degrees of glycemic impairment are associated with varying degrees of change in IGF protein levels. The changes observed in the diabetes mellitus group have been previously shown to be associated with heart failure, cancer, and noncancer mortality.
Keywords: Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Retrospective Studies

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

DCAF4, a novel gene associated with leucocyte telomere length. - Mangino, Massimo; Christiansen, Lene; Stone, Rivka; Hunt, Steven C; Horvath, Kent; Eisenberg, Dan T A; Kimura, Masayuki; Petersen, Inge; Kark, Jeremy D; Herbig, Utz; Reiner, Alex P; Benetos, Athanase; et al. (J Med Genet, 2015)
BACKGROUND: Leucocyte telomere length (LTL), which is fashioned by multiple genes, has been linked to a host of human diseases, including sporadic melanoma. A number of genes associated with LTL have already been identified through genome-wide association studies. The main aim of this study was to establish whether DCAF4 (DDB1 and CUL4-associated factor 4) is associated with LTL. In addition, using ingenuity pathway analysis (IPA), we examined whether LTL-associated genes in the general population might partially explain the inherently longer LTL in patients with sporadic melanoma, the risk for which is increased with ultraviolet radiation (UVR). RESULTS: Genome-wide association (GWA) meta-analysis and de novo genotyping of 20 022 individuals revealed a novel association (p=6.4×10(-10)) between LTL and rs2535913, which lies within DCAF4. Notably, eQTL analysis showed that rs2535913 is associated with decline in DCAF4 expressions in both lymphoblastoid cells and sun-exposed skin (p=4.1×10(-3) and 2×10(-3), respectively). Moreover, IPA revealed that LTL-associated genes, derived from GWA meta-analysis (N=9190), are over-represented among genes engaged in melanoma pathways. Meeting increasingly stringent p value thresholds (p<0.05, <0.01, <0.005, <0.001) in the LTL-GWA meta-analysis, these genes were jointly over-represented for melanoma at p values ranging from 1.97×10(-169) to 3.42×10(-24). CONCLUSIONS: We uncovered a new locus associated with LTL in the general population. We also provided preliminary findings that suggest a link of LTL through genetic mechanisms with UVR and melanoma in the general population.
Keywords: Alleles; Carrier Proteins; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Melanoma; Risk Factors; Telomere; Telomere Homeostasis

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Generalized estimating equations for genome-wide association studies using longitudinal phenotype data. - Sitlani, Colleen M; Rice, Kenneth M; Lumley, Thomas; McKnight, Barbara; Cupples, L Adrienne; Avery, Christy L; Noordam, Raymond; Stricker, Bruno H C; Whitsel, Eric A; Psaty, Bruce M (Stat Med, 2015)
Many longitudinal cohort studies have both genome-wide measures of genetic variation and repeated measures of phenotypes and environmental exposures. Genome-wide association study analyses have typically used only cross-sectional data to evaluate quantitative phenotypes and binary traits. Incorporation of repeated measures may increase power to detect associations, but also requires specialized analysis methods. Here, we discuss one such method-generalized estimating equations (GEE)-in the contexts of analysis of main effects of rare genetic variants and analysis of gene-environment interactions. We illustrate the potential for increased power using GEE analyses instead of cross-sectional analyses. We also address challenges that arise, such as the need for small-sample corrections when the minor allele frequency of a genetic variant and/or the prevalence of an environmental exposure is low. To illustrate methods for detection of gene-drug interactions on a genome-wide scale, using repeated measures data, we conduct single-study analyses and meta-analyses across studies in three large cohort studies participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium-the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Rotterdam Study.
Keywords: Aged; Aging; Cardiovascular Diseases; Cohort Studies; Computer Simulation; Cross-Sectional Studies; Epidemiologic Research Design; Gene-Environment Interaction; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Longitudinal Studies; Meta-Analysis as Topic; Models, Genetic; Pharmacogenetics; Risk Assessment; United States

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome-Wide Association Study and Linkage Analysis of the Healthy Aging Index. - Minster, Ryan L; Sanders, Jason L; Singh, Jatinder; Kammerer, Candace M; Barmada, M Michael; Matteini, Amy M; Zhang, Qunyuan; Wojczynski, Mary K; Daw, E Warwick; Brody, Jennifer A; Arnold, Alice M; Lunetta, Kathryn L; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The Healthy Aging Index (HAI) is a tool for measuring the extent of health and disease across multiple systems. METHODS: We conducted a genome-wide association study and a genome-wide linkage analysis to map quantitative trait loci associated with the HAI and a modified HAI weighted for mortality risk in 3,140 individuals selected for familial longevity from the Long Life Family Study. The genome-wide association study used the Long Life Family Study as the discovery cohort and individuals from the Cardiovascular Health Study and the Framingham Heart Study as replication cohorts. RESULTS: There were no genome-wide significant findings from the genome-wide association study; however, several single-nucleotide polymorphisms near ZNF704 on chromosome 8q21.13 were suggestively associated with the HAI in the Long Life Family Study (p < 10(-) (6)) and nominally replicated in the Cardiovascular Health Study and Framingham Heart Study. Linkage results revealed significant evidence (log-odds score = 3.36) for a quantitative trait locus for mortality-optimized HAI in women on chromosome 9p24-p23. However, results of fine-mapping studies did not implicate any specific candidate genes within this region of interest. CONCLUSIONS: ZNF704 may be a potential candidate gene for studies of the genetic underpinnings of longevity.
Keywords: Aging; Apolipoproteins E; Forkhead Transcription Factors; Genetic Linkage; Genome-Wide Association Study; Humans; Longevity; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Intermediate and long-term risk of new-onset heart failure after hospitalization for pneumonia in elderly adults. - Corrales-Medina, Vicente F; Taljaard, Monica; Yende, Sachin; Kronmal, Richard; Dwivedi, Girish; Newman, Anne B; Elkind, Mitchell S V; Lyles, Mary F; Chirinos, Julio A (Am Heart J, 2015)
BACKGROUND: Pneumonia is associated with high risk of heart failure (HF) in the short term (30 days) postinfection. Whether this association persists beyond this period is unknown. METHODS: We studied 5,613 elderly (≥65 years) adults enrolled in the Cardiovascular Health Study between 1989 and 1994 at 4 US communities. Participants had no clinical diagnosis of HF at enrollment, and they were followed up through December 2010. Hospitalizations for pneumonia were identified using validated International Classification of Disease Ninth Revision codes. A centralized committee adjudicated new-onset HF events. Using Cox regression, we estimated adjusted hazard ratios (HRs) of new-onset HF at different time intervals after hospitalization for pneumonia. RESULTS: A total of 652 participants hospitalized for pneumonia during follow-up were still alive and free of clinical diagnosis of HF by day 30 posthospitalization. Relative to the time of their hospitalization, new-onset HF occurred in 22 cases between 31 and 90 days (HR 6.9, 95% CI 4.46-10.63, P < .001), 14 cases between 91 days and 6 months (HR 3.2, 95% CI 1.88-5.50, P < .001), 20 cases between 6 months and 1 year (HR 2.6, 95% CI 1.64-4.04, P < .001), 76 cases between 1 and 5 years (HR 1.7, 95% CI 1.30-2.12, P < .001), and 71 cases after 5 years (HR 2.0, 95% CI 1.56-2.58, P < .001). Results were robust to sensitivity analyses using stringent definitions of pneumonia and extreme assumptions for potential informative censoring. CONCLUSION: Hospitalization for pneumonia is associated with increased risk of new-onset HF in the intermediate and long term. Studies should characterize the mechanisms of this association in order to prevent HF in elderly pneumonia survivors.
Keywords: Aged; Disease Progression; Female; Follow-Up Studies; Forecasting; Heart Failure; Hospitalization; Humans; Incidence; Inpatients; Male; Patient Readmission; Pneumonia; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Risk Factors; Time Factors

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Age, Race, and Sex With Acute Kidney Injury. - Grams, Morgan E; Sang, Yingying; Ballew, Shoshana H; Gansevoort, Ron T; Kimm, Heejin; Kovesdy, Csaba P; Naimark, David; Oien, Cecilia; Smith, David H; Coresh, Josef; Sarnak, Mark J; Stengel, Bénédicte; et al. (Am J Kidney Dis, 2015)
BACKGROUND: Acute kidney injury (AKI) is a serious global public health problem. We aimed to quantify the risk of AKI associated with estimated glomerular filtration rate (eGFR), albuminuria (albumin-creatinine ratio [ACR]), age, sex, and race (African American and white). STUDY DESIGN: Collaborative meta-analysis. SETTING & POPULATION: 8 general-population cohorts (1,285,049 participants) and 5 chronic kidney disease (CKD) cohorts (79,519 participants). SELECTION CRITERIA FOR STUDIES: Available eGFR, ACR, and 50 or more AKI events. PREDICTORS: Age, sex, race, eGFR, urine ACR, and interactions. OUTCOME: Hospitalized with or for AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: 16,480 (1.3%) general-population cohort participants had AKI over a mean follow-up of 4 years; 2,087 (2.6%) CKD participants had AKI over a mean follow-up of 1 year. Lower eGFR and higher ACR were strongly associated with AKI. Compared with eGFR of 80mL/min/1.73m(2), the adjusted HR of AKI at eGFR of 45mL/min/1.73m(2) was 3.35 (95% CI, 2.75-4.07). Compared with ACR of 5mg/g, the risk of AKI at ACR of 300mg/g was 2.73 (95% CI, 2.18-3.43). Older age was associated with higher risk of AKI, but this effect was attenuated with lower eGFR or higher ACR. Male sex was associated with higher risk of AKI, with a slight attenuation in lower eGFR but not in higher ACR. African Americans had higher AKI risk at higher levels of eGFR and most levels of ACR. LIMITATIONS: Only 2 general-population cohorts could contribute to analyses by race; AKI identified by diagnostic code. CONCLUSIONS: Reduced eGFR and increased ACR are consistent strong risk factors for AKI, whereas associations of AKI with age, sex, and race may be weaker in more advanced stages of CKD.
Keywords: Acute Kidney Injury; Adolescent; Adult; African Americans; Age Distribution; Aged; Albuminuria; Continental Population Groups; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Young Adult

Microvascular and Macrovascular Abnormalities and Cognitive and Physical Function in Older Adults: Cardiovascular Health Study. - Kim, Dae Hyun; Grodstein, Francine; Newman, Anne B; Chaves, Paulo H M; Odden, Michelle C; Klein, Ronald; Sarnak, Mark J; Lipsitz, Lewis A (J Am Geriatr Soc, 2015)
OBJECTIVES: To evaluate and compare the associations between microvascular and macrovascular abnormalities and cognitive and physical function DESIGN: Cross-sectional analysis of the Cardiovascular Health Study (1998-1999). SETTING: Community. PARTICIPANTS: Individuals with available data on three or more of five microvascular abnormalities (brain, retina, kidney) and three or more of six macrovascular abnormalities (brain, carotid artery, heart, peripheral artery) (N = 2,452; mean age 79.5). MEASUREMENTS: Standardized composite scores derived from three cognitive tests (Modified Mini-Mental State Examination, Digit-Symbol Substitution Test, Trail-Making Test (TMT)) and three physical tests (gait speed, grip strength, 5-time sit to stand) RESULTS: Participants with high microvascular and macrovascular burden had worse cognitive (mean score difference = -0.30, 95% confidence interval (CI) = -0.37 to -0.24) and physical (mean score difference = -0.32, 95% CI = -0.38 to -0.26) function than those with low microvascular and macrovascular burden. Individuals with high microvascular burden alone had similarly lower scores than those with high macrovascular burden alone (cognitive function: -0.16, 95% CI = -0.24 to -0.08 vs -0.13, 95% CI = -0.20 to -0.06; physical function: -0.15, 95% CI = -0.22 to -0.08 vs -0.12, 95% CI = -0.18 to -0.06). Psychomotor speed and working memory, assessed using the TMT, were only impaired in the presence of high microvascular burden. Of the 11 vascular abnormalities considered, white matter hyperintensity, cystatin C-based glomerular filtration rate, large brain infarct, and ankle-arm index were independently associated with cognitive and physical function. CONCLUSION: Microvascular and macrovascular abnormalities assessed using noninvasive tests of the brain, kidney, and peripheral artery were independently associated with poor cognitive and physical function in older adults. Future research should evaluate the usefulness of these tests in prognostication.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological Tests; Vascular Malformations

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Multisystem physiologic impairments and changes in gait speed of older adults. - Rosso, Andrea L; Sanders, Jason L; Arnold, Alice M; Boudreau, Robert M; Hirsch, Calvin H; Carlson, Michelle C; Rosano, Caterina; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: Slowed gait is an important health indicator in older adults but a single identifiable cause is often lacking. We assessed whether a summary index measuring impairments across multiple physiologic systems was associated with slowed gait in older individuals. METHODS: Data from the Cardiovascular Health Study (n = 3,010) were used to assess associations between baseline physiologic index (measuring vasculature, brain, kidneys, lungs, and glucose metabolism; range 0-10 with 0-2 points/system and lower score indicating higher function) and annual gait speed (m/s) over 6 years. Participants with complete data on the physiologic index and at least two gait speed measures were included. Mean gait speed and 95% confidence intervals (CI) by category of index were calculated using mixed effects models. RESULTS: Those with scores of three or higher on the index had significantly slower gait speed at baseline compared to those with scores of 0-2 (7-10: mean speed = 0.83 m/s, 95% CI: 0.80, 0.84; 0-2: mean speed = 1.01 m/s, 95% CI: 0.99, 1.03). Those with higher indices also had faster decline in gait speed compared to those with lower scores after adjustment for demographic and health characteristics (7-10: change in speed = -0.020 m/s/year, 95% CI: -0.024, -0.016; 0-2: change in speed= -0.010 m/s/year, 95% CI: -0.014, -0.006). CONCLUSIONS: Greater impairment across five organ systems was associated with slower gait speed and greater declines in gait speed over 6 years. Impairments accumulated over multiple physiologic systems may make older adults more vulnerable to slow gait speed.
Keywords: Age Factors; Aged; Aged, 80 and over; Brain; Cardiovascular Physiological Phenomena; Cohort Studies; Female; Gait; Geriatric Assessment; Glucose; Health Status Indicators; Humans; Kidney; Lung; Male; Sensitivity and Specificity; Time Factors

Older Adults, "Malignant" Left Ventricular Hypertrophy, and Associated Cardiac-Specific Biomarker Phenotypes to Identify the Differential Risk of New-Onset Reduced Versus Preserved Ejection Fraction Heart Failure: CHS (Cardiovascular Health Study). - Seliger, Stephen L; de Lemos, James; Neeland, Ian J; Christenson, Robert; Gottdiener, John; Drazner, Mark H; Berry, Jarett; Sorkin, John; DeFilippi, Christopher (JACC Heart Fail, 2015)
OBJECTIVES: This study hypothesized that biomarkers of subclinical myocardial injury (high-sensitivity cardiac troponin T [hs-cTnT]) and hemodynamic stress (N-terminal pro-B-type natriuretic peptide [NT-proBNP]) would differentiate heart failure (HF) risk among older adults with left ventricular hypertrophy (LVH). BACKGROUND: The natural history of LVH, an important risk factor for HF, is heterogeneous. METHODS: NT-proBNP and hs-cTnT were measured at baseline and after 2 to 3 years in older adults without prior HF or myocardial infarction in the CHS (Cardiovascular Health Study). LVH and left ventricular ejection fraction were determined by echocardiography. HF events were adjudicated over a median of 13.1 years and classified as preserved or reduced left ventricular ejection fraction (heart failure with preserved ejection fraction or heart failure with reduced ejection fraction [HFrEF]). Adjusted risk of HF by LVH and biomarker tertiles, and by LVH and longitudinal increase in each biomarker was estimated using Cox regression. RESULTS: Prevalence of LVH was 12.5% among 2,347 participants with complete measures. Adjusted risk of HF (N = 643 events) was approximately 3.8-fold higher among participants with LVH and in the highest biomarker tertile, compared with those with low biomarker levels without LVH (NT-proBNP, hazard ratio [HR]: 3.78; 95% confidence interval [CI]: 2.78 to 5.15 and hs-cTnT, HR: 3.86; 95% CI: 2.84 to 5.26). The adjusted risk of HFrEF was 7.8 times higher among those with the highest tertile of hs-cTnT and LVH (HR: 7.83; 95% CI: 4.43 to 13.83). Those with LVH and longitudinal increases in hs-cTnT or NT-proBNP were approximately 3-fold more likely to develop HF, primarily HFrEF, compared with those without LVH and with stable biomarkers. CONCLUSIONS: The combination of LVH with greater hs-cTnT or NT-proBNP levels, and their longitudinal increase, identifies older adults at highest risk for symptomatic HF, especially HFrEF. These biomarkers may characterize sub-phenotypes in the transition from LVH to HF and suggest modifiable targets for prevention.
Keywords: Aged; Biomarkers; Echocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Natriuretic Peptide, Brain; Peptide Fragments; Phenotype; Prospective Studies; Risk Factors; Troponin T

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Predicting Future Years of Life, Health, and Functional Ability: A Healthy Life Calculator for Older Adults. - Diehr, Paula; Diehr, Michael; Arnold, Alice; Yee, Laura M; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Psaty, Bruce M; Johnson, W Craig; Kizer Md, Jorge R; Newman, Anne (Gerontol Geriatr Med, 2015)
To create personalized estimates of future health and ability status for older adults.Data came from the Cardiovascular Health Study (CHS), a large longitudinal study. Outcomes included years of life, years of healthy life (based on self-rated health), years of able life (based on activities of daily living), and years of healthy and able life. We developed regression estimates using the demographic and health characteristics that best predicted the four outcomes. Internal and external validity were assessed.A prediction equation based on 11 variables accounted for about 40% of the variability for each outcome. Internal validity was excellent, and external validity was satisfactory. The resulting CHS Healthy Life Calculator (CHSHLC) is available at http://healthylifecalculator.org.CHSHLC provides a well-documented estimate of future years of healthy and able life for older adults, who may use it in planning for the future.

Prognostic Significance of High-Sensitivity Cardiac Troponin T Concentrations between the Limit of Blank and Limit of Detection in Community-Dwelling Adults: A Metaanalysis. - Parikh, Ravi H; Seliger, Stephen L; de Lemos, James; Nambi, Vijay; Christenson, Robert; Ayers, Colby; Sun, Wensheng; Gottdiener, John S; Kuller, Lewis H; Ballantyne, Christie; deFilippi, Christopher R (Clin Chem, 2015)
BACKGROUND: There is controversy regarding whether to report concentrations of high-sensitivity cardiac troponin T (hs-cTnT) to the limit of blank (LOB) (3 ng/L) or the limit of detection (LOD) (5 ng/L) of the assay in community-based cohorts. We hypothesized that hs-cTnT concentrations between the LOB and LOD would be associated with poorer cardiovascular outcomes compared to concentrations below the LOB. METHODS: hs-cTnT was analyzed in a total of 10 723 participants from the Cardiovascular Health Study (CHS), Atherosclerosis Risk in Communities (ARIC) study, and Dallas Heart Study (DHS). Participants were divided into 2 groups, those with hs-cTnT concentrations below the limit of blank (LOB) (<3 ng/L) and those with hs-cTnT between the LOB and limit of detection (LOD) (3-4.99 ng/L). Cross-sectional associations with traditional cardiovascular risk factors and cardiac structural measurements, and longitudinal associations with long-term cardiovascular outcomes of incident heart failure and cardiovascular death, were determined. RESULTS: Participants with hs-cTnT between the LOB and LOD for all 3 cohorts were older, more likely to be male, and have a higher burden of cardiovascular risk factors and structural pathology. A metaanalysis of the 3 cohorts showed participants with hs-cTnT between the LOB and LOD were at increased risk of new-onset heart failure (hazard ratio, 1.18; 95% CI, 1.02-1.38) and cardiovascular mortality (hazard ratio, 1.29; 95% CI, 1.06-1.57). CONCLUSIONS: hs-cTnT concentrations between the LOB and LOD (3-4.99 ng/L) are associated with a higher prevalence of traditional risk factors, more cardiac pathology, and worse outcomes than concentrations below the LOB (<3 ng/L).
Keywords: Aged; Atherosclerosis; Biomarkers; Cross-Sectional Studies; Female; Heart Failure; Humans; Independent Living; Limit of Detection; Longitudinal Studies; Male; Middle Aged; Myocardial Infarction; Prognosis; Risk Assessment; Risk Factors; Sex Factors; Troponin T

Race/Ethnic Differences in the Associations of the Framingham Risk Factors with Carotid IMT and Cardiovascular Events. - Gijsberts, Crystel M; Groenewegen, Karlijn A; Hoefer, Imo E; Eijkemans, Marinus J C; Asselbergs, Folkert W; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; et al. (PLoS One, 2015)
BACKGROUND: Clinical manifestations and outcomes of atherosclerotic disease differ between ethnic groups. In addition, the prevalence of risk factors is substantially different. Primary prevention programs are based on data derived from almost exclusively White people. We investigated how race/ethnic differences modify the associations of established risk factors with atherosclerosis and cardiovascular events. METHODS: We used data from an ongoing individual participant meta-analysis involving 17 population-based cohorts worldwide. We selected 60,211 participants without cardiovascular disease at baseline with available data on ethnicity (White, Black, Asian or Hispanic). We generated a multivariable linear regression model containing risk factors and ethnicity predicting mean common carotid intima-media thickness (CIMT) and a multivariable Cox regression model predicting myocardial infarction or stroke. For each risk factor we assessed how the association with the preclinical and clinical measures of cardiovascular atherosclerotic disease was affected by ethnicity. RESULTS: Ethnicity appeared to significantly modify the associations between risk factors and CIMT and cardiovascular events. The association between age and CIMT was weaker in Blacks and Hispanics. Systolic blood pressure associated more strongly with CIMT in Asians. HDL cholesterol and smoking associated less with CIMT in Blacks. Furthermore, the association of age and total cholesterol levels with the occurrence of cardiovascular events differed between Blacks and Whites. CONCLUSION: The magnitude of associations between risk factors and the presence of atherosclerotic disease differs between race/ethnic groups. These subtle, yet significant differences provide insight in the etiology of cardiovascular disease among race/ethnic groups. These insights aid the race/ethnic-specific implementation of primary prevention.
Keywords: Adult; Age Distribution; Aged; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Cholesterol, LDL; Comorbidity; Continental Population Groups; Diabetes Mellitus; Dyslipidemias; Ethnic Groups; Female; Follow-Up Studies; Global Health; Humans; Hypertension; Incidence; Linear Models; Male; Middle Aged; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Smoking; Stroke

Rare and Coding Region Genetic Variants Associated With Risk of Ischemic Stroke: The NHLBI Exome Sequence Project. - Auer, Paul L; Nalls, Mike; Meschia, James F; Worrall, Bradford B; Longstreth, W T; Seshadri, Sudha; Kooperberg, Charles; Burger, Kathleen M; Carlson, Christopher S; Carty, Cara L; Chen, Wei-Min; Cupples, L Adrienne; et al. (JAMA Neurol, 2015)
IMPORTANCE: Stroke is the second leading cause of death and the third leading cause of years of life lost. Genetic factors contribute to stroke prevalence, and candidate gene and genome-wide association studies (GWAS) have identified variants associated with ischemic stroke risk. These variants often have small effects without obvious biological significance. Exome sequencing may discover predicted protein-altering variants with a potentially large effect on ischemic stroke risk. OBJECTIVE: To investigate the contribution of rare and common genetic variants to ischemic stroke risk by targeting the protein-coding regions of the human genome. DESIGN, SETTING, AND PARTICIPANTS: The National Heart, Lung, and Blood Institute (NHLBI) Exome Sequencing Project (ESP) analyzed approximately 6000 participants from numerous cohorts of European and African ancestry. For discovery, 365 cases of ischemic stroke (small-vessel and large-vessel subtypes) and 809 European ancestry controls were sequenced; for replication, 47 affected sibpairs concordant for stroke subtype and an African American case-control series were sequenced, with 1672 cases and 4509 European ancestry controls genotyped. The ESP's exome sequencing and genotyping started on January 1, 2010, and continued through June 30, 2012. Analyses were conducted on the full data set between July 12, 2012, and July 13, 2013. MAIN OUTCOMES AND MEASURES: Discovery of new variants or genes contributing to ischemic stroke risk and subtype (primary analysis) and determination of support for protein-coding variants contributing to risk in previously published candidate genes (secondary analysis). RESULTS: We identified 2 novel genes associated with an increased risk of ischemic stroke: a protein-coding variant in PDE4DIP (rs1778155; odds ratio, 2.15; P = 2.63 × 10(-8)) with an intracellular signal transduction mechanism and in ACOT4 (rs35724886; odds ratio, 2.04; P = 1.24 × 10(-7)) with a fatty acid metabolism; confirmation of PDE4DIP was observed in affected sibpair families with large-vessel stroke subtype and in African Americans. Replication of protein-coding variants in candidate genes was observed for 2 previously reported GWAS associations: ZFHX3 (cardioembolic stroke) and ABCA1 (large-vessel stroke). CONCLUSIONS AND RELEVANCE: Exome sequencing discovered 2 novel genes and mechanisms, PDE4DIP and ACOT4, associated with increased risk for ischemic stroke. In addition, ZFHX3 and ABCA1 were discovered to have protein-coding variants associated with ischemic stroke. These results suggest that genetic variation in novel pathways contributes to ischemic stroke risk and serves as a target for prediction, prevention, and therapy.
Keywords: Aged; Brain Ischemia; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Muscle Proteins; National Heart, Lung, and Blood Institute (U.S.); Nuclear Proteins; Open Reading Frames; Palmitoyl-CoA Hydrolase; Stroke; United States

Resting heart rate and risk of incident heart failure: three prospective cohort studies and a systematic meta-analysis. - Khan, Hassan; Kunutsor, Setor; Kalogeropoulos, Andreas P; Georgiopoulou, Vasiliki V; Newman, Anne B; Harris, Tamara B; Bibbins-Domingo, Kirsten; Kauhanen, Jussi; Gheorghiade, Mihai; Fonarow, Gregg C; Kritchevsky, Stephen B; Laukkanen, Jari A; et al. (J Am Heart Assoc, 2015)
BACKGROUND: The relationship between resting heart rate (RHR) and incident heart failure (HF) has been questioned. METHODS AND RESULTS: RHR was assessed at baseline in 7073 participants in 3 prospective cohorts (Cardiovascular Health Study, Health ABC study and Kuopio Ischemic Heart Disease Study) that recorded 1189 incident HF outcomes during 92 702 person-years of follow-up. Mean age of participants was 67 (9.9) years and mean RHR was 64.6 (11.1) bpm. Baseline RHR correlated (P<0.001) positively with body mass index (r=0.10), fasting glucose (r=0.18), and C-reactive protein (r=0.20); and inversely with serum creatinine (r=-0.05) and albumin (r=-0.05). Baseline RHR was non-linearly associated with HF risk. The age and sex-adjusted hazard ratio for HF comparing the top (>72 bpm) versus the bottom (<57 bpm) quartile of baseline RHR was 1.48 (95% confidence interval [CI] 1.26 to 1.74) and was modestly attenuated (1.30, 95% CI 1.10 to 1.53) with further adjustment for body mass index, history of diabetes, hypertension, smoking status, serum creatinine, and left ventricular hypertrophy. These findings remained consistent in analyses accounting for incident coronary heart disease, excluding individuals with prior cardiovascular events, or those taking beta-blockers; and in subgroups defined by several individual participant characteristics. In a pooled random effects meta-analysis of 7 population-based studies (43 051 participants and 3476 HF events), the overall hazard ratio comparing top versus bottom fourth of RHR was 1.40 (95% CI: 1.19 to 1.64). CONCLUSIONS: There is a non-linear association between RHR and incident HF. Further research is needed to understand the physiologic foundations of this association.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Heart Failure; Heart Rate; Humans; Incidence; Japan; Male; Predictive Value of Tests; Prospective Studies; Rest; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

Sex, Race, and Age Differences in Observed Years of Life, Healthy Life, and Able Life among Older Adults in The Cardiovascular Health Study. - Thielke, Stephen M; Diehr, Paula H; Yee, Laura M; Arnold, Alice M; Quiñones, Ana R; Whitson, Heather E; Jacob, Mini E; Newman, Anne B (J Pers Med, 2015)
OBJECTIVE: Longevity fails to account for health and functional status during aging. We sought to quantify differences in years of total life, years of healthy life, and years of able life among groups defined by age, sex, and race. DESIGN: Primary analysis of a cohort study. SETTING: 18 years of annual evaluations in four U.S. communities. PARTICIPANTS: 5888 men and women aged 65 and older. MEASUREMENTS: Years of life were calculated as the time from enrollment to death or 18 years. Years of total, healthy, and able life were determined from self-report during annual or semi-annual contacts. Cumulative years were summed across each of the age and sex groups. RESULTS: White women had the best outcomes for all three measures, followed by white men, non-white women, and non-white men. For example, at the mean age of 73, a white female participant could expect 12.9 years of life, 8.9 of healthy life and 9.5 of able life, while a non-white female could expect 12.6, 7.0, and 8.0 years, respectively. A white male could expect 11.2, 8.1, and 8.9 years of life, healthy life, and able life, and a non-white male 10.3, 6.2, and 7.9 years. Regardless of starting age, individuals of the same race and sex groups spent similar amounts (not proportions) of time in an unhealthy or unable state. CONCLUSION: Gender had a greater effect on longevity than did race, but race had a greater effect on years spent healthy or able. The mean number of years spent in an unable or sick state was surprisingly independent of the lifespan.

Shared genetic basis for migraine and ischemic stroke: A genome-wide analysis of common variants. - Malik, Rainer; Freilinger, Tobias; Winsvold, Bendik S; Anttila, Verneri; Vander Heiden, Jason; Traylor, Matthew; de Vries, Boukje; Holliday, Elizabeth G; Terwindt, Gisela M; Sturm, Jonathan; Bis, Joshua C; Hopewell, Jemma C; et al. (Neurology, 2015)
OBJECTIVE: To quantify genetic overlap between migraine and ischemic stroke (IS) with respect to common genetic variation. METHODS: We applied 4 different approaches to large-scale meta-analyses of genome-wide data on migraine (23,285 cases and 95,425 controls) and IS (12,389 cases and 62,004 controls). First, we queried known genome-wide significant loci for both disorders, looking for potential overlap of signals. We then analyzed the overall shared genetic load using polygenic scores and estimated the genetic correlation between disease subtypes using data derived from these models. We further interrogated genomic regions of shared risk using analysis of covariance patterns between the 2 phenotypes using cross-phenotype spatial mapping. RESULTS: We found substantial genetic overlap between migraine and IS using all 4 approaches. Migraine without aura (MO) showed much stronger overlap with IS and its subtypes than migraine with aura (MA). The strongest overlap existed between MO and large artery stroke (LAS; p = 6.4 × 10(-28) for the LAS polygenic score in MO) and between MO and cardioembolic stroke (CE; p = 2.7 × 10(-20) for the CE score in MO). CONCLUSIONS: Our findings indicate shared genetic susceptibility to migraine and IS, with a particularly strong overlap between MO and both LAS and CE pointing towards shared mechanisms. Our observations on MA are consistent with a limited role of common genetic variants in this subtype.
Keywords: Brain Ischemia; Genome-Wide Association Study; Humans; Migraine with Aura; Migraine without Aura; Stroke

Social Network Size and Cranial Magnetic Resonance Imaging Findings in Older Adults: The Cardiovascular Health Study. - Flatt, Jason D; Rosso, Andrea L; Aizenstein, Howard J; Schulz, Richard; Longstreth, W T; Newman, Anne B; Fowler, Nicole R; Rosano, Caterina (J Am Geriatr Soc, 2015)
Keywords: Aged; Brain; Cardiovascular Diseases; Cross-Sectional Studies; Female; Geriatric Assessment; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Social Participation; Social Support

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

Association of Smoking, Alcohol, and Obesity with Cardiovascular Death and Ischemic Stroke in Atrial Fibrillation: The Atherosclerosis Risk in Communities (ARIC) Study and Cardiovascular Health Study (CHS). - Kwon, Younghoon; Norby, Faye L; Jensen, Paul N; Agarwal, Sunil K; Soliman, Elsayed Z; Lip, Gregory Y H; Longstreth, W T; Alonso, Alvaro; Heckbert, Susan R; Chen, Lin Y (PLoS One, 2016)
Atrial fibrillation (AF) is associated with an increased risk of ischemic stroke and cardiovascular (CV) death. Whether modifiable lifestyle risk factors are associated with these CV outcomes in AF is unknown. Among Atherosclerosis Risk in Communities (ARIC) study and Cardiovascular Health Study (CHS) participants with incident AF, we estimated the risk of composite endpoint of ischemic stroke or CV death associated with candidate modifiable risk factor (smoking, heavy alcohol consumption, or high body mass index [BMI]), and computed the C-statistic, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) of incorporating each factor into the CHA2DS2-VASc. Among 1222 ARIC (mean age: 63.4) and 756 CHS (mean age: 79.1) participants with incident AF, during mean follow-up of 6.9 years and 5.7 years, there were 332 and 335 composite events respectively. Compared with never smokers, current smokers had a higher incidence of the composite endpoint in ARIC [HR: 1.65 (1.21-2.26)] but not in CHS [HR: 1.05 (0.69-1.61)]. In ARIC, the addition of current smoking did not improve risk prediction over and above the CHA2DS2-VASc. No significant associations were observed with alcohol consumption or BMI with CVD outcomes in AF patients from either cohort. Smoking is associated with an increased risk of ischemic stroke or CV death in ARIC, which comprised mostly middle-aged to young-old (65-74 years), but not in CHS, which comprised mostly middle-old or oldest-old (≥75 years) adults with AF. However, addition of smoking to the CHA2DS2-VASc score did not improve risk prediction of these outcomes.
Keywords: Aged; Alcohol Drinking; Atrial Fibrillation; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Obesity; Smoking; Stroke

Brain natriuretic peptide and insulin resistance in older adults. - Kim, F; Biggs, M L; Kizer, J R; Brutsaert, E F; de Fillipi, C; Newman, A B; Kronmal, R A; Tracy, R P; Gottdiener, J S; Djoussé, L; de Boer, I H; Psaty, B M; et al. (Diabet Med, 2016)
AIMS: Higher levels of brain natriuretic peptide (BNP) have been associated with a decreased risk of diabetes in adults, but whether BNP is related to insulin resistance in older adults has not been established. METHODS: N-Terminal (NT)-proBNP was measured among Cardiovascular Health Study participants at the 1989-1990, 1992-1993 and 1996-1997 examinations. We calculated measures of insulin resistance [homeostatic model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI), Gutt index, Matsuda index] from fasting and 2-h concentrations of glucose and insulin among 3318 individuals with at least one measure of NT-proBNP and free of heart failure, coronary heart disease and chronic kidney disease, and not taking diabetes medication. We used generalized estimating equations to assess the cross-sectional association of NT-proBNP with measures of insulin resistance. Instrumental variable analysis with an allele score derived from nine genetic variants (single nucleotide polymorphisms) within or near the NPPA and NPPB loci was used to estimate an un-confounded association of NT-proBNP levels on insulin resistance. RESULTS: Lower NT-proBNP levels were associated with higher insulin resistance even after adjustment for BMI, waist circumference and other risk factors (P < 0.001 for all four indices). Although the genetic score was strongly related to measured NT-proBNP levels amongst European Americans (F statistic = 71.08), we observed no association of genetically determined NT-proBNP with insulin resistance (P = 0.38; P = 0.01 for comparison with the association of measured levels of NT-proBNP). CONCLUSIONS: In older adults, lower NT-proBNP is associated with higher insulin resistance, even after adjustment for traditional risk factors. Because related genetic variants were not associated with insulin resistance, the causal nature of this association will require future study. This article is protected by copyright. All rights reserved.

Can a Healthy Lifestyle Compress the Disabled Period in Older Adults? - Jacob, Mini E; Yee, Laura M; Diehr, Paula H; Arnold, Alice M; Thielke, Stephen M; Chaves, Paulo H M; Gobbo, Liana Del; Hirsch, Calvin; Siscovick, David; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine whether lifestyle factors, measured late in life, could compress the disabled period toward the end of life. DESIGN: Community-based cohort study of older adults followed from 1989 to 2015. SETTING: Four U.S. communities. PARTICIPANTS: Community-living men and women aged 65 and older (N = 5,248, mean age 72.7 ± 5.5, 57% female, 15.2% minority) who were not wheelchair dependent and were able to give informed consent at baseline. MEASUREMENTS: Multiple lifestyle factors, including smoking, alcohol consumption, physical activity, diet, body mass index (BMI), social networks, and social support, were measured at baseline. Activities of daily living (ADLs) were assessed at baseline and throughout follow-up. Years of life (YoL) was defined as years until death. Years of able life (YAL) was defined as years without any ADL difficulty. YAL/YoL%, the proportion of life lived able, was used to indicate the relative compression or expansion of the disabled period. RESULTS: The average duration of disabled years was 4.5 (out of 15.4 mean YoL) for women and 2.9 (out of 12.4 mean YoL) for men. In a multivariable model, obesity was associated with 7.3 percentage points (95% confidence interval (CI) = 5.4-9.2) lower YAL/YoL% than normal weight. Scores in the lowest quintile of the Alternate Healthy Eating Index were associated with a 3.7% (95% CI = 1.6-5.9) lower YAL/YoL% than scores in the highest quintile. Every 25 blocks walked in a week was associated with 0.5 percentage points (95% CI = 0.3-0.8) higher YAL/YoL%. CONCLUSION: The effects of healthy lifestyle factors on the proportion of future life lived free of disability indicate that the disabled period can be compressed, given the right combination of these factors.

Development and Validation of a Sudden Cardiac Death Prediction Model for the General Population. - Deo, Rajat; Norby, Faye L; Katz, Ronit; Sotoodehnia, Nona; Adabag, Selcuk; deFilippi, Christopher R; Kestenbaum, Bryan; Chen, Lin Y; Heckbert, Susan R; Folsom, Aaron R; Kronmal, Richard A; Konety, Suma; et al. (Circulation, 2016)
BACKGROUND: Most sudden cardiac death (SCD) events occur in the general population among persons who do not have any prior history of clinical heart disease. We sought to develop a predictive model of SCD among US adults. METHODS: We evaluated a series of demographic, clinical, laboratory, electrocardiographic, and echocardiographic measures in participants in the ARIC study (Atherosclerosis Risk in Communities) (n=13 677) and the CHS (Cardiovascular Health Study) (n=4207) who were free of baseline cardiovascular disease. Our initial objective was to derive a SCD prediction model using the ARIC cohort and validate it in CHS. Independent risk factors for SCD were first identified in the ARIC cohort to derive a 10-year risk model of SCD. We compared the prediction of SCD with non-SCD and all-cause mortality in both the derivation and validation cohorts. Furthermore, we evaluated whether the SCD prediction equation was better at predicting SCD than the 2013 American College of Cardiology/American Heart Association Cardiovascular Disease Pooled Cohort risk equation. RESULTS: There were a total of 345 adjudicated SCD events in our analyses, and the 12 independent risk factors in the ARIC study included age, male sex, black race, current smoking, systolic blood pressure, use of antihypertensive medication, diabetes mellitus, serum potassium, serum albumin, high-density lipoprotein, estimated glomerular filtration rate, and QTc interval. During a 10-year follow-up period, a model combining these risk factors showed good to excellent discrimination for SCD risk (c-statistic 0.820 in ARIC and 0.745 in CHS). The SCD prediction model was slightly better in predicting SCD than the 2013 American College of Cardiology/American Heart Association Pooled Cohort risk equations (c-statistic 0.808 in ARIC and 0.743 in CHS). Only the SCD prediction model, however, demonstrated similar and accurate prediction for SCD using both the original, uncalibrated score and the recalibrated equation. Finally, in the echocardiographic subcohort, a left ventricular ejection fraction <50% was present in only 1.1% of participants and did not enhance SCD prediction. CONCLUSIONS: Our study is the first to derive and validate a generalizable risk score that provides well-calibrated, absolute risk estimates across different risk strata in an adult population of white and black participants without a clinical diagnosis of cardiovascular disease.

Diagnostic Yield and Clinical Utility of Sequencing Familial Hypercholesterolemia Genes in Patients With Severe Hypercholesterolemia. - Khera, Amit V; Won, Hong-Hee; Peloso, Gina M; Lawson, Kim S; Bartz, Traci M; Deng, Xuan; van Leeuwen, Elisabeth M; Natarajan, Pradeep; Emdin, Connor A; Bick, Alexander G; Morrison, Alanna C; Brody, Jennifer A; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Approximately 7% of American adults have severe hypercholesterolemia (untreated low-density lipoprotein [LDL] cholesterol ≥190 mg/dl), which may be due to familial hypercholesterolemia (FH). Lifelong LDL cholesterol elevations in FH mutation carriers may confer coronary artery disease (CAD) risk beyond that captured by a single LDL cholesterol measurement. OBJECTIVES: This study assessed the prevalence of an FH mutation among those with severe hypercholesterolemia and determined whether CAD risk varies according to mutation status beyond the observed LDL cholesterol level. METHODS: Three genes causative for FH (LDLR, APOB, and PCSK9) were sequenced in 26,025 participants from 7 case-control studies (5,540 CAD case subjects, 8,577 CAD-free control subjects) and 5 prospective cohort studies (11,908 participants). FH mutations included loss-of-function variants in LDLR, missense mutations in LDLR predicted to be damaging, and variants linked to FH in ClinVar, a clinical genetics database. RESULTS: Among 20,485 CAD-free control and prospective cohort participants, 1,386 (6.7%) had LDL cholesterol ≥190 mg/dl; of these, only 24 (1.7%) carried an FH mutation. Within any stratum of observed LDL cholesterol, risk of CAD was higher among FH mutation carriers than noncarriers. Compared with a reference group with LDL cholesterol <130 mg/dl and no mutation, participants with LDL cholesterol ≥190 mg/dl and no FH mutation had a 6-fold higher risk for CAD (odds ratio: 6.0; 95% confidence interval: 5.2 to 6.9), whereas those with both LDL cholesterol ≥190 mg/dl and an FH mutation demonstrated a 22-fold increased risk (odds ratio: 22.3; 95% confidence interval: 10.7 to 53.2). In an analysis of participants with serial lipid measurements over many years, FH mutation carriers had higher cumulative exposure to LDL cholesterol than noncarriers. CONCLUSIONS: Among participants with LDL cholesterol ≥190 mg/dl, gene sequencing identified an FH mutation in <2%. However, for any observed LDL cholesterol, FH mutation carriers had substantially increased risk for CAD.

Digit Symbol Substitution test and future clinical and subclinical disorders of cognition, mobility and mood in older adults. - Rosano, Caterina; Perera, Subashan; Inzitari, Marco; Newman, Anne B; Longstreth, William T; Studenski, Stephanie (Age Ageing, 2016)
OBJECTIVE: to examine whether psychomotor speed predicts individual and combined disorders in cognition, mobility and mood and if white matter hyperintensities explain these associations. DESIGN AND SETTING: longitudinal; Cardiovascular Health Study. SUBJECTS: 5,888 participants (57.6% women, 15.7% black, 75.1 (5.5), mean years (SD)). METHODS: psychomotor speed (Digit Symbol Substitution Test (DSST)) and small vessel disease (white matter hyperintensities (WMH)) were measured in 1992-94. Global cognition (Modified Mini-Mental State (3MS) examination), mobility (gait speed (GS)) and mood (Center for Epidemiologic Studies Depression (CES-D) scale) were measured annually over 5 years and classified as clinical, subclinical or no disorders based on established values (3MS: 80 and 85 points; GS: 0.6 and 1.0 m/s; CES-D: 10 and 5 points). Analyses were adjusted for demographics, baseline status, education, diabetes, hypertension, ankle-arm index. RESULTS: among those with no disorder in cognition, mobility and mood (N = 619) in 1992-94, being in the lowest DSST quartile compared to the highest was associated with nearly twice the odds of developing 1+ clinical or subclinical disorders (N = 413) during follow-up. Associations were stronger for incident clinical disorders in cognition (OR: 8.44, p < 0.01) or mobility (OR: 9.09, p < 0.05) than for mood (OR: 1.88, p < 0.10). Results were similar after adjustment for WMH. CONCLUSIONS: slower psychomotor speed may serve as a biomarker of risk of clinical disorders of cognition, mobility and mood. While in part attributable to vascular brain disease, other potentially modifiable contributors may be present. Further studying the causes of psychomotor slowing with ageing might provide novel insights into age-related brain disorders.

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

Dyspnea in Community-Dwelling Older Persons: A Multifactorial Geriatric Health Condition. - Miner, Brienne; Tinetti, Mary E; Van Ness, Peter H; Han, Ling; Leo-Summers, Linda; Newman, Anne B; Lee, Patty J; Vaz Fragoso, Carlos A (J Am Geriatr Soc, 2016)
OBJECTIVES: To evaluate the associations between a broad array of cardiorespiratory and noncardiorespiratory impairments and dyspnea in older persons. DESIGN: Cross-sectional. SETTING: Cardiovascular Health Study. PARTICIPANTS: Community-dwelling persons (N = 4,413; mean age 72.6, 57.1% female, 4.5% African American, 27.2% <high school education, 54.7% ever-smokers). MEASUREMENTS: Dyspnea severity (moderate to severe defined as American Thoracic Society Grade ≥2) and several impairments, including those established using spirometry (forced expiratory volume in 1 second (FEV1 )), maximal inspiratory pressure (respiratory muscle strength), echocardiography, ankle-brachial index, blood pressure, whole-body muscle mass (bioelectrical impedance), single chair stand (lower extremity function), grip strength, serum hemoglobin and creatinine, Center for Epidemiologic Studies Depression Scale (CES-D), Mini-Mental State Examination, medication use, and body mass index (BMI). RESULTS: In a multivariable logistic regression model, impairments that had strong associations with moderate to severe dyspnea were FEV1 less than the lower limit of normal (adjusted odds ratio (aOR) = 2.88, 95% confidence interval (CI) = 2.37-3.49), left ventricular ejection fraction less than 45% (aOR = 2.12, 95% CI = 1.43, 3.16), unable to perform a single chair stand (aOR = 2.10, 95% CI = 1.61-2.73), depressive symptoms (CES-D score ≥16; aOR = 2.02, 95% CI = 1.26-3.23), and obesity (BMI ≥30; aOR = 2.07, 95% CI = 1.67-2.55). Impairments with modest but still statistically significant associations with moderate to severe dyspnea included respiratory muscle weakness, diastolic cardiac dysfunction, grip weakness, anxiety symptoms, and use of cardiovascular and psychoactive medications (aORs = 1.31-1.71). CONCLUSION: In community-dwelling older persons, several cardiorespiratory and noncardiorespiratory impairments were significantly associated with moderate to severe dyspnea, akin to a multifactorial geriatric health condition.

Echocardiographic Predictors of Sudden Cardiac Death: The Atherosclerosis Risk in Communities Study and Cardiovascular Health Study. - Konety, Suma H; Koene, Ryan J; Norby, Faye L; Wilsdon, Tony; Alonso, Alvaro; Siscovick, David; Sotoodehnia, Nona; Gottdiener, John; Fox, Ervin R; Chen, Lin Y; Adabag, Selcuk; Folsom, Aaron R (Circ Cardiovasc Imaging, 2016)
BACKGROUND: This study assessed the echocardiographic predictors of sudden cardiac death (SCD) within 2 population-based cohorts. METHODS AND RESULTS: Echocardiograms were obtained on 2383 participants (1993-1995) from the ARIC study (Atherosclerosis Risk in Communities; 100% black) and 5366 participants (1987-1989 and 1994-1995) from the CHS (Cardiovascular Health Study). The main outcome was physician-adjudicated SCD. We used Cox proportional-hazards models with incident coronary heart disease and heart failure as time-dependent covariates to assess the association between echocardiographic variables and SCD, adjusting for Framingham risk score variables, coronary heart disease, and renal function. Cohort-specific results were meta-analyzed. During a median follow-up of 7.3 and 13.1 years, 44 ARIC study participants and 275 CHS participants had SCD, respectively. In the meta-analyzed results, the adjusted hazard ratios (95% confidence intervals) for predictors of SCD were 3.07 (2.29-4.11) for reduced left ventricular ejection fraction; 1.85 (1.36-2.52) for mitral annular calcification; 1.64 (1.07-2.51) for mitral E/A >1.5, and 1.52 (1.14-2.02) for mitral E/A <0.7 (versus mitral E/A 0.7-1.5); 1.30 (1.15-1.48) per 1 SD increase in left ventricular mass; and 1.15 (1.02-1.30) per 1 SD increase in left atrial diameter. A receiver-operating characteristic model for prediction of SCD using Framingham risk score variables had a C statistic of 0.61 for ARIC study and 0.67 for CHS; the full multivariable model including all echocardiographic variables had a C statistic of 0.76 for ARIC study and 0.74 for CHS. CONCLUSIONS: In addition to reduced left ventricular ejection fraction, we identified other echocardiographic-derived variables predictive for SCD that provided incremental value compared with clinical risk factors.

Effects of Disease Burden and Functional Adaptation on Morbidity and Mortality on Older Adults. - Sanders, Jason L; Arnold, Alice M; Hirsch, Calvin H; Thielke, Stephen M; Kim, Dae; Mukamal, Kenneth J; Kizer, Jorge R; Ix, Joachim H; Kaplan, Robert C; Kritchevsky, Stephen B; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To ascertain whether older adults with extensive disease but relative vigor (adapters) shorten the period at the end of life in which they live with morbidity (compress morbidity). DESIGN: Prospective, community-based cohort study in four U.S. cities. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older. MEASUREMENTS: Participants were categorized into three groups according to extent of disease (assessed noninvasively), vigor, and frailty (expected agers (n = 3,528, extent of disease similar to vigor and frailty-reference group), adapters (n = 882, higher disease but vigorous), and prematurely frail (n = 855, lower disease but frail)) and compared according to years of able life (YAL), years of self-reported healthy life (YHL), and mortality using multivariable regression and survival analysis. RESULTS: After adjustment, adapters had 0.97 (95% confidence interval (CI) = 0.60-1.33) more YAL and 0.54 (95% CI = 0.19-0.90) more YHL than expected agers, and those who were prematurely frail had -0.99 (95% CI = -1.36 to -0.62) fewer YAL and -0.53 (95% CI = -0.89 to -0.17) fewer YHL than expected agers. Adapters had 0.9 more and prematurely frail had 1.5 fewer years of total life than expected agers (P < .001). Adapters spent 55% of their remaining life able and healthy, those who were prematurely frail spent 37%, and of expected agers spent 47% (P < .001). CONCLUSION: Despite similar levels of disease burden, older adults who were more vigorous appeared to compress morbidity and live longer. Older adults with higher frailty lengthened morbidity and had greater mortality. Adaptive factors may compress morbidity and decrease mortality.

Electrocardiographic Predictors of Incident Atrial Fibrillation. - Nguyen, Kaylin T; Vittinghoff, Eric; Dewland, Thomas A; Mandyam, Mala C; Stein, Phyllis K; Soliman, Elsayed Z; Heckbert, Susan R; Marcus, Gregory M (Am J Cardiol, 2016)
Atrial fibrillation (AF) is likely secondary to multiple different pathophysiological mechanisms that are increasingly but incompletely understood. Motivated by the hypothesis that 3 previously described electrocardiographic predictors of AF identify distinct AF mechanisms, we sought to determine if these electrocardiographic findings independently predict incident disease. Among Cardiovascular Health Study participants without prevalent AF, we determined whether left anterior fascicular block (LAFB), a prolonged QTC, and atrial premature complexes (APCs) each predicted AF after adjusting for each other. We then calculated the attributable risk in the exposed for each electrocardiographic marker. LAFB and QTC intervals were assessed on baseline 12-lead electrocardiogram (n = 4,696). APC count was determined using 24-hour Holter recordings obtained in a random subsample (n = 1,234). After adjusting for potential confounders and each electrocardiographic marker, LAFB (hazard ratio [HR] 2.1, 95% confidence interval [CI] 1.1 to 3.9, p = 0.023), a prolonged QTC (HR 2.5, 95% CI 1.4 to 4.3, p = 0.002), and every doubling of APC count (HR 1.2, 95% CI 1.1 to 1.3, p <0.001) each remained independently predictive of incident AF. The attributable risk of AF in the exposed was 35% (95% CI 13% to 52%) for LAFB, 25% (95% CI 0.6% to 44%) for a prolonged QTC, and 34% (95% CI 26% to 42%) for APCs. In conclusion, in a community-based cohort, 3 previously established electrocardiogram-derived AF predictors were each independently associated with incident AF, suggesting that they may represent distinct mechanisms underlying the disease.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

Gait Speed Predicts Incident Disability: A Pooled Analysis. - Perera, Subashan; Patel, Kushang V; Rosano, Caterina; Rubin, Susan M; Satterfield, Suzanne; Harris, Tamara; Ensrud, Kristine; Orwoll, Eric; Lee, Christine G; Chandler, Julie M; Newman, Anne B; Cauley, Jane A; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Functional independence with aging is an important goal for individuals and society. Simple prognostic indicators can inform health promotion and care planning, but evidence is limited by heterogeneity in measures of function. METHODS: We performed a pooled analysis of data from seven studies of 27,220 community-dwelling older adults aged 65 or older with baseline gait speed, followed for disability and mortality. Outcomes were incident inability or dependence on another person in bathing or dressing; and difficulty walking ¼ - ½ mile or climbing 10 steps within 3 years. RESULTS: Participants with faster baseline gait had lower rates of incident disability. In subgroups (defined by 0.2 m/s-wide intervals from <0.4 to ≥ 1.4 m/s) with increasingly greater gait speed, 3-year rates of bathing or dressing dependence trended from 10% to 1% in men, and from 15% to 1% in women, while mobility difficulty trended from 47% to 4% in men and 40% to 6% in women. The age-adjusted relative risk ratio per 0.1 m/s greater speed for bathing or dressing dependence in men was 0.68 (0.57-0.81) and in women: 0.74 (0.66-0.82); for mobility difficulty, men: 0.75 (0.68-0.82), women: 0.73 (0.67-0.80). Results were similar for combined disability and mortality. Effects were largely consistent across subgroups based on age, gender, race, body mass index, prior hospitalization, and selected chronic conditions. In the presence of multiple other risk factors for disability, gait speed significantly increased the area under the receiver operator characteristic curve. CONCLUSION: In older adults, gait speed predicts 3 year incidence of bathing or dressing dependence, mobility difficulty, and a composite outcome of disability and mortality.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cohort Studies; Disability Evaluation; Disabled Persons; Female; Gait; Geriatric Assessment; Humans; Independent Living; Male; Mobility Limitation; Predictive Value of Tests; Prognosis; Psychomotor Performance; Risk Assessment; Risk Factors; ROC Curve; Survival Analysis; United States

{Gene-gene Interaction Analyses for Atrial Fibrillation - Lin, H.; Mueller-Nurasyid, M.; Smith, A. V.; Arking, D. E.; Barnard, J.; Bartz, T. M.; Lunetta, K. L.; Lohman, K.; Kleber, M. E.; Lubitz, S. A.; Geelhoed, B.; Trompet, S.; et al. (Sci Rep, 2016)
{Atrial fibrillation (AF) is a heritable disease that affects more than thirty million individuals worldwide. Extensive efforts have been devoted to the study of genetic determinants of AF. The objective of our study is to examine the effect of gene-gene interaction on AF susceptibility. We performed a large-scale association analysis of gene-gene interactions with AF in 8,173 AF cases, and 65,237 AF-free referents collected from 15 studies for discovery. We examined putative interactions between genome-wide SNPs and 17 known AF-related SNPs. The top interactions were then tested for association in an independent cohort for replication, which included more than 2,363 AF cases and 114,746 AF-free referents. One interaction, between rs7164883 at the HCN4 locus and rs4980345 at the SLC28A1 locus, was found to be significantly associated with AF in the discovery cohorts (interaction OR = 1.44, 95% CI: 1.27-1.65

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

A genome-wide association study meta-analysis of clinical fracture in 10,012 African American women. - Taylor, Kira C; Evans, Daniel S; Edwards, Digna R Velez; Edwards, Todd L; Sofer, Tamar; Li, Guo; Liu, Youfang; Franceschini, Nora; Jackson, Rebecca D; Giri, Ayush; Donneyong, Macarius; Psaty, Bruce; et al. (Bone Rep, 2016)
BACKGROUND: Osteoporosis is a major public health problem associated with excess disability and mortality. It is estimated that 50-70% of the variation in osteoporotic fracture risk is attributable to genetic factors. The purpose of this hypothesis-generating study was to identify possible genetic determinants of fracture among African American (AA) women in a GWAS meta-analysis. METHODS: Data on clinical fractures (all fractures except fingers, toes, face, skull or sternum) were analyzed among AA female participants in the Women's Health Initiative (WHI) (N = 8155), Cardiovascular Health Study (CHS) (N = 504), BioVU (N = 704), Health ABC (N = 651), and the Johnston County Osteoarthritis Project (JoCoOA) (N = 291). Affymetrix (WHI) and Illumina (Health ABC, JoCoOA, BioVU, CHS) GWAS panels were used for genotyping, and a 1:1 ratio of YRI:CEU HapMap haplotypes was used as an imputation reference panel. We used Cox proportional hazard models or logistic regression to evaluate the association of ~ 2.5 million SNPs with fracture risk, adjusting for ancestry, age, and geographic region where applicable. We conducted a fixed-effects, inverse variance-weighted meta-analysis. Genome-wide significance was set at P < 5 × 10- 8. RESULTS: One SNP, rs12775980 in an intron of SVIL on chromosome 10p11.2, reached genome-wide significance (P = 4.0 × 10- 8). Although this SNP has a low minor allele frequency (0.03), there was no evidence for heterogeneity of effects across the studies (I2 = 0). This locus was not reported in any previous osteoporosis-related GWA studies. We also interrogated previously reported GWA-significant loci associated with fracture or bone mineral density in our data. One locus (SMOC1) generalized, but overall there was not substantial evidence of generalization. Possible reasons for the lack of generalization are discussed. CONCLUSION: This GWAS meta-analysis of fractures in African American women identified a potentially novel locus in the supervillin gene, which encodes a platelet-associated factor and was previously associated with platelet thrombus formation in African Americans. If validated in other populations of African descent, these findings suggest potential new mechanisms involved in fracture that may be particularly important among African Americans.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

Insulinlike growth factor binding protein-1 and ghrelin predict health outcomes among older adults: CHS cohort. - Kaplan, Robert C; Strizich, Garrett; Aneke-Nash, Chino; Dominguez-Islas, Clara; Bůzková, Petra; Strickler, Howard; Rohan, Thomas; Pollak, Michael; Kuller, Lewis; Kizer, Jorge R; Cappola, Anne; Li, Christopher I; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: Multiple diseases may explain the association of the growth hormone / insulinlike growth factor-I (GH/IGF-I) axis with longevity. OBJECTIVE: To relate circulating GH/IGF-I system protein levels with major health events. DESIGN: Cohort study Setting: Four US communities Participants: Adults (n=2268) 65 years and older free of diabetes and cardiovascular disease. MEASUREMENTS: We assessed insulinlike growth factor binding protein-1 (IGFBP-1) and ghrelin in fasting and 2-hour oral glucose tolerance test (OGTT) blood samples, as well as fasting IGF-I and IGFBP-3. Hazard ratios for mortality and a composite outcome for first incident myocardial infarction, stroke, heart failure, hip fracture, or death were adjusted for sociodemographic, behavioral, and physiologic covariates. RESULTS: During 13,930 person-years of follow-up, 48.1% individuals sustained one or more components of the composite outcome and 31.8% died. Versus the lowest quartiles, the highest quartiles of fasting and 2-h ghrelin were associated with a 27% higher (95% CI: 6%, 53%) and 39% higher (95% CI: 14%, 71%) risks of the composite outcome, respectively. The highest quartile of 2-h IGFBP-1 was associated with 35% higher (95% CI: 1%, 52%) risk of the composite endpoint. Similarly, higher mortality was significantly associated with higher fasting and 2-h ghrelin level, and with 2-h IGFBP-1 level. When examined together, 2-h post-OGTT levels of IGFBP-1 and ghrelin tended to predict outcomes better than fasting levels. CONCLUSIONS: Circulating IGFBP-1 and ghrelin measured during an OGTT predict major health events and death in older adults, which may explain the influence of the GH-IGF-axis on lifespan and health.

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Large-scale pharmacogenomic study of sulfonylureas and the QT, JT and QRS intervals: CHARGE Pharmacogenomics Working Group. - Floyd, J S; Sitlani, C M; Avery, C L; Noordam, R; Li, X; Smith, A V; Gogarten, S M; Li, J; Broer, L; Evans, D S; Trompet, S; Brody, J A; et al. (Pharmacogenomics J, 2016)
Sulfonylureas, a commonly used class of medication used to treat type 2 diabetes, have been associated with an increased risk of cardiovascular disease. Their effects on QT interval duration and related electrocardiographic phenotypes are potential mechanisms for this adverse effect. In 11 ethnically diverse cohorts that included 71 857 European, African-American and Hispanic/Latino ancestry individuals with repeated measures of medication use and electrocardiogram (ECG) measurements, we conducted a pharmacogenomic genome-wide association study of sulfonylurea use and three ECG phenotypes: QT, JT and QRS intervals. In ancestry-specific meta-analyses, eight novel pharmacogenomic loci met the threshold for genome-wide significance (P<5 × 10(-8)), and a pharmacokinetic variant in CYP2C9 (rs1057910) that has been associated with sulfonylurea-related treatment effects and other adverse drug reactions in previous studies was replicated. Additional research is needed to replicate the novel findings and to understand their biological basis.The Pharmacogenomics Journal advance online publication, 13 December 2016; doi:10.1038/tpj.2016.90.

Lipoprotein-Associated Phospholipase A2 and Incident Peripheral Arterial Disease in Older Adults: The Cardiovascular Health Study. - Garg, Parveen K; Arnold, Alice M; Hinckley Stukovsky, Karen D; Koro, Carol; Jenny, Nancy S; Mukamal, Kenneth J; Criqui, Michael H; Furberg, Curt D; Newman, Anne B; Cushman, Mary (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Although prior studies report a relationship between elevated lipoprotein-associated phospholipase A2 (Lp-PLA2) and incident cardiovascular disease, the prospective association of Lp-PLA2 with incident peripheral arterial disease (PAD) has not been studied. We investigated the association between Lp-PLA2 mass and activity and the risk of developing clinical PAD and low ankle-brachial index (ABI). APPROACH AND RESULTS: Among Cardiovascular Health Study participants, a population-based cohort of 5888 adults aged ≥65 years enrolled in 1989 to 1990, Lp-PLA2 mass and activity were measured in 4537 individuals without baseline PAD. Clinical PAD, defined as leg artery revascularization or diagnosed claudication, was ascertained through 2011. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among 3537 individuals who had an ABI >0.9 at baseline and a second ABI measurement 3 or 6 years later. Analyses were adjusted for demographics, cholesterol, smoking, comorbidities, and C-reactive protein. Each standard deviation increment in Lp-PLA2 mass (117 ng/mL) was associated with a higher risk of developing clinical PAD (hazard ratio 1.28; 95% confidence interval 1.13, 1.45) and incident low ABI (odds ratio 1.16; 95% confidence interval 1.00, 1.33). Results per standard deviation increment in Lp-PLA2 activity (13 nmol/min per mL) were similar for clinical PAD (hazard ratio 1.24; 95% confidence interval 1.07, 1.44) and low ABI (odds ratio 1.28; 95% confidence interval 1.09, 1.50). CONCLUSIONS: Higher Lp-PLA2 mass and activity were associated with development of both incident clinical PAD and low ABI. Future studies are needed to determine whether pharmacological inhibition of Lp-PLA2 reduces the incidence of PAD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Age Factors; Aged; Aging; Ankle Brachial Index; Biomarkers; Chi-Square Distribution; Female; Humans; Incidence; Inflammation Mediators; Logistic Models; Male; Odds Ratio; Peripheral Arterial Disease; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Boerwinkle, Eric; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

Risk of dementia and death in the long-term follow-up of the Pittsburgh Cardiovascular Health Study-Cognition Study. - Kuller, Lewis H; Lopez, Oscar L; Becker, James T; Chang, Yuefang; Newman, Anne B (Alzheimers Dement, 2016)
INTRODUCTION: Increasing life expectancy has resulted in a larger population of older individuals at risk of dementia. METHODS: The Cardiovascular Health Study-Cognition Study followed 532 participants from 1998-99 (mean age 79) to 2013 (mean age 93) for death and dementia. RESULTS: Risk of death was determined by extent of coronary artery calcium, high-sensitivity cardiac troponin, brain natriuretic peptide, and white matter grade. Significant predictors of dementia were age, apolipoprotein-E4, vocabulary raw score, hippocampal volume, ventricular size, cognitive performance, and number of blocks walked. By 2013, 160 of 532 were alive, including 19 cognitively normal. Those with normal cognition had higher grade education, better cognition test scores, greater hippocampal volume, faster gait speed, and number of blocks walked as compared with survivors who were demented. DISCUSSION: Few survived free of dementia and disability. Prevention and delay of cognitive decline for this older population is an imperative.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Apolipoprotein E4; Brain; Cardiovascular Diseases; Cognition; Dementia; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Pennsylvania; Risk Factors; Walking

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Subclinical Cardiovascular Disease and Death, Dementia, and Coronary Heart Disease in Patients 80+ Years. - Kuller, Lewis H; Lopez, Oscar L; Mackey, Rachel H; Rosano, Caterina; Edmundowicz, Daniel; Becker, James T; Newman, Anne B (J Am Coll Cardiol, 2016)
BACKGROUND: The successful prevention and treatment of coronary heart disease (CHD) and stroke has resulted in a substantial increase in longevity, with subsequent growth in the population of older people at risk for dementia. OBJECTIVES: The authors evaluated the relationship of coronary and other peripheral atherosclerosis to risk of death, dementia, and CHD in the very elderly. Because the extent of vascular disease differs substantially between men and women, sex- and race-specific analyses were included, with a specific focus on women with low coronary artery calcium (CAC) Agatston scores. METHODS: We evaluated the relationship between measures of subclinical cardiovascular disease (CAC, carotid intimal medial thickness, stenosis, and ankle brachial index) and risk of dementia, CHD, and total mortality in 532 participants of the Cardiovascular Health Study-Cognition Study from 1998/1999 (mean age, 80 years) to 2012/2013 (mean age, 93 years). RESULTS: Thirty-six percent of participants had CAC scores >400. Women and African-Americans had lower CAC scores. Few men had low CAC scores. CAC score and number of coronary calcifications were directly related to age-adjusted total mortality and CHD. The age-specific incidence of dementia was higher than for CHD. Only about 25% of deaths were caused by CHD and 16% by dementia. Approximately 64% of those who died had a prior diagnosis of dementia. White women with low CAC scores had a significantly decreased incidence of dementia. CONCLUSIONS: In subjects 80+ years of age, there is a greater incidence of dementia than of CHD. CAC, as a marker of atherosclerosis, is a determinant of mortality, and risk of CHD and myocardial infarction. White women with low CAC scores had a significantly decreased risk of dementia. A very important unanswered question, especially in the very elderly, is whether prevention of atherosclerosis and its complications is associated with less Alzheimer disease pathology and dementia. (Cardiovascular Health Study [CHS]; NCT00005133).
Keywords: Age Factors; Aged, 80 and over; Cause of Death; Coronary Artery Disease; Dementia; Female; Humans; Incidence; Male; Pennsylvania; Retrospective Studies; Risk Factors; Survival Rate

Targeted Sequencing of Genome Wide Significant Loci Associated with Bone Mineral Density (BMD) Reveals Significant Novel and Rare Variants: The Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Gibbs, Richard A; et al. (Hum Mol Genet, 2016)
BACKGROUND: Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. METHODS AND RESULTS: Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study (n=925) and Cardiovascular Health Study (n=366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS, ARHGAP1, and 5' of MEF2C (p-values < 8x10(-5); false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. CONCLUSIONS: Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trajectories of function and biomarkers with age: the CHS All Stars Study. - Newman, Anne B; Sanders, Jason L; Kizer, Jorge R; Boudreau, Robert M; Odden, Michelle C; Zeki Al Hazzouri, Adina; Arnold, Alice M (Int J Epidemiol, 2016)
BACKGROUND: Multimorbidity is a major driver of physical and cognitive impairment, but rates of decline are also related to ageing. We sought to determine trajectories of decline in a large cohort by disease status, and examined their correspondence with biomarkers of ageing processes including growth hormone, sex steroid, inflammation, visceral adiposity and kidney function pathways. METHODS: We have followed the 5888 participants in the Cardiovascular Health Study (CHS) for healthy ageing and longevity since 1989-90. Gait speed, grip strength, modified mini-mental status examination (3MSE) and the digit symbol substitution test (DSST) were assessed annually to 1998-99 and again in 2005-06. Insulin-like growth hormone (IGF-1), dehydroepiandrosterone sulphate (DHEAS), interleukin-6 (IL-6), adiponectin and cystatin-C were assessed 3-5 times from stored samples. Health status was updated annually and dichotomized as healthy vs not healthy. Trajectories for each function measure and biomarker were estimated using generalized estimating equations as a function of age and health status using standardized values. RESULTS: Trajectories of functional decline showed strong age acceleration late in life in healthy older men and women as well as in chronically ill older adults. Adiponectin, IL-6 and cystatin-C tracked with functional decline in all domains; cystatin-C was consistently associated with functional declines independent of other biomarkers. DHEAS was independently associated with grip strength and IL-6 with grip strength and gait speed trajectories. CONCLUSIONS: Functional decline in late life appears to mark a fundamental ageing process in that it occurred and was accelerated in late life regardless of health status. Cystatin C was most consistently associated with these functional declines.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Boerwinkle, Eric; Gibbs, Richard A; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.

740 adults from 20 prospective cohort studies - Wu, J. H. Y.; Marklund, M.; Imamura, F.; Tintle, N.; Ardisson Korat, A. V.; de Goede, J.; Zhou, X.; Yang, W. S.; de Oliveira Otto, M. C.; ger, J.; Qureshi, W.; Virtanen, J. K.; et al. (Lancet Diabetes Endocrinol, 2017)
The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes.\ We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We analysed data from 20 prospective cohort studies from ten countries (Iceland, the Netherlands, the USA, Taiwan, the UK, Germany, Finland, Australia, Sweden, and France), with biomarkers sampled between 1970 and 2010. Participants included in the analyses were aged 18 years or older and had data available for linoleic acid and arachidonic acid biomarkers at baseline. We excluded participants with type 2 diabetes at baseline. The main outcome was the association between omega-6 PUFA biomarkers and incident type 2 diabetes. We assessed the relative risk of type 2 diabetes prospectively for each cohort and lipid compartment separately using a prespecified analytic plan for exposures, covariates, effect modifiers, and analysis, and the findings were then pooled using inverse-variance weighted meta-analysis.\ 13).\ Findings suggest that linoleic acid has long-term benefits for the prevention of type 2 diabetes and that arachidonic acid is not harmful.\ Funders are shown in the appendix.

Age, Race and Gender Factors in Incident Disability. - Jacob, Mini E; Marron, Megan M; Boudreau, Robert; Odden, Michelle C; Arnold, Alice M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2017)
Background: Incident disability rates enable the comparison of risk across populations. Understanding these by age, sex and race is important for planning for the care of older adults and targeting prevention. Methods: We calculated incident disability rates among older adults in the Cardiovascular Health Study, a study of 5,888 older adults aged ≥ 65 years over 6 years of follow-up. Disability was defined in 2 ways: 1) self-report of disability (severe difficulty or inability) in any of 6 ADLs, and 2) mobility difficulty (any difficulty walking half a mile or climbing 10 steps). Incident disability rates were calculated as events per 100 person years for age, gender and race groups. Results: The incidence of ADL disability, and mobility difficulty were 2.7 (2.5-2.8), and 9.8 (9.4 -10.3) events per 100 person years. Women, older participants and blacks had higher rates in both domains. Conclusion: Incidence rates are considerably different based on the domain examined as well as age, race and gender composition of the population. Prevention efforts should focus on high risk populations and attempt to ameliorate factors that increase risk in these groups.

The Alzheimer's Disease Sequencing Project: Study design and sample selection. - Beecham, Gary W; Bis, J C; Martin, E R; Choi, S-H; DeStefano, A L; van Duijn, C M; Fornage, M; Gabriel, S B; Koboldt, D C; Larson, D E; Naj, A C; Psaty, B M; et al. (Neurol Genet, 2017)

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Blood Pressure Trajectory With Mortality, Incident Cardiovascular Disease, and Heart Failure in the Cardiovascular Health Study. - Smitson, Christopher C; Scherzer, Rebecca; Shlipak, Michael G; Psaty, Bruce M; Newman, Anne B; Sarnak, Mark J; Odden, Michelle C; Peralta, Carmen A (Am J Hypertens, 2017)
BACKGROUND: Common blood pressure (BP) trajectories are not well established in elderly persons, and their association with clinical outcomes is uncertain. METHODS: We used hierarchical cluster analysis to identify discrete BP trajectories among 4,067 participants in the Cardiovascular Health Study using repeated BP measures from years 0 to 7. We then evaluated associations of each BP trajectory cluster with all-cause mortality, incident cardiovascular disease (CVD, defined as stroke or myocardial infarction) (N = 2,837), and incident congestive heart failure (HF) (N = 3,633) using Cox proportional hazard models. RESULTS: Median age was 77 years at year 7. Over a median 9.3 years of follow-up, there were 2,475 deaths, 659 CVD events, and 1,049 HF events. The cluster analysis identified 3 distinct trajectory groups. Participants in cluster 1 (N = 1,838) had increases in both systolic (SBP) and diastolic (DBP) BPs, whereas persons in cluster 2 (N = 1,109) had little change in SBP but declines in DBP. Persons in cluster 3 (N = 1,120) experienced declines in both SBP and DBP. After multivariable adjustment, clusters 2 and 3 were associated with increased mortality risk relative to cluster 1 (hazard ratio = 1.21, 95% confidence interval: 1.06-1.37 and hazard ratio = 1.20, 95% confidence interval: 1.05-1.36, respectively). Compared to cluster 1, cluster 3 had higher rates of incident CVD but associations were not statistically significant in demographic-adjusted models (hazard ratio = 1.16, 95% confidence interval: 0.96-1.39). Findings were similar when stratified by use of antihypertensive therapy. CONCLUSIONS: Among community-dwelling elders, distinct BP trajectories were identified by integrating both SBP and DBP. These clusters were found to have differential associations with outcomes.

Association of Coronary Artery Calcium Score vs Age With Cardiovascular Risk in Older Adults: An Analysis of Pooled Population-Based Studies. - Yano, Yuichiro; O'Donnell, Christopher J; Kuller, Lewis; Kavousi, Maryam; Erbel, Raimund; Ning, Hongyan; D'Agostino, Ralph; Newman, Anne B; Nasir, Khurram; Hofman, Albert; Lehmann, Nils; Dhana, Klodian; et al. (JAMA Cardiol, 2017)
Importance: Besides age, other discriminators of atherosclerotic cardiovascular disease (ASCVD) risk are needed in older adults. Objectives: To examine the predictive ability of coronary artery calcium (CAC) score vs age for incident ASCVD and how risk prediction changes by adding CAC score and removing only age from prediction models. Design, Setting, and Participants: We conducted an analysis of pooled US population-based studies, including the Framingham Heart Study, the Multi-Ethnic Study of Atherosclerosis, and the Cardiovascular Health Study. Results were compared with 2 European cohorts, the Rotterdam Study and the Heinz Nixdorf Recall Study. Participants underwent CAC scoring between 1998 and 2006 using cardiac computed tomography. The participants included adults older than 60 years without known ASCVD at baseline. Exposures: Coronary artery calcium scores. Main Outcomes and Measures: Incident ASCVD events including coronary heart disease (CHD) and stroke. Results: The study included 4778 participants from 3 US cohorts, with a mean age of 70.1 years; 2582 (54.0%) were women, and 2431 (50.9%) were nonwhite. Over 11 years of follow-up (44 152 person-years), 405 CHD and 228 stroke events occurred. Coronary artery calcium score (vs age) had a greater association with incident CHD (C statistic, 0.733 vs 0.690; C statistics difference, 0.043; 95% CI of difference, 0.009-0.075) and modestly improved prediction of incident stroke (C statistic, 0.695 vs 0.670; C statistics difference, 0.025; 95% CI of difference, -0.015 to 0.064). Adding CAC score to models including traditional cardiovascular risk factors, with only age being removed, provided improved discrimination for incident CHD (C statistic, 0.735 vs 0.703; C statistics difference, 0.032; 95% CI of difference, 0.002-0.062) but not for stroke. Coronary artery calcium score was more likely than age to provide higher category-free net reclassification improvement among participants who experienced an ASCVD event (0.390; 95% CI, 0.312-0.467 vs 0.08; 95% CI -0.001 to 0.181) and to result in more accurate reclassification of risk for ASCVD events among these individuals. The findings were similar in the 2 European cohorts (n = 4990). Conclusions and Relevance: Coronary artery calcium may be an alternative marker besides age to better discriminate between lower and higher CHD risk in older adults. Whether CAC score can assist in guiding the decision to initiate statin treatment for primary prevention in older adults requires further investigation.

Atrial ectopy as a mediator of the association between race and atrial fibrillation. - Christensen, Matthew A; Nguyen, Kaylin T; Stein, Phyllis K; Fohtung, Raymond B; Soliman, Elsayed Z; Dewland, Thomas A; Vittinghoff, Eric; Psaty, Bruce M; Heckbert, Susan R; Marcus, Gregory M (Heart Rhythm, 2017)
BACKGROUND: Blacks have a lower risk of atrial fibrillation (AF) despite having more AF risk factors, but the mechanism remains unknown. Premature atrial contraction (PAC) burden is a recently identified risk factor for AF. OBJECTIVE: The purpose of this study was to determine whether the burden of PACs explains racial differences in AF risk. METHODS: PAC burden (number per hour) was assessed by 24-hour ambulatory electrocardiographic (ECG) monitoring in a randomly selected subset of patients in the Cardiovascular Health Study. Participants were followed prospectively for the development of AF, diagnosed by study ECG and hospital admission records. RESULTS: Among 938 participants (median age 73 years; 34% black; 58% female), 206 (22%) developed AF over a median follow-up of 11.0 years (interquartile range 6.1-13.4). After adjusting for age, sex, body mass index, coronary disease, congestive heart failure, diabetes, hypertension, alcohol consumption, smoking status, and study site, black race was associated with a 42% lower risk of AF (hazard ratio 0.58, 95% confidence interval [CI] 0.40-0.85; P = .005). The baseline PAC burden was 2.10 times (95% CI 1.57-2.83; P <.001) higher in whites than blacks. There was no detectable difference in premature ventricular contraction (PVC) burden by race. PAC burden mediated 19.5% (95% CI 6.3-52.5) of the adjusted association between race and AF. CONCLUSION: On average, whites exhibited more PACs than blacks, and this difference statistically explains a modest proportion of the differential risk of AF by race. The differential PAC burden, without differences in PVCs, by race suggests that identifiable common exposures or genetic influences might be important to atrial pathophysiology.

Bivariate Genome-Wide Association Study of Depressive Symptoms with Type 2 Diabetes and Quantitative Glycemic Traits. - Haljas, Kadri; Amare, Azmeraw T; Alizadeh, Behrooz Z; Hsu, Yi-Hsiang; Mosley, Thomas; Newman, Anne; Murabito, Joanne; Tiemeier, Henning; Tanaka, Toshiko; van Duijn, Cornelia; Ding, Jingzhong; Llewellyn, David J; et al. (Psychosom Med, 2017)
OBJECTIVE: Shared genetic background may explain phenotypic associations between depression and Type-2-Diabetes (T2D). We aimed to study, on a genome-wide level, if genetic correlation and pleiotropic loci exist between depressive symptoms and T2D or glycemic traits. METHODS: We estimated SNP-based heritability and analyzed genetic correlation between depressive symptoms and T2D and glycemic traits with the LD Score Regression (LDSC) by combining summary statistics of previously conducted meta-analyses for depressive symptoms by CHARGE consortium (N = 51,258), T2D by Diagram consortium (N = 34,840 patients and 114,981 controls), fasting glucose, fasting insulin, HOMA-β, and HOMA-IR by MAGIC consortium (N = 58,074). Finally, we investigated pleiotropic loci using a bivariate GWAS approach with summary statistics from GWAS meta-analyses and reported loci with genome-wide significant bivariate association p-value (p < 5x10). Biological annotation and function of significant pleiotropic SNPs were assessed in several databases. RESULTS: The SNP-based heritability ranged from 0.04 to 0.10 in each individual trait. In the LDSC analyses, depressive symptoms showed no significant genetic correlation with T2D or glycemic traits (p > 0.37). Yet, we identified pleiotropic genetic variations for depressive symptoms and T2D (in the IGF2BP2, CDKAL1, CDKN2B-AS, and PLEKHA1 genes), and fasting glucose (in the MADD, CDKN2B-AS, PEX16, and MTNR1B genes). CONCLUSIONS: We found no significant overall genetic correlations between depressive symptoms, T2D or glycemic traits suggesting major differences in underlying biology of these traits. Yet, several potential pleiotropic loci were identified between depressive symptoms, T2D and fasting glucose suggesting that previously established phenotypic associations may be partly explained by genetic variation in these specific loci.

Brain Structural Markers and Caregiving Characteristics as Interacting Correlates of Caregiving Strain. - Smagula, Stephen F; Beach, Scott; Rosso, Andrea L; Newman, Anne B; Schulz, Richard (Am J Geriatr Psychiatry, 2017)
OBJECTIVE: To evaluate the association between brain structural markers and caregiving strain among older informal caregivers. DESIGN: A secondary data analysis combining data from the Caregiver Health Effects Study (1993-1994) and the Cardiovascular Health Study MRI examination (1992-1994). SETTING: Four United States communities. PARTICIPANTS: Co-residing spousal caregivers (N = 237; mean age: 76.2 years, SD: 2.2 years). MEASUREMENTS: Visually rated ventricular and white matter (WM) grades from magnetic resonance imaging, caregiving strain defined as "emotional or physical strain associated with providing care" for any of 12 activities of daily living (ADLs) and instrumental activities of daily living (IADLs), plus measures of caregiving characteristics and caregiver's health. RESULTS: Overall, 56% of caregivers reported strain. We detected an interaction where strain was very common (>82%) among caregivers who helped with four or more IADLs, regardless of WM grades, and among caregivers with the worst WM grades (WM grades ≥4), regardless of the number of IADLs they helped with. Among caregivers helping with fewer than four IADLs, having WM grade 4 or greater was associated with a 55% higher prevalence ratio for reporting strain. This association remained statistically significant but was most markedly attenuated by adjustments for: care recipient's memory and behavioral problems, caregiver's depression symptoms, and caregiver's ADL impairment. CONCLUSIONS: Caregiving strain is very common among older informal caregivers who provide help with many IADLs, and among caregivers who help with fewer IADLs, but have manifest signs of white matter pathology. Modern quantitative-neuroimaging studies are needed to evaluate whether more subtle variability in brain structure confers caregiving strain and the related health consequences.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Dairy consumption, systolic blood pressure, and risk of hypertension: Mendelian randomization study. - Ding, Ming; Huang, Tao; Bergholdt, Helle Km; Nordestgaard, Børge G; Ellervik, Christina; Qi, Lu (BMJ, 2017)
Objective To examine whether previous observed inverse associations of dairy intake with systolic blood pressure and risk of hypertension were causal.Design Mendelian randomization study using the single nucleotide polymorphism rs4988235 related to lactase persistence as an instrumental variable.Setting CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium.Participants Data from 22 studies with 171 213 participants, and an additional 10 published prospective studies with 26 119 participants included in the observational analysis.Main outcome measures The instrumental variable estimation was conducted using the ratio of coefficients approach. Using meta-analysis, an additional eight published randomized clinical trials on the association of dairy consumption with systolic blood pressure were summarized.Results Compared with the CC genotype (CC is associated with complete lactase deficiency), the CT/TT genotype (TT is associated with lactose persistence, and CT is associated with certain lactase deficiency) of LCT-13910 (lactase persistence gene) rs4988235 was associated with higher dairy consumption (0.23 (about 55 g/day), 95% confidence interval 0.17 to 0.29) serving/day; P<0.001) and was not associated with systolic blood pressure (0.31, 95% confidence interval -0.05 to 0.68 mm Hg; P=0.09) or risk of hypertension (odds ratio 1.01, 95% confidence interval 0.97 to 1.05; P=0.27). Using LCT-13910 rs4988235 as the instrumental variable, genetically determined dairy consumption was not associated with systolic blood pressure (β=1.35, 95% confidence interval -0.28 to 2.97 mm Hg for each serving/day) or risk of hypertension (odds ratio 1.04, 0.88 to 1.24). Moreover, meta-analysis of the published clinical trials showed that higher dairy intake has no significant effect on change in systolic blood pressure for interventions over one month to 12 months (intervention compared with control groups: β=-0.21, 95% confidence interval -0.98 to 0.57 mm Hg). In observational analysis, each serving/day increase in dairy consumption was associated with -0.11 (95% confidence interval -0.20 to -0.02 mm Hg; P=0.02) lower systolic blood pressure but not risk of hypertension (odds ratio 0.98, 0.97 to 1.00; P=0.11).Conclusion The weak inverse association between dairy intake and systolic blood pressure in observational studies was not supported by a comprehensive instrumental variable analysis and systematic review of existing clinical trials.
Keywords: Blood Pressure; Dairy Products; Feeding Behavior; Genetic Predisposition to Disease; Humans; Hypertension; Lactase; Mendelian Randomization Analysis; Observational Studies as Topic; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic

Detection of genetic loci associated with plasma fetuin-A: A meta-analysis of genome-wide association studies from the CHARGE Consortium. - Jensen, Majken K; Jensen, Richard A; Mukamal, Kenneth J; Guo, Xiuqing; Yao, Jie; Sun, Qi; Cornelis, Marilyn; Liu, Yongmei; Chen, Ming-Huei; Kizer, Jorge R; Djoussé, Luc; Siscovick, David S; et al. (Hum Mol Genet, 2017)
Plasma fetuin-A is associated with type 2 diabetes, and AHSG, the gene encoding fetuin-A, has been identified as a susceptibility locus for diabetes and metabolic syndrome. Thus far, unbiased investigations of the genetic determinants of plasma fetuin-A concentrations have not been conducted. We searched for single nucleotide polymorphisms (SNPs) related to fetuin-A concentrations by a genome-wide association study in six population-based studies.We examined the association of fetuin-A levels with ∼ 2.5 million genotyped and imputed SNPs in 9,055 participants of European descent and 2,119 African Americans. In both ethnicities, strongest associations were centered in a region with a high degree of LD near the AHSG locus. Among 136 genome-wide significant (p < 0.05x10-8) SNPs near the AHSG locus, the top SNP was rs4917 (p = 1.27x10-303), a known coding SNP in exon 6 that is associated with a 0.06 g/L (∼13%) lower fetuin-A level. This variant alone explained 14% of the variation in fetuin-A levels. Analyses conditioned on rs4917 indicated that the strong association with the AHSG locus stems from additional independent associations of multiple variants among European Americans. In conclusion, levels of fetuin-A in plasma are strongly associated with SNPs in its encoding gene, AHSG, but not elsewhere in the genome. Given the strength of the associations observed for multiple independent SNPs, the AHSG gene is an example of a candidate locus suitable for additional investigations including fine mapping to elucidate the biological basis of the findings and further functional experiments to clarify AHSG as a potential therapeutic target.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery and replication of SNP-SNP interactions for quantitative lipid traits in over 60,000 individuals. - Holzinger, Emily R; Verma, Shefali S; Moore, Carrie B; Hall, Molly; De, Rishika; Gilbert-Diamond, Diane; Lanktree, Matthew B; Pankratz, Nathan; Amuzu, Antoinette; Burt, Amber; Dale, Caroline; Dudek, Scott; et al. (BioData Min, 2017)
BACKGROUND: The genetic etiology of human lipid quantitative traits is not fully elucidated, and interactions between variants may play a role. We performed a gene-centric interaction study for four different lipid traits: low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TG). RESULTS: Our analysis consisted of a discovery phase using a merged dataset of five different cohorts (n = 12,853 to n = 16,849 depending on lipid phenotype) and a replication phase with ten independent cohorts totaling up to 36,938 additional samples. Filters are often applied before interaction testing to correct for the burden of testing all pairwise interactions. We used two different filters: 1. A filter that tested only single nucleotide polymorphisms (SNPs) with a main effect of p < 0.001 in a previous association study. 2. A filter that only tested interactions identified by Biofilter 2.0. Pairwise models that reached an interaction significance level of p < 0.001 in the discovery dataset were tested for replication. We identified thirteen SNP-SNP models that were significant in more than one replication cohort after accounting for multiple testing. CONCLUSIONS: These results may reveal novel insights into the genetic etiology of lipid levels. Furthermore, we developed a pipeline to perform a computationally efficient interaction analysis with multi-cohort replication.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

Ectopy on a Single 12-Lead ECG, Incident Cardiac Myopathy, and Death in the Community. - Nguyen, Kaylin T; Vittinghoff, Eric; Dewland, Thomas A; Dukes, Jonathan W; Soliman, Elsayed Z; Stein, Phyllis K; Gottdiener, John S; Alonso, Alvaro; Chen, Lin Y; Psaty, Bruce M; Heckbert, Susan R; Marcus, Gregory M (J Am Heart Assoc, 2017)
BACKGROUND: Atrial fibrillation and heart failure are 2 of the most common diseases, yet ready means to identify individuals at risk are lacking. The 12-lead ECG is one of the most accessible tests in medicine. Our objective was to determine whether a premature atrial contraction observed on a standard 12-lead ECG would predict atrial fibrillation and mortality and whether a premature ventricular contraction would predict heart failure and mortality. METHODS AND RESULTS: We utilized the CHS (Cardiovascular Health) Study, which followed 5577 participants for a median of 12 years, as the primary cohort. The ARIC (Atherosclerosis Risk in Communities Study), the replication cohort, captured data from 15 792 participants over a median of 22 years. In the CHS, multivariable analyses revealed that a baseline 12-lead ECG premature atrial contraction predicted a 60% increased risk of atrial fibrillation (hazard ratio, 1.6; 95% CI, 1.3-2.0; P<0.001) and a premature ventricular contraction predicted a 30% increased risk of heart failure (hazard ratio, 1.3; 95% CI, 1.0-1.6; P=0.021). In the negative control analyses, neither predicted incident myocardial infarction. A premature atrial contraction was associated with a 30% increased risk of death (hazard ratio, 1.3; 95% CI, 1.1-1.5; P=0.008) and a premature ventricular contraction was associated with a 20% increased risk of death (hazard ratio, 1.2; 95% CI, 1.0-1.3; P=0.044). Similarly statistically significant results for each analysis were also observed in ARIC. CONCLUSIONS: Based on a single standard ECG, a premature atrial contraction predicted incident atrial fibrillation and death and a premature ventricular contraction predicted incident heart failure and death, suggesting that this commonly used test may predict future disease.

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Factors Associated With Ischemic Stroke Survival and Recovery in Older Adults. - Winovich, Divya Thekkethala; Longstreth, William T; Arnold, Alice M; Varadhan, Ravi; Zeki Al Hazzouri, Adina; Cushman, Mary; Newman, Anne B; Odden, Michelle C (Stroke, 2017)
BACKGROUND AND PURPOSE: Little is known about factors that predispose older adults to poor recovery after a stroke. In this study, we sought to evaluate prestroke measures of frailty and related factors as markers of vulnerability to poor outcomes after ischemic stroke. METHODS: In participants aged 65 to 99 years with incident ischemic strokes from the Cardiovascular Health Study, we evaluated the association of several risk factors (frailty, frailty components, C-reactive protein, interleukin-6, and cystatin C) assessed before stroke with stroke outcomes of survival, cognitive decline (≥5 points on Modified Mini-Mental State Examination), and activities of daily living decline (increase in limitations). RESULTS: Among 717 participants with incident ischemic stroke with survival data, slow walking speed, low grip strength, and cystatin C were independently associated with shorter survival. Among participants <80 years of age, frailty and interleukin-6 were also associated with shorter survival. Among 509 participants with recovery data, slow walking speed, and low grip strength were associated with both cognitive and activities of daily living decline poststroke. C-reactive protein and interleukin-6 were associated with poststroke cognitive decline among men only. Frailty status was associated with activities of daily living decline among women only. CONCLUSIONS: Markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. Inflammation, kidney function, and frailty also seemed to be determinants of survival and recovery after an ischemic stroke. These markers of vulnerability may identify targets for differing pre and poststroke medical management and rehabilitation among older adults at risk of poor stroke outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Frail Elderly; Humans; Male; Recovery of Function; Risk Factors; Stroke; Survival Rate

Fibroblast Growth Factor 23 and the Risk of Infection-Related Hospitalization in Older Adults. - Nowak, Kristen L; Bartz, Traci M; Dalrymple, Lorien; de Boer, Ian H; Kestenbaum, Bryan; Shlipak, Michael G; Garimella, Pranav S; Ix, Joachim H; Chonchol, Michel (J Am Soc Nephrol, 2017)
Within monocytes, 1,25-dihydroxyvitamin D [1,25(OH)2D] is important for production of cathelicidins, which in turn, are critical for antibacterial action. Fibroblast growth factor 23 (FGF23) decreases 1,25(OH)2D production and thus, could increase infection risk. We examined this possibility in 3141 community-dwelling adults ages ≥65 years old at baseline in the Cardiovascular Health Study using Cox proportional hazards models to examine the association between FGF23 concentrations and first infection-related hospitalizations and determine whether associations differed by the presence of CKD (eGFR<60 ml/min per 1.73 m(2) [n=832] or urine albumin-to-creatinine ratio >30 mg/g [n=577]). Mean±SD age of participants was 78±5 years old, 60% of participants were women, and the median plasma FGF23 concentration was 70 (interquartile range, 53-99) relative units per milliliter. In fully adjusted models, higher FGF23 concentrations associated with higher risk of first infection-related hospitalization (hazard ratio [HR], 1.11; 95% confidence interval [95% CI], 1.03 to 1.20 per doubling of FGF23) during a median follow-up of 8.6 years. In participants with or without CKD (defined by eGFR), FGF23 concentration associated with first infection-related hospitalization with HRs of 1.24 (95% CI, 1.08 to 1.42) and 1.06 (95% CI, 0.97 to 1.17) per doubling of FGF23, respectively (P=0.13 for interaction). Associations did not differ between groups when stratified by urine albumin-to-creatinine ratio. In sensitivity analyses, the addition of serum calcium, phosphorus, 25-hydroxyvitamin D, intact parathyroid hormone, and 24,25-dihydroxyvitamin D did not meaningfully change the estimates. In conclusion, in community-dwelling older adults, higher plasma FGF23 concentrations independently associated with the risk of first infection-related hospitalization.

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Fine mapping of QT interval regions in global populations refines previously identified QT interval loci and identifies signals unique to African and Hispanic descent populations. - Avery, Christy L; Wassel, Christina L; Richard, Melissa A; Highland, Heather M; Bien, Stephanie; Zubair, Niha; Soliman, Elsayed Z; Fornage, Myriam; Bielinski, Suzette J; Tao, Ran; Seyerle, Amanda A; Shah, Sanjiv J; et al. (Heart Rhythm, 2017)
BACKGROUND: The electrocardiographically measured QT interval (QT) is heritable and its prolongation is an established risk factor for several cardiovascular diseases. Yet, most QT genetic studies have been performed in European ancestral populations, possibly reducing their global relevance. OBJECTIVE: To leverage diversity and improve biological insight, we fine mapped 16 of the 35 previously identified QT loci (46%) in populations of African American (n = 12,410) and Hispanic/Latino (n = 14,837) ancestry. METHODS: Racial/ethnic-specific multiple linear regression analyses adjusted for heart rate and clinical covariates were examined separately and in combination after inverse-variance weighted trans-ethnic meta-analysis. RESULTS: The 16 fine-mapped QT loci included on the Illumina Metabochip represented 21 independent signals, of which 16 (76%) were significantly (P-value≤9.1×10(-5)) associated with QT. Through sequential conditional analysis we also identified three trans-ethnic novel SNPs at ATP1B1, SCN5A-SCN10A, and KCNQ1 and three Hispanic/Latino-specific novel SNPs at NOS1AP and SCN5A-SCN10A (two novel SNPs) with evidence of associations with QT independent of previous identified GWAS lead SNPs. Linkage disequilibrium patterns helped to narrow the region likely to contain the functional variants at several loci, including NOS1AP, USP50-TRPM7, and PRKCA, although intervals surrounding SLC35F1-PLN and CNOT1 remained broad in size (>100 kb). Finally, bioinformatics-based functional characterization suggested a regulatory function in cardiac tissues for the majority of independent signals that generalized and the novel SNPs. CONCLUSION: Our findings suggest that a majority of identified SNPs implicate gene regulatory dysfunction in QT prolongation, that the same loci influence variation in QT across global populations, and that additional, novel, population-specific QT signals exist.

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Health and Functional Status of Adults Aged 90 Years in the United States. - Odden, Michelle C; Koh, William Jen Hoe; Arnold, Alice M; Psaty, Bruce M; Newman, Anne B (JAMA Intern Med, 2017)

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets. - Lam, Max; Trampush, Joey W; Yu, Jin; Knowles, Emma; Davies, Gail; Liewald, David C; Starr, John M; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; Reinvang, Ivar; et al. (Cell Rep, 2017)
Here, we present a large (n = 107,207) genome-wide association study (GWAS) of general cognitive ability ("g"), further enhanced by combining results with a large-scale GWAS of educational attainment. We identified 70 independent genomic loci associated with general cognitive ability. Results showed significant enrichment for genes causing Mendelian disorders with an intellectual disability phenotype. Competitive pathway analysis implicated the biological processes of neurogenesis and synaptic regulation, as well as the gene targets of two pharmacologic agents: cinnarizine, a T-type calcium channel blocker, and LY97241, a potassium channel inhibitor. Transcriptome-wide and epigenome-wide analysis revealed that the implicated loci were enriched for genes expressed across all brain regions (most strongly in the cerebellum). Enrichment was exclusive to genes expressed in neurons but not oligodendrocytes or astrocytes. Finally, we report genetic correlations between cognitive ability and disparate phenotypes including psychiatric disorders, several autoimmune disorders, longevity, and maternal age at first birth.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness. - Willems, Sara M; Wright, Daniel J; Day, Felix R; Trajanoska, Katerina; Joshi, Peter K; Morris, John A; Matteini, Amy M; Garton, Fleur C; Grarup, Niels; Oskolkov, Nikolay; Thalamuthu, Anbupalam; Mangino, Massimo; et al. (Nat Commun, 2017)
Hand grip strength is a widely used proxy of muscular fitness, a marker of frailty, and predictor of a range of morbidities and all-cause mortality. To investigate the genetic determinants of variation in grip strength, we perform a large-scale genetic discovery analysis in a combined sample of 195,180 individuals and identify 16 loci associated with grip strength (P<5 × 10) in combined analyses. A number of these loci contain genes implicated in structure and function of skeletal muscle fibres (ACTG1), neuronal maintenance and signal transduction (PEX14, TGFA, SYT1), or monogenic syndromes with involvement of psychomotor impairment (PEX14, LRPPRC and KANSL1). Mendelian randomization analyses are consistent with a causal effect of higher genetically predicted grip strength on lower fracture risk. In conclusion, our findings provide new biological insight into the mechanistic underpinnings of grip strength and the causal role of muscular strength in age-related morbidities and mortality.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Predictors and outcomes of heart failure with mid-range ejection fraction. - Bhambhani, Vijeta; Kizer, Jorge R; Lima, João A C; van der Harst, Pim; Bahrami, Hossein; Nayor, Matthew; de Filippi, Christopher R; Enserro, Danielle; Blaha, Michael J; Cushman, Mary; Wang, Thomas J; Gansevoort, Ron T; et al. (Eur J Heart Fail, 2017)
AIMS: While heart failure with preserved (HFpEF) and reduced ejection fraction (HFrEF) are well described, determinants and outcomes of heart failure with mid-range ejection fraction (HFmrEF) remain unclear. We sought to examine clinical and biochemical predictors of incident HFmrEF in the community. METHODS AND RESULTS: We pooled data from four community-based longitudinal cohorts, with ascertainment of new heart failure (HF) classified into HFmrEF [ejection fraction (EF) 41-49%], HFpEF (EF ≥50%), and HFrEF (EF ≤40%). Predictors of incident HF subtypes were assessed using multivariable Cox models. Among 28 820 participants free of HF followed for a median of 12 years, there were 200 new HFmrEF cases, compared with 811 HFpEF and 1048 HFrEF. Clinical predictors of HFmrEF included age, male sex, systolic blood pressure, diabetes mellitus, and prior myocardial infarction (multivariable adjusted P ≤ 0.003 for all). Biomarkers that predicted HFmrEF included natriuretic peptides, cystatin-C, and high-sensitivity troponin (P ≤ 0.0004 for all). Natriuretic peptides were stronger predictors of HFrEF [hazard ratio (HR) 2.00 per 1 standard deviation increase, 95% confidence interval (CI) 1.81-2.20] than of HFmrEF (HR 1.51, 95% CI 1.20-1.90, P = 0.01 for difference), and did not differ in their association with incident HFmrEF and HFpEF (HR 1.56, 95% CI 1.41-1.73, P = 0.68 for difference). All-cause mortality following the onset of HFmrEF was worse than that of HFpEF (50 vs. 39 events per 1000 person-years, P = 0.02), but comparable to that of HFrEF (46 events per 1000 person-years, P = 0.78). CONCLUSIONS: We found overlap in predictors of incident HFmrEF with other HF subtypes. In contrast, mortality risk after HFmrEF was worse than HFpEF, and similar to HFrEF.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Short telomere length is associated with impaired cognitive performance in European ancestry cohorts. - Hägg, S; Zhan, Y; Karlsson, R; Gerritsen, L; Ploner, A; van der Lee, S J; Broer, L; Deelen, J; Marioni, R E; Wong, A; Lundquist, A; Zhu, G; et al. (Transl Psychiatry, 2017)
The association between telomere length (TL) dynamics on cognitive performance over the life-course is not well understood. This study meta-analyses observational and causal associations between TL and six cognitive traits, with stratifications on APOE genotype, in a Mendelian Randomization (MR) framework. Twelve European cohorts (N=17 052; mean age=59.2±8.8 years) provided results for associations between qPCR-measured TL (T/S-ratio scale) and general cognitive function, mini-mental state exam (MMSE), processing speed by digit symbol substitution test (DSST), visuospatial functioning, memory and executive functioning (STROOP). In addition, a genetic risk score (GRS) for TL including seven known genetic variants for TL was calculated, and used in associations with cognitive traits as outcomes in all cohorts. Observational analyses showed that longer telomeres were associated with better scores on DSST (β=0.051 per s.d.-increase of TL; 95% confidence interval (CI): 0.024, 0.077; P=0.0002), and MMSE (β=0.025; 95% CI: 0.002, 0.047; P=0.03), and faster STROOP (β=-0.053; 95% CI: -0.087, -0.018; P=0.003). Effects for DSST were stronger in APOE ɛ4 non-carriers (β=0.081; 95% CI: 0.045, 0.117; P=1.0 × 10-5), whereas carriers performed better in STROOP (β=-0.074; 95% CI: -0.140, -0.009; P=0.03). Causal associations were found for STROOP only (β=-0.598 per s.d.-increase of TL; 95% CI: -1.125, -0.072; P=0.026), with a larger effect in ɛ4-carriers (β=-0.699; 95% CI: -1.330, -0.069; P=0.03). Two-sample replication analyses using CHARGE summary statistics showed causal effects between TL and general cognitive function and DSST, but not with STROOP. In conclusion, we suggest causal effects from longer TL on better cognitive performance, where APOE ɛ4-carriers might be at differential risk.
Keywords: Adult; Aged; Apolipoprotein E4; Cognitive Dysfunction; Cohort Studies; European Continental Ancestry Group; Female; Genetic Carrier Screening; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neuropsychological Tests; Psychometrics; Statistics as Topic; Telomere

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Sleep-disordered breathing is associated with higher carboxymethyllysine level in elderly women but not elderly men in the cardiovascular health study. - Ahiawodzi, Peter D; Kerber, Richard A; Taylor, Kira C; Groves, Frank D; O'Brien, Elizabeth; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Robbins, John; et al. (Biomarkers, 2017)
CONTEXT: Carboxymethyl-lysine (CML) results from oxidative stress and has been linked to cardiovascular disease. OBJECTIVE: The objective of this study is to investigate the association between sleep-disordered breathing (SDB) - a source of oxidative stress - and CML. MATERIALS AND METHODS: About 1002 participants in the Cardiovascular Health Study (CHS) were studied. RESULTS: Women with SDB had significantly higher CML concentration compared with those without SDB (OR = 1.63, 95%CI = 1.03-2.58, p = 0.04). The association was not significant among men. DISCUSSION: SDB was associated with CML concentration among elderly women but not men in the Cardiovascular Health Study. CONCLUSION: Accumulation of CML may be an adverse health consequence of SDB.

Subclinical Atherosclerosis, Cardiac and Kidney Function, Heart Failure, and Dementia in the Very Elderly. - Kuller, Lewis H; Lopez, Oscar L; Gottdiener, John S; Kitzman, Dalane W; Becker, James T; Chang, Yuefang; Newman, Anne B (J Am Heart Assoc, 2017)
BACKGROUND: Heart failure (HF) and dementia are major causes of disability and death among older individuals. Risk factors and biomarkers of HF may be determinants of dementia in the elderly. We evaluated the relationship between biomarkers of cardiovascular disease and HF and risk of dementia and death. Three hypotheses were tested: (1) higher levels of high-sensitivity cardiac troponin T, N-terminal of prohormone brain natriuretic peptide, and cystatin C predict risk of death, cardiovascular disease, HF, and dementia; (2) higher levels of cardiovascular disease biomarkers are associated with increased risk of HF and then secondary increased risk of dementia; and (3) risk of dementia is lower among participants with a combination of lower coronary artery calcium, atherosclerosis, and lower high-sensitivity cardiac troponin T (myocardial injury). METHODS AND RESULTS: The Cardiovascular Health Study Cognition Study was a continuation of the Cardiovascular Health Study limited to the Pittsburgh, PA, center from 1998-1999 to 2014. In 1992-1994, 924 participants underwent magnetic resonance imaging of the brain. There were 199 deaths and 116 developed dementia before 1998-1999. Of the 609 participants eligible for the Pittsburgh Cardiovascular Health Study Cognition Study, 87.5% (n=532) were included in the study. There were 120 incident HF cases and 72% had dementia. In 80 of 87, dementia preceded HF. A combination of low coronary artery calcium score and low high-sensitivity cardiac troponin T was significantly associated with reduced risk of dementia and HF. CONCLUSIONS: Most participants with HF had dementia but with onset before HF. Lower high-sensitivity cardiac troponin T and coronary artery calcium was associated with low risk of dementia based on a small number of events. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00005133.

Systems biology approach to late-onset Alzheimer's disease genome-wide association study identifies novel candidate genes validated using brain expression data and Caenorhabditis elegans experiments. - Mukherjee, Shubhabrata; Russell, Joshua C; Carr, Daniel T; Burgess, Jeremy D; Allen, Mariet; Serie, Daniel J; Boehme, Kevin L; Kauwe, John S K; Naj, Adam C; Fardo, David W; Dickson, Dennis W; Montine, Thomas J; et al. (Alzheimers Dement, 2017)
INTRODUCTION: We sought to determine whether a systems biology approach may identify novel late-onset Alzheimer's disease (LOAD) loci. METHODS: We performed gene-wide association analyses and integrated results with human protein-protein interaction data using network analyses. We performed functional validation on novel genes using a transgenic Caenorhabditis elegans Aβ proteotoxicity model and evaluated novel genes using brain expression data from people with LOAD and other neurodegenerative conditions. RESULTS: We identified 13 novel candidate LOAD genes outside chromosome 19. Of those, RNA interference knockdowns of the C. elegans orthologs of UBC, NDUFS3, EGR1, and ATP5H were associated with Aβ toxicity, and NDUFS3, SLC25A11, ATP5H, and APP were differentially expressed in the temporal cortex. DISCUSSION: Network analyses identified novel LOAD candidate genes. We demonstrated a functional role for four of these in a C. elegans model and found enrichment of differentially expressed genes in the temporal cortex.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Animals, Genetically Modified; Antigens, Neoplasm; Caenorhabditis elegans; Disease Models, Animal; Early Growth Response Protein 1; Female; Gene Expression Regulation; Genome-Wide Association Study; Heparin-binding EGF-like Growth Factor; Humans; Male; Membrane Transport Proteins; Mitochondrial ADP, ATP Translocases; NADH Dehydrogenase; Polymorphism, Single Nucleotide; Protein Interaction Maps; RNA Interference; Systems Biology; Temporal Lobe

Trajectories of IGF-I Predict Mortality in Older Adults: The Cardiovascular Health Study. - Sanders, Jason L; Guo, Wensheng; O'Meara, Ellen S; Kaplan, Robert C; Pollak, Michael N; Bartz, Traci M; Newman, Anne B; Fried, Linda P; Cappola, Anne R (J Gerontol A Biol Sci Med Sci, 2017)
Background: Disruption of insulin-like growth factor-I (IGF-I) increases health and life span in animal models, though this is unconfirmed in humans. If IGF-I stability indicates homeostasis, the absolute level of IGF-I may be less clinically relevant than maintaining an IGF-I setpoint. Methods: Participants were 945 U.S. community-dwelling individuals aged ≥65 years enrolled in the Cardiovascular Health Study with IGF-I levels at 3-6 timepoints. We examined the association of baseline IGF-I level, trajectory slope, and variability around the trajectory with mortality. Results: There were 633 deaths over median 11.3 years of follow-up. Lower IGF-I levels, declining or increasing slope, and increasing variability were each individually associated with higher mortality (all p < .001). In an adjusted model including all three trajectory parameters, baseline IGF-I levels <70 ng/mL (hazard ratio [HR] 1.58, 95% CI 1.28-1.96 relative to IGF-I levels of 170 ng/mL), steep declines and steep increases in trajectory slope (HR 2.22, 1.30-3.80 for a 15% decline; HR 1.40, 1.07-1.84 for a 10% decline; HR 1.80, 1.12-2.89 for a 15% increase; HR 1.31, 1.00-1.72 for a 10% increase, each vs no change), and variability ≥10% (HR 1.59, 1.09-2.32 for ≥ 30%; HR 1.36, 1.06-1.75 for 20%; and HR 1.17, 1.03-1.32 for 10% variability, each vs 0%) in IGF-I levels were independently associated with mortality. Conclusions: In contrast to data from animal models, low IGF-I levels are associated with higher mortality in older humans. Irrespective of the actual IGF-I level, older individuals with stability of IGF-I levels have lower mortality than those whose IGF-I levels fluctuate over time.

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Visit-to-Visit Blood Pressure Variability and Mortality and Cardiovascular Outcomes Among Older Adults: The Health, Aging, and Body Composition Study. - Wu, Chenkai; Shlipak, Michael G; Stawski, Robert S; Peralta, Carmen A; Psaty, Bruce M; Harris, Tamara B; Satterfield, Suzanne; Shiroma, Eric J; Newman, Anne B; Odden, Michelle C (Am J Hypertens, 2017)
BACKGROUND: Level of blood pressure (BP) is strongly associated with cardiovascular (CV) events and mortality. However, it is questionable whether mean BP can fully capture BP-related vascular risk. Increasing attention has been given to the value of visit-to-visit BP variability. METHODS: We examined the association of visit-to-visit BP variability with mortality, incident myocardial infarction (MI), and incident stroke among 1,877 well-functioning elders in the Health, Aging, and Body Composition Study. We defined visit-to-visit diastolic BP (DBP) and systolic BP (SBP) variability as the root-mean-square error of person-specific linear regression of BP as a function of time. Alternatively, we counted the number of considerable BP increases and decreases (separately; 10mm Hg for DBP and 20mm Hg for SBP) between consecutive visits for each individual. RESULTS: Over an average follow-up of 8.5 years, 623 deaths (207 from CV disease), 153 MIs, and 156 strokes occurred. The median visit-to-visit DBP and SBP variability was 4.96 mmHg and 8.53 mmHg, respectively. After multivariable adjustment, visit-to-visit DBP variability was related to higher all-cause (hazard ratio (HR) = 1.18 per 1 SD, 95% confidence interval (CI) = 1.01-1.37) and CV mortality (HR = 1.35, 95% CI = 1.05-1.73). Additionally, individuals having more considerable decreases of DBP (≥10mm Hg between 2 consecutive visits) had higher risk of all-cause (HR = 1.13, 95% CI = 0.99-1.28) and CV mortality (HR = 1.30, 95% CI = 1.05-1.61); considerable increases of SBP (≥20mm Hg) were associated with higher risk of all-cause (HR = 1.18, 95% CI = 1.03-1.36) and CV mortality (HR = 1.37, 95% CI = 1.08-1.74). CONCLUSIONS: Visit-to-visit DBP variability and considerable changes in DBP and SBP were risk factors for mortality in the elderly.
Keywords: Aged; Aging; Blood Pressure; Blood Pressure Determination; Body Composition; California; Cohort Studies; Female; Health Status; Humans; Hypertension; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Office Visits; Prognosis; Retrospective Studies; Risk Factors; Stroke; Survival Rate

Aortic Stiffness is Associated with Increased Risk of Incident Dementia in Older Adults. - Cui, Chendi; Sekikawa, Akira; Kuller, Lewis H; Lopez, Oscar L; Newman, Anne B; Kuipers, Allison L; Mackey, Rachel H (J Alzheimers Dis, 2018)
Cardiovascular disease risk factors, including age, hypertension, and diabetes, contribute to aortic stiffness and subclinical cardiovascular and brain disease, increasing dementia risk. Aortic stiffness, measured by carotid-femoral pulse wave velocity (cfPWV), reduces the buffering of pulsatile blood flow, exposing cerebral small arteries to microvascular damage. High cfPWV is related to white matter hyperintensities and brain amyloid deposition, and to cognitive decline, but it is unclear whether cfPWV independently predicts incident dementia. Therefore, we tested the hypothesis that cfPWV predicts incident dementia in older adults, independent of potential confounders. The Cardiovascular Health Study Cognition Study followed 532 non-demented older adults with annual cognitive exams from 1998-99 through 2013. CfPWV was measured on 356 (mean age = 78, 59% women) between 1996-2000. Over 15 years, 212 (59.6%) developed dementia (median time from cfPWV measurement = 4 years). In age and sex-adjusted Cox models, cfPWV was significantly associated with increased risk of dementia, but systolic blood pressure, mean arterial pressure and pulse pressure were not. CfPWV (transformed as - 1/cfPWV) remained significantly associated with dementia risk when further adjusted for education, race, APOEɛ4, diabetes, body mass index, mean arterial pressure, and anti-hypertensive medication (hazard ratio = 1.60, 95% CI = 1.02, 2.51). Results were similar when further adjusted for baseline global cognition, subclinical brain measures, and coronary artery calcification. Finally, higher cfPWV was related to lower physical activity intensity and higher systolic blood pressure, heart rate, and waist circumference measured 5 years prior. An important unanswered question is whether interventions to slow arterial stiffening can reduce the risk of dementia.

Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. - Segna, D; Bauer, D C; Feller, M; Schneider, C; Fink, H A; Aubert, C E; Collet, T-H; da Costa, B R; Fischer, K; Peeters, R P; Cappola, A R; Blum, M R; et al. (J Intern Med, 2018)
BACKGROUND: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. OBJECTIVE: To investigate the association between subclinical thyroid dysfunction and bone loss. METHODS: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946-2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid-stimulating hormone [TSH] 0.45-4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50-19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X-ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random-effects two-step approach. RESULTS: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person-years of follow-up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = -0.18 (95% CI: -0.34, -0.02; I2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = -0.14 (95% CI: -0.38, 0.10; I2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: -0.30, 0.36; I2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = -0.59; [95% CI: -0.99, -0.19]) and total hip region (%ΔBMD = -0.46 [95% CI: -1.05, -0.13]). In contrast, SHypo was not associated with bone loss at any site. CONCLUSION: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.
Keywords: Aged; Asymptomatic Diseases; Bone Density; Female; Fractures, Bone; Humans; Hyperthyroidism; Hypothyroidism; Male; Risk Factors

Association of Alcohol Consumption After Development of Heart Failure With Survival Among Older Adults in the Cardiovascular Health Study. - Sadhu, Justin S; Novak, Eric; Mukamal, Kenneth J; Kizer, Jorge R; Psaty, Bruce M; Stein, Phyllis K; Brown, David L (JAMA Netw Open, 2018)
Importance: More than 1 million older adults develop heart failure annually. The association of alcohol consumption with survival among these individuals after diagnosis is unknown. Objective: To determine whether alcohol use is associated with increased survival among older adults with incident heart failure. Design, Setting, and Participants: This prospective cohort study included 5888 community-dwelling adults aged 65 years or older who were recruited to participate in the Cardiovascular Health Study between June 12, 1989, and June 1993, from 4 US sites. Of the total participants, 393 individuals had a new diagnosis of heart failure within the first 9 years of follow-up through June 2013. The study analysis was performed between January 19, 2016, and September 22, 2016. Exposures: Alcohol consumption was divided into 4 categories: abstainers (never drinkers), former drinkers, 7 or fewer alcoholic drinks per week, and more than 7 drinks per week. Primary Outcomes and Measures: Participant survival after the diagnosis of incident heart failure. Results: Among the 393 adults diagnosed with incident heart failure, 213 (54.2%) were female, 339 (86.3%) were white, and the mean (SD) age was 78.7 (6.0) years. Alcohol consumption after diagnosis was reported in 129 (32.8%) of the participants. Across alcohol consumption categories of long-term abstainers, former drinkers, consumers of 1-7 drinks weekly and consumers of more than 7 drinks weekly, the percentage of men (32.1%, 49.0%, 58.0%, and 82.4%, respectively; P < .001 for trend), white individuals (78.0%, 92.7%, 92.0%, and 94.1%, respectively, P <. 001 for trend), and high-income participants (22.0%, 43.8%, 47.3%, and 64.7%, respectively; P < .001 for trend) increased with increasing alcohol consumption. Across the 4 categories, participants who consumed more alcohol had more years of education (mean, 12 years [interquartile range (IQR), 8.0-10.0 years], 12 years [IQR, 11.0-14.0 years], 13 years [IQR, 12.0-15.0 years], and 13 years [IQR, 12.0-14.0 years]; P < .001 for trend). Diabetes was less common across the alcohol consumption categories (32.1%, 26.0%, 22.3%, and 5.9%, respectively; P = .01 for trend). Across alcohol consumption categories, there were fewer never smokers (58.3%, 44.8%, 35.7%, and 29.4%, respectively; P < .001 for trend) and more former smokers (34.5%, 38.5%, 50.0%, and 52.9%, respectively; P = .006 for trend). After controlling for other factors, consumption of 7 or fewer alcoholic drinks per week was associated with additional mean survival of 383 days (95% CI, 17-748 days; P = .04) compared with abstinence from alcohol. Although the robustness was limited by the small number of individuals who consumed more than 7 drinks per week, a significant inverted U-shaped association between alcohol consumption and survival was observed. Multivariable model estimates of mean time from heart failure diagnosis to death were 2640 days (95% CI, 1967-3313 days) for never drinkers, 3046 days (95% CI, 2372-3719 days) for consumers of 0 to 7 drinks per week, and 2806 (95% CI, 1879-3734 days) for consumers of more than 7 drinks per week (P = .02). Consumption of 10 drinks per week was associated with the longest survival, a mean of 3381 days (95% CI, 2806-3956 days) after heart failure diagnosis. Conclusions and Relevance: These findings suggest that limited alcohol consumption among older adults with incident heart failure is associated with survival benefit compared with long-term abstinence. These findings suggest that older adults who develop heart failure may not need to abstain from moderate levels of alcohol consumption.

Association of biomarker and physiologic indices with mortality in older adults: Cardiovascular Health Study. - Sanders, Jason L; Arnold, Alice M; Boudreau, Robert M; Hirsch, Calvin H; Kizer, Jorge R; Kaplan, Robert C; Cappola, Anne R; Cushman, Mary; Jacob, Mini E; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2018)
Background: A goal of gerontology is discovering aging phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers strongly and independently associated with mortality and which statistically attenuate chronologic age could be used to define such a phenotype. We determined the association of a Biomarker Index (BI) with mortality and compared it to a validated Physiologic Index (PI) in older adults. Methods: The indices were constructed in the Cardiovascular Health Study, mean (SD) age 74.5 (5.1) years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor (IGF)-1, IGF binding protein 3, amino-terminal pro-B-type natriuretic peptide, dehydroepiandrosterone sulfate, and interleukin-6, and was built in test (N=2197) and validation (N=1124) samples. The PI included carotid intima-media thickness, pulmonary capacity, brain white matter grade, cystatin-C, and fasting glucose. Multivariable Cox proportional hazards models predicting death were calculated with 10 years of follow-up. Results: In separate age-adjusted models, the hazard ratio (HR) for mortality per point of the BI was 1.30 (95% CI 1.25, 1.34) and the BI attenuated age by 25%. The HR for the PI was 1.28 (1.24, 1.33) (29% age attenuation). In the same model, the HR for the BI was 1.23 (1.18, 1.28) and for the PI was 1.22 (1.17, 1.26), and age was attenuated 42.5%. Associations persisted after further adjustment. Conclusions: The BI and PI were significantly and independently associated with mortality. Both attenuated the age effect on mortality substantially. The indices may be feasible phenotypes for developing interventions hoping to alter the trajectory of aging.

Association of Cardiovascular Biomarkers With Incident Heart Failure With Preserved and Reduced Ejection Fraction. - de Boer, Rudolf A; Nayor, Matthew; deFilippi, Christopher R; Enserro, Danielle; Bhambhani, Vijeta; Kizer, Jorge R; Blaha, Michael J; Brouwers, Frank P; Cushman, Mary; Lima, João A C; Bahrami, Hossein; van der Harst, Pim; et al. (JAMA Cardiol, 2018)
Importance: Nearly half of all patients with heart failure have preserved ejection fraction (HFpEF) as opposed to reduced ejection fraction (HFrEF), yet associations of biomarkers with future heart failure subtype are incompletely understood. Objective: To evaluate the associations of 12 cardiovascular biomarkers with incident HFpEF vs HFrEF among adults from the general population. Design, Setting, and Participants: This study included 4 longitudinal community-based cohorts: the Cardiovascular Health Study (1989-1990; 1992-1993 for supplemental African-American cohort), the Framingham Heart Study (1995-1998), the Multi-Ethnic Study of Atherosclerosis (2000-2002), and the Prevention of Renal and Vascular End-stage Disease study (1997-1998). Each cohort had prospective ascertainment of incident HFpEF and HFrEF. Data analysis was performed from June 25, 2015, to November 9, 2017. Exposures: The following biomarkers were examined: N-terminal pro B-type natriuretic peptide or brain natriuretic peptide, high-sensitivity troponin T or I, C-reactive protein (CRP), urinary albumin to creatinine ratio (UACR), renin to aldosterone ratio, D-dimer, fibrinogen, soluble suppressor of tumorigenicity, galectin-3, cystatin C, plasminogen activator inhibitor 1, and interleukin 6. Main Outcomes and Measures: Development of incident HFpEF and incident HFrEF. Results: Among the 22 756 participants in these 4 cohorts (12 087 women and 10 669 men; mean [SD] age, 60 [13] years) in the study, during a median follow-up of 12 years, 633 participants developed incident HFpEF, and 841 developed HFrEF. In models adjusted for clinical risk factors of heart failure, 2 biomarkers were significantly associated with incident HFpEF: UACR (hazard ratio [HR], 1.33; 95% CI, 1.20-1.48; P < .001) and natriuretic peptides (HR, 1.27; 95% CI, 1.16-1.40; P < .001), with suggestive associations for high-sensitivity troponin (HR, 1.11; 95% CI, 1.03-1.19; P = .008), plasminogen activator inhibitor 1 (HR, 1.22; 95% CI, 1.03-1.45; P = .02), and fibrinogen (HR, 1.12; 95% CI, 1.03-1.22; P = .01). By contrast, 6 biomarkers were associated with incident HFrEF: natriuretic peptides (HR, 1.54; 95% CI, 1.41-1.68; P < .001), UACR (HR, 1.21; 95% CI, 1.11-1.32; P < .001), high-sensitivity troponin (HR, 1.37; 95% CI, 1.29-1.46; P < .001), cystatin C (HR, 1.19; 95% CI, 1.11-1.27; P < .001), D-dimer (HR, 1.22; 95% CI, 1.11-1.35; P < .001), and CRP (HR, 1.19; 95% CI, 1.11-1.28; P < .001). When directly compared, natriuretic peptides, high-sensitivity troponin, and CRP were more strongly associated with HFrEF compared with HFpEF. Conclusions and Relevance: Biomarkers of renal dysfunction, endothelial dysfunction, and inflammation were associated with incident HFrEF. By contrast, only natriuretic peptides and UACR were associated with HFpEF. These findings highlight the need for future studies focused on identifying novel biomarkers of the risk of HFpEF.

Association of lipoprotein-associated phospholipase A and risk of incident atrial fibrillation: Findings from 3 cohorts. - Garg, Parveen K; Bartz, Traci M; Norby, Faye L; Jorgensen, Neal W; McClelland, Robyn L; Ballantyne, Christie M; Chen, Lin Y; Gottdiener, John S; Greenland, Philip; Hoogeveen, Ron; Jenny, Nancy S; Kizer, Jorge R; et al. (Am Heart J, 2018)
BACKGROUND: Multiple prospective studies have established an association between inflammation and higher risk of atrial fibrillation (AF), but the association between lipoprotein-associated phospholipase A (Lp-PLA) mass and activity and incident AF has not been extensively evaluated. METHODS: Using data from 10,794 Atherosclerosis Risk In Communities (ARIC) study participants aged 53-75 years, 5,181 Cardiovascular Health Study (CHS) participants aged 65 to 100 years, and 5,425 Multi-Ethnic Study of Atherosclerosis (MESA) participants aged 45-84 years, we investigated the association between baseline Lp-PLA levels and the risk of developing AF. Incident AF was identified in each cohort by follow-up visit electrocardiograms, hospital discharge coding of AF, or Medicare claims data. RESULTS: Over a mean of 13.1, 11.5, and 10.0 years of follow-up, 1,439 (13%), 2,084 (40%), and 615 (11%) incident AF events occurred in ARIC, CHS, and MESA, respectively. In adjusted analyses, each SD increment in Lp-PLA activity was associated with incident AF in both ARIC (hazard ratio [HR] 1.13, 95% CI 1.06-1.20) and MESA (HR 1.24, 95% CI 1.05-1.46). Each SD increment in Lp-PLA mass was also associated with incident AF in MESA (HR 1.25, 95% CI 1.11-1.41). No significant associations were observed among CHS participants. CONCLUSIONS: Although higher Lp-PLA mass and activity were associated with development of AF in ARIC and MESA, this relationship was not observed in CHS, a cohort of older individuals.

The Association of Obesity and Cardiometabolic Traits With Incident HFpEF and HFrEF. - Savji, Nazir; Meijers, Wouter C; Bartz, Traci M; Bhambhani, Vijeta; Cushman, Mary; Nayor, Matthew; Kizer, Jorge R; Sarma, Amy; Blaha, Michael J; Gansevoort, Ron T; Gardin, Julius M; Hillege, Hans L; et al. (JACC Heart Fail, 2018)
OBJECTIVES: This study evaluated the associations of obesity and cardiometabolic traits with incident heart failure with preserved versus reduced ejection fraction (HFpEF vs. HFrEF). Given known sex differences in HF subtype, we examined men and women separately. BACKGROUND: Recent studies suggest that obesity confers greater risk of HFpEF versus HFrEF. Contributions of associated metabolic traits to HFpEF are less clear. METHODS: We studied 22,681 participants from 4 community-based cohorts followed for incident HFpEF versus HFrEF (ejection fraction ≥50% vs. <50%). We evaluated the association of body mass index (BMI) and cardiometabolic traits with incident HF subtype using Cox models. RESULTS: The mean age was 60 ± 13 years, and 53% were women. Over a median follow-up of 12 years, 628 developed incident HFpEF and 835 HFrEF. Greater BMI portended higher risk of HFpEF compared with HFrEF (hazard ratio [HR]: 1.34 per 1-SD increase in BMI; 95% confidence interval [CI]: 1.24 to 1.45 vs. HR: 1.18; 95% CI: 1.10 to 1.27). Similarly, insulin resistance (homeostatic model assessment of insulin resistance) was associated with HFpEF (HR: 1.20 per 1-SD; 95% CI: 1.05 to 1.37), but not HFrEF (HR: 0.99; 95% CI: 0.88 to 1.11; p < 0.05 for difference HFpEF vs. HFrEF). We found that the differential association of BMI with HFpEF versus HFrEF was more pronounced among women (p for difference HFpEF vs. HFrEF = 0.01) when compared with men (p = 0.34). CONCLUSIONS: Obesity and related cardiometabolic traits including insulin resistance are more strongly associated with risk of future HFpEF versus HFrEF. The differential risk of HFpEF with obesity seems particularly pronounced among women and may underlie sex differences in HF subtypes.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

{Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies - Huang, T.; Ding, M.; Bergholdt, H. K. M.; Wang, T.; Heianza, Y.; Sun, D.; Frazier-Wood, A. C.; Aslibekyan, S.; North, K. E.; Voortman, T.; Graff, M.; Smith, C. E.; et al. (Clin Chem, 2018)
Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined.\ We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene (LCT-13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between (a) dairy intake and BMI, (b) rs4988235 and dairy intake, and (c) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies.\ Higher dairy intake was associated with higher BMI (β = 0.03 kg/m2 per serving/day; 95% CI, 0.00-0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14-0.25) serving/day higher dairy intake (P = 3.15 × 10-12) and 0.12 (95% CI, 0.06-0.17) kg/m2 higher BMI (P = 2.11 × 10-5). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m2 per serving/day; 95% CI, 0.27-0.92; P = 3.0 × 10-4).\ The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.

Development, Construct Validity, and Predictive Validity of a Continuous Frailty Scale: Results from Two Large U.S. Cohorts. - Wu, Chenkai; Geldhof, G John; Xue, Qian-Li; Kim, Dae H; Newman, Anne B; Odden, Michelle C (Am J Epidemiol, 2018)
Frailty is an age-related clinical syndrome of decreased resilience to stressors. Among numerous assessments of frailty, the frailty phenotype (FP) scale, proposed by Fried and colleagues has been the most widely used one. We aimed to develop a continuous frailty scale that may overcome limitations facing the categorical FP scale and to evaluate its construct validity, predictive validity, and measurement properties. Data were from the Cardiovascular Health Study (N = 4243) and Health and Retirement Study (N = 7600). Frailty was conceptualized as a continuous construct, measured by five measures used in FP scale: gait speed, grip strength, exhaustion, physical activity, and weight loss. We used confirmatory factor analysis to investigate the relationship between five indicators and the latent frailty construct. We examined the association of the continuous frailty scale with mortality and disability. The unidimensional model fit the data satisfactorily; similar factor structure was observed across two cohorts. Gait speed and weight loss were the strongest and weakest indicators, respectively; grip strength, exhaustion, and physical activity had similar strength in measuring frailty. In each cohort, the continuous frailty scale was strongly associated with mortality and disability and persisted to be associated with outcomes among robust and prefrail persons classified by the FP scale.

Discovery, fine-mapping, and conditional analyses of genetic variants associated with C-reactive protein in multiethnic populations using the Metabochip in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Kocarnik, Jonathan M; Richard, Melissa; Graff, Misa; Haessler, Jeffrey; Bien, Stephanie; Carlson, Chris; Carty, Cara L; Reiner, Alexander P; Avery, Christy L; Ballantyne, Christie M; LaCroix, Andrea Z; Assimes, Themistocles L; et al. (Hum Mol Genet, 2018)
C-reactive protein (CRP) is a circulating biomarker indicative of systemic inflammation. We aimed to evaluate genetic associations with CRP levels among non-European-ancestry populations through discovery, fine-mapping and conditional analyses. A total of 30 503 non-European-ancestry participants from 6 studies participating in the Population Architecture using Genomics and Epidemiology study had serum high-sensitivity CRP measurements and ∼200 000 single nucleotide polymorphisms (SNPs) genotyped on the Metabochip. We evaluated the association between each SNP and log-transformed CRP levels using multivariate linear regression, with additive genetic models adjusted for age, sex, the first four principal components of genetic ancestry, and study-specific factors. Differential linkage disequilibrium patterns between race/ethnicity groups were used to fine-map regions associated with CRP levels. Conditional analyses evaluated for multiple independent signals within genetic regions. One hundred and sixty-three unique variants in 12 loci in overall or race/ethnicity-stratified Metabochip-wide scans reached a Bonferroni-corrected P-value <2.5E-7. Three loci have no (HACL1, OLFML2B) or only limited (PLA2G6) previous associations with CRP levels. Six loci had different top hits in race/ethnicity-specific versus overall analyses. Fine-mapping refined the signal in six loci, particularly in HNF1A. Conditional analyses provided evidence for secondary signals in LEPR, IL1RN and HNF1A, and for multiple independent signals in CRP and APOE. We identified novel variants and loci associated with CRP levels, generalized known CRP associations to a multiethnic study population, refined association signals at several loci and found evidence for multiple independent signals at several well-known loci. This study demonstrates the benefit of conducting inclusive genetic association studies in large multiethnic populations.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Generalization and fine mapping of red blood cell trait genetic associations to multi-ethnic populations: The PAGE Study. - Jo Hodonsky, Chani; Schurmann, Claudia; Schick, Ursula M; Kocarnik, Jonathan; Tao, Ran; van Rooij, Frank Ja; Wassel, Christina; Buyske, Steve; Fornage, Myriam; Hindorff, Lucia A; Floyd, James S; Ganesh, Santhi K; et al. (Am J Hematol, 2018)
Red blood cell (RBC) traits provide insight into a wide range of physiological states and exhibit moderate to high heritability, making them excellent candidates for genetic studies to inform underlying biologic mechanisms. Previous RBC trait genome-wide association studies were performed primarily in European- or Asian-ancestry populations, missing opportunities to inform understanding of RBC genetic architecture in diverse populations and reduce intervals surrounding putative functional SNPs through fine-mapping. Here, we report the first fine-mapping of six correlated (Pearson's r range: |0.04 - 0.92|) RBC traits in up to 19,036 African Americans and 19,562 Hispanic/Latinos participants of the Population Architecture using Genomics and Epidemiology (PAGE) consortium. Trans-ethnic meta-analysis of race/ethnic- and study-specific estimates for approximately 11,000 SNPs flanking 13 previously identified association signals as well as 150,000 additional array-wide SNPs was performed using inverse-variance meta-analysis after adjusting for study and clinical covariates. Approximately half of previously reported index SNP-RBC trait associations generalized to the trans-ethnic study population (p<1.7x10 ); previously unreported independent association signals within the ABO region reinforce the potential for multiple functional variants affecting the same locus. Trans-ethnic fine-mapping did not reveal additional signals at the HFE locus independent of the known functional variants. Finally, we identified a potential novel association in the Hispanic/Latino study population at the HECTD4/RPL6 locus for RBC count (p=1.9x10 ). The identification of a previously unknown association, generalization of a large proportion of known association signals, and refinement of known association signals all exemplify the benefits of genetic studies in diverse populations. This article is protected by copyright. All rights reserved.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genetic Variation in Genes Underlying Diverse Dementias May Explain a Small Proportion of Cases in the Alzheimer's Disease Sequencing Project. - Blue, Elizabeth E; Bis, Joshua C; Dorschner, Michael O; Tsuang, Debby W; Barral, Sandra M; Beecham, Gary; Below, Jennifer E; Bush, William S; Butkiewicz, Mariusz; Cruchaga, Carlos; DeStefano, Anita; Farrer, Lindsay A; et al. (Dement Geriatr Cogn Disord, 2018)
BACKGROUND/AIMS: The Alzheimer's Disease Sequencing Project (ADSP) aims to identify novel genes influencing Alzheimer's disease (AD). Variants within genes known to cause dementias other than AD have previously been associated with AD risk. We describe evidence of co-segregation and associations between variants in dementia genes and clinically diagnosed AD within the ADSP. METHODS: We summarize the properties of known pathogenic variants within dementia genes, describe the co-segregation of variants annotated as "pathogenic" in ClinVar and new candidates observed in ADSP families, and test for associations between rare variants in dementia genes in the ADSP case-control study. The participants were clinically evaluated for AD, and they represent European, Caribbean Hispanic, and isolate Dutch populations. RESULTS/CONCLUSIONS: Pathogenic variants in dementia genes were predominantly rare and conserved coding changes. Pathogenic variants within ARSA, CSF1R, and GRN were observed, and candidate variants in GRN and CHMP2B were nominated in ADSP families. An independent case-control study provided evidence of an association between variants in TREM2, APOE, ARSA, CSF1R, PSEN1, and MAPT and risk of AD. Variants in genes which cause dementing disorders may influence the clinical diagnosis of AD in a small proportion of cases within the ADSP.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association study and meta-analysis identify loci associated with ventricular and supraventricular ectopy. - Napier, Melanie D; Franceschini, Nora; Gondalia, Rahul; Stewart, James D; Méndez-Giráldez, Rául; Sitlani, Colleen M; Seyerle, Amanda A; Highland, Heather M; Li, Yun; Wilhelmsen, Kirk C; Yan, Song; Duan, Qing; et al. (Sci Rep, 2018)
The genetic basis of supraventricular and ventricular ectopy (SVE, VE) remains largely uncharacterized, despite established genetic mechanisms of arrhythmogenesis. To identify novel genetic variants associated with SVE/VE in ancestrally diverse human populations, we conducted a genome-wide association study of electrocardiographically identified SVE and VE in five cohorts including approximately 43,000 participants of African, European and Hispanic/Latino ancestry. In thirteen ancestry-stratified subgroups, we tested multivariable-adjusted associations of SVE and VE with single nucleotide polymorphism (SNP) dosage. We combined subgroup-specific association estimates in inverse variance-weighted, fixed-effects and Bayesian meta-analyses. We also combined fixed-effects meta-analytic t-test statistics for SVE and VE in multi-trait SNP association analyses. No loci reached genome-wide significance in trans-ethnic meta-analyses. However, we found genome-wide significant SNPs intronic to an apoptosis-enhancing gene previously associated with QRS interval duration (FAF1; lead SNP rs7545860; effect allele frequency = 0.02; P = 2.0 × 10) in multi-trait analysis among European ancestry participants and near a locus encoding calcium-dependent glycoproteins (DSC3; lead SNP rs8086068; effect allele frequency = 0.17) in meta-analysis of SVE (P = 4.0 × 10) and multi-trait analysis (P = 2.9 × 10) among African ancestry participants. The novel findings suggest several mechanisms by which genetic variation may predispose to ectopy in humans and highlight the potential value of leveraging pleiotropy in future studies of ectopy-related phenotypes.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

Genome-wide meta-analysis of SNP-by9-ACEI/ARB and SNP-by-thiazide diuretic and effect on serum potassium in cohorts of European and African ancestry. - Irvin, Marguerite R; Sitlani, Colleen M; Noordam, Raymond; Avery, Christie L; Bis, Joshua C; Floyd, James S; Li, Jin; Limdi, Nita A; Srinivasasainagendra, Vinodh; Stewart, James; de Mutsert, Renée; Mook-Kanamori, Dennis O; et al. (Pharmacogenomics J, 2018)
We evaluated interactions of SNP-by-ACE-I/ARB and SNP-by-TD on serum potassium (K+) among users of antihypertensive treatments (anti-HTN). Our study included seven European-ancestry (EA) (N = 4835) and four African-ancestry (AA) cohorts (N = 2016). We performed race-stratified, fixed-effect, inverse-variance-weighted meta-analyses of 2.5 million SNP-by-drug interaction estimates; race-combined meta-analysis; and trans-ethnic fine-mapping. Among EAs, we identified 11 significant SNPs (P < 5 × 10) for SNP-ACE-I/ARB interactions on serum K+ that were located between NR2F1-AS1 and ARRDC3-AS1 on chromosome 5 (top SNP rs6878413 P = 1.7 × 10; ratio of serum K+ in ACE-I/ARB exposed compared to unexposed is 1.0476, 1.0280, 1.0088 for the TT, AT, and AA genotypes, respectively). Trans-ethnic fine mapping identified the same group of SNPs on chromosome 5 as genome-wide significant for the ACE-I/ARB analysis. In conclusion, SNP-by-ACE-I /ARB interaction analyses uncovered loci that, if replicated, could have future implications for the prevention of arrhythmias due to anti-HTN treatment-related hyperkalemia. Before these loci can be identified as clinically relevant, future validation studies of equal or greater size in comparison to our discovery effort are needed.

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Harmonization of Respiratory Data From 9 US Population-Based Cohorts: The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Cassano, Patricia A; Couper, David; Enright, Paul L; Folsom, Aaron R; Hankinson, John; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Kronmal, Richard; Lange, Leslie; et al. (Am J Epidemiol, 2018)
Chronic lower respiratory diseases (CLRDs) are the fourth leading cause of death in the United States. To support investigations into CLRD risk determinants and new approaches to primary prevention, we aimed to harmonize and pool respiratory data from US general population-based cohorts. Data were obtained from prospective cohorts that performed prebronchodilator spirometry and were harmonized following 2005 ATS/ERS standards. In cohorts conducting follow-up for noncardiovascular events, CLRD events were defined as hospitalizations/deaths adjudicated as CLRD-related or assigned relevant administrative codes. Coding and variable names were applied uniformly. The pooled sample included 65,251 adults in 9 cohorts followed-up for CLRD-related mortality over 653,380 person-years during 1983-2016. Average baseline age was 52 years; 56% were female; 49% were never-smokers; and racial/ethnic composition was 44% white, 22% black, 28% Hispanic/Latino, and 5% American Indian. Over 96% had complete data on smoking, clinical CLRD diagnoses, and dyspnea. After excluding invalid spirometry examinations (13%), there were 105,696 valid examinations (median, 2 per participant). Of 29,351 participants followed for CLRD hospitalizations, median follow-up was 14 years; only 5% were lost to follow-up at 10 years. The NHLBI Pooled Cohorts Study provides a harmonization standard applied to a large, US population-based sample that may be used to advance epidemiologic research on CLRD.

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

Large-scale whole-exome sequencing association studies identify rare functional variants influencing serum urate levels. - Tin, Adrienne; Li, Yong; Brody, Jennifer A; Nutile, Teresa; Chu, Audrey Y; Huffman, Jennifer E; Yang, Qiong; Chen, Ming-Huei; Robinson-Cohen, Cassianne; Mace, Aurelien; Liu, Jun; Demirkan, Ayse; et al. (Nat Commun, 2018)
Elevated serum urate levels can cause gout, an excruciating disease with suboptimal treatment. Previous GWAS identified common variants with modest effects on serum urate. Here we report large-scale whole-exome sequencing association studies of serum urate and kidney function among ≤19,517 European ancestry and African-American individuals. We identify aggregate associations of low-frequency damaging variants in the urate transporters SLC22A12 (URAT1; p = 1.3 × 10) and SLC2A9 (p = 4.5 × 10). Gout risk in rare SLC22A12 variant carriers is halved (OR = 0.5, p = 4.9 × 10). Selected rare variants in SLC22A12 are validated in transport studies, confirming three as loss-of-function (R325W, R405C, and T467M) and illustrating the therapeutic potential of the new URAT1-blocker lesinurad. In SLC2A9, mapping of rare variants of large effects onto the predicted protein structure reveals new residues that may affect urate binding. These findings provide new insights into the genetic architecture of serum urate, and highlight molecular targets in SLC22A12 and SLC2A9 for lowering serum urate and preventing gout.
Keywords: Exome; Genetic Predisposition to Disease; Glucose Transport Proteins, Facilitative; Humans; Kidney Function Tests; Meta-Analysis as Topic; Organic Anion Transporters; Organic Cation Transport Proteins; Protein Structure, Secondary; Uric Acid

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Long-Term Cognitive Decline After Newly Diagnosed Heart Failure: Longitudinal Analysis in the CHS (Cardiovascular Health Study). - Hammond, Christa A; Blades, Natalie J; Chaudhry, Sarwat I; Dodson, John A; Longstreth, W T; Heckbert, Susan R; Psaty, Bruce M; Arnold, Alice M; Dublin, Sascha; Sitlani, Colleen M; Gardin, Julius M; Thielke, Stephen M; et al. (Circ Heart Fail, 2018)
BACKGROUND: Heart failure (HF) is associated with cognitive impairment. However, we know little about the time course of cognitive change after HF diagnosis, the importance of comorbid atrial fibrillation, or the role of ejection fraction. We sought to determine the associations of incident HF with rates of cognitive decline and whether these differed by atrial fibrillation status or reduced versus preserved ejection fraction. METHODS AND RESULTS: Participants were 4864 men and women aged ≥65 years without a history of HF and free of clinical stroke in the CHS (Cardiovascular Health Study)-a community-based prospective cohort study in the United States, with cognition assessed annually from 1989/1990 through 1998/1999. We identified 496 participants with incident HF by review of hospital discharge summaries and Medicare claims data, with adjudication according to standard criteria. Global cognitive ability was measured by the Modified Mini-Mental State Examination. In adjusted models, 5-year decline in model-predicted mean Modified Mini-Mental State Examination score was 10.2 points (95% confidence interval, 8.6-11.8) after incident HF diagnosed at 80 years of age, compared with a mean 5-year decline of 5.8 points (95% confidence interval, 5.3-6.2) from 80 to 85 years of age without HF. The association was stronger at older ages than at younger ages, did not vary significantly in the presence versus absence of atrial fibrillation (=0.084), and did not vary significantly by reduced versus preserved ejection fraction (=0.734). CONCLUSIONS: Decline in global cognitive ability tends to be faster after HF diagnosis than without HF. Clinical and public health implications of this finding warrant further attention.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Rare loss of function variants in candidate genes and risk of colorectal cancer. - Rosenthal, Elisabeth A; Shirts, Brian H; Amendola, Laura M; Horike-Pyne, Martha; Robertson, Peggy D; Hisama, Fuki M; Bennett, Robin L; Dorschner, Michael O; Nickerson, Deborah A; Stanaway, Ian B; Nassir, Rami; Vickers, Kathy T; et al. (Hum Genet, 2018)
Although ~ 25% of colorectal cancer or polyp (CRC/P) cases show familial aggregation, current germline genetic testing identifies a causal genotype in the 16 major genes associated with high penetrance CRC/P in only 20% of these cases. As there are likely other genes underlying heritable CRC/P, we evaluated the association of variation at novel loci with CRC/P. We evaluated 158 a priori selected candidate genes by comparing the number of rare potentially disruptive variants (PDVs) found in 84 CRC/P cases without an identified CRC/P risk-associated variant and 2440 controls. We repeated this analysis using an additional 73 CRC/P cases. We also compared the frequency of PDVs in select genes among CRC/P cases with two publicly available data sets. We found a significant enrichment of PDVs in cases vs. controls: 20% of cases vs. 11.5% of controls with ≥ 1 PDV (OR = 1.9, p = 0.01) in the original set of cases. Among the second cohort of CRC/P cases, 18% had a PDV, significantly different from 11.5% (p = 0.02). Logistic regression, adjusting for ancestry and multiple testing, indicated association between CRC/P and PDVs in NTHL1 (p = 0.0001), BRCA2 (p = 0.01) and BRIP1 (p = 0.04). However, there was no significant difference in the frequency of PDVs at each of these genes between all 157 CRC/P cases and two publicly available data sets. These results suggest an increased presence of PDVs in CRC/P cases and support further investigation of the association of NTHL1, BRCA2 and BRIP1 variation with CRC/P.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium. - Inker, Lesley A; Grams, Morgan E; Levey, Andrew S; Coresh, Josef; Cirillo, Massimo; Collins, John F; Gansevoort, Ron T; Gutierrez, Orlando M; Hamano, Takayuki; Heine, Gunnar H; Ishikawa, Shizukiyo; Jee, Sun Ha; et al. (Am J Kidney Dis, 2018)
RATIONALE & OBJECTIVE: Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework. STUDY DESIGN: Cross-sectional individual participant-level analyses in a global consortium. SETTING & STUDY POPULATIONS: 17 CKD and 38 general population and high-risk cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension. DATA EXTRACTION: Data were obtained and analyzed between July 2015 and January 2018. ANALYTICAL APPROACH: We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses. RESULTS: The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g). LIMITATIONS: Variations in study era, health care delivery system, typical diet, and laboratory assays. CONCLUSIONS: Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Reversal of Aging-Induced Increases in Aortic Stiffness by Targeting Cytoskeletal Protein-Protein Interfaces. - Nicholson, Christopher J; Singh, Kuldeep; Saphirstein, Robert J; Gao, Yuan Z; Li, Qian; Chiu, Joanna G; Leavis, Paul; Verwoert, Germaine C; Mitchell, G F; Porter, Tyrone; Morgan, Kathleen G (J Am Heart Assoc, 2018)
BACKGROUND: The proximal aorta normally functions as a critical shock absorber that protects small downstream vessels from damage by pressure and flow pulsatility generated by the heart during systole. This shock absorber function is impaired with age because of aortic stiffening. METHODS AND RESULTS: We examined the contribution of common genetic variation to aortic stiffness in humans by interrogating results from the AortaGen Consortium genome-wide association study of carotid-femoral pulse wave velocity. Common genetic variation in the N-WASP () locus is associated with carotid-femoral pulse wave velocity (rs600420, =0.0051). Thus, we tested the hypothesis that decoy proteins designed to disrupt the interaction of cytoskeletal proteins such as N-WASP with its binding partners in the vascular smooth muscle cytoskeleton could decrease ex vivo stiffness of aortas from a mouse model of aging. A synthetic decoy peptide construct of N-WASP significantly reduced activated stiffness in ex vivo aortas of aged mice. Two other cytoskeletal constructs targeted to VASP and talin-vinculin interfaces similarly decreased aging-induced ex vivo active stiffness by on-target specific actions. Furthermore, packaging these decoy peptides into microbubbles enables the peptides to be ultrasound-targeted to the wall of the proximal aorta to attenuate ex vivo active stiffness. CONCLUSIONS: We conclude that decoy peptides targeted to vascular smooth muscle cytoskeletal protein-protein interfaces and microbubble packaged can decrease aortic stiffness ex vivo. Our results provide proof of concept at the ex vivo level that decoy peptides targeted to cytoskeletal protein-protein interfaces may lead to substantive dynamic modulation of aortic stiffness.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Serial circulating omega 3 polyunsaturated fatty acids and healthy ageing among older adults in the Cardiovascular Health Study: prospective cohort study. - Lai, Heidi Tm; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; McKnight, Barbara; Song, Xiaoling; King, Irena B; Chaves, Paulo Hm; Odden, Michelle C; Newman, Anne B; Siscovick, David S; Mozaffarian, Dariush (BMJ, 2018)
OBJECTIVE: To determine the longitudinal association between serial biomarker measures of circulating omega 3 polyunsaturated fatty acid (n3-PUFA) levels and healthy ageing. DESIGN: Prospective cohort study. SETTING: Four communities in the United States (Cardiovascular Health Study) from 1992 to 2015. PARTICIPANTS: 2622 adults with a mean (SD) age of 74.4 (4.8) and with successful healthy ageing at baseline in 1992-93. EXPOSURE: Cumulative levels of plasma phospholipid n3-PUFAs were measured using gas chromatography in 1992-93, 1998-99, and 2005-06, expressed as percentage of total fatty acids, including α-linolenic acid from plants and eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid from seafoood. MAIN OUTCOME MEASURE: Healthy ageing defined as survival without chronic diseases (ie, cardiovascular disease, cancer, lung disease, and severe chronic kidney disease), the absence of cognitive and physical dysfunction, or death from other causes not part of the healthy ageing outcome after age 65. Events were centrally adjudicated or determined from medical records and diagnostic tests. RESULTS: Higher levels of long chain n3-PUFAs were associated with an 18% lower risk (95% confidence interval 7% to 28%) of unhealthy ageing per interquintile range after multivariable adjustments with time-varying exposure and covariates. Individually, higher eicosapentaenoic acid and docosapentaenoic acid (but not docosahexaenoic acid) levels were associated with a lower risk: 15% (6% to 23%) and 16% (6% to 25%), respectively. α-linolenic acid from plants was not noticeably associated with unhealthy ageing (hazard ratio 0.92, 95% confidence interval 0.83 to 1.02). CONCLUSIONS: In older adults, a higher cumulative level of serially measured circulating n3-PUFAs from seafood (eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid), eicosapentaenoic acid, and docosapentaenoic acid (but not docosahexaenoic acid from seafood or α-linolenic acid from plants) was associated with a higher likelihood of healthy ageing. These findings support guidelines for increased dietary consumption of n3-PUFAs in older adults.

Sleep characteristics that predict atrial fibrillation. - Christensen, Matthew A; Dixit, Shalini; Dewland, Thomas A; Whitman, Isaac R; Nah, Gregory; Vittinghoff, Eric; Mukamal, Kenneth J; Redline, Susan; Robbins, John A; Newman, Anne B; Patel, Sanjay R; Magnani, Jared W; et al. (Heart Rhythm, 2018)
BACKGROUND: The relationship between sleep disruption, independent of obstructive sleep apnea (OSA), and atrial fibrillation (AF) is unknown. OBJECTIVE: The purpose of this study was to determine whether poor sleep itself is a risk factor for AF. METHODS: We first performed an analysis of participants in the Health eHeart Study and validated those findings in the longitudinal Cardiovascular Health Study, including a subset of patients undergoing polysomnography. To determine whether the observed relationships readily translated to medical practice, we examined 2005-2009 data from the California Healthcare Cost and Utilization Project. RESULTS: Among 4553 Health eHeart participants, the 526 with AF exhibited more frequent nighttime awakening (odd ratio [OR] 1.47; 95% confidence interval [CI] 1.14-1.89; P = .003). In 5703 Cardiovascular Health Study participants followed for a median 11.6 years, frequent nighttime awakening predicted a 33% greater risk of AF (hazard ratio [HR] 1.33; 95% CI 1.17-1.51; P <.001). In patients with polysomnography (N = 1127), every standard deviation percentage decrease in rapid eye movement (REM) sleep was associated with a 18% higher risk of developing AF (HR 1.18; 95% CI 1.00-1.38; P = .047). Among 14,330,651 California residents followed for a median 3.9 years, an insomnia diagnosis predicted a 36% increased risk of new AF (HR 1.36; 95% CI 1.30-1.42; P <.001). CONCLUSION: Sleep disruption consistently predicted AF before and after adjustment for OSA and other potential confounders across several different populations. Sleep quality itself may be important in the pathogenesis of AF, potentially representing a novel target for prevention.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Sugar-sweetened beverage intake associations with fasting glucose and insulin concentrations are not modified by selected genetic variants in a ChREBP-FGF21 pathway: a meta-analysis. - McKeown, Nicola M; Dashti, Hassan S; Ma, Jiantao; Haslam, Danielle E; Kiefte-de Jong, Jessica C; Smith, Caren E; Tanaka, Toshiko; Graff, Mariaelisa; Lemaitre, Rozenn N; Rybin, Denis; Sonestedt, Emily; Frazier-Wood, Alexis C; et al. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Sugar-sweetened beverages (SSBs) are a major dietary contributor to fructose intake. A molecular pathway involving the carbohydrate responsive element-binding protein (ChREBP) and the metabolic hormone fibroblast growth factor 21 (FGF21) may influence sugar metabolism and, thereby, contribute to fructose-induced metabolic disease. We hypothesise that common variants in 11 genes involved in fructose metabolism and the ChREBP-FGF21 pathway may interact with SSB intake to exacerbate positive associations between higher SSB intake and glycaemic traits. METHODS: Data from 11 cohorts (six discovery and five replication) in the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided association and interaction results from 34,748 adults of European descent. SSB intake (soft drinks, fruit punches, lemonades or other fruit drinks) was derived from food-frequency questionnaires and food diaries. In fixed-effects meta-analyses, we quantified: (1) the associations between SSBs and glycaemic traits (fasting glucose and fasting insulin); and (2) the interactions between SSBs and 18 independent SNPs related to the ChREBP-FGF21 pathway. RESULTS: In our combined meta-analyses of discovery and replication cohorts, after adjustment for age, sex, energy intake, BMI and other dietary covariates, each additional serving of SSB intake was associated with higher fasting glucose (β ± SE 0.014 ± 0.004 [mmol/l], p = 1.5 × 10-3) and higher fasting insulin (0.030 ± 0.005 [log e pmol/l], p = 2.0 × 10-10). No significant interactions on glycaemic traits were observed between SSB intake and selected SNPs. While a suggestive interaction was observed in the discovery cohorts with a SNP (rs1542423) in the β-Klotho (KLB) locus on fasting insulin (0.030 ± 0.011 log e pmol/l, uncorrected p = 0.006), results in the replication cohorts and combined meta-analyses were non-significant. CONCLUSIONS/INTERPRETATION: In this large meta-analysis, we observed that SSB intake was associated with higher fasting glucose and insulin. Although a suggestive interaction with a genetic variant in the ChREBP-FGF21 pathway was observed in the discovery cohorts, this observation was not confirmed in the replication analysis. TRIAL REGISTRATION: Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005121 (Framingham Offspring Study), NCT00005487 (Multi-Ethnic Study of Atherosclerosis) and NCT00005152 (Nurses' Health Study).

Trajectories of Nonagenarian Health: Gender, Age, and Period Effects. - Odden, Michelle C; Koh, William Jen Hoe; Arnold, Alice M; Rawlings, Andreea M; Psaty, Bruce M; Newman, Anne B (Am J Epidemiol, 2018)
The US population aged 90 years and older is growing rapidly and there are limited data on their health. The Cardiovascular Health Study is a prospective study of black and white adults ≥65 years recruited in two waves (1989-90 and 1992-93) from Medicare eligibility lists in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. We created a synthetic cohort of the 1,889 participants who had reached age 90 at baseline or during follow-up through July 16th, 2015. Participants entered the cohort at 90 years and we evaluated their changes in health after age 90 (median [IQR] follow-up: 3 [1.3-5] years). Measures of health included cardiovascular events, cognitive function, depressive symptoms, prescription medications, self-rated health, and measures of functional status. The mortality rate was high: 19.0 (95% CI: 17.8, 20.3) per 100 person-years in women and 20.9 (95% CI: 19.2, 22.8) in men. Cognitive function and all measures of functional status declined with age; these changes were similar by gender. When we isolated period effects, we found that medications use increased over time. These estimates can help inform future research and health care systems to meet the needs of this growing population.

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Validation of the REGARDS Severe Sepsis Risk Score. - Wang, Henry E; Donnelly, John P; Yende, Sachin; Levitan, Emily B; Shapiro, Nathan I; Dai, Yuling; Zhao, Hong; Heiss, Gerardo; Odden, Michelle; Newman, Anne; Safford, Monika (J Clin Med, 2018)
There are no validated systems for characterizing long-term risk of severe sepsis in community-dwelling adults. We tested the ability of the REasons for Geographic and Racial Differences in Stroke-Severe Sepsis Risk Score (REGARDS-SSRS) to predict 10-year severe sepsis risk in separate cohorts of community-dwelling adults. We internally tested the REGARDS-SSRS on the REGARDS-Medicare subcohort. We then externally validated the REGARDS-SSRS using (1) the Cardiovascular Health Study (CHS) and (2) the Atherosclerosis Risk in Communities (ARIC) cohorts. Participants included community-dwelling adults: REGARDS-Medicare, age ≥65 years, = 9522; CHS, age ≥65 years, = 5888; ARIC, age 45⁻64 years, = 11,584. The primary exposure was 10-year severe sepsis risk, predicted by the REGARDS-SSRS from participant sociodemographics, health behaviors, chronic medical conditions and select biomarkers. The primary outcome was first severe sepsis hospitalizations, defined as the concurrent presence of ICD-9 discharge diagnoses for a serious infection and organ dysfunction. Median SSRS in the cohorts were: REGARDS-Medicare 11 points (IQR 7⁻16), CHS 10 (IQR 6⁻15), ARIC 7 (IQR 5⁻10). Severe sepsis incidence rates were: REGARDS-Medicare 30.7 per 1000 person-years (95% CI: 29.2⁻32.2); CHS 11.9 (10.9⁻12.9); ARIC 6.8 (6.3⁻7.3). SSRS discrimination for first severe sepsis events were: REGARDS-Medicare C-statistic 0.704 (95% CI: 0.691⁻0.718), CHS 0.696 (0.675⁻0.716), ARIC 0.697 (0.677⁻0.716). The REGARDS-SRSS may potentially play a role in identifying community-dwelling adults at high severe sepsis risk.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Whole genome sequencing of Caribbean Hispanic families with late-onset Alzheimer's disease. - Vardarajan, Badri N; Barral, Sandra; Jaworski, James; Beecham, Gary W; Blue, Elizabeth; Tosto, Giuseppe; Reyes-Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al. (Ann Clin Transl Neurol, 2018)
Objective: To identify rare causal variants underlying known loci that segregate with late-onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case-control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene-based associations with disease within LOAD GWAS loci. Results: A variant in p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07-30.9, = 0.041). In addition, missense mutations in and under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow-up genotyping both were nominally significant ( < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including ( = 0.049), ( = 0.0098) and ( = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.

The Accuracy of Cardiovascular Pooled Cohort Risk Estimates in U.S. Older Adults. - Nanna, Michael G; Peterson, Eric D; Wojdyla, Daniel; Navar, Ann Marie (J Gen Intern Med, 2019)
BACKGROUND: The ACC/AHA guidelines for primary prevention rely on the Pooled Cohort Risk Equations (PCE) risk estimates of atherosclerotic cardiovascular disease (ASCVD) to guide treatment decisions. In light of the PCE being derived in younger populations, their accuracy in older adults is uncertain. OBJECTIVE: To evaluate the predictive accuracy and calibration of the PCE in older individuals. DESIGN AND SETTING: We estimated CVD predicted and observed risk among individuals from four large prospective cohort studies: Cardiovascular Health Study, Multiethnic Study of Atherosclerosis, Framingham Original, and Framingham Offspring. PARTICIPANTS: 12,527 overall individuals without ASCVD, including 9864 individuals aged 40-74 years and 2663 aged ≥75 years. MEASUREMENTS: We examined the operating characteristics of the PCE to estimate 5-year risk of stroke, MI, and CHD death overall and by age and sex strata. The associations between individual components of the PCE and cardiovascular events by age group (≥75 vs 40-74 years) were also evaluated. RESULTS: The PCE had low discrimination for 5-year ASCVD risk in older (≥75 years) (c-statistic = 0.62, 95% CI 0.60-0.65) vs. younger (40-74 years) adults (c-statistic = 0.75, 95% CI 0.73-0.76). Calibration of the PCE was suboptimal in both older and younger adults, overestimating risk in the highest risk groups. Performance of the PCE in older adults was similarly poor when stratified by sex and age ≥ 80 years. LIMITATIONS: Since the PCE were derived from similar cohorts, though using different age groups and exams, this analysis likely overestimates the performance of the PCE. CONCLUSION: The performance of the PCE for ASCVD risk estimation in older adults is suboptimal; new models to effectively risk-stratify older adults are needed.

Advanced glycation end product carboxymethyl-lysine and risk of incident peripheral artery disease in older adults: The Cardiovascular Health Study. - Garg, Parveen K; Biggs, Mary L; Barzilay, Joshua; Djoussé, Luc; Hirsch, Calvin; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Mukamal, Kenneth J (Diab Vasc Dis Res, 2019)
Carboxymethyl-lysine is an advanced glycation end product that is detectable in the serum. Higher carboxymethyl-lysine levels have been associated with increased risk of coronary heart disease, stroke and cardiovascular mortality. We determined whether high carboxymethyl-lysine levels are also associated with the risk of peripheral artery disease in Cardiovascular Health Study participants who were all aged 65 years and older at baseline. Multivariate Cox proportional hazards models were used to determine the association of baseline carboxymethyl-lysine levels with incident peripheral artery disease in 3267 individuals followed for a median length of 10.0 years. A total of 157 cases of incident peripheral artery disease occurred during follow-up. No significant relationship between carboxymethyl-lysine and risk of peripheral artery disease was found (hazard ratio per standard deviation increment = 1.03; 95% confidence interval = 0.87, 1.23).

{Association of dietary folate and vitamin B-12 intake with genome-wide DNA methylation in blood: a large-scale epigenome-wide association analysis in 5841 individuals - Mandaviya, P. R.; Joehanes, R.; Brody, J.; Castillo-Fernandez, J. E.; Dekkers, K. F.; Do, A. N.; Graff, M.; H?nninen, I. K.; Tanaka, T.; de Jonge, E. A. L.; Kiefte-de Jong, J. C.; Absher, D. M.; et al. (Am J Clin Nutr, 2019)
Folate and vitamin B-12 are essential micronutrients involved in the donation of methyl groups in cellular metabolism. However, associations between intake of these nutrients and genome-wide DNA methylation levels have not been studied comprehensively in humans.\ The aim of this study was to assess whether folate and/or vitamin B-12 intake are asssociated with genome-wide changes in DNA methylation in leukocytes.\ A large-scale epigenome-wide association study of folate and vitamin B-12 intake was performed on DNA from 5841 participants from 10 cohorts using Illumina 450k arrays. Folate and vitamin B-12 intakes were calculated from food-frequency questionnaires (FFQs). Continuous and categorical (low compared with high intake) linear regression mixed models were applied per cohort, controlling for confounders. A meta-analysis was performed to identify significant differentially methylated positions (DMPs) and regions (DMRs), and a pathway analysis was performed on the DMR annotated genes.\ The categorical model resulted in 6 DMPs, which are all negatively associated with folate intake, annotated to FAM64A, WRAP73, FRMD8, CUX1, and LCN8 genes, which have a role in cellular processes including centrosome localization, cell proliferation, and tumorigenesis. Regional analysis showed 74 folate-associated DMRs, of which 73 were negatively associated with folate intake. The most significant folate-associated DMR was a 400-base pair (bp) spanning region annotated to the LGALS3BP gene. In the categorical model, vitamin B-12 intake was associated with 29 DMRs annotated to 48 genes, of which the most significant was a 1100-bp spanning region annotated to the calcium-binding tyrosine phosphorylation-regulated gene (CABYR). Vitamin B-12 intake was not associated with DMPs.\ We identified novel epigenetic loci that are associated with folate and vitamin B-12 intake. Interestingly, we found a negative association between folate and DNA methylation. Replication of these methylation loci is necessary in future studies.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Common Genetic Variation in Relation to Brachial Vascular Dimensions and Flow-Mediated Vasodilation. - Dörr, Marcus; Hamburg, Naomi M; Müller, Christian; Smith, Nicholas L; Gustafsson, Stefan; Lehtimäki, Terho; Teumer, Alexander; Zeller, Tanja; Li, Xiaohui; Lind, Lars; Raitakari, Olli T; Völker, Uwe; et al. (Circ Genom Precis Med, 2019)

Discrepancy in Frailty Identification: Move beyond Predictive Validity. - Xue, Qian-Li; Tian, Jing; Walston, Jeremy D; Chaves, Paulo H M; Newman, Anne B; Bandeen-Roche, Karen (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: To evaluate the discordance in frailty classification between the frailty index (FI) and the physical frailty phenotype (PFP) and identify factors discriminating those with discordant frailty classification from each other and from those for whom the assessments agree. METHODS: A prospective observational study of older adults aged 65 and older selected from Medicare eligibility lists in four US communities (n=5,362). The PFP was measured by the Cardiovascular Health Study PFP. Subjects meeting ≥3 of the 5 criteria were deemed frail. The FI was calculated as the proportion of deficits in an a priori selected set of 48 measures and subjects were classified as frail if FI>0.35. RESULTS: The prevalence of frailty was 7.0% by the PFP and 8.3% by the FI. Of the 730 deemed frail by either instrument, only 12% were in agreement; whereas 39% were classified as frail by PFP but not FI; and 48% were classified as frail by FI but not PFP. Participants aged 65-72 or greater disease burden were mostly likely to be characterized as being FI-frail but not PFP-frail. The associations of frailty with age and mortality was stronger when frailty was measured by the PFP rather than the FI. CONCLUSIONS: Despite comparable frailty prevalence between the PFP and the FI, there was substantial discordance in individual-level classification, with highest agreement existing only in the most vulnerable subset. These findings suggest that there are clinically important contexts in which PFP and FI cannot be used interchangeably.

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls - Flannick, J.; Mercader, J. M.; Fuchsberger, C.; Udler, M. S.; Mahajan, A.; Wessel, J.; Teslovich, T. M.; Caulkins, L.; Koesterer, R.; Barajas-Olmos, F.; Blackwell, T. W.; Boerwinkle, E.; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 Ã— 10-3) and candidate genes from knockout mice (P = 5.2 Ã— 10-3). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)
) with at least one obesity or lipid trait. Candidate genes include PRKAR2A, PTH1R, and HDAC9, which have been suggested to play roles in adipocyte differentiation or bone marrow adipose tissue. Taken together, these findings provide further insights into the processes that influence circulating adiponectin levels.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{A genome-wide association study identifies genetic loci associated with specific lobar brain volumes - van der Lee, S. J.; Knol, M. J.; Chauhan, G.; Satizabal, C. L.; Smith, A. V.; Hofer, E.; Bis, J. C.; Hibar, D. P.; Hilal, S.; van den Akker, E. B.; Arfanakis, K.; Bernard, M.; et al. (Commun Biol, 2019)
Brain lobar volumes are heritable but genetic studies are limited. We performed genome-wide association studies of frontal, occipital, parietal and temporal lobe volumes in 16,016 individuals, and replicated our findings in 8,789 individuals. We identified six genetic loci associated with specific lobar volumes independent of intracranial volume. Two loci, associated with occipital (6q22.32) and temporal lobe volume (12q14.3), were previously reported to associate with intracranial and hippocampal volume, respectively. We identified four loci previously unknown to affect brain volumes: 3q24 for parietal lobe volume, and 1q22, 4p16.3 and 14q23.1 for occipital lobe volume. The associated variants were located in regions enriched for histone modifications (DAAM1 and THBS3), or close to genes causing Mendelian brain-related diseases (ZIC4 and FGFRL1). No genetic overlap between lobar volumes and neurological or psychiatric diseases was observed. Our findings reveal part of the complex genetics underlying brain development and suggest a role for regulatory regions in determining brain volumes.

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genome-wide association study of breakfast skipping links clock regulation with food timing. - Dashti, Hassan S; Merino, Jordi; Lane, Jacqueline M; Song, Yanwei; Smith, Caren E; Tanaka, Toshiko; McKeown, Nicola M; Tucker, Chandler; Sun, Dianjianyi; Bartz, Traci M; Li-Gao, Ruifang; Nisa, Hoirun; et al. (Am J Clin Nutr, 2019)
BACKGROUND: Little is known about the contribution of genetic variation to food timing, and breakfast has been determined to exhibit the most heritable meal timing. As breakfast timing and skipping are not routinely measured in large cohort studies, alternative approaches include analyses of correlated traits. OBJECTIVES: The aim of this study was to elucidate breakfast skipping genetic variants through a proxy-phenotype genome-wide association study (GWAS) for breakfast cereal skipping, a commonly assessed correlated trait. METHODS: We leveraged the statistical power of the UK Biobank (n = 193,860) to identify genetic variants related to breakfast cereal skipping as a proxy-phenotype for breakfast skipping and applied several in silico approaches to investigate mechanistic functions and links to traits/diseases. Next, we attempted validation of our approach in smaller breakfast skipping GWAS from the TwinUK (n = 2,006) and the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium (n = 11,963). RESULTS: In the UK Biobank, we identified 6 independent GWAS variants, including those implicated for caffeine (ARID3B/CYP1A1), carbohydrate metabolism (FGF21), schizophrenia (ZNF804A), and encoding enzymes important for N6-methyladenosine RNA transmethylation (METTL4, YWHAB, and YTHDF3), which regulates the pace of the circadian clock. Expression of identified genes was enriched in the cerebellum. Genome-wide correlation analyses indicated positive correlations with anthropometric traits. Through Mendelian randomization (MR), we observed causal links between genetically determined breakfast skipping and higher body mass index, more depressive symptoms, and smoking. In bidirectional MR, we demonstrated a causal link between being an evening person and skipping breakfast, but not vice versa. We observed association of our signals in an independent breakfast skipping GWAS in another British cohort (P = 0.032), TwinUK, but not in a meta-analysis of non-British cohorts from the CHARGE consortium (P = 0.095). CONCLUSIONS: Our proxy-phenotype GWAS identified 6 genetic variants for breakfast skipping, linking clock regulation with food timing and suggesting a possible beneficial role of regular breakfast intake as part of a healthy lifestyle.

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Genomics of 1 million parent lifespans implicates novel pathways and common diseases and distinguishes survival chances. - Timmers, Paul Rhj; Mounier, Ninon; Läll, Kristi; Fischer, Krista; Ning, Zheng; Feng, Xiao; Bretherick, Andrew D; Clark, David W; Agbessi, M; Ahsan, H; Alves, I; Andiappan, A; et al. (Elife, 2019)
We use a genome-wide association of 1 million parental lifespans of genotyped subjects and data on mortality risk factors to validate previously unreplicated findings near , , , , , and 13q21.31, and identify and replicate novel findings near , , and . We also validate previous findings near 5q33.3/ and , whilst finding contradictory evidence at other loci. Gene set and cell-specific analyses show that expression in foetal brain cells and adult dorsolateral prefrontal cortex is enriched for lifespan variation, as are gene pathways involving lipid proteins and homeostasis, vesicle-mediated transport, and synaptic function. Individual genetic variants that increase dementia, cardiovascular disease, and lung cancer - but not other cancers - explain the most variance. Resulting polygenic scores show a mean lifespan difference of around five years of life across the deciles. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).

Heterogeneous Exposure Associations in Observational Cohort Studies: The Example of Blood Pressure in Older Adults. - Odden, Michelle C; Rawlings, Andreea M; Khodadadi, Abtin; Fern, Xiaoli; Shlipak, Michael G; Bibbins-Domingo, Kirsten; Covinsky, Kenneth; Kanaya, Alka M; Lee, Anne; Haan, Mary N; Newman, Anne B; Psaty, Bruce M; et al. (Am J Epidemiol, 2019)
Heterogeneous exposure associations (HEAs) can be defined as differences in the association of a exposure with an outcome among subgroups that differ by a set of characteristics. This manuscript intends to foster discussion of HEAs in the epidemiological literature, and present a variant of the random forest algorithm that can be used to identify HEAs. We demonstrate the use of this algorithm in the setting of the association of systolic blood pressure and death in older adults. The training set included pooled data from the baseline examination of the Cardiovascular Health Study (1989-1993), the Health, Aging, and Body Composition study (1997-1998), and the Sacramento Area Latino Study on Aging (1998-1999). The test set included data from the National Health and Nutrition Examination Survey (1999-2002). The hazard ratios ranged from 1.25 (95% CI: 1.13, 1.37) per 10 mmHg higher systolic blood pressure in men aged ≤67 years with diastolic blood pressure >80 mmHg, to 1.00 (0.96, 1.03) in women with creatinine <0.7 mg/dL and a history of hypertension. HEAs have the potential to improve our understanding of disease mechanisms in diverse populations, and guide the design of randomized controlled trials to control exposures in heterogeneous populations.

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) Îµ4) is associated with lower odds of surviving to the 90th and 99th percentile age, while rs7412 (ApoE Îµ2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{Meta-Analysis of Genomewide Association Studies Reveals Genetic Variants for Hip Bone Geometry - Hsu, Y. H.; Estrada, K.; Evangelou, E.; Ackert-Bicknell, C.; Akesson, K.; Beck, T.; Brown, S. J.; Capellini, T.; Carbone, L.; Cauley, J.; Cheung, C. L.; Cummings, S. R.; et al. (J Bone Miner Res, 2019)
Hip geometry is an important predictor of fracture. We performed a meta-analysis of GWAS studies in adults to identify genetic variants that are associated with proximal femur geometry phenotypes. We analyzed four phenotypes: (i) femoral neck length; (ii) neck-shaft angle; (iii) femoral neck width, and (iv) femoral neck section modulus, estimated from DXA scans using algorithms of hip structure analysis. In the Discovery stage, 10 cohort studies were included in the fixed-effect meta-analysis, with up to 18,719 men and women ages 16 to 93 years. Association analyses were performed with ∼2.5 million polymorphisms under an additive model adjusted for age, body mass index, and height. Replication analyses of meta-GWAS significant loci (at adjusted genomewide significance [GWS], threshold p ≤ 2.6 × 10-8 ) were performed in seven additional cohorts in silico. We looked up SNPs associated in our analysis, for association with height, bone mineral density (BMD), and fracture. In meta-analysis (combined Discovery and Replication stages), GWS associations were found at 5p15 (IRX1 and ADAMTS16); 5q35 near FGFR4; at 12p11 (in CCDC91); 11q13 (near LRP5 and PPP6R3 (rs7102273)). Several hip geometry signals overlapped with BMD, including LRP5 (chr. 11). Chr. 11 SNP rs7102273 was associated with any-type fracture (p = 7.5 × 10-5 ). We used bone transcriptome data and discovered several significant eQTLs, including rs7102273 and PPP6R3 expression (p = 0.0007), and rs6556301 (intergenic, chr.5 near FGFR4) and PDLIM7 expression (p = 0.005). In conclusion, we found associations between several genes and hip geometry measures that explained 12% to 22% of heritability at different sites. The results provide a defined set of genes related to biological pathways relevant to BMD and etiology of bone fragility. © 2019 American Society for Bone and Mineral Research.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Multiethnic Genome-Wide Association Study of Diabetic Retinopathy Using Liability Threshold Modeling of Duration of Diabetes and Glycemic Control. - Pollack, Samuela; Igo, Robert P; Jensen, Richard A; Christiansen, Mark; Li, Xiaohui; Cheng, Ching-Yu; Ng, Maggie C Y; Smith, Albert V; Rossin, Elizabeth J; Segrè, Ayellet V; Davoudi, Samaneh; Tan, Gavin S; et al. (Diabetes, 2019)
To identify genetic variants associated with diabetic retinopathy (DR), we performed a large multiethnic genome-wide association study. Discovery included eight European cohorts ( = 3,246) and seven African American cohorts ( = 2,611). We meta-analyzed across cohorts using inverse-variance weighting, with and without liability threshold modeling of glycemic control and duration of diabetes. Variants with a value <1 × 10 were investigated in replication cohorts that included 18,545 European, 16,453 Asian, and 2,710 Hispanic subjects. After correction for multiple testing, the C allele of rs142293996 in an intron of nuclear VCP-like () was associated with DR in European discovery cohorts ( = 2.1 × 10), but did not reach genome-wide significance after meta-analysis with replication cohorts. We applied the Disease Association Protein-Protein Link Evaluator (DAPPLE) to our discovery results to test for evidence of risk being spread across underlying molecular pathways. One protein-protein interaction network built from genes in regions associated with proliferative DR was found to have significant connectivity ( = 0.0009) and corroborated with gene set enrichment analyses. These findings suggest that genetic variation in as well as variation within a protein-protein interaction network that includes genes implicated in inflammation, may influence risk for DR.

{New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders - Evangelou, E.; Gao, H.; Chu, C.; Ntritsos, G.; Blakeley, P.; Butts, A. R.; Pazoki, R.; Suzuki, H.; Koskeridis, F.; Yiorkas, A. M.; Karaman, I.; Elliott, J.; et al. (Nat Hum Behav, 2019)
Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. Here we conducted a meta-analysis of genome-wide association studies of alcohol consumption (g d-1) from the UK Biobank, the Alcohol Genome-Wide Consortium and the Cohorts for Heart and Aging Research in Genomic Epidemiology Plus consortia, collecting data from 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 new common loci and investigated their potential functional importance using magnetic resonance imaging data and gene expression studies. We identify genetic pathways associated with alcohol consumption and suggest genetic mechanisms that are shared with neuropsychiatric disorders such as schizophrenia.

No causal effects of serum urate levels on the risk of chronic kidney disease: A Mendelian randomization study. - Jordan, Daniel M; Choi, Hyon K; Verbanck, Marie; Topless, Ruth; Won, Hong-Hee; Nadkarni, Girish; Merriman, Tony R; Do, Ron (PLoS Med, 2019)
BACKGROUND: Studies have shown strong positive associations between serum urate (SU) levels and chronic kidney disease (CKD) risk; however, whether the relation is causal remains uncertain. We evaluate whether genetic data are consistent with a causal impact of SU level on the risk of CKD and estimated glomerular filtration rate (eGFR). METHODS AND FINDINGS: We used Mendelian randomization (MR) methods to evaluate the presence of a causal effect. We used aggregated genome-wide association data (N = 110,347 for SU, N = 69,374 for gout, N = 133,413 for eGFR, N = 117,165 for CKD), electronic-medical-record-linked UK Biobank data (N = 335,212), and population-based cohorts (N = 13,425), all in individuals of European ancestry, for SU levels and CKD. Our MR analysis showed that SU has a causal effect on neither eGFR level nor CKD risk across all MR analyses (all P > 0.05). These null associations contrasted with our epidemiological association findings from the 4 population-based cohorts (change in eGFR level per 1-mg/dl [59.48 μmol/l] increase in SU: -1.99 ml/min/1.73 m2; 95% CI -2.86 to -1.11; P = 8.08 × 10(-6); odds ratio [OR] for CKD: 1.48; 95% CI 1.32 to 1.65; P = 1.52 × 10(-11)). In contrast, the same MR approaches showed that SU has a causal effect on the risk of gout (OR estimates ranging from 3.41 to 6.04 per 1-mg/dl increase in SU, all P < 10-3), which served as a positive control of our approach. Overall, our MR analysis had >99% power to detect a causal effect of SU level on the risk of CKD of the same magnitude as the observed epidemiological association between SU and CKD. Limitations of this study include the lifelong effect of a genetic perturbation not being the same as an acute perturbation, the inability to study non-European populations, and some sample overlap between the datasets used in the study. CONCLUSIONS: Evidence from our series of causal inference approaches using genetics does not support a causal effect of SU level on eGFR level or CKD risk. Reducing SU levels is unlikely to reduce the risk of CKD development.
Keywords: Adult; Age Factors; Female; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Male; Mendelian Randomization Analysis; Renal Insufficiency, Chronic; Sex Factors; Uric Acid; Young Adult

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

The role of functional status on the relationship between blood pressure and cognitive decline: the Cardiovascular Health Study. - Miller, Lindsay M; Peralta, Carmen A; Fitzpatrick, Annette L; Wu, Chenkai; Psaty, Bruce M; Newman, Anne B; Odden, Michelle C (J Hypertens, 2019)
OBJECTIVE: To examine whether self-reported functional status modified the association between blood pressure (BP) and cognitive decline among older adults. METHODS: The study included 2097 US adults aged 75 years and older from the Cardiovascular Health Study, followed for up to 6 years. Functional status was ascertained by self-reported limitation in activities of daily living (ADL; none vs. any). Cognitive function was assessed by the Modified Mini Mental State Exam (3MSE). We used linear mixed models to examine whether the presence of at least one ADL limitation modified the association between BP and cognitive decline. Potential confounders included demographics, physiologic measures, antihypertensive medication use and apolipoprotein E ε4 allele. We conducted stratified analyses for significant interactions between BP and ADL. RESULTS: The association between BP and change in 3MSE differed by baseline ADL limitation. Among participants without ADL limitation, elevated systolic BP (≥140 mmHg) was associated with a 0.15 decrease (95% CI -0.24 to -0.07); P value for interaction less than 0.001, whereas in those with an ADL limitation, elevated systolic BP was independently associated with a 0.30 increase in 3MSE scores per year (95% CI 0.06-0.55). Elevated diastolic BP (≥80 mmHg) was associated with an increase in cognitive function in both groups, although the increase was greater in those with ADL limitation (0.47 points per year vs. 0.18 points per year, P value for interaction = 0.01). CONCLUSION: Elevated BP appears to be associated with a decrease in cognitive scores among functioning older adults, and modest improvements in cognitive function among poorly functioning elders.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

Translating Alzheimer's disease-associated polymorphisms into functional candidates: a survey of IGAP genes and SNPs. - Katsumata, Yuriko; Nelson, Peter T; Estus, Steven; Fardo, David W (Neurobiol Aging, 2019)
The International Genomics of Alzheimer's Project (IGAP) is a consortium for characterizing the genetic landscape of Alzheimer's disease (AD). The identified and/or confirmed 19 single-nucleotide polymorphisms (SNPs) associated with AD are located on non-coding DNA regions, and their functional impacts on AD are as yet poorly understood. We evaluated the roles of the IGAP SNPs by integrating data from many resources, based on whether the IGAP SNP was (1) a proxy for a coding SNP or (2) associated with altered mRNA transcript levels. For (1), we confirmed that 12 AD-associated coding common SNPs and five nonsynonymous rare variants are in linkage disequilibrium with the IGAP SNPs. For (2), the IGAP SNPs in CELF1 and MS4A6A were associated with expression of their neighboring genes, MYBPC3 and MS4A6A, respectively, in blood. The IGAP SNP in DSG2 was an expression quantitative trait loci (eQTL) for DLGAP1 and NETO1 in the human frontal cortex. The IGAP SNPs in ABCA7, CD2AP, and CD33 each acted as eQTL for AD-associated genes in brain. Our approach for identifying proxies and examining eQTL highlighted potentially impactful, novel gene regulatory phenomena pertinent to the AD phenotype.

Trends in Blood Pressure and High-Sensitivity Cardiac Troponin-T with Cardiovascular Disease: The Cardiovascular Health Study. - Tehrani, David M; Fan, Wenjun; Nambi, Vijay; Gardin, Julius; Hirsch, Calvin H; Amsterdam, Ezra; deFilippi, Christopher R; Polonsky, Tamar; Wong, Nathan D (Am J Hypertens, 2019)
BACKGROUND: High-sensitivity cardiac troponin T (hs-cTnT) is individually associated with incident hypertension (HTN) and cardiovascular disease (CVD) events. We hypothesize that the increases in hs-cTnT with increases in blood pressure will be related to higher incidence of CVD. METHODS: The Cardiovascular Health Study is a longitudinal cohort of older adults. Those with hs-cTnT data and CVD risk factors at baseline and follow-up (2-3 years later) were stratified based on systolic blood pressure (SBP) (optimal: <120 mmHg, intermediate: 120-139 mmHg, elevated: ≥140 mmHg) and hs-cTnT (undetectable: <5 ng/L, detectable: 5-13 ng/L, elevated: ≥14 ng/L) categories. SBP and hs-cTnT were classified as increased or decreased if they changed categories between exams, and stable if they did not. Cox regression evaluated incident CVD events over an average 9 year follow-up. RESULTS: Among 2219 adults, 510 (23.0 %) had decreased hs-cTnT, 1,279 (57.6 %) had stable hs-cTnT, and 430 (19.4 %) had increased hs-cTnT. Those with increased hs-cTnT had a higher CVD risk with stable SBP (HR: 1.28 [1.04-1.57], p=0.02) or decreased SBP (HR: 1.57 [1.08-2.28], p=0.02) compared to those within the same SBP group but a stable hs-cTnT. In those with lower SBP at follow-up, there was an inverse relation between DBP and risk of CVD events in those with increased hs-cTnT (HR: 0.44 per 10 mmHg increase, p<0.01). CONCLUSION: An increase in hs-cTnT over time is associated with a higher risk of CVD even when the blood pressure is stable or decreases over time.

Alzheimer Disease Pathology-Associated Polymorphism in a Complex Variable Number of Tandem Repeat Region Within the MUC6 Gene, Near the AP2A2 Gene. - Katsumata, Yuriko; Fardo, David W; Bachstetter, Adam D; Artiushin, Sergey C; Wang, Wang-Xia; Wei, Angela; Brzezinski, Lena J; Nelson, Bela G; Huang, Qingwei; Abner, Erin L; Anderson, Sonya; Patel, Indumati; et al. (J Neuropathol Exp Neurol, 2020)
We found evidence of late-onset Alzheimer disease (LOAD)-associated genetic polymorphism within an exon of Mucin 6 (MUC6) and immediately downstream from another gene: Adaptor Related Protein Complex 2 Subunit Alpha 2 (AP2A2). PCR analyses on genomic DNA samples confirmed that the size of the MUC6 variable number tandem repeat (VNTR) region was highly polymorphic. In a cohort of autopsied subjects with quantitative digital pathology data (n = 119), the size of the polymorphic region was associated with the severity of pTau pathology in neocortex. In a separate replication cohort of autopsied subjects (n = 173), more pTau pathology was again observed in subjects with longer VNTR regions (p = 0.031). Unlike MUC6, AP2A2 is highly expressed in human brain. AP2A2 expression was lower in a subset analysis of brain samples from persons with longer versus shorter VNTR regions (p = 0.014 normalizing with AP2B1 expression). Double-label immunofluorescence studies showed that AP2A2 protein often colocalized with neurofibrillary tangles in LOAD but was not colocalized with pTau proteinopathy in progressive supranuclear palsy, or with TDP-43 proteinopathy. In summary, polymorphism in a repeat-rich region near AP2A2 was associated with neocortical pTau proteinopathy (because of the unique repeats, prior genome-wide association studies were probably unable to detect this association), and AP2A2 was often colocalized with neurofibrillary tangles in LOAD.
Keywords: Adaptor Protein Complex 2; Adaptor Protein Complex alpha Subunits; Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Minisatellite Repeats; Mucin-6; Neurofibrillary Tangles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; TDP-43 Proteinopathies

{Androgens In Men Study (AIMS): protocol for meta-analyses of individual participant data investigating associations of androgens with health outcomes in men - Yeap, B. B.; Marriott, R. J.; Adams, R. J.; Antonio, L.; Ballantyne, C. M.; Bhasin, S.; Cawthon, P. M.; Couper, D. J.; Dobs, A. S.; Flicker, L.; Karlsson, M.; Martin, S. A.; et al. (BMJ Open, 2020)
This study aims to clarify the role(s) of endogenous sex hormones to influence health outcomes in men, specifically to define the associations of plasma testosterone with incidence of cardiovascular events, cancer, dementia and mortality risk, and to identify factors predicting testosterone concentrations. Data will be accrued from at least three Australian, two European and four North American population-based cohorts involving approximately 20 000 men.\ Eligible studies include prospective cohort studies with baseline testosterone concentrations measured using mass spectrometry and 5 years of follow-up data on incident cardiovascular events, mortality, cancer diagnoses or deaths, new-onset dementia or decline in cognitive function recorded. Data for men, who were not taking androgens or drugs suppressing testosterone production, metabolism or action; and had no prior orchidectomy, are eligible. Systematic literature searches were conducted from 14 June 2019 to 31 December 2019, with no date range set for searches. Aggregate level data will be sought where individual participant data (IPD) are not available. One-stage IPD random-effects meta-analyses will be performed, using linear mixed models, generalised linear mixed models and either stratified or frailty-augmented Cox regression models. Heterogeneity in estimates from different studies will be quantified and bias investigated using funnel plots. Effect size estimates will be presented in forest plots and non-negligible heterogeneity and bias investigated using subgroup or meta-regression analyses.\ Ethics approvals obtained for each of the participating cohorts state that participants have consented to have their data collected and used for research purposes. The Androgens In Men Study has been assessed as exempt from ethics review by the Human Ethics office at the University of Western Australia (file reference number RA/4/20/5014). Each of the component studies had obtained ethics approvals; please refer to respective component studies for details. Research findings will be disseminated to the scientific and broader community via the publication of four research articles, with each involving a separate set of IPD meta-analyses (articles will investigate different, distinct outcomes), at scientific conferences and meetings of relevant professional societies. Collaborating cohort studies will disseminate findings to study participants and local communities.\ CRD42019139668.

Association of Nonobstructive Chronic Bronchitis With Respiratory Health Outcomes in Adults. - Balte, Pallavi P; Chaves, Paulo H M; Couper, David J; Enright, Paul; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard A; Loehr, Laura R; London, Stephanie J; Newman, Anne B; O'Connor, George T; Schwartz, Joseph E; et al. (JAMA Intern Med, 2020)
Importance: Chronic bronchitis has been associated with cigarette smoking as well as with e-cigarette use among young adults, but the association of chronic bronchitis in persons without airflow obstruction or clinical asthma, described as nonobstructive chronic bronchitis, with respiratory health outcomes remains uncertain. Objective: To assess whether nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes in adult ever smokers and never smokers. Design, Setting, and Participants: This prospective cohort study included 22 325 adults without initial airflow obstruction (defined as the ratio of forced expiratory volume in the first second [FEV1] to forced vital capacity [FVC] of <0.70) or clinical asthma at baseline. The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 9 US general population-based cohorts. Thus present study is based on data from 5 of these cohorts. Participants were enrolled from August 1971 through May 2007 and were followed up through December 2018. Exposures: Nonobstructive chronic bronchitis was defined by questionnaire at baseline as both cough and phlegm for at least 3 months for at least 2 consecutive years. Main Outcomes and Measures: Lung function was measured by prebronchodilator spirometry. Hospitalizations and deaths due to chronic lower respiratory disease and respiratory disease-related mortality were defined by events adjudication and administrative criteria. Models were stratified by smoking status and adjusted for anthropometric, sociodemographic, and smoking-related factors. The comparison group was participants without nonobstructive chronic bronchitis. Results: Among 22 325 adults included in the analysis, mean (SD) age was 53.0 (16.3) years (range, 18.0-95.0 years), 58.2% were female, 65.9% were non-Hispanic white, and 49.6% were ever smokers. Among 11 082 ever smokers with 99 869 person-years of follow-up, participants with nonobstructive chronic bronchitis (300 [2.7%]) had accelerated decreases in FEV1 (4.1 mL/y; 95% CI, 2.1-6.1 mL/y) and FVC (4.7 mL/y; 95% CI, 2.2-7.2 mL/y), increased risks of chronic lower respiratory disease-related hospitalization or mortality (hazard ratio [HR], 2.2; 95% CI, 1.7-2.7), and greater respiratory disease-related (HR, 2.0; 95% CI, 1.1-3.8) and all-cause mortality (HR, 1.5; 95% CI, 1.3-1.8) compared with ever smokers without nonobstructive chronic bronchitis. Among 11 243 never smokers with 120 004 person-years of follow-up, participants with nonobstructive chronic bronchitis (151 [1.3%]) had greater rates of chronic lower respiratory disease-related hospitalization or mortality (HR, 3.1; 95% CI, 2.1-4.5) compared with never smokers without nonobstructive chronic bronchitis. Nonobstructive chronic bronchitis was not associated with FEV1:FVC decline or incident airflow obstruction. The presence of at least 1 of the component symptoms of nonobstructive chronic bronchitis (ie, chronic cough or phlegm), which was common in both ever smokers (11.0%) and never smokers (6.7%), was associated with adverse respiratory health outcomes. Conclusions and Relevance: The findings suggest that nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes, particularly in ever smokers, and may be a high-risk phenotype suitable for risk stratification and targeted therapies.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asthma; Bronchitis, Chronic; Female; Humans; Lung; Male; Middle Aged; Prospective Studies; Respiratory Function Tests; Smokers; Smoking; Young Adult

Brachial Flow-mediated Dilation and Risk of Dementia: The Cardiovascular Health Study. - Garg, Parveen K; Tan, Annabel X; Odden, Michelle C; Gardin, Julius M; Lopez, Oscar L; Newman, Anne B; Rawlings, Andreea M; Mukamal, Kenneth J (Alzheimer Dis Assoc Disord, 2020)
INTRODUCTION: Brachial flow-mediated dilation (FMD) is a physiologic measure of endothelial function. We determined the prospective association of brachial FMD with incident dementia among older adults. METHODS: We included 2777 Cardiovascular Health Study participants who underwent brachial FMD measurement. Incident dementia was ascertained by medication use, International Classification of Diseases-9 codes, requirement for a proxy, and death certificates and calibrated to gold-standard assessments performed in a subset of the cohort. RESULTS: Mean participant age at time of brachial FMD measurement was 77.9 years. We identified 1650 incident dementia cases (median follow-up=10.5 y). After adjusting for age, race, sex, education, clinic site, and baseline arterial diameter, risk of dementia for participants in the highest quartile of percent brachial FMD did not differ from those in lowest quartile (hazard ratio=0.89, 95% confidence interval: 0.77, 1.03). CONCLUSIONS: Brachial FMD, measured late in life, is not associated with an increased risk of incident dementia.

Carotid Intima-Media Thickness and the Risk of Sudden Cardiac Death: The ARIC Study and the CHS. - Suzuki, Takeki; Wang, Wanmei; Wilsdon, Anthony; Butler, Kenneth R; Adabag, Selcuk; Griswold, Michael E; Nambi, Vijay; Rosamond, Wayne; Sotoodehnia, Nona; Mosley, Thomas H (J Am Heart Assoc, 2020)
Background Sudden cardiac death (SCD) is associated with severe coronary heart disease in the great majority of cases. Whether carotid intima-media thickness (C-IMT), a known surrogate marker of subclinical atherosclerosis, is associated with risk of SCD in a general population remains unknown. The objective of this study was to investigate the association between C-IMT and risk of SCD. Methods and Results We examined a total of 20 862 participants: 15 307 participants of the ARIC (Atherosclerosis Risk in Communities) study and 5555 participants of the CHS (Cardiovascular Health Study). C-IMT and common carotid artery intima-media thickness was measured at baseline by ultrasound. Presence of plaque was judged by trained readers. Over a median of 23.5 years of follow-up, 569 participants had SCD (1.81 cases per 1000 person-years) in the ARIC study. Mean C-IMT and common carotid artery intima-media thickness were associated with risk of SCD after adjustment for traditional risk factors and time-varying adjustors: hazard ratios (HRs) with 95% CIs for fourth versus first quartile were 1.64 (1.15-2.63) and 1.49 (1.05-2.11), respectively. In CHS, 302 participants developed SCD (4.64 cases per 1000 person-years) over 13.1 years. Maximum C-IMT was associated with risk of SCD after adjustment: HR (95% CI) for fourth versus first quartile was 1.75 (1.22-2.51). Presence of plaque was associated with 35% increased risk of SCD: HR (95% CI) of 1.37 (1.13-1.67) in the ARIC study and 1.32 (1.04-1.68) in CHS. Conclusions C-IMT was associated with risk of SCD in 2 biracial community-based cohorts. C-IMT may be used as a marker of SCD risk and potentially to initiate early therapeutic interventions to mitigate the risk.

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

Genetic and regulatory architecture of Alzheimer's disease in the region. - Kulminski, Alexander M; Shu, Leonardo; Loika, Yury; He, Liang; Nazarian, Alireza; Arbeev, Konstantin; Ukraintseva, Svetlana; Yashin, Anatoliy; Culminskaya, Irina (Alzheimers Dement (Amst), 2020)
Introduction: Apolipoprotein E () ε2 and ε4 alleles encoded by rs7412 and rs429358 polymorphisms, respectively, are landmark contra and pro "risk" factors for Alzheimer's disease (AD). Methods: We examined differences in linkage disequilibrium (LD) structures between (1) AD-affected and unaffected subjects and (2) older AD-unaffected and younger subjects in the 19q13.3 region harboring rs7412 and rs429358. Results: AD is associated with sex-nonspecific heterogeneous patterns of decreased and increased LD of rs7412 and rs429358, respectively, with other polymorphisms from five genes in this region in AD-affected subjects. The LD patterns in older AD-unaffected subjects resembled those in younger individuals. Polarization of the ε4- and ε2 allele-related heterogeneous LD clusters differentiated cell types and implicated specific tissues in AD pathogenesis. Discussion: Protection and predisposition to AD is characterized by an interplay of rs7412 and rs429358, with multiple polymorphisms in the 19q13.3 region in a tissue-specific manner, which is not driven by common evolutionary forces.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

{Genome-Wide Association Study Meta-Analysis of Stroke in 22 000 Individuals of African Descent Identifies Novel Associations With Stroke - Keene, K. L.; Hyacinth, H. I.; Bis, J. C.; Kittner, S. J.; Mitchell, B. D.; Cheng, Y. C.; Pare, G.; Chong, M.; O'Donnell, M.; Meschia, J. F.; Chen, W. M.; Sale, M. M.; et al. (Stroke, 2020)
Stroke is a complex disease with multiple genetic and environmental risk factors. Blacks endure a nearly 2-fold greater risk of stroke and are 2× to 3× more likely to die from stroke than European Americans.\ The COMPASS (Consortium of Minority Population Genome-Wide Association Studies of Stroke) has conducted a genome-wide association meta-analysis of stroke in >22 000 individuals of African ancestry (3734 cases, 18 317 controls) from 13 cohorts.\ In meta-analyses, we identified one single nucleotide polymorphism (rs55931441) near the HNF1A gene that reached genome-wide significance (P=4.62×10-8) and an additional 29 variants with suggestive evidence of association (P<1×10-6), representing 24 unique loci. For validation, a look-up analysis for a 100 kb region flanking the COMPASS single nucleotide polymorphism was performed in SiGN (Stroke Genetics Network) Europeans, SiGN Hispanics, and METASTROKE (Europeans). Using a stringent Bonferroni correction P value of 2.08×10-3 (0.05/24 unique loci), we were able to validate associations at the HNF1A locus in both SiGN (P=8.18×10-4) and METASTROKE (P=1.72×10-3) European populations. Overall, 16 of 24 loci showed evidence for validation across multiple populations. Previous studies have reported associations between variants in the HNF1A gene and lipids, C-reactive protein, and risk of coronary artery disease and stroke. Suggestive associations with variants in the SFXN4 and TMEM108 genes represent potential novel ischemic stroke loci.\ These findings represent the most thorough investigation of genetic determinants of stroke in individuals of African descent, to date.

{An individual participant data analysis of prospective cohort studies on the association between subclinical thyroid dysfunction and depressive symptoms - Wildisen, L.; Del Giovane, C.; Moutzouri, E.; Beglinger, S.; Syrogiannouli, L.; Collet, T. H.; Cappola, A. R.; ?svold, B. O.; Bakker, S. J. L.; Yeap, B. B.; Almeida, O. P.; Ceresini, G.; et al. (Sci Rep, 2020)
{In subclinical hypothyroidism, the presence of depressive symptoms is often a reason for starting levothyroxine treatment. However, data are conflicting on the association between subclinical thyroid dysfunction and depressive symptoms. We aimed to examine the association between subclinical thyroid dysfunction and depressive symptoms in all prospective cohorts with relevant data available. We performed a systematic review of the literature from Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane Library from inception to 10th May 2019. We included prospective cohorts with data on thyroid status at baseline and depressive symptoms during follow-up. The primary outcome was depressive symptoms measured at first available follow-up, expressed on the Beck's Depression Inventory (BDI) scale (range 0-63, higher values indicate more depressive symptoms, minimal clinically important difference: 5 points). We performed a two-stage individual participant data (IPD) analysis comparing participants with subclinical hypo- or hyperthyroidism versus euthyroidism, adjusting for depressive symptoms at baseline, age, sex, education, and income (PROSPERO CRD42018091627). Six cohorts met the inclusion criteria, with IPD on 23,038 participants. Their mean age was 60 years, 65% were female, 21,025 were euthyroid, 1342 had subclinical hypothyroidism and 671 subclinical hyperthyroidism. At first available follow-up [mean 8.2 (Â± 4.3) years], BDI scores did not differ between participants with subclinical hypothyroidism (mean difference = 0.29, 95% confidence interval = - 0.17 to 0.76

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Level and change in N-terminal pro B-type Natriuretic Peptide and kidney function and survival to age 90. - Häberle, Astrid D; Biggs, Mary L; Cushman, Mary; Psaty, Bruce M; Newman, Anne B; Shlipak, Michael G; Gottdiener, John; Wu, Chenkai; Gardin, Julius M; Bansal, Nisha; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Many traditional cardiovascular risk factors do not predict survival to very old age. Studies have shown associations of estimated glomerular filtration rate (eGFR) and N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) with cardiovascular disease and mortality in older populations. This study aimed to evaluate the associations of the level and change in eGFR and NT-pro-BNP with longevity to age 90 years. METHODS: The population included participants (n=3,645) in the Cardiovascular Health Study, aged between 67-75 at baseline. The main exposures were eGFR, calculated with the Berlin Initiative Study equation (BIS2), and NT-pro-BNP, and the main outcome was survival to age 90. Mixed models were used to estimate level and change of the main exposures. RESULTS: There was an association between baseline level and change of both eGFR and NT-pro-BNP and survival to 90, and this association persisted after adjustment for covariates. Each 10 ml/min per 1.73 m2 higher eGFR level was associated with an adjusted odds ratio (OR) of 1.23 (95% CI: 1.13, 1.34) of survival to 90, and a 0.5 ml/min/ 1.73 m2 slower decline in eGFR was associated with an OR of 1.51 (95% CI: 1.31, 1.74). A 2-fold higher level of NT-pro-BNP level had an adjusted OR of 0.67 (95% CI: 0.61, 0.73), and a 1.05-fold increase per year in NT-pro-BNP had an OR of 0.53 (95% CI: 0.43, 0.65) for survival to age 90. CONCLUSION: eGFR and NT-pro-BNP appear to be important risk factors for longevity to age 90.

Lung function decline in former smokers and low-intensity current smokers: a secondary data analysis of the NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Folsom, Aaron R; Freedman, Neal D; Jacobs, David R; Kalhan, Ravi; Mathew, Amanda R; Kronmal, Richard A; Loehr, Laura R; et al. (Lancet Respir Med, 2020)
BACKGROUND: Former smokers now outnumber current smokers in many developed countries, and current smokers are smoking fewer cigarettes per day. Some data suggest that lung function decline normalises with smoking cessation; however, mechanistic studies suggest that lung function decline could continue. We hypothesised that former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers, including among those without prevalent lung disease. METHODS: We used data on six US population-based cohorts included in the NHLBI Pooled Cohort Study. We restricted the sample to participants with valid spirometry at two or more exams. Two cohorts recruited younger adults (≥17 years), two recruited middle-aged and older adults (≥45 years), and two recruited only elderly adults (≥65 years) with examinations done between 1983 and 2014. FEV decline in sustained former smokers and current smokers was compared to that of never-smokers by use of mixed models adjusted for sociodemographic and anthropometric factors. Differential FEV decline was also evaluated according to duration of smoking cessation and cumulative (number of pack-years) and current (number of cigarettes per day) cigarette consumption. FINDINGS: 25 352 participants (ages 17-93 years) completed 70 228 valid spirometry exams. Over a median follow-up of 7 years (IQR 3-20), FEV decline at the median age (57 years) was 31·01 mL per year (95% CI 30·66-31·37) in sustained never-smokers, 34·97 mL per year (34·36-35·57) in former smokers, and 39·92 mL per year (38·92-40·92) in current smokers. With adjustment, former smokers showed an accelerated FEV decline of 1·82 mL per year (95% CI 1·24-2·40) compared to never-smokers, which was approximately 20% of the effect estimate for current smokers (9·21 mL per year; 95% CI 8·35-10·08). Compared to never-smokers, accelerated FEV decline was observed in former smokers for decades after smoking cessation and in current smokers with low cumulative cigarette consumption (<10 pack-years). With respect to current cigarette consumption, the effect estimate for FEV decline in current smokers consuming less than five cigarettes per day (7·65 mL per year; 95% CI 6·21-9·09) was 68% of that in current smokers consuming 30 or more cigarettes per day (11·24 mL per year; 9·86-12·62), and around five times greater than in former smokers (1·57 mL per year; 1·00-2·14). Among participants without prevalent lung disease, associations were attenuated but were consistent with the main results. INTERPRETATION: Former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers. These results suggest that all levels of smoking exposure are likely to be associated with lasting and progressive lung damage. FUNDING: National Institutes of Health, National Heart Lung and Blood Institute, and US Environmental Protection Agency.
Keywords: Adult; Aged; Case-Control Studies; Ex-Smokers; Female; Follow-Up Studies; Humans; Lung; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Non-Smokers; Respiratory Physiological Phenomena; Smokers; Smoking; Spirometry; United States; Young Adult

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Metabolites Associated with Walking Ability Among the Oldest Old from the CHS All Stars Study. - Marron, Megan M; Wendell, Stacy G; Boudreau, Robert M; Clish, Clary B; Santanasto, Adam J; Tseng, George C; Zmuda, Joseph M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Low walking ability is highly prevalent with advancing age and predicts major health outcomes. Metabolomics may help to better characterize differences in walking ability among older adults, providing insight into potentially altered molecular processes underlying age-related decline in functioning. We sought to identify metabolites and metabolic pathways associated with high versus low walking ability among 120 participants ages 79-95 from the CHS All Stars study. METHODS: Using a nested case-control design, 60 randomly selected participants with low walking ability were matched one-to-one on age, gender, race, and fasting time with 60 participants with high walking ability. High versus low walking ability was defined as being in the best versus worst tertiles for both gait speed (≥0.9 vs <0.7 m/s) and the Walking Ability Index (7-9 vs 0-1). Using liquid chromatography-mass spectrometry, 569 metabolites were identified in overnight-fasting plasma. RESULTS: Ninety-six metabolites were associated with walking ability, where 24% were triacylglycerols. Triacylglycerols that were higher among those with high walking ability consisted mostly of polyunsaturated fatty acids, whereas triacylglycerols that were lower among those with high walking ability consisted mostly of saturated or monounsaturated fatty acids. Body composition partly explained associations between some metabolites and walking ability. Proline and arginine metabolism was a top pathway associated with walking ability. CONCLUSION: These results may partly reflect pathways of modifiable risk factors, including excess dietary lipids and lack of physical activity, contributing to obesity and further alterations in metabolic pathways that lead to age-related decline in walking ability in this older adult cohort.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Female; Geriatric Assessment; Humans; Male; Metabolomics; Risk Factors; Walking; Walking Speed

Mitochondrial DNA copy number can influence mortality and cardiovascular disease via methylation of nuclear DNA CpGs. - Castellani, Christina A; Longchamps, Ryan J; Sumpter, Jason A; Newcomb, Charles E; Lane, John A; Grove, Megan L; Bressler, Jan; Brody, Jennifer A; Floyd, James S; Bartz, Traci M; Taylor, Kent D; Wang, Penglong; et al. (Genome Med, 2020)
BACKGROUND: Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. METHODS: To investigate this hypothesis, we assessed the relationship between mtDNA-CN and nDNA methylation in 2507 African American (AA) and European American (EA) participants from the Atherosclerosis Risk in Communities (ARIC) study. To validate our findings, we assayed an additional 2528 participants from the Cardiovascular Health Study (CHS) (N = 533) and Framingham Heart Study (FHS) (N = 1995). We further assessed the effect of experimental modification of mtDNA-CN through knockout of TFAM, a regulator of mtDNA replication, via CRISPR-Cas9. RESULTS: Thirty-four independent CpGs were associated with mtDNA-CN at genome-wide significance (P < 5 × 10). Meta-analysis across all cohorts identified six mtDNA-CN-associated CpGs at genome-wide significance (P < 5 × 10). Additionally, over half of these CpGs were associated with phenotypes known to be associated with mtDNA-CN, including coronary heart disease, cardiovascular disease, and mortality. Experimental modification of mtDNA-CN demonstrated that modulation of mtDNA-CN results in changes in nDNA methylation and gene expression of specific CpGs and nearby transcripts. Strikingly, the "neuroactive ligand receptor interaction" KEGG pathway was found to be highly overrepresented in the ARIC cohort (P = 5.24 × 10), as well as the TFAM knockout methylation (P = 4.41 × 10) and expression (P = 4.30 × 10) studies. CONCLUSIONS: These results demonstrate that changes in mtDNA-CN influence nDNA methylation at specific loci and result in differential expression of specific genes that may impact human health and disease via altered cell signaling.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Non-Esterified Fatty Acids and Risks of Frailty, Disability, and Mobility Limitation in Older Adults: The Cardiovascular Health Study. - Ahiawodzi, Peter; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne; Mukamal, Kenneth J (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: Non-esterified fatty acids (NEFAs) play central roles in the relationship between adiposity and glucose metabolism, and they have been implicated in the pathogenesis of cardiovascular disease, but few studies have assessed their effects on complex geriatric syndromes like frailty that cross multiple organ systems. We sought to determine the relationships between NEFAs and incident frailty, disability, and mobility limitation in a population-based cohort of older persons. METHODS: We analyzed 4,710 Cardiovascular Health Study (CHS) participants who underwent measurement of circulating total fasting NEFAs in 1992-1993 and were assessed for frailty in 1996-1997 and for disability and mobility limitation annually. We used ordinal logistic regression to model incident frailty, linear regression to model components of frailty, and Cox regression to model disability and mobility limitation in relation to baseline NEFAs. To ensure proportional hazards, we truncated follow-up at 9 years for disability and 6.5 years for mobility limitation. RESULTS: A total of 42 participants became frail and 510 became pre-frail over a 4-year period, and we documented 1,720 cases of disability and 1,225 cases of mobility limitation during follow-up. NEFAs were positively associated in a dose-dependent manner with higher risks of incident frailty, disability, and mobility limitation. The adjusted odds ratios for frailty were 1.37 (95% confidence interval [CI] = 1.01-1.86; P = .04) across extreme tertiles and 1.17 (95% CI = 1.03-1.33; P = .01) per standard deviation increment. The corresponding hazard ratios for incident disability were 1.14 (95% CI = 1.01-1.30; P = .04) and 1.11 (95% CI = 1.06-1.17; P < .0001); those for incident mobility limitation were 1.23 (95% CI = 1.06-1.43; P = .006) and 1.15 (95% CI = 1.08-1.22; P < .0001). Results were largely consistent among both men and women. Among individual components of frailty, NEFAs were significantly associated with self-reported exhaustion (β = .07; standard error = .03; P = .02). CONCLUSION: Circulating NEFAs are significantly associated with frailty, disability, and mobility limitation among older adults. These results highlight the broad spectrum of adverse health issues associated with NEFA in older adults.

Patterns of Cardiovascular Risk Factors in Old Age and Survival and Health Status at 90. - Odden, Michelle C; Rawlings, Andreea M; Arnold, Alice M; Cushman, Mary; Biggs, Mary L; Psaty, Bruce M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: The population age 90 years and older is the fastest growing segment of the U.S. population. Only recently is it possible to study the factors that portend survival to this age. METHODS: Among participants of the Cardiovascular Health Study, we studied the association of repeated measures of cardiovascular risk factors measured over 15-23 years of follow-up and not only survival to 90 years of age, but also healthy aging outcomes among the population who reached age 90. We included participants aged 67-75 years at baseline (n = 3,613/5,888) to control for birth cohort effects, and followed participants until death or age 90 (median follow-up = 14.7 years). RESULTS: Higher systolic blood pressure was associated with a lower likelihood of survival to age 90, although this association was attenuated at older ages (p-value for interaction <.001) and crossed the null for measurements taken in participants' 80's. Higher levels of high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and body mass index (BMI) were associated with greater longevity. Among the survivors to age 90, those with worse cardiovascular profile (high blood pressure, LDL cholesterol, glucose, and BMI; low HDL cholesterol) had lower likelihood of remaining free of cardiovascular disease, cognitive impairment, and disability. CONCLUSION: In summary, we observed paradoxical associations between some cardiovascular risk factors and survival to old age; whereas, among those who survive to very old age, these risk factors were associated with higher risk of adverse health outcomes.

Performance of the Pooled Cohort Equations to Estimate Atherosclerotic Cardiovascular Disease Risk by Body Mass Index. - Khera, Rohan; Pandey, Ambarish; Ayers, Colby R; Carnethon, Mercedes R; Greenland, Philip; Ndumele, Chiadi E; Nambi, Vijay; Seliger, Stephen L; Chaves, Paulo H M; Safford, Monika M; Cushman, Mary; Xanthakis, Vanessa; et al. (JAMA Netw Open, 2020)
Importance: Obesity is a global health challenge and a risk factor for atherosclerotic cardiovascular disease (ASVCD). Performance of the pooled cohort equations (PCE) for ASCVD risk by body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) is unknown. Objective: To assess performance of the PCE across clinical BMI categories. Design, Setting, and Participants: This cohort study used pooled individual-level data from 8 community-based, prospective, longitudinal cohort studies with 10-year ASCVD event follow-up from 1996 to 2016. We included all adults ages 40 to 79 years without baseline ASCVD or statin use, resulting in a sample size of 37 311 participants. Data were analyzed from August 2017 to July 2020. Exposures: Participant BMI category: underweight (<18.5), normal weight (18.5 to <25), overweight (25 to <30), mild obesity (30 to <35), and moderate to severe obesity (≥35). Main Outcomes and Measures: Discrimination (Harrell C statistic) and calibration (Nam-D'Agostino χ2 goodness-of-fit test) of the PCE across BMI categories. Improvement in discrimination and net reclassification with addition of BMI, waist circumference, and high-sensitivity C-reactive protein (hsCRP) to the PCE. Results: Among 37 311 participants (mean [SD] age, 58.6 [11.8] years; 21 897 [58.7%] women), 380 604 person-years of follow-up were conducted. Mean (SD) baseline BMI was 29.0 (6.2), and 360 individuals (1.0%) were in the underweight category, 9937 individuals (26.6%) were in the normal weight category, 13 601 individuals (36.4%) were in the overweight category, 7783 individuals (20.9%) were in the mild obesity category, and 5630 individuals (15.1%) were in the moderate to severe obesity category. Median (interquartile range [IQR]) 10-year estimated ASCVD risk was 7.1% (2.5%-15.4%), and 3709 individuals (9.9%) developed ASCVD over a median (IQR) 10.8 [8.5-12.6] years. The PCE overestimated ASCVD risk in the overall cohort (estimated/observed [E/O] risk ratio, 1.22; 95% CI, 1.18-1.26) and across all BMI categories except the underweight category. Calibration was better near the clinical decision threshold in all BMI groups but worse among individuals with moderate or severe obesity (E/O risk ratio, 1.36; 95% CI, 1.25-1.47) and among those with the highest estimated ASCVD risk ≥20%. The PCE C statistic overall was 0.760 (95% CI, 0.753-0.767), with lower discrimination in the moderate or severe obesity group (C statistic, 0.742; 95% CI, 0.721-0.763) compared with the normal-range BMI group (C statistic, 0.785; 95% CI, 0.772-0.798). Waist circumference (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.03-1.11) and hsCRP (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.05-1.09), but not BMI, were associated with increased ASCVD risk when added to the PCE. However, these factors did not improve model performance (C statistic, 0.760; 95% CI, 0.753-0.767) with or without added metrics. Conclusions and Relevance: These findings suggest that the PCE had acceptable model discrimination and were well calibrated at clinical decision thresholds but overestimated risk of ASCVD for individuals in overweight and obese categories, particularly individuals with high estimated risk. Incorporation of the usual clinical measures of obesity did not improve risk estimation of the PCE. Future research is needed to determine whether incorporation of alternative high-risk obesity markers (eg, weight trajectory or measures of visceral or ectopic fat) into the PCE may improve risk prediction.
Keywords: Adult; Aged; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Correlation of Data; Female; Humans; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Predicting Risk of Atherosclerotic Cardiovascular Disease Using Pooled Cohort Equations in Older Adults With Frailty, Multimorbidity, and Competing Risks. - Nguyen, Quoc Dinh; Odden, Michelle C; Peralta, Carmen A; Kim, Dae Hyun (J Am Heart Assoc, 2020)
Background Assessment of atherosclerotic cardiovascular disease (ASCVD) risk is crucial for prevention and management, but the performance of the pooled cohort equations in older adults with frailty and multimorbidity is unknown. We evaluated the pooled cohort equations in these subgroups and the impact of competing risks. Methods and Results In 4249 community-dwelling adults, aged ≥65 years, from the CHS (Cardiovascular Health Study), we calculated 10-year risk of hard ASCVD. Frailty was determined using the Fried phenotype. Latent class analysis was used to identify individuals with multimorbidity patterns using chronic conditions. We assessed discrimination using the C-statistic and calibration by comparing predicted ASCVD risks with estimated risk using cause-specific and cumulative incidence models, by multimorbidity patterns and frailty status. A total of 917 (21.6%) participants had an ASCVD event, and 706 (16.6%) had a competing event of death. C-statistic was 0.68 in men and 0.69 in women; calibration was good when compared with cause-specific and cumulative incidence estimated risks (males, -0.1% and 3.3%; females, 0.6% and 1.4%). Latent class analysis identified 4 patterns: minimal disease, cardiometabolic, low cognition, musculoskeletal-lung depression. In the cardiometabolic pattern, ASCVD risk was overpredicted compared with cumulative incidence risk in men (7.4%) and women (6.8%). Risk was underpredicted in men (-10.7%) and women (-8.2%) with frailty compared with cause-specific risk. Miscalibration occurred mostly at high predicted risk ranges. Conclusions ASCVD prediction was good in this cohort of adults aged ≥65 years. Although calibration varied by multimorbidity patterns, frailty, and competing risks, miscalibration was mostly present at high predicted risk ranges and thus less likely to alter decision making for primary prevention therapy.

Putative Cut-Points in Sarcopenia Components and Incident Adverse Health Outcomes: An SDOC Analysis. - Cawthon, Peggy M; Manini, Todd; Patel, Sheena M; Newman, Anne; Travison, Thomas; Kiel, Douglas P; Santanasto, Adam J; Ensrud, Kristine E; Xue, Qian-Li; Shardell, Michelle; Duchowny, Kate; Erlandson, Kristine M; et al. (J Am Geriatr Soc, 2020)
OBJECTIVES: Analyses performed by the Sarcopenia Definitions and Outcomes Consortium (SDOC) identified cut-points in several metrics of grip strength for consideration in a definition of sarcopenia. We describe the associations between the SDOC-identified metrics of low grip strength (absolute or standardized to body size/composition); low dual-energy x-ray absorptiometry (DXA) lean mass as previously defined in the literature (appendicular lean mass [ALM]/ht ); and slowness (walking speed <.8 m/s) with subsequent adverse outcomes (falls, hip fractures, mobility limitation, and mortality). DESIGN: Individual-level, sex-stratified pooled analysis. We calculated odds ratios (ORs) or hazard ratios (HRs) for incident falls, mobility limitation, hip fractures, and mortality. Follow-up time ranged from 1 year for falls to 8.8 ± 2.3 years for mortality. SETTING: Eight prospective observational cohort studies. PARTICIPANTS: A total of 13,421 community-dwelling men and 4,828 community-dwelling women. MEASUREMENTS Grip strength by hand dynamometry, gait speed, and lean mass by DXA. RESULTS: Low grip strength (absolute or standardized to body size/composition) was associated with incident outcomes, usually independently of slowness, in both men and women. ORs and HRs generally ranged from 1.2 to 3.0 for those below vs above the cut-point. DXA lean mass was not consistently associated with these outcomes. When considered together, those who had both muscle weakness by absolute grip strength (<35.5 kg in men and <20 kg in women) and slowness were consistently more likely to have a fall, hip fracture, mobility limitation, or die than those without either slowness or muscle weakness. CONCLUSION: Older men and women with both muscle weakness and slowness have a higher likelihood of adverse health outcomes. These results support the inclusion of grip strength and walking speed as components in a summary definition of sarcopenia. J Am Geriatr Soc 68:1429-1437, 2020.

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.

Sex-Specific Associations of Cardiovascular Risk Factors and Biomarkers With Incident Heart Failure. - Suthahar, Navin; Lau, Emily S; Blaha, Michael J; Paniagua, Samantha M; Larson, Martin G; Psaty, Bruce M; Benjamin, Emelia J; Allison, Matthew A; Bartz, Traci M; Januzzi, James L; Levy, Daniel; Meems, Laura M G; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Whether cardiovascular (CV) disease risk factors and biomarkers associate differentially with heart failure (HF) risk in men and women is unclear. OBJECTIVES: The purpose of this study was to evaluate sex-specific associations of CV risk factors and biomarkers with incident HF. METHODS: The analysis was performed using data from 4 community-based cohorts with 12.5 years of follow-up. Participants (recruited between 1989 and 2002) were free of HF at baseline. Biomarker measurements included natriuretic peptides, cardiac troponins, plasminogen activator inhibitor-1, D-dimer, fibrinogen, C-reactive protein, sST2, galectin-3, cystatin-C, and urinary albumin-to-creatinine ratio. RESULTS: Among 22,756 participants (mean age 60 ± 13 years, 53% women), HF occurred in 2,095 participants (47% women). Age, smoking, type 2 diabetes mellitus, hypertension, body mass index, atrial fibrillation, myocardial infarction, left ventricular hypertrophy, and left bundle branch block were strongly associated with HF in both sexes (p < 0.001), and the combined clinical model had good discrimination in men (C-statistic = 0.80) and in women (C-statistic = 0.83). The majority of biomarkers were strongly and similarly associated with HF in both sexes. The clinical model improved modestly after adding natriuretic peptides in men (ΔC-statistic = 0.006; likelihood ratio chi-square = 146; p < 0.001), and after adding cardiac troponins in women (ΔC-statistic = 0.003; likelihood ratio chi-square = 73; p < 0.001). CONCLUSIONS: CV risk factors are strongly and similarly associated with incident HF in both sexes, highlighting the similar importance of risk factor control in reducing HF risk in the community. There are subtle sex-related differences in the predictive value of individual biomarkers, but the overall improvement in HF risk estimation when included in a clinical HF risk prediction model is limited in both sexes.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole Blood DNA Methylation Signatures of Diet Are Associated With Cardiovascular Disease Risk Factors and All-Cause Mortality. - Ma, Jiantao; Rebholz, Casey M; Braun, Kim V E; Reynolds, Lindsay M; Aslibekyan, Stella; Xia, Rui; Biligowda, Niranjan G; Huan, Tianxiao; Liu, Chunyu; Mendelson, Michael M; Joehanes, Roby; Hu, Emily A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: DNA methylation patterns associated with habitual diet have not been well studied. METHODS: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healthy Eating Index score. We conducted ethnicity-specific and trans-ethnic epigenome-wide association analyses for diet quality and leukocyte-derived DNA methylation at over 400 000 CpGs (cytosine-guanine dinucleotides) in 5 population-based cohorts including 6662 European ancestry, 2702 African ancestry, and 360 Hispanic ancestry participants. For diet-associated CpGs identified in epigenome-wide analyses, we conducted Mendelian randomization (MR) analysis to examine their relations to cardiovascular disease risk factors and examined their longitudinal associations with all-cause mortality. RESULTS: We identified 30 CpGs associated with either Mediterranean-style diet score or Alternative Healthy Eating Index, or both, in European ancestry participants. Among these CpGs, 12 CpGs were significantly associated with all-cause mortality (Bonferroni corrected <1.6×10). Hypermethylation of cg18181703 () was associated with higher scores of both Mediterranean-style diet score and Alternative Healthy Eating Index and lower risk for all-cause mortality (=5.7×10). Ten additional diet-associated CpGs were nominally associated with all-cause mortality (<0.05). MR analysis revealed 8 putatively causal associations for 6 CpGs with 4 cardiovascular disease risk factors (body mass index, triglycerides, high-density lipoprotein cholesterol concentrations, and type 2 diabetes mellitus; Bonferroni corrected MR <4.5×10). For example, hypermethylation of cg11250194 () was associated with lower triglyceride concentrations (MR, =1.5×10).and hypermethylation of cg02079413 (; ) was associated with body mass index (corrected MR, =1×10). CONCLUSIONS: Habitual diet quality was associated with differential peripheral leukocyte DNA methylation levels of 30 CpGs, most of which were also associated with multiple health outcomes, in European ancestry individuals. These findings demonstrate that integrative genomic analysis of dietary information may reveal molecular targets for disease prevention and treatment.

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Association Between Myocardial Strain and Frailty in CHS. - Tan, Annabel X; Shah, Sanjiv J; Sanders, Jason L; Psaty, Bruce M; Wu, Chenkai; Gardin, Julius M; Peralta, Carmen A; Newman, Anne B; Odden, Michelle C (Circ Cardiovasc Imaging, 2021)
BACKGROUND: Myocardial strain, measured by speckle-tracking echocardiography, is a novel measure of subclinical cardiovascular disease and may reflect myocardial aging. We evaluated the association between myocardial strain and frailty-a clinical syndrome of lack of physiological reserve. METHODS: Frailty was defined in participants of the CHS (Cardiovascular Health Study) as having ≥3 of the following clinical criteria: weakness, slowness, weight loss, exhaustion, and inactivity. Using speckle-tracking echocardiography data, we examined the cross-sectional (n=3206) and longitudinal (n=1431) associations with frailty among participants who had at least 1 measure of myocardial strain, left ventricular longitudinal strain (LVLS), left ventricular early diastolic strain rate and left atrial reservoir strain, and no history of cardiovascular disease or heart failure at the time of echocardiography. RESULTS: In cross-sectional analyses, lower (worse) LVLS was associated with prevalent frailty; this association was robust to adjustment for left ventricular ejection fraction (adjusted odds ratio, 1.32 [95% CI, 1.07-1.61] per 1-SD lower strain; =0.007) and left ventricular stroke volume (adjusted OR, 1.32 [95% CI, 1.08-1.61] per 1-SD lower strain; =0.007). In longitudinal analyses, adjusted associations of LVLS and left ventricular early diastolic strain with incident frailty were 1.35 ([95% CI, 0.96-1.89] =0.086) and 1.58 ([95% CI, 1.11-2.27] =0.013, respectively). Participants who were frail and had the worst LVLS had a 2.2-fold increased risk of death (hazard ratio, 2.20 [95% CI, 1.81-2.66]; <0.0001). CONCLUSIONS: In community-dwelling older adults without prevalent cardiovascular disease, worse LVLS by speckle-tracking echocardiography, reflective of subclinical myocardial dysfunction, was associated with frailty. Frailty and LVLS have an additive effect on mortality risk.

Association Between Preserved Ratio Impaired Spirometry and Clinical Outcomes in US Adults. - Wan, Emily S; Balte, Pallavi; Schwartz, Joseph E; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Daviglus, Martha L; Dransfield, Mark T; Gharib, Sina A; Jacobs, David R; Kalhan, Ravi; London, Stephanie J; et al. (JAMA, 2021)
Importance: Chronic lung diseases are a leading cause of morbidity and mortality. Unlike chronic obstructive pulmonary disease, clinical outcomes associated with proportional reductions in expiratory lung volumes without obstruction, otherwise known as preserved ratio impaired spirometry (PRISm), are poorly understood. Objective: To examine the prevalence, correlates, and clinical outcomes associated with PRISm in US adults. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study was a retrospective study with harmonized pooled data from 9 US general population-based cohorts (enrollment, 65 251 participants aged 18 to 102 years of whom 53 701 participants had valid baseline lung function) conducted from 1971-2011 (final follow-up, December 2018). Exposures: Participants were categorized into mutually exclusive groups by baseline lung function. PRISm was defined as the ratio of forced expiratory volume in the first second to forced vital capacity (FEV1:FVC) greater than or equal to 0.70 and FEV1 less than 80% predicted; obstructive spirometry FEV1:FVC ratio of less than 0.70; and normal spirometry FEV1:FVC ratio greater than or equal to 0.7 and FEV1 greater than or equal to 80% predicted. Main Outcomes and Measures: Main outcomes were all-cause mortality, respiratory-related mortality, coronary heart disease (CHD)-related mortality, respiratory-related events (hospitalizations and mortality), and CHD-related events (hospitalizations and mortality) classified by adjudication or validated administrative criteria. Absolute risks were adjusted for age and smoking status. Poisson and Cox proportional hazards models comparing PRISm vs normal spirometry were adjusted for age, sex, race and ethnicity, education, body mass index, smoking status, cohort, and comorbidities. Results: Among all participants (mean [SD] age, 53.2 [15.8] years, 56.4% women, 48.5% never-smokers), 4582 (8.5%) had PRISm. The presence of PRISm relative to normal spirometry was significantly associated with obesity (prevalence, 48.3% vs 31.4%; prevalence ratio [PR], 1.68 [95% CI, 1.55-1.82]), underweight (prevalence, 1.4% vs 1.0%; PR, 2.20 [95% CI, 1.72-2.82]), female sex (prevalence, 60.3% vs 59.0%; PR, 1.07 [95% CI, 1.01-1.13]), and current smoking (prevalence, 25.2% vs 17.5%; PR, 1.33 [95% CI, 1.22-1.45]). PRISm, compared with normal spirometry, was significantly associated with greater all-cause mortality (29.6/1000 person-years vs 18.0/1000 person-years; difference, 11.6/1000 person-years [95% CI, 10.0-13.1]; adjusted hazard ratio [HR], 1.50 [95% CI, 1.42-1.59]), respiratory-related mortality (2.1/1000 person-years vs 1.0/1000 person-years; difference, 1.1/1000 person-years [95% CI, 0.7-1.6]; adjusted HR, 1.95 [95% CI, 1.54-2.48]), CHD-related mortality (5.4/1000 person-years vs 2.6/1000 person-years; difference, 2.7/1000 person-years [95% CI, 2.1-3.4]; adjusted HR, 1.55 [95% CI, 1.36-1.77]), respiratory-related events (12.2/1000 person-years vs 6.0/1000 person-years; difference, 6.2/1000 person-years [95% CI, 4.9-7.5]; adjusted HR, 1.90 [95% CI, 1.69-2.14]), and CHD-related events (11.7/1000 person-years vs 7.0/1000 person-years; difference, 4.7/1000 person-years [95% CI, 3.7-5.8]; adjusted HR, 1.30 [95% CI, 1.18-1.42]). Conclusions and Relevance: In a large, population-based sample of US adults, baseline PRISm, compared with normal spirometry, was associated with a small but statistically significant increased risk for mortality and adverse cardiovascular and respiratory outcomes. Further research is needed to explore whether this association is causal.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Prevalence; Retrospective Studies; Spirometry; United States; Vital Capacity

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of Midlife Cardiovascular Risk Factors With the Risk of Heart Failure Subtypes Later in Life. - Cohen, Laura P; Vittinghoff, Eric; Pletcher, Mark J; Allen, Norrina B; Shah, Sanjiv J; Wilkins, John T; Chang, Patricia P; Ndumele, Chiadi E; Newman, Anne B; Ives, Diane; Maurer, Mathew S; Oelsner, Elizabeth C; et al. (J Card Fail, 2021)
BACKGROUND: Independent associations between cardiovascular risk factor exposures during midlife and later life development of heart failure (HF) with preserved ejection fraction (HFpEF) versus reduced EF (HFrEF) have not been previously studied. METHODS: We pooled data from 4 US cohort studies (Atherosclerosis Risk in Communities, Cardiovascular Health, Health , Aging and Body Composition, and Multi-Ethnic Study of Atherosclerosis) and imputed annual risk factor trajectories for body mass index, systolic and diastolic blood pressure, low-density lipoprotein and high-density lipoprotein cholesterol, and glucose starting from age 40 years. Time-weighted average exposures to each risk factor during midlife and later life were calculated and analyzed for associations with the development of HFpEF or HFrEF. RESULTS: A total of 23,861 participants were included (mean age at first in-person visit, 61.8 ±1 0.2 years; 56.6% female). During a median follow-up of 12 years, there were 3666 incident HF events, of which 51% had EF measured, including 934 with HFpEF and 739 with HFrEF. A high midlife systolic blood pressure and low midlife high-density lipoprotein cholesterol were associated with HFrEF, and a high midlife body mass index, systolic blood pressure, pulse pressure, and glucose were associated with HFpEF. After adjusting for later life exposures, only midlife pulse pressure remained independently associated with HFpEF. CONCLUSIONS: Midlife exposure to cardiovascular risk factors are differentially associated with HFrEF and HFpEF later in life. Having a higher pulse pressure during midlife is associated with a greater risk for HFpEF but not HFrEF, independent of later life exposures.

Association of Retail Environment and Neighborhood Socioeconomic Status with Mortality among Community-dwelling Older Adults in the US: Cardiovascular Health Study. - Zhang, Kehan; Lovasi, Gina S; Odden, Michelle C; Michael, Yvonne L; Newman, Anne B; Arnold, Alice M; Kim, Dae Hyun; Wu, Chenkai (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Few studies have examined the association of neighborhood environment and mortality among community-dwelling older populations. Geographic Information Systems (GIS)-based measures of neighborhood physical environment may provide new insights on the health effects of the social and built environment. METHODS: We studied 4,379 community-dwelling older adults in the US aged ≥65 years from the Cardiovascular Health Study. Principal component analysis was used to identify neighborhood components from 48 variables assessing facilities and establishments, demographic composition, socio-economic status, and economic prosperity. We used a Cox model to evaluate the association of neighborhood components with five-year mortality. Age, sex, race, education, income, marital status, body mass index, smoking status, disability, coronary heart disease, and diabetes were included as covariates. We also examined the interactions between neighborhood components and sex and race (Black vs. white or other). RESULTS: We identified five neighborhood components, representing facilities and resources, immigrant communities, community-level economic deprivation, resident-level socio-economic status and residents' age. Communities' economic deprivation and residents' socio-economic status were significantly associated with five-year mortality. We did not find interactions between sex or race and any of the five neighborhood components. The results were similar in a sensitivity analysis where we used ten-year mortality as the outcome. CONCLUSIONS: We found that communities' economic status but not facilities in communities was associated with mortality among older adults. These findings revealed the importance and benefits living in a socio-economically advantaged neighborhood could have on health among older residents with different demographic backgrounds.

Association of Trimethylamine N-Oxide and Related Metabolites in Plasma and Incident Type 2 Diabetes: The Cardiovascular Health Study. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; McKnight, Barbara; Nemet, Ina; Biggs, Mary L; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Psaty, Bruce M; Siscovick, David S; Hazen, Stanley L; et al. (JAMA Netw Open, 2021)
Importance: Although rodent studies suggest that trimethylamine N-oxide (TMAO) influences glucose homeostasis and risk of type 2 diabetes, evidence in humans is limited. Objective: To examine the associations of serial measures of plasma TMAO and related metabolite concentrations with incident type 2 diabetes, fasting plasma insulin and glucose levels, and the Gutt insulin sensitivity index (ISI). Design, Setting, and Participants: This prospective cohort design assessed the association of plasma TMAO and related metabolite concentrations with diabetes outcome, whereas a cross-sectional design assessed the association with insulin and glucose levels and Gutt ISI. The participants were a cohort of older US adults from the Cardiovascular Health Study (CHS). Data from June 1989 to May 1990, from November 1992 to June 1993, and from June 1995 to June 1997 were included, with follow-up through June 2010. Levels of TMAO and related metabolites were measured in CHS plasma samples. Data were analyzed from July 2019 to September 2020. Exposures: Plasma concentrations of TMAO, carnitine, betaine, choline, crotonobetaine, and γ-butyrobetaine, measured by high-performance liquid chromatography and mass spectrometry. Main Outcomes and Measures: Linear regression for associations of TMAO and related metabolites with insulin and glucose levels and Gutt ISI, and proportional hazards regression for associations with diabetes. Results: The study included 4442 participants without diabetes at baseline (mean [SD] age, 73 [6] years at entry; 2710 [61%] women). In multivariable analyses, plasma TMAO, carnitine, crotonobetaine, and γ-butyrobetaine concentrations were positively associated with fasting insulin level (insulin mean geometric ratio comparing fifth with first quintiles of metabolite concentration: 1.07 [95% CI, 1.04-1.10] for TMAO; 1.07 [95% CI, 1.03-1.10] for carnitine; 1.05 [95% CI, 1.02-1.08] for crotonobetaine; and 1.06 [95% CI, 1.02-1.09] for γ-butyrobetaine). In contrast, betaine and choline concentrations were associated with greater insulin sensitivity (mean difference in Gutt ISI comparing fifth with first quintiles: 6.46 [95% CI, 4.32-8.60] and 2.27 [95% CI, 0.16-4.38], respectively). Incident diabetes was identified in 661 participants during a median 12.1 (interquartile range, 6.9-17.1) years of follow-up. In multivariable analyses, TMAO and metabolites were not significantly associated with type 2 diabetes risk (hazard ratios of diabetes comparing fifth with first quintile: 1.20 [95% CI, 0.94-1.55] for TMAO; 0.96 [95% CI, 0.74-1.24] for choline; 0.88 [95% CI, 0.67-1.15] for betaine; 1.07 [95% CI, 0.83-1.37] for carnitine; 0.79 [95% CI, 0.60-1.04] for γ-butyrobetaine; and 1.06 [95% CI, 0.83-1.35] for crotonobetaine). Conclusions and Relevance: Plasma TMAO and related metabolites were not significantly associated with type 2 diabetes among older adults. The metabolites TMAO, carnitine, γ-butyrobetaine, and crotonobetaine may be associated with insulin resistance, and betaine and choline may be associated with greater insulin sensitivity, but temporality of the associations was not established.

Associations of Body Mass Index and Waist Circumference in Young Adulthood with Later Life Incident Diabetes. - Nair, Nandini; Vittinghoff, Eric; Pletcher, Mark J; Oelsner, Elizabeth C; Allen, Norrina B; Ndumele, Chiadi E; West, Nancy A; Strotmeyer, Elsa S; Mukamal, Kenneth J; Siscovick, David S; Biggs, Mary L; Laferrère, Blandine; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: The independent contribution of young adult exposure to overweight and obesity to later-life incident diabetes is not well studied. OBJECTIVE: To assess the associations of exposures to elevated body mass index (BMI) and waist circumference (WC) in young adulthood (ages 18-39 years) with incident diabetes later in life (≥40 years). DESIGN: Pooled data from 6 US prospective cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Risk Development in Young Adults Study, Cardiovascular Health Study, (4) Framingham Heart Study Offspring Cohort, (5) Health, Aging and Body Composition Study, and (6) Multi-Ethnic Study of Atherosclerosis. SETTING: Population-based cohort studies. PARTICIPANTS: 30 780 participants (56.1% female, 69.8% non-Hispanic white) without a diagnosis of diabetes by age 40. INTERVENTIONS: We imputed BMI and WC trajectories from age 18 for every participant and estimated time-weighted average exposures to BMI or WC during young adulthood and later life. MAIN OUTCOME MEASURE(S): Incident diabetes defined as fasting glucose ≥126 mg/dL, nonfasting glucose ≥200 mg/dL, or use of diabetes medications. RESULTS: During a 9-year median follow-up, 4323 participants developed incident diabetes. Young adult BMI and WC were associated with later-life incident diabetes after controlling for later-life exposures [hazard ratios (HR) 1.99 for BMI ≥ 30 kg/m2 and 2.13 for WC > 88cm (women)/>102cm (men) compared to normal ranges]. Young adult homeostatic model of insulin resistance mediated 49% and 44% of the association between BMI and WC with later-life incident diabetes. High-density lipoproteins and triglycerides mediated a smaller proportion of these associations. CONCLUSIONS: Elevated BMI and WC during young adulthood were independently associated with later-life incident diabetes. Insulin resistance may be a key mediator.
Keywords: Adolescent; Adult; Biomarkers; Body Mass Index; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Male; Obesity; Overweight; Prognosis; Prospective Studies; Risk Factors; United States; Waist Circumference; Young Adult

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

Estimating Systolic Blood Pressure Intervention Trial Participant Posttrial Survival Using Pooled Epidemiologic Cohort Data. - Bellows, Brandon K; Zhang, Yiyi; Zhang, Zugui; Lloyd-Jones, Donald M; Bress, Adam P; King, Jordan B; Kolm, Paul; Cushman, William C; Johnson, Karen C; Tamariz, Leonardo; Oelsner, Elizabeth C; Shea, Steven; et al. (J Am Heart Assoc, 2021)
Background Intensive systolic blood pressure treatment (<120 mm Hg) in SPRINT (Systolic Blood Pressure Intervention Trial) improved survival compared with standard treatment (<140 mm Hg) over a median follow-up of 3.3 years. We projected life expectancy after observed follow-up in SPRINT using SPRINT-eligible participants in the NHLBI-PCS (National Heart, Lung, and Blood Institute Pooled Cohorts Study). Methods and Results We used propensity scores to weight SPRINT-eligible NHLBI-PCS participants to resemble SPRINT participants. In SPRINT participants, we estimated in-trial survival (<4 years) using a time-based flexible parametric survival model. In SPRINT-eligible NHLBI-PCS participants, we estimated posttrial survival (≥4 years) using an age-based flexible parametric survival model and applied the formula to SPRINT participants to predict posttrial survival. We projected overall life expectancy for each SPRINT participant and compared it to parametric regression (eg, Gompertz) projections based on SPRINT data alone. We included 8584 SPRINT and 10 593 SPRINT-eligible NHLBI-PCS participants. After propensity weighting, mean (SD) age was 67.9 (9.4) and 68.2 (8.8) years, and 35.5% and 37.6% were women in SPRINT and NHLBI-PCS, respectively. Using the NHLBI-PCS-based method, projected mean life expectancy from randomization was 21.0 (7.4) years with intensive and 19.1 (7.2) years with standard treatment. Using the Gompertz regression, life expectancy was 11.2 (2.3) years with intensive and 10.5 (2.2) years with standard treatment. Conclusions Combining SPRINT and NHLBI-PCS observed data likely offers a more realistic estimate of life expectancy than parametrically extrapolating SPRINT data alone. These results offer insight into the potential long-term effectiveness of intensive SBP goals.

FGL1 as a modulator of plasma D-dimer levels: Exome-wide marker analysis of plasma tPA, PAI-1, and D-dimer. - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A T; Chen, Ming-Huei; O'Donnell, Christopher J; Kleber, Marcus E; Delgado, Graciela E; Guo, Xiuqing; Yao, Jie; Taylor, Kent D; Ozel, Ayse Bilge; et al. (J Thromb Haemost, 2021)
BACKGROUND: Use of targeted exome-arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator-inhibitor 1 (PAI-1), tissue plasminogen activator (tPA), and the plasma product D-dimer are important components of the fibrinolytic system. There have been few large-scale genome-wide or exome-wide studies of PAI-1, tPA, and D-dimer. OBJECTIVES: We sought to discover new genetic loci contributing to variation in these traits using an exome-array approach. METHODS: Cohort-level analyses and fixed effects meta-analyses of PAI-1 (n = 15 603), tPA (n = 6876,) and D-dimer (n = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single-variant analyses and gene-based burden testing. RESULTS: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D-dimer levels, achieved genome-wide significance (P < 5 × 10 ). Replication was sought for these 5 variants, as well as 45 well-imputed variants with P < 1 × 10 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen-like-1) with increased plasma D-dimer levels. Additionally, a candidate-gene approach revealed a suggestive association for a coding variant (rs143202684-C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830-A) in SCARB1 associated with increased D-dimer levels. CONCLUSION: This work provides new evidence for a role of FGL1 in hemostasis.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

{Genome-Wide Association Study of Circulating Interleukin 6 Levels Identifies Novel Loci - Ahluwalia, T. S.; Prins, B. P.; Abdollahi, M.; Armstrong, N. J.; Aslibekyan, S.; Bain, L.; Jefferis, B.; Baumert, J.; Beekman, M.; Ben-Shlomo, Y.; Bis, J. C.; Mitchell, B. D.; et al. (Hum Mol Genet, 2021)
Interleukin-6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery, and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed-effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on Chromosome (Chr) 2q14, (pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.

{Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Jones, G.; Trajanoska, K.; Santanasto, A. J.; Stringa, N.; Kuo, C. L.; Atkins, J. L.; Lewis, J. R.; Duong, T.; Hong, S.; Biggs, M. L.; Luan, J.; Sarnowski, C.; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10-17), arthritis (GDF5 p = 4 × 10-13), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.

{The genomics of heart failure: design and rationale of the HERMES consortium - Lumbers, R. T.; Shah, S.; Lin, H.; Czuba, T.; Henry, A.; Swerdlow, D. I.; Malarstig, A.; Andersson, C.; Verweij, N.; Holmes, M. V.; Ärnlöv, J.; Svensson, P.; et al. (ESC Heart Fail, 2021)
The HERMES (HEart failure Molecular Epidemiology for Therapeutic targetS) consortium aims to identify the genomic and molecular basis of heart failure.\ under an additive genetic model.\ HERMES is a global collaboration aiming to (i) identify the genetic determinants of heart failure; (ii) generate insights into the causal pathways leading to heart failure and enable genetic approaches to target prioritization; and (iii) develop genomic tools for disease stratification and risk prediction.

Longitudinal Plasma Measures of Trimethylamine N-Oxide and Risk of Atherosclerotic Cardiovascular Disease Events in Community-Based Older Adults. - Lee, Yujin; Nemet, Ina; Wang, Zeneng; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda M; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (J Am Heart Assoc, 2021)
Background Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of dietary choline, L-carnitine, and phosphatidylcholine-rich foods. On the basis of experimental studies and patients with prevalent disease, elevated plasma TMAO may increase risk of atherosclerotic cardiovascular disease (ASCVD). TMAO is also renally cleared and may interact with and causally contribute to renal dysfunction. Yet, how serial TMAO levels relate to incident and recurrent ASCVD in community-based populations and the potential mediating or modifying role of renal function are not established. Methods and Results We investigated associations of serial measures of plasma TMAO, assessed at baseline and 7 years, with incident and recurrent ASCVD in a community-based cohort of 4131 (incident) and 1449 (recurrent) older US adults. TMAO was measured using stable isotope dilution liquid chromatography-tandem mass spectrometry (laboratory coefficient of variation, <6%). Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, sudden cardiac death, or other atherosclerotic death) was centrally adjudicated using medical records. Risk was assessed by multivariable Cox proportional hazards regression, including time-varying demographics, lifestyle factors, medical history, laboratory measures, and dietary habits. Potential mediating effects and interaction by estimated glomerular filtration rate (eGFR) were assessed. During prospective follow-up, 1766 incident and 897 recurrent ASCVD events occurred. After multivariable adjustment, higher levels of TMAO were associated with a higher risk of incident ASCVD, with extreme quintile hazard ratio (HR) compared with the lowest quintile=1.21 (95% CI, 1.02-1.42; -trend=0.029). This relationship appeared mediated or confounded by eGFR (eGFR-adjusted HR, 1.07; 95% CI, 0.90-1.27), as well as modified by eGFR (-interaction <0.001). High levels of TMAO were associated with higher incidence of ASCVD in the presence of impaired renal function (eGFR <60 mL/min per 1.73 m: HR, 1.56 [95% CI, 1.13-2.14]; -trend=0.007), but not normal or mildly reduced renal function (eGFR ≥60 mL/min per 1.73 m: HR, 1.03 [95% CI, 0.85-1.25]; -trend=0.668). Among individuals with prior ASCVD, TMAO associated with higher risk of recurrent ASCVD (HR, 1.25 [95% CI, 1.01-1.56]; -trend=0.009), without significant modification by eGFR. Conclusions In this large community-based cohort of older US adults, serial measures of TMAO were associated with higher risk of incident ASCVD, with apparent modification by presence of impaired renal function and with higher risk of recurrent ASCVD.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

n-3 Fatty Acid Biomarkers and Incident Type 2 Diabetes: An Individual Participant-Level Pooling Project of 20 Prospective Cohort Studies - Qian, F.; Ardisson Korat, A. V.; Imamura, F.; Marklund, M.; Tintle, N.; Virtanen, J. K.; Zhou, X.; Bassett, J. K.; Lai, H.; Hirakawa, Y.; Chien, K. L.; Wood, A. C.; et al. (Diabetes Care, 2021)
-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with T2D risk through an individual participant-level pooled analysis.\ For our analysis we incorporated data from a global consortium of 20 prospective studies from 14 countries. We included 65,147 participants who had blood measurements of ALA, EPA, DPA, or DHA and were free of diabetes at baseline. De novo harmonized analyses were performed in each cohort following a prespecified protocol, and cohort-specific associations were pooled using inverse variance-weighted meta-analysis.\ 0.001). ALA was not associated with T2D (HR 0.97 [95% CI 0.92, 1.02]) per interquintile range. Associations were robust across prespecified subgroups as well as in sensitivity analyses.\ Higher circulating biomarkers of seafood-derived n-3 fatty acids, including EPA, DPA, DHA, and their sum, were associated with lower risk of T2D in a global consortium of prospective studies. The biomarker of plant-derived ALA was not significantly associated with T2D risk.

Nonesterified Fatty Acids and Kidney Function Decline in Older Adults: Findings From the Cardiovascular Health Study. - Walther, Carl P; Ix, Joachim H; Biggs, Mary L; Kizer, Jorge R; Navaneethan, Sankar D; Djoussé, Luc; Mukamal, Kenneth J (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Circulating non-esterified fatty acids (NEFAs) make up a small portion of circulating lipids but are a metabolically important energy source. Excessive circulating NEFAs may contribute to lipotoxicity in many tissues, including the kidneys. We investigated the relationship between total circulating NEFA concentration and kidney outcomes in older, community-dwelling adults. STUDY DESIGN: Prospective cohort study. SETTING & PARTICIPANTS: 4,698 participants ≥65 years of age in the Cardiovascular Health Study who underwent total fasting serum NEFA concentration measurements in 1992-1993. EXPOSURE: Fasting serum NEFA concentration at one timepoint. OUTCOMES: Three primary outcomes: estimated glomerular filtration rate (eGFR) decline of >30%; the composite of eGFR decline ≥30% or kidney failure with replacement therapy (KFRT); and change in eGFR. These outcomes were assessed over 4- and 13-year periods. ANALYTICAL APPROACH: Logistic regression for the dichotomous outcomes and mixed effects models for the continuous outcome, with sequential adjustment for baseline covariates. Inverse probability of attrition weighting was implemented to account for informative attrition during the follow-up periods. RESULTS: Serum NEFA concentrations were not independently associated with kidney outcomes. In unadjusted and partially adjusted analyses, the highest quartile of serum NEFA concentration (compared to lowest) was associated with a higher risk of ≥30% eGFR decline at 4 years and faster rate of decline of eGFR. No associations were evident after adjustment for comorbidities, lipid levels, insulin sensitivity, medications, and vital signs: odds ratio 1.33 (95%CI 0.83-2.13); estimated glomerular filtration rate change per year, Q4 vs Q1: -0.15 ml/min/1.73m/year (95%CI -0.36 to 0.06). LIMITATIONS: Single NEFA measurements, no measurements of post-glucose load NEFA concentrations or individual NEFA species, no measurement of baseline urine albumin. CONCLUSIONS: A single fasting serum NEFA concentration was not independently associated with long-term adverse kidney outcomes in a cohort of older community-living adults.

Performance of the American Heart Association/American College of Cardiology Pooled Cohort Equations to Estimate Atherosclerotic Cardiovascular Disease Risk by Self-reported Physical Activity Levels. - Pandey, Ambarish; Mehta, Anurag; Paluch, Amanda; Ning, Hongyan; Carnethon, Mercedes R; Allen, Norrina B; Michos, Erin D; Berry, Jarett D; Lloyd-Jones, Donald M; Wilkins, John T (JAMA Cardiol, 2021)
Importance: The American Heart Association/American College of Cardiology pooled cohort equations (PCEs) are used for predicting 10-year atherosclerotic cardiovascular disease (ASCVD) risk. Pooled cohort equation risk prediction capabilities across self-reported leisure-time physical activity (LTPA) levels and the change in model performance with addition of LTPA to the PCE are unclear. Objective: To evaluate PCE risk prediction performance across self-reported LTPA levels and the change in model performance by adding LTPA to the existing PCE model. Design, Setting, and Participants: Individual-level pooling of data from 3 longitudinal cohort studies-Atherosclerosis Risk in Communities, Multi-Ethnic Study of Atherosclerosis, and Cardiovascular Health Study-was performed. A total of 18 824 participants were stratified into 4 groups based on self-reported LTPA levels: inactive (0 metabolic equivalent of task [MET]-min/wk), less than guideline-recommended (<500 MET-min/wk), guideline-recommended (500-1000 MET-min/week), and greater than guideline-recommended (>1000 MET-min/wk). Pooled cohort equation risk discrimination was studied using the C statistic and reclassification capabilities were studied using the Greenwood Nam-D'Agostino χ2 goodness-of-fit test. Change in risk discrimination and reclassification on adding LTPA to PCEs was evaluated using change in C statistic, integrated discrimination index, and categorical net reclassification index. Main Outcomes and Measures: Adjudicated ASCVD events during 10-year follow-up. Results: Among 18 824 participants studied, 10 302 were women (54.7%); mean (SD) age was 57.6 (8.2) years. A total of 5868 participants (31.2%) were inactive, 3849 (20.4%) had less than guideline-recommended LTPA, 3372 (17.9%) had guideline-recommended LTPA, and 5735 (30.5%) had greater than guideline-recommended LTPA level. Higher LTPA levels were associated with a lower risk of ASCVD after adjustment for risk factors (hazard ratio [HR] per 1-SD higher LTPA, 0.91; 95% CI, 0.86-0.96). Across LTPA groups, PCE risk discrimination (C statistic, 0.76-0.78) and risk calibration (all χ2﻿ P > .10) was similar. Addition of LTPA to the PCE model resulted in no significant change in the C statistic (0.0005; 95% CI, -0.0004 to 0.0015; P = .28) and categorical net reclassification index (-0.003; 95% CI, -0.010 to 0.010; P = .95), but a minimal improvement in the integrated discrimination index (0.0008; 95% CI, 0.0002-0.0013; P = .005) was observed. Similar results were noted when cohort-specific coefficients were used for creating the baseline model. Conclusions and Relevance: Higher self-reported LTPA levels appear to be associated with lower ASCVD risk and increasing LTPA promotes cardiovascular wellness. These findings suggest the American Heart Association/American College of Cardiology PCEs are accurate at estimating the probability of 10-year ASCVD risk regardless of LTPA level. The addition of self-reported LTPA to PCEs does not appear to be associated with improvement in risk prediction model performance.

The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction. - Trompet, Stella; Postmus, Iris; Warren, Helen R; Noordam, Raymond; Smit, Roelof A J; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I; Hitman, Graham A; Munroe, Patricia B; Rotter, Jerome I; et al. (Front Pharmacol, 2021)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been assessed in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigated whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with a fixed-effects model, inverse variance weighted meta-analysis. All SNPs with -values <5.0 × 10 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (eight studies, = 10,769, 4,212 cases), we observed no genome-wide significant results ( < 5.0 × 10). A total of 144 genetic variants were followed-up in the second stage (three studies, = 1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. It does not appear likely that genetic testing for predicting effects of statins on clinical events will become a useful tool in clinical practice.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

Premature ventricular complexes and development of heart failure in a community-based population. - Limpitikul, Worawan B; Dewland, Thomas A; Vittinghoff, Eric; Soliman, Elsayed; Nah, Gregory; Fang, Christina; Siscovick, David S; Psaty, Bruce M; Sotoodehnia, Nona; Heckbert, Susan; Stein, Phyllis K; Gottdiener, John; et al. (Heart, 2021)
OBJECTIVE: A higher premature ventricular complex (PVC) frequency is associated with incident congestive heart failure (CHF) and death. While certain PVC characteristics may contribute to that risk, the current literature stems from patients in medical settings and is therefore prone to referral bias. This study aims to identify PVC characteristics associated with incident CHF in a community-based setting. METHODS: The Cardiovascular Health Study is a cohort of community-dwelling individuals who underwent prospective evaluation and follow-up. We analysed 24-hour Holter data to assess PVC characteristics and used multivariable logistic and Cox proportional hazards models to identify predictors of a left ventricular ejection fraction (LVEF) decline and incident CHF, respectively. RESULTS: Of 871 analysed participants, 316 participants exhibited at least 10 PVCs during the 24-hour recording. For participants with PVCs, the average age was 72±5 years, 41% were women and 93% were white. Over a median follow-up of 11 years, 34% developed CHF. After adjusting for demographics, cardiovascular comorbidities, antiarrhythmic drug use and PVC frequency, a greater heterogeneity of the PVC coupling interval was associated with an increased risk of LVEF decline and incident CHF. Of note, neither PVC duration nor coupling interval duration exhibited a statistically significant relationship with either outcome. CONCLUSIONS: In this first community-based study to identify Holter-based features of PVCs that are associated with LVEF reduction and incident CHF, the fact that coupling interval heterogeneity was an independent risk factor suggests that the mechanism of PVC generation may influence the risk of heart failure.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

{Rare Coding Variants Associated With Electrocardiographic Intervals Identify Monogenic Arrhythmia Susceptibility Genes: A Multi-Ancestry Analysis - Choi, S. H.; Jurgens, S. J.; Haggerty, C. M.; Hall, A. W.; Halford, J. L.; Morrill, V. N.; Weng, L. C.; Lagerman, B.; Mirshahi, T.; Pettinger, M.; Guo, X.; Lin, H. J.; et al. (Circ Genom Precis Med, 2021)
Alterations in electrocardiographic (ECG) intervals are well-known markers for arrhythmia and sudden cardiac death (SCD) risk. While the genetics of arrhythmia syndromes have been studied, relations between electrocardiographic intervals and rare genetic variation at a population level are poorly understood.\ Using a discovery sample of 29 000 individuals with whole-genome sequencing from Trans-Omics in Precision Medicine and replication in nearly 100 000 with whole-exome sequencing from the UK Biobank and MyCode, we examined associations between low-frequency and rare coding variants with 5 routinely measured electrocardiographic traits (RR, P-wave, PR, and QRS intervals and corrected QT interval).\ ), a marker of SCD risk. Incomplete penetrance of such deleterious variation was common as over 70% of carriers had normal electrocardiographic intervals.\ Our findings indicate that large-scale high-depth sequence data and electrocardiographic analysis identifies monogenic arrhythmia susceptibility genes and rare variants with large effects. Known pathogenic variation in conventional arrhythmia and SCD genes exhibited incomplete penetrance and accounted for only a small fraction of marked electrocardiographic interval prolongation.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Sugar-Sweetened Beverage Consumption May Modify Associations Between Genetic Variants in the CHREBP (Carbohydrate Responsive Element Binding Protein) Locus and HDL-C (High-Density Lipoprotein Cholesterol) and Triglyceride Concentrations. - Haslam, Danielle E; Peloso, Gina M; Guirette, Melanie; Imamura, Fumiaki; Bartz, Traci M; Pitsillides, Achilleas N; Wang, Carol A; Li-Gao, Ruifang; Westra, Jason M; Pitkänen, Niina; Young, Kristin L; Graff, Mariaelisa; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: ChREBP (carbohydrate responsive element binding protein) is a transcription factor that responds to sugar consumption. Sugar-sweetened beverage (SSB) consumption and genetic variants in the locus have separately been linked to HDL-C (high-density lipoprotein cholesterol) and triglyceride concentrations. We hypothesized that SSB consumption would modify the association between genetic variants in the locus and dyslipidemia. METHODS: Data from 11 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (N=63 599) and the UK Biobank (N=59 220) were used to quantify associations of SSB consumption, genetic variants, and their interaction on HDL-C and triglyceride concentrations using linear regression models. A total of 1606 single nucleotide polymorphisms within or near were considered. SSB consumption was estimated from validated questionnaires, and participants were grouped by their estimated intake. RESULTS: In a meta-analysis, rs71556729 was significantly associated with higher HDL-C concentrations only among the highest SSB consumers (β, 2.12 [95% CI, 1.16-3.07] mg/dL per allele; <0.0001), but not significantly among the lowest SSB consumers (=0.81; <0.0001). Similar results were observed for 2 additional variants (rs35709627 and rs71556736). For triglyceride, rs55673514 was positively associated with triglyceride concentrations only among the highest SSB consumers (β, 0.06 [95% CI, 0.02-0.09] ln-mg/dL per allele, =0.001) but not the lowest SSB consumers (=0.84; =0.0005). CONCLUSIONS: Our results identified genetic variants in the locus that may protect against SSB-associated reductions in HDL-C and other variants that may exacerbate SSB-associated increases in triglyceride concentrations. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00005133, NCT00005121, NCT00005487, and NCT00000479.

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

Total carotenoid intake is associated with reduced loss of grip strength and gait speed over time in adults: The Framingham Offspring Study. - Sahni, Shivani; Dufour, Alyssa B; Fielding, Roger A; Newman, Anne B; Kiel, Douglas P; Hannan, Marian T; Jacques, Paul F (Am J Clin Nutr, 2021)
BACKGROUND: Lower antioxidant serum concentrations have been linked to declines in lean mass and physical function in older adults. Yet population data on the effect of dietary antioxidants on loss of muscle strength and physical function are lacking. OBJECTIVE: We sought to determine the association of antioxidant intake [vitamin C, vitamin E, and total and individual carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein + zeaxanthin)] with annualized change in grip strength and gait speed in adults from the Framingham Offspring study. METHODS: This prospective cohort study included participants with a valid FFQ at the index examination and up to 2 prior examinations and at ≥2 measures of primary outcomes: grip strength (n = 2452) and/or gait speed (n = 2422) measured over 3 subsequent examinations. Annualized change in grip strength (kg/y) and change in gait speed (m/s/y) over the follow-up period were used. Linear regression was used to calculate β coefficients and P values, adjusting for covariates. RESULTS: Mean ± SD age of participants was 61 ± 9 y (range: 33-88 y). Median intakes (IQR, mg/d) of vitamin C, vitamin E, and total carotenoid across available examinations were 209.2 (133.1-394.2), 27.1 (7.4-199.0), and 15.3 (10.4-21.3), respectively. The mean follow-up time was ∼12 ± 2 y (range: 4.5-15.4 y). In the sex-combined sample, higher intakes of total carotenoids, lycopene, and lutein + zeaxanthin were associated with increased annualized change in grip strength [β (SE) per 10-mg higher intake/d, range: 0.0316 (0.0146) to 0.1223 (0.0603) kg/y)]. All antioxidants except for vitamin C were associated with faster gait speed [β (SE) per 10-mg higher intake/d, range: 0.00008 (0.00004) to 0.0187 (0.0081) m/s/y]. CONCLUSIONS: Higher antioxidant intake was associated with increase in grip strength and faster gait speed in this cohort of adults. This finding highlights the need for a randomized controlled trial of dietary antioxidants and their effect on muscle strength and physical function.
Keywords: Adult; Aged; Aged, 80 and over; Carotenoids; Cohort Studies; Diet; Female; Hand Strength; Humans; Male; Middle Aged; Prospective Studies; Walking Speed

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

What Cut-Point in Gait Speed Best Discriminates Community-Dwelling Older Adults With Mobility Complaints From Those Without? A Pooled Analysis From the Sarcopenia Definitions and Outcomes Consortium. - Cawthon, Peggy M; Patel, Sheena M; Kritchevsky, Stephen B; Newman, Anne B; Santanasto, Adam; Kiel, Douglas P; Travison, Thomas G; Lane, Nancy; Cummings, Steven R; Orwoll, Eric S; Duchowny, Kate A; Kwok, Timothy; et al. (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Cut-points to define slow walking speed have largely been derived from expert opinion. METHODS: Study participants (13 589 men and 5043 women aged ≥65years) had walking speed (m/s) measured over 4-6 m (mean ± SD: 1.20 ± 0.27 m/s in men and 0.94 ± 0.24 m/s in women.) Mobility limitation was defined as any self-reported difficulty with walking approximately 1/4 mile (prevalence: 12.6% men, 26.4% women). Sex-stratified classification and regression tree (CART) models with 10-fold cross-validation identified walking speed cut-points that optimally discriminated those who reported mobility limitation from those who did not. RESULTS: Among 5043 women, CART analysis identified 2 cut-points, classifying 4144 (82.2%) with walking speed ≥0.75 m/s, which we labeled as "fast"; 478 (9.5%) as "intermediate" (walking speed ≥0.62 m/s but <0.75 m/s); and 421 (8.3%) as "slow" (walking speed <0.62 m/s). Among 13 589 men, CART analysis identified 3 cut-points, classifying 10 001 (73.6%) with walking speed ≥1.00 m/s ("very fast"); 2901 (21.3%) as "fast" (walking speed ≥0.74 m/s but <1.00 m/s); 497 (3.7%) as "intermediate" (walking speed ≥0.57 m/s but <0.74 m/s); and 190 (1.4%) as "slow" (walking speed <0.57 m/s). Prevalence of self-reported mobility limitation was lowest in the "fast" or "very fast" (11% for men and 19% for women) and highest in the "slow" (60.5% in men and 71.0% in women). Rounding the 2 slower cut-points to 0.60 m/s and 0.75 m/s reclassified very few participants. CONCLUSIONS: Cut-points in walking speed of approximately 0.60 m/s and 0.75 m/s discriminate those with self-reported mobility limitation from those without.
Keywords: Aged; Female; Gait; Humans; Independent Living; Male; Mobility Limitation; Sarcopenia; Walking; Walking Speed

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

Association of immune cell subsets with incident heart failure in two population-based cohorts. - Sinha, Arjun; Sitlani, Colleen M; Doyle, Margaret F; Fohner, Alison E; Bůzková, Petra; Floyd, James S; Huber, Sally A; Olson, Nels C; Njoroge, Joyce N; Kizer, Jorge R; Delaney, Joseph A; Shah, Sanjiv S; et al. (ESC Heart Fail, 2022)
AIMS: Circulating inflammatory markers are associated with incident heart failure (HF), but prospective data on associations of immune cell subsets with incident HF are lacking. We determined the associations of immune cell subsets with incident HF as well as HF subtypes [with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF)]. METHODS AND RESULTS: Peripheral blood immune cell subsets were measured in adults from the Multi-Ethnic Study of Atherosclerosis (MESA) and Cardiovascular Health Study (CHS). Cox proportional hazard models adjusted for demographics, HF risk factors, and cytomegalovirus serostatus were used to evaluate the association of the immune cell subsets with incident HF. The average age of the MESA cohort at the time of immune cell measurements was 63.0 ± 10.4 years with 51% women, and in the CHS cohort, it was 79.6 ± 4.4 years with 62% women. In the meta-analysis of CHS and MESA, a higher proportion of CD4+ T helper (Th) 1 cells (per one standard deviation) was associated with a lower risk of incident HF [hazard ratio (HR) 0.91, (95% CI 0.83-0.99), P = 0.03]. Specifically, higher proportion of CD4+ Th1 cells was significantly associated with a lower risk of HFrEF [HR 0.73, (95% CI 0.62-0.85), <0.001] after correction for multiple testing. No association was observed with HFpEF. No other cell subsets were associated with incident HF. CONCLUSIONS: We observed that higher proportions of CD4+ Th1 cells were associated with a lower risk of incident HFrEF in two distinct population-based cohorts, with similar effect sizes in both cohorts demonstrating replicability. Although unexpected, the consistency of this finding across cohorts merits further investigation.

An association test of the spatial distribution of rare missense variants within protein structures identifies Alzheimer's disease-related patterns - Jin, B.; Capra, J. A.; Benchek, P.; Wheeler, N.; Naj, A. C.; Hamilton-Nelson, K. L.; Farrell, J. J.; Leung, Y. Y.; Kunkle, B.; Vadarajan, B.; Schellenberg, G. D.; Mayeux, R.; et al. (Genome Res, 2022)
is a novel AD risk gene that has a cluster of variants primarily shared by case subjects around the Sec6 domain. This cluster is also validated in an independent replication data set and a validation data set with a larger sample size.

The Associations of Individual and Subclasses of Non-Esterified Fatty Acids with Disability, and Mobility Limitation in Older Adults: the Cardiovascular Health Study. - Ahiawodzi, Peter; Bůzková, Petra; Lichtenstein, Alice H; Matthan, Nirupa R; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne B; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (J Gerontol A Biol Sci Med Sci, 2022)
BACKGROUND: We sought to determine the associations between individual non-esterified fatty acids (NEFAs) and disability and mobility limitation. METHODS: We studied 1734 participants in the Cardiovascular Health Study (CHS), an ongoing population-based cohort study of community-living older American adults. We measured 35 individual NEFA species in fasting serum samples obtained at the 1996-1997 clinic visit. Using yearly assessments of activities of daily living and self-reported mobility, we identified participants with incident disability or mobility limitation during 15 years of follow-up. Cox proportional hazards regression models were used to determine the associations between per-SD increment in the individual NEFAs and incident disability and mobility limitations with adjustment for potential confounding factors. RESULTS: Higher concentrations of total and a broad range of individual NEFA species were associated with risk of disability and mobility limitation [disability: HR per SD of total NEFA (SD=174.70) =1.11, 95%CI=1.04-1.18, p=0.001; mobility limitation: HR per SD of total NEFA=1.09, 95%CI=1.02-1.16, p=0.01). Among individual saturated NEFAs (SFAs), myristic (14:0) and palmitic (16:0) acids were significantly associated with higher risk of both disability and mobility limitations, but longer-chain FAs were not. Most individual monounsaturated (MUFA), n-6 polyunsaturated fatty acids (PUFAs), and trans FAs were positively significantly associated with higher risks of both disability and mobility limitation. In contrast, most n-3 PUFA species were not associated with disability or mobility limitation. CONCLUSIONS: Higher risks of disability and mobility limitation were observed for pro-inflammatory intermediate-chain SFAs, MUFAs, n-6 PUFAs, and trans FAs. Our findings indicated no significant association for anti-inflammatory n-3 PUFAs.

Associations of modifiable behavioral risk factor combinations at 65-74 years old with cognitive healthspan over 20 years. - Smagula, Stephen F; Biggs, Mary L; Jacob, Mini E; Rawlings, Andreea M; Odden, Michelle C; Arnold, Alice; Newman, Anne B; Buysse, Daniel J (Psychosom Med, 2022)
OBJECTIVE: Behavioral risk factors for dementia tend to co-occur and inter-relate, especially poor diet, physical inactivity, sleep disturbances, and depression. Having multiple of these modifiable behavioral risk factors (MBRFs) may predict a particularly shortened cognitive healthspan, and therefore, may signal high-risk status/high intervention need. METHODS: This secondary analyses of data from the Cardiovascular Health Study included 3149 participants aged 65-74 years (mean age = 69.5, standard deviation (SD) = 2.5; 59.6% female). MBRF exposures were self-reports regarding: (1) diet, (2) activity, (3) sleep, and (4) depression symptoms. We primarily analyzed MBRF counts. Over up to 26 years of follow-up, we assessed the: (1) number of remaining cognitively healthy life years (CHLYs); and (2) percentage of remaining life years (LYs) that were CHLYs (%CHLY). We estimated CHLYs as time before a dementia diagnosis, cognitive screener scores indicating impairment, proxy port indicating significant cognitive decline, or dementia medication use. RESULTS: Participants averaged a remaining 16 LYs (SD = 7), 12.2 CHLYs (SD = 6.6), and 78.1% of LYs being CHLYs (SD = 25.6). Compared with having no MBRFs, having one was associated with ~1 less LY and CHLY, but not a relatively lower %CHLY. In contrast, having 3+ MBRFs was associated with about 2-3 fewer LYs and CHLYs as well as about 6% lower %CHLY (95% confidence interval: -9.0, -2.5 %CHLYs), p = 0.001). CONCLUSIONS: MBRF-related reductions in the cognitive healthspan are most apparent when people have multiple MBRFs. Future research is needed to determine if/how behavioral risks converge mechanistically, and if dementia prevention efficacy improves when targeting MBRF combinations.

Body Composition and Incident Heart Failure in Older Adults: Results From 2 Prospective Cohorts. - Zhang, Lili; Bartz, Traci M; Santanasto, Adam; Djoussé, Luc; Mukamal, Kenneth J; Forman, Daniel E; Hirsch, Calvin H; Newman, Anne B; Gottdiener, John S; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Aging is associated with central fat redistribution and skeletal muscle decline, yet the relationships of tissue compartments with heart failure (HF) remain incompletely characterized. We assessed the contribution of body composition to incident HF in elders. Methods and Results Participants from 2 older cohorts who completed dual-energy X-ray absorptiometry (DEXA) and, in one cohort, computed tomography were included. We evaluated associations with incident HF for DEXA principal components (PCs) and total lean, appendicular lean, total fat and trunk fat mass; and for computed tomography measures of abdominal visceral and subcutaneous fat, thigh muscle, intermuscular fat area and thigh muscle density. DEXA analysis included 3621, and computed tomography analysis 2332 participants. During median follow-up of 11.8 years, 927 participants developed HF. DEXA principal components showed no relationship with HF. After adjustment for height, weight, and cardiovascular risk factors, total lean mass was near significantly associated with higher HF (hazard ratio [HR], 1.25 per SD [1.00-1.56]), whereas total fat mass and thigh muscle density were significantly related to lower HF (HR, 0.82 [0.68-0.99] and HR, 0.87 [0.78-0.97], respectively). Patterns were similar for HF subtypes. The relationships with HF for total lean and fat mass were attenuated after adjusting for intercurrent atrial fibrillation or excluding high natriuretic peptide levels. Conclusions Total lean mass was positively associated, while total fat mass and thigh muscle density were inversely associated, with incident HF. These findings highlight the limitations of DEXA for assessment of HF risk in elders and support the preeminence of computed tomography-measured skeletal muscle quality over mass as a determinant of HF incidence.
Keywords: Absorptiometry, Photon; Aged; Aging; Body Composition; Body Mass Index; Heart Failure; Humans; Muscle, Skeletal; Prospective Studies

Circulating Androgen Concentrations and Risk of Incident Heart Failure in Older Men: The Cardiovascular Health Study. - Njoroge, Joyce N; Tressel, William; Biggs, Mary L; Matsumoto, Alvin M; Smith, Nicholas L; Rosenberg, Emily; Hirsch, Calvin H; Gottdiener, John S; Mukamal, Kenneth J; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Circulating androgen concentrations in men decline with age and have been linked to diabetes and atherosclerotic cardiovascular disease (ASCVD). A similar relationship has been reported for low total testosterone and incident heart failure (HF) but remains unstudied for free testosterone or the more potent androgen dihydrotestosterone (DHT). We hypothesized that total/free testosterone are inversely related, sex hormone-binding globulin is positively related, and total/free DHT bear a U-shaped relationship with incident HF. Methods and Results In a sample of men from the CHS (Cardiovascular Health Study) without atherosclerotic cardiovascular disease or HF, serum testosterone and DHT concentrations were measured by liquid chromatography-tandem mass spectrometry, and sex hormone-binding globulin by immunoassay. Free testosterone or DHT was calculated from total testosterone or total DHT, sex hormone-binding globulin, and albumin. We used Cox regression to estimate relative risks of HF after adjustment for potential confounders. In 1061 men (aged 76±5 years) followed for a median of 9.6 years, there were 368 HF events. After adjustment, lower calculated free testosterone was significantly associated with higher risk of HF (hazard ratio [HR], 1.14 [95% CI, 1.01-1.28]). Risk estimates for total testosterone (HR, 1.12 [95% CI, 0.99-1.26]), total DHT (HR, 1.10 [95% CI, 0.97-1.24]), calculated free dihydrotestosterone (HR, 1.09 [95% CI, 0.97-1.23]), and sex hormone-binding globulin (HR, 1.07 [95% CI, 0.95-1.21]) were directionally similar but not statistically significant. Conclusions Calculated free testosterone was inversely associated with incident HF, suggesting a contribution of testosterone deficiency to HF incidence among older men. Additional research is necessary to determine whether testosterone replacement therapy might be an effective strategy to lower HF risk in older men.
Keywords: Aged; Androgens; Cardiovascular Diseases; Dihydrotestosterone; Estradiol; Heart Failure; Humans; Male; Sex Hormone-Binding Globulin; Testosterone

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

Clonal Hematopoiesis of Indeterminate Potential and Kidney Function Decline in the General Population. - Kestenbaum, Bryan; Bick, Alexander G; Vlasschaert, Caitlyn; Rauh, Michael J; Lanktree, Matthew B; Franceschini, Nora; Shoemaker, Moore B; Harris, Raymond C; Psaty, Bruce M; Köttgen, Anna; Natarajan, Pradeep; Robinson-Cohen, Cassianne (Am J Kidney Dis, 2022)
RATIONALE & OBJECTIVE: Clonal hematopoiesis of indeterminate potential (CHIP), defined by the age-related ontogenesis of expanded leukemogenic variants indicative of a genetically distinct clonal leukocyte population, is associated with risk of hematologic malignancy and cardiovascular disease. In experimental models, recapitulation of CHIP promotes kidney interstitial fibrosis with direct tissue infiltration of donor macrophages. We tested the hypothesis that CHIP is associated with kidney function decline in the general population. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 12,004 individuals from 3 community-based cohorts in the TOPMed Consortium. EXPOSURE: CHIP status from whole-genome sequences obtained from DNA extracted from peripheral blood. OUTCOME: Risk of 30% decline in estimated glomerular filtration rate (eGFR) and percent eGFR decline per year during the follow-up period. ANALYTICAL APPROACH: Cox proportional hazards models for 30% eGFR decline end point and generalized estimating equations for annualized relative change in eGFR with meta-analysis. Study-specific estimates were combined using fixed-effect meta-analysis. RESULTS: The median baseline eGFR was 84mL/min/1.73m. The prevalence of CHIP was 6.6%, 9.0%, and 12.2% in persons aged 50-60, 60-70, and>70 years, respectively. Over a median follow-up period of 8 years, for the 30% eGFR outcome 205 events occurred among 1,002 CHIP carriers (2.1 events per 100 person-years) and 2,041 events in persons without CHIP (1.7 events per 100 person-years). In meta-analysis, CHIP was associated with greater risk of a 30% eGFR decline (17% [95% CI, 1%-36%] higher; P=0.04). Differences were not observed between those with baseline eGFR above or below 60mL/min/1.73m, of age above or below 60 years, or with or without diabetes. LIMITATIONS: Small number of participants with moderate-to-advanced kidney disease and restricted set of CHIP driver variants. CONCLUSIONS: We report an association between CHIP and eGFR decline in 3 general population cohorts without known kidney disease. Further studies are needed to investigate this novel condition and its potential impact among individuals with overt kidney disease.

{Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease - Uddin, M. D. M.; Nguyen, N. Q. H.; Yu, B.; Brody, J. A.; Pampana, A.; Nakao, T.; Fornage, M.; Bressler, J.; Sotoodehnia, N.; Weinstock, J. S.; Honigberg, M. C.; Nachun, D.; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Diabetes Status Modifies the Association Between Different Measures of Obesity and Heart Failure Risk Among Older Adults: A Pooled Analysis of Community-Based NHLBI Cohorts. - Patel, Kershaw V; Segar, Matthew W; Lavie, Carl J; Kondamudi, Nitin; Neeland, Ian J; Almandoz, Jaime P; Martin, Corby K; Carbone, Salvatore; Butler, Javed; Powell-Wiley, Tiffany M; Pandey, Ambarish (Circulation, 2022)
BACKGROUND: Obesity and diabetes are associated with a higher risk of heart failure (HF). The interrelationships between different measures of adiposity-overall obesity, central obesity, fat mass (FM)-and diabetes status for HF risk are not well-established. METHODS: Participant-level data from the ARIC study (Atherosclerosis Risk in Communities; visit 5) and the CHS (Cardiovascular Health Study; visit 1) cohorts were obtained from the National Heart, Lung, and Blood Institute Biologic Specimen and Data Repository Information Coordinating Center, harmonized, and pooled for the present analysis, excluding individuals with prevalent HF. FM was estimated in all participants using established anthropometric prediction equations additionally validated using the bioelectrical impedance-based FM in the ARIC subgroup. Incident HF events on follow-up were captured across both cohorts using similar adjudication methods. Multivariable-adjusted Fine-Gray models were created to evaluate the associations of body mass index (BMI), waist circumference (WC), and FM with risk of HF in the overall cohort as well as among those with versus without diabetes at baseline. The population attributable risk of overall obesity (BMI≥30 kg/m), abdominal obesity (WC>88 and 102 cm in women and men, respectively), and high FM (above sex-specific median) for incident HF was evaluated among participants with and without diabetes. RESULTS: The study included 10 387 participants (52.9% ARIC; 25.1% diabetes; median age, 74 years). The correlation between predicted and bioelectrical impedance-based FM was high (=0.90; n=5038). During a 5-year follow-up, 447 participants developed HF (4.3%). Higher levels of each adiposity measure were significantly associated with higher HF risk (hazard ratio [95% CI] per 1 SD higher BMI=1.15 [1.05, 1.27], WC=1.22 [1.10, 1.36]; FM=1.13 [1.02, 1.25]). A significant interaction was noted between diabetes status and measures of BMI ( interaction=0.04) and WC ( interaction=0.004) for the risk of HF. In stratified analysis, higher measures of each adiposity parameter were significantly associated with higher HF risk in individuals with diabetes (hazard ratio [95% CI] per 1 SD higher BMI=1.29 [1.14-1.47]; WC=1.48 [1.29-1.70]; FM=1.25 [1.09-1.43]) but not those without diabetes, including participants with prediabetes and euglycemia. The population attributable risk percentage of overall obesity, abdominal obesity, and high FM for incident HF was higher among participants with diabetes (12.8%, 29.9%, and 13.7%, respectively) versus those without diabetes (≤1% for each). CONCLUSIONS: Higher BMI, WC, and FM are strongly associated with greater risk of HF among older adults, particularly among those with prevalent diabetes.
Keywords: Aged; Cohort Studies; Diabetes Mellitus; Female; Heart Failure; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Obesity; Risk Factors; United States

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Endophenotype effect sizes support variant pathogenicity in monogenic disease susceptibility genes. - Halford, Jennifer L; Morrill, Valerie N; Choi, Seung Hoan; Jurgens, Sean J; Melloni, Giorgio; Marston, Nicholas A; Weng, Lu-Chen; Nauffal, Victor; Hall, Amelia W; Gunn, Sophia; Austin-Tse, Christina A; Pirruccello, James P; et al. (Nat Commun, 2022)
Accurate and efficient classification of variant pathogenicity is critical for research and clinical care. Using data from three large studies, we demonstrate that population-based associations between rare variants and quantitative endophenotypes for three monogenic diseases (low-density-lipoprotein cholesterol for familial hypercholesterolemia, electrocardiographic QTc interval for long QT syndrome, and glycosylated hemoglobin for maturity-onset diabetes of the young) provide evidence for variant pathogenicity. Effect sizes are associated with pathogenic ClinVar assertions (P < 0.001 for each trait) and discriminate pathogenic from non-pathogenic variants (area under the curve 0.82-0.84 across endophenotypes). An effect size threshold of ≥ 0.5 times the endophenotype standard deviation nominates up to 35% of rare variants of uncertain significance or not in ClinVar in disease susceptibility genes with pathogenic potential. We propose that variant associations with quantitative endophenotypes for monogenic diseases can provide evidence supporting pathogenicity.
Keywords: Disease Susceptibility; Endophenotypes; Humans; Long QT Syndrome; Virulence

eSCAN: scan regulatory regions for aggregate association testing using whole-genome sequencing data. - Yang, Yingxi; Sun, Quan; Huang, Le; Broome, Jai G; Correa, Adolfo; Reiner, Alexander; Raffield, Laura M; Yang, Yuchen; Li, Yun (Brief Bioinform, 2022)
Multiple statistical methods for aggregate association testing have been developed for whole-genome sequencing (WGS) data. Many aggregate variants in a given genomic window and ignore existing knowledge to define test regions, resulting in many identified regions not clearly linked to genes, and thus, limiting biological understanding. Functional information from new technologies (such as Hi-C and its derivatives), which can help link enhancers to their effector genes, can be leveraged to predefine variant sets for aggregate testing in WGS data. Here, we propose the eSCAN (scan the enhancers) method for genome-wide assessment of enhancer regions in sequencing studies, combining the advantages of dynamic window selection in SCANG (SCAN the Genome), a previously developed method, with the advantages of incorporating putative regulatory regions from annotation. eSCAN, by searching in putative enhancers, increases statistical power and aids mechanistic interpretation, as demonstrated by extensive simulation studies. We also apply eSCAN for blood cell traits using NHLBI Trans-Omics for Precision Medicine WGS data. Results from real data analysis show that eSCAN is able to capture more significant signals, and these signals are of shorter length (indicating higher resolution fine-mapping capability) and drive association of larger regions detected by other methods.
Keywords: Genome; Genome-Wide Association Study; Genomics; Regulatory Sequences, Nucleic Acid; Whole Genome Sequencing

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

{Gene Set Enrichment Analsyes Identify Pathways Involved in Genetic Risk for Diabetic Retinopathy - Sobrin, L.; Susarla, G.; Stanwyck, L.; Rouhana, J. M.; Li, A.; Pollack, S.; Igo, R. P.; Jensen, R. A.; Li, X.; Ng, M. C. Y.; Smith, A. V.; Kuo, J. Z.; et al. (Am J Ophthalmol, 2022)
{To identify functionally related genes associated with diabetic retinopathy (DR) risk using gene set enrichment analyses applied to genome-wide association study meta-analyses.\ .05.\ .05) in the other method. These pathways were regulation of the lipid catabolic process (2-fold enrichment

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases - Li, Y.; Cheng, Y.; Consolato, F.; Schiano, G.; Chong, M. R.; Pietzner, M.; Nguyen, N. Q. H.; Scherer, N.; Biggs, M. L.; Kleber, M. E.; Haug, S.; Göçmen, B.; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Integrative analysis of clinical and epigenetic biomarkers of mortality. - Huan, Tianxiao; Nguyen, Steve; Colicino, Elena; Ochoa-Rosales, Carolina; Hill, W David; Brody, Jennifer A; Soerensen, Mette; Zhang, Yan; Baldassari, Antoine; Elhadad, Mohamed Ahmed; Toshiko, Tanaka; Zheng, Yinan; et al. (Aging Cell, 2022)
DNA methylation (DNAm) has been reported to be associated with many diseases and with mortality. We hypothesized that the integration of DNAm with clinical risk factors would improve mortality prediction. We performed an epigenome-wide association study of whole blood DNAm in relation to mortality in 15 cohorts (n = 15,013). During a mean follow-up of 10 years, there were 4314 deaths from all causes including 1235 cardiovascular disease (CVD) deaths and 868 cancer deaths. Ancestry-stratified meta-analysis of all-cause mortality identified 163 CpGs in European ancestry (EA) and 17 in African ancestry (AA) participants at p < 1 × 10 , of which 41 (EA) and 16 (AA) were also associated with CVD death, and 15 (EA) and 9 (AA) with cancer death. We built DNAm-based prediction models for all-cause mortality that predicted mortality risk after adjusting for clinical risk factors. The mortality prediction model trained by integrating DNAm with clinical risk factors showed an improvement in prediction of cancer death with 5% increase in the C-index in a replication cohort, compared with the model including clinical risk factors alone. Mendelian randomization identified 15 putatively causal CpGs in relation to longevity, CVD, or cancer risk. For example, cg06885782 (in KCNQ4) was positively associated with risk for prostate cancer (Beta = 1.2, P  = 4.1 × 10 ) and negatively associated with longevity (Beta = -1.9, P  = 0.02). Pathway analysis revealed that genes associated with mortality-related CpGs are enriched for immune- and cancer-related pathways. We identified replicable DNAm signatures of mortality and demonstrated the potential utility of CpGs as informative biomarkers for prediction of mortality risk.
Keywords: Biomarkers; Cardiovascular Diseases; DNA Methylation; Epigenesis, Genetic; Epigenomics; Humans; Male; Neoplasms

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Longitudinal Associations of Plasma TMAO and Related Metabolites with Cognitive Impairment and Dementia in Older Adults: The Cardiovascular Health Study. - de Oliveira Otto, Marcia C; Li, Xinmin S; Wang, Zeneng; Siscovick, David; Newman, Anne B; Lai, Heidi Tsz Mung; Nemet, Ina; Lee, Yujin; Wang, Meng; Fretts, Amanda; Lemaitre, Rozenn N; Tang, W H Wilson; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Animal studies suggest that gut microbiome metabolites such as trimethylamine N-oxide (TMAO) may influence cognitive function and dementia risk. However potential health effects of TMAO and related metabolites remain unclear. OBJECTIVE: We examined prospective associations of TMAO, γ-butyrobetaine, crotonobetaine, carnitine, choline, and betaine with risk of cognitive impairment and dementia among older adults aged 65 years and older in the Cardiovascular Health Study (CHS). METHODS: TMAO and metabolites were measured in stored plasma specimens collected at baseline. Incident cognitive impairment was assessed using the 100-point Modified Mini-Mental State Examination administered serially up to 7 times. Clinical dementia was identified using neuropsychological tests adjudicated by CHS Cognition Study investigators, and by ICD-9 codes from linked Medicare data. Associations of each metabolite with cognitive outcomes were assessed using Cox proportional hazards models. RESULTS: Over a median of 13 years of follow-up, 529 cases of cognitive impairment, and 522 of dementia were identified. After multivariable adjustment for relevant risk factors, no associations were seen with TMAO, carnitine, choline, or betaine. In contrast, higher crotonobetaine was associated with 20-32% higher risk of cognitive impairment and dementia per interquintile range (IQR), while γ-butyrobetaine was associated with ∼25% lower risk of the same cognitive outcomes per IQR.∥Conclusion:These findings suggest that γ-butyrobetaine, crotonobetaine, two gut microbe and host metabolites, are associated with risk of cognitive impairment and dementia. Our results indicate a need for mechanistic studies evaluating potential effects of these metabolites, and their interconversion on brain health, especially later in life.

Monogenic and Polygenic Contributions to QTc Prolongation in the Population. - Nauffal, Victor; Morrill, Valerie N; Jurgens, Sean J; Choi, Seung Hoan; Hall, Amelia W; Weng, Lu-Chen; Halford, Jennifer L; Austin-Tse, Christina; Haggerty, Christopher M; Harris, Stephanie L; Wong, Eugene K; Alonso, Alvaro; et al. (Circulation, 2022)
Rare sequence variation in genes underlying cardiac repolarization and common polygenic variation influence QT interval duration. However, current clinical genetic testing of individuals with unexplained QT prolongation is restricted to examination of monogenic rare variants. The recent emergence of large-scale biorepositories with sequence data enables examination of the joint contribution of rare and common variation to the QT interval in the population. We performed a genome wide association study (GWAS) of the QTc in 84,630 United Kingdom Biobank (UKB) participants and created a polygenic risk score (PRS). Among 26,976 participants with whole genome sequencing and electrocardiogram data in the Trans-Omics for Precision Medicine (TOPMed) program, we identified 160 carriers of putative pathogenic rare variants in 10 genes known to be associated with the QT interval. We examined QTc associations with the PRS and with rare variants in TOPMed. Fifty-four independent loci were identified by GWAS in the UKB. Twenty-one loci were novel, of which 12 were replicated in TOPMed. The PRS comprising 1,110,494 common variants was significantly associated with the QTc in TOPMed (ΔQTc/ = 1.4 ms, 95% CI 1.3 -1.5; p-value=1.1×10). Carriers of putative pathogenic rare variants had longer QTc than non-carriers (ΔQTc=10.9 ms [7.4-14.4]). 23.7% of individuals with QTc>480 ms carried either a monogenic rare variant or had a PRS in the top decile (3.4% monogenic, 21% top decile of PRS). QTc duration in the population is influenced by both rare variants in genes underlying cardiac repolarization and polygenic risk, with a sizeable contribution from polygenic risk. Comprehensive assessment of the genetic determinants of QTc prolongation includes incorporation of both polygenic and monogenic risk.

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

Multi-Scalar Data Integration Links Glomerular Angiopoietin-Tie Signaling Pathway Activation With Progression of Diabetic Kidney Disease. - Liu, Jiahao; Nair, Viji; Zhao, Yi-Yang; Chang, Dong-Yuan; Limonte, Christine; Bansal, Nisha; Fermin, Damian; Eichinger, Felix; Tanner, Emily C; Bellovich, Keith A; Steigerwalt, Susan; Bhat, Zeenat; et al. (Diabetes, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease (ESKD). Prognostic biomarkers reflective of underlying molecular mechanisms are critically needed for effective management of DKD. A three-marker panel was derived from a proteomics analysis of plasma samples by an unbiased machine learning approach from participants (N = 58) in the Clinical Phenotyping and Resource Biobank study. In combination with standard clinical parameters, this panel improved prediction of the composite outcome of ESKD or a 40% decline in glomerular filtration rate. The panel was validated in an independent group (N = 68), who also had kidney transcriptomic profiles. One marker, plasma angiopoietin 2 (ANGPT2), was significantly associated with outcomes in cohorts from the Cardiovascular Health Study (N = 3,183) and the Chinese Cohort Study of Chronic Kidney Disease (N = 210). Glomerular transcriptional angiopoietin/Tie (ANG-TIE) pathway scores, derived from the expression of 154 ANG-TIE signaling mediators, correlated positively with plasma ANGPT2 levels and kidney outcomes. Higher receptor expression in glomeruli and higher ANG-TIE pathway scores in endothelial cells corroborated potential functional effects in the kidney from elevated plasma ANGPT2 levels. Our work suggests that ANGPT2 is a promising prognostic endothelial biomarker with likely functional impact on glomerular pathogenesis in DKD.
Keywords: Angiopoietin-1; Angiopoietin-2; Angiopoietins; Biomarkers; Cohort Studies; Diabetes Mellitus; Diabetic Nephropathies; Disease Progression; Endothelial Cells; Humans; Kidney Failure, Chronic; Receptor, TIE-2; Signal Transduction

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Non-linear machine learning models incorporating SNPs and PRS improve polygenic prediction in diverse human populations. - Elgart, Michael; Lyons, Genevieve; Romero-Brufau, Santiago; Kurniansyah, Nuzulul; Brody, Jennifer A; Guo, Xiuqing; Lin, Henry J; Raffield, Laura; Gao, Yan; Chen, Han; de Vries, Paul; Lloyd-Jones, Donald M; et al. (Commun Biol, 2022)
Polygenic risk scores (PRS) are commonly used to quantify the inherited susceptibility for a trait, yet they fail to account for non-linear and interaction effects between single nucleotide polymorphisms (SNPs). We address this via a machine learning approach, validated in nine complex phenotypes in a multi-ancestry population. We use an ensemble method of SNP selection followed by gradient boosted trees (XGBoost) to allow for non-linearities and interaction effects. We compare our results to the standard, linear PRS model developed using PRSice, LDpred2, and lassosum2. Combining a PRS as a feature in an XGBoost model results in a relative increase in the percentage variance explained compared to the standard linear PRS model by 22% for height, 27% for HDL cholesterol, 43% for body mass index, 50% for sleep duration, 58% for systolic blood pressure, 64% for total cholesterol, 66% for triglycerides, 77% for LDL cholesterol, and 100% for diastolic blood pressure. Multi-ancestry trained models perform similarly to specific racial/ethnic group trained models and are consistently superior to the standard linear PRS models. This work demonstrates an effective method to account for non-linearities and interaction effects in genetics-based prediction models.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Machine Learning; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Plasma proteomic signature of decline in gait speed and grip strength. - Liu, Xiaojuan; Pan, Stephanie; Xanthakis, Vanessa; Vasan, Ramachandran S; Psaty, Bruce M; Austin, Thomas R; Newman, Anne B; Sanders, Jason L; Wu, Chenkai; Tracy, Russell P; Gerszten, Robert E; Odden, Michelle C (Aging Cell, 2022)
The biological mechanisms underlying decline in physical function with age remain unclear. We examined the plasma proteomic profile associated with longitudinal changes in physical function measured by gait speed and grip strength in community-dwelling adults. We applied an aptamer-based platform to assay 1154 plasma proteins on 2854 participants (60% women, aged 76 years) in the Cardiovascular Health Study (CHS) in 1992-1993 and 1130 participants (55% women, aged 54 years) in the Framingham Offspring Study (FOS) in 1991-1995. Gait speed and grip strength were measured annually for 7 years in CHS and at cycles 7 (1998-2001) and 8 (2005-2008) in FOS. The associations of individual protein levels (log-transformed and standardized) with longitudinal changes in gait speed and grip strength in two populations were examined separately by linear mixed-effects models. Meta-analyses were implemented using random-effects models and corrected for multiple testing. We found that plasma levels of 14 and 18 proteins were associated with changes in gait speed and grip strength, respectively (corrected p < 0.05). The proteins most strongly associated with gait speed decline were GDF-15 (Meta-analytic p = 1.58 × 10 ), pleiotrophin (1.23 × 10 ), and TIMP-1 (5.97 × 10 ). For grip strength decline, the strongest associations were for carbonic anhydrase III (1.09 × 10 ), CDON (2.38 × 10 ), and SMOC1 (7.47 × 10 ). Several statistically significant proteins are involved in the inflammatory responses or antagonism of activin by follistatin pathway. These novel proteomic biomarkers and pathways should be further explored as future mechanisms and targets for age-related functional decline.
Keywords: Adult; Female; Gait; Hand Strength; Humans; Independent Living; Male; Proteomics; Walking Speed

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

Pooled Cohort Probability Score for Subclinical Airflow Obstruction. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Jaeger, Byron C; Cassano, Patricia A; Chaves, Paulo H; Couper, David; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Lloyd-Jones, Donald; Newman, Anne B; et al. (Ann Am Thorac Soc, 2022)
Early detection of chronic obstructive pulmonary disease (COPD) is a public health priority. Airflow obstruction is the single most important risk factor for adverse COPD outcomes, but spirometry is not routinely recommended for screening. To describe the burden of subclinical airflow obstruction (SAO) and to develop a probability score for SAO to inform potential detection and prevention programs. Lung function and clinical data were harmonized and pooled across nine U.S. general population cohorts. Adults with respiratory symptoms, inhaler use, or prior diagnosis of COPD or asthma were excluded. A probability score for prevalent SAO (forced expiratory volume in 1 second/forced vital capacity < 0.70) was developed via hierarchical group-lasso regularization from clinical variables in strata of sex and smoking status, and its discriminative accuracy for SAO was assessed in the pooled cohort as well as in an external validation cohort (NHANES [National Health and Nutrition Examination Survey] 2011-2012). Incident hospitalizations and deaths due to COPD (respiratory events) were defined by adjudication or administrative criteria in four of nine cohorts. Of 33,546 participants (mean age 52 yr, 54% female, 44% non-Hispanic White), 4,424 (13.2%) had prevalent SAO. The incidence of respiratory events ( = 14,024) was threefold higher in participants with SAO versus those without (152 vs. 39 events/10,000 person-years). The probability score, which was based on six commonly available variables (age, sex, race and/or ethnicity, body mass index, smoking status, and smoking pack-years) was well calibrated and showed excellent discrimination in both the testing sample (C-statistic, 0.81; 95% confidence interval [CI], 0.80-0.82) and in NHANES (C-statistic, 0.83; 95% CI, 0.80-0.86). Among participants with predicted probabilities ⩾ 15%, 3.2 would need to undergo spirometry to detect one case of SAO. Adults with SAO demonstrate excess respiratory hospitalization and mortality. A probability score for SAO using commonly available clinical risk factors may be suitable for targeting screening and primary prevention strategies.
Keywords: Adult; Female; Forced Expiratory Volume; Humans; Lung; Male; Middle Aged; Nutrition Surveys; Pulmonary Disease, Chronic Obstructive; Risk Factors; Spirometry; Vital Capacity

{A population-based meta-analysis of circulating GFAP for cognition and dementia risk - Gonzales, M. M.; Wiedner, C.; Wang, C. P.; Liu, Q.; Bis, J. C.; Li, Z.; Himali, J. J.; Ghosh, S.; Thomas, E. A.; Parent, D. M.; Kautz, T. F.; Pase, M. P.; et al. (Ann Clin Transl Neurol, 2022)
Expression of glial fibrillary acidic protein (GFAP), a marker of reactive astrocytosis, colocalizes with neuropathology in the brain. Blood levels of GFAP have been associated with cognitive decline and dementia status. However, further examinations at a population-based level are necessary to broaden generalizability to community settings.\ Circulating GFAP levels were assayed using a Simoa HD-1 analyzer in 4338 adults without prevalent dementia from four longitudinal community-based cohort studies. The associations between GFAP levels with general cognition, total brain volume, and hippocampal volume were evaluated with separate linear regression models in each cohort with adjustment for age, sex, education, race, diabetes, systolic blood pressure, antihypertensive medication, body mass index, apolipoprotein E ε4 status, site, and time between GFAP blood draw and the outcome. Associations with incident all-cause and Alzheimer's disease dementia were evaluated with adjusted Cox proportional hazard models. Meta-analysis was performed on the estimates derived from each cohort using random-effects models.\ 0.05). However, each standard deviation unit increase in log-transformed GFAP levels was significantly associated with a 2.5-fold higher risk of incident all-cause dementia (Hazard Ratio [HR]: 2.47 (95% CI: 1.52-4.01)) and Alzheimer's disease dementia (HR: 2.54 [95% CI: 1.42-4.53]) over up to 15-years of follow-up.\ Results support the potential role of circulating GFAP levels for aiding dementia risk prediction and improving clinical trial stratification in community settings.

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

{Replication study of AD-associated rare variants - Neupane, A.; Lenny, B.; Budde, J. P.; Wang, F.; Norton, J.; Morris, J. C.; Cruchaga, C.; Fernández, M. V. (Alzheimers Dement, 2022)

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Sex- and race-specific associations of bone mineral density with incident heart failure and its subtypes in older adults. - Gao, Hans; Patel, Sheena; Fohtung, Raymond B; Cawthon, Peggy M; Newman, Anne B; Cauley, Jane A; Carbone, Laura; Chaves, Paulo H M; Stein, Phyllis K; Civitelli, Roberto; Kizer, Jorge R (J Am Geriatr Soc, 2022)
BACKGROUND: Previous studies have suggested an association between bone mineral density (BMD) and heart failure (HF) risk that may be race-dependent. METHODS: We evaluated the relationship between BMD and incident HF in a cohort of older adults, the Health, Aging, and Body Composition (Health ABC) study (n = 2835), and next performed a pooled analysis involving a second older cohort, the Cardiovascular Health Study (n = 1268). Hip BMD was measured by dual-energy X-ray absorptiometry in both cohorts and spine BMD by computed tomography in a subset from Health ABC. RESULTS: In Health ABC, lower BMD at the total hip was associated with higher incident HF in Black women after multivariable adjustment. Similar associations were found for BMD at the femoral neck and spine. In both cohorts, pooled analysis again revealed an association between lower total hip BMD and increased risk of HF in Black women (HR = 1.41 per 0.1-g/cm decrement [95% CI = 1.23-1.62]), and showed the same to be true for White men (HR = 1.12 [1.03-1.21]). There was a decreased risk of HF in Black men (HR 0.80 [0.70-0.91]), but no relationship in White women. The associations were numerically stronger with HFpEF for Black women and White men, and with HFrEF for Black men. Findings were similar for femoral neck BMD. Sensitivity analyses delaying HF follow-up by 2 years eliminated the association in Black men. CONCLUSIONS: Lower BMD was associated with higher risk of HF and especially HFpEF in older Black women and White men, highlighting the need for additional investigation into underlying mechanisms.

Sleep problems and risk of cancer incidence and mortality in an older cohort: The Cardiovascular Health Study (CHS). - Sillah, Arthur; Watson, Nathaniel F; Peters, Ulrike; Biggs, Mary L; Nieto, F Javier; Li, Christopher I; Gozal, David; Thornton, Timothy; Barrie, Sonnah; Phipps, Amanda I (Cancer Epidemiol, 2022)
BACKGROUND: Sleep problems (SP) can indicate underlying sleep disorders, such as obstructive sleep apnea, which may adversely impact cancer risk and mortality. METHODS: We assessed the association of baseline and longitudinal sleep apnea and insomnia symptoms with incident cancer (N = 3930) and cancer mortality (N = 4580) in the Cardiovascular Health Study. We used Cox proportional hazards regression to calculate adjusted hazard ratios (HR) and 95% confidence intervals (CI) to evaluate the associations. RESULTS: Overall, 885 incident cancers and 804 cancer deaths were identified over a median follow-up of 12 and 14 years, respectively. Compared to participants who reported no sleep apnea symptoms, the risk of incident cancer was inversely associated [(HR (95%CI)] with snoring [0.84 (0.71, 0.99)]. We noted an elevated prostate cancer incidence for apnea [2.34 (1.32, 4.15)] and snoring [1.69 (1.11, 2.57)]. We also noted an elevated HR for lymphatic or hematopoietic cancers [daytime sleepiness: 1.81 (1.06, 3.08)]. We found an inverse relationship for cancer mortality with respect to snoring [0.73 (0.62, 0.8)] and apnea [(0.69 (0.51, 0.94))]. We noted a significant inverse relationship between difficulty falling asleep and colorectal cancer death [0.32 (0.15, 0.69)] and snoring with lung cancer death [0.56 (0.35, 0.89)]. CONCLUSIONS: The relationship between SP and cancer risk and mortality was heterogeneous. Larger prospective studies addressing more cancer sites, molecular type-specific associations, and better longitudinal SP assessments are needed for improved delineation of SP-cancer risk dyad.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

Trimethylamine N-oxide and hip fracture and bone mineral density in older adults: The cardiovascular health study. - Elam, Rachel E; Bůzková, Petra; Barzilay, Joshua I; Wang, Zeneng; Nemet, Ina; Budoff, Matthew J; Cauley, Jane A; Fink, Howard A; Lee, Yujin; Robbins, John A; Wang, Meng; Hazen, Stanley L; et al. (Bone, 2022)
CONTEXT: Gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) may adversely affect bone by inducing oxidative stress. Whether this translates into increased fracture risk in older adults is uncertain. OBJECTIVE: Determine the associations of plasma TMAO with hip fracture and bone mineral density (BMD) in older adults. DESIGN AND SETTING: Cox hazard models and linear regression stratified by sex examined the associations of TMAO with hip fracture and BMD in the longitudinal cohort of the Cardiovascular Health Study. PARTICIPANTS: 5019 U.S. adults aged ≥65 years. EXPOSURE: Plasma TMAO. MAIN OUTCOME MEASURES: Incident hip fractures; total hip BMD dual x-ray absorptiometry in a subset (n = 1400). RESULTS: Six hundred sixty-six incident hip fractures occurred during up to 26 years of follow-up (67,574 person-years). After multivariable adjustment, TMAO was not significantly associated with hip fracture (women: hazard ratio (HR) [95% confidence interval (CI)] of 1.00[0.92,1.09] per TMAO doubling; men: 1.12[0.95,1.33]). TMAO was also not associated with total hip BMD (women: BMD difference [95% CI] of 0.42 g/cm*100 [-0.34,1.17] per TMAO doubling; men: 0.19[-1.04,1.42]). In exploratory analyses, we found an interaction between body mass index (BMI) and the association of TMAO with hip fracture (P < 0.01). Higher TMAO was significantly associated with risk of hip fracture in adults with overweight or obesity (BMI ≥ 25) (HR [95% CI]:1.17[1.05,1.31]), but not normal or underweight. CONCLUSIONS: Among older US men and women, TMAO was not significantly associated with risk of hip fracture or BMD overall. Exploratory analyses suggested a significant association between higher TMAO and hip fracture when BMI was elevated, which merits further study.
Keywords: Absorptiometry, Photon; Aged; Bone Density; Female; Hip Fractures; Humans; Male; Methylamines; Risk Factors

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Boerwinkle, Eric; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldorsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-Exome Sequencing Study Identifies Four Novel Gene Loci Associated with Diabetic Kidney Disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Metcalf, Ginger; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2022)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease (CKD) and diabetes. Our two-stage whole-exome sequencing study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort (CRIC) and Atherosclerosis Risk in Communities (ARIC) studies (stage-1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine (TOPMed) participants (stage-2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex, and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test (SKAT-O) implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds (95% confidence interval: 33.6, 1105) of DKD compared with non-carriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% confidence interval: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association of a blood-based aging biomarker index with death and chronic disease: Cardiovascular Health Study. - Zhang, Xiao; Sanders, Jason L; Boudreau, Robert M; Arnold, Alice M; Justice, Jamie N; Espeland, Mark A; Kuchel, George A; Barzilai, Nir; Kuller, Lewis H; Lopez, Oscar L; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: A goal of gerontology is to discover phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers that are strongly associated with mortality could be used to define such a phenotype. However, the relation of such an index with multiple chronic conditions warrants further exploration. METHODS: A Biomarker Index (BI) was constructed in the Cardiovascular Health Study (N=3197), with a mean age of 74 years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor-1, interleukin-6, amino-terminal pro-B-type natriuretic peptide, cystatin-C, C-reactive protein, tumor necrosis factor-alpha soluble receptor 1, fasting insulin, and fasting glucose, and was built based on their relationships with mortality. Cox proportional hazards models predicting a composite of death and chronic disease involving cardiovascular disease, dementia, and cancer were calculated with 6 years of follow-up. RESULTS: The hazard ratio (HR, 95% CI) for the composite outcome of death or chronic disease per category of BI was 1.65 (1.52, 1.80) and 1.75 (1.58, 1.94) in women and men, respectively. The HR (95% CI) per 5 years of age was 1.57 (1.48, 1.67) and 1.55 (1.44, 1.67) in women and men, respectively. Moreover, BI could attenuate the effect of age on the composite outcome by 16.7% and 22.0% in women and men, respectively. CONCLUSIONS: BI was significantly and independently associated with a composite outcome of death and chronic disease, and attenuated the effect of age. The BI that is composed of plasma biomarkers may be a practical intermediate phenotype for interventions aiming to modify the course of aging.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer's disease (AD) and AD related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from nine diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5 to 20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs. ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed Mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (Beta=0.04; 95% CI 0.02, 0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the US. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Boerwinkle, Eric; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.

Association of Severe Hypercholesterolemia and Familial Hypercholesterolemia Genotype With Risk of Coronary Heart Disease. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (Circulation, 2023)
Keywords: Coronary Disease; Genotype; Humans; Hypercholesterolemia; Hyperlipoproteinemia Type II

Circulating Growth Differentiation Factors 11 and 8, Their Antagonists Follistatin and Follistatin-like-3, and Risk of Heart Failure in Elders. - Kizer, Jorge R; Patel, Sheena; Ganz, Peter; Newman, Anne B; Bhasin, Shalender; Lee, Se-Jin; Cawthon, Peggy M; LeBrasseur, Nathan; Shah, Sanjiv J; Psaty, Bruce M; Tracy, Russell P; Cummings, Steven R (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Heterochronic parabiosis has identified growth differentiation factor (GDF)-11 as a potential means of cardiac rejuvenation, but findings have been inconsistent. A major barrier has been lack of assay specificity for GDF-11 and its homolog GDF-8. METHODS: We tested the hypothesis that GDF-11 and GDF-8, and their major antagonists follistatin and follistatin-like (FSTL)-3, are associated with incident heart failure (HF) and its subtypes in elders. Based on validation experiments, we used liquid chromatography tandem mass spectrometry to measure total serum GDF-11 and GDF-8, along with follistatin and follistatin-like (FSTL)-3 by immunoassay, in two longitudinal cohorts of older adults. RESULTS: In 2,599 participants (age 75.2±4.3) followed for 10.8±5.6 years, 721 HF events occurred. After adjustment, neither GDF-11 (HR per doubling: 0.93 [0.67, 1.30]) nor GDF-8 (HR: 1.02 per doubling [0.83, 1.27]) was associated with incident HF or its subtypes. Positive associations with HF were detected for follistatin (HR: 1.15 [1.00, 1.32]) and FLST-3 (HR: 1.38 [1.03, 1.85]), and with HF with preserved ejection fraction for FSTL-3 (HR: 1.77 [1.03, 3.02]). (All HRs per doubling of biomarker.) FSTL-3 associations with HF appeared stronger at higher follistatin levels and vice versa, and also for men, Blacks and lower kidney function. CONCLUSIONS: Among older adults, serum follistatin and FSTL-3, but not GDF-11 or GDF-8, were associated with incident HF. These findings do not support the concept that low serum levels of total GDF-11 or GDF-8 contribute to HF late in life, but do implicate transforming growth factor-βsuperfamily pathways as potential therapeutic targets.

Clonal hematopoiesis is associated with protection from Alzheimer's disease. - Bouzid, Hind; Belk, Julia A; Jan, Max; Qi, Yanyan; Sarnowski, Chloe; Wirth, Sara; Ma, Lisa; Chrostek, Matthew R; Ahmad, Herra; Nachun, Daniel; Yao, Winnie; Beiser, Alexa; et al. (Nat Med, 2023)
Clonal hematopoiesis of indeterminate potential (CHIP) is a premalignant expansion of mutated hematopoietic stem cells. As CHIP-associated mutations are known to alter the development and function of myeloid cells, we hypothesized that CHIP may also be associated with the risk of Alzheimer's disease (AD), a disease in which brain-resident myeloid cells are thought to have a major role. To perform association tests between CHIP and AD dementia, we analyzed blood DNA sequencing data from 1,362 individuals with AD and 4,368 individuals without AD. Individuals with CHIP had a lower risk of AD dementia (meta-analysis odds ratio (OR) = 0.64, P = 3.8 × 10), and Mendelian randomization analyses supported a potential causal association. We observed that the same mutations found in blood were also detected in microglia-enriched fraction of the brain in seven of eight CHIP carriers. Single-nucleus chromatin accessibility profiling of brain-derived nuclei in six CHIP carriers revealed that the mutated cells comprised a large proportion of the microglial pool in the samples examined. While additional studies are required to validate the mechanistic findings, these results suggest that CHIP may have a role in attenuating the risk of AD.

Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Determinants of mosaic chromosomal alteration fitness. - Pershad, Yash; Mack, Taralynn; Poisner, Hannah; Jakubek, Yasminka A; Stilp, Adrienne M; Mitchell, Braxton D; Lewis, Joshua P; Boerwinkle, Eric; Loos, Ruth J; Chami, Nathalie; Wang, Zhe; Barnes, Kathleen; et al. (medRxiv, 2023)
Clonal hematopoiesis (CH) is characterized by the acquisition of a somatic mutation in a hematopoietic stem cell that results in a clonal expansion. These driver mutations can be single nucleotide variants in cancer driver genes or larger structural rearrangements called mosaic chromosomal alterations (mCAs). The factors that influence the variations in mCA fitness and ultimately result in different clonal expansion rates are not well-understood. We used the Passenger-Approximated Clonal Expansion Rate (PACER) method to estimate clonal expansion rate for 6,381 individuals in the NHLBI TOPMed cohort with gain, loss, and copy-neutral loss of heterozygosity mCAs. Our estimates of mCA fitness were correlated (R = 0.49) with an alternative approach that estimated fitness of mCAs in the UK Biobank using a theoretical probability distribution. Individuals with lymphoid-associated mCAs had a significantly higher white blood cell count and faster clonal expansion rate. In a cross-sectional analysis, genome-wide association study of estimates of mCA expansion rate identified , , and locus variants as modulators of mCA clonal expansion rate.

Elevated Plasma Levels of Ketone Bodies Are Associated With All-Cause Mortality and Incidence of Heart Failure in Older Adults: The CHS. - Niezen, Sebastian; Connelly, Margery A; Hirsch, Calvin; Kizer, Jorge R; Benitez, Maria E; Minchenberg, Scott; Perez-Matos, Maria Camila; Jiang, Zhenghui Gordon; Mukamal, Kenneth J (J Am Heart Assoc, 2023)
Background Chronic disease, such as heart failure, influences cellular metabolism and shapes circulating metabolites. The relationships between key energy metabolites and chronic diseases in aging are not well understood. This study aims to determine the relationship between main components of energy metabolism with all-cause mortality and incident heart failure. Methods and Results We analyzed the association between plasma metabolite levels with all-cause mortality and incident heart failure among US older adults in the CHS (Cardiovascular Health Study). We followed 1758 participants without heart failure at baseline with hazard ratios (HRs) of analyte levels and metabolic profiles characterized by high levels of ketone bodies for all-cause mortality and incident heart failure. Multivariable Cox analyses revealed a dose-response relationship of 50% increase in all-cause mortality between lowest and highest quintiles of ketone body concentrations (HR, 1.5 [95% CI, 1.0-1.9]; =0.007). Ketone body levels remained associated with incident heart failure after adjusting for cardiovascular disease confounders (HR, 1.2 [95% CI, 1.0-1.3]; =0.02). Using K-means cluster analysis, we identified a cluster with higher levels of ketone bodies, citrate, interleukin-6, and B-type natriuretic peptide but lower levels of pyruvate, body mass index, and estimated glomerular filtration rate. The cluster with elevated ketone body levels was associated with higher all-cause mortality (HR, 1.7 [95% CI, 1.1-2.7]; =0.01). Conclusions Higher concentrations of ketone bodies predict incident heart failure and all-cause mortality in an older US population, independent of metabolic and cardiovascular confounders. This association suggests a potentially important relationship between ketone body metabolism and aging.
Keywords: Aged; Aging; Cardiovascular Diseases; Heart Failure; Humans; Incidence; Ketone Bodies

Evaluation of Associations of Growth Differentiation Factor-11, Growth Differentiation Factor-8 and their Binding Proteins Follistatin and Follistatin-like protein-3 with Dementia and Cognition. - Newman, Anne B; Patel, Sheena; Kizer, Jorge; Lee, Se-Jin; Bhasin, Shalinder; Cawthon, Peggy; LeBrasseur, Nathan; Tracy, Russel P; Ganz, Peter; Cummings, Steve (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Studies using heterochronic parabiosis discovered that circulating factors mediate brain aging in animal models. METHODS: We assessed Growth Differentiation Factor (GDF)-11 and GDF-8 using mass spectrometry and inhibitors follistatin and follistatin-like protein-3 (FSTL-3) with ELISA in in the Cardiovascular Health Study (N=1506) and the Health ABC study (N=1237). CLL-11 and Beta 2 microglobulin (B2M) were measured with ELISA in a subset of 400 individuals in Health ABC. Associations were assessed with cognitive function, brain magnetic resonance imaging (MRI) findings (CHS only) and incident dementia using correlations, linear regression and Cox proportional hazards models. RESULTS: In CHS, levels of GDF-11, GDF-8 and follistatin were not correlated cross sectionally with the 3MSE or DSST, brain MRI findings of white matter hyperintensity, atrophy or small infarcts, nor were they associated with incident dementia. FSTL-3 was modestly correlated with poorer cognitive function, greater white matter hyperintensities and atrophy on MRI as well as with incident dementia with an adjusted HR of 1.72 (95% CI=1.13, 2.61) per doubling of FSTL-3. FSTL-3 was not associated with cognition or dementia in Health ABC, but GDF-8 was associated with both. The adjusted HR for incident dementia was 1.50 (95%CI 1.07, 2.10) per doubling of GDF-8. CONCLUSIONS: Total GDF-11 level was not related to cognition or dementia in older adults. Associations of GDF-8 with cognitive outcomes in Health ABC were not expected, but consistent with animal models. Associations of FSTL-3 with cognition, brain abnormalities, and incident dementia in CHS implicates TGF-B superfamily inhibition in the pathogenesis of dementia.

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Boerwinkle, Eric; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Gibbs, Richard; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genome-Wide Interaction Analysis with DASH Diet Score Identified Novel Loci for Systolic Blood Pressure. - Guirette, Melanie; Lan, Jessie; McKeown, Nicola; Brown, Michael R; Chen, Han; de Vries, Paul S; Kim, Hyunju; Rebholz, Casey M; Morrison, Alanna C; Bartz, Traci M; Fretts, Amanda M; Guo, Xiuqing; et al. (medRxiv, 2023)
OBJECTIVE: We examined interactions between genotype and a Dietary Approaches to Stop Hypertension (DASH) diet score in relation to systolic blood pressure (SBP). METHODS: We analyzed up to 9,420,585 biallelic imputed single nucleotide polymorphisms (SNPs) in up to 127,282 individuals of six population groups (91% of European population) from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (CHARGE; n=35,660) and UK Biobank (n=91,622) and performed European population-specific and cross-population meta-analyses. RESULTS: We identified three loci in European-specific analyses and an additional four loci in cross-population analyses at P for interaction < 5e-8. We observed a consistent interaction between rs117878928 at 15q25.1 (minor allele frequency = 0.03) and the DASH diet score (P for interaction = 4e-8; P for heterogeneity = 0.35) in European population, where the interaction effect size was 0.42±0.09 mm Hg (P for interaction = 9.4e-7) and 0.20±0.06 mm Hg (P for interaction = 0.001) in CHARGE and the UK Biobank, respectively. The 1 Mb region surrounding rs117878928 was enriched with -expression quantitative trait loci (eQTL) variants (P = 4e-273) and -DNA methylation quantitative trait loci (mQTL) variants (P = 1e-300). While the closest gene for rs117878928 is , the highest narrow sense heritability accounted by SNPs potentially interacting with the DASH diet score in this locus was for gene at 15q25.1. CONCLUSION: We demonstrated gene-DASH diet score interaction effects on SBP in several loci. Studies with larger diverse populations are needed to validate our findings.

High-risk carotid plaques and incident ischemic stroke in patients with atrial fibrillation in the Cardiovascular Health Study. - Noubiap, Jean Jacques; Thomas, Gijo; Kamtchum-Tatuene, Joseph; Middeldorp, Melissa E; Sanders, Prashanthan (Eur J Neurol, 2023)
BACKGROUND AND PURPOSE: Whether carotid artery disease could improve stroke risk stratification tools in patients with atrial fibrillation (AF) remains uncertain. This study was undertaken to investigate the risk of ischemic stroke associated with occlusive and nonocclusive carotid atherosclerotic disease in patients with AF in the prospective population-based Cardiovascular Health Study. METHODS: We included participants aged ≥65 years with AF. We used multivariable Cox regression analysis to explore the risk of ischemic stroke associated with the percentage of carotid stenosis, plaque irregularity, echogenicity, and vulnerability (markedly irregular, ulcerated, or hypoechoic plaques). RESULTS: A total of 1398 participants were included (55.2% female, 61.7% aged 65-74 years). The maximum carotid stenosis was <50%, 50%-99%, and 100% in 94.5%, 5%, and 0.5% of participants, respectively. High-risk plaques based on echogenicity and plaque irregularity were found in 25.6% and 8.9% of participants, respectively. After a median follow-up of 10.9 years (interquartile range = 7.5-15.6), 298 ischemic strokes were recorded. There was no difference in the incidence of ischemic stroke according to the degree of carotid artery stenosis (p = 0.44), plaque echogenicity (low vs. high risk, p = 0.68), plaque irregularity (low vs. high risk, p = 0.55), and plaque vulnerability (p = 0.86). The CHA₂DS₂-VASc score was associated with an increased risk of ischemic stroke (adjusted hazard ratio = 1.28, 95% confidence interval = 1.18-1.40, p < 0.001). Both maximum grade of stenosis and plaque vulnerability were not associated with incident ischemic stroke (all p > 0.05). CONCLUSIONS: Neither the degree of carotid stenosis nor the presence of vulnerable plaques was associated with incident ischemic stroke in this cohort of individuals with AF. This suggests that carotid disease was probably not a significant contributor to ischemic stroke in this population.
Keywords: Atrial Fibrillation; Carotid Artery Diseases; Carotid Stenosis; Female; Humans; Ischemic Stroke; Male; Plaque, Atherosclerotic; Prospective Studies; Risk Factors; Stroke

Large-scale exome array summary statistics resources for glycemic traits to aid effector gene prioritization. - Willems, Sara M; Ng, Natasha H J; Fernandez, Juan; Fine, Rebecca S; Wheeler, Eleanor; Wessel, Jennifer; Kitajima, Hidetoshi; Marenne, Gaelle; Sim, Xueling; Yaghootkar, Hanieh; Wang, Shuai; Chen, Sai; et al. (Wellcome Open Res, 2023)
BACKGROUND: Genome-wide association studies for glycemic traits have identified hundreds of loci associated with these biomarkers of glucose homeostasis. Despite this success, the challenge remains to link variant associations to genes, and underlying biological pathways. METHODS: To identify coding variant associations which may pinpoint effector genes at both novel and previously established genome-wide association loci, we performed meta-analyses of exome-array studies for four glycemic traits: glycated hemoglobin (HbA1c, up to 144,060 participants), fasting glucose (FG, up to 129,665 participants), fasting insulin (FI, up to 104,140) and 2hr glucose post-oral glucose challenge (2hGlu, up to 57,878). In addition, we performed network and pathway analyses. RESULTS: Single-variant and gene-based association analyses identified coding variant associations at more than 60 genes, which when combined with other datasets may be useful to nominate effector genes. Network and pathway analyses identified pathways related to insulin secretion, zinc transport and fatty acid metabolism. HbA1c associations were strongly enriched in pathways related to blood cell biology. CONCLUSIONS: Our results provided novel glycemic trait associations and highlighted pathways implicated in glycemic regulation. Exome-array summary statistic results are being made available to the scientific community to enable further discoveries.

Late-life plasma proteins associated with prevalent and incident frailty: A proteomic analysis. - Liu, Fangyu; Austin, Thomas R; Schrack, Jennifer A; Chen, Jingsha; Walston, Jeremy; Mathias, Rasika A; Grams, Morgan; Odden, Michelle C; Newman, Anne; Psaty, Bruce M; Ramonfaur, Diego; Shah, Amil M; et al. (Aging Cell, 2023)
Proteomic approaches have unique advantages in the identification of biological pathways that influence physical frailty, a multifactorial geriatric syndrome predictive of adverse health outcomes in older adults. To date, proteomic studies of frailty are scarce, and few evaluated prefrailty as a separate state or examined predictors of incident frailty. Using plasma proteins measured by 4955 SOMAmers in the Atherosclerosis Risk in Community study, we identified 134 and 179 proteins cross-sectionally associated with prefrailty and frailty, respectively, after Bonferroni correction (p < 1 × 10 ) among 3838 older adults aged ≥65 years, adjusting for demographic and physiologic factors and chronic diseases. Among them, 23 (17%) and 82 (46%) were replicated in the Cardiovascular Health Study using the same models (FDR p < 0.05). Notably, higher odds of prefrailty and frailty were observed with higher levels of growth differentiation factor 15 (GDF15; p  = 1 × 10 , p  = 2 × 10 ), transgelin (TAGLN; p  = 2 × 10 , p  = 6 × 10 ), and insulin-like growth factor-binding protein 2 (IGFBP2; p  = 5 × 10 , p  = 1 × 10 ) and with a lower level of growth hormone receptor (GHR, p  = 3 × 10 , p  = 2 × 10 ). Longitudinally, we identified 4 proteins associated with incident frailty (p < 1 × 10 ). Higher levels of triggering receptor expressed on myeloid cells 1 (TREM1), TAGLN, and heart and adipocyte fatty-acid binding proteins predicted incident frailty. Differentially regulated proteins were enriched in pathways and upstream regulators related to lipid metabolism, angiogenesis, inflammation, and cell senescence. Our findings provide a set of plasma proteins and biological mechanisms that were dysregulated in both the prodromal and the clinical stage of frailty, offering new insights into frailty etiology and targets for intervention.

Mosaic chromosomal alterations in blood across ancestries using whole-genome sequencing. - Jakubek, Yasminka A; Zhou, Ying; Stilp, Adrienne; Bacon, Jason; Wong, Justin W; Ozcan, Zuhal; Arnett, Donna; Barnes, Kathleen; Bis, Joshua C; Boerwinkle, Eric; Brody, Jennifer A; Carson, April P; et al. (Nat Genet, 2023)
Megabase-scale mosaic chromosomal alterations (mCAs) in blood are prognostic markers for a host of human diseases. Here, to gain a better understanding of mCA rates in genetically diverse populations, we analyzed whole-genome sequencing data from 67,390 individuals from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program. We observed higher sensitivity with whole-genome sequencing data, compared with array-based data, in uncovering mCAs at low mutant cell fractions and found that individuals of European ancestry have the highest rates of autosomal mCAs and the lowest rates of chromosome X mCAs, compared with individuals of African or Hispanic ancestry. Although further studies in diverse populations will be needed to replicate our findings, we report three loci associated with loss of chromosome X, associations between autosomal mCAs and rare variants in DCPS, ADM17, PPP1R16B and TET2 and ancestry-specific variants in ATM and MPL with mCAs in cis.
Keywords: Black People; Genome, Human; Genome-Wide Association Study; Hispanic or Latino; Humans; Mosaicism; Precision Medicine

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Non-esterified fatty acids and risk of peripheral artery disease in older adults: The cardiovascular health study. - Ahiawodzi, Peter; Solaru, Khendi White; Chaves, Paulo H M; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (Atherosclerosis, 2023)
BACKGROUND AND AIMS: Non-esterified fatty acids have been implicated in the pathogenesis of diabetes and cardiovascular disease. No longitudinal study has assessed their effects on peripheral artery disease (PAD). We determined the relationships between NEFAs and incident clinical PAD and abnormal ankle-brachial index (ABI) in a population-based cohort of older persons. METHODS: We evaluated 4575 community living participants aged >65 years who underwent measurement of circulating NEFAs in fasting specimens and ABI in 1992-1993. Participants were assessed annually for clinical PAD until 2015 and underwent repeat ABI in 1998-1999. We used Cox proportional hazards regression to model the associations between NEFAs and risk of clinical PAD and logistic regression to model the associations of NEFAs with incident abnormal ABI. RESULTS: Mean age was 74.8 years, 59% were female, and 17% were Black. NEFAs were associated with higher risk of clinical PAD in unadjusted and adjusted models. The adjusted hazard ratios for incident clinical PAD were 1.51 (95%CI = 1.06-2.13, p = 0.02) across extreme tertiles, and 1.14 (95%CI = 0.99-1.31, p = 0.08) per standard deviation higher NEFA. The corresponding odds ratios for abnormal ABI were 0.95 (95%CI = 0.69-1.32, p = 0.76) across extreme tertiles, and 1.03 (95%CI = 0.89-1.20, p = 0.68) per standard deviation higher NEFA. Relationships appeared similar irrespective of sex, race, or pre-existing cardiovascular disease, but were stronger later than earlier in follow-up. CONCLUSIONS: Higher serum levels of NEFAs are significantly associated with increased likelihood of clinical PAD over long-term follow-up but not with 6-year decline in ABI. NEFAs may offer a potential target for intervention against clinical PAD.

Plasma Trimethylamine--Oxide and Incident Ischemic Stroke: The Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; Sitlani, Colleen M; Nemet, Ina; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Zhu, Weifei; Budoff, Matt; Longstreth, W T; Psaty, Bruce M; et al. (J Am Heart Assoc, 2023)
Background The association of circulating trimethylamine--oxide (TMAO) with stroke has received limited attention. To address this gap, we examined the associations of serial measures of plasma TMAO with incident ischemic stroke. Methods and Results We used a prospective cohort design with data pooled from 2 cohorts. The settings were the CHS (Cardiovascular Health Study), a cohort of older adults, and the MESA (Multi-Ethnic Study of Atherosclerosis), both in the United States. We measured plasma concentrations of TMAO at baseline and again during the follow-up using high-performance liquid chromatography and mass spectrometry. We assessed the association of plasma TMAO with incident ischemic stroke using proportional hazards regression adjusted for risk factors. The combined cohorts included 11 785 participants without a history of stroke, on average 73 (CHS) and 62 (MESA) years old at baseline, including 60% (CHS) and 53% (MESA) women. We identified 1031 total incident ischemic strokes during a median 15-year follow-up in the combined cohorts. In multivariable analyses, TMAO was significantly associated with incident ischemic stroke risk (hazard ratios comparing a doubling of TMAO: 1.11 [1.03-1.18], =0.004). The association was linear over the range of TMAO concentrations and appeared restricted to those without diagnosed coronary heart disease. An association with hemorrhagic stroke was not found. Conclusions Plasma TMAO levels are associated with incident ischemic stroke in a diverse population. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Atherosclerosis; Female; Humans; Ischemic Stroke; Methylamines; Oxides; Prospective Studies; Risk Factors; Stroke; United States

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

Social networks, social support, and life expectancy in older adults: the Cardiovascular Health Study. - Bhatia, Roma; Hirsch, Calvin; Arnold, Alice M; Newman, Anne B; Mukamal, Kenneth J (Arch Gerontol Geriatr, 2023)
BACKGROUND: Social support and social networks have long been postulated to impact health outcomes but their impact on life expectancy and disability in older adults remains poorly quantified. METHODS: As part of the Cardiovascular Health Study, we followed 5,749 adults aged 65 years and older from 4 US field centers for 25 years. We assessed the Lubben social network score [range 0-50] and a social support score [range 0-24] derived from the Interpersonal Support Evaluation List (ISEL-12) in two consecutive years starting at study recruitment. We used remaining years of life (YOL) from study enrollment to death to approximate life expectancy. We defined years of active life (YAL) as the number of study years in which participants lived without any difficulties in activities of daily living. We used compression of disability to reflect the proportion of life lived able (YAL/YOL). We used linear regression to adjust for socio-demographics and comorbidity. RESULTS: The mean (standard deviation [SD]) scores were 32.3 ± 6.8 points for social network score and 8.3 ± 2.4 points for social support score. For every 1-SD increase in social network score, adjusted participant life expectancy was 0.40 years higher (95% CI 0.22-0.58; p<0.0001) and disability-free life expectancy 0.35 years higher (95% CI 0.18-0.53; p<0.0001). The association with life expectancy was modified by participant age (p<0.001), but it remained significant even among participants aged ≥75 years (3 months per SD; 95% CI 0.1-6 months, p = 0.04). Further adjustment for frailty did not attenuate the estimates. The social support scale was not significantly associated with YOL or YAL after adjustment for social network score, and neither measure was associated with compression of disability. DISCUSSION: In older adults, higher social network scores are significantly associated with longer life expectancy and disability-free life expectancy.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Heon Kwak, Soo; Chen, Han; Li, Xihao; DiCorpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-Genome Sequencing Analysis of Human Metabolome in Multi-Ethnic Populations. - Feofanova, Elena V; Brown, Michael R; Alkis, Taryn; Manuel, Astrid M; Li, Xihao; Tahir, Usman A; Li, Zilin; Mendez, Kevin M; Kelly, Rachel S; Qi, Qibin; Chen, Han; Larson, Martin G; et al. (Nat Commun, 2023)
Circulating metabolite levels may reflect the state of the human organism in health and disease, however, the genetic architecture of metabolites is not fully understood. We have performed a whole-genome sequencing association analysis of both common and rare variants in up to 11,840 multi-ethnic participants from five studies with up to 1666 circulating metabolites. We have discovered 1985 novel variant-metabolite associations, and validated 761 locus-metabolite associations reported previously. Seventy-nine novel variant-metabolite associations have been replicated, including three genetic loci located on the X chromosome that have demonstrated its involvement in metabolic regulation. Gene-based analysis have provided further support for seven metabolite-replicated loci pairs and their biologically plausible genes. Among those novel replicated variant-metabolite pairs, follow-up analyses have revealed that 26 metabolites have colocalized with 21 tissues, seven metabolite-disease outcome associations have been putatively causal, and 7 metabolites might be regulated by plasma protein levels. Our results have depicted the genetic contribution to circulating metabolite levels, providing additional insights into understanding human disease.
Keywords: Ethnicity; Genome-Wide Association Study; Humans; Metabolome; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Whole-genome sequencing uncovers two loci for coronary artery calcification and identifies ARSE as a regulator of vascular calcification. - de Vries, Paul S; Conomos, Matthew P; Singh, Kuldeep; Nicholson, Christopher J; Jain, Deepti; Hasbani, Natalie R; Jiang, Wanlin; Lee, Sujin; Lino Cardenas, Christian L; Lutz, Sharon M; Wong, Doris; Guo, Xiuqing; et al. (Nat Cardiovasc Res, 2023)
Coronary artery calcification (CAC) is a measure of atherosclerosis and a well-established predictor of coronary artery disease (CAD) events. Here we describe a genome-wide association study (GWAS) of CAC in 22,400 participants from multiple ancestral groups. We confirmed associations with four known loci and identified two additional loci associated with CAC ( and ), with evidence of significant associations in replication analyses for both novel loci. Functional assays of and in human vascular smooth muscle cells (VSMCs) demonstrate that is a promoter of VSMC calcification and VSMC phenotype switching from a contractile to a calcifying or osteogenic phenotype. Furthermore, we show that the association of variants near with reduced CAC is likely explained by reduced expression with the G allele of enhancer variant rs5982944. Our study highlights ARSE as an important contributor to atherosclerotic vascular calcification, and a potential drug target for vascular calcific disease.

Alzheimer's Disease Sequencing Project Release 4 Whole Genome Sequencing Dataset - Leung, Y. Y.; Lee, W. P.; Kuzma, A. B.; Nicaretta, H.; Valladares, O.; Gangadharan, P.; Qu, L.; Zhao, Y.; Ren, Y.; Cheng, P. L.; Kuksa, P. P.; Wang, H.; et al. (medRxiv, 2024)
The Alzheimer's Disease Sequencing Project (ADSP) is a national initiative to understand the genetic architecture of Alzheimer's Disease and Related Dementias (AD/ADRD) by sequencing whole genomes of affected participants and age-matched cognitive controls from diverse populations. The Genome Center for Alzheimer's Disease (GCAD) processed whole-genome sequencing data from 36,361 ADSP participants, including 35,014 genetically unique participants of which 45% are from non-European ancestry, across 17 cohorts in 14 countries in this fourth release (R4). This sequencing effort identified 387 million bi-allelic variants, 42 million short insertions/deletions, and 2.2 million structural variants. Annotations and quality control data are available for all variants and samples. Additionally, detailed phenotypes from 15,927 participants across 10 domains are also provided. A linkage disequilibrium panel was created using unrelated AD cases and controls. Researchers can access and analyze the genetic data via NIAGADS Data Sharing Service, the VariXam tool, or NIAGADS GenomicsDB.

Association of Coagulation Factor XI Level With Cardiovascular Events and Cardiac Function in Community-Dwelling Adults: From ARIC and CHS. - Ji, Yuekai; Zhang, Michael J; Wang, Wendy; Norby, Faye L; Eaton, Anne A; Inciardi, Riccardo M; Alonso, Alvaro; Sedaghat, Sanaz; Ganz, Peter; Van't Hof, Jeremy; Solomon, Scott D; Chaves, Paulo H M; et al. (Circulation, 2024)
BACKGROUND: Coagulation factor XI (FXI) inhibitors are a promising and novel class of anticoagulants, but a recent animal study found that FXI inhibition exacerbated diastolic dysfunction and heart failure (HF). In the ARIC study (Atherosclerosis Risk in Communities), we investigated whether plasma FXI level was associated with cardiovascular events and cardiac function. METHODS: ARIC was our primary analytic cohort. We included 4471 participants (median age, 75 years; 57% female; 17% Black) who attended visit 5 (2011-2013) with Somalogic-quantified plasma FXI levels and echocardiographic cardiac function. Prevalent HF and atrial fibrillation (AF) cases were defined as having HF or AF diagnosed at or before each participant's visit 5 exam date. Incident HF and AF events were ascertained through 2021. Associations were assessed using Cox, logistic, and linear regression models. Primary prospective associations were also validated in the CHS (Cardiovascular Health Study) using an orthogonal FXI assay (enzyme-linked immunosorbent assay). RESULTS: At ARIC visit 5, there were 665 and 419 participants with prevalent HF and AF, respectively. During a median follow-up of 9 years, there were 580 and 788 incident HF and AF events, respectively. Lower FXI level was associated prospectively with higher incidence of HF (hazard ratio [HR], 1.36 [for each 1-unit decrement of log-transformed FXI level] [95% CI, 1.01-1.83]) but not incident AF, and cross-sectionally with increased odds of AF (odds ratio [OR], 1.96 [95% CI, 1.23-3.07]) but not HF. In age-stratified analyses, decreased FXI was associated with higher incidence of HF in participants ≥75 years of age (HR, 1.57 [95% CI, 1.08-2.28]) but not <75 years of age (HR, 1.11 [95% CI, 0.68-1.79]). The inverse FXI-HF association was validated in CHS (HR, 1.18 [95% CI, 1.02-1.36]). At ARIC visit 5, lower FXI level was also associated with higher prevalence of diastolic dysfunction and worse E/A ratio, left atrial (LA) volume index, LA function, and left ventricular mass index, but not left ventricular ejection fraction or global longitudinal strain. CONCLUSIONS: Decreased FXI level is associated with greater incidence of HF, especially in older adults. It is also associated with prevalent AF, worse diastolic function, worse LA function, and greater LA size. More research is needed to assess potential unwanted effects of FXI inhibition on the risk of cardiovascular events and cardiac function.

Associations between toxicity-weighted concentrations and dementia risk: Results from the Cardiovascular Health Cognition Study. - Crane, Breanna M; Moored, Kyle D; Donahue, Patrick T; Corrigan, Anne E; Curriero, Frank C; Shields, Timothy M; Desjardins, Michael R; Richards, Emily A; Rosso, Andrea L; Lovasi, Gina S; Odden, Michelle C; Lopez, Oscar L; et al. (Sci Total Environ, 2024)
BACKGROUND: Air pollution is a modifiable risk factor for dementia. Yet, studies on specific sources of air pollution (i.e., toxic chemical emissions from industrial facilities) and dementia risk are scarce. We examined associations between toxicity-weighted concentrations of industrial pollution and dementia outcomes among a large, multi-site cohort of older adults. METHODS: Participants (n = 2770) were ≥ 65 years old (Mean = 75.3, SD = 5.1 years) from the Cardiovascular Health Cognition Study (1992-1999). Toxicity-weighted concentrations were estimated using the Risk Screening Environmental Indicator (RSEI) model which incorporates total reported chemical emissions with toxicity, fate, and transport models. Estimates were aggregated to participants' baseline census tract, averaged across 1988-1992, and log2-transformed. Dementia status was clinically adjudicated in 1998-1999 and categorized by subtype (Alzheimer's, vascular, mixed). We assessed whether RSEI-estimated toxicity-weighted concentrations were associated with 1) odds of prevalent dementia and 2) incident dementia risk by subtype. RESULTS: After adjusting for individual and census-tract level covariates, a doubling in toxicity-weighted concentrations was associated with 9 % higher odds of prevalent dementia (OR = 1.09, 95 % CI: 1.00, 1.19). In discrete-time survival models, each doubling in toxicity-weighted concentrations was associated with a 16 % greater hazard of vascular dementia (HR = 1.16, 95 % CI: 1.01, 1.34) but was not significantly associated with all-cause, Alzheimer's disease, or mixed dementia (p's > 0.05). DISCUSSION: Living in regions with higher toxicity-weighted concentrations was associated with higher odds of prevalent dementia and a higher risk of incident vascular dementia in this large, community-based cohort of older adults. These findings support the need for additional studies to examine whether toxic chemical emissions from industrial and federal facilities may be a modifiable target for dementia prevention.
Keywords: Aged; Aged, 80 and over; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Female; Humans; Male; Risk Factors

Associations of Neurological Biomarkers in Serum with Gait Measures: The Cardiovascular Health Study. - Nadkarni, Abhijay; Mukamal, Kenneth J; Zhu, Xiaonan; Siscovick, David; Brach, Jennifer S; Jacob, Mini; Seshadri, Sudha; Abe, Temidayo; Rosano, Caterina; Djoussé, Luc; Rosso, Andrea L (J Gerontol A Biol Sci Med Sci, 2024)
BACKGROUND: Gait impairment leads to increased mobility decline and may have neurological contributions. This study explores how neurological biomarkers are related to gait in older adults. METHODS: We studied participants in the Cardiovascular Health Study, a population-based cohort of older Americans, who underwent a serum biomarker assessment from samples collected in 1996-97 for neurofilament light-chain (NfL), glial fibrillary acidic protein (GFAP), ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), and total tau (n=1959, mean age=78.0 years, 60.8% female). In a subsample (n=380), cross-sectional associations with quantitative gait measures were explored. This subsample was assessed on a mat for gait speed, step length, double support time, step time, step length variability and step time variability. Gait speed was also measured over a 15-ft walkway annually from 1996-97 to 1998-99, for longitudinal analyses. Linear regression models assessed cross-sectional associations of biomarkers with gait measures, while mixed effects models assessed longitudinal gait speed change from baseline to 1998-99. RESULTS: NfL was significantly associated with annual gait speed decline (standardized β = -0.64 m/s, 95% CI: [-1.23, -0.06]) after adjustment for demographic and health factors. Among gait mat-assessed phenotypes, NfL was also cross-sectionally associated with gait speed (β = 0.001 m/s [0.0003, 0.002]) but not with other gait measures. None of the remaining biomarkers were significantly related to gait in either longitudinal or cross-sectional analyses. CONCLUSION: Higher NfL levels were related to greater annual gait speed decline. Gait speed decline may be related to axonal degeneration. The clinical utility of NfL should be explored.

Associations of Serum GDF-15 Levels with Physical Performance, Mobility Disability, Cognition, Cardiovascular Disease, and Mortality in Older Adults. - Webber, Katey; Patel, Sheena; Kizer, Jorge R; Eastell, Richard; Psaty, Bruce M; Newman, Anne B; Cummings, Steven R (medRxiv, 2024)
BACKGROUND: Growth differentiation factor 15 (GDF-15) is a member of the TGFβ superfamily secreted by many cell types and found at higher blood concentrations as chronological age increases (1). Given the emergence of GDF-15 as a key protein associated with aging, it is important to understand the multitude of conditions with which circulating GDF-15 is associated. METHODS: We pooled data from 1,174 randomly selected Health ABC Study (Health ABC) participants and 1,503 Cardiovascular Health Study (CHS) participants to evaluate the risk of various conditions and age-related outcomes across levels of GDF-15. The primary outcomes were (1) risk of mobility disability and falls; (2) impaired cognitive function; (3) and increased risk of cardiovascular disease and total mortality. RESULTS: The pooled study cohort had a mean age of 75.4 +/-4.4 years. Using a Bonferroni-corrected threshold, our analyses show that high levels of GDF-15 were associated with a higher risk of severe mobility disability (HR: 2.13 [1.64, 2.77]), coronary heart disease (HR: 1.47 [1.17, 1.83]), atherosclerotic cardiovascular disease (HR: 1.56 [1.22, 1.98]), heart failure (HR: 2.09 [1.66, 2.64]), and mortality (HR: 1.81 [1.53, 2.15]) when comparing the highest and lowest quartiles. For CHS participants, analysis of extreme quartiles in fully adjusted models revealed a 3.5-fold higher risk of dementia (HR: 3.50 [1.97, 6.22]). CONCLUSIONS: GDF-15 is associated with several age-related outcomes and diseases, including mobility disability, impaired physical and cognitive performance, dementia, cardiovascular disease, and mortality. Each of these findings demonstrates the importance of GDF-15 as a potential biomarker for many aging-related conditions.

Development and Validation of the American Heart Association's PREVENT Equations. - Khan, Sadiya S; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Surapaneni, Aditya; Blaha, Michael J; Carson, April P; Chang, Alexander R; Ciemins, Elizabeth; Go, Alan S; Gutierrez, Orlando M; et al. (Circulation, 2024)
BACKGROUND: Multivariable equations are recommended by primary prevention guidelines to assess absolute risk of cardiovascular disease (CVD). However, current equations have several limitations. Therefore, we developed and validated the American Heart Association Predicting Risk of CVD EVENTs (PREVENT) equations among US adults 30 to 79 years of age without known CVD. METHODS: The derivation sample included individual-level participant data from 25 data sets (N=3 281 919) between 1992 and 2017. The primary outcome was CVD (atherosclerotic CVD and heart failure). Predictors included traditional risk factors (smoking status, systolic blood pressure, cholesterol, antihypertensive or statin use, and diabetes) and estimated glomerular filtration rate. Models were sex-specific, race-free, developed on the age scale, and adjusted for competing risk of non-CVD death. Analyses were conducted in each data set and meta-analyzed. Discrimination was assessed using the Harrell C-statistic. Calibration was calculated as the slope of the observed versus predicted risk by decile. Additional equations to predict each CVD subtype (atherosclerotic CVD and heart failure) and include optional predictors (urine albumin-to-creatinine ratio and hemoglobin A1c), and social deprivation index were also developed. External validation was performed in 3 330 085 participants from 21 additional data sets. RESULTS: Among 6 612 004 adults included, mean±SD age was 53±12 years, and 56% were women. Over a mean±SD follow-up of 4.8±3.1 years, there were 211 515 incident total CVD events. The median C-statistics in external validation for CVD were 0.794 (interquartile interval, 0.763-0.809) in female and 0.757 (0.727-0.778) in male participants. The calibration slopes were 1.03 (interquartile interval, 0.81-1.16) and 0.94 (0.81-1.13) among female and male participants, respectively. Similar estimates for discrimination and calibration were observed for atherosclerotic CVD- and heart failure-specific models. The improvement in discrimination was small but statistically significant when urine albumin-to-creatinine ratio, hemoglobin A1c, and social deprivation index were added together to the base model to total CVD (ΔC-statistic [interquartile interval] 0.004 [0.004-0.005] and 0.005 [0.004-0.007] among female and male participants, respectively). Calibration improved significantly when the urine albumin-to-creatinine ratio was added to the base model among those with marked albuminuria (>300 mg/g; 1.05 [0.84-1.20] versus 1.39 [1.14-1.65]; =0.01). CONCLUSIONS: PREVENT equations accurately and precisely predicted risk for incident CVD and CVD subtypes in a large, diverse, and contemporary sample of US adults by using routinely available clinical variables.
Keywords: Adult; Aged; Albumins; American Heart Association; Atherosclerosis; Cardiovascular Diseases; Creatinine; Female; Glycated Hemoglobin; Heart Failure; Humans; Male; Middle Aged; Risk Assessment; Risk Factors

Epigenetic and proteomic signatures associate with clonal hematopoiesis expansion rate. - Mack, Taralynn M; Raddatz, Michael A; Pershad, Yash; Nachun, Daniel C; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Kenny, Eimear E; Loos, Ruth J F; Redline, Susan; Cade, Brian E; et al. (Nat Aging, 2024)
Clonal hematopoiesis of indeterminate potential (CHIP), whereby somatic mutations in hematopoietic stem cells confer a selective advantage and drive clonal expansion, not only correlates with age but also confers increased risk of morbidity and mortality. Here, we leverage genetically predicted traits to identify factors that determine CHIP clonal expansion rate. We used the passenger-approximated clonal expansion rate method to quantify the clonal expansion rate for 4,370 individuals in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) cohort and calculated polygenic risk scores for DNA methylation aging, inflammation-related measures and circulating protein levels. Clonal expansion rate was significantly associated with both genetically predicted and measured epigenetic clocks. No associations were identified with inflammation-related lab values or diseases and CHIP expansion rate overall. A proteome-wide search identified predicted circulating levels of myeloid zinc finger 1 and anti-Müllerian hormone as associated with an increased CHIP clonal expansion rate and tissue inhibitor of metalloproteinase 1 and glycine N-methyltransferase as associated with decreased CHIP clonal expansion rate. Together, our findings identify epigenetic and proteomic patterns associated with the rate of hematopoietic clonal expansion.

Epigenome-wide DNA Methylation Association Study of CHIP Provides Insight into Perturbed Gene Regulation. - Levy, Daniel; Kirmani, Sara; Huan, Tianxiao; Van Amburg, Joseph; Joehanes, Roby; Uddin, Md Mesbah; Nguyen, Ngoc Quynh; Yu, Bing; Brody, Jennifer; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; et al. (Res Sq, 2024)
With age, hematopoietic stem cells can acquire somatic mutations in leukemogenic genes that confer a proliferative advantage in a phenomenon termed "clonal hematopoiesis of indeterminate potential" (CHIP). How these mutations confer a proliferative advantage and result in increased risk for numerous age-related diseases remains poorly understood. We conducted a multiracial meta-analysis of epigenome-wide association studies (EWAS) of CHIP and its subtypes in four cohorts (N=8196) to elucidate the molecular mechanisms underlying CHIP and illuminate how these changes influence cardiovascular disease risk. The EWAS findings were functionally validated using human hematopoietic stem cell (HSC) models of CHIP. A total of 9615 CpGs were associated with any CHIP, 5990 with DNMT3A CHIP, 5633 with TET2 CHIP, and 6078 with ASXL1 CHIP (P <1×10). CpGs associated with CHIP subtypes overlapped moderately, and the genome-wide DNA methylation directions of effect were opposite for TET2 and DNMT3A CHIP, consistent with their opposing effects on global DNA methylation. There was high directional concordance between the CpGs shared from the meta-EWAS and human edited CHIP HSCs. Expression quantitative trait methylation analysis further identified transcriptomic changes associated with CHIP-associated CpGs. Causal inference analyses revealed 261 CHIP-associated CpGs associated with cardiovascular traits and all-cause mortality (FDR adjusted p-value <0.05). Taken together, our study sheds light on the epigenetic changes impacted by CHIP and their associations with age-related disease outcomes. The novel genes and pathways linked to the epigenetic features of CHIP may serve as therapeutic targets for preventing or treating CHIP-mediated diseases.

Familial Hypercholesterolemia Variant and Cardiovascular Risk in Individuals With Elevated Cholesterol. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Familial hypercholesterolemia (FH) is a genetic disorder that often results in severely high low-density lipoprotein cholesterol (LDL-C) and high risk of premature coronary heart disease (CHD). However, the impact of FH variants on CHD risk among individuals with moderately elevated LDL-C is not well quantified. OBJECTIVE: To assess CHD risk associated with FH variants among individuals with moderately (130-189 mg/dL) and severely (≥190 mg/dL) elevated LDL-C and to quantify excess CHD deaths attributable to FH variants in US adults. DESIGN, SETTING, AND PARTICIPANTS: A total of 21 426 individuals without preexisting CHD from 6 US cohort studies (Atherosclerosis Risk in Communities study, Coronary Artery Risk Development in Young Adults study, Cardiovascular Health Study, Framingham Heart Study Offspring cohort, Jackson Heart Study, and Multi-Ethnic Study of Atherosclerosis) were included, 63 of whom had an FH variant. Data were collected from 1971 to 2018, and the median (IQR) follow-up was 18 (13-28) years. Data were analyzed from March to May 2023. EXPOSURES: LDL-C, cumulative past LDL-C, FH variant status. MAIN OUTCOMES AND MEASURES: Cox proportional hazards models estimated associations between FH variants and incident CHD. The Cardiovascular Disease Policy Model projected excess CHD deaths associated with FH variants in US adults. RESULTS: Of the 21 426 individuals without preexisting CHD (mean [SD] age 52.1 [15.5] years; 12 041 [56.2%] female), an FH variant was found in 22 individuals with moderately elevated LDL-C (0.3%) and in 33 individuals with severely elevated LDL-C (2.5%). The adjusted hazard ratios for incident CHD comparing those with and without FH variants were 2.9 (95% CI, 1.4-6.0) and 2.6 (95% CI, 1.4-4.9) among individuals with moderately and severely elevated LDL-C, respectively. The association between FH variants and CHD was slightly attenuated when further adjusting for baseline LDL-C level, whereas the association was no longer statistically significant after adjusting for cumulative past LDL-C exposure. Among US adults 20 years and older with no history of CHD and LDL-C 130 mg/dL or higher, more than 417 000 carry an FH variant and were projected to experience more than 12 000 excess CHD deaths in those with moderately elevated LDL-C and 15 000 in those with severely elevated LDL-C compared with individuals without an FH variant. CONCLUSIONS AND RELEVANCE: In this pooled cohort study, the presence of FH variants was associated with a 2-fold higher CHD risk, even when LDL-C was only moderately elevated. The increased CHD risk appeared to be largely explained by the higher cumulative LDL-C exposure in individuals with an FH variant compared to those without. Further research is needed to assess the value of adding genetic testing to traditional phenotypic FH screening.

Gene-Excessive Sleepiness Interactions Suggest Treatment Targets for Obstructive Sleep Apnea Subtype. - Nagarajan, Pavithra; Kurniansyah, Nuzulul; Lee, Jiwon; Gharib, Sina A; Xu, Yushan; Zhang, Yiyan; Spitzer, Brian; Faquih, Tariq; Zhou, Hufeng; Boerwinkle, Eric; Chen, Han; Gottlieb, Daniel J; et al. (medRxiv, 2024)
Obstructive sleep apnea (OSA) is a multifactorial sleep disorder characterized by a strong genetic basis. Excessive daytime sleepiness (EDS) is a symptom that is reported by a subset of OSA patients, persisting even after treatment with continuous positive airway pressure (CPAP). It is recognized as a clinical subtype underlying OSA carrying alarming heightened cardiovascular risk. Thus, conceptualizing EDS as an exposure variable, we sought to investigate EDS's influence on genetic variation linked to apnea-hypopnea index (AHI), a diagnostic measure of OSA severity. This study serves as the first large-scale genome-wide gene x environment interaction analysis for AHI, investigating the interplay between its genetic markers and EDS across and within specific sex. Our work pools together whole genome sequencing data from seven cohorts, enabling a diverse dataset (four population backgrounds) of over 11,500 samples. Among the total 16 discovered genetic targets with interaction evidence with EDS, eight are previously unreported for OSA, including , , and identified in all sexes; , , and identified in males; and and identified in females. We discuss connections to insulin resistance, thiamine deficiency, and resveratrol use that may be worthy of therapeutic consideration for excessively sleepy OSA patients.

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

{Genetic associations with dementia-related proteinopathy: Application of item response theory - Katsumata, Y.; Fardo, D. W.; Shade, L. M. P.; Wu, X.; Karanth, S. D.; Hohman, T. J.; Schneider, J. A.; Bennett, D. A.; Farfel, J. M.; Gauthreaux, K.; Mock, C.; Kukull, W. A.; et al. (Alzheimers Dement, 2024)
Although dementia-related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.\ -synuclein, and TDP-43.\ -synuclein/Lewy bodies. Novel suggestive proteinopathy-linked alleles were also discovered, including several (SDHAF1, TMEM68, and ARHGEF28) with colocalization analyses and/or high degrees of biologic credibility.\ A novel methodology using GPCM enabled insights into gene candidates for driving misfolded proteinopathies.\ Latent factor scores for proteinopathies were estimated using a generalized partial credit model. The three latent continuous scores corresponded well with proteinopathy severity. Novel genes associated with proteinopathies were identified. Several genes had high degrees of biologic credibility for dementia risk factors.

The Genetic Determinants and Genomic Consequences of Non-Leukemogenic Somatic Point Mutations. - Weinstock, Joshua S; Chaudhry, Sharjeel A; Ioannou, Maria; Viskadourou, Maria; Reventun, Paula; Jakubek, Yasminka A; Alexander Liggett, L; Laurie, Cecelia; Broome, Jai G; Khan, Alyna; Taylor, Kent D; Guo, Xiuqing; et al. (medRxiv, 2024)
Clonal hematopoiesis (CH) is defined by the expansion of a lineage of genetically identical cells in blood. Genetic lesions that confer a fitness advantage, such as point mutations or mosaic chromosomal alterations (mCAs) in genes associated with hematologic malignancy, are frequent mediators of CH. However, recent analyses of both single cell-derived colonies of hematopoietic cells and population sequencing cohorts have revealed CH frequently occurs in the absence of known driver genetic lesions. To characterize CH without known driver genetic lesions, we used 51,399 deeply sequenced whole genomes from the NHLBI TOPMed sequencing initiative to perform simultaneous germline and somatic mutation analyses among individuals without leukemogenic point mutations (LPM), which we term CH-LPMneg. We quantified CH by estimating the total mutation burden. Because estimating somatic mutation burden without a paired-tissue sample is challenging, we developed a novel statistical method, the Genomic and Epigenomic informed Mutation (GEM) rate, that uses external genomic and epigenomic data sources to distinguish artifactual signals from true somatic mutations. We performed a genome-wide association study of GEM to discover the germline determinants of CH-LPMneg. After fine-mapping and variant-to-gene analyses, we identified seven genes associated with CH-LPMneg ( , , ), and one locus associated with a sex-associated mutation pathway ( . We performed a secondary analysis excluding individuals with mCAs, finding that the genetic architecture was largely unaffected by their inclusion. Functional analyses of and implicated altered HSC self-renewal and proliferation as the primary mediator of mutation burden in blood. We then performed comprehensive multi-tissue transcriptomic analyses, finding that the expression levels of 404 genes are associated with GEM. Finally, we performed phenotypic association meta-analyses across four cohorts, finding that GEM is associated with increased white blood cell count and increased risk for incident peripheral artery disease, but is not significantly associated with incident stroke or coronary disease events. Overall, we develop GEM for quantifying mutation burden from WGS without a paired-tissue sample and use GEM to discover the genetic, genomic, and phenotypic correlates of CH-LPMneg.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

Genome-wide analysis in over 1 million individuals of European ancestry yields improved polygenic risk scores for blood pressure traits. - Keaton, Jacob M; Kamali, Zoha; Xie, Tian; Vaez, Ahmad; Williams, Ariel; Goleva, Slavina B; Ani, Alireza; Evangelou, Evangelos; Hellwege, Jacklyn N; Yengo, Loic; Young, William J; Traylor, Matthew; et al. (Nat Genet, 2024)
Hypertension affects more than one billion people worldwide. Here we identify 113 novel loci, reporting a total of 2,103 independent genetic signals (P < 5 × 10) from the largest single-stage blood pressure (BP) genome-wide association study to date (n = 1,028,980 European individuals). These associations explain more than 60% of single nucleotide polymorphism-based BP heritability. Comparing top versus bottom deciles of polygenic risk scores (PRSs) reveals clinically meaningful differences in BP (16.9 mmHg systolic BP, 95% CI, 15.5-18.2 mmHg, P = 2.22 × 10) and more than a sevenfold higher odds of hypertension risk (odds ratio, 7.33; 95% CI, 5.54-9.70; P = 4.13 × 10) in an independent dataset. Adding PRS into hypertension-prediction models increased the area under the receiver operating characteristic curve (AUROC) from 0.791 (95% CI, 0.781-0.801) to 0.826 (95% CI, 0.817-0.836, ∆AUROC, 0.035, P = 1.98 × 10). We compare the 2,103 loci results in non-European ancestries and show significant PRS associations in a large African-American sample. Secondary analyses implicate 500 genes previously unreported for BP. Our study highlights the role of increasingly large genomic studies for precision health research.

The Gut Microbial Metabolite Trimethylamine N-oxide, Incident CKD, and Kidney Function Decline. - Wang, Meng; Tang, W H Wilson; Li, Xinmin S; de Oliveira Otto, Marcia C; Lee, Yujin; Lemaitre, Rozenn N; Fretts, Amanda; Nemet, Ina; Sotoodehnia, Nona; Sitlani, Colleen M; Budoff, Matthew; DiDonato, Joseph A; et al. (J Am Soc Nephrol, 2024)
BACKGROUND: Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite of dietary phosphatidylcholine and carnitine. Experimentally, TMAO causes kidney injury and tubulointerstitial fibrosis. Little is known about prospective associations between TMAO and kidney outcomes, especially incident CKD. We hypothesized that higher plasma TMAO levels would be associated with higher risk of incident CKD and greater rate of kidney function decline. METHODS: We included 10,564 participants from two community-based, prospective cohorts with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73m2 to assess incident CKD. TMAO was measured using targeted mass spectrometry at baseline and one follow-up visit. Creatinine and Cystatin C were measured up to 4 times during follow-up and used to compute eGFR. Incident CKD was defined as an eGFR decline ≥ 30% from baseline and a resulting eGFR<60 ml/min/1.73 m2. Time-varying Cox models assessed the association of serial TMAO measures with incident CKD, adjusting for sociodemographic, lifestyle, diet, and cardiovascular disease risk factors. Linear mixed models assessed the association with annualized eGFR change in 10,009 participants with at least one follow-up eGFR measure without exclusions for baseline eGFR levels. RESULTS: During a median follow-up of 9.4 years (interquartile range: 9.1-11.6 years), 979 incident CKD events occurred. Higher TMAO levels associated with higher risk of incident CKD (2nd to 5th vs. 1st quintile HR[95%CI]= 1.65 [1.22-2.23], 1.68 [1.26-2.25], 2.28 [1.72-3.02], and 2.24[1.68-2.98], respectively) and greater annualized eGFR decline ( 2nd to 5th vs. 1st quintile annualized eGFR change= -0.21 [-0.32, -0.09], -0.17 [-0.29, -0.05], -0.35 [-0.47, -0.22], and -0.43[-0.56, -0.30], respectively) with monotonic dose-response relationships. These associations were consistent across different racial/ethnic groups examined. The association with eGFR decline was similar to or larger than that seen for established CKD risk factors including diabetes, per 10 mmHg of higher systolic blood pressure, per 10 years of older age, and Black race. CONCLUSIONS: In community-based US adults, higher serial measures of plasma TMAO were associated with higher risk of incident CKD and greater annualized kidney function decline.

High Throughput Plasma Proteomics and Risk of Heart Failure and Frailty in Late Life. - Ramonfaur, Diego; Buckley, Leo F; Arthur, Victoria; Yang, Yimin; Claggett, Brian L; Ndumele, Chiadi E; Walker, Keenan A; Austin, Thomas; Odden, Michelle C; Floyd, James S; Sanders-van Wijk, Sandra; Njoroge, Joyce; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Heart failure (HF) and frailty frequently coexist and may share a common pathobiology, although the underlying mechanisms remain unclear. Understanding these mechanisms may provide guidance for preventing and treating both conditions. OBJECTIVE: To identify shared pathways between incident HF and frailty in late life using large-scale proteomics. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, 4877 aptamers (Somascan v4) were measured among participants in the community-based longitudinal Atherosclerosis Risk In Communities (ARIC) cohort study at visit 3 (V3; 1993-1995; n = 10 638) and at visit 5 (V5; 2011-2013; n = 3908). Analyses were externally replicated among 3189 participants in the Cardiovascular Health Study (CHS). Data analysis was conducted from February 2022 to June 2023. EXPOSURES: Protein aptamers, measured at study V3 and V5. MAIN OUTCOMES AND MEASURES: Outcomes assessed included incident HF hospitalization after V3 and after V5, prevalent frailty at V5, and incident frailty between V5 and visit 6 (V6; 2016-2017; n = 4131). Frailty was assessed using the Fried criteria. Analyses were adjusted for age, gender, race, field center, hypertension, diabetes, smoking status, body mass index, estimated glomerular filtration rate, prevalent coronary heart disease, prevalent atrial fibrillation, and history of myocardial infarction. Mendelian randomization (MR) analysis was performed to assess potential causal effects of candidate proteins on HF and frailty. RESULTS: A total of 4877 protein aptamers were measured among 10 638 participants at V3 (mean [SD] age, 60 [6] years; 4886 [46%] men). Overall, 286 proteins were associated with incident HF after V3 (822 events; P < 1.0 × 10-5), 83 of which were also associated with incident after V5 (336 events; P < 1.7 × 10-4). Among HF-free participants at V5 (n = 3908; mean [SD] age, 75 [5] years; 1861 [42%] men), 48 of 83 HF-associated proteins were associated with prevalent frailty (223 cases; P < 6.0 × 10-4), 18 of which were also associated with incident frailty at V6 (152 cases; P < 1.0 × 10-3). These proteins enriched fibrosis and inflammation pathways and demonstrated stronger associations with incident HF with preserved ejection fraction (HFpEF) than HF with reduced ejection fraction. All 18 proteins were associated with both prevalent frailty and incident HF in CHS. MR identified potential causal effects of several proteins on frailty and HF. CONCLUSIONS AND RELEVANCE: In this study, the proteins associated with risk of HF and frailty enrich for pathways related to inflammation and fibrosis as well as risk of HFpEF. Several of these proteins could potentially contribute to the shared pathophysiology of frailty and HF.
Keywords: Aged; Biomarkers; Female; Frailty; Heart Failure; Humans; Incidence; Male; Middle Aged; Proteomics; Risk Factors

Human Plasma Proteomic Profile of Clonal Hematopoiesis. - Yu, Zhi; Vromman, Amélie; Nguyen, Ngoc Quynh H; Schuermans, Art; Rentz, Thiago; Vellarikkal, Shamsudheen K; Uddin, Md Mesbah; Niroula, Abhishek; Griffin, Gabriel; Honigberg, Michael C; Lin, Amy E; Gibson, Christopher J; et al. (bioRxiv, 2024)
Plasma proteomic profiles associated with subclinical somatic mutations in blood cells may offer novel insights into downstream clinical consequences. Here, we explore such patterns in clonal hematopoiesis of indeterminate potential (CHIP), which is linked to several cancer and non-cancer outcomes, including coronary artery disease (CAD). Among 61,833 ancestrally diverse participants (3,881 with CHIP) from NHLBI TOPMed and UK Biobank with blood-based DNA sequencing and proteomic measurements (1,148 proteins by SomaScan in TOPMed and 2,917 proteins by Olink in UK Biobank), we identified 32 and 345 unique proteins from TOPMed and UK Biobank, respectively, associated with the most prevalent driver genes (, , and ). These associations showed substantial heterogeneity by driver genes, sex, and race, and were enriched for immune response and inflammation pathways. Mendelian randomization in humans, coupled with ELISA in hematopoietic -/- vs wild-type mice validation, disentangled causal proteomic perturbations from CHIP. Lastly, we identified plasma proteins shared between CHIP and CAD.

Human whole-exome genotype data for Alzheimer's disease. - Leung, Yuk Yee; Naj, Adam C; Chou, Yi-Fan; Valladares, Otto; Schmidt, Michael; Hamilton-Nelson, Kara; Wheeler, Nicholas; Lin, Honghuang; Gangadharan, Prabhakaran; Qu, Liming; Clark, Kaylyn; Kuzma, Amanda B; et al. (Nat Commun, 2024)
The heterogeneity of the whole-exome sequencing (WES) data generation methods present a challenge to a joint analysis. Here we present a bioinformatics strategy for joint-calling 20,504 WES samples collected across nine studies and sequenced using ten capture kits in fourteen sequencing centers in the Alzheimer's Disease Sequencing Project. The joint-genotype called variant-called format (VCF) file contains only positions within the union of capture kits. The VCF was then processed specifically to account for the batch effects arising from the use of different capture kits from different studies. We identified 8.2 million autosomal variants. 96.82% of the variants are high-quality, and are located in 28,579 Ensembl transcripts. 41% of the variants are intronic and 1.8% of the variants are with CADD > 30, indicating they are of high predicted pathogenicity. Here we show our new strategy can generate high-quality data from processing these diversely generated WES samples. The improved ability to combine data sequenced in different batches benefits the whole genomics research community.
Keywords: Alzheimer Disease; Computational Biology; Data Accuracy; Exome; Genotype; Humans

Large-scale circulating proteome association study (CPAS) meta-analysis identifies circulating proteins and pathways predicting incident hip fractures. - Austin, Thomas R; Fink, Howard A; Jalal, Diana I; Törnqvist, Anna E; Bůzková, Petra; Barzilay, Joshua I; Lu, Tianyuan; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Hveem, Kristian; Jonasson, Christian; et al. (J Bone Miner Res, 2024)
Hip fractures are associated with significant disability, high cost, and mortality. However, the exact biological mechanisms underlying susceptibility to hip fractures remain incompletely understood. In an exploratory search of the underlying biology as reflected through the circulating proteome, we performed a comprehensive Circulating Proteome Association Study (CPAS) meta-analysis for incident hip fractures. Analyses included 6430 subjects from two prospective cohort studies (Cardiovascular Health Study and Trøndelag Health Study) with circulating proteomics data (aptamer-based 5 K SomaScan version 4.0 assay; 4979 aptamers). Associations between circulating protein levels and incident hip fractures were estimated for each cohort using age and sex-adjusted Cox regression models. Participants experienced 643 incident hip fractures. Compared with the individual studies, inverse-variance weighted meta-analyses yielded more statistically significant associations, identifying 23 aptamers associated with incident hip fractures (conservative Bonferroni correction 0.05/4979, P < 1.0 × 10-5). The aptamers most strongly associated with hip fracture risk corresponded to two proteins of the growth hormone/insulin growth factor system (GHR and IGFBP2), as well as GDF15 and EGFR. High levels of several inflammation-related proteins (CD14, CXCL12, MMP12, ITIH3) were also associated with increased hip fracture risk. Ingenuity pathway analysis identified reduced LXR/RXR activation and increased acute phase response signaling to be overrepresented among those proteins associated with increased hip fracture risk. These analyses identified several circulating proteins and pathways consistently associated with incident hip fractures. These findings underscore the usefulness of the meta-analytic approach for comprehensive CPAS in a similar manner as has previously been observed for large-scale human genetic studies. Future studies should investigate the underlying biology of these potential novel drug targets.

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Wang, Heming; Nagarajan, Pavithra; Winkler, Thomas; Bentley, Amy; Miller, Clint; Kraja, Aldi; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael; Morrison, John; Giri, Ayush; et al. (Res Sq, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to 23 genes. Investigating these genes' functional implications shed light on neurological, thyroidal, bone metabolism, and hematopoietic pathways that necessitate future investigation for blood pressure management that caters to sleep health lifestyle. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausible nature of distinct influences of both sleep duration extremes in cardiovascular health. Several of our loci are specific towards a particular population background or sex, emphasizing the importance of addressing heterogeneity entangled in gene-environment interactions, when considering precision medicine design approaches for blood pressure management.

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Nagarajan, Pavithra; Winkler, Thomas W; Bentley, Amy R; Miller, Clint L; Kraja, Aldi T; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael R; Morrison, John L; Giri, Ayush; O'Connell, Jeffrey R; et al. (medRxiv, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to genes involved in neurological, thyroidal, bone metabolism, and hematopoietic pathways. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausibility of distinct influences of both sleep duration extremes in cardiovascular health. With several of our loci reflecting specificity towards population background or sex, our discovery sheds light on the importance of embracing granularity when addressing heterogeneity entangled in gene-environment interactions, and in therapeutic design approaches for blood pressure management.

Methylation patterns associated with C-reactive protein in racially and ethnically diverse populations. - Lundin, Jessica I; Peters, Ulrike; Hu, Yao; Ammous, Farah; Avery, Christy L; Benjamin, Emelia J; Bis, Joshua C; Brody, Jennifer A; Carlson, Chris; Cushman, Mary; Gignoux, Chris; Guo, Xiuqing; et al. (Epigenetics, 2024)
Systemic low-grade inflammation is a feature of chronic disease. C-reactive protein (CRP) is a common biomarker of inflammation and used as an indicator of disease risk; however, the role of inflammation in disease is not completely understood. Methylation is an epigenetic modification in the DNA which plays a pivotal role in gene expression. In this study we evaluated differential DNA methylation patterns associated with blood CRP level to elucidate biological pathways and genetic regulatory mechanisms to improve the understanding of chronic inflammation. The racially and ethnically diverse participants in this study were included as 50% White, 41% Black or African American, 7% Hispanic or Latino/a, and 2% Native Hawaiian, Asian American, American Indian, or Alaska Native (total  = 13,433) individuals. We replicated 113 CpG sites from 87 unique loci, of which five were novel (, , and cg03282312), across a discovery set of 1,150 CpG sites associated with CRP level ( < 1.2E-7). The downstream pathways affected by DNA methylation included the identification of and CpG-gene transcript pairs which contributed to the innate immune response gene enrichment pathway along with , , and . Gene enrichment analysis also identified the nuclear factor-kappaB transcription pathway. Using two-sample Mendelian randomization (MR) we inferred methylation at three CpG sites as causal for CRP levels using both White and Black or African American MR instrument variables. Overall, we identified novel CpG sites and gene transcripts that could be valuable in understanding the specific cellular processes and pathogenic mechanisms involved in inflammation.
Keywords: C-Reactive Protein; CpG Islands; DNA; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Inflammation; Intracellular Signaling Peptides and Proteins

{Multi-ancestry genome-wide association study reveals novel genetic signals for lung function decline - Patchen, B. K.; Zhang, J.; Gaddis, N.; Bartz, T. M.; Chen, J.; Debban, C.; Leonard, H.; Nguyen, N. Q.; Seo, J.; Tern, C.; Allen, R.; DeMeo, D. L.; et al. (medRxiv, 2024)
Accelerated decline in lung function contributes to the development of chronic respiratory disease. Despite evidence for a genetic component, few genetic associations with lung function decline have been identified.\ To evaluate genome-wide associations and putative downstream functionality of genetic variants with lung function decline in diverse general population cohorts.\ /FVC) in participants across six cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. Genotypes were imputed to TOPMed (CHARGE cohorts) or Haplotype Reference Consortium (HRC) (UK Biobank) reference panels, and GWAS analyses used generalized estimating equation models with robust standard error. Models were stratified by cohort, ancestry, and sex, and adjusted for important lung function confounders and genotype principal components. Results were combined in cross-ancestry and ancestry-specific meta-analyses. Selected top variants were tested for replication in two independent COPD-enriched cohorts.\ ) with consistent associations across ancestries or decline phenotypes. Annotation class analysis revealed significant enrichment of several regulatory processes for corticosteroid biosynthesis and metabolism. Drug repurposing analysis identified 43 approved compounds targeting eight of the implicated 38 genes.\ Our multi-ancestry GWAS meta-analyses identified numerous genetic loci associated with lung function decline. These findings contribute knowledge to the genetic architecture of lung function decline, provide evidence for a role of endogenous corticosteroids in the etiology of lung function decline, and identify drug targets that merit further study for potential repurposing to slow lung function decline and treat lung disease.

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

NIAGADS: A Comprehensive National Data Repository for Alzheimer's Disease and Related Dementia Genetics and Genomics Research - Kuzma, A.; Valladares, O.; Greenfest-Allen, E.; Nicaretta, H.; Kirsch, M.; Ren, Y.; Katanic, Z.; White, H.; Wilk, A.; Bass, L.; Brettschneider, J.; Carter, L.; et al. (medRxiv, 2024)
NIAGADS is the National Institute on Aging (NIA) designated national data repository for human genetics research on Alzheimer's Disease and related dementia (ADRD). NIAGADS maintains a high-quality data collection for ADRD genetic/genomic research and supports genetics data production and analysis. NIAGADS hosts whole genome and exome sequence data from the Alzheimer's Disease Sequencing Project (ADSP) and other genotype/phenotype data, encompassing 209,000 samples. NIAGADS shares these data with hundreds of research groups around the world via the Data Sharing Service, a FISMA moderate compliant cloud-based platform that fully supports the NIH Genome Data Sharing Policy. NIAGADS Open Access consists of multiple knowledge bases with genome-wide association summary statistics and rich annotations on the biological significance of genetic variants and genes across the human genome. NIAGADS stands as a keystone in promoting collaborations to advance the understanding and treatment of Alzheimer's disease.

A plasma protein-based risk score to predict hip fractures. - Austin, Thomas R; Nethander, Maria; Fink, Howard A; Törnqvist, Anna E; Jalal, Diana I; Bůzková, Petra; Barzilay, Joshua I; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Lu, Tianyuan; Hveem, Kristian; et al. (Nat Aging, 2024)
As there are effective treatments to reduce hip fractures, identification of patients at high risk of hip fracture is important to inform efficient intervention strategies. To obtain a new tool for hip fracture prediction, we developed a protein-based risk score in the Cardiovascular Health Study using an aptamer-based proteomic platform. The proteomic risk score predicted incident hip fractures and improved hip fracture discrimination in two Trøndelag Health Study validation cohorts using the same aptamer-based platform. When transferred to an antibody-based proteomic platform in a UK Biobank validation cohort, the proteomic risk score was strongly associated with hip fractures (hazard ratio per s.d. increase, 1.64; 95% confidence interval 1.53-1.77). The proteomic risk score, but not available polygenic risk scores for fractures or bone mineral density, improved the C-index beyond the fracture risk assessment tool (FRAX), which integrates information from clinical risk factors (C-index, FRAX 0.735 versus FRAX + proteomic risk score 0.776). The developed proteomic risk score constitutes a new tool for stratifying patients according to hip fracture risk; however, its improvement in hip fracture discrimination is modest and its clinical utility beyond FRAX with information on femoral neck bone mineral density remains to be determined.

Plasma proteome-wide analysis of cerebral small vessel disease identifies novel biomarkers and disease pathways. - Gomez, Gabriela T; Shi, Liu; Fohner, Alison E; Chen, Jingsha; Yang, Yunju; Fornage, Myriam; Duggan, Michael R; Peng, Zhongsheng; Daya, Gulzar N; Tin, Adrienne; Schlosser, Pascal; Longstreth, W T; et al. (medRxiv, 2024)
Cerebral small vessel disease (SVD), as defined by neuroimaging characteristics such as white matter hyperintensities (WMHs), cerebral microhemorrhages (CMHs), and lacunar infarcts, is highly prevalent and has been associated with dementia risk and other clinical sequelae. Although conditions such as hypertension are known to contribute to SVD, little is known about the diverse set of subclinical biological processes and molecular mediators that may also influence the development and progression of SVD. To better understand the mechanisms underlying SVD and to identify novel SVD biomarkers, we used a large-scale proteomic platform to relate 4,877 plasma proteins to MRI-defined SVD characteristics within 1,508 participants of the Atherosclerosis Risk in Communities (ARIC) Study cohort. Our proteome-wide analysis of older adults (mean age: 76) identified 13 WMH-associated plasma proteins involved in synaptic function, endothelial integrity, and angiogenesis, two of which remained associated with late-life WMH volume when measured nearly 20 years earlier, during midlife. We replicated the relationship between 9 candidate proteins and WMH volume in one or more external cohorts; we found that 11 of the 13 proteins were associated with risk for future dementia; and we leveraged publicly available proteomic data from brain tissue to demonstrate that a subset of WMH-associated proteins was differentially expressed in the context of cerebral atherosclerosis, pathologically-defined Alzheimer's disease, and cognitive decline. Bidirectional two-sample Mendelian randomization analyses examined the causal relationships between candidate proteins and WMH volume, while pathway and network analyses identified discrete biological processes (lipid/cholesterol metabolism, NF-kB signaling, hemostasis) associated with distinct forms of SVD. Finally, we synthesized these findings to identify two plasma proteins, oligodendrocyte myelin glycoprotein (OMG) and neuronal pentraxin receptor (NPTXR), as top candidate biomarkers for elevated WMH volume and its clinical manifestations.

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

A polygenic risk score of atrial fibrillation improves prediction of lifetime risk for heart failure. - Alkis, Taryn; Luo, Xi; Wall, Katherine; Brody, Jennifer; Bartz, Traci; Chang, Patricia P; Norby, Faye L; Hoogeveen, Ron C; Morrison, Alanna C; Ballantyne, Christie M; Coresh, Josef; Boerwinkle, Eric; et al. (ESC Heart Fail, 2024)
AIMS: Heart failure (HF) has shared genetic architecture with its risk factors: atrial fibrillation (AF), body mass index (BMI), coronary heart disease (CHD), systolic blood pressure (SBP), and type 2 diabetes (T2D). We aim to assess the association and risk prediction performance of risk-factor polygenic risk scores (PRSs) for incident HF and its subtypes in bi-racial populations. METHODS AND RESULTS: Five PRSs were constructed for AF, BMI, CHD, SBP, and T2D in White participants of the Atherosclerosis Risk in Communities (ARIC) study. The associations between PRSs and incident HF and its subtypes were assessed using Cox models, and the risk prediction performance of PRSs was assessed using C statistics. Replication was performed in the ARIC study Black and Cardiovascular Health Study (CHS) White participants. In 8624 ARIC study Whites, 1922 (31% cumulative incidence) HF cases developed over 30 years of follow-up. PRSs of AF, BMI, and CHD were associated with incident HF (P < 0.001), where PRS showed the strongest association [hazard ratio (HR): 1.47, 95% confidence interval (CI): 1.41-1.53]. Only the addition of PRS to the ARIC study HF risk equation improved C statistics for 10 year risk prediction from 0.812 to 0.829 (∆C: 0.017, 95% CI: 0.009-0.026). The PRS was associated with both incident HF with reduced ejection fraction (HR: 1.43, 95% CI: 1.27-1.60) and incident HF with preserved ejection fraction (HR: 1.46, 95% CI: 1.33-1.62). The associations between PRS and incident HF and its subtypes, as well as the improved risk prediction, were replicated in the ARIC study Blacks and the CHS Whites (P < 0.050). Protein analyses revealed that N-terminal pro-brain natriuretic peptide and other 98 proteins were associated with PRS . CONCLUSIONS: The PRS was associated with incident HF and its subtypes and had significant incremental value over an established HF risk prediction equation.

Proteogenomics in cerebrospinal fluid and plasma reveals new biological fingerprint of cerebral small vessel disease. - Debette, Stephanie; Caro, Ilana; Western, Daniel; Namba, Shinichi; Sun, Na; Kawaguchi, Shuji; He, Yunye; Fujita, Masashi; Roshchupkin, Gennady; D'Aoust, Tim; Duperron, Marie-Gabrielle; Sargurupremraj, Murali; et al. (Res Sq, 2024)
Cerebral small vessel disease (cSVD) is a leading cause of stroke and dementia with no specific mechanism-based treatment. We used Mendelian randomization to combine a unique cerebrospinal fluid (CSF) and plasma pQTL resource with the latest European-ancestry GWAS of MRI-markers of cSVD (white matter hyperintensities, perivascular spaces). We describe a new biological fingerprint of 49 protein-cSVD associations, predominantly in the CSF. We implemented a multipronged follow-up, across fluids, platforms, and ancestries (Europeans and East-Asian), including testing associations of direct plasma protein measurements with MRI-cSVD. We highlight 16 proteins robustly associated in both CSF and plasma, with 24/4 proteins identified in CSF/plasma only. cSVD-proteins were enriched in extracellular matrix and immune response pathways, and in genes enriched in microglia and specific microglial states (integration with single-nucleus RNA sequencing). Immune-related proteins were associated with MRI-cSVD already at age twenty. Half of cSVD-proteins were associated with stroke, dementia, or both, and seven cSVD-proteins are targets for known drugs (used for other indications in directions compatible with beneficial therapeutic effects. This first cSVD proteogenomic signature opens new avenues for biomarker and therapeutic developments.

Rare variant contribution to the heritability of coronary artery disease. - Rocheleau, Ghislain; Clarke, Shoa L; Auguste, Gaëlle; Hasbani, Natalie R; Morrison, Alanna C; Heath, Adam S; Bielak, Lawrence F; Iyer, Kruthika R; Young, Erica P; Stitziel, Nathan O; Jun, Goo; Laurie, Cecelia; et al. (Nat Commun, 2024)
Whole genome sequences (WGS) enable discovery of rare variants which may contribute to missing heritability of coronary artery disease (CAD). To measure their contribution, we apply the GREML-LDMS-I approach to WGS of 4949 cases and 17,494 controls of European ancestry from the NHLBI TOPMed program. We estimate CAD heritability at 34.3% assuming a prevalence of 8.2%. Ultra-rare (minor allele frequency ≤ 0.1%) variants with low linkage disequilibrium (LD) score contribute ~50% of the heritability. We also investigate CAD heritability enrichment using a diverse set of functional annotations: i) constraint; ii) predicted protein-altering impact; iii) cis-regulatory elements from a cell-specific chromatin atlas of the human coronary; and iv) annotation principal components representing a wide range of functional processes. We observe marked enrichment of CAD heritability for most functional annotations. These results reveal the predominant role of ultra-rare variants in low LD on the heritability of CAD. Moreover, they highlight several functional processes including cell type-specific regulatory mechanisms as key drivers of CAD genetic risk.
Keywords: Case-Control Studies; Coronary Artery Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

{The Role of X Chromosome in Alzheimer's Disease Genetics - Belloy, M. E.; Guen, Y. L.; Stewart, I.; Herz, J.; Sherva, R.; Zhang, R.; Merritt, V.; Panizzon, M. S.; Hauger, R. L.; Gaziano, J. M.; Logue, M.; Napolioni, V.; et al. (medRxiv, 2024)
The X chromosome has remained enigmatic in Alzheimer's disease (AD), yet it makes up 5% of the genome and carries a high proportion of genes expressed in the brain, making it particularly appealing as a potential source of unexplored genetic variation in AD.\ Perform the first large-scale X chromosome-wide association study (XWAS) of AD. Primary analyses are non-stratified, while secondary analyses evaluate sex-stratified effects.\ Meta-analysis of genetic association studies in case-control, family-based, population-based, and longitudinal AD-related cohorts from the US Alzheimer's Disease Genetics Consortium (ADGC) and Alzheimer's Disease Sequencing Project (ADSP), the UK Biobank (UKB), the Finnish health registry (FinnGen), and the US Million Veterans Program (MVP). Risk for AD evaluated through case-control logistic regression analyses. Data were analyzed between January 2023 and March 2024.\ Genetic data available from high-density single-nucleotide polymorphism (SNP) microarrays and whole-genome sequencing (WGS). Summary statistics for multi-tissue expression and protein quantitative trait loci (QTL) available from published studies, enabling follow-up genetic colocalization analyses.\ 1,629,863 eligible participants were selected from referred and volunteer samples, of which 477,596 were excluded for analysis exclusion criteria. Number of participants who declined to participate in original studies was not available.\ 5e-8) significance.\ genes.\ regulates pH homeostasis in Golgi secretory compartments and is anticipated to have downstream effects on amyloid beta accumulation. Overall, this study significantly advances our knowledge of AD genetics and may provide novel biological drug targets.

Sociodemographic, lifestyle, and medical factors associated with calculated free testosterone concentrations in men: individual participant data meta-analyses. - Narinx, Nick; Marriott, Ross J; Murray, Kevin; Adams, Robert J; Ballantyne, Christie M; Bauer, Douglas C; Bhasin, Shalender; Biggs, Mary L; Cawthon, Peggy M; Couper, David J; Dobs, Adrian S; Flicker, Leon; et al. (Eur J Endocrinol, 2024)
OBJECTIVE: Sociodemographic, lifestyle, and medical variables influence total testosterone (T) and sex hormone-binding globulin (SHBG) concentrations. The relationship between these factors and "free" T remains unclear. We examined 21 sociodemographic, lifestyle, and medical predictors influencing calculated free T (cFT) in community-dwelling men across ages. DESIGN: This is a cross-sectional analysis in 20 631 participants in the Androgens in Men Study. METHODS: Individual participant data (IPD) were provided by 9 cohorts. Total T was determined using mass spectrometry, SHBG using immunoassays, and cFT using the Vermeulen formula. Associations were analyzed using 2-stage random effects IPD meta-analyses. RESULTS: Cohort median ages ranged from 40 to 76 years and median cFT concentrations from 174.3 to 422.8 pmol/L. In men aged 17-99 years, there was a linear inverse association of cFT with age (-57.2 pmol/L [95% confidence interval, -69.4, -44.9] per 1 SD increase in age). Calculated free T increased with increasing baseline body mass index (BMI) among men with BMI < 23.6 kg/m2, but decreased among men with BMI > 23.6 kg/m2 (-24.7 pmol/L [-29.1, -20.3] per 1 SD increase in the 25.4-29.6 kg/m2 BMI range). Calculated free T was lower in younger men, who were married or in a de facto relationship (-18.4 pmol/L [-27.6, -9.3]) and in men who formerly smoked (-5.7 pmol/L [-8.9, -2.6]), were in poor general health (-14.0 pmol/L [-20.1, -7.8]), and had diabetes (-19.6 pmol/L [-23.0, -16.3]), cardiovascular disease (-5.8 pmol/L [-8.3, -3.2]), or cancer (-19.2 pmol/L [-24.4, -14.1]). CONCLUSIONS: Calculated free T was most prominently associated with age and BMI. The linear, inverse association with age, nonlinear association with BMI, and presence of diabetes, cancer, and sociodemographic factors should be considered when interpreting cFT values.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Humans; Life Style; Male; Middle Aged; Sex Hormone-Binding Globulin; Sociodemographic Factors; Socioeconomic Factors; Testosterone; Young Adult

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People With Type 2 Diabetes. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (Diabetes Care, 2024)
OBJECTIVE: To identify genetic risk factors for incident cardiovascular disease (CVD) among people with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS: We conducted a multiancestry time-to-event genome-wide association study for incident CVD among people with T2D. We also tested 204 known coronary artery disease (CAD) variants for association with incident CVD. RESULTS: Among 49,230 participants with T2D, 8,956 had incident CVD events (event rate 18.2%). We identified three novel genetic loci for incident CVD: rs147138607 (near CACNA1E/ZNF648, hazard ratio [HR] 1.23, P = 3.6 × 10-9), rs11444867 (near HS3ST1, HR 1.89, P = 9.9 × 10-9), and rs335407 (near TFB1M/NOX3, HR 1.25, P = 1.5 × 10-8). Among 204 known CAD loci, 5 were associated with incident CVD in T2D (multiple comparison-adjusted P < 0.00024, 0.05/204). A standardized polygenic score of these 204 variants was associated with incident CVD with HR 1.14 (P = 1.0 × 10-16). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D.

Trajectory of Cognitive Function After Incident Heart Failure. - Shore, Supriya; Li, Hanyu; Zhang, Min; Whitney, Rachael; Gross, Alden L; Bhatt, Ankeet S; Nallamothu, Brahmajee K; Giordani, Bruno; Briceño, Emily M; Sussman, Jeremy B; Gutierrez, Jose; Yaffe, Kristine; et al. (medRxiv, 2024)
BACKGROUND: The size/magnitude of cognitive changes after incident heart failure (HF) are unclear. We assessed whether incident HF is associated with changes in cognitive function after accounting for pre-HF cognitive trajectories and known determinants of cognition. METHODS: This pooled cohort study included adults without HF, stroke, or dementia from six US population-based cohort studies from 1971-2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Linear mixed-effects models estimated changes in cognition at the time of HF (change in the intercept) and the rate of cognitive change over the years after HF (change in the slope), controlling for pre-HF cognitive trajectories and participant factors. Change in global cognition was the primary outcome. Change in executive function and memory were secondary outcomes. Cognitive outcomes were standardized to a -score metric (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. RESULTS: The study included 29,614 adults (mean [SD] age was 61.1 [10.5] years, 55% female, 70.3% White, 22.2% Black 7.5% Hispanic). During a median follow-up of 6.6 (Q1-Q3: 5-19.8) years, 1,407 (4.7%) adults developed incident HF. Incident HF was associated with an acute decrease in global cognition (-1.08 points; 95% CI -1.36, -0.80) and executive function (-0.65 points; 95% CI -0.96, -0.34) but not memory (-0.51 points; 95% CI -1.37, 0.35) at the time of the event. Greater acute decreases in global cognition after HF were seen in those with older age, female sex and White race. Individuals with incident HF, compared to HF-free individuals, demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21, -0.09) and executive function (-0.16 points per year; 95% CI -0.23, -0.09) but not memory ( -0.11 points per year; 95% CI -0.26, 0.04) compared with pre-HF slopes. CONCLUSIONS: In this pooled cohort study, incident HF was associated with an acute decrease in global cognition and executive function at the time of the event and faster declines in global cognition and executive function over the following years.

Trimethylamine -Oxide and Related Gut Microbe-Derived Metabolites and Incident Heart Failure Development in Community-Based Populations. - Tang, W H Wilson; Lemaitre, Rozenn N; Jensen, Paul N; Wang, Meng; Wang, Zeneng; Li, Xinmin S; Nemet, Ina; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Fretts, Amanda M; Sotoodehnia, Nona; et al. (Circ Heart Fail, 2024)
BACKGROUND: Growing evidence indicates that trimethylamine -oxide, a gut microbial metabolite of dietary choline and carnitine, promotes both cardiovascular disease and chronic kidney disease risk. It remains unclear how circulating concentrations of trimethylamine -oxide and its related dietary and gut microbe-derived metabolites (choline, betaine, carnitine, γ-butyrobetaine, and crotonobetaine) affect incident heart failure (HF). METHODS: We evaluated 11 768 participants from the Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis with serial measures of metabolites. Cox proportional hazard models were used to examine the associations between metabolites and incident HF, adjusted for cardiovascular disease risk factors. RESULTS: In all, 2102 cases of HF occurred over a median follow-up of 15.9 years. After adjusting for traditional risk factors, higher concentrations of trimethylamine -oxide (hazard ratio, 1.15 [95% CI, 1.09-1.20]; <0.001), choline (hazard ratio, 1.44 [95% CI, 1.26-1.64]; <0.001), and crotonobetaine (hazard ratio, 1.24 [95% CI, 1.16-1.32]; <0.001) were associated with increased risk for incident HF. After further adjustment for renal function (potential confounder or mediator), these associations did not reach Bonferroni-corrected statistical significance (=0.01, 0.049, and 0.006, respectively). Betaine and carnitine were nominally associated with a higher incidence of HF (<0.05). In exploratory analyses, results were similar for subtypes of HF based on left ventricular ejection fraction, and associations appeared generally stronger among Black and Hispanic/Latino versus White adults, although there were no interactions for any metabolites with race. CONCLUSIONS: In this pooled analysis of 2 well-phenotyped, diverse, community-based cohorts, circulating concentrations of gut microbe-derived metabolites such as trimethylamine -oxide, choline, and crotonobetaine were independently associated with a higher risk of developing HF. REGISTRATION: URL: https://www.clinicaltrials.gov/; Unique identifiers: NCT00005133 and NCT00005487.
Keywords: Aged; Aged, 80 and over; Betaine; Biomarkers; Carnitine; Choline; Female; Gastrointestinal Microbiome; Heart Failure; Humans; Incidence; Male; Methylamines; Middle Aged; Risk Factors; United States

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins

Genomic and phenotypic correlates of mosaic loss of chromosome Y in blood. - Jakubek, Yasminka A; Ma, Xiaolong; Stilp, Adrienne M; Yu, Fulong; Bacon, Jason; Wong, Justin W; Aguet, Francois; Ardlie, Kristin; Arnett, Donna K; Barnes, Kathleen; Bis, Joshua C; Blackwell, Tom; et al. (Am J Hum Genet, 2025)
Mosaic loss of Y (mLOY) is the most common somatic chromosomal alteration detected in human blood. The presence of mLOY is associated with altered blood cell counts and increased risk of Alzheimer disease, solid tumors, and other age-related diseases. We sought to gain a better understanding of genetic drivers and associated phenotypes of mLOY through analyses of whole-genome sequencing (WGS) of a large set of genetically diverse males from the Trans-Omics for Precision Medicine (TOPMed) program. We show that haplotype-based calling methods can be used with WGS data to successfully identify mLOY events. This approach enabled us to identify differences in mLOY frequencies across populations defined by genetic similarity, revealing a higher frequency of mLOY in the European (EUR) ancestry group compared to other ancestries. We identify multiple loci associated with mLOY susceptibility and show that subsets of human hematopoietic stem cells are enriched for the activity of mLOY susceptibility variants. Finally, we found that certain alleles on chromosome Y are more likely to be lost than others in detectable mLOY clones.
Keywords: Alleles; Chromosome Deletion; Chromosomes, Human, Y; Genomics; Haplotypes; Humans; Male; Mosaicism; Phenotype; Whole Genome Sequencing

The impact of common and rare genetic variants on bradyarrhythmia development. - Weng, Lu-Chen; Rämö, Joel T; Jurgens, Sean J; Khurshid, Shaan; Chaffin, Mark; Hall, Amelia Weber; Morrill, Valerie N; Wang, Xin; Nauffal, Victor; Sun, Yan V; Beer, Dominik; Lee, Simon; et al. (Nat Genet, 2025)
To broaden our understanding of bradyarrhythmias and conduction disease, we performed common variant genome-wide association analyses in up to 1.3 million individuals and rare variant burden testing in 460,000 individuals for sinus node dysfunction (SND), distal conduction disease (DCD) and pacemaker (PM) implantation. We identified 13, 31 and 21 common variant loci for SND, DCD and PM, respectively. Four well-known loci (SCN5A/SCN10A, CCDC141, TBX20 and CAMK2D) were shared for SND and DCD, while others were more specific for SND or DCD. SND and DCD showed a moderate genetic correlation (r = 0.63). Cardiomyocyte-expressed genes were enriched for contributions to DCD heritability. Rare-variant analyses implicated LMNA for all bradyarrhythmia phenotypes, SMAD6 and SCN5A for DCD and TTN, MYBPC3 and SCN5A for PM. These results show that variation in multiple genetic pathways (for example, ion channel function, cardiac developmental programs, sarcomeric structure and cellular homeostasis) appear critical to the development of bradyarrhythmias.
Keywords: Bradycardia; Cardiac Conduction System Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Pacemaker, Artificial; Phenotype; Polymorphism, Single Nucleotide; Sick Sinus Syndrome

LD-informed deep learning for Alzheimer's gene loci detection using WGS data - Jo, T.; Bice, P.; Nho, K.; Saykin, A. J. (Alzheimers Dement (N Y), 2025)
The exponential growth of genomic datasets necessitates advanced analytical tools to effectively identify genetic loci from large-scale high throughput sequencing data. This study presents Deep-Block, a multi-stage deep learning framework that incorporates biological knowledge into its AI architecture to identify genetic regions as significantly associated with Alzheimer's disease (AD). The framework employs a three-stage approach: (1) genome segmentation based on linkage disequilibrium (LD) patterns, (2) selection of relevant LD blocks using sparse attention mechanisms, and (3) application of TabNet and Random Forest algorithms to quantify single nucleotide polymorphism (SNP) feature importance, thereby identifying genetic factors contributing to AD risk.\ The Deep-Block was applied to a large-scale whole genome sequencing (WGS) dataset from the Alzheimer's Disease Sequencing Project (ADSP), comprising 7416 non-Hispanic white (NHW) participants (3150 cognitively normal older adults (CN), 4266 AD).\ rs429358 and rs769449. Expression Quantitative Trait Loci (eQTL) analysis across 13 brain regions provided functional evidence for the identified variants. The results were cross-validated against established AD-associated loci from the European Alzheimer's and Dementia Biobank (EADB) and the GWAS catalog.\ The Deep-Block framework effectively processes large-scale high throughput sequencing data while preserving SNP interactions during dimensionality reduction, minimizing bias and information loss. The framework's findings are supported by tissue-specific eQTL evidence across brain regions, indicating the functional relevance of the identified variants. Additionally, the Deep-Block approach has identified both known and novel genetic variants, enhancing our understanding of the genetic architecture and demonstrating its potential for application in large-scale sequencing studies.\ ) were significant.The AI framework uses biological knowledge to enhance detection of Alzheimer's loci.